Partial ring hydrogenation of naphthols over supported metal catalysts in supercritical carbon dioxide solvent - Mine, Eiichi; Haryu, E.; Arai, K.; Sato, T.; Sato, O.; Sasaki, A.; Rode, C. V.; Shirai, M. (Chemistry Letters, 2005)
Selective ring hydrogenation of naphthols to tetrahydronaphthols and tetralones proceeded at 323 K over a charcoal supported rhodium catalyst in supercritical carbon dioxide.

Pd-catalyzed oxidative kinetic resolution of 2-azido-1-arylethanols - Sayyed, I. A.; Kumar, N. S. C. R.; Sudalai, A. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2005)
(-)-Sparteine/Pd (II) complex in combination with oxygen as a stoichiometric oxidant, catalyses the oxidative kinetic resolution of P-azido alcohols to afford the corresponding chiral 2-azido-1-arylethanols.
Keywords: (-)-sparteine-Pd (II) complex; beta-azidoalcohol; chiral 2-azido-1-arylethanol; Kinetic resolution

Performance assessment of HC-290 as a drop-in substitute to HCFC-22 in a window air conditioner - Devotta, S; Padalkar, AS; Sane, NK (International Journal of Refrigeration - Revue Internationale Du Froid, 2005)
As per the Montreal Protocol, CFCs and HCFCs are being phased out. HCFC-22 is used in window air conditioners. This paper presents the experimental performance study of a window air conditioner with propane (HC-290), a natural refrigerant, as a drop-in substitute to HCFC-22. Experimental results showed that HC-290 had 6.6% lower cooling capacity for the lower operating conditions and 9.7% lower for the higher operating conditions with respect to HCFC-22. The coefficient of performance for HC290 was 7.9% higher for the lower operating conditions and 2.8% higher for the higher operating conditions. The energy consumption of the unit with HC-290 was lower in the range 12.4-13.5% than HCFC-22. The discharge pressures for HC-290 were lower in the range 13.7-18.2% than HCFC-22. For HC-290, the pressure drop was lower than HCFC-22 in both heat exchangers. This paper also presents simulation results for the heat exchangers of an HCFC-22 window air conditioner with HC-290 as a drop-in substitute. The simulation has been carried out using EVAP-COND, a heat exchanger model developed by NIST [National Institute of Standards and Technology. EVAP-COND: simulation models for finned-tube heat exchangers, Maryland, USA (2003). http://www2.bfrl.nist.gov/software/evap-cond/ [18]]. The simulated evaporator capacities are within +/- 4% of the experimentally measured cooling capacities for both refrigerants. Simulation results for HC-290 and HCFC-22 are compared. The exit temperatures of HC-290 are lower by 0.3-1.2 degrees C in the condenser and are higher by 2.1-2.4 degrees C in the evaporator than HCFC-22. Evaporating pressures of HC-290 are lower by 2.1-3.3% as compared to HCFC-22. The pressure drops of HC-290 are lower in both the evaporator and the condenser as compared to HCFC-22. The outlet temperatures of air for HCFC-22 and HC-290 in both heat exchangers are nearly the same. (c) 2005 Elsevier Ltd and IIR. All rights reserved.
Keywords: air conditioner; COP; Evaporator; experiment; performance; propane; R-22; simulation; window

Performance assessment of HCFC-22 window air conditioner retrofitted with R-407C - Devotta, S; Padalkar, AS; Sane, NK (Applied Thermal Engineering, 2005)
This paper presents the experimental performance analysis of a 1.5 TR window air-conditioner, retrofitted with R-407C, as a substitute to HCFC-22. Experimental results showed that R-407C, for the operating conditions covered in this study, had lower cooling capacity in the range 2.1-7.9% with respect to HCFC-22. The coefficient of performance for R-407C was lower in the range 7.9-13.5%. The power consumption of the unit with R-407C was higher in the range 6-7% than HCFC-22. The discharge pressures for R-407C were higher in the range 11-13% than HCFC-22. This paper also presents simulation results of heat exchangers of an HCFC-22 window air conditioner retrofitted with R-407C. The simulation has been carried out using EVAP-COND, a heat exchanger model developed by National Institute of Standards and Technology, U.S.A. The simulated evaporator capacities are within +/- 3% of the experimentally measured cooling capacities for both refrigerants. Simulation results for R-407C and HCFC-22 are compared. The exit temperatures of R-407C are lower by 1.9 degrees C to 5.2 degrees C in the condenser and are higher by 3.2 degrees C to 3.8 degrees C in the evaporator than HCFC-22. Evaporating pressures of R-407C are higher by 4.5-5.3% as compared to HCFC-22. The pressure drops of R-407C are lower in both the evaporator and the condenser as compared to HCFC-22. The outlet temperatures of air for HCFC-22 and R-407C in both heat exchangers are nearly the same. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: cooling capacity; COP; measurement; performance; power consumption; R-407C

Phase transfer of oleic acid capped NicoreAgshell nanoparticles assisted by the flexibility of oleic acid on the surface of silver - Bala, Tanushree; Swami, A.; Bhagavatula L. V. Prasad; Sastry, M. (Journal of Colloid and Interface Science, 2005)
The phase transfer protocols in vogue for the oleic acid capped silver nanoparticles, viz., salt-induced precipitation and redispersion or phosphoric acid-induced method, are examined and compared thoroughly. A comprehensive evaluation with respect to the mechanistic aspects involved is made and the merits and demerits of the different procedures are delineated. It is found that the salt-induced precipitation and redispersion is more versatile in that the precipitate can actually be redispersed in both aqueous and organic media. However, in terms of mechanism both the routes seem to be very similar wherein the orientational change of oleic acid on the silver surface in the two different environments-organic and aqueous-plays a crucial role in the adaptability of the system to the different environments. Subsequently, this change of orientation of oleic acid on silver surface in aqueous and organic media has been utilized to phase transfer Ni-based nanoparticulate systems. The nascent oleic acid-capped Ni nanoparticles, which were synthesized by a foam-based protocol, were dispersible in water but not in nonpolar organic media such as cyclohexane or toluene. Then, just by coating a thin shell of silver on them we could achieve complete phase transfer of the NicoreAgshell from aqueous to organic media following similar procedures used for oleic acid-capped silver nanoparticles. Here, the phase transfer seems to be facilitated by the orientational flexibility of oleic acid on the silver surface as opposed to other metal surfaces as evidenced from the infrared and thermogravimetric analyses of oleic acid-capped Ni and NicoreAgshell nanoparticles. This orientation-assisted phase transfer method could be generalized and can be adapted to other systems where, if the nascent nanoparticles cannot be phase transferred as is, they can be coated by a silver shell and oleic acid making them suitable for dispersion in both aqueous and organic media. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: (1) HNMR; FTIR; Phase transfer; transmetalation core-shell nanoparticles; UV-Vis

Phase transitions in octanethiol-capped Ag nanocluster microfilm assemblies - Ellis, A.; D'Arcy-Galla, J.; Vijayamohanan, K.; Goswami, R.; Ganesan, P. G.; Ryu, C.; Ramanath, G. (Thermochimica Acta, 2005)
We describe phase transitions in microfilm assemblies of octanethiol (OT)-capped 2-4 nm-diameter Ag nanoclusters prepared from solutions with OT/Ag+ ratios of similar to50. Using DSC we observe two melting/crystallization-type reversible phase transitions: one at similar to61 degreesC due to interdigiated unattached octanethiol, and the other at similar to125 degreesC due to the phase comprised of the assembly of OT-capped nanoclusters. Increased thermal fluctuations weaken the inter-chain hydrophobic interactions between interdigitated OT molecules, leading to both phase transitions. The thiolate bond of OT-molecules bound to Ag nanoclusters are more rigid, thereby requiring a higher temperature to increase the flexibility of the alkyl chain of OT, and to melt the nanocluster assembly. The mobility of the nanoclusters in the melt is limited, and morphological features of the original assemblies are retained during recrystallization. No observable mass loss is detected up to similar to180 degreesC, above which OT molecules desorb from the Ag nanoclusters. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: differential thermal analysis; infrared spectroscopy; phase transitions; silver nanoclusters

PHB synthase from Streptomyces aureofaciens NRRL 2209 - Ramachander, TVN; Rawal, SK (FEMS Microbiology Letters, 2005)
An similar to4.9 kb Sau3A I genomic DNA fragment from the Streptomyces aureofaciens NRRL 2209 aiding in the biosynthesis of PHB in recombinant Escherichia coli has been sequenced and analysed for phaC gene. The putative phaC(sa) gene of 2 kb is 79.1% GC rich and encodes a 63.5 kDa protein. It expressed under its own promoter and significant PHA synthase activity was detected in the recombinant E coli. This is the first putative PHA synthase gene reported from a Streptomyces sp. with serine as the active nucleophile in the conserved lipase box. The phaC(sa) was found in close proximity to a regulatory gene, which apparently regulated the phaC expression. (C) 2004 Federation of European Microbiological Societies. Published by Elsevier B.V. All rights reserved.
Keywords: PHA synthase; PHB; Streptomyces

Photodegradation of ethylene/propylene/polar monomers co- and terpolymers. I - Prepared by group 4 catalyst systems - Fernandes, Susete N.; Correia, Sandra; Prasad, A. V.; Reddy, K. R.; Rana, S.; Lonkar, Sunil P.; Marques, Maria M.; Singh, R. P. (Journal of Macromolecular Science-Pure and Applied Chemistry, 2005)
The photooxidative degradation behavior of polyethylene, its copolymers (propylene/polar monomers) and terpolymers, synthesized by a group 4 catalyst system, has been studied by Fourier transform infrared spectroscopy and confirmed with scanning elecrton microscopy for morphological changes. The kinetics of photodegradation has also been studied. Surface damage caused by polychromatic (>= 290 nm) at 55 degrees C in air is presented in different micrographs. The rate of photodegradation is very fast in terpolymers containing polar monomers as compared with copolymers and polyethylene. Morphological study of these photodegraded samples showed a very good relation with photodegradation results.
Keywords: functional polyolefins; Photodegradation; UV irradiation

Photoluminescent core-shell particles of organic dye in silica - Ethiraj, Anita S.; Hebalkar, Neha; Kharrazi, Sharmin; Urban, J.; Sainkar, S. R.; Kulkarni, S. K. (Journal of Luminescence, 2005)
Using a single silica precursor, Rhodamine 6G organic dye molecules have been entrapped in silica particles resulting into core-shell particles of similar to 500 nm diameter. Energy dispersive X-ray analysis, X-ray photoelectron spectroscopy and transmission electron microscopy analysis reveals that dye molecules are trapped inside the silica particles. Photoluminescence investigations show that highly luminescent and photostable core-shell particles are formed. Such core-shell particles can be easily suspended in water and would be useful for a variety of applications. However, there is a blue shift in the photolumineseence wavelength in case of core-shell particles compared to bare dye powder sample. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: core-shell; Luminescence; Nanoparticles; photoemission; RH06G dye; tetraethylorthosilicate (TEOS)

PNA C-C+ i-motif: superior stability of PNA TC8 tetraplexes compared to DNA TC8 tetraplexes at low pH - Sharma, NK; Ganesh, Krishna N. (Chemical Communications, 2005)
Study of self-assembly of PNA TC8 monitored by UV thermal transition at 295 nm indicates formation of a C-C+ tetraplex (i-motif) in acidic pH, with higher stability than the analogous dTC(8).

Podborer (Helicoverpa armigera Hubn.) does not show specific adaptations in gut proteinases to dietary Cicer arietinum Kunitz proteinase inhibitor - Srinivasan, A.; Chougule, Nanasaheb P.; Giri, Ashok P.; Gatehouse, J. A.; Gupta, Vidya S. (Journal of Insect Physiology, 2005)
We investigated the response of Helicoverpa armigera larvae towards ingestion of Cicer arietinum Kunitz proteinase inhibitor (CaKPI), which caused antagonistic effects on developing H. armigera larvae. CaKPI-degrading proteinases were not detectable in either control or sensitized larvae. There were negligible increases in total proteinase activity, as well as in trypsin-like and chymotrypsin-like activities of H. armigera gut proteinases (HGPs). Decrease in sensitivity of HGPs to inhibition by CaKPI was not observed when the inhibitor was fed Suggesting that the insect had not shown a specific adaptive response to dietary CaKPI. Semi-quantitative reverse transcriptase polymerase chain reaction (Q RT-PCR) analysis showed a general up-regulation of proteases in larvae that ingested CaKPI and a specific regulation of individual transcripts was not observed. CaKPI had maximum inhibitory activity against HGP derived from fourth instar larvae. CaKPI was equally potent in inhibition of HGPs derived from larvae fed on different host plants, as well as various proteinase inhibitors (Pis) to which larval adaptation was previously reported. The lack of larval response to CaKPI was attributable to the atypical active site sequence and inhibitory activity of CaKPI and/or to the pre-adaptation of H. armigera larvae due to the constant exposure to basal levels of CaKPI in chickpea seeds or a chickpea seed-based diet. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Cicer arietinum; Helicoverpa armigera; insect response; proteinase; Proteinase inhibitor

Poly(acrylonitrile) ultrafiltration membranes. I. polymer-salt-solvent interactions - Phadke, M. A.; Musale, D. A.; Kulkarni, Sudhir S.; Karode, Sandeep K. (Journal of Polymer Science Part B: Polymer Physics, 2005)
Fourier transform infrared spectroscopy was used to study the interactions among LiCl, ZnCl2, and AlCl3 with NN-dimethylformamide (DMF) and poly (acrylonitrile) (PAN). It was observed that all three salts complex with DMF as well as PAN. The strength of the cation interaction with the > C=O oxygen of DMF was found to be higher than that with the -CN group of PAN. The > C=O stretching frequency of DMF with ZnCl2 was red shifted, indicating stronger complex formation compared with other two cations. With the addition of salt, the salt-DMF pseudo solvent was found to become a 0 solvent for PAN compared with neat DMF. This change in PAN solvation power was primarily the result of DMF-salt complexation. As a result of the complexation, Mark-Houwink constant a, was found to reduce from 0.75 (for pure DMF) to similar to 0.6 for DMF-salt solvents, indicating decreased PAN chain expansion. Comparison of intrinsic viscosity [n] values indicated that addition of salts to PAN-DMF solutions resulted in: (i) decrease in the DMF solvation. power, which causes less expanded polymer coils, and (ii) increased interpolymer chain entanglements via salt-promoted chain association. (c) 2005 Wiley Periodicals, Inc.
Keywords: activation energy viscosity; Additives; FT-IR; Poly(acrylonitrile); solution properties

Poly(acrylonitrile) ultrafiltration membranes. II. membrane morphology and permeation characteristics - Phadke, M. A.; Kulkarni, Sudhir S.; Karode, Sandeep K.; Musale, D. A. (Journal of Polymer Science Part B: Polymer Physics, 2005)
The rheology and phase-boundary characteristics of various solutions comprising three polyacrylonitrile (PAN) grades dissolved in solutions of N,N-dimethylformamide + salt (LiCl, ZnCl2, or AICl(3)) additives were correlated with the resulting membrane morphology as determined by microscopy and permeability measurements. The phase separation characteristics of the dope solution were not markedly affected by the PAN molecular weight (MW); however, they were affected by the salt additive. For higher MW grades, the effect of salt addition can also be masked by the increased self-association tendency of the polymer chains. PAN-B and -C membranes were clearly less asymmetric in structure than the lower MW PAN-Abased membranes. This is attributed to the higher viscosity/lower diffusivity of the PAN-13 and -C solutions, which results in slower solvent-nonsolvent exchange during the phase inversion process. Two factors reduce the incidence of surface defects (increased bubble points): (a) higher solution viscosity dampens surface perturbations during phase inversion, and (b) phase inversion pathways resulting in more homogenous morphology lead to membranes with higher bubble points. (c) 2005 Wiley Periodicals, Inc.
Keywords: bubble point; membranes; Morphology; phase inversion; salts; viscosity

Polycondensation in liquid crystalline phases of nonionic surfactants. Kinetics and morphology - Kumaraswamy, Guruswamy; Wadekar, M. N.; Agrawal, Vikrant V.; Pasricha, R. (Polymer, 2005)
We have investigated acid-catalyzed polycondensation of alkoxysilane monomers in liquid crystalline phases of nonionic CnEm surfactants. The liquid crystalline phase is retained when the monomers polymerize. The high molecular weight molecules formed phase separate from the mesophase and are subsequently organized by it to form micron-sized particles. A variety of particle morphologies are formed by organization of the polymer particles in the mesophase. For condensation of dimethyldimethoxysilane (DMS, with trimethoxysilane, TMS as crosslinker) in hexagonal and lamellar phases, specific reaction conditions, viz. slow condensation kinetics and low crosslink density, give rod-like particles in hexagonal phases and sheet-like structures in lamellar phases. However, when higher acid concentrations are used, the reaction kinetics accelerates and irregular particles form. Irregular particles also form when the fraction of trifunctional crosslinker is increased, and finally complex flower-like structures form for condensation of trimethoxysilane in the hexagonal phase. The particle morphology formed is crucially dependent on the details of the polycondensation rate, crosslinker density and surfactant-monomer/oligomer interactions. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: nonionic; surfactant; templated synthesis

Polymerization in surfactant liquid crystalline phases - Wadekar, M. N.; Pasricha, R.; Gaikwad, A. B.; Kumaraswamy, Guruswamy (Chemistry of Materials, 2005)
We report the formation of cross-linked polysiloxane particles having rodlike and sheetlike morphologies by condensation of monomers in organized liquid crystalline mesophases of nonionic surfactants. The characteristic diffraction pattern obtained from the liquid crystalline surfactant assembly is preserved during polymer synthesis. The polymer colloids are rodlike when synthesized in a hexagonal mesophase and are sheetlike when synthesized in a lamellar mesophase. Interestingly, the size of the polymer particles is on the order of micrometers, viz. 3 orders of magnitude larger than the characteristic size of the surfactant mesophase. Thus, the polymers phase separate from the liquid crystalline phase during polymerization, and organize to resemble the mesophase geometry. The polymer particles are organized so as to minimize the elastic distortion of the surfactant mesophase after they phase separate. We speculate that the observed particle morphologies are formed due to the slow kinetics of polycondensation under our experimental conditions.

Poly(pseudo)rotaxane-like network mediated by hydrogen bonds in the solid-state structure of 1,7-phenanthroline - Arora, KK; Pedireddi, VR (Crystal Growth & Design, 2005)
A unique poly(pseudo)rotaxane-like network constituted by C-H center dot center dot center dot N hydrogen bonds in the solid-state structure of 1,7-phenanthroline and a self-inclusion host-guest type assembly in its salt form have been discussed. The assemblies are characterized by single-crystal X-ray diffraction methods.

Porous gold nanospheres by controlled transmetalation reaction: a novel material for application in cell imaging - Shukla, Sourabh; Priscilla, Anie; Banerjee, Meenal; Bhonde, Ramesh R.; Ghatak, J.; Satyam, P. V.; Sastry, Murali (Chemistry of Materials, 2005)
Hollow shell nanostructures have numerous potential applications due to their interesting optical and electronic properties, which can be tuned by varying their shape, size, and shell thickness. In this paper we describe a simple galvanic replacement reaction (transmetalation reaction) involving sacrificial silver nanoparticles and Au(III) ions using a dialysis membrane. The dialysis membrane acts as a partial barrier that provides excellent control over the kinetics of reaction. This process results in the formation of porous gold nanospheres that improve the fluorescence in cell staining by offering an enhanced surface area for binding of the fluorescent dye, propidium iodide (PI). Such porous nanostructures could be ideal candidates for applications such as catalysis, enzyme immobilization, and drug delivery.

Preorganizing linear (self-complementary) quadruple hydrogen-bonding arrays using intramolecular hydrogen bonding as the sole force - Prabhakaran, Panchami; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2005)
In this article we describe a rational approach for prefixing multiple cooperative binding sites in an ideal spatial arrangement on a structurally rigid backbone, constrained exclusively by intramolecular hydrogen bonding. The idea is exemplified by the ability of the self-assembling constructs la-e and 2a,b to form hydrogen-bonded dimers, whose structural preorganization has been solely effected by intramolecular hydrogen bonding. The readily accessible amidinourea backbone has been used as a common platform for the construction of a variety of such self-assembling systems. ESI mass spectrometry and single-crystal X-ray diffraction studies have been particularly effective in investigating the self-assembling propensities of these systems. Remarkably, most the H-bonded dimers reported herein undergo an unusual mode of self-assembly, using intermolecular four-membered ring hydrogen-bonded interaction, affording extended supramolecular networks.

Preparation and characterization of a copper based Indian traditional drug: tamra bhasma - Wadekar, M. P.; Rode, C. V.; Bendale, Y. N.; Patil, K. R.; Prabhune, Asmita (Journal of Pharmaceutical and Biomedical Analysis, 2005)
The copper based Indian traditional drug `tamra bhasma' is administered for various ailments since long. Its synthesis involves treating metallic copper with plant juices and then repeated calcination in presence of air so that the metallic state is transformed into the corresponding oxide form traditionally known as `bhasma'. In this work, we present a systematic characterization of this traditional drug using various techniques like X-ray diffraction (XRD), scanning electron microscopy (SEM)-energy dispersive X-ray analysis (EDX), X-ray photoelectron spectroscopy (XPS), infrared spectroscopy (IR), thermogravimetry (TG) and surface area measurement. The results obtained were found to match very well with those of a standard copper oxide confirming the composition of the drug sample. In addition, some specific findings were also made which could help in interpreting the therapeutic properties of the traditional drug `tamra bhasma'. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: copper oxide; crystallite size; tamra bhasma; traditional medicine; XPS of copper oxide; XRD

Preparation and characterization of composite electrodes of coconut-shell-based activated carbon and hydrous ruthenium oxide for supercapacitors - Dandekar, M. S.; Arabale, G.; Vijayamohanan, K. (Journal of Power Sources, 2005)
The relationship between the structure-specific capacitance (F g(-1)) of a composite electrode consisting of activated coconut-shell carbon and hydrous ruthenium oxide (RuOx(OH)(y)) has been evaluated by impregnating various amounts of RuOx(OH)(y) into activated carbon that is specially prepared with optimum pore-size distribution. The composite electrode shows an enhanced specific capacitance of 250 F g(-1) in 1 M H2SO4 with 9 wt.% ruthenium incorporated. Chemical and structural characterization of the composites reveals a homogeneous distribution of amorphous RuOx(OH)(y) throughout the porous network of the activated carbon. Electrochemical characterization indicates an almost linear dependence of capacitance on the amount of ruthenium owing to its pseudocapacitive nature. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: activated carbon; Composite; Electrochemical characterization; pseudocapacitance; specific capacitance; supercapacitor

Preparation, characterization, and water-sorption study of polyvinyl alcohol based hydrogels with grafted hydrophilic and hydrophobic segments - Shukla, S.; Bajpai, A. K.; Kulkarni, R. A. (Journal of Applied Polymer Science, 2005)
The interpenetrating polymer network hydrogels based on poly(vinyl alcohol) were obtained by graft copolymerization of acrylamide and styrene onto polyvinyl alcohol in the presence of N,N'-methylene bisacrylamide as a crosslinking agent. The hydrogels were characterized by optical microscopy, scanning electron microscopy, infrared spectral analysis, differential scanning calorimeter, and thermogravimetric analysis. The hydrogels showed enormous swelling in aqueous medium and displayed swelling characteristics, which were highly dependent on the chemical composition of the hydrogels and pH of the swelling medium. The kinetics of water uptake and the mechanisms of water transport were studied as a function of composition of the hydrogel and pH of the swelling medium. (C) 2005 Wiley Periodicals, Inc.
Keywords: Characterization; equilibrium swelling; grafting; IPN hydrogels; polyvinyl alcohol

Preparation of ferroelectric BaNb2O6 the urea method - Dhage, S. R.; Pasricha, R.; Ravi, V. (Materials Letters, 2005)
A precipitate was formed when an aqueous solution of BaCl2, NbF5 and urea in required ratio (the ratio of total metal cations to the urea is five) is heated on a water bath at 100 degrees C. This precipitate on decomposition at 600 degrees C yielded the nanocrystallites of BaNb2O6 (BN), as confirmed by X-ray diffraction study (XRD). This is a much lower temperature as compared to that prepared by traditional solid state method (1000 degrees C) as reported for the formation of BaNb2O6. Transmission electron microscope (TEM) investigations revealed that the average particle size is 85 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 900. The ferroelectric hysteresis loop parameters of these samples were also studied. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Chemical synthesis; electronic material; ferroelectricity; Oxides

Preparation of fine MgTa2O6 and Mg4Ta2O9 powders by chemical methods - Navale, SC; Ravi, V (Materials Science and Engineering B-Solid State Materials for Advanced Technology, 2005)
Two different chemical methods are applied to prepare MgTa2O6 (MT2) and Mg4Ta2O9 (M4T2) powders. A gel was formed when a aqueous solution of Mg(NO3)(2), TAF(5) and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 750 degrees C produced the fine crystallites of ternary oxide, M4T2. A simple co-precipitation technique had been successfully applied for the preparation of pure ultrafine single phase MT2. Ammonium hydroxide was used to precipitate Mg2+ and Ta5+ cations as hydroxides simultaneously. This precursor on heating at 750 degrees produces MT2 powders. The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron microscopy (TEM). (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Electron microscopy; powders-chemical preparation; X-ray methods

Preparation of nanocrystalline ferroelectric BaNb(2)O6 by citrate gel method - Gaikwad, S. P.; Samuel, V; Pasricha, R; Ravi, V (Bulletin of Materials Science, 2005)
A gel was formed when a aqueous solution of BaCl2, NbF5 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 600 degrees C yielded the nano crystallites of BaNb2O6, as confirmed by X-ray diffraction study (XRD). This is a much lower temperature as compared to that prepared by traditional solid state method (1000 degrees C) as reported for the formation of BaNb2O6. Transmission electron microscopic. (TEM) investigations revealed that the average particle size is 50 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 1000. The ferroelectric hysteresis loop parameters of these samples were also studied.
Keywords: Ceramics; Chemical synthesis; electronic material; ferroelectricity; Oxides

Preparation of nanocrystalline ferroelectric CaBi2Ta2O9 by the urea method - Gaikwad, S. P.; Pasricha, R; Ravi, V (Ceramics International, 2005)
A precipitate was formed when a aqueous solution of CaCl2, BiCl3, TaF5 and urea in stoichiometric ratio (total metal cations to urea ratio is 5) is heated on a water bath. This precipitate on decomposition at 600 degrees C yielded the nanocrystallites of ternary oxide CaBi2Ta2O9 (CBT) as confirmed by X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). Ferroelectric hysteresis loop parameters such as remnant polarization (P-r) and coercive field (E-C) were also determined. TEM investigations revealed that the average particle size of the polycrystalline powder is 70 nm. The room temperature dielectric constant was found to be 110. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: dielectric properties; Electron microscopy; ferroelectric properties; powders : chemical preparation

Preparation of nanocrystalline ferroelectric CaBi2TaO9 by citrate gel method - Gaikwad, S. P.; Pasricha, R; Ravi, V (Materials Science and Engineering B-Solid State Materials for Advanced Technology, 2005)
A gel was formed when an aqueous solution of CaCl2, BiCl3, TaF5 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 600degreesC yielded the nano-crystallites of ternary oxide, CaBi2Ta2O9 (CBT) as confirmed by X-ray diffraction study (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). Ferroelectric hysteresis loop parameters such as remnant polarization (P-r) and coercive field (E-C) are also determined. TEM investigations revealed that the average particle size of the polycrystalline powder is 40 nm. The room temperature dielectric constant was found to be 90. (C) 2004 Elsevier B.V All rights reserved.
Keywords: Bismuth; diffraction; Electron microscopy

Preparation of nanocrystalline LiNbO3 by citrate gel method - Navale, SC; Samuel, V; Ravi, V (Materials Letters, 2005)
A gel was formed when an aqueous solution of Li(NO3) NbF5 and citric acid in stoichiometric ratio is heated in a water bath at 100 degrees C. This gel on decomposition at 700 degrees C produced the fine crystallites of ternary oxide, LiNbO3 (LN). The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Electron microscopy; electronic materials; lithium niobate; X-ray diffraction

Preparation of nanocrystalline MgNb2O6 by citrate gel method - Pasricha, R; Ravi, V (Materials Letters, 2005)
A gel was formed when a aqueous solution of Mg(NO3)(2), NbF5 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 700 degrees C produced the fine crystallites of ternary oxide, MgNb2O6 (MN). The formation of MN phase and lattice parameters were determined by the powder X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Citrate gel; Electron microscopy; magnesium niobate; powders; X-ray diffraction

Preparation of ultrafine LiTaO3 powders by citrate gel method - Navale, SC; Samuel, V; Ravi, V (Bulletin of Materials Science, 2005)
A gel was formed when a aqueous solution of Li(NO3), TaF5 and citric acid in stoichiometric ratio was heated in a water bath. This gel on decomposition at 700 degrees C produced fine crystallites of ternary oxide, LiTaO3 (LT). The phase contents and lattice parameters were studied by powder X-ray diffraction (XRD). Particle size and morphology were studied by transmission electron spectroscopy (TEM).
Keywords: Ceramics; Electron microscopy; electronic materials; X-ray diffraction

Pressure dependence of the dissociation of acetic, benzoic, mandelic and succinic acids at 298.15 K - Kumar, Anil (Thermochimica Acta, 2005)
Dissociation constants for acetic, benzoic, mandelic and succinic acids have been measured at 298.15 K as a function of pressure up to 138.8 MPa. The spectrophotometric technique using Bromocresol Green as the optical indicator was employed up to ionic strength of 0.03 mol kg(-1) in aqueous solution. Thermodynamic dissociation constants were calculated with the Davies activity coefficient equation. The pressure dependences of the ionization constants for the weak acids can be described by the equation of Lown, Thirsk and Wynne-Jones, application of which leads to accurate partial molal volume change on ionization, Delta(V) over bar (o) and compressibility change, Delta(K) over bar (o) at 0.1 MPa. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: Acetic acid; benzoic acid; dissociation constants; high pressure; mandelic acid; succinic acid

Proceedings of the National Conference on Nanoscience and Technology - Part II - Foreword - Sood, AK; Ganesh, Krishna N.; Sundar, CS; Raychaudhuri, AK (Pramana-Journal of Physics, 2005)

Proceedings of the National Conference on Nanoscience and Technology Part I - National Chemical Laboratory - Pune - 7-8 March 2005 - Foreword - Sood, AK; Ganesh, Krishna N.; Sundar, CS; Raychaudhuri, AK (Pramana-Journal of Physics, 2005)

Purification and properties of a low molecular weight 1,4-beta-D-glucan glucohydrolase having one active site for carboxymethyl cellulose and xylan from an alkalothermophilic Thermomonospora sp - Jagtap, Sharmili; Rao, M (Biochemical and Biophysical Research Communications, 2005)
A low molecular weight 1,4-beta-D-glucan glucohydrolase from an extracellular culture filtrate of Thermomonospora sp. was purified to homogeneity. The molecular weight of the purified enzyme was 14.2 kDa by MALDI-TOF analysis and is in agreement with SDS-PAGE and gel filtration chromatography. The purified enzyme exhibited both endocarboxymethyl cellulase and endoxylanase activities. A kinetic method was employed to study the active site of the enzyme that hydrolyzes both carboxymethyl cellulose and xylan. The experimental data coincide well with the theoretical values calculated for the case of a single active site. Conformation and microenvironment at the active site was probed with fluorescent chemo-affinity labeling using o-phthalaidehyde as the chemical initiator. Formation of isoindole derivative resulted in complete inactivation of the enzyme to hydrolyze both xylan and CMC as judged by fluorescence studies corroborating a single active site for the hydrolysis of xylan and CMC. (C) 2005 Elsevier Inc. All rights reserved.
Keywords: Cellulase; CMC; OPTA; single active site; Thermomonospora sp.; xylan; Xylanase

PVA stabilized gold nanoparticles by use of unexplored albeit conventional reducing agent - Khanna, P. K.; Gokhale, R.; Subbarao, V. V. V. S.; Vishwanath, A. K.; Das, B. K.; Satyanarayana, C. V. V. (Materials Chemistry and Physics, 2005)
Poly(vinyl alcohol) (PVA) stabilized gold nanoparticles have been prepared in aqueous medium using two different reducing viz.; hydrazine hydrate, a stronger reducing agent and sodium formaldehydesulfoxylate (SFS), a slightly weaker reducing agent. SFS is used for first ever time for reduction of gold metal salt. The PVA stabilized gold nanoparticles solutions are wine red to blood red coloured and are stable over a long period of time with no indication of aggregation. The solution shows strong visible light absorptions in the range of 520-540 nm, characteristics of gold nanoparticles. Powder X-ray diffraction patterns of freshly prepared films containing gold nanoparticles indicated particles size to be about 15 nm. Transmission electron microscopy (TEM) of a more than two-week-old sample revealed well-defined non-agglomerated spherical particles of about 50 nm diameter in solutions. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; electronic materials; Nanostructures; Polymer

Pyrazole-tethered heteroditopic ligands and their transition metal complexes: synthesis, structure, and reactivity - Mukherjee, Anuradha; Subramanyam, U.; Puranik, Vedavati G.; Mohandas, T. P.; Sarkar, A. (European Journal of Inorganic Chemistry, 2005)
Various pyrazole-based PN (2a-c) and N,N (3a-b) ligands have been synthesized. Using representative ligands, Ni-II, Co-II, Cu-II, and Cu-I complexes have been prepared and structurally characterized by crystallography. During complexation of Co-II and Cu-II salts, the phosphane part of the PN ligand oxidized to phosphane oxide. For N,N donor ligands, a dimeric chloro-bridged Ni-III complex was obtained. Ni-II complex 4 is an active catalyst for ethylene oligomerization. ((c) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheirn, Germany, 2005).
Keywords: cobalt; Copper; hemilabile ligands; Nickel; oligomerization; Pyrazole

Pyridine mediated supramolecular assemblies of 3,5-dinitro substituted benzoic acid, benzamide and benzonitrile - Arora, KK; PrakashaReddy, J; Pedireddi, VR (Tetrahedron, 2005)
Synthesis and characterization of molecular assemblies of pyridine adducts, la, 2a and 3a, of 3,5-dinitrobenzoic acid, 1, 3,5-dinitrobenzamide, 2 and 3,5-dinitrobenzonitrile, 3, respectively, have been reported. All these adducts were obtained by crystallization of 1, 2 and 3 from pyridine. However, crystallization of I from pyridine in the presence of benzene resulted in the formation of a pyridinium adduct, 1b, along with a water molecule. All the adducts crystallize in a 1: 1 molecular ratio except la, which forms a 1:2 adduct, as characterized by single crystal X-ray diffraction method. The adducts crystallize in different space groups-la, orthorhombic, Pna2(1); 1b, monoclinic, P2(1); 2a, monoclinc, C2/c; 3a, triclinic, P-1. In two-dimensional arrangement, la, 1b and 3a form sheet structures. In la, within the two-dimensional sheets, large cavities are formed, which are occupied by pyridine molecules. In 1b, the sheets are catenated to form a chicken-wire network. However, 2a formed a crossed ribbon packing pattern with empty channels in the three-dimensional structure. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: 3; 5-dinitrobenzamide; 5-dinitrobenzoic acid; 5-dinitrobenzonitrile; channel structures; host-guest complexes; layered structures; molecular recognition; Pyridine

Palladium mediated cycloisomerization of sugar alkynols: synthesis of cyclic enol-ethers and spiroketals - Ramana, C. V.; Mallik, Rosy; Gonnade, Rajesh G.; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
Functionalized bicyclic enol-ethers and spiroketals are prepared by Pd catalyzed cycloisomerization of 3-C-alkynylfuranosyl derivatives. Cycloisomerization of differently substituted alkyne derivatives revealed a preference for 6-endo-dig cyclization over 5-exo-dig if the substituent is not sufficiently electron withdrawing. The scope of these cycloisomerizations has been further extended by integrating with conjugate addition. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: c-alkynylfuranose; cycloisomerization; enol-ether; Palladium; Spiroketal

Partial oxidation of methane to syngas with or without simultaneous steam or CO2 reforming over a high-temperature stable-NiCoMgCeOx supported on zirconia-hafnia catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Applied Catalysis A-General, 2006)
A NiCoMgCeOx (Ni/Co/Mg/Ce: 1:0.2:1.2:1.2)/zirconia-hafnia catalyst with unusually high thermal stability has been investigated for syngas generation via a process that includes the catalytic partial oxidation of methane (CPOM), the oxidative steam reforming of methane (OSRM) and the oxidative CO2 reforming of methane (OCRM). The catalyst calcined at 1400 degrees C (for 4 h) showed excellent activity/selectivity for the CPOM, OSRM and the OCRM reactions; furthermore no catalyst deactivation was observed for a period of 20 h. For the CPOM process, the selectivity for H-2 was > 95% at reaction temperatures > 650 degrees C however temperatures above 800 degrees C were required to achieve > 95% CO selectivity. While the reaction temperature had a considerable influence on the CPOM product H-2/CO ratio, the space velocity (at 850 degrees C) did not affect it to any significant extent. For the OSRM process, the H2O/CH4 ratio and the reaction temperature had a strong effect on the product H-2/CO ratio and the heat of the reaction; depending on the H2O/CH4 ratio and reaction temperature, the OSRM process could be operated in a mildly exothermic, thermoneutral or mildly endothermic mode. The CO2 conversion was very strongly affected by the reaction temperature in the OCRM process; reasonably high CO2 conversion ( > 40%) could only be obtained at high OCRM reaction temperatures ( > 850 degrees C). The exothermicity of the OCRM reaction was found to decrease with increasing reaction temperature. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: dry (CO2) reforming; high-temperature stable; methane; oxy-steam reforming; Partial oxidation; Steam reforming; Syngas

Phase evolution of NiTiO3 prepared by coprecipitation method - Murugan, A. Vadivel; Samuel, V.; Navale, S. C.; Ravi, V. (Materials Letters, 2006)
A simple coprecipitation technique was used for the preparation of NiTiO3 powders. Ammonium carbonate solution was added to a solution mixture containing stoichiometric amounts of Ni(NO3)(2) and TiOCl2 to precipitate nickel as carbonate and titanium as hydroxide under basic conditions. The precipitate was calcined at different temperatures ranging from 100 to 800 degrees C and phase evolution of NiTiO3 was investigated by X-ray diffraction (XRD) studies. It is observed that nickel titanate was formed at 750 degrees C. For comparison, NiTiO3 was also prepared by standard ceramic process. Particle size and morphology was studied by transmission electron microscopy (TEM). (c) 2005 Elsevier B.V. All fights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; NiTiO3; Oxides; X-ray diffraction

Phenol tert-butylation over zirconia-supported 12-molybdophosphoric acid catalyst - Devassy, Biju M.; Shanbhag, G.V.; Halligudi, S.B. (Journal of Molecular Catalysis A-Chemical, 2006)
The alkylation of phenol with tert-butanol was investigated using zirconia-supported 12-molybdophosphoric acid (MPA) as catalyst. The catalysts with different MPA loading (5-25 wt.% calcined at 700 degrees C) and calcination temperature (15 wt.% calcined from 500 to 750 degrees C) were prepared by suspending zirconium oxyhydroxide in methanol solution of MPA followed by drying and calcination. These catalysts were characterized by X-ray diffraction and (31)p MAS NMR spectroscopy measurements. The XRD results indicated that MPA stabilizes the tetragonal phase of zirconia. (31)p MAS NMR spectra showed the presence of three types of phosphorous species, phosphomolybdate in interaction with zirconia, decomposition product of MFPA and an unidentified species. IFTIR pyridine adsorption on 15% MPA catalyst calcined at different temperatures showed the presence of both Bronsted and Lewis acidity and the catalyst calcined at 700 degrees C showed the highest relative Bronsted acidity. Under the reaction conditions of 140 degrees C, tert-butanol/phenol molar ratio of 2 and LHSV of 4 h(-1), the phenol conversion was 80.6% at 2 h (selectivity to 2-TBP 11.5%, 2,4-DTBP 55.2%, and 4-TBP 25.7%), which decreased slowly with time and at 31 h, it was 58.5% (selectivity to 2-TBP 15.2%, 2,4-DTBP 41.6%, and 4-TBP 38.4%). The major reason for the catalyst deactivation was the reduction and leaching of MPA from the catalyst surface. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 12-molybdophosphoric acid; phenol; tert-butylation; Zirconia

Photo-bio-degradability of agro waste and ethylene-propylene copolymers composites under abiotic and biotic environments - Kumar, A. Pratheep; Pandey, Jitendra K.; Kumar, Bijendra; Singh, R. P. (Journal of Polymers and the Environment, 2006)
Composites were prepared by two methods, (i) graft copolymerization (GFC) of isotactic polypropylene (PP) with maliec anhydride, (MAH) followed by esterification with coir fiber and (ii) by direct reactive mixing (DFC) of polypropylene (PP) and ethylene-propylene (EP) copolymers with MAH and peroxide with coir fiber. These composites, after molding in films (5 x 5 cm, - 100 mu m thickness) were examined for susceptibility to biological attack by measuring the percentage weight loss in compost upto 6 months, periodically, and fungal colonization on surface of the samples, when kept as sole carbon source for the growth of Aspergillus niger in culture medium upto 40 days. Photodegradation was evaluated by monitoring the variations in FT-IR spectrum and crack formation after successive treatment with UV light (>= 290 nm) for 0, 20, 50 and 100 h at 60 C in the presence of air. Specimens of virgin PP were taken as a reference during all period of photo and biodegradation studies. Significant changes were observed depending on the preparation methods during photodegradation and biodisintegration of composites. DFCs samples were disintegrated faster than GFCs during the composting whereas, in culture, GFCs were covered highly in well uniform way by fungi. It was observed that photo-oxidative ageing directly enhanced the biodegradability of composites as the increase in fungal growth rate and decrease in weight during composting were found. It was concluded that extent of compatibilization had a profound effect on photo-oxidation and biodisintegration of composite material; consequently ester bonds were main units during fungal consumption. Composition of monomers in copolymers was also showing significant effect on the degradability which decreased with increasing content of ethylene in ethylene-propylene (EP) copolymers.
Keywords: Biodegradation; biodisintegration and composting; composites; ethylene-propylene copolymers; photo-degradation

Photocatalytic degradation of organic contaminants in water by ZnO nanoparticles: revisited - Hariharan, C. (Applied Catalysis A-General, 2006)
Nanoscale photocatalysts have attracted much attention due to their high surface area to volume ratios. This work investigates the photodegradation of organic contaminants using the fluorescence emission characteristics of ZnO nanoparticles (ZnO-nano) in aqueous solutions. This is accomplished by preparing nanocrystalline ZnO; the presence of organic contaminants in water is readily detected from the quenching of fluorescence observed from ZnO semiconductor films. Photolysis of ZnO thin films immersed into an aqueous system containing organic contaminants results in the degradation of the contaminants. A comprehensive study has been done involving several organic contaminants in water (like aliphatic and aromatic chloro compounds as well as some commonly used aromatic solvents) to check the suitability of ZnO-nano as an efficient photocatalyst. The ZnO nanoparticles not only serve as a better catalytic system compared to bulk ZnO and commercially available Degussa TiO2 in achieving degradation of the added contaminants, but unlike other semiconductor systems can also act as a non-specific sensor for the presence of these common contaminants in water. A total cleanup of a cocktail of contaminants in water was also achieved using the ZnO-nano. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Nanoparticles; organic contaminants and photocatalysis; Semiconductor; ZnO

Photoelectrochemical properties of electrochemically deposited CdIn2S4 thin films - Kokate, A. V.; Asabe, M. R.; Delekar, S. D.; Gavali, L. V.; Mulla, Imtiaz S.; Hankare, P. P.; Chougule, B. K. (Journal of Physics and Chemistry of Solids, 2006)
Thin films of CdIn2S4 have been deposited on to stainless steel and fluorine-doped tin oxide (FTO)-coated glass substrates from aqueous acidic bath using an electrodeposition technique. Ethylene diamine tetra-acetic acid (EDTA) disodium salt is used as complexing agent to obtain good-quality deposits by controlling the rate of the reaction. The different preparative parameters like concentration of bath, deposition time, bath temperature, pH of the bath have been optimized by the photoelectrochemical (PEC) technique in order to get good-quality photosensitive material. Different techniques have been used to characterize CdIn2S4 thin films. Optical absorption shows the presence of direct transition with band gap energy 2.17 eV. The X-ray diffraction (XRD) analysis of the as-deposited and annealed films showed the presence of polycrystalline nature. Energy-dispersive analysis by X-ray (EDAX) study for the sample deposited at optimized preparative parameters shows that the In-to-Cd ratio is almost 2 and S-to-Cd ratio is almost 4. Scanning electron microscopy (SEM) for samples deposited at optimized preparative parameters reveals that spherical grains are uniformly distributed over the surface of the substrate indicates the well-defined growth of polycrystalline CdIn2S4 thin film. PEC characterization of the films is carried out by studying photoresponse, spectral response and photovoltaic output characteristics. The fill factor (ff) and power conversion efficiency (eta) of the cell are 69 and 2.94%, respectively. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Thin films; X-ray diffraction

Photoluminescence studies of Eu3+ doped Y2O3 nanophosphor prepared by microwave hydrothermal method - Murugan, A. Vadivel; Viswanath, Annamraju Kasi; Ravi, V.; Kakade, Bhalchandra A.; Saaminathan, V. (Applied Physics Letters, 2006)
In this letter, the authors report the photoluminescence studies of Eu3+ doped Y2O3 nanorods, which have been synthesized by rapid microwave hydrothermal route within 6 min. The nanostructured Eu3+ doped Y2O3 is characterized by x-ray diffraction, transmission electron microscopy, and photoluminescence. The emission spectrum shows transitions from the excited 5D(0) state to F-7(J) (J=0,1,2,3,4) levels of the Eu3+ ion. The most intense peak around 612 nm is due to the D-5(0)-> F-7(2) transition, expected from the Judd-Ofelt selection rules [B. R. Judd, Phys. Rev. 127, 750 (1962); G. S. Ofelt, J. Chem. Phys. 37, 511 (1962)]. Photoluminescence measurements demonstrated that the nanocrystalline Eu3+:Y2O3 phase shows higher photoluminescence intensity. (c) 2006 American Institute of Physics.

Photooxidation of vulcanized EPDM/montmorillonite nanocomposites - Morlat-Therias, Sandrine; Fanton, Elisabeth; Tomer, Namrata S.; Rana, Sravendra; Singh, R. P.; Gardette, Jean Luc (Polymer Degradation and Stability, 2006)
The photooxidation of a vulcanized ethylene-propylene-diene monomer (EPDM)/montmorillonite nanocomposite as well as EPDM/nanocomposite with stabilizers was studied under accelerated UV-light irradiation (lambda >= 300 nm, 60 degrees C) for different times. The development of functional groups during oxidation was monitored by infrared spectroscopy. Photodegradation of the neat polymer and composites took place and the increases of absorbance in hydroxyl and carbonyl groups with irradiation times and also the decreases of the EPDM unsaturations were measured. The data indicated that the photooxidation products were not changed in the presence of the nanofiller. However, the presence of MMt was observed to dramatically enhance the rate of photooxidation of EPDM with a shortening of the oxidation induction time, leading to a decrease of the durability of the nanocomposites. On the other hand, it was observed that addition of stabilizers, either Tinuvin P or 2-mercaptobenzimidazole, was efficient in inhibiting the degradative effect of MMt. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: EPDM; Nanocomposite; photooxidation rate; stabilization

Physical manipulation of biological and chemical syntheses for nanoparticle shape and size control - Ogale, Satishchandra B.; Ahmad, Absar; Pasricha, R.; Dhas, Vivek V.; Syed, A. (Applied Physics Letters, 2006)
A nanosynthesis scheme is demonstrated which renders excellent control of nanoparticle shape, size, and dispersity in a solution based synthesis process. The scheme, termed as percolative microcavity synthesis, involves the use of a granular medium with percolative microcavities which facilitate nearly similar grain size/shape dependent reaction zones limiting intrinsic growth inhomogeneities, enabling particle size/shape control. The viability of the process is demonstrated for the synthesis of gold nanoparticles by a plant extract based biological method as well as a chemical method. (c) 2006 American Institute of Physics.

Pictet-Spengler cyclization in room temperature ionic liquid: a convenient access to tetrahydro beta-carbolines - Muthukrishnan, Murugan; More, Shivaji V.; Garud, Dinesh R.; Ramana, C. V.; Joshi, Rohini R.; Joshi, Ramesh A. (Journal of Heterocyclic Chemistry, 2006)
1,2,3,4-Tetrahydro-beta-carbolines have been synthesized in moderate to good yields in short reaction time using the ionic liquid [bbim] BF4 as reaction medium and promoter. There was no need for the use of an additional catalyst normally employed in Pictet-Spengler condensation.

Plastics materials flow analysis for India - Mutha, N. H.; Patel, M.; Premnath, V. (Resources Conservation and Recycling, 2006)
Forecasting material flows is essential for sound policy making on issues relating to waste management. This paper presents the results of the plastics materials flow analysis (MFA) for India. In the recent past, India has witnessed a substantial growth in the consumption of plastics and an increased production of plastic waste. Polyolefins account for the major share of 60% in the total plastics consumption in India. Packaging is the major plastics consuming sector, with 42% of the total consumption, followed by consumer products and the construction industry. The relationship observed between plastic consumption and the gross domestic product for several countries was used to estimate future plastics consumption (master curve). Elasticities of the individual material growth with respect to GDP were established for the past and for the next three decades estimated for India thereby assuming a development comparable with that of Western Europe. On this basis, the total plastics consumption is projected to grow by a factor of 6 between 2000 and 2030. The consumption of various end products is combined with their corresponding lifetimes to calculate the total waste quantities. The weighted average lifetime of plastics products was calculated as 8 years. Forty-seven percent of the total plastics waste generated is currently recycled in India; this is much higher than the share of recycling in most of the other countries. The recycling sector alone employs as many people as the plastics processing sector, which employs about eight times more people than the plastics manufacturing sector. Due to the increasing share of long-life products in the economy, and consequently in the volume of waste generated, the share of recycling will decrease to 35% over the next three decades. The total waste available for disposal (excluding recycling) will increase at least 10-fold up to the year 2030 from its current level of 1.3 million tonnes. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: employment; India; material flow analysis (MFA); plastics; plastics consumption; plastics waste; Recycling; reuse

Poly(High Internal Phase Emulsion) of 2-EHA, 2-EHMA and EGDA with naturally occurring phenolic compounds", paper presented at international conference on ?polymers for advanced technology - Ingavle, Ganesh C.; Shaikh, A. A.; Bhongale, Sunil Sitaram; Scaria, S.; Chavan, Nayaku; Qureshi, Mohammed; Ponrathnam, Surendra (Polymers for Advanced Technology, 2006)

Polymer supported vanadium and molybdenum complexes as potential catalysts for the oxidation and oxidative bromination of organic substrates - Maurya, Mannar R.; Kumar, Umesh; Manikandan, Palanichamy (Dalton Transactions, 2006)
{The Schiff base (H(2)fsal-ohyba) derived from 3-formylsalicylic acid and o-hydroxybenzylamine has been covalently bonded to chloromethylated polystyrene cross-linked with 5% divinylbenzene ( abbreviated as PS-H(2)fsal-ohyba, I). Treatment of [
Keywords: Bile acids; bis-steroids; hybrids; Peptides; polyamines; saponins; steroidal conjugates; synthetic ionophores

Poly(o-toluidine) coatings on copper: electrochemical synthesis from aqueous media - Shinde, V.; Mandale, A. B.; Patil, K. R.; Gaikwad, A. B.; Patil, P. P. (Surface & Coating Technology, 2006)
Poly(o-toluidine) (POT) coatings were synthesized on copper (Cu) by electrochemical polymerization of o-toluidine using aqueous sodium oxalate solution as supporting electrolyte. The resulting coatings were uniform, compact and strongly adherent to the Cu substrate. These coatings were characterized by using cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), X-ray diffraction (XRD) measurements and X-ray photoelectron spectroscopy (XPS). The results of these studies reveal that the sodium oxalate is suitable supporting electrolyte for the electrochemical polymerization of o-toluidine on Cu substrate. It is found that the electrochemical polymerization of o-toluidine takes place after the passivation of the Cu substrate via formation of copper oxalate (CuC2O4, H2O) layer, which is confirmed by XRD and XPS. The optical absorption spectroscopy study reveals the exclusive formation of the pernigraniline base (PB) form of POT. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Conducting polymer coatings; Copper; Corrosion resistant coatings; cyclic voltammetry; poly(o-toluidine) coatings

Poly(urethane methacrylate-co-glycidyl methacrylate)-supported-polypropylene biphasic membrane for lipase immobilization - Pujari, N. S.; Vaidya, Bx; Bagalkote, S.; Ponrathnam, S.; Nene, Sanjay (Journal of Membrane Science, 2006)
Polypropylene (PP) was hydrophilized by coating followed by UV curing of a blend of 2-hydroxyethyl methacrylate (HEMA) terminated polyurethane prepolymer and glycidyl methacrylate (GMA). This allows formation of a hydrophobic membrane with increased surface hydrophilicity, biocompatibility and stability. Candida rugosa lipase (CRL) was covalently immobilized on this membrane using 5% glutaraldehyde as a crosslinking agent for post immobilization stabilization of enzyme on membrane. The membrane obtained was placed in a batch membrane reactor where a model esterification of oleic acid with octanol was studied. Under optimum conditions, the biocatalytic membrane gave a specific activity of 796.27 units/mg and 90.26% activity yield. Moreover, there was 85. 10% retention of specific activity. The biocatalytic membrane was observed to retain about 84.23% of its synthetic activity after six cycles. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Candida rugosa lipase; Enzyme immobilization; membrane bioreactor; urethane methacrylate

Potassium phosphate or silica sulfuric acid catalyzed conjugate addition of thiols to alpha,beta-unsaturated ketones at room temperature under solvent-free conditions - Pore, D. M.; Soudagar, M. S.; Desai, Uday V.; Thopate, T. S.; Wadagaonkar, P. P. (Tetrahedron Letters, 2006)
Potassium phosphate and silica sulfuric acid have been found to be useful and highly efficient catalysts for conjugate addition of thiols to alpha,beta-unsaturated ketones under solvent-free conditions, at room temperature. Silica sulfuric acid (SSA) was found to be suitable for electron-deficient enones while potassium phosphate was found to effect thia-Michael addition with both, electron-deficient as well as electron-rich conjugated ketones. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: alpha; beta-unsaturated ketones; chalcones; conjugated enones; Michael addition; Potassium phosphate; silica sulfuric acid; thiols

Preparation and characterization of a series of new organically modified montmorillonite clays using X-ray diffraction, thermogravimetric analysis and FTIR spectroscopy - Natarajan, Upendra; Tiwari, Rajkiran R. (231st National Meeting of the American-Chemical-Society, 2006)

Preparation and characterization of novel hybrid of chitosan-g-lactic acid and montmorillonite - Depan, Dilip; Kumar, Annamalai Pratheep; Singh, Raj Pal (Journal of Biomedical Materials Research Part A, 2006)
The utilization of biopolymers and the development of organic-inorganic hybrids are ever increasing interest of material science researchers around the globe for various applications. The present attempt is intended to prepare nanocomposites of lactic acid grafted chitosan and layered silicates. Nanocomposites were prepared by dissolving chitosan and dispersing sodium montmorillonite in aqueous solution of L-lactic acid with subsequent heating and film casting. They were characterized by conventional techniques such as Fourier transform infrared spectroscopy, X-ray diffractometry, thermogravimetric analysis, energy dispersive X-ray spectroscopy, and elemental analysis. The results from polar optical and transmission electron microscopic measurements are also discussed. Sorption behavior of samples has been followed by measuring swelling degree and contact angle. The films have shown enhanced hydrophilicity when compared with polylactic acid (PLA). Issues on the interactions of polycationic chitosan with clay are also discussed. It is observed that nanocomposites are exhibiting better thermal and physical properties than neat chitosang-LA and PLA. (c) 2006 Wiley Periodicals, Inc.
Keywords: Chitosan; contact angle; graft copolymerization; Nanocomposites; polylactic acid; water absorption

Preparation and characterization of sulfonated syndiotactic polystyrene ionomers/organoclay nanocomposites - Govindaiah, P.; Mallikarjuna, S. R.; Ramesh, C. (Macromolecules, 2006)

Preparation and characterization of urea-formaldehyde-pepsin bioconjugate: a new biocatalyst system - Vinod, V. P.; Shinde, Sudhirkumar; D'Britto, Virginia; Shukla, P. G.; Rao, Mala (Biotechnology Progress, 2006)
This study describes the synthesis of urea formaldehyde (UF) microspheres by a dispersion polycondensation polymerization method. These microspheres with proper F/U molar ratio can provide highly reactive groups, capable of further condensation with the amino acid residues of enzyme/proteins. Presence of methylols groups in UF microspheres was confirmed by C-13 NMR study. Pepsin, a proteolytic enzyme, was immobilized on the UF microspheres to form bioconjugate system. As compared to the free enzyme in solution, the pepsin in the bioconjugate system exhibited significantly enhanced pH and temperature stability. The urea-formaldehydepepsin bioconjugate system also exhibited excellent proteolytic activity over eight successive reuse cycles with more than 50% of initial activity. A highlight of this new biocatalyst is the ease with which separation of this biocatalyst from the reaction medium may be achieved by mild centrifugation.

Preparation and performance evaluation of EPDM nanocomposites under accelerated weathering - Rana, Sravendra; Tevtia, Amit K.; Kumar, Bijendra; Singh, R. P. (Journal of Thermoplastic Composite Materials, 2006)
The degradability of ethylene propylene diene monomer (EPDM) nanocomposites, prepared from organically modified montmorillonite (CMMT), is studied under accelerated UV irradiation (lambda >= 290 nm) for different time intervals. The development of functional groups during degradation is monitored by FT-IR spectroscopy whereas, surface changes are studied by scanning electron microscopy (SEM). The effect of clay modifier and clay concentration on the degradability are studied. The degradation of neat polymer and composites taking place traditionally and an increase in carbonyl and hydroxyl groups are observed with irradiation time. Neat EPDM is found to be less degradable than nanocomposites. Degradation products, as seen by FT-IR in nanocomposites are found to be the same as in neat polymer but are generated at a faster rate. According to the experimental results, one can define that both ammonium ion and neat montmorillonite (MMT) accelerate the photo-oxidation of EPDM.
Keywords: carbonyl index; Degradation; EPDM; layered silicates; Nanocomposites; photooxidation

Preparation of gamma-Fe2O3 nanoparticles using DC thermal arc-plasma route, their characterization and magnetic properties - Banerjee, Indrani; Khollam, Y. B.; Balasubramanian, C.; Pasricha, R.; Bakare, P. P.; Patil, K. R.; Das, A. K.; Bhoraskar, S. V. (Scripta Materialia, 2006)
gamma-Fe2O3 particles were prepared, for the first time, using a direct current thermal arc-plasma route. The powder was characterized using X-ray diffraction, Mossbauer spectroscopy, X-ray photoelectron spectroscopy, chemical analysis, vibrating sample magnetometry C and transmission electron microscopy. The high purity, stoichiometry and spherical morphology of the gamma-Fe2O3 particles (saturation magnetization = 79 emu g(-1) and coercivity = 348 Oe) were confirmed. (c) 2006 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: chemical analysis; DC thermal arc-plasma route; maghemite; Mossbauer spectroscopy; XPS

Preparation of nanocrystalline ferroelectric BaBi4Ti4O15 by Pechini method - Murugan, A. Vadivel; Navale, S. C.; Ravi, V. (Materials Letters, 2006)
A gel was formed when an aqueous solution of BaCl2, BiNO3, TiOCl2 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 600 degrees C produced the nano crystallites of ternary oxide, BaBi4Ti4O15 (BBT). The phase contents and lattice parameters were Studied by the powder X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). The room temperature dielectric constant at I KHz is 90. The ferroelectric hysteresis loop parameters of these samples were also studied by a home built Sawyer-tower circuit. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: dielectric properties; Electron microscopy; ferroelectric properties; powders chemical preparation

Production of lactic acid and fructose from media with cane sugar using mutant of Lactobacillus delbrueckii NCIM 2365 - Patil, S. S.; Kadam, S. R.; Patil, S. S.; Bastawade, Kulbhushan B.; Khire, Jayant Malhar; Gokhale, D. V. (Letters in Applied Microbiology, 2006)
Aims: To examine the potential of Lactobacillus delbrueckii mutant, Uc-3 to produce lactic acid and fructose from sucrose-based media. Methods and Results: The mutant of L. delbrueckii NCIM 2365 was cultivated in shake flask containing hydrolysed cane sugar (sucrose)-based medium. The lactic acid yield and volumetric productivity with hydrolysed cane concentration up to 200 g l(-1) were in the range of 92-97% of the theoretical value and between 2.7 and 3.8 g l(-1) h(-1), respectively. The fructose fraction of the syrup produced was more than 95% when the total initial sugar concentration in the medium was higher (150-200 g l(-1)). There are no unwanted byproducts detected in the fermentation broth. Conclusions: We demonstrated that L. delbrueckii mutant Uc-3 was able to utilize glucose preferentially to produce lactic acid and fructose from hydrolysed cane sugar in batch fermentation process. Significance and Impact of the Study: These findings will be useful in the production of lactic acid and high fructose syrups using media with high concentrations of sucrose-based raw materials. This approach can lead to modification of the traditional fermentation processes to obtain value-added byproducts, attaining better process economics.
Keywords: fructose accumulation; hydrolyzed cane sugar; lactic acid production; Lactobacillus delbrueckii; Mutant

Promoter induced rapid synthesis of AlPO4-5 molecular sieve in non-aqueous media using hexamethyleneimine template - Venkatathri, N. (Journal of the Indian Chemical Society, 2006)
AlPO4-5 have been synthesized from non-aqueous media using hexamethyleneimine template in presence of sodium ions. The results show that the sodium catalyses the nucleation and crystallization process of the formation of AlPO4-5 molecular sieve. The material synthesized was characterized by XRD, SEM, carbon and nitrogen analysis, TG/DTA, FT-IR, Al-27 and P-31 MASNMR. The results show that the samples are highly crystalline. The presence of octahedral and tetrahedral sites are observed in 27 At MASNMR, P-31 MASNMR gives only a single peak for tetrahedral phosphorous atoms.
Keywords: aluminophosphates; Molecular sieve; non-aqueous media

Propane conversion to aromatics on highly active H-GaAlMFI: effect of thermal pretreatment - Choudhary, Tushar V.; Kinage, A.; Banerjee, S.; Choudhary, Vasant R. (Energy & Fuel, 2006)
The propane aromatization activity over H-GaAlMFI has been investigated after different thermal pretreatments ( calcination temperature range: 500- 800 degrees C) at a reaction temperature of 500 degrees C and in the space velocity range of 1500-12000 cm(3)/g/h. The calcination temperature had a strong influence on the strong acidity of the zeolite, propane conversion, and aromatic distribution. The decrease in acidity with increased thermal treatment severity correlated well with the decrease in the framework Ga. There was a considerable decrease in propane aromatization activity at calcination temperatures above 600 degrees C. The effect of calcination temperature on the propane aromatization activity can be explained in terms of change in the strong acidity of the zeolite and the extraframework Ga content. The selectivity for aromatics was found to decrease with increasing thermal pretreatment severity, while that for methane, ethane, and propylene was found to increase. The aromatic distribution was also influenced by the thermal pretreatment; the selectivity for benzene increased with increasing pretreatment temperature, while the selectivity for toluene, C-8 aromatics, and C9+ aromatics decreased.

Propargyl glycosides as stable glycosyl donors: anomeric activation and glycoside syntheses - Hotha, Srinivas; Kashyap, Sudhir (Journal of the American Chemical Society, 2006)

Purification, characterization and substrate specificity of thermostable alpha-galactosidase from Bacillus stearothermophilus (NCIM-5146) - Gote, M. M.; Khan, Mohammad Islam; Gokhale, D. V.; Bastawade, Kulbhushan B.; Khire, Jayant Malhar (Process Biochemistry, 2006)
An extracellular thermostable alpha-galactosidase from Bacillus stearothermophilus (NCIM-5146) has been purified to homogeneity by chromatographic step, using Phenyl Sepharose CL-4B column. The specific activity of the enzyme was increased approximately 389-fold, from 1.03 U/mg protein to 400 U/mg protein. The molecular mass of the purified enzyme as determined by SDS-PAGE and gel filtration was 79.9 and 165.9 kDa, respectively, suggesting dimeric nature. The purified alpha-galactosidase is a non-glycosylated protein with a pI of 4.9. The pH and temperature optima for the purified enzyme are 6.5-7.0 and 65 degrees C, respectively. The alpha-galactosidase is stable over a broad pH range (3-9) and its half-life of inactivation (t(1/2)) at 70 degrees C is 30 min. The partial N-terminal sequence of alpha-galactosidase showed remarkable homology (80% similarity) with earlier reported alpha-galactosidase from B. stearothermophilus NUB 3621. The secondary structure of the enzyme determined by circular dichroism (CD) spectroscopy exhibited alpha/beta class of protein and showed temperature induced conformational forms below and above the transition temperature. The purified enzyme showed biphasic Arrhenius plot with break point at 55 degrees C for pNPG and 50 degrees C for melibiose, raffinose and stachyose. The enzyme hydrolyzes alpha-1-3, alpha-1-4, and alpha-1-6 galactosidic linkages and not the beta-galactosidic linkages. Synthetic substrates pNPG and oNPG had lower K-m and higher K-cat as compare to natural substrates, melibiose, raffinose, and stachyose. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: alpha-galactosidase; Bacillus stearothermophilus (NCIM-5146); Purification; Secondary structure; thermostable enzyme

Pathway to copolymer collapse in dilute solution: uniform versus random distribution of comonomers - Dasmahapatra, Ashok Kumar; Nanavati, Hemant; Kumaraswamy, Guruswamy (Journal of Chemical Physics, 2007)
Monte Carlo simulations show that copolymers with uniformly (or periodically) distributed sticky comonomers collapse ``cooperatively,'' abruptly forming a compact intermediate comprising a monomer shell surrounding a core of the aggregated comonomers. In comparison, random copolymers collapse through a relatively less-compact intermediate comprising a comonomer core surrounded by a fluffy monomer shell that densifies over a wide temperature range. This difference between the collapse pathways for random and uniform copolymers persists to higher chain lengths, where uniform copolymers tend to form multiple comonomer cores. In this paper, we describe the formation of such an intermediate state, and the subsequent collapse, by recognizing that these arise from the expected balance between comonomer aggregation enthalpy and loop formation entropy dictated by the chain microstructure. (c) 2007 American Institute of Physics.

PET-SWNT nanocomposites through ultrasound assisted dissolution-evaporation - Anoop, Anand K.; Agarwal, U. S.; Nisal, Anuya; Joseph, Rani (European Polymer Journal, 2007)
Poly(ethylene terephthalate) (PET) based nanocomposites have been prepared with single walled carbon nanotubes (SWNTs) through an ultrasound assisted dissolution-evaporation method. Differential scanning calorimetry studies showed that SWNTs nucleate crystallization in PET at weight fractions as low as 0.3%, as the nanocomposite melt crystallized during cooling at temperature 24 degrees C higher than neat PET of identical molecular weight. Isothermal crystallization studies also revealed that SWNTs significantly accelerate the crystallization process. Mechanical properties of the PET-SWNT nanocomposites improved as compared to neat PET indicating the effective reinforcement provided by nanotubes in the polymer matrix. Electrical conductivity measurements on the nanocomposite films showed that SWNTs at concentrations exceeding 1 wt% in the PET matrix result in electrical percolation. Comparison of crystallization, conductivity and transmission electron microscopy studies revealed that ultrasound assisted dissolution-evaporation method enables more effective dispersion of SWNTs in the PET matrix as compared to the melt compounding method. (c) 2007 Elsevier Ltd. All rights reserved.

Phosphine ligand and base-free, Pd-catalyzed oxidative cross-coupling reaction of arylboronic acids with arylmercuric acetates - Emmanuvel, Lourdusamy; Sudalai, Arumugam (Arkivoc, 2007)
Arylmercuric acetates have been found to undergo Suzuki type cross coupling reactions with arylboronic acids catalyzed by palladium salts in non-polar solvents under ambient conditions to give biaryl derivatives in high yields. The reaction is mild and does not require any organic or inorganic base nor a phosphine ligand.
Keywords: Arylboronic acid; arylmercuric acetate; palladium salts; Suzuki coupling

Phosphotungstic acid as an efficient solid catalyst for intramolecular rearrangement of benzyl phenyl ether to 2-benzyl phenol - Bhure, Mahesh H.; Rode, Chandrashekhar V.; Chikate, Rajeev C.; Patwardhan, Neeraj; Patil, Shraddha (Catalysis Communications, 2007)
An heteropoly acid (phosphotungstic acid, PTA) was found to be a promising solid acid catalyst as an alternative to the conventional stoichiometric reagents for the rearrangement of benzyl phenyl ether giving 2-benzyl phenol as a major product and 4-benzyl phenol and dibenzylated phenols as side products. Catalyst was recovered from the reaction mixture and reused again without loss of activity. Based on the observed product distribution for various substrates a plausible catalytic reaction pathway has also been proposed. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: benzyl phenyl ether; Intramolecular rearrangement; Phosphotungstic acid

Photodegradation of ethylene/propylene/polar monomers, Co-, and terpolymers. II. prepared by Ni catalyst systems - Fernandes, Susete N.; Correia, Sandra; Matos, Ines; Marques, Maria M.; Rana, Sravendra; Kumar, Bijandra; Gupta, M. K.; Singh, R. P. (Journal of Applied Polymer Science, 2007)
The copolymers of ethylene/propylene as well as their terpolymers with polar monomers were prepared by Ni-catalyst systems and their photodegradation behavior was studied by Fourier transform infrared spectroscopy. The polar monomers used to synthesize co- and terpolymers of ethylene/propylene/polar monomer were 5-hexen-1-ol, 10-undecen-1-ol, acrylamide, methylmethacrylate, acrylonitrile, and methylvinyl ketone. The morphological changes of the irradiated samples were determined by scanning electron microscopy. The photodegradation kinetics has also been studied. The surface damage caused by polychromatic irradiation (lambda >= 290 nm) at 55 degrees C in atmospheric air is presented in different micrographs. The rate of photo-oxidative degradation is very fast in terpolymers containing polar monomers as compared with copolymers and homopolymers. The morphological study of the photodegraded samples showed a very good correlation with the photodegraded results. (c) 2007 Wiley Periodicals, Inc.
Keywords: copolymerization; Ethylene; Photodegradation; polar monomers; propylene

Photo-oxidation of EPDM/layered double hydroxides composites: influence of layered hydroxides and stabilizers - Kumar, B.; Rana, S.; Singh, R. P. (Express Polymer Letters, 2007)
The photo-oxidation of ethylene propylene diene monomer (EPDM)/layered double hydroxide (LDH) composites as well as EPDM/LDH with stabilizers is studied under accelerated UV irradiation (lambda >= 290 nm) at 60 degrees C for different time intervals. The development of functional groups during oxidation was monitored by FT-IR spectroscopy. The photo-degradation of the pristine polymer and composites take place and the increase in hydroxyl and carbonyl groups with irradiation times, was estimated. EPDM filled LDH showed higher degradation rate than pristine EPDM, while in acidic medium EPDM/LDH showed almost equal degradation as in isolated conditions. These results show the advantages of LDHs as a filler as well as an acid killer. The effect of stabilizers is very less because of their concentration in comparison of LDH.
Keywords: EPDM; layered double hydroxides; Photo-oxidation; polymer composites

Photo-stabilization of EPDM-clay nanocomposites: effect of antioxidant on the preparation and durability - Lonkar, Sunil P.; Kumar, A. Pratheep; Singh, Raj Pal (Polymers for Advanced Technologies, 2007)
The present study is to examine the photo-stabilization effect of an antioxidant on the photo-oxidation of ethylene-propylene-diene monomer (EPDM)-clay nanocomposites. During the preparation of EPDM-clay nanocomposites via melt processing antioxidants are usually incorporated along with clay, which allows phenolic antioxidant molecules to get adsorbed onto acidic clay platelets and their interaction with metallic impurities reduces the stabilizing efficiency of the antioxidant. The nanocomposites were obtained by solution dispersion followed by melt compounding of EPDM and organophilic montmorillonite (OMMT). The samples were characterized by conventional tools such as X-ray diffraction (XRD), Fourier Transform Infra Red (FT-IR) spectroscopy, and thermo-gravimetric analysis (TGA). It was found, upon photo-irradiation (lambda > 290 nm) studies by following the changes in functional groups and surface morphology, that photo-degradation was lowered by the antioxidant and the efficiency of the antioxidant could be improved by initial incorporation of antioxidant in the EPDM matrix. In EPDM-clay nanocomposites, a stabilizing activity of the antioxidant was observed above some threshold concentration of the antioxidant. The relationship between the nanoclay reinforcement and stabilizing efficiency in terms of photo-oxidation and surface morphology for their applicability are discussed. The methodology adopted for this study is also justified through our observation. Copyright (C) 2007 John Wiley & Sons, Ltd.
Keywords: ethylene-propylene-diene monomer; nanocomposites photo-degradation antioxidant and stabilization

Polyethylene waxes: catalytic synthesis by ti-biphenolates - Umare, Prashant S.; Rao, Karumanchi; Tembe, Gopal L.; Dhoble, Deepa Arun; Trivedi, Bhavna (Journal of Macromolecular Science Part A‐Pure and Applied Chemistry, 2007)
{Soluble complexes of Ti (IV) bearing biphenol groups such as 1,1'-binaphthelene 2, 2' diol (Binol), 1, 1'-methylene di-2-naphthol, biphenol were prepared and characterized. These catalyst precursors formulated as [
Keywords: fibers; Nanoparticles; Self-assembly

Poly(o-anisidine) films on mild steel: electrochemical synthesis and biosensor application - Patil, Dewyani; Gaikwad, A. B.; Patil, Pradip (Journal of Physics D-Applied Physics, 2007)
Poly(o-anisidine) (POA) films were synthesized on mild steel from an aqueous oxalic acid solution by electrochemical polymerization of o-anisidine using cyclic voltammetry. These films were characterized by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The enzyme glucose oxidase (GOx) was entrapped into the POA film by a physical adsorption method. The resulting POA-GOx films were characterized by UV-visible absorption spectroscopy, FTIR and SEM. The amperometric response of the POA-GOx films was measured as a function of glucose concentration in phosphate buffer solution (pH 7.3). The POA-GOx films exhibited a fast amperometric response (1-5 s) and a linear response in the range of 2-20 mM glucose. The maximum current density and Michaelis-Menten constant of POA/GOx films were found to be similar to 406 mu A cm(-2) and 1.03 mM, respectively. The shelf stability, operational stability and thermal stability of these films were also investigated.

Poly(o-ethylaniline) coatings for stainless steel protection - Chaudhari, Sudeshna; Sainkar, S. R.; Patil, P. P. (Progress In Organic Coatings, 2007)
The poly(o-ethylaniline) coatings were electrochemically synthesized on 304-stainless steel by using cyclic voltammetry from an aqueous salicylate medium. Cyclic voltammetry, UV-vis absorption spectroscopy, Fourier transform infrared spectroscopy and scanning electron microscopy were used to characterize these coatings, which indicates that the aqueous salicylate solution is a suitable medium for the electrochemical polymerization of o-ethyaniline on 304-stainless steel. The performance of poly(o-ethylaniline) as protective coating against corrosion of 304-stainless steel in aqueous 3% NaCl was evaluated by the open circuit potential measurements, potentiodynamic polarization technique, cyclic potentiodynamic polarization measurements and electrochemical impedance spectroscopy. The results of the potentiodynamic polarization and cyclic potentiodynamic polarization demonstrate that the poly(o-ethylaniline) coating provides excellent protection to both localized and general corrosion of 304-stainless steel. The corrosion potential was about 0.190 V more positive in aqueous 3% NaCl for the poly(o-ethylaniline) coated steel than that of bare steel and reduces the corrosion rate of steel almost by a factor of 20. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Conducting polymer coatings; Corrosion resistant coatings; cyclic voltammetry; Electrochemical polymerization; poly(o-ethylaniline) coatings; stainless steel

Practical and facile approach towards indole alkaloids: (-)-mitralactonine - Chavan, Subhash P.; Sharma, Pallavi; Sivappa, Rasapalli; Kalkote, Uttam R. (Synlett, 2007)
An efficient approach to (-)-mitralactonine using Pictet-Spengler cyclisation with a highly functionalised masked aldehyde is described. Sharpless asymmetric dihydroxylation (SAD) is utilised to introduce chirality in the key substrate.
Keywords: alkaloids; asymmetric; cyclisations; dihydroxylations; thioacetats

Practical formal synthesis of camptothecin - Chavan, Subhash P.; Pathak, Ashok B.; Kalkote, Uttam R. (Tetrahedron Letter, 2007)
The synthesis of the DE ring of camptothecin using simple and inexpensive starting materials, employing an addition elimination reaction and selective esterification of an aliphatic carboxylic acid as key steps is described. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: alkaloid; Anticancer; camptothecin; Natural product

Practical formal synthesis of D-(+)-biotin from 4-formylazetidin-2-one - Kale, Ajaykumar S.; Puranik, Vedavati G.; Deshmukh, Abdul Rakeeb A. S. (Synthesis-Stuttgart, 2007)
A practical synthesis of (3S,6R)-1,3-dibenzyltetrahydro-1H-furo[3,4-d]imidazole-2,4-dione, an important intermediate in the synthesis of biotin, from 4-formyl-3-mesyloxyazetidin-2-one has been achieved. Acid-catalyzed azetidin-2-one ring opening followed by a one-pot conversion of diamine hydrochloride to a cyclic urea and hydroxymethylene to chloromethylene by triphosgene to obtain (4S,5R)-methyl-1,3-dibenzyl-5-chloromethyl-2-oxoimidazolidine-4-carboxyl ate is the key step in this synthesis.
Keywords: azetidin-2-one; beta-Lactams; cyclization; Lactone; reduction

Practical synthesis of (+/-)-venlafaxine - Chavan, Subhash P.; Khobragade, Dushant A.; Thakkar, Mahesh; Kalkote, Uttam R. (Synthetic Communications, 2007)
A practical total synthesis of antidepressant (+/-)-venlafaxine is disclosed.
Keywords: antidepressant; Grignard reaction; Michael addition

Preface: CAMURE-6 & ISMR-5 symposium in Pune, India - Chaudhari, Raghunath V.; Ranade, Vivek V. (Industrial & Engineering Chemical Research, 2007)

Preparation and evaluation of cellulose acetate butyrate and poly(ethylene oxide) blend microspheres for gastroretentive floating delivery of repaglinide - Rokhade, Ajit P.; Patil, Sangamesh A.; Belhekar, Anagha A.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2007)
In this study, hollow microspheres of cellulose acetate butyrate (CAB) and poly(ethylene oxide) (PEO) were prepared by emulsion-solvent evaporation method. Repaglinide was successfully encapsulated into floating microspheres. Various formulations were prepared by varying the ratio of CAB and PEO, drug loading and concentration of poly(vinyl alcohol) (PVA) solution. Encapsulation of the drug up to 95% was achieved. The microspheres tend to float over the simulated gastric media for more than 10 h. The micromeritic properties of microspheres reveal the excellent flow and good packing properties. The % buoyancy of microspheres was found to be up to 87. SEM showed that microspheres have many pores on their surfaces. Particle size ranges from 159 to 601 mu m. DSC and X-RD revealed the amorphous dispersion in the polymer matrix. In vitro release experiments were performed in simulated gastric fluid. In vitro release studies indicated the dependence of release rate on the extent of drug loading and the amount of PEO in the microspheres; slow release was extended up to 12 h. The release data were fitted to an empirical equation to compute the diffusional exponent (n), which indicated that the release mechanism followed the non-Fickian trend. (C) 2007 Wiley Periodicals, Inc.
Keywords: cellulose acetate butyrate; Controlled release; floating drug delivery; microspheres; repaglinide

Preparation of enantiopure trans-1,2-cyclohexanediol and trans-2-aminocyclohexanol - Chatterjee, A.; Sasikumar, M.; Joshi, Navalkishore N. (Synthetic Communications, 2007)
Trans-1,2-cyclohexanediol and trans-2-aminocycloxexanol are useful chiral auxiliaries. Simple chemical resolution procedures for these molecules are presented.
Keywords: chemical resolution; chiral auxiliaries; epoxide-cleavage

Preparation of nanocrystalline ferroelectric CaBi4Ti4O15 by citrate gel method - Murugan, A. Vadivel; Gaikwad, A. B.; Samuel, V.; Ravi, V. (Ceramics International, 2007)
A gel was formed when an aqueous solution of CaCl2, BiNO3, TiOCl2 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 700 degrees C produced nano crystallites of the ternary oxide, CaBi4Ti4O15 (CBT). The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). The room temperature dielectric constant at 1 kHz is 390. The ferroelectric hysteresis loop parameters of these samples were also studied by a home-built Sawyer-tower circuit. (c) 2006 Elsevier Ltd and Techna Group S.H. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray methods

Production and partial characterization of two types of phytase from aspergillus niger NCIM 563 under submerged fermentation conditions - Soni, Sarvesh Kumar; Khire, Jayant Malhar (World Journal of Microbiology & Biotechnology, 2007)
Novel extracellular phytase was produced by Aspergillus niger NCIM 563 under submerged fermentation conditions at 30 degrees C in medium containing dextrin and glucose as carbon sources along with sodium nitrate as nitrogen source. Maximum phytase activity (41.47 IU/mL at pH 2.5 and 10.71 IU/mL at pH 4.0) was obtained when dextrin was used as carbon source along with glucose and sodium nitrate as nitrogen source. Nearly 13 times increase in phytase activity was observed when phosphate in the form of KH2PO4 (0.004 g/100 mL) was added in the fermentation medium. Physic-chemical properties of partially purified enzyme indicate the possibility of two distinct forms of phytases, Phy I and Phy II. Optimum pH and temperature for Phy I was 2.5 and 60 degrees C while Phy II was 4.0 and 60 degrees C, respectively. Phy I was stable in the pH range 1.5-3.5 while Phy II was stable in the wider pH range, 2.0-7.0. Molecular weight of Phy I and Phy II on Sephacryl S-200 was approximately 304 kDa and 183 kDa, respectively. Phy I activity was moderately stimulated in the presence of 1 mM Mg2+, Mn2+, Ca2+ and Fe3+ ions and inhibited by Zn2+ and Cd2+ ions while Phy II activity was moderately stimulated by Fe3+ ions and was inhibited by Hg2+, Mn2+ and Zn2+ ions at 1 mM concentration in reaction mixture. The Km for Phy I and II was 3.18 and 0.514 mM while Vmax was 331.16 and 59.47 mu mols/min/mg protein, respectively.
Keywords: Aspergillus niger; Phytase; phytate degradation; Poultry feed supplement; Submerged fermentation

Propargyl 1,2-orthoesters as glycosyl donors: stereoselective synthesis of 1,2-trans glycosides and disaccharides - Sureshkumar, Gopalsamy; Hotha, Srinivas (Tetrahedron Letters, 2007)
Propargyl 1,2-orthoesters are identified as glycosyl donors. Various glycosides and disaccharides were synthesized in a stereoselective manner using AuBr3 as the promoter. AuBr3 may activate the alkyne resulting in the formation of a 1,2-dioxolenium ion and also behaves as a Lewis acid to facilitate the attack of the glycosyl acceptor. The versatility of the protocol was demonstrated using a panel of aglycones comprising aliphatic, alicyclic, steroidal and sugar alcohols. (C) 2007 Elsevier Ltd. All rights reserved.

Protecting group directed ring-closing metathesis (RCM): the first total synthesis of an anti-malarial nonenolide - Mohapatra, Debendra K.; Ramesh, Dhondi K.; Giardello, Michael A.; Chorghade, Mukund S.; Gurjar, Mukund K.; Grubbs, Robert H. (Tetrahedron Letters, 2007)
The first synthesis of a newly found naturally occurring anti-malarial nonenolide is described. A pivotal step in the synthesis is the ring-closing metathesis of a dienoic ester prepared by coupling an acid and alcohol that were stereoselectively synthesized from (S)-alpha-hydroxy-gamma-butyrolactone and 1,2-O-isopropylidene D-glyceraldchyde, respectively. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: 1; 2-O-isopropylidene; anti-malarial agent; D-glyceraldehyde; Nonenolide; Ring-closing metathesis; Yamaguchi esterification

Purification and characterization of a lectin from endophytic fungus fusarium solani having complex sugar specificity - Khan, Feroz; Ahmad, Absar; Khan, Mohammad Islam (Archives of Biochemistry and Biophysics, 2007)
A lectin from the mycelial extract of an endophytic strain of Fusarium solani was purified. Its hemagglutinating activity was inhibited by glycoproteins possessing N-linked as well as O-linked glycans. The thermodynamics and kinetics of binding of glycans and glycoproteins to F. solani lectin Was Studied using SUH ace plasmon resonance. The lectin showed high affinity for asialofetuin, asia-lofibrinogen, asialofibrinogen, and thyroglobulin: and comparatively low affinity for mucin, fetuin, fibrinogen, and holotransferrin. Glycoproteins showed glycans with significant contribution from enthalpy and positive entropy, suggesting several fold higher affinity than their corresponding g the involvement of non-polar protein-protein interaction. Moreover, the higher affinity of the glycoproteins was due to their faster association rates and low activation energy. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: endophytic fungus; Fusarium solani; Lectin; Purification; SPR; Thermodynamic properties

Purification by silica gel chromatography using dialysis tubing and characterization of sophorolipids produced from Candida bombicola grown on glucose and arachidonic acid - Shah, Sachin; Prabhune, Asmita (Biotechnology Letters, 2007)
The yeast Candida bombicola (ATCC 22214) grown on primary carbon source glucose (100 g l(-1)) and secondary carbon, arachidonic acid (2 g l(-1)) produced mixture of sophorolipids up to 1.44 g l(-1). The crude product was a heterogeneous mixture of sophorolipids, which are glycolipids of sophorose linked to the fatty acid through glycosidic bond between omega and omega-1 carbon of arachidonic acid. The derived sophorolipids were isolated by silica gel chromatography using dialysis tubing. The purified sophorolipids were characterized by ESI-MS and FT-IR. Acid hydrolysis of the resolved sophorolipids were characterized by ESI-MS for the presence of 20-hydroxy-5Z,8Z,11Z,14Z-eicosatetraenoic acid (20-HETE) and 19-hydroxy-5Z,8Z,11Z,14Z-eico-satetraenoic acid (19-HETE), compounds of pronounced pharmaceutical importance.
Keywords: 19-HETE; 20-HETE; arachidonic acid; electrospray soft ionization mass spectroscopy; silica gel chromatography; Sophorolipid

PdCl2(bipy) complex - an efficient catalyst for Heck reaction in glycol-organic biphasic medium - Jagtap, Sangeeta Vijay; Deshpande, Raj Madhukar (Catalysis Today, 2008)
The Palladium complex PdCl2(bipy) (1) was found to be efficient in catalyzing the Heck reaction of aryl halides in a biphasic system comprising ethylene glycol along with an organic solvent. A proper tailoring of the organic phase ensured that the leaching of the catalyst to the organic phase was negligible. The catalyst was active for the Heck reaction of a number of olefins, aryl halides, in presence of organic and inorganic bases. The PdCl2(bipy) catalyst was stable and could be recycled for five times without any loss in activity and selectivity. A major advantage of this work is that unlike hitherto reported biphasic systems; it does not employ a water-soluble ligand to achieve biphasic catalysis. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Biphasic catalysis; C-C coupling; Heck reaction; PdCl2(bipy) complex

Peculiarities of the adsorption kinetics of mixed convex plus concave contour objects - Shelke, Pradip B.; Ogale, S. B.; Khandkar, M. D.; Limaye, A. V. (Physical Review E, 2008)
Random sequential adsorption of mixed convex plus concave contour (MC) objects exhibits some distinctly different peculiar characteristics than the cases of purely convex objects. Though the substrate coverage approaches the jamming limit with time t as t(-p), same as that for convex objects, the law p similar to 1/d(f), valid for convex objects with d(f) degrees of freedom, does not hold for MC objects. Interestingly, for a fixed number of degrees of freedom, the exponent p changes with the degree of nonconvexity and bears a near perfect correlation with the same.

Periodic mesoporous silicas and organosilicas: an overview towards catalysis - Shylesh, S.; Samuel, Prinson P.; Sisodiya, Sheetal; Singh, A. P. (Catalysis Surveys from Asia, 2008)
Micelle-templated mesoporous and organic-inorganic hybrid mesoporous materials are important in many fields of material research, especially for hosting catalysts in confined space. Among this class, the recent discovery of periodic mesoporous organosilicas (PMOs) represent an exciting new group of organic-inorganic nanocomposites targeted for a broad range of applications ranging from catalysis to microelectronics. Compared to the earlier generation of organic-inorganic hybrid mesoporous samples, obtained by the cocondensation reaction or by the grafting reaction, PMOs represent the right combination of organic and inorganic groups in the frame wall positions. This article reviews the current state of art in organic-inorganic hybrid mesoporous material research with special emphasis over periodic mesoporous organosilica materials having various redox centers (Ti, V, Cr) suitable for oxidation reactions as well as acidic sites (Al, -SO(3)H) for the organic transformation of bulky molecules.
Keywords: Acid catalysis; epoxidation; Mesoporous organosilicas; Organic-inorganic hybrid materials

Permeabilization effect of organic solvents on cell bound penicillin v acylase activity of Erwinia aroideae (DSMZ 30186) - Kumar, Atul; Pundle, Archana (Journal of Biotechnology, 2008)

pH Induced structural alterations in an aspartic protease from Vigna radiata indicating an alkali induced molten globule state - Kulkarni, Aarohi; Gaikwad, Sushama M.; Rao, Mala (International Journal of Biological Macromolecules, 2008)
pH-dependent transitions in secondary and tertiary structure are described for a plant aspartic protease from Vigna radiata. The enzyme was pH stable with pH optima of 3.0. The Lineweaver Burk analysis at various pH yielded pK(a) values of 3.3 and 4.29 indicating acidic amino acids at the active site of the enzyme. The structural changes exemplified compact secondary structure collapsed tertiary structure and exposure of hydrophobic patches at pH 10. The changes at pH 10 are typical of a molten globule state. This alkali induced molten globule is novel since acid induced molten globule state is more reported. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Alkali induced molten globule; Plant aspartic protease; Structural transitions

Phosphotungstic acid on silica with modified acid sites as a solid catalyst for selective cleavage of tert-butyldimethylsilyl ethers - Bhure, Mahesh H.; Kumar, Indresh; Natu, Arun D.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (Catalysis Communications, 2008)
The strength and nature of acid sites of bulk phosphotungstic acid could be modified after dispersing it on silica support which was characterized by XRD, ammonia TPD and (31)P MAS NMR techniques. This solid acid catalyst was found to be highly selective for the cleavage of tert-butyldimethylsilyl ethers at room temperature. The catalyst was easily recovered by filtration and could be reused for several times without loss of any activity giving a TON of 9.5 x 10(5). (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Ammonia TPD; Catalytic cleavage; reaction pathway; solid acid; tert-butyldimethylsilyl ethers; XRD

Photocatalytic activity and characterization of sol-gel-derived Cr(III)-doped TiO(2)-coated active carbon composites - Gambhire, A. B.; Lande, Machhindra K.; Mandale, A. B.; Patil, K. R.; Arbad, B. R. (Philosophical Magazine, 2008)
Cr(III)-doped, TiO(2)-coated active carbon (Cr-TiO(2)/AC) were prepared by a sol-gel method. The effect of supports, including TiO(2) and active carbon (AC), on the molecular structure and photocatalytic activity of chromium oxide for complete decomposition of EDTA has been examined with respect to the content of Cr on the catalyst surface. The photocatalytic activity of the Cr-TiO(2)/AC composites was evaluated in the decomposition of EDTA solution under UV irradiation. The results indicate that Cr-TiO(2)/AC has a higher efficiency in decomposition of EDTA than TiO(2), TiO(2)/AC or active carbon. This was attributed to the different functions of active carbon and chromate species. (1) Nanosize TiO(2) particles on composites were not reunited, possible because active carbon retards transformation of anatase into rutile and decreases the crystallite size. (2) Production of high concentrations of organic compound near Cr-TiO(2). (3) Carbon in active carbon causes some of the TiO(2) to reduce to Ti(3+) ions, which prevents electron-hole pair recombination. (4) Formation of polychromate species, with a stronger redox capability, on the surface of TiO(2)/AC. It was found that the addition of Cr to TiO(2) sol could suppress the grain growth of TiO(2) crystals and increase the hydroxyl content on the surface of TiO(2)/AC. The photocatalytic efficiency and activity of the composites remained good, even after three cycles.
Keywords: EDTA; photoactive; sol-gel; Titanium dioxide; XPS

Photocatalytic decomposition of methylene nanocrystalline titania prepared by different blue on methods - Ramaswamy, Veda; Jagtap, Neelam; Vijayanand, S.; Bhange, Deu S.; Awati, Preeti (Materials Research Bulletin, 2008)
Nanocrystalline particles of pure anatase titania were prepared by two different methods. One is the sol-gel method at ambient temperature using ultrasonication (TiO2-SG-US) and conventional stirring method (TiO2-SG-S) and the other by surfactant assisted hydrothermal synthesis (TiO2-HT). More uniform distribution/dispersion of the nanoparticles (SEM), marginally higher surface area, better thermal stability and phase purity are some of the advantages of preparation of nanocrystalline titania by sol gel ultrasonication method and hydrothermal synthesis method. The behavior of anatase titania in photocatalytic decomposition of methylene blue in aqueous medium was studied as a function of the method of preparation and the crystallite size. The nanoparticles prepared by ultrasonication method were more effective than both, the sample prepared by conventional stirring method and commercial Degussa P-25. The higher photocatalytic activity of TiO2-SG-US is attributed to the more uniform size of the particles as compared to TiO2-SG-S samples. Both TEM and XRD data on TiO2-HT samples reveal a uniform and nanocrystalline TiO2 particles, which showed photocatalytic activity in both UV and visible region although brookite phase was also present. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; Nanostructures; Sol-gel chemistry

Physicomechanical and magnetic properties of neoprene based rubber ferrite composites - Prema, K. H.; Kurian, Philip; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Polymer-Plastics Technology and Engineering, 2008)
Fine (approximately 18nm) particles of nickel ferrite were synthesized by the sol-gel technique, and their structural properties were evaluated by X-ray diffraction. Neoprene-based rubber ferrite composites were prepared by incorporating these nickel ferrite powders in the rubber matrix according to a specific recipe. The cure characteristics were analyzed, and the samples were molded into particular shapes whose properties were determined according to ASTM standards. Magnetization studies were carried out using a Vibrating Sample Magnetometer. This study indicates that neoprene rubber-based flexible magnets with desired magnetic properties and appropriate mechanical properties can be prepared by incorporating an adequate amount of nanoscale nickel ferrite particles within the rubber matrix.
Keywords: Ferrite; ferrite composites; flexible magnets; neoprene rubber; rubber; Sol-gel method

Phytochemical constituents and pharmacological activities of calotropis procera - Qureshi, Absar A.; Qureshi, Azfar A.; Omer, Shaista; Sanghai, Dhirendra B.; Setty, S. R.; Bhajipale, N. S. (Plant Archives, 2008)
In spite of many synthetic compounds, the most efficient drugs have their origin directly or indirectly related with the plant kingdom. Many of the plant extracts have proven to posses important pharmacological actions depending upon the chemical constituents present. Calotropis procera, plant generally considered as a poisonous whereas widely used in the traditional medicinal system like Ayurveda and Unani. This plant has been reported to poses alkaloids, glycosides, flavonoids, triterpines etc in different parts and exhibit various pharmacological activities like anti-fertility, wound healing, antimalerial, antidiarrhoeal, anti-inflammatory etc. This review highlights some of the phytochemical and pharmacological aspects of Calotropis procera.
Keywords: calactin; calotoxin; Calotropis procera; pharmacological activities; phytochemical constituents; procesterol

pK(a)-Directed host-guest assemblies: rational analysis of molecular adducts of 2,4-diamino-6-methyl-1,3,5-triazine with various aliphatic dicarboxylic acids - Delori, Amit; Suresh, Eringathodi; Pedireddi, V. R. (Chemistry-A European Journal, 2008)
Molecular adducts of 2,4-diamino-6-methyl-1,3,5-triazine (1) have been prepared with various aliphatic dicarboxylic acids. The molecular complexes (1a-1i) thus formed by co-crystallizing 1 with oxalic, malonic, succinic, fumaric, acetylene dicarboxylic, glutaric, thiodiglycolic, diglycolic, and adipic acids have been found to give two types of host-guest assemblies that have voids or channels in a three-dimensional arrangement. The different types of host-guest arrangement appear to result from differences in the acidity of the dicarboxylic acids, that is, acids with pK(a) < 3.0 give host networks that consist of 1 and the corresponding acid with water or solvent molecules of crystallization present as guests, whereas acids with pK(a) > 3.0 exist as guests in voids in a host network formed by 1. The former arrangement is observed in adducts 1a, 1b, 1c, and 1h and the latter arrangement is found in adducts 1c, 1d, 1f, 1g and 1i.
Keywords: dicarboxylic acids; host-guest systems; hydrogen bonds; molecular recognition; supramolecular chemistry

Poly(4-methyl-1-pentene)/MWNT nanocomposites - Patil, Prashant A.; Wanjale, Santosh D.; Jog, Jyoti Prakash (E-Polymers, 2008)
Nanocomposites of poly(4-methyl-1-pentene) (PMP) with various weight fractions of multiwall carbon nanotubes (MWNT's) were prepared by melt compounding. The nanocomposites are characterized for structure using scanning electron microscopy. The viscoelastic behavior of the nanocomposites is investigated in solid as well as melt state. The study reveals a significant increase in storage modulus especially in the rubbery regime of the polymer matrix and reduced tan delta. Rheological properties in melt show that the complex viscosity and shear storage modulus are increased as a result of incorporation of MWNT. A systematic decrease in the cross over frequency is noted which is attributed to the increased relaxation time. In dielectric analysis, composition dependent enhanced permittivity and conductivity are observed. The thermal stability of the polymer is found to be significantly improved in presence of MWNT's.

Polymer electrolyte fuel cells using nafion-based composite membranes with functionalized carbon nanotubes - Kannan, Ramaiyan; Kakade, Bhalchandra A.; Pillai, Vijayamohanan K. (Angewandte Chemie-International Edition, 2008)
Keywords: fuel cells; membranes; nanotubes; Polymers; proton transport

Population proportion approach for ranking differentially expressed genes - Gadgil, Mugdha (BMC Bioinformatics, 2008)
Background: DNA microarrays are used to investigate differences in gene expression between two or more classes of samples. Most currently used approaches compare mean expression levels between classes and are not geared to find genes whose expression is significantly different in only a subset of samples in a class. However, biological variability can lead to situations where key genes are differentially expressed in only a subset of samples. To facilitate the identification of such genes, a new method is reported. Methods: The key difference between the Population Proportion Ranking Method (PPRM) presented here and almost all other methods currently used is in the quantification of variability. PPRM quantifies variability in terms of inter-sample ratios and can be used to calculate the relative merit of differentially expressed genes with a specified difference in expression level between at least some samples in the two classes, which at the same time have lower than a specified variability within each class. Results: PPRM is tested on simulated data and on three publicly available cancer data sets. It is compared to the t test, PPST, COPA, OS, ORT and MOST using the simulated data. Under the conditions tested, it performs as well or better than the other methods tested under low intraclass variability and better than t test, PPST, COPA and OS when a gene is differentially expressed in only a subset of samples. It performs better than ORT and MOST in recognizing non differentially expressed genes with high variability in expression levels across all samples. For biological data, the success of predictor genes identified in appropriately classifying an independent sample is reported.

Potential plasmid-curing agent, 8-epidiosbulbin E acetate, from dioscorea bulbifera L. against multidrug-resistant bacteria - Shriram, Varsha; Jahagirdar, Sheetal S.; Latha, C.; Kumar, Vinay; Puranik, Vedavati G.; Rojatkar, Supada; Dhakephalkar, Prashant K.; Shitole, M. G. (International Journal of Antimicrobial Agents, 2008)
Bioassay-guided fractionation of an aqueous methanolic extract of Dioscorea bulbifera L. bulbs was performed using organic solvents. A novel plasmid-curing compound was identified as 8-epidiosbulbin E acetate (EEA) (norditerpene) on the basis of modern spectroscopic analysis and X-ray crystallography. EEA exhibited broad-spectrum plasmid-curing activity against multidrug-resistant (MDR) bacteria, including vancomycin-resistant enterococci. EEA cured antibiotic resistance plasmids (R-plasmids) from clinical isolates of Enterococcus faecalis, Escherichia coli, Shigella sonnei and Pseudomonas aeruginosa with 12-48% curing efficiency. The reference plasmids of Bacillus subtilis (pUB110), E. coli (RP4), P. aeruginosa (RIP64) and Salmonella typhi (R136) were cured with efficiency ranging from 16% to 64%. EEA-mediated R-plasmid curing decreased the minimal inhibitory concentration of antibiotics against MDR bacteria, thus making antibiotic treatment more effective. The antibiotic resistance pattern revealed that the compound was effective in the reversal of bacterial resistance to various antibiotics. In addition, the compound did not show any cytotoxicity against a broad range of human cancer cell lines, namely MCF-7 (breast cancer), SiHa (cervical cancer) and A431 (epidermal carcinoma), and hence has the potential to be used as a lead compound for drug discovery programmes. (C) 2008 Elsevier B. V. and the International Society of Chemotherapy. All rights reserved.
Keywords: 8-Epidiosbulbin E acetate; Antibiotic resistance; Dioscorea bulbifera; Plasmid curing

Practical syntheses of 4-fluoroprolines - Chorghade, Mukund S.; Mohapatra, Debendra K.; Sahoo, Gokarneswar; Gurjar, Mukund K.; Mandlecha, Manish V.; Bhoite, Nitin; Moghe, Santosh; Raines, Ronald T. (Journal of Fluorine Chemistry, 2008)
4-Fluoroprolines are among the most useful nonnatural amino acids in chemical biology. Here, practical routes are reported for the synthesis of the 2S, 4R, 2S, 4S, and 2R,4S diastereomers of 4-fluoroproline. Each route starts with (2S,4R)-4-hydroxyproline, which is a prevalent component of collagen and hence readily available, and uses a fluoride salt to install the fluoro group. Hence, the routes provide process-scale access to these useful nonnatural amino acids. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: 4-Fluoroproline; 4-Hydroxyproline; collagen; Nonnatural amino acid; Process-scale synthesis

Pre-organization-mediated macrocylization: efficient synthesis and structural investigations of BINOL-m-phenylenediamine-derived macrocycles - Srinivas, Deekonda; Gonnade, Rajesh G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2008)
This letter describes a serendipitous discovery of an efficient synthetic route to BINOL-m-phenylenediamine-derived macrocycles. These macrocycles are quickly accessible in an one-pot procedure by the direct condensation of (R) and (S) BINOL bis-acids with suitably substituted m-phenylenediamine analogs. Structural investigations by single crystal X-ray crystallography and solution-state NMR studies provided convincing evidence of their intramolecular hydrogen bonding arrangement and rigid structural architecture. The striking feature of these macrocycles is their ready accessibility in optically pure form coupled with their ease of synthesis. (C) 2008 Elsevier Ltd. All rights reserved.

Preparation and characterization of electrospun fibers of nylon 11 - Dhanalakshmi, M.; Jog, Jyoti Prakash (Express Polymer Letters, 2008)
Nylon 11 nanofibers mats were successfully prepared by electrospinning process from formic acid solution. The scanning electron microscopy (SEM) images showed that nanofibers with uniform diameter were produced when the polymer concentration was 10% w/v, whereas ribbons were formed at a higher concentration. The crystalline structure of the nanofibers mats was investigated using X-ray diffraction (XRD) and it was found that the nanofibers mats crystallized in gamma form. The melt crystallized as well as solution casted films however exhibited a form. The thermal properties of these samples were studied using differential scanning calorimetry (DSC) and it was observed that electrospun fibers showed higher crystallinity than the melt-crystallized samples. However, the crystallinity of electrospun fibers was lower than the solution-crystallized sample.
Keywords: biocompatible polymers; electrospinning; Nanomaterials; Nylon 11

Preparation and characterization of novel hybrid of chitosan-g-PDMS and sodium montmorrilonite - Depan, Dilip; Kumar, Bijandra; Singh, Raj Pal (Journal of Biomedical Materials Research Part B-Applied Biomaterials, 2008)
Preparation and properties of Chitosan (CS)-clay nanocomposites grafted with polydimethyl siloxane (PDMS) with different clay ratios are herein discussed. CS is intercalated into sodium montmorrilonite and PDMS is grafted onto CS under UV irradiation. Sample films of CS intercalated into clay and grafted with PDMS were prepared by solvent casting method with varying amount of nanoclay and PDMS. They were characterized by conventional techniques such as X-ray diffractometry, fourier transform infrared spectroscopy, C-13 NMR, thermo gravimetric analysis, and differential thermal analysis. Sorption behavior of samples has been followed by measuring swelling degree and issues on the interactions of biopolymers with clay are also discussed. The water absorption of composites films reduces with an increase in the amount of incorporated clay. This is due to the barrier formation in the form of cross-linking points, which prevents water permeation into CS. The amount of adsorbed water is more, when the amount of CS exceeds the amount of PDMS. This shows high water retention capacity of CS. (c) 2007 Wiley Periodicals, Inc.
Keywords: Chitosan; graft copolymerization; Nanocomposites; PDMS; water absorption

Preparation and electrochemical characterization of lithium cobalt oxide nanoparticles by modified sol-gel method - Khomane, Ramdas B.; Agrawal, Amit C.; Kulkarni, B. D.; Gopukumar, S.; Sivashanmugam, A. (Materials Research Bulletin, 2008)
Uniformly distributed nanoparticles of LiCoO2 have been synthesized through the simple sol-gel method in presence of neutral surfactant (Tween-80). The powders were characterized by X-ray diffractometry, transmission electron microscopy and electrochemical method including charge-discharge cycling performance. The powder calcined at a temperature of 900 degrees C for 5 h shows pure phase layered LiCoO2. The results show that the particle size is reduced in presence of surfactant as compared to normal sol-gel method. Also, the sample prepared in presence of surfactant and calcined at 900 degrees C for 5 h shows the highest initial discharge capacity (106 mAh g(-1)) with good cycling stability as compared to the sample prepared without surfactant which shows the specific discharge capacity of 50 mAh g(-1). (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Electrochemical properties; intercalation reactions; Layered compounds; Sol-gel chemistry; X-ray diffraction

Preparation of ferroelectric CaBi(4)Ti(4)O(15) powders from novel hydroxide precursors - Deshmukh, Rupali G.; Vaishampayan, Mukta V.; Darshane, Sonali L.; Mulla, Imtiaz S.; Gaikwad, A. B.; Rao, N. Kotaserwara; Ravi, V. (Materials Letters, 2008)
Ferroelectric CaBi(4)Ti(4)O(15) (CBT) powders were prepared for the first time from their respective hydroxides. Commercially purchased Ca(OH)(2) is mixed thoroughly with freshly prepared Bi(OH)(3) and Ti(OH)(4) in stoichiometrie ratio and heated at different temperatures ranging from 100 to 600 degrees C. The CBT phase found to be formed at 500 degrees C by the X-ray diffraction studies. This is the lowest temperature so far reported in the literature for the formation of CBT phase. The advantage of this method is that it also avoids the formation of calcium carbonate phase during synthesis. The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD) method. The average particle size and morphology were studied by scanning electron microscopy (SEM) technique. (c) 2007 Elsevier B.V All rights reserved.
Keywords: CaBi(4)Ti(4)O(15); Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray methods

Presence of a functional nitrate assimilation pathway in mycobacterium smegmatis - Khan, Arshad; Akhtar, Shamim; Ahmad, Jawid N.; Sarkar, Dhiman (Microbial Pathogenesis, 2008)
Ability of Mycobacterium smegmatis to assimilate nitrate was evaluated in its active and dormant phase. Nitrate (10 mM), nitrite (0.5 mM) and ammonia (10 mM)allowed growth of M. smegmatis concomitant with their complete depletion from the culture in 144, 120 and 96 h, respectively, when used as sole nitrogen Source. Azide (50 mu M) stopped the growth of M. smegmatis when nitrate was used as sole nitrogen source. L-methionine-S-sulfoximine (L-MSO), which is a well-known inhibitor of glutamine synthetase, an enzyme also involved in nitrogen metabolic pathway, when applied at 10 mu g/ml concentration, completely inhibited the growth of the organism when nitrate or nitrite was used as sole nitrogen source. There was no effect of either azide or L-MSO at above concentrations on the growth of the organism when asparagine or ammonia was used as sole nitrogen source. More significantly, utilization of nitrate, nitrite and ammonia continued even in oxygen depletion induced dormant culture at the rates of 289, 25 and 354 mu M/day, respectively. These rates were 5-8 times slower than the rates of 1966, 127 and 2890 mu M/day, respectively, in active replicating phase. In the presence of azide (50 mu M) and L-MSO (10 mu g/ml), 2.1 and 1.51 logs reduction in viability of dormant M. smegmatis was observed using nitrate and nitrite, respectively, as sole nitrogen source. Altogether, the results indicated the presence of nitrate assimilation pathway operating in both active and dormant stage of M. smegmatis. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Dormant bacilli; Glutamine synthetase; L-methionine-S-sulfoximine; Mycobacterium smegmatis; Nitrate assimilation

Production and single step purification of cyclodextrin glycosyltransferase from alkalophilic bacillus firmus by ion exchange chromatography - Savergave, Laman S.; Mule, Santosh S.; Jogdand, Vitthal V.; Nene, Sanjay N.; Gadre, Ramchandra V. (Biochemical Engineering Journal, 2008)
Production and purification of starch digesting cyclodextrin glycosyl transferase (CGTase) from alkalophilic Bacillus firmus was investigated. Fermentation was carried out in 141 bioreactor at 28 degrees C using a medium containing dextrin, yeast extract, peptone, (NH4)H2PO4 and MgSO4.7H(2)O. The extracellular enzyme was concentrated by tangential flow ultrafiltration. The concentrated enzyme was chromatographed using DEAE-sepharose and phenyl sepharose. DEAE-sepharose could be used to purify CGTase in a single step with 23.1 fold purification and 80.6% recovery. The enzyme obtained had homogeneity and the molecular weight was 76 kDa confirmed by SDS-PAGE. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: alkalophilic; Bacillus firmus; CGTase; cyclodextrin; Purification

Protection of oligo deoxynucleotides against nuclease degradation through association with self-assembling peptides - Wang, M.; Adikane, H. V.; Duhamel, J.; Chen, P. (Biomaterials, 2008)
Aggregates of the self-assembling peptide EAK16II or EAK16IV and oligodeoxynucleotides (ODNs) were prepared, and their stability upon diluting the solution was investigated by UV-vis spectroscopy. The aggregates prepared at pH 4 and pH 7 did not dissociate after the solution was diluted 5- and 10-fold. The resistance against Escherichia coli exonuclease I of the ODN located in the EAK-ODN aggregates was studied by fluorescence resonance energy transfer (FRET) after the ODN had aggregated with EAK 16II or EAK 16IV at pH 4 or pH 7. The effect that the peptide sequence, peptide concentration, pH, and centrifugation had on protecting the aggregated ODN against nuclease degradation was investigated. Significant nuclease resistance was obtained after the EAK-ODN aggregates had been prepared at pH 4, with an EAK16IV concentration greater than a threshold value, and ensuring that the solution was not centrifuged immediately after sample preparation. Centrifuging the EAK16IV-ODN solution immediately after sample preparation resulted in the loss of this nuclease protection. However, if the solution of EAK-ODN aggregates was centrifuged 24h after sample preparation, the nuclease protection afforded by the EAK16IV-ODN aggregates to the ODN was maintained even after being subject to a 10-fold dilution and up to 4 rounds of centrifugation over 4 days. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: aggregate; centrifugation; Fluorescence resonance energy transfer (FRET); nuclease resistance; oligonucleotide; self-assembling peptide

Purification and characterization of a T-antigen specific lectin from the coelomic fluid of a marine invertebrate, sea cucumber (Holothuria scabra) - Gowda, Nagaraj M.; Goswami, Usha; Khan, Mohammad Islam (Fish & Shellfish Immunology, 2008)
A novel lectin was purified from the coelomic fluid of the sea cucumber Holothuria scabra (HSL), subjected to bacterial challenge. HSL is a monomeric glycoprotein of molecular mass 182 kDa. The lectin is highly thermostable as it retains full activity for 1 h at 80 degrees C. Further, the hemagglutination activity of HSL is unaffected by pH in the range 2-11. Unlike other lectins purified from marine invertebrates, the hemagglutination activity of HSL does not require any divalent metal ions. The affinity profile of HSL was studied by a combination of hemagglutination inhibition and fluorescence spectroscopy. HSL binds to desialylated glycoproteins, Me alpha Gal, T-antigen and T (alpha-ser)-antigen with a distinction between beta 1-4 and beta 1-3 linkages. Me alpha-T-antigen was a potent ligand having highest affinity (K-a 8.32 x 10(7) M-1). Monosaccharide binding is enthalphically driven while disaccharide binding involves both entropic and enthalpic contributions. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Fluorescence spectroscopy; Holothuria scabra; Lectin; marine invertebrate; Thermodynamic properties

Parametric dependence studies on cracking of clay - Pasricha, Kanika; Wad, Uday; Pasricha, Renu; Ogale, Satishchandra (Physica A-Statistical Mechanics and its Applications, 2009)
We have studied the shrinkage-crack patterns formed in the process of drying of clay/water slurries employing simple laboratory experiments. Both isotropic and directional drying was studied. The objective has been to examine the correlation between the solvent, materials parameters and the crack patterns. Attempt is made to fit the observations to specific models. The dynamics of the pattern formation process and the geometric properties of the crack patterns are found to be in conformity with the hydrodynamic model by Lee and Routh [W.P. Lee, A.F. Routh, Langmuir 20 (2004) 9887]. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: clay; Cracks pattern; Hydrodynamic model

Pd(II)-mediated alkynediol spiroketalization: first total synthesis of (-)-cephalosporolide E and (+)-cephalosporolide F - Ramana, C. V.; Suryawanshi, Sharad B.; Gonnade, Rajesh G. (Journal of Organic Chemistry, 2009)
Herein we describe a concise assembly of the central 1.6-dioxaspiro[4.4]nonane core of cephalosporolides E/F by employing a Pd-mediated alkynediol cycloisomerization and their total synthesis. On the basis of spectroscopic data and optical rotation values, the absolute configurations of cephalosporolides E/F were proposed.

Pd-mediated intramolecular ketalization of alkynediols: construction of the central [3.2.1]-bicyclic ketal core of cyclodidemniserinol trisulfate - Ramana, C. V.; Mallik, Rosy; Sahoo, Gokarneswar (Tetrahedron Letters, 2009)
A preliminary study dealing with the Pd-mediated alkynediol cycloisomerization to construct the central bicyclic ketal core of cyclodidemniserinol trisulfate is documented. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Alkynol cycloisomerization; Bridged bicyclic ketal; Cyclodidemniserinol trisulfate; Yamaguchi oxirane-alkyne coupling

Phase behavior of hydrogenation of 2-tert-butylphenol over a charcoal-supported rhodium catalyst in carbon dioxide solvent - Hiyoshi, Norihito; Masuda, Yoshio; Sato, Osamu; Yamaguchi, Aritomo; Rode, Chandrashekhar V.; Shirai, Masayuki (Journal of Chemical and Engineering Data, 2009)
Catalytic hydrogenation of 2-tert-butyl phenol over a charcoal-supported rhodium catalyst in carbon dioxide solvent at 313 K was studied in a batch reactor. To elucidate the effect of carbon dioxide pressure on the initial rate of reaction, the phase behavior of the ternary (2-tert-butylphenol-carbon dioxide-hydrogen) system was separately observed with a view cell, and the calculations of vapor-liquid equilibrium and compositions in the vapor and liquid phases inside the reactor were carried out using the Peng-Robinson equation of state. The hydrogenation behavior in the carbon dioxide solvent is discussed based on the phase behavior of the ternary system.

Photocatalytic mineralization of benzene over gold containing titania nanotubes: role of adsorbed water and nanosize gold crystallites - Awate, S. V.; Sahu, R. K.; Kadgaonkar, Mahesh D.; Kumar, R.; Gupta, N. M. (Catalysis Today, 2009)
Well aligned titania nanotubes, with surface area of similar to 150 m(2) g(-1) and average pore diameter of similar to 5 nm, have been synthesized by subjecting a mesoporous TiO(2) sample to alkaline treatment followed by calcination at different temperatures. Composite catalysts with gold particles dispersed in these nanotubes were also synthesized and their structural, morphological, optical and photocatalytic properties were examined. The catalytic activity of TiO(2) for UV-mediated photo-oxidation of benzene was found to be affected by several factors, such as the sample texture. presence of adsorbed water and gold crystallites. The overall conversion of benzene to form CO(2) followed a trend: Au/nanotube > TiO(2) nanotubes > mesoporous TiO(2). In situ IR spectroscopy revealed that the adsorption and reaction of benzene molecules gave rise to formation of certain phenolic species over TiO(2), while the temperature-programmed desorption (TPD) study showed that the Au/TiO(2) interfaces serve as distinct sites for the adsorption and activation of oxygen molecules. It is suggested that certain hydroxyl and oxygen ion radicals produced under UV-irradiation may promote the deep oxidation of surface phenolic species and phenoxyl (ArO center dot) type transient radicals. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Benzene degradation; Gold containing; Photocatalyst; Role of adsorbed water; TiO(2) nanotubes; Transient species

Photodegradation of EPDM/MWCNT nanocomposites: effect of singlet oxygen - Kumar, Bijandra; Kumar, Indresh; Singh, R. P. (Polymer Composites, 2009)
The photo-oxidation of ethylene propylene diene monomer (EPDM)/multiwall carbon nanotubes (MWCNT) nanocomposites has been studied under accelerated UV-irradiation (lambda >= 290 nm) in the presence of singlet oxygen. The rate of photodegradation of EPDM/MWCNT is found to be higher when compared to the pristine polymer in presence of singlet oxygen. The enhancement of the rate of degradation of composite has been described through [2 + 2] photocycloaddition reaction between singlet oxygen and double bonds on composite which is followed by cleavage. The rate of degradation and the formation of new functional groups on the composite has been monitored by FTIR spectroscopy and found to be increased with irradiation time. The changes in surface morphology have been studied by scanning electron microscope. Differential scanning calorimetry measurements revealed an increase in the glass transition temperature of photodegraded EPDM and EPDM/MWCNT nanocomposites. POLYM. COMPOS., 30:855-860, 2009. (C) 2008 Society of Plastics Engineers

Photoluminescence and gas sensing study of nanostructured pure and Sn doped ZnO - Navale, Shalaka C.; Mulla, Imtiaz S. (Materials Science & Engineering C-Biomimetic and Supramolecular Systems, 2009)
The nanostructured pure and Sn doped ZnO have been synthesized by the thermal evaporation technique. The influence of Sri oil the morphology and structure is investigated by using scanning electron microscopy (SEM), X-ray diffraction (XRD) and energy dispersive X-ray (EDX) analysis techniques, The SEM images indicate change in the growth pattern from nanowires of pure ZnO to tetrapods for Sn doped ZnO. Pure ZnO nanowires exhibit selective response towards acetone vapors while on Sri doping the response decreases. The non-stiochiometry and the morphology of ZnO arc probably responsible for such a difference in gas response. However increase in temperature doesn't improve the sensing behavior. The photoluminescence (PL) Studies reveal UV emission in pure ZnO which shifts to green emission oil doping of Sri. All rights reserved. (C) 2008 Elsevier B V. All rights reserved.
Keywords: Acetone; Gas sensors; Sn doped ZnO

Photophysical investigation into the self-organization in pyrene-based urethane methacrylate comb polymer - Deepak, V. D.; Asha, S. K. (Journal of Physical Chemistry B, 2009)
A side chain urethane methacrylate polymer with pendant pyrene units was synthesized and investigated for its self-organizing process in solution by UV-vis and fluorescence spectra and in film by scanning electron microscopy (SEM), transmission electron microscopy (TEM), and fluorescence microscopy. The polymer exhibited excimer emission centered at 476 nm, even at very dilute concentrations (10(-6) M) as a consequence of the polymer design with pendant pyrene units on every side chain. A change in aggregation pattern was observed upon increasing the concentration to 10(-4) M. New red-shifted peaks appeared in the UV-vis absorption spectra and the I(E)/I(M) ratio, and the peak I/peak III ratio showed a break around 10(-4) M, suggesting formation of stable ground state aggregates. This was further confirmed by the SEM, TEM, AFM and fluorescence microscope studies, which showed the formation of vesicles in THF and giant spherical aggregates in THF/H(2)O. The change in pattern of aggregate formation with concentration also coincided with a sudden increase in the intensity of the hydrogen bonded urethane N-H peak with concentration as recorded by solution FT-IR studies in THF.

Phylogenetic analysis, homology modelling, molecular dynamics and docking studies of caffeoyl-CoA-O- methyl transferase (CCoAOMT 1 and 2) isoforms isolated from subabul (Leucaena leucocephala) - Pagadala, Nataraj Sekhar; Arha, Manish; Reddy, P. S.; Kumar, Ranadheer; Sirisha, V. L.; Prashant, S.; Reddy, K. Janardhan; Khan, Bashir Mohammad; Rawal, S. K.; Kishor, P. B. Kavi (Journal of Molecular Modeling, 2009)
Caffeoyl coenzyme A O-methyltransferase (CCoAOMT) is an important enzyme that participates in lignin biosynthesis especially in the formation of cell wall ferulic esters of plants. It plays a pivotal role in the methylation of the 3-hydroxyl group of caffeoyl CoA. Two cDNA clones that code CCoAOMT were isolated earlier from subabul and in the present study; 3D models of CCoAOMT1 and CCoAOMT2 enzymes were built using the MODELLER7v7 software to find out the substrate binding sites. These two proteins differed only in two amino acids and may have little or no functional redundancy. Refined models of the proteins were obtained after energy minimization and molecular dynamics in a solvated water layer. The models were further assessed by PROCHECK, WHATCHECK, Verify_3D and ERRAT programs and the results indicated that these models are reliable for further active site and docking analysis. The refined models showed that the two proteins have 9 and 10 alpha-helices, 6 and 7 beta-sheets respectively. The models were used for docking the substrates CoA, SAM, SAH, caffeoyl CoA, feruloyl CoA, 5-hydroxy feruloyl CoA and sinapyl CoA which showed that CoA and caffeoyl CoA are binding with high affinity with the enzymes in the presence and absence of SAM. It appears therefore that caffeoyl CoA is the substrate for both the isoenzymes. The results also indicated that CoA and caffeoyl CoA are binding with higher affinity to CCoAOMT2 than CCoAOMT1. Therefore, CCoAOMT2 conformation is thought to be the active form that exists in subabul. Docking studies indicated that conserved active site residues Met58, Thr60, Val63, Glu82, Gly84, Ser90, Asp160, Asp162, Thr169, Asn191 and Arg203 in CCoAOMT1 and CCoAOMT2 enzymes create the positive charge to balance the negatively charged caffeoyl CoA and play an important role in maintaining a functional conformation and are directly involved in donor-substrate binding.
Keywords: Caffeoyl-CoA 3-O-methyl transferase; docking; Modelling; S-adenosyl homocysteine

Physical test of a particle simulation model in a sheared granular system - Rycroft, Chris H.; Orpe, Ashish V.; Kudrolli, Arshad (Physical Review E, 2009)
We report a detailed comparison of a slow gravity-driven sheared granular flow with a discrete-element simulation performed in the same geometry. In the experiments, grains flow inside a silo with a rectangular cross section and are sheared by a rough boundary on one side and smooth boundaries on the other sides. Individual grain position and motion are measured using a particle index-matching imaging technique where a fluorescent dye is added to the interstitial liquid which has the same refractive index as the glass beads. The simulations use a Cundall-Strack contact model between the grains using contact parameters that have been used in many other previous studies and ignore the hydrodynamic effects of the interstitial liquid. Computations are performed to understand the effect of particle coefficient of friction, elasticity, contact model, and polydispersity on mean flow properties. We then perform a detailed comparison of the particle fluctuation properties as measured by the displacement probability distribution function and the mean square displacement. All in all, our study suggests a high level of quantitative agreement between the simulations and experiments.

Physico-chemical, photo-catalytic and O-2-adsorption properties of TiO2 nanotubes coated with gold nanoparticles - Malwadkar, Sachin S.; Gholap, Ramkrishna S.; Awate, Shobhana V.; Korake, Prakash V.; Chaskar, Manohar G.; Gupta, Narendra M. (Journal of Photochemistry and Photobiology A-Chemistry, 2009)
Gold-containing titania nanotubes (Au/NT) were found to display higher activity for photooxidation of acetaldehyde, as compared to corresponding gold-free nanotubes and also a Degussa P-25 catalyst. Besides CO2 as a major reaction product, small amounts of H-2, CH4, CO, H2O and CH3COOH were also formed, irrespective of the catalyst employed. High-resolution TEM examination showed that most of the gold particles in Au/NT were of 1.5-5 nm size, distributed both within and at outside surface of the nanotubes. Some larger size (10-70 run) clusters were also seen at the external surfaces, particularly in the samples calcined at an elevated temperature. The temperature-programmed desorption measurements revealed that, compared to P-25 TiO2, a significant entrapment of O-2 occurred at two distinct tubular sites of NT samples, corresponding activation energy of desorption (E,) being around 36 and 41 kcal mol(-1). On the other hand, gold nanoparticles in Au/NT served as independent low-energy (E-a = 26 kcal mol(-1)) sites for adsorption/activation of O-2. These adsorptive properties of TiO2 and Au were lost completely on calcination, thus revealing a crucial role played by the particle size. In situ IR spectroscopy results showed that room-temperature exposure to acetaldehyde + air gave rise to a molecularly bound state, i.e. CH3CHOad, over both NT and Au/NTsamples, which in turn transformed quickly to yield certain acetate (CH3COOad-) and formate (HCOOad-) type transient species with the involvement of the surface OH groups. The decomposition and oxidation of these surface species with the help of O-2(-), O-ad and hydroxyl ion radicals (OH-) formed at photo-excited Au/NT interfaces led to the reaction products mentioned above. We conclude that, besides electron-hole charge separation, the adsorptive properties of host matrix and nanosize gold may together play a significant role in deciding the photo-catalytic properties of Au/TiO2. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Acetaldehyde oxidation; Gold co-catalyst; O-2-adsorption; Photo-catalytic activity; TiO2 nanotubes

Pilot plant study of recovery of lactic acid from ethyl lactate - Barve, Prashant P.; Rahman, Imran; Kulkarni, Bhaskar D. (Organic Process Research & Development, 2009)
Purified lactic acid is used for production of biodegradable polymer. Esterification with ethanol and subsequent hydrolysis in distillation columns to produce purified lactic acid without catalyst has obvious advantages. In this paper, we present a pilot-plant study of ethyl lactate hydrolysis to produce 3.86 kg/h lactic acid (99.85% purity) using three distillation columns. Simulation of distillation columns at steady state has been carried out, and the results obtained tally with the experimental results of the pilot plant.

Poly(amide-imide)-silica gel hybrids: synthesis and characterization - Avadhani, C. V.; Chujo, Y. (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2009)
{Several poly(amide-imide)-silica gel hybrids containing metal salts were prepared by the sol-gel reaction. Poly(amide-imide)s were prepared by low temperature polycondensation reaction of trimellitic anhydride (TMA) and diisocyanates [
Keywords: 2; 4-diphenyl thiophene; 5-Bis(4-carboxymethylene phenyl) 3; poly(amide-hydrazide)s; Thermal properties; Yamazaki's phosphorylation polycondensation

Polybenzimidazoles tethered with N-Phenyl 1,2,4-triazole units as polymer electrolytes for fuel cells - Potrekar, R. A.; Kulkarni, M. P.; Kulkarni, R. A.; Vernekar, S. P. (Journal of Polymer Science Part A-Polymer Chemistry, 2009)
Polybenzimidazole (PBI) polymers tethered with N-phenyl 1,2,4-triazole (NPT) groups were prepared from a newly synthesized aromatic diacid, 3'-(4-phenyl-4H-1,2,4-triazole-3,5-diyl) dibenzoic acid (PTDBA). The obtained polymers show superior thermal and chemical stability and good solubility in many aprotic solvents. The inherent viscosities of all polymers were around 1 dL/g. They exhibit high thermal stability with initial decomposition temperature ranging from 515 to 530 degrees C, high glass transition temperature ranging from 375 to 410 degrees C, and good mechanical properties with tensile stress in the range of 66-98 MPa and modulus 1897-2600 MPa. XRD analysis indicates that these polymers are amorphous in nature. PhysicochemiCal properties such as water and phosphoric acid-uptake, oxidative stability, and proton conductivity of membranes of these polymers have also been determined. The proton conductivity ranged from 4.7 x 10(-3) to 1.8 x 10(-2) S cm(-1) at 175 degrees C in dry conditions. (C) 2009 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 47: 2289-2303, 2009
Keywords: fuel cells; Polybenzimidazole; synthesis and characterization; Triazole

Polyimides based on aromatic diisocyanates containing pendent flexible alkoxy chains and aromatic dianhydrides: synthesis, characterization, and liquid-crystal alignment properties - Sarkar, Anjana; Halhalli, Mahadeo R.; Kulkarni, Arun D.; Wadgaonkar, Prakash P. (Journal of Applied Polymer Science, 2009)
Four new aromatic diisocyanates containing pendent flexible alkoxy chains, namely, 5-butyloxy-1,3-phenylenediisocyanate, 5-octyloxy-1,3-phenylenediisocyanate, 5-dodecyloxy-1,3-phenylenediisocyanate, and 5-hexadecyloxy-1,3-phenylenediisocyanate, were synthesized by Curtius rearrangement of the corresponding 5-alkoxy-1,3-phenylene diacylazides. These diisocyanates were each polycondensed with three commercially available aromatic dianhydrides: 4,4'-oxydiphthalic anhydride, 3,3',4,4'-(hexafluoroisopropylidene) diphthalic anhydride, and 3,3',4,4'-benzophenonetetracarboxylic dianhydride-in benzonitrile in the presence of 1,4-dizabicyclo[2.2.2]octane as a catalyst to obtain a series of polyimides with inherent viscosities in the range 0.16-0.43 dL/g. Except for 3,3',4, 4'-benzophenonetetracarboxylic dianhydride based polyimides, all of the polyimides were found to be soluble in dichloromethane, m-cresol, 1-methyl-2-pyrrolidinone, tetra-chloroethane, and pyridine either at room temperature or on heating and could be cast into tough, flexible, transparent films from a solution in in-cresol or tetra chloroethane. X-ray diffractograms revealed that the polyimides with longer alkoxy chains had layered structures. The glass-transition temperature of the polyimides containing pendent flexible alkoxy chains were in the range 159-246 degrees C as measured by differential scanning calorimetry. The temperature for the 10% weight loss of the polyimides was in the range 410-460 degrees C in a nitrogen atmosphere, which indicated good thermal stability. A pretilt angle of 2.97 degrees was observed for the polyimide derived from 5-octyloxy-1,, 3-phenylenediisocyanate and 4,4'-oxydiphthalic anhydride. (c) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 112: 461-472, 2009
Keywords: High performance polymers; polyimides; Thermal properties

Polymer crystallization in the presence of ``sticky'' additives - Dasmahapatra, Ashok Kumar; Nanavati, Hemant; Kumaraswamy, Guruswamy (Journal of Chemical Physics, 2009)
The effect of ``sticky'' additives (viz., those that have attractive interactions with the polymer) on polymer crystallization, has been investigated by dynamic Monte Carlo (DMC) simulations. Additive-polymer attractive interactions result in a slowing down of the polymer chain diffusivity in the melt state. Our results show that with increasing additive stickiness, polymer crystallinity decreases monotonically, and thinner crystallites form, viz., crystallization is inhibited by the presence of sticky additives. Unusually, the observed ``specific heat'' peak at the phase transition shows nonmonotonic behavior with additive stickiness, and exhibits a maximum for intermediate values of additive stickiness. While the origins of this unexpected behavior are not clear, we show that it correlates with a large interchange between crystalline and amorphous states of the monomers, in the vicinity of the additives. At this intermediate additive stickiness, we also find that crystallization follows a qualitatively different route-crystallinity shows a non-Avrami-like evolution, unlike the case at low or high additive stickiness.
Keywords: Additives; amorphous state; crystallisation; crystallites; Diffusion; Monte Carlo methods; polymer melts

Polymer-embedded stannic oxide nanoparticles as humidity sensors - Hatamie, Shadie; Dhas, Vivek V.; Kale, B. B.; Mulla, Imtiaz S.; Kale, Sangeeta N. (Materials Science & Engineering C-Biomimetic and Supramolecular Systems, 2009)
Stannic oxide (SnO(2)) nanoparticles have been suspended in polyvinyl alcohol (PVA) matrix in different PVA: SnO(2) molar ratios ranging from 1:1 to 1:5 using simple chemical route. This suspension was deposited on ceramic substrate and upon drying was carefully detached from the substrate. SnO(2)-embedded self-standing, transparent and flexible thin films were hence synthesized. Transmission electron microscopy (TEM) and Xray diffraction (XRD) techniques show the rutile tetragonal structure of SnO(2) with particle size similar to 5 nm. UV-Visible spectroscopy demonstrates the band gap of 3.9 eV, which does not alter when embedded in polymer. Fourier transform infrared spectroscopy (FTIR) reveals that the properties of SnO(2) do not modify due to incorporation in the PVA matrix. The structures work as excellent humidity sensors at room temperature. For a critical PVA:SnO(2) molar ratio of 1:3, the resistance changes to five times of magnitude in 92% humidity within fraction of second when compared with resistance at 11% humidity. The sample regains its original resistance almost instantaneously after being removed from humid chamber. Nanodimensions of SnO(2) particles and percolation mechanism related to transport through polymer matrix and water molecule as a carrier has been used to understand the mechanism. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: humidity sensor; Nanoparticles; Polymer; Stannic oxide

Polymeric ladderphanes - Chou, Chih-Ming; Lee, Shern-Long; Chen, Chih-Hsien; Biju, Akkattu T.; Wang, Hsian-Wen; Wu, Yi-Lin; Zhang, Guo-Fu; Yang, Kuang-Wei; Lim, Tsong-Shin; Huang, Min-Jie; Tsai, Po-Yu; Lin, Kin-Chuan; et al. (Journal of the American Chemical Society, 2009)
A new class of polymers, which have a double-stranded polybinorbornene skeleton with multilayer planar oligoaryl linkers, defined as polymeric ladderphanes, are synthesized. The structures of these ladderphanes are determined by spectroscopic means. Photophysical studies and time-resolved fluorescence spectroscopic investigations reveal that there is a strong interaction between the chromophore linkers. Thus, Soret band splitting in the absorption spectrum of the polymer with porphyrin linker (12e), significant fluorescence quenching with oligoaryl linkers (12b−d), and excimer emission with a terphenylene-diethynylene linker (12a) are characteristic photophysical properties of these polymers. Scanning tunneling microscopy shows that polymers 12b and d exhibit a ladder-like morphology and form a supramolecular assembly leading to a two-dimensional ordered array on a highly oriented pyrolytic graphite surface.

Poly(o-anisidine) coatings on brass: synthesis, characterization and corrosion protection - Chaudhari, Sudeshna; Gaikwad, A. B.; Patil, P. P. (Current Applied Physics, 2009)
Poly(o-anisidine) (POA) coatings were synthesized on brass by electrochemical polymerization of o-anisidine in aqueous salicylate solution by using cyclic voltammetry. These coatings were characterized by cyclic voltammetry, UV-visible absorption spectroscopy., Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The corrosion protection aspects of POA coatings on brass in aqueous 3% NaCl solution were investigated by potentiodynamic polarization technique and electrochemical impedance spectroscopy (EIS). The potentiodynamic polarization measurements show that the POA coating has ability to protect the brass against corrosion. The corrosion potential was about 0.204 V versus SCE more positive for the POA coated brass than that of uncoated brass and reduces the corrosion rate of brass almost by a factor of 800. The corrosion behavior of the POA coatings was also investigated by EIS through immersion tests performed In aqueous 3% NaCl solution. The evolution of the impedance parameters with the immersion time was studied and the results Show that the POA acts as a protective coating on brass against corrosion in 3% NaCl solution. The water uptake and delamination area were also determined to further support the corrosion protection performance of the POA coating. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: brass; conducting polymers; Corrosion resistant coatings; cyclic voltammetry; Electrochemical impedance spectroscopy; Electrochemical polymerization; poly(o-anisidine)

Polypropylene-organoclay nanocomposites containing nucleating agents - Ghugare, S. V.; Govindaiah, P.; Avadhani, C. V. (Polymer Bulletin, 2009)
Polypropylene/organoclay nanocomposites containing nucleating agents, viz., aluminum hydroxybis[2,2-methylenebis(4,6-di-tert-butylphenyl) phosphate (NA21) and 1,3:2,4-bis(3,4-dimethylbenzylidene)sorbitol (Millad 3988), were prepared by direct melt intercalation in a twin-screw extruder. Nucleating agents were added to polypropylene during compounding and their effect on the properties of the nanocomposites was studied. X-ray diffraction (XRD) and transmission electron microscopy (TEM) exhibited clay layers to be intercalated and partially exfoliated. The expansion of inter-gallery distance of the clay layers was governed by the interaction between polypropylene, compatibilizer, and different nucleating agents. Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) indicated higher thermal stability and crystallization temperature for nanocomposites compared to virgin polymer. Even a small addition of the nanoscale filler with 0.2% nucleating agents was found to promote concurrently several PP material properties, including improved tensile characteristics, higher Young's modulus, increased thermal stability and rate of crystallization.
Keywords: Nucleating agents; organoclay; Polypropylene nanocomposites; Thermogravimetric analysis; transmission electron microscopy

Polypyrrole functionalized with FePcTSA for NO(2) sensor application - Paul, Santhosh; Joseph, Michael (Sensors and Actuators B-Chemical, 2009)
The nitrogen dioxide (NO(2)) sensing capability of polypyrrole (PPy) was enhanced dramatically after functionalized with iron(III)phthalocyanine-4,4',4 `',4'''-tetrasulfonic acid monosodium salt (FePcTSA). The incorporated phthalocyanine was confirmed by different characterization techniques such as UV-vis spectroscopy, FTIR, GFAAS, EDAX, etc. The resistance of the functionalized PPy decreased spontaneously during exposure to NO(2) gas at room temperature. This material exhibited excellent stability, reversibility, and reproducibility. The lowest response time (t(50)) thus obtained is 47 s with a highest response factor (Delta R/R(0) x 100) of 50.25. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Chemical sensor; Fe(III)phthalocyanine tetrasulfonate; Nitrogen dioxide; polypyrrole

Polypyrrole functionalized with ferrocenyl derivative as a rapid carbon monoxide sensor - Paul, Santhosh; Chavan, Nayaku; Radhakrishnan, S. (Synthetic Metals, 2009)
A rapid carbon monoxide detection system was developed with the electrochemical functioncalization of polypyrrole (PPy) with ferrocenylmethyltrimethylammonium iodide (FTMA-I) as a co-dopant exhibits very high sensitivity to ppm levels of carbon monoxide gas and fast recovery under normal dry room temperature conditions. The co-dopant was synthesized mainly to incorporate into PPy electrochemically to modify the properties in order to sense carbon monoxide (CO) gas. The FTMA-I doped PPy exhibited the characteristics oxidation/reduction peaks for ferrocene in its cyclic voltammograms. The modified PPy films deposited on interdigited electrodes gave rapid sensitivity within a second to 300 ppm carbon monoxide gas and good sensitivity factor was observed even at 4 mmol of the functional groups in the polymer for 300 ppm carbon monoxide gas. This material detected the CO gas concentration as low as 100 ppm. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: carbon monoxide; Chemical sensor; conducting polymer; polypyrrole

Porous anisotropic metal nanostructures through controlled transmetallation across a dialysis membrane - Shukla, Sourabh; Pasricha, Renu; Sastry, Murali (Journal of Nanoscience and Nanotechnology, 2009)
Nanostructured metals with hollow interiors are of technological importance due to their unique optoelectronic properties and enhanced surface area. We describe herein, a novel method for the synthesis of anisotropic gold and palladium nanoparticles through a simple galvanic replacement reaction across a semi-permeable dialysis membrane. The control over the reaction kinetics achieved by the presence of membrane enables one to tune the bimetal composition, particle porosity and morphology. Rapid outward diffusion of silver ions generated from the sacrificial silver nanoparticles even at room temperatures prevents the precipitation of high quantities of silver chloride, thereby circumventing the need for product purification. The porous anisotropic nanostructures have potential applications in catalysis, cell imaging and therapeutics.
Keywords: Ag/Pd Nanostructures; Anisotropic Nanoparticles; Dialysis; Galvanic Replacement; Porous nanostructures; Silver Nanotriangles; Silver Nanowires; Transmetallation

Prediction of extrudate swell in polymer melt extrusion using an Arbitrary Lagrangian Eulerian (ALE) based finite element method - Ganvir, Vivek; Lele, Ashish K.; Thaokar, Rochish; Gautham, Basavarsu P. (Journal of Non-Newtonian Fluid Mechanics, 2009)
Accurate prediction of extrudate (die) swell in polymer melt extrusion is important as this helps in appropriate die design for profile extrusion applications. Extrudate swell prediction has shown significant difficulties due to two key reasons. The first is the appropriate representation of the constitutive behavior of the polymer melt. The second is regarding the simulation of the free surface, which requires special techniques in the traditionally used Eulerian framework. In this paper we propose a method for simulation of extrudate swell using an Arbitrary Lagrangian Eulerian (ALE) technique based finite element formulation. The ALE technique provides advantages of both Lagrangian and Eulerian frameworks by allowing the computational mesh to move in an arbitrary manner, independent of the material motion. In the present method, a fractional-step ALE technique is employed in which the Lagrangian phase of material motion and convection arising out of mesh motion are decoupled. In the first step, the relevant flow and constitutive equations are solved in Lagrangian framework. The simpler representation of polymer constitutive equations in a Lagrangian framework avoids the difficulties associated with convective terms thereby resulting in a robust numerical formulation besides allowing for natural evolution of the free surface with the flow. In the second step, mesh is moved in ALE mode and the associated convection of the variables due to relative motion of the mesh is performed using a Godunov type scheme. While the mesh is fixed in space in the die region, the nodal points of the mesh on the extrudate free surface are allowed to move normal to flow direction with special rules to facilitate the simulation of swell. A differential exponential Phan Thien Tanner (PTT) model is used to represent the constitutive behavior of the melt. Using this method we simulate extrudate swell in planar and axisymmetric extrusion with abrupt contraction ahead of the die exit. This geometry allows the extrudate to have significant memory for shorter die lengths and acts as a good test for swell predictions. We demonstrate that our predictions of extrudate swell match well with reported experimental and numerical simulations. (c) 2008 Elsevier BY. All rights reserved.
Keywords: Arbitrary Lagrangian Eulerian; Extrudate (die) swell; Free surface simulations

Preparation and characterization of rhodium nanostructures through the evolution of microgalvanic cells and their enhanced electrocatalytic activity for formaldehyde oxidation - Sathe, Bhaskar R.; Shinde, Dhanraj B.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry C, 2009)
Shape-controlled morphological evolution of nanostructured Rh has been demonstrated with the help of a galvanic displacement reaction using Al in 1 mM aqueous Rh(III) chloride at an open circuit potential 0.99 V and at a temperature of 273 K (room temperature). Nanospheres composed of small nanoparticles of size around 2.9 +/- 0.4 nm having uniform distribution with a FCC pattern have been evolved during the course of the reaction. Electrochemical results coupled with structural and morphological characterization data from transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray diffraction (XRD), and cyclic voltammetry (CV) suggested the formation of Rh nanostructures. Considering the role of the potential of substrate Al and Rh and diffusion of reactant and product species toward and from the surface of the Al, we proposed the tentative mechanism for the formation of microgalvanic cell. Significantly, these: rhodium nanostructures exhibit enhanced electrocatalytic activity toward many fuel cell reactions as demonstrated by formaldehyde oxidation in 0.5 M NaOH. The present strategy is expected to be valid for preparing many other similar electrocatalysts (Pt, Au, and Pd) capable of exhibiting such a remarkable size- and shape-dependent reactivity.

Preparation and nonisothermal crystallization behavior of polypropylene/layered double hydroxide nanocomposites - Lonkar, Sunil P.; Morlat-Therias, Sandrine; Caperaa, N.; Leroux, Fabrice; Gardette, Jean Luc; Singh, R. P. (Polymer, 2009)
Polypropylene (PP)/layered double hydroxide (LDH) nanocomposites were prepared via melt intercalation using dodecyl sulfate anion modified LDH and maleated PP as compatibilizing agent. Evidently the interlayer anions in LDH galleries react with maleic anhydride groups of PP-g-MA and lead to a finer dispersion of individual LDH layers in the PP matrix. The nanostructure was characterized by XRD and TEM; the examinations confirmed the nanocomposite formation with exfoliated/intercalated layered double hydroxides well distributed in the PP matrix. The nonisothermal crystallization behavior of resulting nanocomposites was extensively studied using differential scanning calorimetry (DSC) technique at various cooling rates. In nonisothermal crystallization kinetics, the Ozawa approach failed to describe the crystallization behavior of nanocomposites, whereas the Avrami analysis and Jeziorny method well define the crystallization behavior of PP/LDH nanocomposite. Combined Avrami and Ozawa analysis (Liu model) also found useful. The results revealed that very small amounts of LDH (1%) could accelerate the crystallization process relative to the pure PP and increase in the crystallization rates was attributed to the nucleating effect of the nanoparticles. Polarized optical microscopy (POM) observations also support the DSC results. The effective crystallization activation energy was estimated as a function of the relative degree of crystallinity using the isoconversional analysis. Overall, results indicated that the LDH particles in nanometer size might act as nucleating agent and distinctly change the type of nucleation, growth and geometry of PP crystals. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Layered double hydroxide; Nonisothermal crystallization kinetics; Polypropylene nanocomposites

Preparation of nearly monodisperse nickel nanoparticles by a facile solution based methodology and their ordered assemblies - Sidhaye, Deepti S.; Bala, Tanushree; Srinath, S.; Srikanth, H.; Poddar, Pankaj; Sastry, Murali; Bhagavatula L. V. Prasad (Journal of Physical Chemistry C, 2009)
Nickel nanoparticles have been synthesized by a simple wet chemical reduction technique in the presence of a surfactant sodium dodecyl sulfate (SDS) and a capping agent oleic acid. Varying the concentration of the surfactant and the capping agent has been found to critically govern the nature of the nanoparticles prepared. It is observed that at an optimum concentration of SDS and oleic acid, nearly monodisperse Ni nanoparticles are obtained that form highly ordered hexagonally close-packed structures on electron microscopy grids by a simple drop coating procedure. It is also shown that the presence of oleic acid is necessary for the stability of the Ni nanoparticles synthesized. Structural and magnetic characterizations of the nanoparticles are also presented.

Pressure drop across vortex diodes: experiments and design guidelines - Kulkarni, Amol A.; Ranade, Vivek V.; Rajeev, R.; Koganti, S. B. (Chemical Engineering Science, 2009)
Vortex diodes are used as leaky non-return valves in applications where it is desirable to avoid valves with moving parts. Despite their use in practice for several decades, no clear guidelines for design and optimization of vortex diodes are available. Detailed experimental study on flow and pressure drop characteristics of vortex diodes was therefore carried out to evolve such guidelines. The study covered a wide range of vortex diodes. The variation of diodicity (ratio of pressure drop for reverse and forward flow for the same flow rate) with respect to diode geometry, diode size (d(c)), aspect ratio (d(c)/h), nozzle configuration and Reynolds number (Re) was studied. The experimental results were critically analyzed to develop a design methodology. The methodology is shown to be useful for obtaining the diode dimensions that would yield the desired diodicity for the required operating flow rate. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Aspect ratio; Diodicity; Nozzles; pressure drop; Vortex diode

Probing differential Ag+-nucleobase interactions with isothermal titration calorimetry (ITC): towards patterned DNA metallization - Shukla, Sourabh; Sastry, Murali (Nanoscale, 2009)
DNA has been Successfully used as a scaffold for the fabrication of metallic nanowires, primarily based oil the electrostatic complexation and reduction of the metal cations on the negatively charged sugar-phosphate backbone. Here. we probe the differential binding affinities of nucleobases for silver ions using sensitive isothermal titration calorimetry (ITC) measurements of the reaction enthalpies, which go in order: C > G > A >= T. Using the disparity between the interaction of cytosine (strong binding) and thymine (weak binding) with silver ions, we have successfully generated silver nanoparticle doublets and triplets on custom-made oligonucleotides, C-30-T-40-C-30 and C-20-T-20-C-20-T-20-C-20, respectively. Thus, it new and simple method of generating metallized DNA wires is presented, based entirely on the nucleotide sequence of DNA. The concept could be extended to other cations and complex DNA sequences in order to achieve intricately patterned DNA constructs.

Process for the preparation of polymeric absorbents - Lele, Ashish Kishor; Varghese, Shyni; Badiger, Manohar V.; Mashelkar, Raghunath Anant (2009)
The invention discloses a process for the preparation of polymeric absorbents useful for gelling organic liquids. The process comprises mixing one or more monomers with a cross-linking agent, a free radical initiator, an optional solvent, optionally in the presence of a transition metal source and subjecting the mixture so obtained to a conventional polymerisation method. The polymer is removed, crushed to obtain polymer powder, washed with solvent and dried by conventional methods to remove unreacted monomers, followed by swelling in alcohols to obtain the desired product.

Production, purification, and characterization of taxol and 10-DABIII from a new endophytic fungus gliocladium sp isolated from the Indian yew tree, taxus baccata - Sreekanth, D.; Syed, A.; Sarkar, S.; Sarkar, Dhiman; Santhakumari, B.; Ahmad, Absar; Khan, Mohammad Islam (Journal of Microbiology and Biotechnology, 2009)
We have isolated endophytic fungi from the Indian yew tree, Taxus baccata, and then screened for taxol production. Out of the 40 fungal cultures screened, one fungus Gliocladium sp. was found to produce taxol and 10-DABIII (10-deacetyl baccatin III). These compounds were purified by TLC and HPLC and characterized using UV-spectroscopy, ESI-MS, MS/MS, and proton NMR. One liter of Gliocladium sp. culture yielded 10 mu g of taxol and 65 mu g of 10-DABIII. The purified taxol from the fungus showed cytotoxicity towards cancer lines HL-60 (leukemia), A431 (epidermal carcinoma), and MCF-7 (breast cancer).
Keywords: 10 DAB III; Endophytic fungi; Gliocladium sp.; Taxol; Taxus baccata

Proline-catalyzed simple and efficient synthesis of 1,8-dioxo-decahydroacridines in aqueous ethanol medium - Venkatesan, K.; Pujari, Suresh S.; Srinivasan, Kumar V. (Synthetic Communications, 2009)
Proline-catalyzed synthesis of 1,8-dioxo-decahydroacridines is achieved via one-pot, three-component condensation of aromatic aldehydes, cyclic diketone, and aryl amines in aqueous ethanol medium. This method offers the advantages of proceeding in neutral and mild conditions, giving high to excellent yields of acridines with easy workup procedure.
Keywords: 1; 8-dioxodecahydroacridines; aqueous media; one-pot MCR; Proline

Purification and characterization of acidic lipase from aspergillus niger NCIM 1207 - Mhetras, Nutan; Bastawade, Kulbhushan B.; Gokhale, D. V. (Bioresource Technology, 2009)
An extracellular lipase from Aspergillus niger NCIM 1207 has been purified to homogeneity using ammonium sulfate precipitation followed by phenyl sepharose and Sephacryl-100 gel chromatography. This protocol resulted in 149 fold purification with 54% final recovery. The purified enzyme showed a prominent single band on SDS-PAGE. The purified enzyme is a monomeric protein of 32.2 kDa molecular weight and exhibits optimal activity at 50 degrees C. One interesting feature of this enzyme is its highly acidic pH optimum. The isoelectric point (pl) of lipase was 8.5. The purified lipase appears to be unique since it cleaved triolein at only 3-position releasing 1,2-diolein. Chemical modification studies revealed that His, Ser, Carboxylate and Trp are involved in catalysis. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Acidic lipase; Aspergillus niger; Positional specificity

Purification and characterization of putative alkaline [Ni-Fe] hydrogenase from unicellular marine green alga, tetraselmis kochinensis NCIM 1605 - Bhosale, Siddharth H.; Pant, A.; Khan, Mohammad Islam (Microbiological Research, 2009)
Hydrogenase enzyme from the unicellular marine green alga Tetraselmis kochinensis NCIM 1605 was purified 467 fold to homogeneity. The molecular weight was estimated to be similar to 89kDa by SDS-PAGE. This enzyme consists of two subunits with molecular masses of similar to 70 and similar to 19 kDa. The hydrogenase was found to contain 10 g atoms of Fe and 1 g of atom of Ni per mote of protein. The specific activity of hydrogen evolution was 50 mu mol H-2/mg/h of enzyme using reduced methyl viologen as an electron donor. This hydrogenase enzyme has pl value similar to 9.6 representing its alkaline nature. The absorption spectrum of the hydrogenase enzyme showed an absorption peak at 425 nm indicating that the enzyme had iron-sulfur clusters. The total of 16 cysteine residues were found per mote of enzyme under the denaturing condition and 20 cysteine residues in reduced denatured enzyme indicating that it has two disulfide bridges. (C) 2007 Published by Elsevier GmbH.
Keywords: Characterization; Chemical modification; Ni-Fe hydrogenase; Tetraselmis kochinensis; Unicellular green algae

Pd-catalyzed one-pot chemoselective hydrogenation protocol for the preparation of carboxamides directly from azides - Bavikar, Sudhir N.; Salunke, Deepak B.; Hazra, Braja G.; Pore, Vandana S.; Thierry, Josiane; Dodd, Robert H. (Tetrahedron Letters, 2010)
Carboxamides were obtained efficiently in high yields from azides on reaction with the corresponding pre-formed activated carboxylic acids in a single-step reductive transformation using hydrogen atmosphere (balloon) under Pd/BaSO(4) or Pd/CaCO(3) catalysis. The method is highly chemoselective and compatible with extremely labile functional groups such as benzyl carbamates, benzyl ethers, benzyl esters, and olefins. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Azide; Carboxamide; Catalytic hydrogenation; Chemoselective; Palladium; Succinimide ester

Pd-functionalized carbon nanotubes for selective hydrogenation of 2-butyne-1,4-diol - Nadgeri, Jayprakash M.; Garade, Ajit C.; Tambe, Romana A.; Gokhale, Suresh P.; Rode, Chandrashekhar V. (Advanced Science Letters, 2010)
Multiwalled carbon nanotubes were prepared by thermal decomposition method followed by acid treatment and Pd-functionalization with PdCl2 by wet impregnation method. The Pd functionlized carbon nanotubes catalyst was characterized by BET, FT-IR, Raman, XRD, EDX, ICP-OES, SEM and TEM and was evaluated for its activity for hydrogenation of 2-butyne-1,4-diol. It showed higher selectivity (93%) to 2-butene-1,4-diol than Pd supported on commercial carbon (70% selectivity to 2-butene-1,4-diol) for complete conversion of 2-butyne-1,4-diol. The catalyst also exhibited excellent stability as evidenced by the three catalyst recycle experiments.

Perturbations to Al-27 electric field gradients in nanocrystalline alpha-Al2O3 studied by high-resolution solid-state NMR - Sabarinathan, V.; Ramasamy, S.; Ganapathy, Subramanian (Journal of Physical Chemistry B, 2010)
Al-27 solid-state NMR has been employed to study the perturbations to Al-27 electric field gradients for the aluminum environments in nanocrystalline alpha-alumina. Triple quantum magic angle spinning experiments show that the octahedral aluminum coordination remains unchanged down to 12 nm, although severe perturbations to Al-27 electric field gradients are noticed at 28 nm and below. 3Q-MAS and SATRAS experimental data of nano alpha-alumina have been analyzed through extensive spectral simulations to probe Al-27 electric field gradients of aluminum in the grains and grain boundaries. While the aluminum in the grains has a unique field gradient tensor, the same octahedrally coordinated aluminum environments in the grain boundaries suffer a distribution of electric field gradients. This is evidenced by data analysis of both 3Q-MAS and SATRAS spectra. By invoking the Gaussian isotropic model, in which the (C-Q, eta(Q)) parameter space is discretely sampled by the Czjzek distribution, we have been able to analyze the Al-27 SATRAS spectra of nanocrystalline alpha-alumina samples having grain sizes of 52, 28, 20, and 12 nm. Good agreement between experimental and simulated spectra has led to the quantitative determination of grain and grain boundary components in these materials.

Photodegradation of methanol under UV-visible irradiation by titania dispersed on polyester cloth - Bhattacharyya, Kaustava; Tripathi, Arvind K.; Gupta, Narendra M.; Tyagi, Avesh K. (Photochemistry and Photobiology, 2010)
Titania supported on polyester fabric (TiO(2)-PY) with varying titania loadings (2-7 wt%) were prepared via the dip-coating method at room temperature using an aqueous slurry of anatase titania. Structural and morphological characterizations by X-ray diffraction and scanning electron microscopy revealed that the titanium dioxide crystallites deposited on the surface of the polyester fabric were in the micrometer range while their phase remained to be anatase. Photocatalytic activity of TiO(2)-PY fabric catalysts was evaluated for vapor-phase oxidation of methanol in air as a test reaction in the presence of UV as well as solar radiation under ambient conditions. These catalysts were found to be quite active in both UV and solar irradiation with activity being higher in the former case. CO(2) yield from photo-oxidation of methanol depended on titania content and also on its dispersion over polyester fabric support.

Phylogeographical studies in disjunct populations of symplocos laurina wall. using cytoplasmic PCR-RFLP approach - Banu, Sofia; Lagu, Meena D.; Gupta, Vidya S. (Tree Genetics & Genomes, 2010)
Genetic variation, haplotype relationships, and potential regions of diversity in Symplocos laurina Wall. (Symplocaceae), a montane tree species from India, have been tested using molecular and biogeographical data to infer phylogeographic patterns. The polymerase chain reaction-restriction fragment length polymorphism technique was used to determine the chloroplast (cp) and mitochondrial (mt) DNA haplotypes of 218 individuals from 12 populations, collected from Northeast India (NEI), which is a part of Indo-Burma biodiversity hotspot, and South India, which includes the Western Ghats (WG), another biodiversity hotspot from India and Eastern Ghats (EG). Nine cpDNA (chlorotypes) and 24 mtDNA haplotypes (mitotypes) were identified; the WG region was identified as the most diverse for chlorotypes and the NEI region for mitotypes. Although a strong population differentiation was observed, phylogeographic structure was found to be absent for both the genomes. The haplotype network revealed the presence of two main lineages: NEI-WG lineage and EG lineage, largely without overlapping distributions. The study tests two hypotheses, namely vicariance and dispersal, to understand the distribution of plants in India. The population structure of S. laurina strongly suggests the persistence of the species in putative refugial areas preglaciation and further establishment of other populations of S. laurina from these refugial populations.
Keywords: Cytoplasmic genome; Genetic diversity; Phylogeography

Pivaloyl chloride/DMF: a new reagent for conversion of alcohols to chlorides - Dubey, Abhishek; Upadhyay, Arun K.; Kumar, Pradeep (Tetrahedron Letters, 2010)
An efficient procedure for conversion of alcohols into the corresponding chlorides is described. Pivaloyl chloride/DMF complex is employed as a mild and inexpensive reagent. A possible reaction mechanism is proposed. (C) 2009 Elsevier Ltd. All rights reserved.

Poly(amideimide)s containing pendant pentadecyl chains: synthesis and characterization - More, Arvind S.; Patil, Anandrao S.; Wadgaonkar, Prakash P. (Polymer Degradation and Stability, 2010)
A new aromatic diacylhydrazide monomer viz., 4-[4'-(hydrazinocarbonyl)phenoxy]-2- pentadecylbenzo-hydrazide was synthesized starting from cardanol, which in turn is obtainable from cashew nut shell liquid a renewable resource material. A series of new poly(amideimide)s containing flexibilizing ether linkages and pendant pentadecyl chains was synthesized from 4-[4'-(hydrazinocarbonyl)phenoxy]-2-pentade-cylbenzohydrazide and commercially available aromatic dianhydrides, viz., benzene-1,2,4,5-tetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, benzophenone-3,3',4,4'-tetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride and 4,4'-(hexafluoro isopropylidene)diphthalic anhydride by a two-step solution polycondensation in N,N-dimethylacetamide via the poly(hydrazide acid) intermediate. Inherent viscosities of poly(amideimide)s were in the range 0.60-0.64 dL/g in N,N-dimethylacetamide at 30 +/- 0.1 degrees C. Poly(amideimide)s could be solution cast into tough, transparent and flexible films from their N,N-dimethylacetamide solutions. The solubility of poly(amideimide)s was significantly improved by incorporation of pendant pentadecyl chains and were found to be soluble in N,N-dimethylacetamide, 1-methyl-2-pyrrolidinone, pyridine and m-cresol at room temperature or upon heating. Wide angle X-ray diffraction patterns of poly(amideimide)s revealed a broad halo at around 2 theta = similar to 19 degrees suggesting that polymers were amorphous in nature. In the small-angle region, diffuse to sharp reflections of a typically layered structure resulting from the packing of pentadecyl side chains were observed. The temperature at 10% weight loss (T(10)), determined by TGA in nitrogen atmosphere, of poly(amideimide)s was in the range of 388-410 degrees C indicating their good thermal stability. Glass transition temperatures of poly(amideimide)s were in the range 162-198 degrees C. It was observed that the plasticization effect of attached pentadecyl side chains induced the depression of T(g). (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Cardanol; Cashew nut shell liquid; Pentadecyl chains; Plasticization; Poly(amideimide)s; thermal stability

Polyarylate based thin film composite (TFC) membranes: effects of coating parameters, gutter layer, and intrinsic material properties - Chendake, Yogesh J.; Bhole, Yogesh S.; Lohokare, Harshada R.; Kharul, Ulhas K. (Separation Science and Technology, 2010)
Investigations in thin film composite (TFC) membrane formation with polyacrylonitrile ultrafiltration membrane as a support and three polyarylates with sequentially increased polarity are reported. Effects of TFC membrane preparation parameters viz., concentration of the coating solution, dip time, presence of solvent in pores of UF membrane support, and presence of the gutter layer were examined towards the formation of the selective skin layer, which was assessed by gas permeation analysis. TFC membranes prepared using dimethyl bisphenol-A based polyarylate exhibited similar to 3 orders of magnitude higher permeability and comparable selectivity as that of its dense membrane.
Keywords: Gas permeation; gutter layer; polarity; polyarylates; TFC membrane

Polycarbonate/clay nanocomposites via in situ melt polycondensation - Rama, Mallikarjuna S.; Swaminathan, Sivaram (Industrial & Engineering Chemistry Research, 2010)
Polycarbonate (PC)/clay nanocomposites were prepared via in situ melt polycondensation using novel organoclays modified using phosphonium and imidazolium based cations. The molecular weight of the separated polymer separated from the nanocomposites reveals that phosphonium ion modified organoclays catalyze the polycondensation of bisphenol A with diphenyl carbonate. Wide angle X-ray diffraction (WAXD) and transmission electron microscopy (TEM) indicated that exfoliated polycarbonate/clay nanocomposites could be obtained using organoclays which have reactive bisphenol functionality in the modifier. The glass transition temperature (T(g)) of the nanocomposites was studied using differential scanning calorimetry (DSC). The use of a more thermally stable modifier did not improve the color in polycarbonate clay nanocomposites. Although an approach to produce fully exfoliated PC nanocomposites are evident from this study, the process is far from perfect From the point of producing a color free transparent PC.

Polyethersulfone-expanded graphite nanocomposites: charge transport and impedance characteristics - Ramanujam, B. T. S.; Mahale, Rajashree Y.; Radhakrishnan, S. (Composites Science and Technology, 2010)
Polyethersulfone (PES)-expanded graphite nanocomposites have been prepared by solution blending route after sonicating expanded graphite in dichloromethane. It has been observed that ultrasonication results in nanosheets formation leading to a low percolation threshold of 3 wt.%. At 5 wt.% filler loading the conductivity is of the order of 10(-2) S/cm. Hopping type of charge transport occurs at 3.2 wt.% expanded graphite in PES below which capacitive effects couple. The effective dielectric constant at low frequency increases with filler concentration. Impedance measurement has been carried out to evaluate interfacial capacitance which, for 3.2 wt.% expanded graphite addition in PES, increases to 110 pF from 32 pF for 1 wt.% expanded graphite in the polymer. DSC analysis shows an increment of 12 C in the T(g) of PES with 3 wt.% expanded graphite suggesting interaction between the polymer and filler. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Differential scanning calorimetry (DSC); Electrical properties; Modeling; Polymers; Scanning/transmission electron microscopy (STEM)

Polymer-supported palladium-imidazole complex catalyst for hydrogenation of substituted benzylideneanilines - Udayakumar, V.; Alexander, S.; Gayathri, V.; Shivakumaraiah; Patil, K. R.; Viswanathan, B. (Journal of Molecular Catalysis A-Chemical, 2010)
The polymer-supported palladium-imidazole complex catalyst was synthesized and characterized by various techniques Such as elemental analysis, IR spectroscopy and TG analysis. The physico-chemical properties such as bulk density, Surface studies by BET method and swelling studies of catalyst in different solvents were investigated. XPS Studies were carried out to identify the oxidation state of palladium in the catalyst. The morphology of the support and the catalyst was studied using scanning electron microscope. Using the synthesized catalyst, hydrogenation of benzylideneaniline and a few of its para Substituted derivatives was carried out at ambient conditions. The influence of variation in temperature, concentration of the catalyst as well as the substrate on the rate of reaction Was Studied. The catalyst showed an excellent recycling efficiency over six cycles without leaching of metal from the polymer support. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Benzylideneaniline; Hydrogenation; kinetics; Polymer-supported palladium-imidazole complex catalyst

Preparation and characterization of bioceramic nanocomposites based on hydroxyapatite (HA) and carboxymethyl cellulose (CMC) - Kumar, Annamalai Pratheep; Mohaideen, Kamal Khaja; Alariqi, Sameh A. S.; Singh, Raj Pal (Macromolecular Research, 2010)
We report the synthesis of biomimetic nanocomposites based on carboxymethyl cellulose (CMC) and hydroxyapatite (HA) nanoparticles via a co-precipitation method. Physico-chemical characterization was performed before and after calcination by Fourier transform infrared (FTIR) spectroscopy, solid state (31)P nuclear magnetic resonance (NMR) spectroscopy, and thermogravimetric analysis (TGA). The formation of nanocomposites was observed by wide angle X-ray diffraction (WAXD), scanning electron microscopy (SEM) with energy dispersive X-ray analysis (EDX), and transmission electron microscopy (TEM). The spectral and crystallographic data indicated the formation of hydroxyapatite in the presence of CMC. They were observed as aggregates of HA nanoparticles and CMC, whose sizes were approximately similar to 260 +/- 40 nm. The crystallite size of the hydroxyapatite particles decreased (with 2 wt% 18 +/- 3 nm) with increasing CMC content. The morphological aspects of the calcined samples revealed the sintering ability of HA nanoparticles. Nanocomposites of hydroxyapatite nanoparticles that mimic the process of nucleation and growth in nature can be prepared using biomacromolecules such as CMC.
Keywords: biopolymer; cellulose; hydroxyapatite; Nanoparticles; Particle size; X-ray diffraction

Preparation and characterization of CuInSe2 thin films by chemical bath deposition technique - Hankare, P. P.; Rathod, K. C.; Chate, P. A.; Jadhav, A. V.; Mulla, Imtiaz S. (Journal of Alloys and Compounds, 2010)
Copper indium diselenide (CIS) thin films have been deposited using a precursor solution containing copper sulphate, indium trichoride, hydrazine hydrate and sodium selenosulphate in an aqueous alkaline medium at room temperature. The as grown brown colored films were found to be well adherent to glass substrates. The films were characterized by X-ray diffraction, scanning electron microscopy, atomic absorption spectroscopy, optical absorption, electrical resistivity, and thermo electric measurement techniques. The analysis of optical absorption data shows band-gap energy (E-g) to be 1.1 eV. The electrical resistivity of the thin film was found to be of the order of 10(2) (Omega cm). Thermoelectric power measurement shows n-type conduction. (C) 2010 Published by Elsevier B.V.
Keywords: CuInSe2; Optical properties; Thin films; X-ray diffraction

Preparation and characterization of novel hybrid of bio-assisted mineralized Zn-Al layered double hydroxides using chitosan as a template - Depan, Dilip; Singh, Raj Pal (Journal of Applied Polymer Science, 2010)
The purpose of this study was to prepare and characterize a novel nanohybrid prepared from the template-assisted mineralization of Zn-Al Layered Double Hydroxide (LDH) onto the surface of Chitosan (CSI), with an emphasis on morphology, biocompatibitity, and its use as an efficient drug carrier agent. The as prepared LDH is highly crystalline, with platelet-like morphology and curved tactoids when nucleated onto the surface of CSI. Our results indicate that the -OH and -NH functional moieties on CSI can direct an ordered structure of LDH, due to the electrostatic interaction between biopolymer and inorganic lamellae. We have been successful to intercalate an anti-inflammatory drug, Sodium Ibuprofen (Ibu), into LDH, through conventional coprecipitation method. LDHs are endowed with great potential for delivery vector because their stacked layers lead to safe reservation of biofunctional molecules or genes, and their ion exchangeability and solubility in acidic media (pH < 4) give rise to the controlled release of drug molecules. According to the cell-growth studies, LDHs are found as cell viable up to the concentration of 500 mu g/mL. This study reveals that LDH not only plays a role of a biocompatible-delivery matrix but also facilitates a significant increase in the delivery efficiency. (C) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 115:3636-3644,2010
Keywords: bio-assisted mineralization; cell-growth studies; Chitosan; drug delivery systems; layered double hydroxides

Probing binding preferences of DNA and RNA: backbone chirality of thioacetamido-linked nucleic acids and iso-thioacetamido-linked nucleic acids to differentiate DNA versus RNA selective binding - Gokhale, Sachin S.; Gogoi, Khirud; Kumar, Vaijayanti A. (Journal of Organic Chemistry, 2010)
Subtle differences in RNA and DNA duplex geometry could be sensed by the changed stereochemistry at 3 `-amino function in the 5-atom thioacetamido linker of thioacetamido-linked nucleic acids and iso-thioacetamido-linked nucleic acids modified oligomers. In contrast to the preferred N-type sugar conformations for either 3 `- ribo- or xylo amino nucleosides, predominant S-type sugar conformations were found in the dimers. Although the CD spectral differences for the dimer blocks were found to be identical for those found in phosphodiester linked ribo/xylo dimers, the 5-atom thioactamido linker could reverse the RNA binding selectivity to DNA binding selectivity by the change in configuration at the 3 `-amino-substituted sugar.

Probing lewis acidity and reactivity of Sn- and Ti-beta zeolite using industrially important moieties: a periodic density functional study - Kulkarni, Bhakti S.; Krishnamurty, Sailaja; Pal, Sourav (Journal of Molecular Catalysis A-Chemical, 2010)
The Lewis acidic nature and reactivity of two industrially important catalysts, viz.. Sn and Ti substituted beta zeolite (T-BEA) are analyzed using a unique combination of structural parameters, energetics and reactivity descriptors. To achieve this purpose, we adsorb the industrially important moieties (L) namely NH(3), H(2)O, CH(3)OH, CH(3)CN on the active sites of T-BEA. The calculations were performed using a periodic density functional method where the valence electrons are described using a plane wave basis set in conjunction with pseudo-potentials for the core electrons. The analysis of the structural properties of these complexes reveals that TO(4) shows typical characteristic splitting 120 degrees/90 degrees, close to bipyramidal geometry as compared to tetrahedral symmetry observed in the bare T-BEA. This is associated with small variations in the framework bond lengths (>= 0.08 angstrom) and a substantially large variation of bond angles (<= 10 degrees) in all the ligand-zeolite complexes. Further in both cases of Sn and Ti substituted beta zeolite, ligand interacts at optimum inter-atomic bond distance. Our interaction energies show that adsorption of all ligand moieties is stronger at Sn center than that of Ti. In general, the order of stability of the different T-BEA adducts is NH(3) > H(2)O > CH(3)OH > CH(3)CN. The ligand interaction is associated with the corresponding bond elongation and bond reduction of the adsorbed molecules on catalyst active site, which can be taken as measure of red or blue shifted frequencies. Finally, the global descriptors of reactivity justify the fact that soft acid, Sn-BEA, interacts strongly with soft bases following the Pearson's HSAB principle. However, hard acid, Ti-BEA interacts with soft bases to form a stable Lewis adduct. Furthermore, the HOMO-LUMO gap of all Sn-BEA-L adducts is lower than that of Ti-BEA-L adducts indicating to its higher Lewis acidic nature compared to Ti-BEA. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Beta zeolite; Lewis acidity; Ligand-zeolite complex; Periodic-DFT; Reactivity descriptors

Process for synthesis of beaded cross linked polymers, water-in-oil-in-water emulsions and post functionalisation - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Reddy, Krishna Mohan Srinivasulu; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Chelanattukizhakkemadath, Raman Rajan; Tayal, Rajivkumar; Qureshi, Moham (2010)

Production and characterization of a biodegradable poly (hydroxybutyrate-co-hydroxyvalerate) (PHB-co-PHV) copolymer by moderately haloalkalitolerant Halomonas campisalis MCM B-1027 isolated from Lonar Lake, India - Kulkarni, S. O.; Kanekar, Pradnya P.; Nilegaonkar, S. S.; Sarnaik, S. S.; Jog, Jyoti Prakash (Bioresource Technology, 2010)
Several microorganisms produce polyhydroxyalkanoates (PHA). They are accumulated intracellularly as energy storage compounds. The PHAs are of interest because of their potential in biomedical applications. Halophilic bacteria and archaea are known to produce polyhydroxybutyrate (PHB). This paper describes production of a biodegradable copolymer, PHB-co-PHV by a moderately haloalkalitolerant Halomonas campisalis, isolated from Lonar Lake, India. The production of PHA was in the range of 45-81% on dry cell weight basis when the organism was grown in a production medium containing 1% (w/v) maltose and 0.1% (w/v) yeast extract, at pH ranging from 6 to 9 with an inoculum density of 10(5)-10(7) cells/ml of medium, for incubation period of 15-30 h and at 37 degrees C. The polymer produced by the organism is a hydroxyester with molecular weight of 1.3014 x 10(6). Its melting temperature was 171 degrees C. The (1)H NMR analysis revealed that the polymer was a copolymer of PHB-co-PHV. This could be achieved by providing simple carbon source viz. maltose. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Biodegradable plastics; Halomonas campisalis; Polyhydroxyalkanoates

Production of single cell protein, essential amino acids, and xylanase by penicillium janthinellum - Rao, Mala; Varma, Anjanikumar; Deshmukh, Sumedha S. (Bioresources, 2010)
Microbial biomass having 46% crude protein content and enriched with essential amino acids as well as extracellular xylanase activity (100-150 IU/ml) was produced by an efficient fungal strain, Penicillium janthinellum (NCIM St-F-3b). Optimization studies for maximum xylanase and biomass production showed that the fungus required a simple medium containing bagasse hemicellulose as carbon source and ammonium sulphate as the nitrogen source. Therefore bagasse, which is a waste product of the sugar industry, can be efficiently used in microbioal biomass protein preparation for animal feed.
Keywords: Bagasse hydrolysate; Crude protein; Microbial biomass production; Penicillium janthinellum; Xylanase

Proline catalyzed direct diastereoselective 6-enolexo aldolization: toward the synthesis of the imino sugar DNJ - Kumar, Indresh; Rode, Chandrashekhar V. (Tetrahedron-Asymmetry, 2010)
A L-proline catalyzed direct diastereoselective 6-enolexo aldolization reaction of differentiating dialdehydes derived from tartaric acid is presented This organocatalytic approach provides high levels of synselectivity (dr > 10 1) with the stereocontrolled C-C bond formation between C4 and C5 intramolecularly which can serve to synthesize Imino-sugar skeleton quickly (C) 2010 Elsevier Ltd All rights reserved

Protoplast formation and regeneration in lactobacillus delbrueckii - Singhvi, Mamta; Joshi, Dipti; Gaikaiwari, Shalaka A.; Gokhale, Digambar V. (Indian Journal of Microbiology, 2010)
Method for production and regeneration of Lactobacillus delbrueckii protoplasts are described. The protoplasts were obtained by treatment with a mixture of lysozyme and mutanolysin in protoplast buffer at pH 6.5 with different osmotic stabilizers. The protoplasts were regenerated on deMan, Rogosa and Sharpe (MRS) with various osmotic stabilizers. Maximum protoplast formation was obtained in protoplast buffer with sucrose as an osmotic stabilizer using a combination of lysozyme (1 mg/ml) and mutanolysin (10 mu g/ml). Maximum protoplast regeneration was obtained on MRS medium with sucrose (0.5 M) as an osmotic stabilizer. The regeneration medium was also applicable to other species of lactobacilli as well. This is, to our knowledge, the first report on protoplast formation and efficient regeneration in case of L. delbrueckii.
Keywords: Lactobacillus delbrueckii; Protoplast formation; Protoplast regeneration

Pt-MoOx-carbon nanotube redox couple based electrocatalyst as a potential partner with polybenzimidazole membrane for high temperature polymer electrolyte membrane fuel cell applications - Vellacheri, Ranjith; Unni, SreeKuttan M.; Nahire, Sandip; Kharul, Ulhas K.; Kurungot, Sreekumar (Electrochimica Acta, 2010)
A redox couple based electrocatalyst comprising of Pt-Multi Wall Carbon NanoTube (Pt-MWCNT) promoted with molybdenum oxide (MoOx, 2 < x < 3) nanoparticles was prepared. The objective was to effectively organize the Pt-MoOx interface on the smooth MWCNT surface to overcome the practical difficulties associated with establishing such interface with Pt dispersed on carbon morphologies possessing surface irregularities. The present study revealed the importance of stringent controlling of the additive level for maintaining a balanced bifunctional behavior of the catalyst combination through the synergistic effects by the components and the need of a proton conducting membrane operable at high temperature to get better output from the Polymer Electrolyte Membrane Fuel Cell (PEMFC) systems. An indigenously developed polybenzimidazole (PBI) membrane was used to fabricate a membrane electrode assembly (MEA) as it can be operated at higher temperatures compared to that of Nafion membranes. MoOx additive level was carefully controlled by monitoring the active Pt area by cyclic voltammetry. All prepared electrocatalysts were characterized by using HRTEM, XRD and XPS to get information on dispersion and morphology, crystalinity and oxidation state of different elements, respectively. The system prepared with 5% MoOx addition with respect to Pt (hereafter Pt-MoOx(5%)-MWCNT) displayed balanced active Pt area and excellent oxygen reduction reaction (ORR) and methanol oxidation reaction (MOR) activities. Rotating Disk Electrode (ROE) system was extensively utilized to understand the ORR kinetics and the favorable role of MoOx as the promoter in the reaction. The kinetic current (j(k)) measured at 0.02 V vs. Hg/Hg2SO4 electrode from the Koutecky-Levich plots was 9 times higher and the apparent activation energy during single cell evaluation was 27 kJ/mol lower for the MoOx promoted system, compared to the system without the additive. A higher operating temperature significantly favored the cell performance by a combined effect of enhancement in proton conductivity of the PBI membrane and possible kinetic benefit by the well postulated oxygen spill over effect by the MoOx type systems in some combinations involving such systems. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Methanol oxidation reaction; MWCNT; oxygen reduction reaction; PBI membrane; PEMFC

Purification and characterization of two distinct acidic phytases with broad pH stability from aspergillus niger NCIM 563 - Soni, S. K.; Magdum, A.; Khire, Jayant Malhar (World Journal of Microbiology & Biotechnology, 2010)
Aspergillus niger NCIM 563 produced two different extracellular phytases (Phy I and Phy II) under submerged fermentation conditions at 30A degrees C in medium containing dextrin-glucose-sodium nitrate-salts. Both the enzymes were purified to homogeneity using Rotavapor concentration, Phenyl-Sepharose column chromatography and Sephacryl S-200 gel filtration. The molecular mass of Phy I and II as determined by SDS-PAGE and gel filtration were 66, 264, 150 and 148 kDa respectively, indicating that Phy I consists of four identical subunits and Phy II is a monomer. The pI values of Phy I and II were 3.55 and 3.91, respectively. Phy I was highly acidic with optimum pH of 2.5 and was stable over a broad pH range (1.5-9.0) while Phy II showed a pH optimum of 5.0 with stability in the range of pH 3.5-9.0. Phy I exhibited very broad substrate specificity while Phy II was more specific for sodium phytate. Similarly Phy II was strongly inhibited by Ag(+), Hg(2+) (1 mM) metal ions and Phy I was partially inhibited. Peptide analysis by Mass Spectrometry (MS) MALDI-TOF also indicated that both the proteins were totally different. The K (m) for Phy I and II for sodium phytate was 2.01 and 0.145 mM while V (max) was 5,018 and 1,671 mu mol min(-1) mg(-1), respectively. The N-terminal amino acid sequences of Phy I and Phy II were FSYGAAIPQQ and GVDERFPYTG, respectively. Phy II showed no homology with Phy I and any other known phytases from the literature suggesting its unique nature. This, according to us, is the first report of two distinct novel phytases from Aspergillus niger.
Keywords: Aspergillus niger; Phytase; Phytate; Poultry feed; Purification

[Pd]-mediated omega-alkynone cycloisomerization approach for the central tetrahydropyran unit and the synthesis of C(31)-C(48) fragment of aflastatin A - Narute, Sachin B.; Kiran, Neella Chandra; Ramana, Chepuri V. (Organic & Biomolecular Chemistry, 2011)
A concise assembly of the central tetrahydropyran unit of aflastatin A featuring a Pd-mediated alkynone cycloisomerization to provide a glycal and its subsequent stereoselective hydroboration to deliver the requisite stereochemistry at C(33) and C(34) centers is documented.

Pentadecyl phenol- and cardanol-functionalized fluorescent, room- temperature liquid-crystalline perylene bisimides: effect of pendant chain unsaturation on self-assembly - Bhavsar, Ghanashyam A.; Asha, S. K. (Chemistry - A European Journal, 2011)
A new perylene bisimide (PBI) building block based on pentadecyl phenol (PDP) or cardanol was developed, which upon esterification with 3,4,5-tridodecyloxy gallate resulted in highly emissive, room-temperature liquid-crystalline (LC) molecules. The self assembly in solution was studied in detail by NMR spectroscopy, UV/Vis absorption, and fluorescence spectroscopy. In solution both PDP- and cardanol-based PBI exhibited similar behavior. They were molecularly dissolved in chloroform (CHCl3) but formed rotationally displaced H-type aggregates that emitted at 640 nm in methylcyclohexane (MCH). Surface morphology in dropcast films were characterized using microscopic techniques such as SEM, TEM, and atomic force microscopy (AFM). The liquid-crystalline properties were studied using differential scanning calorimetry (DSC), polarized light microscopy (PLM), and variable-temperature X-ray (small-angle X-ray scattering (SAXS) and wide-angle X-ray diffraction (WXRD)) studies. Variable-temperature X-ray studies in the LC phase indicated strong π–π stacking interaction present in the PDP-based PBI derivative, whereas the stacking was absent in the LC phase of the cardanol-based PBI. The latter formed self-organized structures of extremely short length due to the presence of cis double bonds in the C15 alkyl side chain, whereas the saturated alkyl side chain in PDP could pack efficiently, thereby resulting in nanofibers that were several micrometers in length.

Perspectives for nano-biotechnology enabled protection and nutrition of plants - Ghormade, Vandana; Deshpande, Mukund V.; Paknikar, Kishore M. (Biotechnology Advances, 2011)
Indiscriminate use of pesticides and fertilizers causes environmental pollution, emergence of agricultural pests and pathogens, and loss of biodiversity. Nanotechnology, by virtue of nanomaterial related properties, has potential agro-biotechnological applications for alleviation of these problems. The literature pertaining to the role of nanotechnology in plant and soil systems demonstrates that nanomaterials may assist in a) the controlled release of agrochemicals for nutrition and protection against pests and pathogens, b) delivery of genetic material, c) sensitive detection of plant disease and pollutants and d) protection and formation of soil structure. For instance, porous silica (15 nm) and biodegradable, polymeric chitosan (78 nm) nanoparticles displayed slow release of encapsulated pesticide and fertilizer, respectively. Further, nanosized gold (5-25 nm) delivered DNA to plant cells while iron oxide (30 nm) based nanosensors detected pesticides at minute levels. These functions assist the development of precision farming by minimizing pollution and maximizing the value of farming practice. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Biofertilizer; Biopesticides; Controlled delivery; Fertilizer; Genetic material; Nanomaterials; Nanosensors; Pathogen; Pesticides; Residues

Phase behavior of lipid-based lyotropic liquid crystals in presence of colloidal nanoparticles - Venugopal, Edakkal; Bhat, Suresh K.; Vallooran, Jijo J.; Mezzenga, Raffaele (Langmuir, 2011)
We have investigated the microstructure and phase behavior of monoglyceride-based lyotropic liquid crystals in the presence of hydrophilic silica colloidal particles of size comparable to or slightly exceeding the repeat units of the different liquid crystalline phases. Using small angle X-ray scattering (SAXS) and differential scanning calorimetry (DSC), we compare the structural properties of the neat mesophases with those of the systems containing silica colloidal particles. It is found that the colloidal particles always macrophase separate in inverse bicontinuous cubic phases of gyroid (Ia3d) and double diamond (Pn3m) symmetries. SAXS data for the inverse columnar hexagonal phase (H(II)) and lamellar phase (L(alpha)) suggest that a low volume fraction of the nanoparticles can be accommodated within the mesophases, but that at concentrations above a given threshold, the particles do macrophase separate also in these systems. The behavior is interpreted in terms of the enthalpic and entropic interactions of the nanoparticles with the lamellar and hexagonal phases, and we propose that, in the low concentration limit, the nanoparticles are acting as point defects within the mesophases and, upon further increase in concentration, initiate nucleation of nanoparticles dusters, leading to a macroscopic phase separation.

Phase separation of DMDBS from PP: effect of polymer molecular weight and tacticity - Sreenivas, K.; Basargekar, Rajeev; Kumaraswamy, Guruswamy (Macromolecules, 2011)
We report an unexpected dependence of DMDBS phase separation temperature on the molecular weight of the matrix isotactic polypropylene (iPP). DMDBS crystallizes out at lower temperatures for iPP with decreasing molecular weight (and correspondingly lower tacticity). All the iPPs in our study are reasonably high molecular weight samples and there is no molecular weight dependence of their solubility parameter. Therefore, the decrease in DMDBS phase separation temperature for lower molecular weights cannot be rationalized using thermodynamic arguments. This molecular weight dependence appears to be unique to isotactic polypropylene and is not observed for either syndiotactic polypropylene or for random copolymers of isotactic polypropylene containing ethylene comonomer.

Phosphine-mediated synthesis of 1,4-oxazepine- and 1,5-oxazocine-based sugar hybrids from deoxysugar azides - Kurhade, Suresh E.; Salunkhe, Videsh T.; Siddaiah, V.; Bhuniya, Debnath; Reddy, D. Srinivasa (Synthesis-Stuttgart, 2011)
An efficient and convenient method was developed for the synthesis of novel 1,4-oxazepine- and 1,5-oxazocine-based sugar hybrids from readily available deoxysugar azides by means of tributylphosphine-mediated tandem reactions. The resulting glycoconjugates might be useful in increasing the diversity of sugar backbones, and could find applications as potential glycomimetics and in drug discovery.
Keywords: Alkynes; azides; carbohydrates; heterocycles; oxazepines; oxazocines; Tandem reactions

Photoactive RuII-polypyridyl complexes that display sequence selectivity and high-affinity binding to duplex DNA through groove binding - Ghosh, Amrita; Das, Priyadip; Gill, Martin R.; Kar, Prasenjit; Walkar, Michael G.; Thomas, Jim A.; Das, Amitava (Chemistry A European Journal, 2011)
The duplex-DNA binding properties of a nonintercalating polypyridyl ruthenium(II) complex that incorporates a linear extended ligand with a catechol moiety has been probed with a variety of photo- and biophysical techniques. These studies reveal that the complex groove binds to DNA sequences biphasically, and displays binding constants equivalent to those of high-affinity metallointercalators. The complex also displays preferential binding to AT-rich sequences. Changes in the structure of the coordinated catechol ligand and the incorporation of intercalating ancillary ligands into the complex were found to modulate both the optical-binding response and binding parameters of the system, which indicates that the catechol moiety plays a crucial role in the observed enhancement to binding affinities.

Photocatalytic splitting of CS2 to a carbon-sulfur polymer and S8 catalyzed by a bimetallic ruthenium(II) compound with a tertiary amine binding site - towards photocatalytic splitting of CO2? - Livanov, Konstantin; Madhu, Vedichi; Balaraman, Ekambaram; Shimon, Linda J. W.; Diskin-Posner, Yael; Neumann, Ronny (Inorganic Chemistry, 2011)
The catalytic photocleavage of CS2 to S8 and a (CxSy)n polymer with visible light using a dinuclear ruthenium(II) compound with a bipyridine units for photoactivity and a vicinal tertiary amine binding site for CS2 activation was studied. The catalyst was characterized by X-ray diffraction, 1H NMR, and 13C NMR, ESI-MS and elemental analysis. CS2 photocleavage was significant (240 turnovers, 20 h) to yield isolable S8 and a (CxSy)n polymer. A mononuclear catalyst or one without an amine binding site showed significantly less activity. XPS of the (CxSy)n polymer showed a carbon/sulfur ratio ∼1.5–1.6 indicating that in part both C–S bonds of CS2 had been cleaved. Catalyst was also included within the polymer. The absence of peaks in the 1H NMR verified the (CxSy)n nature of the polymer, while 13C NMR and IR indicated that the polymer had multiple types of C–S and C–C bonds.

Photoelectrochemical applications of In2Se3 thin films by chemical deposition - Hankare, P. P.; Rathod, K. C.; Asabe, M. R.; Jadhav, A. V.; Helavi, V. B.; Chavan, Santosh S.; Garadkar, K. M.; Mulla, Imtiaz S. (Journal of Materials Science-Materials in Electronics, 2011)
Indium selenide films have been synthesized by chemical bath deposition method onto stainless steel plate. The configuration of fabricated cell is n-In2Se3| NaOH(1 M) + S(1 M) + Na2S(1 M) |C-(graphite). Characterization of the photoelectrochemical cell was carried out by studying X-ray diffraction, current-voltage and capacitance-voltage characteristics in the dark, barrier height measurements, power output, photoresponse and spectral response. The study shows that the In2Se3 thin films are n-type semiconductor. The junction ideality factor was found to be 3.24. The flat band potential and the barrier height were found to be 0.720 V and 0.196 eV, respectively. From the study of power output characteristics, open circuit voltage, short circuit current, fill factor and efficiency were found to be 310 mV, 20 mu A, 37.64 and 0.61%, respectively. Photoresponse studies show that the lighted ideality factor is 2.78. Maximum current was observed at 575 nm.

Photophysical properties of ligand localized excited state in ruthenium(ii) polypyridyl complexes: a combined effect of electron donor-acceptor ligand - Verma, Sandeep; Kar, Prasenjit; Das, Amitava; Ghosh, Hirendra Nath (Dalton Trans, 2011)
We have synthesized ruthenium(II) polypyridyl complexes (1) Ru(II)(bpy)2(L1), (2) Ru(II)(bpy)2(L2) and (3) Ru(II)(bpy)(L1)(L2), where bpy = 2,2′-bipyridyl, L1 = 4-[2-(4′-methyl-2,2′-bipyridinyl-4-yl)vinyl]benzene-1,2-diol) and L2 = 4-(N,N-dimethylamino-phenyl)-(2,2′-bipyridine) and investigated the intra-ligand charge transfer (ILCT) and ligand–ligand charge transfer (LLCT) states by optical absorption and emission studies. Our studies show that the presence of electron donating –NMe2 functionality in L2 and electron withdrawing catechol fragment in L1 ligands of complex 3 introduces low energy LLCT excited states to aboriginal MLCT states. The superimposed LLCT and MLCT state produces redshift and broadening in the optical absorption spectra of complex 3 in comparison to complexes 1 and 2. The emission quantum yield of complex 3 is observed to be extremely low in comparison to that of complex 1 and 2 at room temperature. This is attributed to quenching of the 3MLCT state by the low-emissive 3LLCT state. The emission due to ligand localized CT state (ILCT and LLCT) of complexes 2 and 3 is revealed at 77 K in the form of a new luminescence band which appeared in the 670–760 nm region. The LLCT excited state of complex 3 is populated either via direct photoexcitation in the LLCT absorption band (350–700 nm) or through internal conversion from the photoexcited 3MLCT (400–600 nm) states. The internal conversion rate is determined by quenching of the 3MLCT state in a time resolved emission study. The internal conversion to LLCT and ILCT excited states are observed to be as fast as ∼200 ps and ∼700 ps for complexes 3 and 2, respectively. The present study illustrates the photophysical property of the ligand localized excited state of newly synthesized heteroleptic ruthenium(II) polypyridyl complexes.

Phytochemical investigation of artemisia pallens - Ruikar, Anjali D.; Jadhav, Ravindra B.; Phalgune, Usha D.; Rojatkar, Supada R.; Puranik, Vedavati G.; Deshpande, Nirmala R. (Helvetica Chimica Acta, 2011)
Two new eudesmanolides, pallensin (1) and 4-epipallensin (2), along with a known eudesmanolide, santonin, and a known flavone, 4-epivalgarin, have been isolated from the aerial part of A. pallens. Their structures were established by detailed spectral studies (1D and 2D) and by comparison of their spectroscopic data with those of known compounds.

PNAs grafted with (alpha/gamma, R/S)-aminomethylene pendants: Regio and stereo specific effects on DNA binding and improved cell uptake - Mitra, Roopa; Ganesh, Krishna N. (Chemical Communications, 2011)
PNAs grafted with cationic aminomethylene (am) pendants on the backbone at the glycyl (alpha) or ethylenediamine (gamma) segments show regio (alpha/gamma) and stereochemistry (R/S) dependent binding with complementary DNA. These are efficiently taken up by cells, with gamma(S-am) aeg-PNA being the best in all properties.

Poly(acrylonitrile) based ultrafiltration membranes: optimization of preparation parameters - Lohokare, Harshada R.; Bhole, Yogesh S.; Taralkar, Suyog; Kharul, Ulhas K. (Desalination, 2011)
Supported ultrafiltration (UF) membranes based on poly(acrylonitrile) were prepared while varying crucial parameters responsible for controlling membrane porosity, viz.; polymer concentration, solvent and additives in the dope solution. Insight into membrane porosity and morphology was obtained by water flux, solute rejection, bubble point, pore size distribution, SEM and AFM analyses. It was found that merely increasing polymer concentration does not necessarily reduce pore size of membranes. Among four solvents used for the dope solution preparation, N-methyl pyrrolidone was found to offer membranes with optimal combination of flux and rejection of various solutes. Some of the PAN(17) (17% w/w PAN concentration in the dope solution) membranes prepared using organic acid as the additive (citric acid, tartaric acid or maleic acid) offered 1.2-1.7 times higher flux than the membrane prepared using inorganic salt, ZnCl2 as an additive. The porosity of PAN(17) membrane prepared using CA as an additive was larger as compared to membrane prepared using ZnCl2 as an additive. Atomic force microscopy (AFM) analysis of this membrane exhibited higher surface roughness as compared to the ZnCl2 based membrane. Both these membranes exhibited bacteria (E. Coli) log reduction value (LRV) of at least 6; depicting applicability of these membrane for water disinfection. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Additive; Bacteria rejection; Poly(acrylonitrile); Pore size distribution; Ultrafiltration

Polyamides containing quinoxaline moiety - Patil, Vidyadhar B.; Sayyed, Maheboob M.; Mahanwar, Prakash A.; Wadgaonkar, Prakash P.; Maldar, Noormahamad N. (Journal of Polymer Research, 2011)
A new quinoxaline moiety containing aromatic diamine; 2,3-bis[4-(4-aminophenoxy)phenyl]quinoxaline (APQ) was synthesized starting from 4-methoxybenzaldehyde and was characterized by IR, (1)H, (13)C NMR and Mass spectrometry. Five new polyamides were synthesized by polycondensation of various aliphatic diacid / aromatic diacids namely, azelaic acid, bis(4-carboxyphenyl)dimethylsilane, 4,4'-oxybis(benzoicacid), isophthalic acid and terephthalic acid with APQ by Yamazaki's phosphorylation method using triphenyl phosphite as condensing agent. The polyamides were characterized by IR spectroscopy, solubility tests, inherent viscosity, X-ray diffraction technique, differential scanning colorimetry and thermogravimetric analysis. The polyamides had inherent viscosities in the range 0.39-0.45 dL/g in N, N-dimethylacetamide at 30 +/- 0.1 A degrees C. The polyamides were soluble in polar aprotic solvents such as N, N-dimethylacetamide, N, N-dimethylformamide, dimethylsulfoxide, N-methylpyrrolidone. X-Ray diffraction studies showed that polyamides were amorphous in nature. The polyamides showed glass transition temperatures in the range 104-205 A degrees C, according to differential scanning calorimetry. Thermogravimetric analysis exhibited initial decomposition temperatures above 348 A degrees C; indicating that these polyamides possessed excellent thermal stability.
Keywords: polyamides; Quinoxaline; solubility; Thermal properties; XRD

Polyaniline modified electrodes for detection of dyes - Mahanta, Debajyoti; Munichandraiah, N.; Radhakrishnan, S.; Madras, Giridhar; Patil, Satish (Synthetic Metals, 2011)
Polyaniline (PANI) is one of the most extensively used conjugated polymers in the design of electrochemical sensors. In this study, we report electrochemical dye detection based on PANI for the adsorption of both anionic and cationic dyes from solution. The inherent property of PANI to adsorb dyes has been explored for the development of electrochemical detection of dye in solution. The PANI film was grown on electrode via electrochemical polymerization. The as grown PANI film could easily adsorb the dye in the electrolyte solution and form an insulating layer on the PANI coated electrode. As a result, the current intensity of the PANI film was significantly altered. Furthermore, PANI coated stainless steel (SS) electrodes show a change in the current intensity of Fe(2+)/Fe(3+) redox peaks due to the addition of dye in electrolyte solution. PANI films coated on both Pt electrodes and non-expensive SS electrodes showed the concentration of dye adsorbed is directly proportional to the current intensity or potential shift and thus can be used for the quantitative detection of textile dyes at very low concentrations. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Electrochemical sensor; Emeraldine base; Emeraldine salt; polyaniline

Polybenzimidazoles based on 3,3 `-diaminobenzidine and aliphatic dicarboxylic acids: synthesis and evaluation of physicochemical properties toward their applicability as proton exchange and gas separation membrane material - Bhavsar, Rupesh S.; Nahire, Sandip B.; Kale, Mrunali S.; Patil, Shubhangi G.; Aher, Pradnya P.; Bhavsar, Ritesh A.; Kharul, Ulhas K. (Journal of Applied Polymer Science, 2011)
A series of aromatic-aliphatic polybenzimidazoles (PBIs) based on 3,3'-diaminobenzidine (DAB) and aliphatic dicarboxylic acid with incremental -CH2- groups were synthesized. Optimization of synthesis parameters and evaluation of physicochemical properties are requisite for PBI applicability as the proton exchange membrane (PEM) and gas separation membrane materials are reported. It was found that though all these PBIs exhibited high thermal, mechanical, and oxidative stability, effect of added flexibility on physical properties is not monotonous. Membranes were prepared by solution casting as well as phase-inversion method. The later types of membranes exhibited much higher H3PO4 content than its doping achieved in the solution casted membranes. These PBIs possess low hydrogen and helium permeability than that of conventional PBI. This low permeability, along with their excellent oxidative stability indicated that they can be promising PEM materials. Their CO2-sorption analysis revealed that PBI6 based on suberic acid possesses appreciable CO2 sorption. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 120: 1090-1099, 2011
Keywords: Gas permeation; mechanical properties; membranes; oxidative stability; polybenzimidazoles

Poly(ether ether ketone)s and poly(ether ether ketone ketone)s containing cardo decahydronaphthalene groups: synthesis and characterization - Honkhambe, Pandurang N.; Pasale, Sharad K.; Bhairamadgi, Nagendra S.; Kumbhar, Kishor P.; Salunkhe, Manikrao M.; Wadgaonkar, Prakash P. (Journal of Applied Polymer Science, 2011)
New poly(ether ether ketone)s and poly (ether ether ketone ketone) s were synthesized by polycondensation of each of the three bisphenols, viz., 4,4'-(octahydro-2(1H)-naphthylidene) bisphenol, 4,4'-(octa-hydro-2(1H)-naphthylidene) bis-3-methylphenol, and 4,4'(octahydro-2(1H)-naphthylidene) bis-3,5-dimethylphenol with 4,4'-difluorobenzophenone and 1,3-bis(4-fluorobenzoyl) benzene in a mixture of N,N-dimethylacetamide and toluene [1 : 1 (v/v)] in the presence of anhydrous potassium carbonate. Inherent viscosities of poly(ether ether ketone) s and poly (ether ether ketone ketone) s were in the range 0.32-0.80 dL/g and number-average molecular weights were in the range 16,100-55,900 g/mol. Poly(ether ether ketone) s and poly(ether ether ketone ketone) s were soluble in organic solvents such as dichloromethane, chloroform, tetrahydrofuran, meta-cresol, pyridine, and 1-methyl-2-pyrrolidinone at room temperature and could be cast into tough, transparent, and flexible films from their chloroform solutions. Wide angle x-ray diffraction measurements revealed the amorphous nature of poly(ether ether ketone) s and poly (ether ether ketone ketone) s. The glass transition temperature poly(ether ether ketone) s and poly(ether ether ketone ketone) s were in the range 185-251 degrees C. The temperature at 10% weight loss, determined from thermogravimetric analysis, of poly(ether ether ketone) s and poly(ether ether ketone ketone) s in nitrogen atmosphere was in the range 462-493 degrees C indicating their good thermal stability. (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 122: 1607-1613, 2011
Keywords: bisphenol; cardo decahydronaphthalene; poly(ether ether ketone ketone)s; poly(ether ether ketone)s; Polycondensation; Thermal properties

Polymerization of ethylene to branched poly(ethylene)s using ansa-eta(5)-monofluorenyl cyclohexanolato zirconium(IV) complex/methylaluminoxane - Rajesh, A.; Sivaram, S. (Polymer Bulletin, 2011)
ansa-eta(5)-Monofluorenyl cyclohexanolato zirconium complex 3 was shown to be active for the polymerization of ethylene when activated with methylaluminoxane (MAO) at 5 bar. Up to a polymerization temperature of 40 A degrees C, 3/MAO resulted in linear poly(ethylene)s with saturated chain ends. However, at polymerization temperatures of 60, 80, and 100 A degrees C, a mixture of branched poly(ethylene)s, linear alpha-olefins and long chain alkanes was obtained. The poly(ethylene)s produced at 80 and 100 A degrees C exhibited a bimodal molecular weight distribution indicative of multiple active species. Very high molecular weight (M (v) > 5 x 10(5)) linear poly(ethylene)s were obtained using 3/MAO at 25 A degrees C.
Keywords: ansa-Monofluorenyl complex; Bimodal MWD; Branched poly(ethylene)s; Ethylene polymerization; Methyl aluminoxane

Polymerization of ethylene using amido functional half-sandwich complexes of group 4 metals - Rajesh, A.; Sivaram, S. (Polymer Engineering and Science, 2011)
Ligands (C(13)H(9))(2,6-R(2)C(6)H(3)NH)SiPh(2) [R = (i)Pr (2a), Me (2b)] were synthesized by single deprotonation of the amino group in 2,6-dialkylanilines with n-BuLi at -78 degrees C followed by reaction with fluorenyl diphenyl silyl chloride [FluSi(Ph(2))Cl]. Single crystal X-ray diffraction studies revealed different geometries around the nitrogen atom for the two compounds. Titanium and zirconium complexes (3a-3d) were prepared by double deprotonation of the ligands with n-butyl lithium (n-BuLi) followed by reaction with the respective metal chlorides, MCl(4) (THF)(2). Polymerization of ethylene was performed using these complexes as catalyst precursors along with methylaluminoxane (MAO) as an activator at 5 bar pressure. Complexes 3a-3d/MAO exhibited moderate catalyst activities for polymerization of ethylene and resulted in high molecular weight linear poly(ethylene)s (M(v) > 4 3 10(5) g/mol). Catalyst activities were much lower when compared to similar N-alkyl substituted complexes presumably due to the resonance effect of the aromatic group on the amido nitrogen. POLYM. ENG. SCI., 51:2103-2108, 2011. (C) 2011 Society of Plastics Engineers

Porosity driven photocatalytic activity of wormhole mesoporous TiO2-xNx in direct sunlight - Sivaranjani, Kumarsrinivasan; Gopinath, Chinnakonda S. (Journal of Materials Chemistry, 2011)
Results obtained by combining four important factors simultaneously, namely, wormhole mesoporosity with low diffusion length for charge carriers, high surface area, nanoparticles with high crystallinity, and visible light absorption due to N-doping, in titania (meso-TiO2-xNx) are reported. Meso-TiO2-xNx materials have been prepared by a combustion method within 10 min and by varying urea : Ti(NO3)(4) between 1 (UT1) and 10 (UT10). All of the prepared materials have been thoroughly characterised. Nanocrystalline anatase phase with high surface area (234 m(2) g(-1)), and type-IV H-3-mesoporosity is observed with UT10. Photocatalytic rhodamine-B degradation was employed to screen for the activity of the materials, and p-anisyl alcohol oxidation to p-anisaldehyde was carried out successfully in aqueous solution under direct sunlight. High photocatalytic activity of UT10 in direct sunlight, in spite of high band gap (3.24 eV), is attributed to the better utilization of holes due to the low charge diffusion barrier associated with wormhole mesoporosity along with highly crystalline, however, nanoparticulate TiO2-xNx.

Porous nitrogen rich cadmium-tetrazolate based metal organic framework (MOF) for H-2 and CO2 uptake - Pachfule, Pradip; Banerjee, Rahul (Crystal Growth & Design, 2011)
The highly porous nitrogen rich metal organic framework [Cd-3(4-TP)(6)] (Cd-4TP-1) was synthesized solvothermally from the predesigned organic building block 4-tetrazole pyridine (4-TP) and Cd(II) as metal center using DMF as solvent. Cd-4TP-1 has a three-dimensional porous architecture where all the binding sites of Cd(II) are exclusively occupied by the nitrogen atoms from the mu(2)-tetrazolyl group or the pyridyl functionality of the 4-TP ligands. Cd-4TP-1 has Brunauer-Emmett-Teller (BET) and Langmuir surface areas of 472.2 and 728.6 m(2)/g, respectively, and shows 1.1 wt % H-2 (77 K) and 2.7 mmol/g CO2 uptake (273 K).

Possible deNO(x) management under net oxidizing conditions: a molecular beam study of (NO)-N-15+CO+O-2 reaction on Pd(111) surfaces - Nagarajan, Sankaranarayanan; Thirunavukkarasu, Kandasamy; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2011)
Isothermal kinetic measurements of (NO)-N-15 reduction with CO on Pd(111) surfaces were carried out under net-oxidizing conditions with (NO)-N-15 + CO + O-2, using a molecular beam instrument (MBI). Transient state (TS) and steady state (SS) kinetic details of the above reaction were obtained for a wide range of temperature and beam compositions, especially with O-2-rich compositions. Increasing O-2 content, generally, suppresses (NO)-N-15 reduction in the SS; nonetheless, irrespective of O-2 content, N-15(2) was produced in TS, and to a significant extent under SS conditions too. Sustainable N-2 production between 450 and 600 K and with low to moderate amount of oxygen was observed, and the extent of NO decomposition was also quantified. The ratio of N-15(2): (N2O)-N-15 was generally found to be around 8:1 under most of the reaction conditions. Maxima in the SS reaction rates of all products were observed between 500 and 600 K. Compared to other elementary reaction steps, a slow decay observed with N + N -> N-2 step under SS beam oscillation conditions demonstrates its contribution to the rate limiting nature of the overall reaction. Fast beam switching experiments have been performed alternately between O-2-lean and -rich conditions, thus highlighting the effectiveness of (NO)-N-15 reduction in TS, irrespective of the beam composition. Possibly in a future technology initiative, this aspect could be exploited to manage more (NO)-N-15 reduction on Pd-based catalysts.

Preparation and characterization of magnetic nanoparticles embedded in hydrogels for protein purification and metal extraction - Nagireddy, Narayana Reddy; Yallapu, Murali Mohan; Kokkarachedu, Varaprasad; Sakey, Ravindra; Kanikireddy, Vimala; Alias, Joy Pattayil; Konduru, Mohana Raju (Journal of Polymer Research, 2011)
The present work involves the development of hydrogel magnetic nanocomposites for protein purification and heavy metal extraction applications. The magnetic nanoparticles (MNPs) were prepared in situ in poly(acrylamide)-gum acacia (PAM-GA) hydrogels. The formation of magnetic nanoparticles in the hydrogel networks was confirmed by Fourier transform infrared (FTIR) spectroscopy and X-ray diffraction (XRD). Scanning electron (SEM) microscopy studies revealed the formation of MNPs throughout the hydrogel networks. The average size of MNPs formed in the hydrogel networks was 3-5 nm as determined by transmission electron microscopy (TEM). The thermal properties of the hydrogel magnetic nanocomposites were evaluated by dynamic scanning calorimetry (DSC) and thermogravimetric (TG) analysis. The magnetic properties of the developed hydrogel magnetic nanocomposites were determined by a vibrating sample magnetometer (VSM). The swelling properties of the hydrogel and the hydrogel magnetic nanocomposites were studied in detail. The hydrogel magnetic nanocomposites are utilized for the removal of toxic metal ions such as Co(II), Ni(II), and Cu(II) and for protein purification. The results confirm that the hydrogel magnetic nanocomposites exhibit superior extraction properties to hydrogels.
Keywords: Bioseparation; Hydrogel; magnetic properties; Metal absorption; Nanocomposite

Probing the furanose conformation in the 2 `-5 ` strand of isoDNA:RNA duplexes by freezing the nucleoside conformations - Erande, Namrata D.; Gunjal, Anita D.; Fernandes, Moneesha; Kumar, Vaijayanti A. (Chemical Communications, 2011)
Sugar conformations in the isoDNA strand of isoDNA : RNA duplexes are preferred S-type locked/frozen in contrast to N-type locked conformations preferred in DNA: RNA duplexes.

Propargyl/methyl furanosides as potential glycosyl donors - Vidadala, Srinivasa Rao; Gayatri, Gaddamannugu; Sastry, G. Narahari; Hotha, Srinivas (Chemical Communications, 2011)
Transfuranosylations are not well studied though many similar studies exist for transpyranosylation; herein, we report that propargyl/methyl D-ribf- and D-lyxf- give only 1,2-trans glycosides whereas D-araf- and D-xylf- result in a mixture of 1,2-trans and 1,2-cis glycosides; observed facts are rationalised by computational studies.

Protecting group directed stereoselective reduction of an epi-inosose: efficient synthesis of epi-inositol - Patil, Madhuri T.; Krishnaswamy, Shobhana; Sarmah, Manash P.; Shashidhar, Mysore S. (Tetrahedron Letters, 2011)
A facile and high yielding synthesis of epi-inositol via stereoselective reduction of a pentaprotected epi-inosose is reported. Extent of stereoselectivity during the hydride reduction appears to depend on the ability of the substrate to complex with metal ions in the reducing agent. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Cyclitol; Inositol; Polyol; reduction; Stereoselective

Protic ionic liquid attenuates the deleterious actions of urea on alpha-chymotrypsin - Attri, Pankaj; Venkatesu, Pannuru; Kumar, Anil; Byrne, Nolene (Physical Chemistry Chemical Physics, 2011)
We present a biocompatible ionic liquid, triethyl ammonium acetate (TEAA), that attenuates the denaturation action of a non-ionic chaotrope, urea, on the industrially relevant proteolytic enzyme alpha-chymotrypsin.

Purification and characterization of an alkaline protease by a new strain of Beauveria sp - Shankar, Shiv; Rao, Mala; Laxman, Ryali Seeta (Process Biochemistry, 2011)
A fungal culture isolated from animal dung was identified as a new strain of Beauveria sp MTCC 5184 based on 18S rDNA and ITS nucleotide sequence homology. The fungal isolate secretes alkaline protease active at pH 9 and 50 degrees C. The alkaline protease from Beauveria sp (BAP) was purified to homogeneity with 10.2-folds increase in specific activity and 38.6% recovery. The molecular mass and isoelectric point of the protease were found to be 29 kDa and 9.3, respectively. The N-terminal sequence of the BAP showed only partial homology with subtilisin like proteases from other fungi. The enzyme was stable up to 40 degrees C and pH 3-11. The protease was inhibited by Cd(2+), Hg(2+) and Mn(2+). The activity was totally lost in the presence of 1 mM PMSF suggesting it to be a serine protease. The protease showed maximum activity with casein followed by haemoglobin and BSA. The purified protease is able to separate the endothelial cells and can be used in animal cell culture. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Alkaline Protease; Animal cell culture; Beauveria sp; Sequence homology

Purification and characterization of bacterial aryl alcohol oxidase from sphingobacterium sp ATM and Its uses in textile dye decolorization - Tamboli, Dhawal P.; Telke, Amar A.; Dawkar, Vishal V.; Jadhav, Shekhar B.; Govindwar, Sanjay P. (Biotechnology and Bioprocess Engineering, 2011)
Aryl alcohol oxidase (AAO) produced by dye decolorizing bacteria Sphingobacterium sp. ATM, was purified 22.63 fold to a specific activity of 21.75 mu mol/min/mg protein using anion exchange and size exclusion chromatography. The molecular weight of the purified AAO was found to be 71 kDa using sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), and confirmed by zymography of AAO using L-dopa. The enzyme showed substrate specificity towards veratryl alcohol, followed by n-propanol. The optimum pH and temperature of purified AAO were found to be 3.0 and 40 degrees C, respectively. The K(m) and V(max) of AAO was 1.1615 mM and 3.13 mM/min when veratryl alcohol was used as substrate. Sodium azide showed maximum inhibition while ethylenediamine tetra acetic acid (EDTA), L-cysteine and dithiothreitol showed slight inhibition. Metal ions also showed slight inhibition. HPLC analysis confirmed the degradation of Direct Red 5B. The metabolite obtained after decolorization of Direct Red 5B was characterized as 3 diazenyl 7 [-(phenyl carbonyl) amino] naphthalene-2-sulfonic acid using GC-MS analysis.
Keywords: aryl alcohol oxidase; Direct Red 5B; dye decolorization; ion exchange chromatography; Sphingobacterium sp ATM

Purification, crystallization and preliminary X-ray characterization of a haemagglutinin from the seeds of Jatropha curcas - Nair, Divya N.; Suresh, C. G.; Singh, Desh Deepak (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2011)
The plant Jatropha curcas (Euphorbiaceae) is an important source of biofuel from the inedible oil present in its toxic seeds. The toxicity arises from the presence of curcin, a ribosome-inactivating protein showing haemagglutination activity. In this communication, the purification, crystallization and preliminary X-ray characterization are reported of a small protein isolated from J. curcas seeds with a molecular mass of 10 kDa that agglutinates rabbit erythrocytes. The protein was crystallized using the hanging-drop vapour-diffusion method and also by the microbatch method in 72-well HLA plates, using PEG 8000 as the precipitant in both conditions. X-ray diffraction data collected from the rod-shaped crystals were processed in the orthorhombic space group P212121. The crystals diffracted to 2.8 angstrom resolution at 103 K.
Keywords: haemagglutinins; Jatropha curcas

Purification, crystallization and X-ray characterization of a Kunitz-type trypsin inhibitor protein from the seeds of chickpea (Cicer arietinum) - Sharma, Urvashi; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2011)
{A Kunitz-type trypsin inhibitor protein (CPTI) purified from chickpea seeds was estimated to have a molecular mass of 18 kDa on SDS-PAGE. The IC50 value of CPTI was determined to be 2.5 mu g against trypsin. The inhibitory activity of CPTI is 114 TIU (trypsin inhibitory units) per milligram of protein, which is high compared with those of other known Kunitz-type trypsin inhibitors from legumes. CPTI crystallized in three different orthorhombic crystal forms: P2(1)2(1)2 form A, P2(1)2(1)2 form B and P2(1)2(1)2(1). The crystals of P2(1)2(1)2 form angstrom, with unit-cell parameters a = 37.2

Palladium-catalyzed routes to geranylated or farnesylated phenolic stilbenes: synthesis of pawhuskin C and schweinfurthin J - Singh, Mandeep; N. P. Argade (Synthesis-Stuttgart, 2012)
Starting from double MOM-protected phloroglucinol, the facile total syntheses of bioactive natural products pawhuskin C and schweinfurthin J were accomplished in good overall yields. The Heck, Stille, or Suzuki coupling reactions of two different electron-rich phenolic segments bearing geranylated or farnesylated units were involved in the decisive step. The Sonogashira coupling reaction followed by palladium-catalyzed chemo-and stereoselective cis-reduction of an alkyne unit and subsequent isomerization to give the desired natural products is also described.
Keywords: geranylated or farnesylated stilbenes; Natural products; palladium-catalyzed coupling reactions; phloroglucinol; Total synthesis

Pd-Catalyzed imine cyclization: synthesis of antimalarial natural products aplidiopsamine A, marinoquinoline A, and their potential hybrid NCLite-M1 - Mahajan, Jyoti P.; Suryawanshi, Yogeshwar R.; Mhaske, Santosh B. (Organic Letters, 2012)
Palladium-catalyzed cyclization of imines has been developed to construct the extremely rare 3H-pyrrolo[2,3-c]quinoline ring system for diversity oriented first total synthesis of antimalarial marine natural product Aplidiopsamine A as well as synthesis of Marinoquinoline A and potential natural product hybrid NCLite-M1.

Pd-catalyzed selective hydrosilylation of aryl ketones and aldehydes - Chouthaiwale, Pandurang V.; Rawat, Varun; Sudalai, Arumugam (Tetrahedron Letters, 2012)
Pd salts in combination with triethylsilane as hydride source and DMF as solvent has been found to be excellent catalytic combination that selectively reduces aryl ketones and aldehydes under mild conditions to afford triethylsilyloxy compounds in excellent yields. Product selectivity to the respective benzyl alcohols can however be achieved when the reaction was performed in DMF/H2O (4:1) as solvent system. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: aldehydes; Hydrosilylation; Ketones; Palladium; Triethylsilane

pH Sensitive graft copolymers for zero order drug release: a mechanistic analysis - Muthusamy, Ramesh; Kulkarni, Mohan Gopalkrishna (Drug Development and Industrial Pharmacy, 2012)
Aliphatic polyesters containing pendent unsaturation were synthesized by the polycondensation of a diol, dicarboxylic acid and glycidyl methacrylate. Grafting methacrylic acid (MAA) resulted in graft copolymers containing polyester backbone and MAA grafts. Depending on composition, the polymers swelled extensively and eroded or dissolved at near neutral pH but remained in collapsed state at acidic pH. Three representative drugs differing in solubility, viz., Diltiazem hydrochloride (DH), Indomethacin (IM) and Verapamil hydrochloride (VH) were released at constant rate from tablets made by compressing spray-dried microparticles. The release of DH at constant rate has been attributed to increase in diffusion coefficient of the drug from the swollen layer of matrix. The release of IM and VH at constant rate was governed by erosion and was enhanced in matrices which undergo dissolution. The release rate was enhanced with increasing MAA content and the frequency of grafts along the polyester backbone. Once a day dosage forms for drugs differing in solubility have been developed using a single polymer matrix which is easy to manufacture.
Keywords: Diffusion; erosion; Graft copolymer; matrix tablets; microparticles; spray drying; sustained release

Photocatalytic degradation of Azo dyes using Au:TiO2, gamma-Fe2O3:TiO2 functional nanosystems - Jagadale, Tushar C.; Kulkarni, Manjusha; Pravarthana, D.; Ramadan, Wegdan; Thakur, Pragati (Journal of Nanoscience and Nanotechnology, 2012)
We report photocatalytic degradation studies on Navy Blue HE2R (NB) dye on significant details as a representative from the class of azo dyes using functional nanosystems specifically designed to allow a strong photocatalytic activity. A modified sol-gel route was employed to synthesize Au and gamma-Fe2O3 modified TiO2 nanoparticles (NPs) at low temperature. The attachment strategy is better because it allows clear surface of TiO2 to remain open for photo-catalysis. X-ray diffraction, Raman and UV-VIS spectroscopy studies showed the presence of gold and iron oxide phases along-with the anatase TiO2 phase. TEM studies showed TiO2 nanocomposite particles of size similar to 10-12 nm. A detailed investigation on heterogeneous photocatalytic performance for Navy Blue HE2R dye was done using the as-synthesized catalysts Au:TiO2 and gamma-Fe2O3:TiO2 in aqueous suspension under 8 W low-pressure mercury vapour lamp irradiation. Also, the photocatalytic degradation of Amranth and Orange G azo dyes were studied. The surface modified TiO2 NPs showed significantly improved photocatalytic activity as compared to pure TiO2. Exposure of the dye to the UV light in the presence of pure and gold NPs attached TiO2 catalysts caused dye degradation of about similar to 20% and similar to 80%, respectively, in the first couple of hours. In the presence of gamma-Fe2O3 NPs attached TiO2, a remarkable similar to 95% degradation of the azo dye was observed only in the first 15 min of UV exposure. The process parameters for the optimum catalytic activity are established which lead to a complete decoloration and substantial dye degradation, supported by the values of the Chemical Oxygen Demand (COD) similar to 93% and Total Organic Carbon (TOC) similar to 65% of the treated dye solution after 5 hours on the employment of the UV/Au:TiO2/H2O2 photocatalytic process.
Keywords: Azo Dye; COD; H2O2; Photocatalysis; TiO2

Photocatalytic degradation of phenolics by N-doped mesoporous titania under solar radiation - Mangrulkar, Priti A.; Kamble, Sanjay P.; Joshi, Meenal M.; Meshram, Jyotsna S.; Labhsetwar, Nitin K.; Rayalu, Sadhana S. (International Journal of Photoenergy, 2012)
In this study, nitrogen-doped mesoporous titania was synthesized by templating method using chitosan. This biopolymer chitosan plays the dual role of acting as a template (which imparts mesoporosity) and precursor for nitrogen. BET-SA, XRD, UV-DRS, SEM, and FTIR were used to characterize the photocatalyst. The doping of nitrogen into TiO2 lattice and its state was substantiated and measured by XPS. The photocatalytic activity of the prepared N-doped mesoporous titania for phenol and o-chlorophenol degradation was investigated under solar and artificial radiation. The rate of photocatalytic degradation was observed to be higher for o-chlorophenol than that of phenol. The photodegradation of o-chlorophenol was 98.62% and 72.2%, while in case of phenol, degradation to the tune of 69.25% and 30.58% was achieved in solar and artificial radiation. The effect of various operating parameters, namely, catalyst loading, pH, initial concentration and the effect of coexisting ions on the rate of photocatalytic degradation were studied in detail.

Photocatalytic degradation of phosphamidon using Ag-doped ZnO nanorods - Korake, Prakash V.; Sridharkrishna, R.; Hankare, P. P.; Garadkar, K. M. (Toxicological and Environmental Chemistry, 2012)
The photocatalytic degradation of the organo-phosphorous pesticide phosphamidon at low concentration in aqueous solution on Ag-doped ZnO nanorods was investigated. Nanosized Ag-doped ZnO rods were synthesized by using a microwave assisted aqueous method. High molecular weight polyvinyl alcohol was used as a stabilizing agent. Composition and structure were investigated using energy-dispersive X-ray spectroscopy (EDAX) and X-ray diffraction (XRD). The XRD pattern reveals that ZnO nanorods are of hexagonal wurtzite structure. The average crystallite size calculated from Scherrer's relation was found to be 30 nm. The effects of catalyst loading, pH value, and initial concentration of phosphamidon on the photocatalytic degradation efficiency using Ag-doped ZnO nanorods as a photocatalyst have been discussed. The results revealed that Ag-doped ZnO nanorods with a diameter of 30 nm showed highest photocatalytic activity at a surface density of 1 g dm(-3). The catalyst doped with 0.2 mol% Ag is effective for the degradation of phosphamidon with visible light. This opens a new possibility to decompose pesticides that are present in wastewater.
Keywords: Ag-doped zinc oxide; phosphamidon; Photocatalysis; Photodegradation

Photopatternable nano-composite (SU-8/ZnO) thin films for piezo-electric applications - Kandpal, Manoj; Sharan, Chandrashekhar; Poddar, Pankaj; Prashanthi, K.; Apte, Prakash R.; Rao, V. Ramgopal (Applied Physics Letters, 2012)
Photo-curable nanocomposite material was formulated by embedding ZnO nanoparticles into a SU-8 matrix and studied for its piezoelectric properties for low cost fabrication of self-powered nanodevices. The piezoelectric coefficient of ZnO nanoparticles was observed to be ranging between 15 and 23 pm/V, which is the highest reported. These experimental studies support the recent theoretical predictions where the piezoelectric coefficients in ZnO nanoparticles were found to be higher compared to the thin films because of the surface relaxation induced volume reductions in the nanometer scale. The photo-curable property of these polymer composite films is exploited to demonstrate fabrication of a micro-cantilever test structure. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4748575]

Photopolymerization kinetics of 2-phenylethyl (meth) acrylates studied by photo DSC - Ghorpade, Ravindra V.; Bhosle, Sonali Madhavrao; Ponrathnam, S.; Rajan, C. R.; Chavan, Nayaku; Harikrishna, Reghunathan (Journal of Polymer Research, 2012)
The present work deals with the photopolymerization of 2-phenylethyl (meth)acrylates and estimation of their kinetic parameters. Formulations were made by independently homogenizing the monomers with photoinitiators of two different classes. Two different compositions of photoinitiators were used to study the effect of concentration of photoinitiator on cure kinetics. These compositions obtained were tested for photo curing performance using differential photocalorimetry (DPC) or photo DSC under polychromatic radiation. The heat flow against time was recorded for all formulations under isothermal conditions and the rates of polymerization as well as the percentage conversions were estimated. It was observed that due to a longer timescale for reaction diffusion, the methacrylate formulations showed a higher conversion than acrylate formulations. Other parameters such as induction time, maximum rate and conversion attained as well as the time to attain peak maximum were noted. The photopolymerization and kinetic estimations of the formulations including evaluation of kinetic models are discussed.
Keywords: Bimolecular termination model; Photo DSC; Photopolymerization; Variable autocatalytic model

Photosensitization of nanoparticulate TiO2 using a Re(I)-polypyridyl complex: studies on interfacial electron transfer in the ultrafast time domain - Kar, Prasenjit; Banerjee, Tanmay; Verma, Sandeep; Sen, Anik; Das, Amitava; Ganguly, Bishwajit; Ghosh, Hirendra N. (Physical Chemistry Chemical Physics, 2012)
We have synthesized a new photoactive rhenium(I)-complex having a pendant catechol functionality [Re(CO)3Cl(L)] (1) (L is 4-[2-(4′-methyl-2,2′-bipyridinyl-4-yl)vinyl]benzene-1,2-diol) for studying the dynamics of the interfacial electron transfer between nanoparticulate TiO2 and the photoexcited states of this Re(I)-complex using femtosecond transient absorption spectroscopy. Our steady state absorption studies revealed that complex 1 can bind strongly to TiO2 surfaces through the catechol functionality with the formation of a charge transfer (CT) complex, which has been confirmed by the appearance of a new red-shifted CT band. The longer wavelength absorption band for 1, bound to TiO2 through the proposed catecholate functionality, could also be explained based on the DFT calculations. Dynamics of the interfacial electron transfer between 1 and TiO2 nanoparticles was investigated by studying kinetics at various wavelengths in the visible and near infrared regions. Electron injection into the conduction band of the nanoparticulate TiO2 was confirmed by detection of the conduction band electron in TiO2 (Image ID:c2cp24105f-t1.gif) and the cation radical of the adsorbed dye (1˙+) in real time as monitored by transient absorption spectroscopy. A single exponential and pulse-width limited (<100 fs) electron injection was observed. Back electron transfer dynamics was determined by monitoring the decay kinetics of 1˙+ and Image ID:c2cp24105f-t2.gif.

Phyllocladane diterpenes from anisomeles heyneana - Kulkarni, Roshan R.; Shurpali, Ketaki; Gawade, Rupesh L.; Sarkar, Dhiman; Puranik, Vedavati G.; Joshi, Swati P. (Journal of Asian Natural Products Research, 2012)
New phyllocladane diterpene, phyllocladan-16 alpha,17-dihydroxy-19-oic acid (1), together with known phyllocladane diterpene, phyllocladan-16 alpha,19-diol (2), cembrane diterpene ovatodiolide (3), sitosteryl-3-O-beta-D-glucoside (4), and verbascoside (5), were isolated from aerial parts of Anisomeles heyneana. The structure of compound 1 was elucidated by 1D and 2D NMR analyses which included HSQC, HMBC, and nuclear overhauser effect spectroscopy (NOESY) experiments as well as X-ray crystallography. This is the first report of phyllocladane diterpenes from genus Anisomeles. Compounds 1, 3, 4, and 5 were evaluated for inhibition of Mycobacterium tuberculosis and 3 was found to exhibit anti-mycobacterial activity with IC90 6.53 mu g/ml. Compounds 1, 3, and 5, at 100 mu g/ml, were also evaluated for inhibition of Thp-1 cell lines, and compounds 1 and 3 showed 59.02% and 96.4% inhibitions, respectively.
Keywords: Anisomeles heyneana; Lamiaceae; Mycobacterium tuberculosis; phyllocladane diterpenes

Phylogenomic analysis of UDP glycosyltransferase 1 multigene family in Linum usitatissimum identified genes with varied expression patterns - Barvkar, Vitthal T.; Pardeshi, Varsha C.; Kale, Sandip M.; Kadoo, Narendra Y.; Gupta, Vidya S. (BMC Genomics, 2012)
Background: The glycosylation process, catalyzed by ubiquitous glycosyltransferase (GT) family enzymes, is a prevalent modification of plant secondary metabolites that regulates various functions such as hormone homeostasis, detoxification of xenobiotics and biosynthesis and storage of secondary metabolites. Flax (Linum usitatissimum L.) is a commercially grown oilseed crop, important because of its essential fatty acids and health promoting lignans. Identification and characterization of UDP glycosyltransferase (UGT) genes from flax could provide valuable basic information about this important gene family and help to explain the seed specific glycosylated metabolite accumulation and other processes in plants. Plant genome sequencing projects are useful to discover complexity within this gene family and also pave way for the development of functional genomics approaches. Results: Taking advantage of the newly assembled draft genome sequence of flax, we identified 137 UDP glycosyltransferase (UGT) genes from flax using a conserved signature motif. Phylogenetic analysis of these protein sequences clustered them into 14 major groups (A-N). Expression patterns of these genes were investigated using publicly available expressed sequence tag (EST), microarray data and reverse transcription quantitative real time PCR (RT-qPCR). Seventy-three per cent of these genes (100 out of 137) showed expression evidence in 15 tissues examined and indicated varied expression profiles. The RT-qPCR results of 10 selected genes were also coherent with the digital expression analysis. Interestingly, five duplicated UGT genes were identified, which showed differential expression in various tissues. Of the seven intron loss/gain positions detected, two intron positions were conserved among most of the UGTs, although a clear relationship about the evolution of these genes could not be established. Comparison of the flax UGTs with orthologs from four other sequenced dicot genomes indicated that seven UGTs were flax diverged. Conclusions: Flax has a large number of UGT genes including few flax diverged ones. Phylogenetic analysis and expression profiles of these genes identified tissue and condition specific repertoire of UGT genes from this crop. This study would facilitate precise selection of candidate genes and their further characterization of substrate specificities and in planta functions.

Phytosynthesis of intracellular and extracellular gold nanoparticles by living peanut plant (Arachis hypogaea L.) - Raju, Dugyala; Mehta, Urmil J.; Ahmad, Absar (Biotechnology and Applied Biochemistry, 2012)
Inorganic nanomaterials of different chemical compositions are conventionally synthesized under harsh environments such as extremes of temperature, pressure, and pH. Moreover, these methods are eco-unfriendly and cumbersome, yield bigger particles, and agglomerate because of not being capped by capping agents. In contrast, biological synthesis of inorganic nanomaterials occurs under ambient conditions, namely room temperature, atmospheric pressure, and physiological pH. These methods are reliable, eco-friendly, and cheap. In this paper, we report for the first time the extracellular and intracellular synthesis of gold nanoparticles (GNPs) using living peanut seedlings. The formed GNPs were highly stable in solution and inside the plant tissue. Transmission electron microscopy revealed that extracellular GNPs distributions were in the form of monodispersed nanoparticles. The nanoparticles ranged from 4 to 6 nm in size. The intercellular nanoparticles were of oval shape and size ranged from 5 to 50 nm. Both extracellular and intracellular nanoparticles were further characterized by standard techniques. The formed GNPs inside the plant tissue were estimated by inductively coupled plasma spectrometry. This opens up an exciting possibility of a plant-based nanoparticle synthesis strategy, wherein the nanoparticles may be entrapped in the biomass in the form of a film or produced in the solution, both of which have interesting applications.
Keywords: cells; extracellular; living plant; Peanut; root; TEM

Poly(allyl glycidyl ether-co-ethylene glycol dimethacrylate) copolymer beads as support for covalent immobilization of L-aminoacylase - Vaidya, Bhalchandra K.; Ingavle, Ganesh C.; Ponrathnam, S.; Nene, Sanjay N. (Reactive & Functional Polymers, 2012)
Porous epoxy-activated copolymer beads were synthesized as support for the covalent immobilization of Aspergillus melleus L-aminoacylase. Here, a series of copolymer bead were synthesized using either glycidyl methacrylate (GMA) or ally] glycidyl ether (AGE) as monomer units and ethylene glycol dimethacrylate (EGDM) as cross-linking agent. The effect of monomer used and the effect of amount of cross-linking agent on covalent immobilization of aminoacylase were studied. Furthermore, the effect of porogen on immobilization of aminoacylase was also evaluated. AGE-co-EGDM copolymer beads gave higher binding of aminoacylase than GMA-co-EGDM copolymer beads. AGE-co-EGDM copolymer beads synthesized with lauryl alcohol as porogen and having 150% cross-linked density (i.e. AGE-(L)-150) gave maximum enzyme binding. Under optimum conditions, AGE-(L)-150 copolymer beads gave about 130 U/g of aminoacylase activity which corresponds to 72.24% of activity yield. Immobilized aminoacylase showed a broader pH, higher temperature and extended storage stability. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Enzyme immobilization; Epoxy-activated support; L-Aminoacylase

Polybenzimidazole mediated N-doping along the inner and outer surfaces of a carbon nanofiber and its oxygen reduction properties - Balan, Beena K.; Manissery, Aiswarya Padinhare; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar (Journal of Materials Chemistry, 2012)
Nitrogen-doped (N-doped) hollow carbon nanofiber (CNF) was synthesized by incorporating a nitrogen containing polymer precursor, polybenzimidazole (PBI-BuI), in the inner cavity as well as on the outer walls of the CNF, followed by a high temperature treatment. PBI-BuI incorporation along the inner and outer surface of the CNF was accomplished by synthesizing a low molecular weight polymer by tuning the synthetic parameters. The solution concentration of the PBI-BuI is also varied to facilitate its entry into the CNF by capillary action. The high temperature treatment (700-1000 degrees C) of the resulting CNF-PBI material decomposes the polymer and induces N-doping along the inner and outer surfaces of the CNF. The initial PBI-BuI content and the annealing temperature are also systematically varied to choose the right combination of starting precursors and heat-treatment conditions. Detailed X-ray photoelectron spectroscopy analysis of the samples shows that pyridinic-type nitrogen is the major component in all the samples. Electrochemical characterizations of this material using cyclic voltammetry, rotating disc electrode studies and durability analysis demonstrated that this material can act as a metal-free oxygen reduction electrocatalyst with improved oxygen reduction kinetics and stability. It is also revealed that the onset potential, limiting current density, number of transferred electrons, etc. have a strong dependence on the annealing temperature.

Polymeric ionic liquids (PILs): effect of anion variation on their CO2 sorption - Bhavsar, Rupesh S.; Kumbharkar, Santosh C.; Kharul, Ulhas K. (Journal of Membrane Science, 2012)
A series of polymeric ionic liquids (PILs) based on poly(diallyldimethylammonium chloride), P[DADMA][Cl] as a precursor was investigated by varying anions categorized into carboxylates, sulphonates and inorganic type. For the exchange of chloride from P[DADMA][Cl] by another anion, silver salt of the corresponding anion was preferred. Obtained PILs were investigated for physical properties which are anticipated to affect gas sorption. PILs possessing carboxylate (especially acetate) anion exhibited attractive CO2 sorption capacity as well as sorption selectivity over H-2 and N-2, in Comparison to Other two Categories. PIL with acetate anion, P[DADMA][Ac] possessed appreciable CO2 sorption coupled with high selectivity (S-CO2/S-N2 = 114.3). This crucial finding from this series of PILs was further substantiated by making PIL based on poly(vinylbenzyltrimethylammonium chloride), P[VBTMA][Cl] as a precursor. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Anion exchange; CO2 sorption; Polymeric ionic liquid

Polymorphs, salts, and cocrystals: what's in a name? - Aitipamula, Srinivasulu; Banerjee, Rahul; Bansal, Arvind K.; Biradha, Kumar; Cheney, Miranda L.; Choudhury, Angshuman Roy; Desiraju, Gautam R.; Dikundwar, Amol G.; Dubey, Ritesh; Duggirala, Nagakiran; Ghogale, Preetam P.; Ghosh, Soumyajit; et al. (Crystal Growth & Design, 2012)
The December 2011 release of a draft United States Food and Drug Administration (FDA) guidance concerning regulatory classification of pharmaceutical cocrystals of active pharmaceutical ingredients (APIs) addressed two matters of topical interest to the crystal engineering and pharmaceutical science communities: (1) a proposed definition of cocrystals; (2) a proposed classification of pharmaceutical cocrystals as dissociable ``API-excipient'' molecular complexes. The Indo U.S. Bilateral Meeting sponsored by the Indo-U.S. Science and Technology Forum titled The Evolving Role of Solid State Chemistry in Pharmaceutical Science was held in Manesar near Delhi, India, from February 2-4, 2012. A session of the meeting was devoted to discussion of the FDA guidance draft. The debate generated strong consensus on the need to define cocrystals more broadly and to classify them like salts. It was also concluded that the diversity of API crystal forms makes it difficult to classify solid forms into three categories that are mutually exclusive. This perspective summarizes the discussion in the Indo-U.S. Bilateral Meeting and includes contributions from researchers who were not participants in the meeting.

Polymorphs, salts and cocrystals: what's in a name? (vol 12, pg 2147, 2012) - Aitipamula, Srinivasulu; Banerjee, Rahul; Bansal, Arvind K.; Biradha, Kumar; Cheney, Miranda L.; Choudhury, Angshuman Roy; Desiraju, Gautam R.; Dikundwar, Amol G.; Dubey, Ritesh; Duggirala, Nagakiran; Ghogale, Preetam P.; Ghosh, Soumyajit; et al. (Crystal Growth & Design, 2012)

Porous ZnO nanorod for targeted delivery of doxorubicin: in vitro and in vivo response for therapeutic applications - Mitra, Shouvik; Subia, B.; Patra, Prasun; Chandra, Sourov; Debnath, Nitai; Das, Sumistha; Banerjee, Rahul; Kundu, Subhas C.; Pramanik, Panchanan; Goswami, Arunava (Journal of Materials Chemistry, 2012)
Cancer cell specific targeted delivery (TDD) by porous nanocarrier is on a high role. Here in a simple route for the synthesis of porous ZnO nanorods (ZnO) has been demonstrated. ZnO expressed very high surface area of 305.14 m(2) g(-1) (S-BET) and uniformly distributed pores of 5 nm. In continuation ZnO has been fabricated with 3-aminophosphonic acid followed by folic acid to yield folate conjugated porous ZnO nanorod (ZnO-FA). High surface area, uniformly distributed pores on its surface make the nanocarrier suitable for high drug loading (88%) of the anticancer drug doxorubicin (DOX). A pH triggered drug release was observed with minimum release in pathophysical conditions. In vitro efficacy of DOX loaded ZnO-FA (ZnO-FA-DOX) has been evaluated against breast cancer cells MDA-MB-231, which is not possible alone by DOX or ZnO-FA. Targeted scaffold with pendant -NH2 group has been covalently bonded with fluorescent dye (RITC) for cellular uptake and imaging studies in MDA-MB-231 cells; the possible pathway for cancer regression has also been evaluated. Even in vivo acute and intravenous toxicological evaluation on murine model system complemented biocompatibility of ZnO-FA in TDD. All together we have collaged a template free synthesis of porous ZnO nanorod, successful targeting on to cancer cells, high drug loading, pH triggered drug release, in vitro efficacy of ZnO-FA-DOX against MDA-MB-231 cells and in vivo compatibility as well. We envisioned the future prospect of porous ZnO nanostructures in TDD.

Potential use of nitrate reductase as a biomarker for the identification of active and dormant inhibitors of mycobacterium tuberculosis in a THP1 infection model - Sarkar, Sampa; Sarkar, Dhiman (Journal of Biomolecular Screening, 2012)
The development of a macrophage-based, antitubercular high-throughput screening system could expedite discovery programs for identifying novel inhibitors. In this study, the kinetics of nitrate reduction (NR) by Mycobacterium tuberculosis during growth in Thp1 macrophages was found to be almost parallel to viable bacilli count. NR in the culture medium containing 50 mM of nitrate was found to be optimum on the fifth day after infection with M. tuberculosis. The signal-to-noise (S/N) ratio and Z-factor obtained from this macrophage-based assay were 5.4 and 0.965, respectively, which confirms the robustness of the assay protocol. The protocol was further validated by using standard antitubercular inhibitors such as rifampicin, isoniazid, streptomycin, ethambutol, and pyrazinamide, added at their IC90 value, on the day of infection. These inhibitors were not able to kill the bacilli when added to the culture on the fifth day after infection. Interestingly, pentachlorophenol and rifampicin killed the bacilli immediately after addition on the fifth day of infection. Altogether, this assay protocol using M. tuberculosis-infected Thp-1 macrophages provides a novel, cost-efficient, robust, and easy-to-perform screening platform for the identification of both active and hypoxic stage-specific inhibitors against tuberculosis.
Keywords: high-throughput screening; inhibitor; Mycobacterium tuberculosis; nitrate reductase; THP1

Practical and general diels-alder reaction of pentafulvenes with arynes - Bhojgude, Sachin Suresh; Kaicharla, Trinadh; Bhunia, Anup; Biju, Akkattu T. (Organic Letters, 2012)
A high-yielding, versatile and practical Diels–Alder reaction of pentafulvenes with arynes under mild reaction conditions is reported. The aryne generated by the fluoride induced 1,2-elimination of 2-(trimethylsilyl)aryl triflates undergoes efficient cycloaddition with 6-substituted and 6,6-disubstituted pentafulvenes leading to the formation of benzonorbornadiene derivatives.

Practical and highly efficient protocol for multicomponent synthesis of beta-phosphonomalononitriles and 2-amino-4H-chromen-4-yl phosphonates using diethylamine as a novel organocatalyst - Kulkarni, M. A.; Pandurangi, V. R.; Desai, Uday V.; Wadgaonkar, P. P. (Comptes Rendus Chimie, 2012)
Diethylamine has been demonstrated for the first time to be a highly efficient organocatalyst in the solvent-free synthesis of beta-phosphonomalononitriles by a three component condensation of aldehyde, malononitrile and dialkyl phosphite at ambient temperature. The applicability of the same catalyst in the synthesis of diethyl (2-amino-3-cyano-chromene-4-yl) phosphonic acid esters has also been described. (c) 2012 Published by Elsevier Masson SAS on behalf of Academie des sciences.
Keywords: 2-amino-4H-chromenes; beta-phosphonomalononitriles; diethylamine; multicomponent reactions; organocatalyst; Phospha-Michael reaction

Practical syntheses of proposed and revised manzacidin B and their congeners - Sankar, Kuppusamy; Rahman, Hasibur; Das, Pragna P.; Bhimireddy, Eswar; Sridhar, B.; Mohapatra, Debendra K. (Organic Letters, 2012)
A concise and highly stereoselective total synthesis of manzacidin B and its congeners has been developed following chelation-controlled syn-epoxidation and Lewis acid catalyzed intramolecular regioselective epoxide ring opening to generate the quarternary amine center. Elaboration of the triol moiety to the target molecule was achieved in good overall yield, representing practical total syntheses of manzacidin B and its congeners. From the XRD, NMR, and analytical data, the correct structure of natural manzacidin B, (4R,5R,6R)-6, was confirmed.

Prediction of structure and energy of trans-1,4-polybutadiene glassy surface by atomistic simulations of free-standing ultrathin films - Ijantkar, Ashwini S.; Natarajan, Upendra (Journal of Macromolecular Science Part B-Physics, 2012)
Atomistic modeling of amorphous trans-1,4-polybutadiene (TPBD), using molecular mechanics and molecular dynamics (MD) simulations, is performed to generate three-dimensionally periodic bulk and two-dimensionally periodic thin film condensed phases. The condensed structures are constructed using multiple polymer chains. Structural and energetic relaxations and sampling of properties are performed using MD in the canonical ensemble (NVT) by a procedure that relieves local high-energy spots and brings the system to realistic thermodynamic states. The calculated surface energy for TPBD, 30.72 erg/cm(2), is in excellent agreement with the reported experimental value of 31 erg/cm(2). The structure of the surface layers is probed in terms of the atomic mass density variations, bond-bond orientation function profiles, and the distribution of the dihedral angles about the rotatable backbone bonds. The thickness of the surface layer over which the density varies smoothly but rapidly is found to be approximately 15 angstrom. The level of agreement of the calculated surface energy with the experimental value is superior in comparison to previous investigations in the literature using the atomistic approach for flexible polymers.
Keywords: 4-polybutadiene; atomistic simulation; bond-orientation; Conformation; molecular dynamics; polymer glass; surface energy; trans-1

Preferential oxidation of CO on Ni/CeO2 catalysts in the presence of excess H-2 and CO2 - Malwadkar, Sachin S.; Bera, Parthasarathi; Hegde, M. S.; Satyanarayana, C. V. V. (Reaction Kinetics Mechanisms and Catalysis, 2012)
Preferential oxidation of CO (CO-PROX) was carried out over Ni supported on CeO2 prepared by the co-precipitation method. The influence of metal loadings (2.5, 5 and 10 wt.% Ni) and the reaction conditions such as reaction temperature and feed composition on CO oxidation and oxidation selectivity were evaluated by using dry reformate gas. No other reactions like CO or CO2 methanation, coking, reverse water gas shift (RWGS) reaction is observed in the temperature range of 100-200 A degrees C on these catalysts. Hydrogen oxidation dominates over CO oxidation above the temperature of 200 A degrees C. An increase in oxygen leads to an increase in CO conversion but a simultaneous decrease in the O-2 selectivity. It has been noticed that 5 and 10 % Ni/CeO2 show better catalytic activity towards CO-PROX reaction. These catalysts were characterized by S-BET, XRD, TEM, XPS and H-2-TPR.
Keywords: CeO2; CO-PROX; fuel cells; Methanation; Ni

Preparation and characterization of calcium silicate for CO2 sorption - Kale, Kishor B.; Raskar, Reshma Y.; Rane, Vilash H.; Gaikwad, Abaji G. (Adsorption Science & Technology, 2012)
An attempt has been made to develop different samples of calcium silicate and to screen these samples for CO2 sorption and alkalinity in order to achieve maximum CO2 sorption. The CO2 sorption capacity of these samples was examined at different temperatures. Various methods such as solid-solid fusion, sol-gel, molten salt and templates (CTAB, cetyltrimethylammonium bromide or Aliquat 336, tricaprylmethylammonium chloride) were used to prepare the calcium silicate samples. The solid mass of calcium silicate samples were obtained by calcining the solid product obtained in an atmosphere of air or helium at 900 degrees C for 3 hours. The calcium silicate samples were characterized for surface area, alkalinity, scanning electron microscopic images and X-ray diffraction patterns. The temperature profile of CO2 sorption by calcium silicate was studied in the temperature range of 40-850 degrees C. Our results showed that the alkalinity and surface area of calcium silicate were in the range from 2.35 to 20 mmol g(-1) and 1.4 to 10 m(2) g(-1), respectively. The sorption of CO2 at 500 degrees C over calcium silicate for the different Ca/Si mol ratio (range: 1-6) was found to be in the range from 3.12 to 29.96 wt%. Addition of a promoter such as sodium, potassium, caesium and lanthanum was found to enhance the sorption of CO2 by calcium silicate. Several samples of different mol ratios of Ca/Si prepared by different methods were tested for the sorption of CO2 at 500 degrees C.

Preparation of cross-linked enzyme aggregates of L-aminoacylase via co-aggregation with polyethyleneimine - Vaidya, Bhalchandra K.; Kuwar, Suyog S.; Golegaonkar, Sandeep B.; Nene, Sanjay N. (Journal of Molecular Catalysis B-Enzymatic, 2012)
L-Aminoacylase from Aspergillus melleus was co-aggregated with polyethyleneimine and subsequently cross-linked with glutaraldehyde to obtain aminoacylase-polyethyleneimine cross-linked enzyme aggregates (termed as AP-CLEA). Under the optimum conditions, AP-CLEA expressed 74.9% activity recovery and 81.2% aggregation yield. The said method of co-aggregation and cross-linking significantly improved the catalytic stability of L-aminoacylase with respect to temperature and storage. AP-CLEA were employed for enantioselective synthesis of three unnatural amino acids (namely: phenylglycine, homophenylalanine and 2-naphthylalanine) via chiral resolution of their ester-. amide- and N-acetyl derivatives. The enantioselectivity of AP-CLEA was the highest for hydrolysis of amino acid amides; was moderate for hydrolysis of N-acetyl amino acids and was the least for hydrolysis of amino acid esters. Furthermore, AP-CLEA were found to retain more than 92% of the initial activity after five consecutive batches of (RS)-homophenylalanine hydrolysis suggesting an adequate operational stability of the biocatalyst. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: chiral resolution; Cross-linked enzyme aggregates; L-Aminoacylase; Polyethyleneimine; Unnatural amino acids

Preparation of pure methyl esters from corresponding alkali metal salts of carboxylic acids using carbon dioxide and methanol - Barve, Prashant P.; Kamble, Sanjay P.; Joshi, Jyeshtharaj B.; Gupte, Milind Y.; Kulkarni, Bhaskar D. (Industrial & Engineering Chemistry Research, 2012)
In the present article, for the first time, we report the synthesis of alkyl esters by direct esterification of alkali metal salts of carboxylic acids using carbon dioxide and alcohol. Methyl acetate, methyl benzoate, methyl salicylate, and methyl lactate have been synthesized by esterification of sodium acetate, sodium benzoate, sodium salicylate, and calcium lactate, respectively. The esterification reaction was carried out in a batch as well as in a semicontinuous mode of operation. A detailed study on the esterification of calcium lactate using methanol and carbon dioxide was carried out to record the effects of various operating parameters (like CO2 pressure, reaction temperature, moisture content in the calcium lactate, and initial concentrations of calcium lactate) on the esterification reaction. This synthesis route produces highly pure methyl lactate by direct esterification of calcium lactate with calcium carbonate as byproduct. The byproduct calcium carbonate was characterized for its crystallinity, surface area, and pore volume. The process route has the advantage that the synthesized byproduct can be recycled into the fermenter to make corresponding alkali metal lactate or the finely precipitated calcium carbonate can be used for various other applications. Thus, the recovery and recycle of alkali metal is possible providing a pollution free process for synthesis of pure methyl lactate.

Preparation of spherical particles of 1,1-diamino-2,2-dinitroethene (FOX-7) using a micellar nanoreactor - Mandal, Alok Kumar; Thanigaivelan, U.; Pandey, Raj Kishore; Asthana, Srinandan; Khomane, Ramdas B.; Kulkarni, Bhaskar Dattatraya (Organic Process Research & Development, 2012)
The need and preparation of spherical 1,1-diamino-2,2-dinitroethene (FOX-7) particles to meet certain special applications in high explosives and propellant formulation have been illustrated. Preparation of spherical FOX-7 particles by using a microemulsion technique has not been reported in the literature. In the present study, the preparation of spherical FOX-7 particles has been described using the novel concept of a micelle-based nanoreactor. Micelle-based nanoreactors have been prepared using a microemulsion of Triton X-100, cyclohexane, and water. Formation of spherical FOX-7 particles in the reverse micelle reactors have been described in the subsequent sections of this article. It is observed that spherical particles of FOX-7 are formed within 2 h in the microemulsion media. Analysis of the experimental results revealed that the particle size and shape of FOX-7 can be varied by changing the water/surfactant molar ratio in the microemulsion. Spherical particles synthesized by this method have diameters that are generally in the submicrometer to nanometer range. Impact sensitivity (h(50)) of the spherical particles obtained by the fall-hammer method is around 45 cm compared to regular synthesized FOX-7 (i.e., 50 +/- 5 cm) without any change in friction sensitivity, i.e. 36 kg. Loadability of the explosive charges can be enhanced by using these spherical particles of FOX-7.

Preparative separation of alpha- and beta-santalenes and (Z)-alpha- and (Z)-beta-santalols using silver nitrate-impregnated silica gel medium pressure liquid chromatography and analysis of sandalwood oil - Daramwar, Pankaj P.; Srivastava, Prabhakar Lal; Priyadarshini, Balaraman; Thulasiram, Hirekodathakallu V. (Analyst, 2012)
The major sesquiterpene constituents of East-Indian sandalwood oil (Z)-alpha- and (Z)-beta-santalols have shown to be responsible for most of the biological activities and organoleptic properties of sandalwood oil. The work reported here describes the strategic use of medium pressure liquid chromatography (MPLC) for the separation of both alpha- and beta-santalenes and (Z)-alpha- and (Z)-beta-santalols. Silver nitrate impregnated silica gel was used as the stationary phase in MPLC for quantitative separation of alpha- and beta-santalenes and (Z)-alpha- and (Z)-beta-santalols with mobile phases hexane and dichloromethane, respectively. The purities of alpha-santalene and (Z)-alpha-santalol obtained were >96%; however, beta-santalene and (Z)-beta-santalol were obtained with their respective inseparable epi-isomers. Limits of quantification (LoQ) relative to the FID detector were measured for important sesquiterpene alcohols of heartwood oil of S. album using serial dilutions of the standard stock solutions and demonstrated that the quality of the commercial sandalwood oil can be assessed for the content of individual sesquiterpene alcohols regulated by Australian Standard (AS2112-2003), International Organization for Standardization ISO 3518: 2002 (E) and European Union (E. U.).

Probing influence of mesophasic transformation on performance of self-emulsifying system: effect of ion - Patil, Sharvil S.; Venugopal, Edakkal; Bhat, Suresh K.; Mahadik, Kakasaheb R.; Paradkar, Anant R. (Molecular Pharmaceutics, 2012)
Self-emulsifying systems are mixtures of oils and surfactants, ideally isotropic, sometimes including cosolvents, which emulsify under conditions of gentle agitation, similar to those which would be encountered in the gastrointestinal tract. The process of self-emulsification has remained the center of attraction for most researchers. Controlled hydration of self-emulsifying systems shows formation of an intermediate gel phase which upon rupture forms an emulsion. Current work was undertaken to understand and explore the microstructural properties of intermediate gel phase which are believed to influence the performance (droplet size) of the final formulation. The effect of additives on microstructural properties of intermediate gel phase has also been investigated. Microstructural elucidation of hydrated samples of intermediate regimes was done by using techniques such as small angle X-ray scattering, differential scanning calorimetry and rheology. Samples from intermediate regimes showed formation of local lamellar structure which swelled with hydration. In the present work, the effect of addition of salt form of naproxen (sodium and potassium) and naproxen (base) on microstructural properties of intermediate regimes was investigated. Systems containing naproxen salts formed larger droplets whereas naproxen base formed smaller ones. Microstructural properties of intermediate lamellar structures were well correlated with performance of the final formulation. The current studies indicate that by controlling the properties of intermediate regimes optimized formulations with desired performance can be tailor-made.
Keywords: emulsion; lamellar structure; liquid crystal; Microstructure; Naproxen; self-emulsifying system

Probing the mechanism of baylis-hillman reaction in ionic liquids - Singh, Anshu; Kumar, Anil (Journal of Organic Chemistry, 2012)
The kinetic data for a Baylis-Hillman reaction in certain ionic liquids possessing ethylsulfate anion [EtSO4](-) demonstrate that the rate determining step (RIDS) is second order in aldehyde, but first order in acrylate and DABCO. This observation is similar to the one made by McQuade et al., who carried out this reaction in an aprotic polar solvent like DMSO. However, this is in contrast to the general observation that ADS is first order in aldehyde, acrylate, and DABCO in organic solvents.

Probing thermal interactions of ionic liquids with dimethyl sulfoxide - Rai, Gitanjali; Kumar, Anil (Chemphyschem, 2012)
Interactions between ionic liquids and dimethyl sulfoxide (DMSO) are probed by isothermal titration calorimetry. The excess partial molar enthalpies of ionic liquids H-IL(E) in DMSO are discussed in terms of solutesolvent interactions. The specific interaction theory originally developed by Pitzer is used to analyze the apparent molar enthalpy phi(L) of ionic liquids in DMSO with the help of ion-interaction parameters. Furthermore, quantitative information on solvent reorganization and clathrate formation is obtained and interpreted.
Keywords: calorimetry; dimethyl sulfoxide; ionic liquids; solvent effects; thermochemistry

Production, purification, and characterization of a beta-glucosidase of penicillium funiculosum NCL1 - Ramani, Gurusamy; Meera, Balasubramanian; Vanitha, Chinnathambi; Rao, Mala; Gunasekaran, Paramasamy (Applied Biochemistry and Biotechnology, 2012)
Penicillium funiculosum NCL1, a filamentous fungus, produced significantly higher levels of beta-glucosidase. The effect of initial pH, incubation temperature, and different carbon sources on extracellular beta-glucosidase production was studied in submerged fermentation. At 30 A degrees C with initial pH 5.0, enzyme production was increased by 48-fold upon induction with paper mill waste, as compared to commercial cellulose powder. In zymogram analysis, four isoforms of beta-glucosidases were observed with wheat bran whereas a minimum of one isoform was observed with other carbon sources. A major beta-glucosidase (Bgl3A) with the apparent molecular weight of similar to 120 kDa, induced by paper mill waste, was purified 19-fold to homogeneity, with a specific activity of 1,796 U/mg. Bgl3A was a monomeric glycoprotein with 29% of neutral carbohydrate content. It showed optimum activity at pH 4.0 and 5.0, optimum temperature at 60 A degrees C, and exhibited a half-life of 1 h at 60 A degrees C. K (m) of Bgl3A was found to be 0.057 mM with p-nitrophenyl beta-d-glucoside and V (max) was 1,920 U/mg. The purified enzyme exhibited glucose tolerance with a K (i) of 1.5 mM. Bgl3A readily hydrolyzed glucosides with beta-linkage. Bgl3A activity was enhanced (156%) by Zn2+ and was not affected by other metal cations and reagents. The supplementation of Bgl3A (5 U/mg) with Trichoderma reesei cellulase complex (5 FPU/mg) resulted in about 70% of enhanced glucose production, which emphasizes the industrial importance of Bgl3A.
Keywords: beta-Glucosidase; Paper mill waste; Penicillium funiculosum NCL1; Purification; Thermostability

Proteome profiling of flax (linum usitatissimum) seed: characterization of functional metabolic pathways operating during seed development - Barvkar, Vitthal T.; Pardeshi, Varsha C.; Kale, Sandip M.; Kadoo, Narendra Y.; Giri, Ashok P.; Gupta, Vidya S. (Journal of Proteome Research, 2012)
Flax (Linum usitatissimum L.) seeds are an important source of food and feed due to the presence of various health promoting compounds, making it a nutritionally and economically important plant. An in-depth analysis of the proteome of developing flax seed is expected to provide significant information with respect to the regulation and accumulation of such storage compounds. Therefore, a proteomic analysis of seven seed developmental stages (4, 8, 12, 16, 22, 30, and 48 days after anthesis) in a flax variety, NL-97 was carried out using a combination of ID-SDS-PAGE and LC-MSE methods. A total 1716 proteins were identified and their functional annotation revealed that a majority of them were involved in primary metabolism, protein destination, storage and energy. Three carbon assimilatory pathways appeared to operate in flax seeds. Reverse transcription quantitative PCR of selected 19 genes was carried out to understand their roles during seed development. Besides storage proteins, methionine synthase, RuBisCO and S-adenosylmethionine synthetase were highly expressed transcripts, highlighting their importance in flax seed development. Further, the identified proteins were mapped onto developmental seed specific expressed sequence tag (EST) libraries of flax to obtain transcriptional evidence and 81% of them had detectable expression at the mRNA level. This study provides new insights into the complex seed developmental processes operating in flax.
Keywords: alpha-linolenic acid; carbon flux; Digital expression analysis; flax seed development; MSE; secoisolariciresinol diglucoside

Proteomic analysis of glycated proteins from streptozotocin-induced diabetic rat kidney - Chougale, Ashok D.; Bhat, Shweta P.; Bhujbal, Swapnil V.; Zambare, Mandar R.; Puntambekar, Shraddha; Somani, Rahul S.; Boppana, Ramanamurthy; Giri, Ashok P.; Kulkarni, Mahesh J. (Molecular Biotechnology, 2012)
Glycation of proteins leading to formation of advanced glycation end products (AGEs) has been considered as one of the important causes of diabetic nephropathy. Therefore, in this study, glycated proteins were detected by anti-AGE antibodies from kidney of streptozotocin-induced diabetic rat showing nephropathic symptoms, by using two dimensional electrophoresis and western blot analysis. These glycated proteins were identified and characterized by using combination of peptide mass finger printing and tandem mass spectrometric approaches. Glycated proteins identified included proteins from metabolic pathways, oxidative stress, cell signaling, and transport. Several of the proteins modified by glycation were involved in glucose metabolism. The extent of glycation was higher in diabetes compared to control, in the glycated proteins that were common to both control and diabetic kidney. Two dimensional electrophoresis proteins profiling of glycated proteins suggest that four of the glycated proteins were significantly up regulated in diabetes.
Keywords: AGE; Diabetes; Glucose toxicity; Nephropathy; Post-translation modification

Purification and biochemical characterization of endoglucanase from Penicillium pinophilum MS 20 - Pol, Dipali; Laxman, Ryali Seeta; Rao, Mala (Indian Journal of Biochemistry & Biophysics, 2012)
Cellulases find increasing prominence in sustainable production of fuel and feedstock from lignocellulosic biomass. The purification and biochemical characterization of individual components of cellulase complex is important to understand the mechanism of their action for the solubilization of crystalline cellulose. In this study, an extra-cellular endoglucanase isolated from culture filtrate of Penicillium pinophilum MS 20 was purified to homogeneity by ammonium sulphate precipitation, ion-exchange chromatography and gel filtration. The purified endoglucanase (specific activity 69 U/mg) was a monomeric protein with molecular mass of 42 kDa, as determined by SDS-PAGE. The endoglucanase was active over a broad range of pH (4-7) with maximum activity at pH 5 and showed optimum temperature of 50 degrees C. It retained 100% activity at 50 degrees C for 6 h and half- lives of 4 h and 3 h at 60 degrees C and 70 degrees C, respectively. The kinetic constants for the endoglucanase determined with carboxymethyl cellulose as substrate were V-max of 72.5 U/mg and apparent K-m of 4.8 mg/ml. The enzyme also showed moderate activity towards H3PO4 swollen cellulose and p-nitrophenyl beta-D-glucoside, but no activity towards filter paper, Avicel and oat spelt xylan. The activity was positively modulated by 47, 32 and 25% in the presence of Co2+, Zn2+ and Mg2+, respectively to the reaction mixture. The wide pH stability (4-7) and temperature stability up to 50 degrees C of endoglucanase makes the enzyme suitable for use in cellulose saccharification at moderate temperature and pH.
Keywords: Biochemical properties; Carboxymethyl cellulose; Endoglucanase; Penicillium pinophilum MS 20; Purification

Purification and characterization of an antioxidant protein (similar to 16 kDa) from Terminalia chebula fruit - Srivastava, Pratibha; Raut, Hema N.; Wagh, Renuka S.; Puntambekar, Hemalata M.; Kulkarni, Mahesh J. (Food Chemistry, 2012)
Terminalia chebula fruit is used as folk medicine in India and Southeast Asia. An antioxidant protein was isolated by bioassay guided fractionation of T. chebula fruit by homogenizing in the citrate phosphate buffer. The isolated protein (TCP-III) obtained from fruit was purified by gel chromatography and preparative HPLC, showed apparent molecular weight of 16 kDa by SDS-PAGE and MALDI-TOF/MS analyses. Amino acid sequence obtained by LC-MSE analysis showed homology with the predicted protein fragments of Populus trichocarpa, putative uncharacterized protein fragments from Oryza sativa and with fragments of 17 kDa thylakoid lumenal protein from Spinacia oleracea. TCP-III exhibited significant radical scavenging in DPPH, NO, H2O2 and ABTS assays. In addition, TCP-III inhibited oxidation of linoleic acid in beta-carotene bleaching assay, reduced ferric ions and chelated ferrous ions. The present finding demonstrates uniquely, for the first time, characterization of an antioxidant protein from T. chebula fruit. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: 16 kDa protein molecule of T. chebula; Antioxidant and free radical scavenging activity; Characterization; Purification; Terminalia chebula fruit

Purification and characterization of YxeI, a penicillin acylase from Bacillus subtilis - Rathinaswamy, Priya; Gaikwad, Sushama M.; Suresh, C. G.; Prabhune, Asmita; Brannigan, James A.; Dodson, Guy G.; Pundle, Archana V. (International Journal of Biological Macromolecules, 2012)
The paper reports the purification and characterization of the first penicillin acylase from Bacillus subtilis. YxeI, the protein annotated as hypothetical, coded by the gene yxeI in the open reading frame between iol and hut operons in B. subtilis was cloned and expressed in Eshcherichia coli, purified and characterized. The purified protein showed measurable penicillin acylase activity with penicillin V. The enzyme was a homotetramer of 148 kDa. The apparent Km of the enzyme for penicillin V and the synthetic substrate 2-nitro-5-(phenoxyacetamido)-benzoic acid was 40 mM and 0.63 mM, respectively, and the association constants were 8.93 x 10(2) M-1 and 2.51 x 10(5) M-1, respectively. It was inhibited by cephalosporins and conjugated bile salts, substrates of the closely related bile acid hydrolases. It had good sequence homology with other penicillin V acylases and conjugated bile acid hydrolases, members of the Ntn hydrolase family. The N-terminal nucleophile was a cysteine which is revealed by a simple removal of N-formyl-methionine. The activity of the protein was affected by high temperature, acidic pH and the presence of the denaturant guanidine hydrochloride. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Bacillus subtilis; Conjugated bile acid hydrolases; Ntn hydrolase; Penicillin acylase

Purification of lactic acid via esterification of lactic acid using a packed column, followed by hydrolysis of methyl lactate using three continuously stirred tank reactors (CSTRs) in series: a continuous pilot plant study - Kamble, Sanjay P.; Barve, Prashant P.; Joshi, Jyeshtharaj B.; Rahman, Imran; Kulkarni, Bhaskar D. (Industrial & Engineering Chemistry Research, 2012)
The world market of lactic acid is growing every year, mainly as a solvent and precursor to poly(lactic acid) (PLA). The cost of renewable biomass-derived PLA will have to compete with other synthetic polymers, if it is to grab a significant and sustainable fraction of the market share. It is thus necessary to have efficient and cost-effective technology for the production of pure-grade lactic acid (LA). In this article, a novel cost-effective, eco-friendly continuous process for the production of high-quality lactic acid at pilot plant scale has been demonstrated. The novelty of this process is that, for the first time, we report and use the concept of inverse reactive distillation for the esterification of crude concentrated LA in a continuous countercurrent packed column mode. This allows us to operate the column at higher temperatures, improving the kinetic rate process and leading to shorter columns. This is followed by the hydrolysis of methyl lactate (MLA) in a series of three continuously stirred tank reactors (CSTRs), where LA itself acts as a catalyst. The LA obtained in the pilot plant process shows 99.81% purity (by weight) on water-free basis and has an optical purity of 99.9%. The pilot scale experimental results pertaining to the autocatalytic esterification of LA and hydrolysis of MLA have been compared and validated, with respect to simulated results. The innovations reported here can make the process economically viable for commercial use.

Palladium chloride catalyzed photochemical heck reaction - Waghmode, Suresh B.; Arbuj, Sudhir S.; Wani, Bina N.; Gopinath, Chinnakonda S. (Canadian Journal of Chemistry-Revue Canadienne De Chimie, 2013)
PdCl2 catalyzed carbon-carbon bond formation (Heck reaction) between substituted aryl halides and olefins was carried out without a ligand, under irradiation with UV-visible light. The results demonstrated that UV-visible light accelerated the rate of the reaction, leading to an excellent yield of corresponding products. The recovered palladium nanoparticles could be thermally recycled several times. PdCl2 gave excellent conversion up to the fifth addition of substrate.
Keywords: C-C coupling; Heck reaction; iodobenzene; photochemical reaction

Palladium-promoted [2+2+2] cocyclization of arynes and unsymmetrical conjugated dienes: synthesis of justicidin B and retrojusticidin B - Patel, Ramesh M.; N. P. Argade (Organic Letters, 2013)
A facile synthesis of natural and unnatural arylnaphthalenes has been demonstrated via the unprecedented palladium-promoted [2 + 2 + 2] cocyclization of arynes and unsymmetrical conjugated dienes using the N-heterocyclic carbene as a ligand. The unsymmetrical dienes used herein are actually alpha-coupled acrylate - cinnamate combinations bearing two beta-positive carbons and follow the key [2 + 2 + 2] cocyclization pathway.

Pd ultra-small clusters as precursors for silica-encapsulated Pd nanoreactors: highly sinter-resistant catalysts - Samanta, Anupam; Devi, R. Nandini (Chemcatchem, 2013)
Sintering and consequent deactivation in supported metal catalysts is a severe problem encountered in heterogeneous catalysis. This problem can be addressed by encapsulating active metal nanoparticles within inert oxides such as silica, provided the oxide shell is porous to enable access of reactant molecules to the nanoparticle surface to facilitate catalysis. We report the synthesis of highly sinter-resistant silica-encapsulated Pd catalysts with nanoparticle sizes stabilized at (3.4 +/- 0.6)nm at high temperatures of approximately 750 degrees C. The synthesis was achieved by utilizing thiol-protected ultra-small clusters of Pd as precursors for silica encapsulation. The ultra-small clusters were synthesized by using propyl ammonium functionalised thiols making them water-dispersible and amenable for silica encapsulation. Abundance of organics also aided in creating porosity subsequent to calcination at high temperatures.
Keywords: cluster compounds; Encapsulation; nanoreactors; Palladium; silicates

PEEK/SiO2 composites with high thermal stability for electronic applications - Goyal, R. K.; Rokade, K. A.; Kapadia, A. S.; Selukar, B. S.; Garnaik, Baijayantimala (Electronic Materials Letters, 2013)
Thermal and mechanical properties of new high performance polymer matrix composites based on poly(etheretherketone) (PEEK) as matrix and crystalline-silica (SiO2) as reinforcement were discussed for application in electronic packaging substrates or printed circuit boards. The content of SiO2 was varied between 0 and 50 wt. %. Scanning electron microscopy showed uniform dispersion of SiO2 particles in the matrix. Thermogravimetry analysis showed significant increase in thermal stability and char yield with increase in SiO2 content in the matrix. Differential scanning calorimetry showed that SiO2 had a heterogeneous nucleating effect on PEEK, leading to an increase in peak temperature of crystallization and onset crystallization temperature of the composites compared to a pure matrix. The microhardness increased approximately 42%. A modified rule of mixtures with a strengthening efficiency factor equal to 0.06 fit the data nicely. The results show that the prepared PEEK/SiO2 composites may have potential applications in electronics.
Keywords: hardness; PEEK; polymer matrix composites; Thermal properties

Performance of the EOMIP-CCSD(2) method for determining the structure and properties of doublet radicals: a benchmark investigation - Dutta, Achintya Kumar; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2013)
We present a benchmark study on the performance of the EOMIP-CCSD(2) method for computation of structure and properties of doublet radicals. The EOMIP-CCSD(2) method is a second-order approximation to the standard EOMIP-CCSD method. By retaining the black box nature of the standard EOMIP-CCSD method and adding favorable N-5 scaling, the EOMIP-CCSD(2) method can become the method of choice for predicting the structure and spectroscopic properties of large doublet radicals. The EOMIP-CCSD(2) method overcomes the typical problems associated with the standard single reference ab initio treatment of doublet radicals. We compare our results for geometries and harmonic vibrational frequencies with those obtained using the standard EOMIP-CCSD method, as well as unrestricted Hartree-Fock (UHF)- and restricted open-shell Hartree-Fock (ROHF)-based single-reference coupled-cluster and second order many-body perturbation theory (MBPT(2)) methods. The effect of the basis set on the quality of the results has been studied using a hierarchy of Dunning's correlation-consistent aug-cc-pVXZ (X = D, T, Q) basis sets. Numerical results show that the EOMIP-CCSD(2) method, despite its N-5 scaling, gives better agreement with experimental results, compared to the UHF- and ROHF-based MBPT(2), as well as the single-reference coupled-cluster methods.

Perturbative approximations to single and double spin flip equation of motion coupled cluster singles doubles methods - Dutta, Achintya Kumar; Pal, Sourav; Ghosh, Debashree (Journal of Chemical Physics, 2013)
Spin flip equation of motion coupled cluster (EOM-SF-CC) can correctly treat situations involving electronic degeneracies or near degeneracies, e. g., bond breaking, di- and tri-radicals, etc. However, for large systems EOM-SF-CC (even in single and double excitations) is computationally prohibitively expensive. Therefore, earlier approximations to EOM-SF-CC methods such as spin flip configuration interaction singles with perturbative doubles (SF-CIS(D)) have been proposed. In this work, we present a new perturbative approximation to EOM-SF-CC, which has been found to be more accurate than SF-CIS(D). The capabilities, advantages, and timings of the new approach have been demonstrated considering the singlet-triplet gaps in di- and triradicals as well as bond breaking examples. The method is extended to double spin flip EOM-CC and its capabilities have been tested. (C) 2013 AIP Publishing LLC.

Phase, size and shape transformation by fungal biotransformation of bulk TiO2 - Khan, Shadab Ali; Ahmad, Absar (Chemical Engineering Journal, 2013)
Nanosynthesis is an ever expanding frontier in recent years in view of its implications to many future technologies covering diverse fields. Considerable progress has been made realizing high quality synthesis of elemental nanomaterials as well as compounds as chemical, biological and physical routes. The issue of technologically viable large scale synthesis still continues to be a challenge. Here we demonstrate a novel environmentally friendly top down approach to nanosynthesis which exploits the strength and peculiarities of fungus based bioleaching in extracting radicals from compounds and then providing them with a reactive as well as capping environment. Thus protein capped nanoparticles of TiO2 (5-28 nm, circular and brookite phase) are formed directly from micron size (150-250 nm, disc shape, anatase phase) powder by exposing them to a medium of fungus Humicola sp. at just 50 degrees C. The fungus Humicola sp. is not only useful for the synthesis of nanoparticles but also for the transformation of shape, phase and size of TiO2. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Anatase; Biotransformation; Brookite; humicola sp; TiO2

Photopolymerization of bis-aromatic and alicyclic based solid urethane acrylate macromonomer in the presence of large excess of reactive diluent Kinetics and modeling - Harikrishna, Reghunathan; Ponrathnam, S.; Rajan, C. R.; Tambe, S. S. (Journal of Thermal Analysis and Calorimetry, 2013)
A solid urethane acrylate macromonomer with bis-aromatic as well as alicyclic moieties was synthesized and the kinetics of photopolymerization reactions were studied in the presence of varying concentration of photoinitiator and large excess of reactive diluent using photo DSC. The studies show that the rate of maximum polymerization was found to increase with increase in concentration of photoinitiator while a decrease was observed by an increase in temperature. The final conversion showed a decrease at highest isothermal condition due to vitrification. Estimation of kinetic parameters including applicability of autocatalytic and modified autocatalytic models were investigated by nonlinear regression. It was observed that the modified models gave a better fit with the experimental data and kinetic parameters showed a decrease with increase in temperature and an increase with increase in concentration of photoinitiator.
Keywords: Autocatalytic model; kinetics; Levenberg-Marquardt method; Photopolymerization

Phytase isozymes from aspergillus niger NCIM 563 under solid state fermentation: biochemical characterization and their correlation with submerged phytases - Bhavsar, Kavita P.; Buddhiwant, Priyanka; Soni, Sarvesh K.; Depan, Dilip; Sarkar, Sampa; Khire, Jayant Malhar (Process Biochemistry, 2013)
Aspergillus niger NCIM 563 produces dissimilar phytase isozymes under solid state and submerged fermentation conditions. Biochemical characterization and applications of phytase Phy III and Phy IV in SSF and their comparison with submerged fermentation Phy I and Phy III were studied. SSF phytases have a higher metabolic potential as compared to SmF. Phy I is tetramer and Phy II, III and IV are monomers. Phy I and IV have pH optima of 2.5 and Phy II and III have pH optima of 5.0 and 5.6, respectively. Phy I, III and IV exhibited very broad substrate specificity while Phy II was more specific for sodium phytate. SSF phytase is less thermostable as compared to SmF phytase. Phy land II show homology with other known phytases while Phy III and IV show no homology with SmF phytases and any other known phytases from the literature suggesting their unique nature. This is the first report about differences among phytase produced under SSF and SmF by A. niger and this study provides basis for explanation of the stability and catalytic differences observed for these enzymes. Exclusive biochemical characteristics and multilevel application of SSF native phytases determine their efficacy and is exceptional. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: A. niger; Isozymes; Phytase; Solid state fermentation; Submerged fermentation

Phytosynthesis of silver nanoparticles by semecarpus anacardium L. leaf extract - Raju, D.; Hazra, Sulekha; Mehta, Urmil J. (Materials Letters, 2013)
Green synthesis of silver nanoparticles (AgNPs) using Semecmpus anacardium L leaf extract was studied. The reduction of silver (Ag+) ions was characterized by using UV-vis spectrophotometer showing formation of AgNPs within 15-20 mm. A time dependent reaction showed the increase in the nanoparticles (NPs) with time. Transmission electron microscopy (TEM) analysis showed that the synthesized AgNPs varied from 10 to 25 nm and has spherical shape. The Fourier transform infrared (FTIR) analysis showed that phenols and protein were responsible for the formation of the AgNPs. The energy dispersive spectroscopy (EDAX) analysis confirms the formed NPs were of silver. The quantification of AgNPs was studied by inductive coupled plasma spectrometry (ICP-AES). The important outcome of this work can be value addition to the medicinal plants in synthesis of NPs for biomedical applications. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: FTIR; Leaf extract; Nanoparticles; Semecarpus anacardium; synthesis; TEM

Plasticity of protease gene expression in helicoverpa armigera upon exposure to multi-domain capsicum annuum protease inhibitor - Mahajan, Neha S.; Mishra, Manasi; Tamhane, Vaijayanti A.; Gupta, Vidya S.; Giri, Ashok P. (Biochimica et Biophysica Acta (BBA) - General Subjects, 2013)
Background A multi-domain Pin-II type protease inhibitor from Capsicum annuum (CanPI-7) is known to be effective against the insect pest, Helicoverpa armigera. The present study is an attempt to investigate the optimal dose of recombinant CanPI-7 (rCanPI-7) for effective antibiosis to H. armigera and further to characterize the responses of digestive proteases upon rCanPI-7 ingestion. Methods The gut protease activity was assessed biochemically and transcript accumulation pattern for selected trypsin and chymotrypsin genes was analyzed by quantitative Real-Time PCR. Results The growth retardation upon exposure to rCanPI-7 was more prominent in neonates as compared to third instar larvae. Influence of stage and dosage of rCanPI-7 was conspicuous on the expression and regulation of candidate trypsin and chymotrypsin genes in H. armigera. The transcript accumulation pattern correlated with the protease activity in rCanPI-7 exposed larvae. Conclusions We conclude that early exposure and specific dose of protease inhibitor are essential for effective antibiosis despite the large diversity and plasticity in the expression of protease genes in H. armigera. Moreover, it is also evident that the regulation and expression of H. armigera gut proteases are specific to the stage of PI exposure. General significance These results highlight the requirement of optimal PI concentration for effective growth retardation and for inhibiting the major gut proteases of H. armigera.

PNN-Ru pincer complexes based on phosphinated 2,2’-dipyridinemethane- and 2,2’-oxobispyridine. metal-ligand cooperation in cyclometallation and catalysis - Barrios-Francisco, Rigoberto; Balaraman, Ekambaram; Diskin-Posner, Yael; Leitus, Gregory; Shimon, Linda J. W.; Milstein, David (Organometallics, 2013)
The synthesis of novel PNN ruthenium pincer complexes based on 2,2′-dipyridinemethane phosphine derivatives, as well as on 2,2′-oxobispyridine phosphine ligands, and their reactivity toward dearomatization and cyclometalation are described. The dearomatized compounds 7a,b undergo cyclometalation to yield complexes 8a,b. In order for cyclometalation to proceed, the coordination sphere around the Ru center has to rearrange, and this depends on the flexibility of the system, showing that the cyclometalation is qualitatively faster in the case of the dimethyl derivative 7a than in the case of the spyrocyclopentyl derivative 7b. The cyclometalation occurs diastereoselectively and leads to only one diastereomer of the cyclometalated compounds. In the case of the 2,2′-oxobispyridine complex 6c, the dearomatized complex was too unstable to be isolated; however it was possible to isolate and characterize a stable dicarbonyl-dearomatized ruthenium(II) complex, 9c, when the deprotonation was performed under a CO atmosphere. Dearomatization of 6a under CO also led to dicarbonyl-dearomatized ruthenium(II) complex 9a, which slowly rearranged into the dicarbonyl-aromatized ruthenium(0) complex 10a. These complexes were tested in catalytic alcohol–amine coupling, esterification of primary alcohols, and hydrogenation of secondary amides. Moderate activity was observed in hydrogenation of amides to alcohols and amines and low activity in the other transformations, owing mainly to the formation of stable cyclometalated compounds.

Polarizability of few electron quantum dots: extended coupled-cluster response approach - Heidari, Ideh; Vaval, Nayana; Pal, Sourav; Kanhere, Dilip G. (Chemical Physics Letters, 2013)
The dipole polarizability is studied for few electron quantum dots using extended coupled cluster linear response method (ECCLR). The polarizability of pure parabolic quantum dots depends only on the number of electrons and the parabolic confinement strength. We added impurity in a GAUSSIAN form to the external parabolic potential and used ECCLR to calculate polarizability. To examine the effect of external potential, we changed the parabolic confinement to square-well and repeated all calculations. We mainly looked at eigenvalue spectrum and charge density specially when the system shifts towards lower density regions. (C) 2012 Elsevier B. V. All rights reserved.

Poly-L-arginine grafted silica mesoporous nanoparticles for enhanced cellular uptake and their application in DNA delivery and controlled drug release - Kar, Mrityunjoy; Tiwari, Neha; Tiwari, Mitali; Lahiri, Mayurika; Sen Gupta, Sayam (Particle & Particle Systems Characterization, 2013)
Mesoporous silica nanoparticles (MSNs), that are capable of delivering gene and drugs to organisms in an effective and selective way have attracted much attention lately for its potential in the treatment of cancer. However, the successful application of MSNs for delivery of plasmid DNA or drugs requires surface modification of the silica with positively charged functional groups so that it binds to the negatively charged nucleic acids and also helps it penetrate through the cell membrane. We report for the first time the synthesis of a hybrid MSN where the cell penetrating cationic polypeptide poly-L-arginine synthesized by NCA polymerization is grafted onto the external surface of MSN using click chemistry. These poly-L-arginine grafted MSNs show low cytotoxity (85% cell viability at 100 g/mL MSN concentration) and high cellular uptake by both HeLa and A549 (>90%). The poly-L-arginine grafted MSNs were used effectively to deliver mCherry DNA plasmid into cells leading to expression of the protein mCherry inside the cells (transfection efficiency 60%). In contrast, poly-L-arginine grafted non-porous silica nanoparticles were unable to express the protein mCherry inside the cells although their uptake into the cells was as efficient as with poly-L-arginine grafted MSNs. We also show preliminary results to demonstrate that these hybrid MSNs can be used as a delivery vehicle for the anticancer drug Doxorubicin towards cancerous cells HeLa and A549. The biocompatibility of poly-L-arginine and its cell penetrating ability are expected to make these MSN conjugates very useful carriers for the delivery of genes and drugs into cancer cells.

Polymer solar cells - Singh, Ram Prakash; Kushwaha, Omkar Singh (Journal of Materials Education, 2013)
It is a well known fact that the amount of solar energy impinging on the earth's surface in one hour is higher than the worldwide energy demand per year. Solar energy is the ultimate renewable zero emission energy source. Solar energy technology which is dominated by the crystalline silicon has not found widespread acceptance due to size, weight, aesthetics, cost and installation of solar panels. On the other hand, polymer solar cells being light weight, inexpensive, colorful and capable to be fabricated into large area flexible devices by roll to roll processes, portend potential for large scale non-grid and grid power generation applications. Polymer solar cells would reduce the need for petroleum and natural gas for power generation; therefore, the use of cells would slow down the disappearance of non-renewable resources and promote sustainability. In spite of these facts, polymer solar cells are not covered in current curricula and textbooks of Materials Science and Engineering. The present article intends to provide the remedy to this situation and exhaustively discusses materials, mechanisms and applications in the development of highly efficient polymer solar cells (PSCs).
Keywords: Bulk heterojunction polymer solar cells; Electron acceptors; Electron donors; Inverted and Tandem solar cells; Roll to roll processing; Solar cell efficiency

Polymer solar cells: an overview - Singh, Ram Prakash; Kushwaha, Omkar Singh (Macromolecular Symposia, 2013)
Polymer Solar cells being flexible, light weight, inexpensive, colorful and large area devices, portend potential for large scale grid power generation. The first major breakthrough in organic solar cell performance came in 1986 when Tang discovered that much higher efficiencies about 1% can be attained when electron donor (D) and electron acceptor (A) are brought together in one cell. With the discovery of photo induced electron transfer from a conjugated polymer to fullerene molecules in 1992, the bulk heterojunction (BHJ) polymer solar cell has become the most successful device structure developed in the field till date. Poly(3-hexyl thiophene) (P3HT) has been the subject of intensive investigations upto 2008 yielding power conversion efficiencies (PCEs) around 5-6%. OPV technology has grown during the past decade with cell efficiencies quadrupling. As alternative route of higher performance, two or more single cells can be combined in tandem structure. The most efficient tandem organic solar cell reported by Yang Yang's group has 8.62% power conversion efficiency (PCE) which has been further improved with an NREL - certified PCE of 10.6%. An overview of the above will be presented in this paper.
Keywords: bulk heterojunction; electron acceptor; electron donor; fullerenes; polymer solar cells

Polyproline fold-In imparting kinetic stability to an alkaline serine endopeptidase - Rohamare, Sonali B.; Dixit, Vaishali; Nareddy, Pavan Kumar; Sivaramakrishna, D.; Swamy, Musti J.; Gaikwad, Sushama M. (Biochimica Et Biophysica Acta-Proteins and Proteomics, 2013)
Polyproline II (PPII) fold, an unusual structural element was detected in the serine protease from Nocardiopsis sp. NCIM 5124 (NprotI) based on far UV circular dichroism spectrum, structural transitions of the enzyme in presence of GdnHCl and a distinct isodichroic point in chemical and thermal denaturation. The functional activity and conformational transitions of the enzyme were studied under various denaturing conditions. Enzymatic activity of NprotI was stable in the vicinity of GdnHCl upto 6.0 M concentration, organic solvents viz, methanol, ethanol, propanol (all 90% v/v), acetonitrile (75% v/v) and proteases such as trypsin, chymottypsin and proteinase K (NprotI:protease 10:1). NprotI seems to be a kinetically stable protease with a high energy barrier between folded and unfolded states. Also, an enhancement in the activity of the enzyme was observed in 1 M GdnHCl upto 8 h, in organic solvents (75% v/v) for 72 h and in presence of proteolytic enzymes. The polyproline fold remained unaltered or became more prominent under the above mentioned conditions. However, it diminished gradually during thermal denaturation above 60 degrees C. Thermal transition studies by differential scanning calorimetry (DSC) showed scan rate dependence as well as irreversibility of denaturation, the properties characteristic of kinetically stable proteins. This is the first report of PPII helix being the global conformation of a non structural protein, an alkaline serine protease, from a microbial source, imparting kinetic stability to the protein. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Conformation; differential scanning calorimetry; Kinetic stability; Nocardiopsis sp.; Polyproline fold; Serine protease

POM-catalyzed in situ ligand synthesis for the construction of metal complexes and their use in the formation of coordination polymers - Dey, Chandan; Banerjee, Rahul (Chemphyschem, 2013)
Six organicinorganic hybrid materials were synthesized by the in situ oxidation of neocuproine by using MoO3/Na2MoO4 as the catalyst in the presence of Cu(NO3)2. The crystal structures of Mo8-Cu4-PHEN and Mo8-Cu2-5(2PIC) are composed of [Mo8O26]4 polyoxometalate (POM) units, whereas the crystal structure of Mo6-Cu-COPHEN is composed of a [Mo6O19]2 POM unit; both POM units could be considered as the active form of the catalyst. Reaction of the hybrid materials with 1,3,5-benzenetricarboxylic acid (BTC) resulted in the formation of two different coordination polymers (CPs) under different reaction conditions. These CPs, depending on their structural attributes, exhibit distinct differences in the adsorption of H2, CO2, and water. The use of 2-methylpyridine instead of neocuproine does not give any oxidation products under the same reaction conditions due to the incorrect positioning of the methyl group with respect to the CuII center.
Keywords: coordination polymers; Copper; N ligands; organicinorganic hybrid composites; polyoxometalates

Porous carbons from nonporous MOFs: influence of ligand characteristics on intrinsic properties of end carbon - Aiyappa, Harshitha Barike; Pachfule, Pradip; Banerjee, Rahul; Kurungot, Sreekumar (Crystal Growth & Design, 2013)
Synthesis of porous carbons on direct carbonization of nonporous Zn-based MOFs has been achieved without using any additional carbon precursor. The effect of ligand nature on the resulting carbon porosity has been studied systematically using the MOFs synthesized from rigid and flexible ligands. The linear relations between Zn/C ratio of the MOF versus surface area of the resulting carbon, micro-porosity versus H-2 uptake achieved in these carbons, and surface area versus specific capacitance of the end carbons have been verified from the gas adsorption, molecular composition, and electrochemical studies, respectively. Cyclic voltammetry and charge-discharge cycling have been carried out to study the capacitive behavior of the carbons. The interdependence of capacitive behavior on the surface area has been analyzed using data derived from N-2 adsorption isotherms and charge-discharge curves. Among the carbons synthesized, C-MOF-2 shows maximal surface area of 1378 m(2)/g with a specific capacitance of 170 F/g at 1 A/g.

Porous Co3O4 nanorods as superior electrode material for supercapacitors and rechargeable Li-ion batteries - Vijayanand, S.; Kannan, Ramaiyan; Potdar, H. S.; Pillai, V. K.; Joy, Pattayil Alias (Journal of Applied Electrochemistry, 2013)
Porous aggregated nanorods of Co3O4 with a surface area of similar to 100 m(2) g(-1) synthesized without using any templates or surfactants give very high specific capacitance of similar to 780 F g(-1) when used as electrode in a faradaic supercapacitor, with a cycle life of more than 1,000 cycles. Further, in Li-ion batteries when used as an anode, the Co3O4 nanorods achieved a capacity of 1155 mA h g(-1) in the first cycle and upon further cycling it is stabilized at 820 mA h g(-1) for more than 25 cycles. Detailed characterization indicated the stability of the material and the improved performance is attributed to the shorter Li-insertion/desertion pathways offered by the highly porous nanostructures. The environmentally benign and easily scalable method of synthesis of the porous Co3O4 nanorods coupled with the superior electrode characteristics in supercapacitors and Li-ion batteries provide efficient energy storage capabilities with promising applications.
Keywords: Cobalt oxide; Electrode materials; Li-ion battery; Porous nanostructures; supercapacitor

Porous-organic-framework-templated nitrogen-rich porous carbon as a more proficient electrocatalyst than Pt/C for the electrochemical reduction of oxygen - Pachfule, Pradip; Dhavale, Vishal M.; Kandambeth, Sharath; Kurungot, Sreekumar; Banerjee, Rahul (Chemistry-A European Journal, 2013)
Porous nitrogen-rich carbon (POF-C-1000) that was synthesized by using a porous organic framework (POF) as a self-sacrificing host template in a nanocasting process possessed a high degree of graphitization in an ordered structural arrangement with large domains and well-ordered arrays of carbon sheets. POF-C-1000 exhibits favorable electrocatalytic activity for the oxygen-reduction reaction (ORR) with a clear positive shift of about 40 mV in the onset potential compared to that of a traditional, commercially available Pt/C catalyst. In addition, irrespective of its moderate surface area (785 m2?g-1), POF-C-1000 showed a reasonable H2 adsorption of 1.6 wt?% (77 K) and a CO2 uptake of 3.5 mmol?g-1 (273 K).
Keywords: Adsorption; Electrochemistry; fuel cells; oxygen-reduction reaction; porous organic frameworks

Pre-combustion capture of carbon dioxide in a fixed bed reactor using the clathrate hydrate process - Babu, Ponnivalavan; Kumar, Rajnish; Linga, Praveen (Energy, 2013)
Hydrate based gas separation (HBGS) process with silica sand and silica gel as contact medium was employed to capture CO2 from fuel gas mixture. Gas uptake measurement at three different pressures (7.5, 8.5 and 9.0 MPa) and 274.15 K were conducted for hydrate formation kinetics and overall conversion of water to hydrate, rate of hydrate formation were determined. Water conversion of up to 36% was achieved with silica sand bed compared to 13% conversion in the silica gel bed. Effect of driving force on the rate of hydrate formation and gas consumption was significant in silica sand bed whereas it was found to be insignificant in silica gel bed. Hydrate dissociation experiments by thermal stimulation (at constant pressure) alone and a combination of depressurization and thermal stimulation were carried out for complete recovery of the hydrated gas. A driving force of 23 K was found to be sufficient to recover all the hydrated gas within 1 h. This study indicates that silica sand can be an effective porous media for separation of CO2 from fuel gas when compared to silica gel. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate hydrates; Gas separation; Global warming; Pre-combustion

Preparation-method-dependent morphological, band structural, microstructural, and photocatalytic properties of noble metal-GaNbO4 nanocomposites - Devi, Suman; Kelkar, Sarika A.; Kashid, Vikas; Salunke, Hemant G.; Gupta, Narendra M. (RSC Advances, 2013)
We report the distinct physicochemical and photophysical properties of gallium niobate photocatalysts (bandgap: similar to 3.1 eV), prepared by a solid-state (SS) reaction and sol-gel (SG) method and dispersed with a noble metal (similar to 0.5% of Pt, Au, or RuOx) cocatalyst. SG-GaNbO4 comprised smaller size particles (similar to 20-50 nm) and a larger surface area (similar to 160 m(2) g(-1)) compared to SS-GaNbO4 (particle size similar to 30-150 nm, surface area similar to 27 m(2) g(-1)). XRD patterns revealed a preparation-dependent variation in the relative intensity of prominent reflections. In TEM examination, SG samples exhibited small-range grain boundaries and heterogeneous metal/substrate interfacial contacts, while SS-GaNbO4 had long-range ordering. Laser-Raman and thermoluminescence investigations revealed that lattice distortion, defect-induced inter-bandgap charge trapping states, and the local environment around the metal/semiconductor interfaces may also depend on the preparation method. Metal-GaNbO4 nanocomposites showed no activity for the dissociation of pure water under UV (>250 nm) irradiation, despite the favourable conduction and valence band potentials. This was attributed to the sharp Ga and Nb d-levels in the narrow conduction band of GaNbO4, as confirmed by ab initio electronic structure calculation. These photocatalysts, however, showed good activity for semiconductor-mediated photo-dissociation of aqueous methanol to produce H-2; a cocatalyst-dependent activity trend, Pt > RuOx > Au, was observed. Doping of S at similar to 5% of the oxygen sites led to decreased photoactivity, ascribed to the presence of localized S 3p states just above the O 2p valence level. In conclusion, besides band characteristics, certain morphological and microstructural properties play a crucial role in the photoactivity of the metal/oxide nanocomposites.

Probing interaction of Gram-positive and Gram-negative bacterial cells with ZnO nanorods - Jain, Aanchal; Bhargava, Richa; Poddar, Pankaj (Materials Science & Engineering C-Materials for Biological Applications, 2013)
In the present work, the physiological effects of the ZnO nanorods on the Gram positive (Staphylococcus aureus and Bacillus subtilis) and Gram-negative (Escherichia coli and Aerobacter aerogenes) bacterial cells have been studied. The analysis of bacterial growth curves for various concentrations of ZnO nanorods indicates that Gram positive and Gram negative bacterial cells show inhibition at concentrations of similar to 64 and similar to 256 mu g/mL respectively. The marked difference in susceptibility towards nanorods was also validated by spread plate and disk diffusion methods. In addition, the scanning electron micrographs show a clear damage to the cells via changed morphology of the cells from rod to coccoid etc. The confocal optical microscopy images of these cells also demonstrate the reduction in live cell count in the presence of ZnO nanorods. These, results clearly indicate that the antibacterial activity of ZnO nanorods is higher towards Gram positive bacterium than Gram negative bacterium which indicates that the structure of the cell wall might play a major role in the interaction with nanostructured materials and shows high sensitivity to the particle concentration. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Confocal; Growth curve; Nanorods; SEM; Zeta potential; ZnO

Probing the acidity of carboxylic acids in protic ionic liquids, water, and their binary mixtures: activation energy of proton transfer - Shukla, Shashi Kant; Kumar, Anil (Journal of Physical Chemistry B, 2013)
Acidity functions were used to express the ability of a solvent/solution to donate/accept a proton to a solute. The present work accounts for the acidity determination of HCOOH, CH3COOH, and CH3CH2COOH in the alkylimidazolium-based protic ionic liquids (PILs), incorporated with carboxylate anion, water, and in a binary mixture of PIL and water using the Hammett acidity function, H-0. A reversal in the acidity trend was observed, when organic acids were transferred from water to PIL. It was emphasized that an increased stabilization offered by PIL cation toward the more basic conjugate anion of organic acid was responsible for this anomalous change in acidity order in PILs, which was absent in water. The greater stabilization of a basic organic anion by PIL cation is discussed in terms of the stable hard-soft acid base (HSAB) pairing. A change in the H-0 values of these acids was observed with a change in temperature, and a linear correlation between the ln H-0 and 1/T was noted. This relationship points toward the activation energy of proton transfer (E-a,E-H+), a barrier provided by the medium during the proton transfer from Bronsted acid to indicator. The H-0 function in binary mixtures points to the involvement of pseudosolvent, the behavior of which changes with the nature and concentration of acid. The presence of the maxima/minima in the H-0 function is discussed in terms of the synergetic behavior of the pseudosolvent composed of the mixtures of aqueous PILs.

Probing the active site of cinnamoyl CoA reductase 1 (Ll-CCRH1) from Leucaena leucocephala - Sonawane, Prashant; Patel, Krunal; Vishwakarma, Rishi Kishore; Srivastava, Sameer; Singh, Somesh; Gaikwad, Sushama M.; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2013)
Lack of three dimensional crystal structure of cinnamoyl CoA reductase (CCR) limits its detailed active site characterization studies. Putative active site residues involved in the substrate/NADPH binding and catalysis for Leucaena leucocephala CCR (Ll-CCRH1; GenBank: DQ986907) were identified by amino acid sequence alignment and homology modeling. Putative active site residues and proximal H215 were subjected for site directed mutagenesis, and mutated enzymes were expressed, purified and assayed to confirm their functional roles. Mutagenesis of S136, Y170 and K174 showed complete loss of activity, indicating their pivotal roles in catalysis. Mutant S212G exhibited the catalytic efficiencies less than 10% of wild type, showing its indirect involvement in substrate binding or catalysis. R51G, D77G, F30V and I31N double mutants showed significant changes in K-m values, specifying their roles in substrate binding. Finally, chemical modification and substrate protection studies corroborated the presence Ser, Tyr, Lys, Arg and carboxylate group at the active site of Ll-CCRH1. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: Chemical modification; Cinnamoyl CoA reductase 1; Docking simulations; homology modeling; Site directed mutagenesis; Substrate protection

Production, purification and characterization of cholesterol oxidase from a newly isolated streptomyces sp. - Niwas, Ram; Singh, Vineeta; Singh, Rajbir; Tripathi, Divya; Tripathi, C. K. M. (World Journal of Microbiology & Biotechnology, 2013)
Cholesterol oxidase production (COD) by a new isolate characterized as Streptomyces sp. was studied in different production media and fermentation conditions. Individual supplementation of 1 % maltose, lactose, sucrose, peptone, soybean meal and yeast extract enhanced COD production by 80-110 % in comparison to the basal production medium (2.4 U/ml). Supplementation of 0.05 % cholesterol (inducer) enhanced COD production by 150 %. COD was purified 14.3-fold and its molecular weight was found to be 62 kDa. V-max (21.93 mu M/min mg) and substrate affinity K-m (101.3 mu M) suggested high affinity of the COD for cholesterol. In presence of Ba2+ and Hg2+ the enzyme activity was inhibited while Cu2+ enhanced the activity nearly threefold. Relative activity of the enzyme was found maximum in triton X-100 whereas sodium dodecyl sulfate inactivated the enzyme. The enzyme activity was also inhibited by the thiol-reducing reagents like Dithiothreitol and beta-mercaptoethanol. The COD showed moderate stability towards all organic solvents except acetone, benzene and chloroform. The activity increased in presence of isopropanol and ethanol. The enzyme was most active at pH 7 and 37 A degrees C temperature. This organism is not reported to produce COD.
Keywords: Affinity chromatography; Cholesterol oxidase; HPLC; SDS PAGE; Streptomyces sp.

Proline catalyzed alpha-aminoxylation reaction in the synthesis of biologically active compounds - Kumar, Pradeep; Dwivedi, Namrata (Accounts of Chemical Research, 2013)
The search for new and efficient ways to synthesize optically pure compounds is an active area of research in organic synthesis. Asymmetric catalysis provides a practical, cost-effective, and efficient method to create a variety of complex natural products containing multiple stereocenters. In recent years, chemists have become more interested in using small organic molecules to catalyze organic reactions. As a result, organocatalysis has emerged both as a promising strategy and as an alternative to catalysis with expensive proteins or toxic metals. One of the most successful and widely studied secondary amine-based organocatalysts is proline. This small molecule can catalyze numerous reactions such as the aldol, Mannich, Michael addition, Robinson annulation, Diels-Alder, alpha-functionalization, alpha-amination, and alpha-aminoxylation reactions. Catalytic and enantioselective alpha-oxygenation of carbonyl compounds is an important reaction to access a variety of useful building blocks for bioactive molecules. Proline catalyzed alpha-aminoxylation using nitrosobenzene as oxygen source, followed by in situ reduction, gives enantiomerically pure 1,2-diol. This molecule can then undergo a variety of organic reactions. In addition, proline organocatalysis provides access to an assortment of biologically active natural products including mevinoline (a cholesterol lowering drug), tetrahydrolipstatin (an antiobesity drug), R(+)-alpha-lipoic acid, and bovidic acid. In this Account, we present an iterative organocatalytic approach to synthesize both syn- and anti-1,3-polyols, both enantio- and stereoselectively. This method is primarily based on proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons (HWE) olefination of aldehyde to give a gamma-hydroxy ester. In addition, we briefly illustrate the broad application of our recently developed strategy for 1,3-polyols, which serve as valuable, enantiopure building blocks for polyketides and other structurally diverse and complex natural products. Other research groups have also applied similar strategies to prepare such bioactive molecules as littoralisone, brasoside and (+)-cytotrienin A. Among the various synthetic approaches reported for 1,3-polyols, our organocatalytic iterative approach appears to be very promising and robust. This method combines the merit of organocatalytic reaction with an easy access to both enantiomerically pure forms of proline, mild reaction conditions, and tolerance to both air and moisture. In this Account, we present the latest applications of organocatalysis and how organic chemists can use this new tool for the total synthesis of complex natural products

Proline catalyzed sequential alpha-aminooxylation or -amination/reductive cyclization of o-nitrohydrocinnamaldehydes: a high yield synthesis of chiral 3-substituted tetrahydroquinolines - Rawat, Varun; Kumar, B. Senthil; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2013)
A new sequential organocatalytic method for the synthesis of chiral 3-substituted (X = OH, NH2) tetrahydroquinoline derivatives (THQs) [ee up to 99%, yield up to 87%] based on alpha-aminooxylation or -amination followed by reductive cyclization of o-nitrohydrocinnamaldehydes has been described. This methodology has been efficiently demonstrated in the synthesis of two important bioactive molecules namely (-)-sumanirole (96% ee) and 1-[(S)-3-(dimethylamino)-3,4-dihydro-6,7-dimethoxy-quinolin-1(2H)-yl]- propanone (92% ee).

Proline-catalyzed asymmetric synthesis of syn- and anti-1,3-diamines - Kumar, Pradeep; Jha, Vishwajeet; Gonnade, Rajesh G. (Journal of Organic Chemistry, 2013)
A general organocatalytic strategy for asymmetric synthesis of both syn/anti-1,3-diamines has been developed. The strategy employs proline-catalyzed sequential alpha-amination and Horner-Wadsworth-Emmons (HWE) olefination of aldehydes as the key step where syn-1,3-diamine was obtained as the most favorable product.

Promising stability of gold-based catalysts prepared by direct anionic exchange for DeNO (x) applications in lean burn conditions - Nguyen, D. -L.; Shubhangi B. Umbarkar; Dongare, Mohan K.; Lancelot, Christine; Girardon, J. S.; Dujardin, Christophe; Granger, P. (Topics in Catalysis, 2013)
Supported gold catalysts on gamma-Al2O3 have been investigated in the catalytic reduction of NO (x) in simulated Diesel exhaust gas conditions. Different parameters have been examined essentially the mode of gold incorporation via classical deposition-precipitation and anionic exchange methods and the nature of the pre-activation thermal treatment. The resistance to thermal ageing under reactive conditions at 500 A degrees C was found completely different with a significant rate enhancement on anionic-exchange samples. Further comparisons also show that the nature of the pre-activation thermal treatment influences the extent of surface reconstructions during thermal ageing with a detrimental effect of reductive pre-treatment on the catalytic performances.
Keywords: Anionic-exchange; Au/Al2O3 catalyst; Deposition-precipitation; NOx abatement; Selective catalytic reduction

Proposing late transition metal complexes as frustrated Lewis pairs - a computational investigation - Pal, Amrita; Vanka, Kumar (Dalton Transactions, 2013)
There has been considerable interest in recent times to develop transition metal complex systems that can demonstrate metal-ligand cooperativity. It has recently been shown (Wass et al., J. Am. Chem. Soc., 2011, 133, 18463) that early transition metals can cooperate with ligands carrying phosphines as pendant groups, working as metal analogues to frustrated Lewis pairs (FLPs) to mediate in a variety of important reactions. What the current work attempts to do is to show how this concept of metal containing FLPs can be expanded to include late transition metal complexes as well: complexes that have been modified from existing systems that serve as efficient catalysts for homogeneous polymerization. A modified palladium complex has been considered in this regard as an example of a potential late transition metal FLP and studied with full quantum mechanical calculations. The calculations indicate that this complex would be effective at catalyzing ammonia borane dehydrogenation. The possibility of competing side reactions such as reductive elimination have also been considered, and it has been found that such processes would also yield stable products which could act as an FLP in catalyzing reactions such as the dehydrogenation of ammonia borane. The current work therefore expands the scope of metal containing FLPs to include late transition metals and demonstrates computationally the potential of such complexes for exhibiting metal-ligand cooperativity.

Proteome wide reduction in AGE modification in streptozotocin induced diabetic mice by hydralazine mediated transglycation - Kesavan, Suresh K.; Bhat, Shweta; Golegaonkar, Sandeep B.; Jagadeeshaprasad, Mashanipalya G.; Deshmukh, Arati B.; Patil, Harshal S.; Bhosale, Santosh D.; Shaikh, Mahemud L.; Thulasiram, Hirekodathakallu V.; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Scientific Reports, 2013)
The non-enzymatic reaction between glucose and protein can be chemically reversed by transglycation. Here we report the transglycation activity of hydralazine using a newly developed MALDI-TOF-MS based assay. Hydralazine mediated transglycation of HbA1c, plasma proteins and kidney proteins was demonstrated in streptozotocin (STZ) induced diabetic mice, as evidenced by decrease in protein glycation, as well as presence of hydralazine-glucose conjugate in urine of diabetic mice treated with hydralazine. Hydralazine down regulated the expression of Receptor for Advanced Glycation End products (RAGE), NADPH oxidase (NOX), and super oxide dismutase (SOD). These findings will provide a new dimension for developing intervention strategies for the treatment of glycation associated diseases such as diabetes complications, atherosclerosis, and aging.

Proteomic analysis of protease resistant proteins in the diabetic rat kidney - Bansode, Sneha B.; Chougale, Ashok D.; Joshi, Rakesh S.; Giri, Ashok P.; Bodhankar, Subhash L.; Harsulkar, Abhay M.; Kulkarni, Mahesh J. (Molecular & Cellular Proteomics, 2013)
Glycation induced protein aggregation has been implicated in the development of diabetic complications and neurodegenerative diseases. These aggregates are known to be resistant to proteolytic digestion. Here we report the identification of protease resistant proteins from the streptozotocin induced diabetic rat kidney, which included enzymes in glucose metabolism and stress response proteins. These protease resistant proteins were characterized to be advanced glycation end products modified and ubiquitinated by immunological and mass spectrometry analysis. Further, diabetic rat kidney exhibited significantly impaired proteasomal activity. The functional analysis of identified physiologically important enzymes showed that their activity was reduced in diabetic condition. Loss of functional activity of these proteins was compensated by enhanced gene expression. Aggregation prone regions were predicted by in silico analysis and compared with advanced glycation end products modification sites. These findings suggested that the accumulation of protein aggregates is an inevitable consequence of impaired proteasomal activity and protease resistance due to advanced glycation end products modification. Molecular & Cellular Proteomics 12: 10.1074/mcp.M112.020651, 228-236, 2013.

Proteomic profiling and interactome analysis of ER-positive/HER2/neu negative invasive ductal carcinoma of the breast: towards proteomics biomarkers - Korwar, Arvind M.; Bhonsle, Hemangi S.; Ghole, Vikram S.; Gawai, Kachru R.; Koppikar, Chaitanyananda B.; Kulkarni, Mahesh J. (OMICS-A Journal of Integrative Biology, 2013)
Breast cancer, especially ER positive/HER2/neu negative IDC, is the predominant subtype of invasive ductal carcinoma. Although proteomic approaches have been used towards biomarker discovery in clinical breast cancer, ER positive/HER2/neu negative IDC is the least studied subtype. To discover biomarkers, as well as to understand the molecular events associated with disease progression of estrogen receptor positive/HER2/neu negative subtype of invasive ductal carcinoma, differential protein expression profiling was performed by using LC-MSE (MS at elevated energy). A total of 118 proteins were identified, of which 26 were differentially expressed. These identified proteins were functionally classified and their interactions and coexpression were analyzed by using bioinformatic tools PANTHER (Protein Analysis THrough Evolutionary Relationships) and STRING (Search Tool for the Retrieval of Interacting Genes). These proteins were found to be upregulated and were involved in cytoskeletal organization, calcium binding, and stress response. Interactions of annexin A5, actin, S100 A10, glyceraldehyde 3 phosphate dehydrogenase, superoxide dismutase 1, apolipoprotein, fibrinogen, and heat shock proteins were prominent. Differential expression of these proteins was validated by two-dimensional gel electrophoresis and Western blot analysis. The cluster of these proteins may serve as a signature profile for estrogen receptor positive/ HER2/neu negative subtype.

Proteomic study reveals downregulation of apolipoprotein A1 in plasma of poorly controlled diabetes: a pilot study - Bhonsle, Hemangi S.; Korwar, Arvind M.; Chougale, Ashok D.; Kote, Sachin S.; Dhande, Nitin L.; Shelgikar, Kishore M.; Kulkarni, Mahesh J. (Molecular Medicine Reports, 2013)
Proteomic approaches aid in gaining a better understanding of the pathophysiology of diabetic complications. In view of this, differential protein expression in diabetic plasma samples was studied by a combination of proteomic and western blot analyses. Diabetic plasma samples were categorized based on glycated haemoglobin levels as controlled diabetes (CD; 7-8%), poorly controlled diabetes (PCD; >8%) and non-diabetic control (ND;<6.4%). Two-dimensional electrophoresis and liquid chromatography-mass spectrometry revealed differential expression of proteins including upregulation of fibrinogen and haptoglobin and downregulation of vitamin D binding protein, alpha-1-antitrypsin, transthyretin and apolipoprotein A1 (Apo A1) in diabetic compared with non-diabetic plasma samples. Amongst these proteins, Apo A1 downregulation was prominent in PCD. Downregulation of Apo A1 may serve as an early predictive marker of diabetic complications.
Keywords: biomarker; HbA1c; proteomics

Proton-conducting supramolecular metallogels from the lowest molecular weight assembler ligand: a quote for simplicity - Saha, Subhadeep; Schoen, Eva-Maria; Cativiela, Carlos; Diaz, David Diaz; Banerjee, Rahul (Chemistry-A European Journal, 2013)
Oxalic acid has been proven to be the lowest molecular weight organic ligand able to form robust supramolecular metallogel networks in the presence of metal salts. In particular, two novel multifunctional metallogels were readily prepared at room temperature by simple mixing of stock solutions of Cu-II acetate monohydrate or Cu-II perchlorate hexahydrate and oxalic acid dihydrate. Formation of different polymorphs and unprecedented proton conduction under anhydrous conditions were also demonstrated with some of these materials.
Keywords: Copper; low-molecular-weight ligands; metallogels; proton conductivity; supramolecular chemistry

Purification and characterization of a thermolysin like protease from thermoactinomyces thalpophilus MCMB-380 - Majumder, Devipriya R.; Kanekar, Pradnya P.; Gaikwad, Sushama M. (Protein and Peptide Letters, 2013)
The extracellular thermolysin like protease (TLP) was purified and characterized from Thermoactinomyces thalpophilus MCMB-380 (Genbank Accession No. EF397000). The enzyme was purified to homogeneity by successive ultra filtration steps using 50 kDa and 10 kDa membrane filters followed by anion exchange chromatography. The molecular mass and isoelectric point of the enzyme were found to be 34.4 kDa and 9.5, respectively. The proteolytic activity was inhibited by EDTA and the enzyme required Ca2+ to show the full activity as well as thermostability. The T-50 of the enzyme at 80 degrees C was 1 h and the activation energy was estimated to be 11.02 Kcal / mol. Atomic absorption spectrophotometric analysis revealed the presence of Zn2+ ion in the protein core indicating that it is a metalloprotease. This protease has commercial potential in catalyzing the condensation reaction of two amino acids for production of the dipeptide aspartame, an artificial sweetener. The one hour time-frame is significantly faster than that of the enzyme thermolysin from Bacillus thermoproteolyticus. Moreover the TLP was stable at 80 degrees C for one hour which makes it industrially robust. The Zn2+ ion in the T. thalpophilus protease appears to be necessary for maintaining the active conformation of the enzyme molecule.
Keywords: Metalloprotease; Thermostability; TLP

Palladium nanoparticles supported on magnesium hydroxide fluorides: a selective catalyst for olefin hydrogenation - Acham, Vaibhav R.; Biradar, Ankush V.; Dongare, Mohan K.; Kemnitz, Erhard; Umbarkar, Shubhangi B. (ChemCatChem, 2014)
A one-pot synthesis of palladium nanoparticles supported on magnesium hydroxide fluoride has been performed with the fluorolytic sol-gel method. The prepared catalysts were characterized by using various physicochemical techniques. The sol-gel method led to high surface area (>135 m(2)g(-1)), mesoporous catalysts (pore volume=0.19-0.23 cm(3)g(-1), pore diameter=3-5 nm) with uniformly dispersed palladium nanoparticles approximately 2 nm in diameter on the surface. The catalysts synthesized by using different concentrations of aqueous hydrofluoric acid exhibited changing surface and acidic properties. Very high dispersion of palladium on magnesium fluoride (47%) was obtained with 1 wt% palladium loading. The catalysts were used for hydrogenation of various olefins in the presence of other organic functionalities at room temperature and atmospheric hydrogen pressure. Various substituted olefins were hydrogenated with almost 100% conversion and selectivity. The catalysts were recycled efficiently over five cycles without appreciable loss in catalytic activity. There was no palladium leaching under the reaction conditions, which was confirmed by inductively coupled plasma atomic emission spectroscopy analysis. Activation of olefin on the catalyst surface could not be observed by in situ FTIR studies, indicating facile activation of hydrogen on the palladium supported on magnesium hydroxide fluoride.
Keywords: alkenes; heterogeneous catalysis; Hydrogenation; magnesium fluorides; Palladium

Partitioned EOMEA-MBPT(2): an efficient N-5 scaling method for calculation of electron affinities - Dutta, Achintya Kumar; Gupta, Jitendra; Pathak, Himadri; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2014)
We present an N-5 scaling modification to the standard EOMEA-CCSD method, based on the matrix partitioning technique and perturbative approximations. The method has lower computational scaling and smaller storage requirements than the standard EOMEA-CCSD method and, therefore, can be used to calculate electron affinities of large molecules and clusters. The performance and capabilities of the new method have been benchmarked with the standard EOMEA-CCSD method, for a test set of 20 small molecules, and the average absolute deviation is only 0.03 eV. The method is further used to investigate electron affinities of DNA and RNA nucleobases, and the results are in excellent agreement with the experimental values.

PBI-BuI and PAN-PSSALi based UF membranes: effects of solute and membrane surface interactions on rejection and flux - Bhagat, Deepti G.; Mule, Bhavana; Mandlekar, Neeraj; Pandare, Kiran; Kharul, Ulhas K. (Desalination, 2014)
Ultrafiltration membrane using tert-butylpolybenzimidazole (PBI-BuI) was prepared and characterized for flux and rejection performance using Gel Permeation Chromatography (GPC). Polyethylene glycol (PEG) and polyethylene oxide (PEO) with different molecular weights were used as the solutes. While using feed solution containing mixture of PEGs, higher rejection was observed than using individual PEG. The water flux of PBI-BuI membrane after passing individual PEG solutions showed considerable (similar to 36%) reduction, which could be attributable to the PEG adsorption on the membrane pore surface. PEG adsorption was further substantiated by SEM, IR and TGA. The amphoteric nature of PBI-BuI could cause H-bonding between membrane surface and PEG molecules, leading to PEG adsorption on the membrane and pore surface. To ascertain this postulation, a study with PAN-PSSALi (which does not contain H-bonding) based UF membrane containing negatively charged -SO3- group was done. It was found that PEG adsorption in this case is not as predominant as in earlier case. This membrane showed marginal reduction in water flux of 8%, vis-a-vis 36% reduction shown by PBI-BuI based membrane. This indicated that H-bonding present in PBI-BuI is mainly responsible for the PEG adsorption on its membrane and pore surface, in spite of PEG being a neutral molecule. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Gel permeation chromatography; Polybenzimidazole; Rejection; Solute adsorption; Ultrafiltration

Pd-Phosphinesulfonate bravely battles the ``vinyl halide insertion copolymerization'' barricade - Gaikwad, Shahaji R.; Deshmukh, Satej S.; Chikkali, Samir H. (Journal of Polymer Science Part A-Polymer Chemistry, 2014)
This overview provides insights into the current state-of-the-art solutions to insertion copolymerization of functional olefinic monomers. The challenges in insertion copolymerization of functional olefinic monomers, with a special emphasis on vinyl halides, are highlighted. The crucial design of the Pd-phosphinesulfonate [Pd(PO)] enables up to 3.6 mol % incorporation of vinyl fluoride (VF) in an ethylene-VF copolymerization reaction. In a significant development, insertion copolymerization of industrially relevant functional olefin, that is, vinyl chloride (VC), was unambiguously ascertained, and a detectable amount of VC (0.4 mol %) was incorporated (at the chain end). In a detailed investigation, the in situ existence of (PO)PdH species during the polymerization was revealed, and it was demonstrated that these are indeed responsible for VC incorporation. (c) 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 1-6
Keywords: functional olefin; insertion copolymerization; palladium catalyst; phosphinesulfonate; vinyl chloride

Permeation of lipidated protein in bilayer using unbiased simulations reveals signature motif for protein-membrane binding - Thukral, Lipi; Sengupta, Durba; Gokhale, Rajesh S. (Biophysical Journal, 2014)

Perturbative approximation to hybrid equation of motion coupled cluster/effective fragment potential method - Ghosh, Debashree (Journal of Chemical Physics, 2014)
Hybrid quantum mechanics/molecular mechanics (QM/MM) methods provide an attractive way to closely retain the accuracy of the QM method with the favorable computational scaling of the MM method. Therefore, it is not surprising that QM/MM methods are being increasingly used for large chemical/biological systems. Hybrid equation of motion coupled cluster singles doubles/effective fragment potential (EOM-CCSD/EFP) methods have been developed over the last few years to understand the effect of solvents and other condensed phases on the electronic spectra of chromophores. However, the computational cost of this approach is still dominated by the steep scaling of the EOM-CCSD method. In this work, we propose and implement perturbative approximations to the EOM-CCSD method in this hybrid scheme to reduce the cost of EOM-CCSD/EFP. The timings and accuracy of this hybrid approach is tested for calculation of ionization energies, excitation energies, and electron affinities of microsolvated nucleic acid bases (thymine and cytosine), phenol, and phenolate. (C) 2014 AIP Publishing LLC.

Pharmaceutical solids in crystal engineering - Nangia, Ashwini (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: cocrystals; crystal engineering; Supramolecular synthon

Pharmacokinetic modeling of caco-2 cell permeability using genetic programming (GP) method - Vyas, Renu; Goel, Purva; Karthikeyan, Muthukumarasamy; Tambe, S. S.; Kulkarni, B. D. (Letters in Drug Design & Discovery, 2014)
An accurate prediction of the pharmacokinetic properties of orally administered drugs is of paramount importance in pharmaceutical industry. Caco-2 cell permeability is a well established parameter for assessing the drug absorption profiles of lead molecules. Due to the restrictions on animal testing, prohibitive in situ models and ethical issues, the development of predictive models is essential. Genetic programming (GP) is an artificial intelligence (AI)-based exclusively data driven modeling paradigm. Given an example input-output data, it searches and optimizes, both the structure and parameters of a well fitting linear/non-linear input-output model. Despite this novelty, GP has not been widely exploited in drug design. Accordingly, in this study we propose a GP based approach for the in silico prediction of Caco-2 cell permeability using a diverse set of molecules. The predictions yielded a high magnitude for the training and test set correlation coefficient with low RMSE, indicating accurate Caco-2 permeability prediction and generalization performance by the GP model. The predictions were better or comparable to artificial neural networks (ANN) and support vector regression (SVR) methods. The GP based modeling approach illustrated will find diverse applications in (QSAR, QSPR and QSTR) modeling for the virtual screening of large libraries.
Keywords: ADME modeling; Caco-2 cell permeability; genetic programming; MLP; SVR

pH-Dependent single-step rapid synthesis of cuo and cu2o nanoparticles from the same precursor - Nikam, Arun V.; Arulkashmir, Arulraj; Krishnamoorthy, Kothandam; Kulkarni, Amol A.; Bhagavatula L. V. Prasad (Crystal Growth & Design, 2014)
A single-step protocol to prepare Cu2O and CuO nanocrystalline particles from the same precursor by microwave irradiation has been developed using the pH of the solution as the only variable parameter. The utility of different bivalent Cu-precursors for synthesis of CuO and Cu2O nanoparticles was also investigated. The morphology, phase purity, and optical properties of these nanoparticles were analyzed using TEM, SEM, XRD, and optical spectroscopy. The band edges were determined using cyclic voltammetry. Field effect transistors based on CuO nanoparticles showed a hole mobility of 3.5 x 10(-2) cm(2) V-1 s(-1), making them a suitable candidate for energy-related applications. The effect of hydrazine vapor exposure on the IV-characteristics of CuO nanoparticles was also investigated. This revealed a decrease in source current with respect to time.

Phosphine free SBA-15-EDTA-Pd highly active recyclable catalyst: synthesis characterization and application for suzuki and sonogashira reaction - Sharma, Priti; Singh, A. P. (Catalysis Science & Technology, 2014)
Phosphine obstructed highly efficient and reusable SBA-15-EDTA-Pd(11) has been synthesized by anchoring a Pd-EDTA complex over the surface of organo-functionalized SBA-15. The physiochemical properties of the organo-functionalized catalyst were analyzed by elemental analysis, ICP-OES, XRD, N-2 sorption measurement isotherms, TGA and DTA, solid state C-13, Si-29 NMR spectroscopy FT-IR, XPS DRS UV-visible, SEM and TEM. The XRD and N-2 sorption analyses of the synthesized catalyst confirm that the ordered mesoporous channel structure was retained even after the multistep synthetic procedures. The (100), (110) and (200) reflections in SBA-15 provide a good structural stability, an the existence of a long range order and high pore wall thickness. The TGA-DTA results reveal that the thermal stability of the synthesized catalyst SBA-15-EDTA-Pd(11) was maintained at higher temperature. The organic moieties anchored over the surface of the SBA-15 and inside the pore wall were demonstrated by solid state C-13 NMR and FT-IR spectroscopy. Further, solid state Si-29 NMR spectroscopy provides information about the degree of functionalization of the surface silanol groups, of the SBA-15 with organic moieties. The electronic environment and oxidation state of the Pd metal in the SBA-15-EDTA-Pd(11) were monitored by XPS, and DRS UV-visible techniques. Moreover, the morphologies and topographic information of the synthesized catalyst were confirmed by SEM and TEM spectroscopy. The synthesized catalyst SBA-15-EDTA-Pd(11) was screened for the Suzuki and Sonogashira coupling reactions and shows a higher catalytic activity with higher TON (turn over number). The anchored solid catalyst can be recycled efficiently and reused five times, without a major loss in the reactivity.

Phosphoric acid loaded azo (-N=N-) based covalent organic framework for proton conduction - Chandra, Suman; Kundu, Tanay; Kandambeth, Sharath; BabaRao, Ravichandar; Marathe, Yogesh N.; Kunjir, Shrikant M.; Banerjee, Rahul (Journal of the American Chemical Society, 2014)
Two new chemically stable functional crystalline covalent organic frameworkds (COFs) (Tp-Azo and Tp-Stb) were synthesized using the Schiff base reaction between triformylphloroglucinol (Tp) and 4,4'-azodianiline (Azo) or 4,4'-diaminostilbene (Stb), respectively. Both COFs show the expected keto-enamine form, and high stability toward boiling water, strong acidic, and basic media. H3PO4 doping in Tp-Azo leads to immobilization of the acid within the porous framework, which facilitates proton conduction in both the hydrous (sigma = 9.9 X 10(-4) S cm(-1)) and anhydrous state (sigma = 6.7 X 10(-5) S cm-1). This report constitutes the first emergence of COFs as proton conducting materials.

Photocatalytic H-2 evolution from water-methanol system by anisotropic InFeO3(ZnO)(m) oxides without cocatalyst in visible light - Narendranath, Soumya B.; Yadav, Ashok Kumar; Bhattacharyya, Dibyendu; Jha, Shambhu Nath; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2014)
InFeO3(ZnO)(m), series of oxides are found to give unprecedented H-2 evolution from water-methanol mixtures without using any cocatalysts. This family of compounds has an anisotropically layered structure in which Zn/FeOn polyhedra are sandwiched between InO6 octahedral layers. Local structure characterization by X-ray absorption spectroscopy reveals that Zn coordination changes from pentacoordinated to tetrahedral geometry across the series, whereas Fe geometry remains trigonal bipyramidal in all the compounds. This peculiar structure is conducive for a spatial separation of photogenerated charges reducing recombination losses. Band gap energies calculated from absorption spectra indicate potential visible light activity, and this may be due to the orbital mixing of Fe 3d and O 2p as revealed by pre-edge features of X-ray absorption spectra. Band positions are also advantageously placed for a visible light H-2 generation and is indeed found to be the case in methanol-assisted water splitting with standardized hydrogen evolution of similar to 19.5 mmol g(-1) h(-1) for all the catalysts.
Keywords: anisotropic structure; H-2 evolution; InFeO3(ZnO)(m); layered oxide; photocatalytic water splitting

Photocatalytic metal-organic framework from cds quantum dot incubated luminescent metallohydrogel - Saha, Subhadeep; Das, Gobinda; Thote, Jayshri; Banerjee, Rahul (Journal of the American Chemical Society, 2014)
Cadmium sulfide (CdS) quantum dots (<10 nm in size) have been successfully synthesized in situ without any capping agent in a Zn(II)-based low-molecular-weight metallohydrogel (ZAVA). Pristine ZAVA hydrogel shows blue luminescence, but the emission can be tuned upon encapsulation of the CdS quantum dots. Time-dependent tunable emission (white to yellow to orange) of the CdS incubated gel (CdS@ZAVA gel) can be attributed to sluggish growth of the quantum dots inside the gel matrix. Once CdS quantum dots are entrapped, their augmentation can be stopped by converting the gel into xerogel, wherein the quantum dots remains embedded in the solid xerogel matrix. Similar size stabilization of CdS quantum dots can be achieved by means of a unique room-temperature conversion of the CdS incubated ZAVA gel to CdS incubated MOF (CdS@ZAVCl) crystals. This in turn arrests the tunability in emission owing to the restriction in the growth of CdS quantum dots inside xerogel and MOF. These CdS embedded MOFs have been utilized as a catalyst for water splitting under visible light.

Photochromic metal organic frameworks for inkless and erasable printing - Garai, Bikash; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Erasable Printing; Inkless Printing; metal organic framework

Photoelectrochemical splitting of water with nanocrystalline Zn1-xMnxO thin films: first-principle DFT computations supporting the systematic experimental endeavor - Sharma, Vidhika; Dixit, Mudit; Satsangi, Vibha R.; Dass, Sahab; Pal, Sourav; Shrivastav, Rohit (International Journal of Hydrogen Energy, 2014)
Photoelectrochemical splitting of water with nanocrystalline Zn1-xMnxO thin films was investigated. ZnO thin films with 1, 3, 5 and 7% at. Mn incorporation were synthesized by sol gel method and characterized by X-Ray Diffraction (XRD) analysis, Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM), X-ray Photoelectron spectroscopy (XPS), High Resolution Transmission Electron Microscopy (HR-TEM) and UV-Vis spectroscopy. Mn incorporation coupled with variation in sintering temperature led to significant microstructural changes, which tentatively influenced the magnitude of optical absorption and charge carrier mobility, thereby impacting the performance of such systems towards photoelectrochemical splitting of water. Electronic structure computations based on first principle density functional theory (DFT) revealed electronic states of Mn being responsible for the marginally recorded red shift in bandgap energy. Photoelectrochemical measurements using thin films of 1% at. Mn:ZnO sintered at 600 degrees C yielded 3 times enhanced photocurrent at zero bias due to improved optical absorption. Plausible explanations for the effect have also been offered. Copyright (C) 2014, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Density functional theory; Hydrogen energy; Mn doped ZnO; Optical properties; Photoelectrochemical water splitting

Photo-enhanced field emission studies of tapered CdS nanobelts - Chavan, Padmakar G.; More, Mahendra A.; Joag, Dilip S.; Badadhe, Satish S.; Mulla, Imtiaz S. (2014 27th International Vacuum Nanoelectronics Conference (IVNC), 2014)
Field emission and photo-enhanced field emission characteristics of single crystalline tapered CdS nanobelts have been investigated. The turn-on field for the emission current density of similar to 0.1 mu A/cm(2) is found to be similar to 2.1 V/mu m, which is much lower than reported values for various CdS nanostructures. The photo-enhanced field emission current shows a reproducible photo-switching behavior with rise in current level nearly four times that of its initial preset value (similar to 1 mu A) which is found to be very remarkable. Possible mechanism of photo-enhanced field emission is discussed.
Keywords: Current stability; field emission; Nanobelts; Photoswitching

Photophysical and photoconductivity properties of thiol-functionalized graphene-CdSe QD composites - Debgupta, Joyashish; Mandal, Sadananda; Kalita, Hemen; Aslam, Mohammed; Patra, Amitava; Pillai, Vijayamohanan (RSC Advances, 2014)
Graphene-semiconductor QD hybrid nanostructure materials have recently emerged as a new class of functional materials because of their potential applications in solar energy conversion, optoelectronic devices, sensing etc. Here, oleic acid-capped CdSe QDs are attached to -PhSH functionalized graphene by ligand exchange via bonding with the -SH group. The shifting of the G-band and D-band due to structural changes for the attachment of QD with graphene has been evaluated by using Raman spectroscopy. Steady state photoluminescence (PL) and time resolved fluorescence measurements have been employed to understand the electronic interactions between graphene and CdSe QDs. A time resolved fluorescence spectroscopic study has been used to understand the fluorescence dynamics of the photoexcitated CdSe QDs in the presence of graphene. It is evident that the electron transfer occurs from photoexcited QDs to graphene and the electron transfer rate is found to be 12.8 x 10(8) s(-1) for 3.8 nm CdSe QDs. Photoconductivity properties of the graphene-QD device under illumination have been examined and it is to be noted that 2-3 fold increase in the photocurrent is found in this composite device in presence of 1.5 AM solar simulated light. The enhancement of the photocurrent in this hybrid device is found to be suitable for potential applications in optoelectronic and solar cell systems.

Photophysical, bandstructural, and textural properties of o-FeNbO4 in relation to its cocatalyst-assisted photoactivity for water oxidation - Babu, Robin; Kelkar, Sarika A.; Kashid, Vikas; Achary, Srungarpu N.; Salunke, Hemant G.; Gupta, Narendra M. (RSC Advances, 2014)
In this study, a relationship between physicochemical, photophysical and photocatalytic properties of hydrothermally synthesized orthorhombic iron niobate (FeNbO4) is investigated. o-FeNbO4 displayed a multi-regime optical absorbance, which was ascribed to at least two distinct phenomena: (i) bandgap (similar to 3.4 eV) excitation giving rise to UV absorbance and (ii) energy transitions involving disorder-induced sub-bandgap donor or acceptor states leading to visible light absorbance. The preparation-dependent distortion in the crystal lattice and the existence of closely spaced inter-bandgap energy states were corroborated by powder X-ray diffraction, photoluminescence, thermoluminescence, and Raman spectroscopy studies. The first principles electronic structure elucidation and photoelectrochemical measurements supported a wide bandgap for FeNbO4, in contrast to the narrow bandgap reported previously. Correspondingly, a small photocurrent density was observed for FeNbO4 (similar to 2 to 3 mu A cm(-2)) under 1 sun illumination, suggesting the availability of a smaller cross section of photogenerated charge pairs. Following these band characteristics, while no H-2 evolution was observed, FeNbO4 gave rise to particle size-dependent O-2 evolution during visible light irradiation of water in the presence of electron scavengers, the samples loaded with NiO as cocatalyst showing better activity. Further, the transmission electron microscopy examination revealed the dominant exposure of (011) facets of FeNbO4, besides a significant heterogeneity of inter-domain boundaries. Overall, our results confirm that the photoactivity of metal/oxide nanocomposites is governed by a combination of factors, such as: grain morphology, microstructure, surface adsorption states, and the localized inter-bandgap energy states. Our study also reveals that, in contrast to prevalent assumptions, the wavelength at the absorption edge may not represent the true band-to-band energy gap of metal oxide semiconductors, which is relevant to their photocatalytic activity.

Photopolymerization kinetics of bis-aromatic based urethane acrylate macromonomers in the presence of reactive diluent - Harikrishna, Reghunathan; Ponrathnam, S.; Rajan, C. R. (Progress in Organic Coatings, 2014)
The present work deals with the photopolymerization of bis-aromatic based urethane acrylate macromonomers in the presence of excess end capping agent as reactive diluent and estimation of their kinetic parameters. Formulations were made by independently homogenizing the macromonomers with photoinitiators of three different classes. Three different compositions of photoinitiators were used to study the effect of concentration of photoinitiator on cure kinetics. These compositions obtained were tested for photo curing performance using photo DSC under polychromatic radiation. The heat flows against time were recorded for all formulations under isothermal condition and the rates of polymerization, peak maximum times as well as the percentage conversions were estimated. It was observed that due to a longer timescale for reaction diffusion, formulations with macromonomer containing propoxylated backbone showed higher conversions than the corresponding ethoxylated analogue. The photopolymerization and kinetic estimations of the formulations including evaluation of kinetic model are discussed. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Bimolecular termination model; kinetics; Macromonomer; Photopolymerization

Photopolymerization kinetics of block polyether based terminal urethane methacrylate with/without cross-linker - Reghunathan, Harikrishna (Advances in Polymer Technology, 2014)
The present work deals with the photopolymerization of difunctional macromonomer with a polyether chain and urethane methacrylate terminations. Macromonomeric formulations were prepared by mixing macromonomer with two different concentrations of photoinitiator. Formulations were also prepared by the addition of 10 wt% of soft-segmented difunctional cross-linker to the abovementioned macromonomic formulations. All formulations were then subjected to photopolymerization studies and the effects of light intensity on the photopolymerization kinetics were studied at two different isothermal conditions using photo differential scanning calorimetry (Photo DSC) with polychromatic radiation. The isothermal heat flow against time was recorded for all formulations and the kinetic parameters were noted. It was observed that the rate of maximum polymerization as well as peak maximum time showed a general trend. However, the ultimate conversion as well as the conversion at maximum rate did not show any trend due to diffusional restrictions imparted by the increase in viscosity with conversion. The photopolymerization of the formulations and curing kinetics including evaluation of autocatalytic model are discussed. (C) 2014 Wiley Periodicals, Inc.
Keywords: kinetics; Macromonomers; Modeling; Photo DSC; Photopolymerization

Photopolymerization of high internal phase emulsions based on 2-ethylhexyl (meth)acrylates and ethylene glycol dimethacrylate - Harikrishna, Reghunathan; Shaikh, A. W.; Ponrathnam, S.; Rajan, C. R.; Bhongale, Sunil Sitaram (Designed Monomers and Polymers, 2014)
Photopolymerization of high internal phase emulsions based on 2-ethylhexyl (meth)acrylates and ethylene glycol dimethacrylate was carried out in presence of low concentration of different photoinitiators. The stable emulsions obtained by mixing with individual photoinitiators were subjected to low-intensity photopolymerization under UV-Visible lamp. Identical samples were irradiated for differing periods ranging from 2 to 10min at an interval of 2min. The percentage conversions of each monomer in the compositions with respect to the time of irradiation were determined using gas chromatography. It was observed that the formulations containing IRGACURE 819 showed the highest conversion while that containing IRGACURE 2959 showed the least conversion. The former showed high conversion due to the proximity of the absorption maxima of photoinitiator to the major emission line of mercury spectrum at 365nm while the latter showed least conversion due to non-availability of major absorption maxima within the irradiation range.
Keywords: (meth)acrylates; high internal phase emulsion; Photopolymerization; residual monomer analysis

Photoresponsive smectic liquid crystalline multipods and hyperbranched azo polymers - Nardele, Chinmay G.; Asha, S. K. (Journal of Physical Chemistry B, 2014)
Liquid crystalline azobenzene containing triped and tetraped monomers were designed and synthesized and further used as B-3 and B-4 type monomers to form hyperbranched polymers with tetraethylene glycol as the A(2) type comonomer. The mesophase characteristics of the multiarm-star mesogens and hyperbranched polymers were analyzed using various instrumentation techniques like differential scanning calorimetry (DSC), polarized light microscopy (PLM) and variable temperature XRD. The multipod monomers as well as hyperbranched polymers exhibited thermotropic smectic liquid crystalline characteristics with a tendency toward higher ordered smectic LC phases with increased branching. The hyperbranched polymers exhibited lamellar organization even in the as-solvent precipitated powder sample indicating higher extent of nanosegregation. Their potential application as fast switching photochromic materials was highlighted by carrying out isothermal photo-switching experiments in the LC state. Reversible isothermal smectic-isotropic phase transition could be achieved by UV irradiation in <1 s in the multipod monomers, while it required >2 s UV irradiation in the case of the hyperbranched polymers.

Photosensitive field emission study of SnS2 nanosheets (27th International Vacuum Nanoelectronics Conference ) - Joshi, Padmashree D.; Joag, Dilip S.; Rout, Chandra Shekhar; Late, Dattatray J. (2014 27TH International Vacuum Nanoelectronics Conference (IVNC), 2014)
SnS2 nanosheets (SnS(2)NSs), synthesized by one-step hydrothermal reaction, are subjected to Field Emission (FE) studies. For synthesis, specific concentrations of Na2SnO3 and thioamide solution are used. The FE study is carried out in all metal Ultra High Vacuum (UHV) chamber in planar diode configuration at a base pressure of similar to 10(-8) torr. A maximum current density of 110 mu A/cm(2) was attainable. The turn on field required to draw a current density of 1 mu A/cm(2) is found to be 2.6 V/mu m. A separate study was carried out to investigate the photosensitivity of the emitter by illuminating the specimen under visible light. In dark, the FN plot is non-linear, indicative of semiconductor nature of the emitter. However, on illumination, the FN plot is observed to be linear. This remarkable change can be explained by the photoconductivity imparted on illumination. The field at the tip is high in presence of light, than in dark, due to enhanced conductivity. It is also observed that on switching ON the light, the FE current increases almost instantaneously. Repetitive switching is observed at a fixed applied voltage, generating current pulses. The visible light soaking of the sample is carried out by illuminating the lamp for more than 100 minutes, where the current seems to saturate. On switching off the lamp the emission current decayed almost to its initial value exponentially. The photosensitivity has been studied for different wavelengths in the visible spectra. The maximum photosensitive field emission is observed for green filter. With this photoresponse, it is envisaged that SnS2 nanosheets are a potential candidate for optoelectronic applications of field emitters.
Keywords: field emission; photosensitivity; Photoswitching

Plasmon-enhanced photocurrent generation from click-chemically modified graphene - Yenchalwar, Sandeep G.; Devarapalli, Rami Reddy; Deshmukh, Ashvini B.; Shelke, Manjusha V. (Chemistry-A European Journal, 2014)
The visible-light response of Au nanoparticles (AuNPs) assembled on rGO through different molecular bridges was investigated by transient photocurrent generation. We prepared rGO with two self-assembled monolayers (SAMs), one linear and the other with aromatic triazoles through a click cycloaddition reaction. A fivefold photocurrent enhancement was observed for triazole linkers over the aminopropyltrimethoxysilane (APTMS) linker. Cyclic voltammetry (CV) and impedance measurements also suggest fast electron transfer on account of the low resistance offered by the click-modified rGO surface whereby introduction of triazoles offers the efficient bridge between the donor AuNPs and acceptor rGO.
Keywords: Gold; graphene; Nanoparticles; photophysics; surface plasmon resonance

Plasmonic light harvesting of dye sensitized solar cells by Au-nanoparticle loaded TiO2 nanofibers - Naphade, Rounak A.; Tathavadekar, Mukta; Jog, Jyoti P.; Agarkar, Shruti; Ogale, Satishchandra (Journal of Materials Chemistry A, 2014)
We report a significant enhancement in the performance of dye sensitized solar cells by using in situ Au nanoparticle (Au NP) loaded TiO2 nanofibers (Au: TiO2 NFs) as the light harvesting (LH) layer as compared to the use of only TiO2 nanofibers (NFs) as the LH layer. The Au NP: TiO2 nanofibers are prepared by electro-spinning of a precursor mixture whereby nanostructured porous TiO2 nanofibers are formed and get in situ loaded with only 4-5 nm AuNPs. The as-synthesized nanofibers are characterized by X-ray diffraction, Raman, photoluminescence (PL) and Mott-Schottky analyses. The presence of gold nanoparticles shows considerable improvements in light harvesting and the electrochemical properties of TiO2 nanofibers. A remarkable enhancement in the efficiency by 25% is achieved with the AuNF LH layer as compared to 12% with the NF layer, over the value without any light harvesting layer. The IPCE and impedance analyses reveal commensurate improvements. The impedance study shows a decrease in the transport resistance (R-TiO2) and an increment in the chemical capacitance and life time of the solar cell. Systematic analyses of the optical properties suggest that the enhanced light harvesting by Au NP loaded TiO2 nanofibers is caused by the role of plasmon-polariton modes at the distributed nanoscale Schottky junctions in the Au: TiO2 nanofibers.

Polarization switching characteristics of 0.5BaTi(0.8)Zr(0.2)O(3)-0.5Ba(0.7)Ca(0.3)TiO(3) lead free ferroelectric thin films by pulsed laser deposition - Kolekar, Y. D.; Bhaumik, A.; Shaikh, P. A.; Ramana, C. V.; Ghosh, K. (JOURNAL OF APPLIED PHYSICS, 2014)
We report on the ferroelectricity for morphotropic-phase-boundary lead (Pb) free 0.5BaTi(0.8)Zr(0.2)O(3)-0.5Ba(0.7)Ca(0.3)TiO(3) (0.5BZT-0.5BCT) thin films. Thin films were grown on Pt/Ti/SiO2/Si substrate using pulsed laser deposition. Raman spectroscopic data combined with the X-ray diffraction analyses confirm body centered tetragonal crystallographic structure 0.5BZT-0.5 BCT thin films on Pt/Ti/SiO2/Si. Polarization studies demonstrate that these 0.5BZT-0.5BCT films exhibit a large remnant and saturation polarization of 37 mu C/cm(2) and 40 mu C/cm(2), respectively, with a coercive field of 140 kV/cm. A correlation between polarization dynamics, structural distortion, and phonon vibration is established. The splitting of X-ray diffraction peak of the thin film in the 2 theta range of 44.5 degrees to 46.5 degrees represents high degree of tetragonality. The tetragonality factor calculated by Rietveld analysis was found to be 0.006 and can be a major cause for the increased remnant polarization value. It is established from Raman spectra that the non-centrosymmetricity due to the displacement of Ti/Zr ions from its octahedral position is related to the peak position as well as the broadening of the A(1) (LO) optical phonon mode. This increase of broadness in the thin film causes an increase in the dipole moment of the unit cell and, hence, the net increase in polarization values. (C) 2014 AIP Publishing LLC.

Poly (3,4-ethylenedioxythiophene) (PEDOT) and poly (3,4-ethylenedioxythiophene)-few walled carbon nanotube (PEDOT-FWCNT) nanocomposite based thin films for Schottky diode application - Gupta, Bhavana; Mehta, Minisha; Melvin, Ambrose A.; Kamalakannan, R.; Dash, Sitaram; Kamruddin, M.; Tyagi, A. K. (Materials Chemistry and Physics, 2014)
Transparent, conductive films of poly (3,4-ethylenedioxythiophene) (PEDOT) and poly (3,4-ethylenedioxythiophene)-few walled carbon nanotube (PEDOT-FWCNT) nanocomposite were synthesized by in-situ oxidative polymerization and investigated for their Schottky diode property. The prepared films were characterized by UV-Vis spectroscopy, thermal gravimetric analysis (TGA), surface resistivity, cyclic voltametery, scanning electron microscopy (SEM) and high resolution transmission electron microscopy (HRTEM). SEM reveals the formation of homogeneous and adhesive polymer films while HRTEM confirms the uniform wrapping of polymer chains around the nanotube walls for PEDOT-FWCNT film. Improved thermal stability, conductivity and charge storage property of PEDOT in the presence of FWCNT is observed. Among different compositions, 5 wt. % of FWCNT is found to be optimum with sheet resistance and transmittance of 500 Omega sq(-1) and 77%, respectively. Moreover, the electronic and junction properties of polymer films were studied and compared by fabricating sandwich type devices with a configuration of Al/PEDOT or PEDOT-FWCNT nanocomposite/indium tin oxide (ITO) coated glass. The measured current density-voltage characteristics show typical rectifying behavior for both configurations. However, enhanced rectification ratio and higher forward current density is observed in case of PEDOT-FWCNT based Schottky diode. Furthermore, reliability test depicts smaller hysteresis effect and better performance of PEDOT-FWCNT based diodes. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Composite materials; Electrical properties; Polymer; Thin films

Polybenzimidazole based film forming polymeric ionic liquids: synthesis and effects of cation-anion variation on their physical properties - Bhavsar, Rupesh S.; Kumbharkar, Santosh C.; Rewar, Anita S.; Kharul, Ulhas K. (Polymer Chemistry, 2014)
Polymeric ionic liquids (PILs) are gaining wide attention due to their tunable properties and applicability in various upcoming areas, including membranes for CO2 separation. The known methodologies yield PILs that are difficult to convert into film form. The present work investigates a synthetic approach for obtaining PILs based on a strong film forming with a fully aromatic rigid backbone while incorporating ionic liquid character in it. Three structurally different polybenzimidazoles (PBI-I, PBI-BuI and ABPBI) were N-quaternized by a methyl group, followed by iodide exchange with various promising anions. The extent of iodide exchange by another anion was high enough (>94% in most cases). Most of the resulting PILs with various anions offer mechanically strong films, with the exception of those based on acetate and benzoate as an anion. Although the base PBI has excellent film forming ability, this result conveyed the role of anion in governing the film forming ability of the PIL. Salient features of this methodology include a fully aromatic polycation backbone, wide structural tunability (by virtue of variation not only of the anion/cation, but also with N-substituent) and introducing two IL characters per repeat unit of a PIL (except for PILs based on ABPBI). Attempted PIL structural variations showed diverse property variations in bulk and surface properties (solvent solubility, contact angle, water sorption, thermal stability, polyelectrolyte behaviour, CO2 sorption and ionic conductivity). Mechanical properties of film forming PILs exhibited high enough tensile strength, conveying their applicability as membrane materials.

Polyketide synthesis in tobacco plants transformed with a plumbago zeylanica type III hexaketide synthase - Jadhav, Supriya; Phapale, Prasad; Thulasiram, Hirekodathakallu V.; Bhargava, Sujata (Phytochemistry, 2014)
A type III polyketide synthase from Plumbago zeylanica (PzPKS) was cloned and expressed in tobacco plants to study whether the transgenic tobacco plants expressing PzPKS synthesize the pharmacologically important polyketide, plumbagin. High resolution mass spectrometry based metabolite profiling of two transgenic events and wild type tobacco plants was carried out to investigate changes in polyketides, including plumbagin. Ten polyketides, which included six pyrones and four naphthalene derivatives, were identified in PzPKS transgenic plants. While one pyrone, styry1-2-pyranone, was detected in both, wild type and transgenic tobacco plants, three pyrones were expressed only in the leaves of transgenic tobacco plants. The transgenic tobacco plants did not accumulate plumbagin, but showed accumulation of isoshinanolone in the roots, which is postulated to be the reduction product of plumbagin. In addition, leaves of transgenic tobacco plants accumulated 3-methyl-1,8-naphthalenediol, a postulated precursor of plumbagin. The results indicated the requirement of additional Plumbago-specific components in the biosynthetic pathway of this polyketide. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: HR-MS; Metabolite profiling; Napthalene derivatives; Plumbago zeylanica L.; Polyketide synthase; Pyrones; Tobacco transgenics

Polystyrene/TiO2 composite electrospun fibers as fillers for poly(butylene succinate-co-adipate): Structure, morphology and properties - Neppalli, Ramesh; Causin, Valerio; Benetti, Edmondo Maria; Ray, Suprakas Sinha; Esposito, Antonella; Wanjale, Santosh; Birajdar, Mallinath S.; Saiter, Jean-Marc; Marigo, Antonio (European Polymer Journal, 2014)
In this work, composite polystyrene/titanium dioxide (PS/TiO2) electrospun fibers were used as a reinforcement for a poly(butylene succinate-co-adipate) (PBSA) matrix. The structure, morphology, mechanical properties and degradation behavior of such materials were investigated, finding that, as a function of their TiO2 content, the fibers exerted different effects. The main mechanism through which the fibers modified the structure and morphology of the polymer matrix is by altering its crystallization kinetics. The presence of TiO2 modified the roughness of the fibers and therefore affected the interfacial adhesion between the filler and the matrix. The modulus of PBSA was improved, even though the brittleness of the materials was increased by the presence of the fibers. Different amounts of TiO2 within the fibers allowed to tune the hydrolytic degradation rate of the composites. This paper shows the potential of using composite electrospun fibers as effective fillers for the preparation of polymer-based composites. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Biodegradable polymers; Degradation; electrospinning; Morphology; Nanocomposites; Polycaprolactone

Porous porphyrin organic polymer for visible light triggered hydrogen production - Mukherjee, Gargi (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Photocatalysis; Porous Porphyrin Organic Polymer (PPOP); titania

Post modification of MOF derived carbon via g-C3N4 entrapment for an efficient metal-free oxygen reduction reaction - Pandiaraj, Sekar; Aiyappa, Harshitha Barike; Banerjee, Rahul; Kurungot, Sreekumar (Chemical Communications, 2014)
High surface area carbon with a nitrogen content of 7.0% is derived from MOF via in situ g-C3N4 formation. The material shows excellent ORR activity with an onset potential of 0.035 V (vs. Hg/HgO) in alkaline medium apart from high durability and strong disinclination towards methanol crossover.

Post-synthetically modified porous covalent framework (PCF) for high proton conduction - Samanta, Partha; Desai, Aamod; Anothumakkool, Bihag; Shirolkar, Mandar; Karmakar, Avishek; Kurungot, Sreekumar; Ghosh, Sujit (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Porous Covalent Framework; Post-synthetic Modification; proton conduction

Practical synthesis of phthalimides and benzamides by a multicomponent reaction involving arynes, isocyanides, and CO2/H2O - Kaicharla, Trinadh; Thangaraj, Manikandan; Biju, Akkattu T. (Organic Letters, 2014)
Transition-metal-free multicomponent reactions involving arynes and isocyanides with either CO2 or H2O have been reported. With CO2 as the third component, the reactions resulted in the formation of N-substituted phthalimides. The utility of water as the third component furnished benzamide derivatives in moderate to good yields. These reactions took place under mild conditions with broad scope.

Prediction of higher heating value of solid biomass fuels using artificial intelligence formalisms - Ghugare, Suhas B.; Tiwary, S.; Elangovan, V.; Tambe, S. S. (Bioenergy Research, 2014)
The higher heating value (HHV) is an important property defining the energy content of biomass fuels. A number of proximate and/or ultimate analysis based predominantly linear correlations have been proposed for predicting the HHV of biomass fuels. A scrutiny of the relationships between the constituents of the proximate and ultimate analyses and the corresponding HHVs suggests that all relationships are not linear and thus nonlinear models may be more appropriate. Accordingly, a novel artificial intelligence (AI) formalism, namely genetic programming (GP) has been employed for the first time for developing two biomass HHV prediction models, respectively using the constituents of the proximate and ultimate analyses as the model inputs. The prediction and generalization performance of these models was compared rigorously with the corresponding multilayer perceptron (MLP) neural network based as also currently available high-performing linear and nonlinear HHV models. This comparison reveals that the HHV prediction performance of the GP and MLP models is consistently better than that of their existing linear and/or nonlinear counterparts. Specifically, the GP- and MLP-based models exhibit an excellent overall prediction accuracy and generalization performance with high (> 0.95) magnitudes of the coefficient of correlation and low (< 4.5 %) magnitudes of mean absolute percentage error in respect of the experimental and model-predicted HHVs. It is also found that the proximate analysis-based GP model has outperformed all the existing high-performing linear biomass HHV prediction models. In the case of ultimate analysis-based HHV models, the MLP model has exhibited best prediction accuracy and generalization performance when compared with the existing linear and nonlinear models. The AI-based models introduced in this paper due to their excellent performance have the potential to replace the existing biomass HHV prediction models.
Keywords: Artificial intelligence; Artificial neural networks; Biomass fuels; genetic programming; Higher heating value; Multilayer perceptron

Preferential growth of Au on CdSe quantum dots using langmuir-blodgett technique - Das, Subhasis; Satpati, Biswarup; Chauhan, Himani; Deka, Sasanka; Gopinath, Chinnakonda S.; Bala, Tanushree (RSC Advances, 2014)
Oleyl amine capped CdSe quantum dots (QD) were synthesised by hot injection technique. These QDs formed a self-assembled monolayer on an aqueous subphase of a Langmuir-Blodgett (LB) trough. Here, in this report we introduced a simple but very efficient route to form a metal (Au)-QD hybrid nanostructure via the LB technique. In this method, the metal counterpart of the hybrid nanostructure could be deposited exclusively on one side of the QDs. The formation of stable monolayer of QDs was evidenced from a surface pressure-area (P-A) isotherm. The development of gold tip was confirmed and monitored by detailed TEM study on the monolayer deposited on TEM grids from the LB trough. Other characterizations like UV-Vis spectroscopy, FTIR, XPS and EDX also suggested the same. Oleyl amine was shown to act both as a reducing agent as well as a capping agent in this strategy.

Preparation and characterization of porous fly ash/NiFe2O4 composite: promising adsorbent for the removal of congo red dye from aqueous solution - Sonar, Shilpa K.; Niphadkar, Prashant S.; Mayadevi, S.; Joshi, Praphulla N. (Materials Chemistry and Physics, 2014)
A series of fly ash/NiFe2O4 composites were prepared using fly ash and aqueous solutions of Ni, Fe nitrate salts and NaOH by co-precipitation followed by calcination method. The % mass ratio of fly ash: NiFe2O4 was varied in the range of 0:100 to 100:0. Samples were characterized by powder XRD, SEM, FTIR and N-2 adsorption-desorption measurements. These samples were further evaluated for their adsorptive performance in removal of Congo red (CR) dye from an aqueous solution. In all the composites, spinel nickel ferrite phase was found to be capable to get anchored with the fly ash surface and exhibited more crystalline nature as compared to pure NiFe2O4 phase. The BET surface area and porous character of the composite were found to increase with the decrease in the contribution of the fly ash, reach to maximum and then decreases on further decrease in fly ash. The composite having % mass ratio of fly ash: NiFe2O4 = 50:50 exhibited maximum CR adsorption from the aqueous solution on account of the higher BET surface area, more porous character, favorable condition for diffusion of dye molecules and combined effect of chemisorption and physisorption. Under optimum conditions, it has shown the recyclability with adsorption capacity of the magnitude 23.33 mg g(-1), which is much higher than individual fly ash, NiFe2O4 and other composites. The sorption data provided good fit with pseudo-second order kinetic model. The analyses of the adsorption data indicated that, the Langmuir model provides better correlation with the experimental data. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Composite material; Electron microscopy (SEM); Inorganic compounds; powder diffraction; Precipitation

Preparation and characterization of silver particulate films on softened polystyrene and poly(4-vinylpyridine) blends - Gurumurthy, S. C.; Pattabi, Manjunatha; Krishna, Shreedhar; Gaikwad, A. B. (Journal of Materials Science-Materials In Electronics, 2014)
Results of the investigations carried out on the optical properties of silver particulate films deposited at a rate of 0.4 nm/s on softened polystyrene and poly(4-vinylpyridine) (P4VP) blends held at 455 K are reported. Under the conditions of deposition, a sub-surface particulate structure is expected. It had been shown earlier that the morphology of the sub-surface particulate structure is dependent on polymer-metal interaction. In the present studies, an inert polymer like polystyrene (PS) is blended with an interacting polymer P4VP. The optical studies on the silver particulate films deposited on softened blends of PS/P4VP have been carried out. The results show a shift in plasmon resonance to higher wavelength with increasing P4VP concentration of the blends in comparison to that of the films deposited on pure PS. An X-ray photoelectron spectroscopy study at two different electron take off angles indicates the formation of subsurface particulate structures for films deposited on blends.

Preparation of pyrazole carboxylic acid analogues as anti-mycobacterial drug candidates - Gajbhiye, Jayant M. (WO2014174457 A1, 2014)
The present invention relates to the pyrazole carboxylic acid analogues of Formula (1) or stereoisomers, or esters or pharmaceutically acceptable salts thereof, as potent anti- mycobacterial agents. Formula Further it discloses the pharmaceutical composition comprising compounds of Formula-I for the treatment of mycobacterial infections.

Probing the folding induction ability of orthanilic acid in peptides: some observations - Roy, Arup; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (RSC Advances, 2014)
This paper describes the ability of orthanilic acid (2-aminobenzenesulfonic acid, (S)Ant) to promote folding when introduced in a peptide sequence. Three peptide sequences, containing orthanilic acid (SAnt) with a sulfonamide moiety in the turn segment, have been synthesized in the solution phase using suitable coupling agents, and their structural aspects investigated using NMR and X-ray crystallographic studies. Solid- and solution-state conformational analyses reveal that the peptide sequences containing orthanilic acid in their backbone exist in a folded conformation featuring long-range 15-membered ring H-bonding.

Process optimization by response surface methodology and kinetic modeling for synthesis of methyl oleate biodiesel over H3PW12O40 anchored montmorillonite K10 - Nandiwale, Kakasaheb Y.; Bokade, Vijay V. (Industrial & Engineering Chemistry Research, 2014)
Heterogeneous acid catalysts comprised of 1030% (w/w) H3PW12O40 anchored to montmorillonite (K10) were used for synthesis of methyl oleate biodiesel by esterification of free fatty acid (oleic acid) with methanol in closed batch system. Response surface methodology (RSM) was employed to optimize esterification of oleic acid with methanol over 20% (w/w) H3PW12O40/K-10. The effects of various process parameters such as catalyst loading, molar ratio, and reaction temperature on oleic acid conversion were addressed by BoxBehnken experimental design (BBD). Coefficient of determination (R-2) of this model was 0.996. 20% (w/w) H3PW12O40/K-10 was proved to be potential catalyst with 100% oleic acid conversion at optimized process parameters and with reusability of four cycles. Moreover, a second-order pseudohomogeneous (PH) kinetic model has been proposed and validated (R-2 > 0.97) with experimental data. Kinetics confirmed that esterification reaction is performed in the kinetic regime due to high activation energy of 43.7 kJ mol(-1).

Processable aromatic polyesters based on bisphenol derived from cashew nut shell liquid: synthesis and characterization - Tawade, Bhausaheb V.; Salunke, Jagadish K.; Sane, Prakash S.; Wadgaonkar, Prakash P. (Journal of Polymer Research, 2014)
A new bisphenol viz., 4-(4-hydroxyphenoxy)-3-pentadecylphenol (HPPDP) was synthesized starting from cashew nut shell liquid (CNSL). Aromatic (co)polyesters containing ether linkages in the main chain and pendent pentadecyl chains were synthesized by the interfacial polycondensation of HPPDP with terephthalic acid chloride (TPC), isophthalic acid chloride (IPC) and a mixture of TPC and IPC (50: 50 mol %) and by polycondenation of varying composition of HPPDP and bisphenol-A (BPA) with TPC. The resultant (co) polyesters exhibited inherent viscosities in the range 0.70-1.21 dL g(-1) and number-average molecular weights in the range 16,000-48,200 (GPC, polystyrene standard). Polyesters were soluble in common organic solvents such as chloroform and dichloromethane and could be cast into films from chloroform solution. Polyesters exhibited T-10 values in the range 430-455 degrees C and Tg values were in the range 29-202 degrees C. Dynamic mechanical storage modulus and maximum on transition of tan delta curve decreased with increased content of HPPDP in copolyesters. Importantly, the large difference between Tg and T-10 values offers the possibility to process these polyesters in the melt.
Keywords: Aromatic polyesters; Cashew nut shell liquid; pentadecyl; Polycondensation; processability; Thermal properties

Production of octyl levulinate biolubricant over modified H-ZSM-5: Optimization by response surface methodology - Nandiwale, Kakasaheb Y.; Yadava, Sunil K.; Bokade, Vijay V. (Journal of Energy Chemistry, 2014)
The present study highlighted the use of modified H-ZSM-5 (Meso-HZ-5) as heterogeneous catalyst for the synthesis of octyl levulinate biolubricant by catalytic esterification of biomass derived renewable levulinic acid (LA) with n-octanol. The process variables such as catalyst loading (X-1), n-octanol to LA molar ratio (X-2) and reaction temperature (X-3) were optimized through response surface methodology (RSM), using Box-Behnken model. Analysis of variance was performed to determine the adequacy and significance of the quadratic model. The yield of octyl levulinate was obtained to be 99% at optimum process parameters. The developed quadratic model was found to be adequate and statistically accurate with correlation value (R-2) of 0.9971 to predict the yield of octyl levulinate biolubricant. The study was also extended on the validation of theoretical and experimental data, including catalyst reusability.
Keywords: biolubricant; Esterification; H-ZSM-5; levulinic acid; octyl levulinate; Response surface methodology

Proposing efficient new pendant group polymer electrolyte membranes for fuel cells: a computational study - Mane, Manoj V.; Vanka, Kumar (Journal of Physical Chemistry C, 2014)
There is a need to develop new membranes for fuel cells that can conduct protons with high efficiency and at high temperatures. This paper reports a theoretical study of proton transfer barriers in newly proposed polymer electrolyte membranes (PEMs), having pendant nitrogen containing crown ether groups on an alkyl backbone. The proton transfer in the proposed pendant group PEMs would occur without the need of an external agent such as water or phosphoric acid, and without the need for the pendant groups to rotate and reorient themselves after each proton transfer. The current study shows that this would make the proposed PEMs very efficient, with low proton transfer barriers. This has been seen to be true for a range of different PEM cases considered, differing in the number of linker atoms in the alkyl backbone and in the number of nitrogens contained in each pendant group, thus, indicating the potential of the proposed structures as PEMs for fuel cells.

Protecting group free and scalable approach towards total synthesis of (-)-venlafaxine - Chavan, Subhash P.; Pawar, Kailash P.; Garai, Sumanta (RSC Advances, 2014)
A protecting group free asymmetric total synthesis of (-)-venlafaxine is reported. The strategy employs Sharpless epoxidation and regio-selective epoxide ring opening by an in situ generated Gilman reagent as key steps. This paper reports a 53% overall yield in 6 steps for total synthesis of (-)-venlafaxine.

Protecting-group-free diastereoselective total synthesis of (+/-)-6-epi-cleistenolide and chemoenzymatic synthesis of (-)-6-epi-cleistenolide - Mahajan, Pankaj S.; Gonnade, Rajesh G.; Mhaske, Santosh B. (European Journal of Organic Chemistry, 2014)
A short, efficient, practical, and protecting-group-free diastereoselective total synthesis of (+/-)-6-epi-cleistenolide (1) has been achieved in five steps in 60% overall yield. The use of a chemoenzymatic approach also gave (-)-6-epi-cleistenolide (1) (>99.9% ee). The Achmatowicz reaction, chemoselective oxidation of a hemiacetal, diastereoselective 1,3-anti reduction of alpha-hydroxy ketone, and enzymatic resolution of a 1,3-diol are the key features of this linear total synthesis. The synthetic strategy demonstrated in this paper could be extended for an asymmetric total synthesis of (-)-cleistenolide (1) and related biologically active natural products.
Keywords: Asymmetric synthesis; diastereoselectivity; Enzyme catalysis; Lipases; Oxygen heterocycles; Total synthesis

Protein mediated synthesis of Au-Ag bimetallic nanoparticles - Raju, D.; Mendapara, Ritul; Mehta, Urmil J. (Materials Letters, 2014)
There is growing need to develop environment friendly method for synthesis of bimetallic nanoparticle that do not use toxic chemicals during their synthesis process. Here, we report synthesis of Au-Ag bimetallic nanoparticles by using macerase enzyme as reducing agent at different temperatures. Bimetallic nanoparticles were synthesized at 80 and 90 degrees C. The intensity of formation of nanoparticles was more at 80 degrees C. The bimetallic nanoparticles are characterized by using UV-vis, TEM and EDAX. The TEM study shows the inner gold and outer silver bimetallic nanoparticles. The formed nanoparticles are 4-20 nm in size and spherical in shape. EDAX confirms the formed bimetallic nanoparticles are of gold and silver. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Enzyme; Gold; Macerase; Particles; Silver; synthesis

Protein-coated polymer as a matrix for enzyme immobilization: immobilization of trypsin on bovine serum albumin-coated allyl glycidyl ether-ethylene glycol dimethacrylate copolymer - Jasti, Lakshmi Swarnalatha; Dola, Sandhya Rani; Kumaraguru, Thenkrishnan; Bajja, Sreedhar; Fadnavis, Nitin W.; Addepally, Uma; Rajdeo, Kishor; Ponrathnam, Surendra; Deokar, Sarika Babasaheb (Biotechnology Progress, 2014)
Allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymer with 25% crosslink density (AGE-25) shows excellent bovine serum albumin (BSA) adsorption (up to 16% (w/w)) at pH 8.0 and the adsorbed BSA is strongly bound. This protein-coated polymer provides a novel matrix with naturally existing functional groups such as thiol, amino, and carboxylic acid that are available for covalent immobilization of functional enzymes. Employing appropriate strategies, trypsin as a model protein was covalently bound to BSA-coated matrix both independently, and in a stepwise manner on the same matrix, with less than 5% loss of enzyme activity during immobilization. Glutaraldehyde crosslinking after immobilization provide stable enzyme preparation with activity of 510 units/g recycled up to six times without loss of enzyme activity. AFM studies reveal that the polymer surface has protein peaks and valleys rather than a uniform monolayer distribution of the protein and the immobilized enzyme preparation can best be described as polymer supported cross-linked enzyme aggregates (CLEAs). (c) 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:317-323, 2014
Keywords: allyl glycidyl ether; Bovine serum albumin; ethylene glycol dimethacrylate; Immobilization; Trypsin

Proteomic analysis of human plasma in chronic rheumatic mitral stenosis reveals proteins involved in the complement and coagulation cascade - Mukherjee, Somaditya; Jagadeeshaprasad, Mashanipalya G.; Banerjee, Tanima; Ghosh, Sudip K.; Biswas, Monodeep; Dutta, Santanu; Kulkarni, Mahesh J.; Pattari, Sanjib; Bandyopadhyay, Arun (Clinical Proteomics, 2014)
Background: Rheumatic fever in childhood is the most common cause of Mitral Stenosis in developing countries. The disease is characterized by damaged and deformed mitral valves predisposing them to scarring and narrowing (stenosis) that results in left atrial hypertrophy followed by heart failure. Presently, echocardiography is the main imaging technique used to diagnose Mitral Stenosis. Despite the high prevalence and increased morbidity, no biochemical indicators are available for prediction, diagnosis and management of the disease. Adopting a proteomic approach to study Rheumatic Mitral Stenosis may therefore throw some light in this direction. In our study, we undertook plasma proteomics of human subjects suffering from Rheumatic Mitral Stenosis (n = 6) and Control subjects (n = 6). Six plasma samples, three each from the control and patient groups were pooled and subjected to low abundance protein enrichment. Pooled plasma samples (crude and equalized) were then subjected to in-solution trypsin digestion separately. Digests were analyzed using nano LC-MSE. Data was acquired with the Protein Lynx Global Server v2.5.2 software and searches made against reviewed Homo sapiens database (UniProtKB) for protein identification. Label-free protein quantification was performed in crude plasma only.

Proteomics of arsenic stress in the gram-positive organism Exiguobacterium sp PS NCIM 5463 - Sacheti, Poonam; Patil, Rajendra; Dube, Ankita; Bhonsle, Hemangi S.; Thombre, Dipalee; Marathe, Sayali; Vidhate, Ravindra; Wagh, Priyanka; Kulkarni, Mahesh J.; Rapole, Srikanth; Gade, Wasudeo N. (Applied Microbiology and Biotechnology, 2014)
The general responses of microorganisms to environmental onslaughts are modulated by altering the gene expression pattern to reduce damage in the cell and produce compensating stress responses. The present study attempts to unravel the response of the Gram-positive Exiguobacterium sp. PS NCIM 5463 in the presence of [As(III)] and arsenate [As(V)] using comparative proteomics via two-dimension gel electrophoresis (2-DE) coupled with identification of proteins using matrix-assisted laser desorption/ionisation (MALDI-TOF/MALDI-TOF/TOF). Out of 926 Coomassie-stained proteins, 45 were differentially expressed (p < 0.05). Considering the resolution and abundance level, 24 spots (peptides) were subjected to MALDI analysis, identified and categorised into several functional categories, viz., nitrogen metabolism, energy and stress regulators, carbohydrate metabolism, protein synthesis components and others. A functional role of each protein is discussed in Exiguobacterium sp. PS 5463 under arsenic stress and validated at their transcript level using a quantitative real-time polymerase chain reaction. Unlike previous reports that unravel the responses toward arsenic stress in Gram-negative organisms, the present study identified new proteins under arsenic stress in a Gram-positive organism, Exiguobacterium sp. PS NCIM 5463, which could elucidate the physiology of organisms under arsenic stress.
Keywords: Arsenic; Exiguobacterium; proteomics; Stress; Transcriptomics

Pseudo-homogeneous kinetic model for esterification of acetic acid with propanol isomers over dodecatungstophosphoric acid supported on montmorillonite k10 - Gurav, Hanumant R.; Nandiwale, Kakasaheb Y.; Bokade, Vijay V. (Journal of Physical Organic Chemistry, 2014)
Esterification of acetic acid with propanol isomers such as isopropanol and naEuropropanol was carried out over dodecatungstophosphoric acid (DTPA), dodecamolybdophosphoric acid ammonium salt hydrate, and sodium tungstate hydrated purified supported on montmorillonite K10, which were characterized by powder XaEuroray diffraction, BrunaueraEuro'EmmettaEuro'Teller, and temperature programmed ammonia desorption. A pseudoaEurohomogeneous (PaEuroH) kinetic model was established for esterification of acetic acid with propanol isomers over DTPA supported on montmorillonite K10. Effects of various parameters such as reaction time, speed of agitation, particle size, temperature, percent catalyst loading, molar ratio and mixture of propanol isomer were investigated in detail. The 20% (w/w) DTPA/K10 was found to be an optimum solid catalyst with 82% naEuropropanol and 53% isopropanol conversion with 100% selectivity toward propyl acetate. The 20% (w/w) DTPA/K10 catalyst was found to be reusable for three cycles. The reaction follows secondaEuroorder kinetics with activation energies of 25.53aEuro?kJaEuro?mol(a?'1) and 28.15aEuro?kJaEuro?mol(a?'1) for isopropanol and naEuropropanol, respectively. PseudoaEurohomogeneous kinetic model fitted with R-2 value of trend line 0.999. This implies that esterification reaction is kinetically controlled owing to high activation energy. Copyright a (c) 2013 John Wiley & Sons, Ltd.
Keywords: Acetic acid; dodecatungstophosphoric acid; Esterification; kinetic model; montmorillonite K10

Pt States in BaCe0.98Pt0.02O3-delta during start up and shut down operations under different conditions: stability and activity of ionic Pt in water gas shift reaction - Rajesh, Thattarathody; Devi, R. Nandini (Catalysis Letters, 2014)
Stability of Pt species in doped BaCeO3 perovskites under Water gas shift reaction conditions is studied using X-ray absorption spectroscopy and in situ powder X-ray diffraction. The catalyst BaCe0.98Pt0.02O3-delta has Pt in +2 oxidation state and is found to be stable in the ionic form under reaction conditions as well as under various highly reducing shut down and start up conditions. In-situ XRD under Water Gas shift reaction conditions also reveals the Pt ions to be highly stabilized in lattice and no egress is observed.
Keywords: BaCeO3; Deactivation; platinum; WGS reaction; XPS

Pulsed laser-deposited MoS2 thin films on W and Si: field emission and photoresponse studies - Late, Dattatray J.; Shaikh, Parvez A.; Khare, Ruchita T.; Kashid, Ranjit V.; Chaudhary, Minakshi V.; More, Mahendra A.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2014)
We report field electron emission investigations on pulsed laser-deposited molybdenum disulfide (MoS2) thin films on W-tip and Si substrates. In both cases, under the chosen growth conditions, the dry process of pulsed laser deposition (PLD) is seen to render a dense nanostructured morphology of MoS2, which is important for local electric field enhancement in field emission application. In the case of the MoS2 film on silicon (Si), the turn-on field required to draw an emission current density of 10 mu A/cm(2) is found to be 2.8 V/mu m. Interestingly, the MoS2 film on a tungsten (W) tip emitter delivers a large emission current density of similar to 30 mA/cm(2) at a relatively lower applied voltage of similar to 3.8 kV. Thus, the PLD-MoS2 can be utilized for various field emission-based applications. We also report our results of photodiode-like behavior in (n- and p- type) Si/PLDMoS2 heterostructures. Finally we show that MoS2 films deposited on flexible kapton substrate show a good photoresponse and recovery. Our investigations thus hold great promise for the development of PLD MoS2 films in application domains such as field emitters and heterostructures for novel nanoelectronic devices.
Keywords: field emission; MoS2; photodiode heterostructures; pulsed laser deposition; thin film

Pyrene based conjugated materials: synthesis, characterization and electroluminescent properties - Salunke, Jagadish K.; Sonar, Prashant; Wong, F. L.; Roy, V. A. L.; Lee, C. S.; Wadgaonkar, Prakash P. (Physical Chemistry Chemical Physics, 2014)
In this work, three novel pyrene cored small conjugated molecules, namely 1,3,6,8-tetrakis(6-(octyloxy)naphthalene-2-yl) pyrene (PY-1), 1,3,6,8-tetrakis((E)-2-(6-(n-octyloxy) naphthalene-2-yl) vinyl) pyrene (PY-2) and 1,3,6,8-tetrakis((6-(n-octyloxy) naphthalene-2-yl) ethynyl) pyrene (PY-3) have been synthesized by Suzuki, heck and Sonogashira organometallic coupling reactions, respectively. The effects of single, double and triple bonds on their optical, electrochemical, and thermal properties are studied in detail. These all materials are fluorescent and they have been used in organic light-emitting diodes (OLEDs) and their electroluminescent properties have been studied.

p-Aminobenzoic acid (pABA) sensitization of LaF3:Tb3+ nanoparticles and its applications in the detection of explosive materials - Ghosh, Debasish; Luwang, Meitram Niraj (RSC Advances, 2015)
This work reports the utilization of water dispersible terbium (Tb3+) doped spherical LaF3 nanoparticles (similar to 5 nm) surface functionalised with p-aminobenzoic acid (pABA) for the detection of aromatic nitro explosives. The functionalised nanoparticles show remarkable sensitivity to a number of highly electron deficient aromatic nitro compounds like picric acid (PA), 2,4,6-trinitrotoluene (TNT), 2,4-dinitrotoluene (2,4-DNT), 2,4-dinitrophenol (2,4-DNP) etc. All of these nitro compounds can be detected easily at ppm level using this luminescence quenching technique whereas in the case of TNT it can detect concentrations as low as 50 ppb. This novel approach of utilising the Tb3+ doped NPs sensitised by pABA has potential application in the detection of explosive materials.

Partial ionic bonding in homogeneous sodium clusters - Kaware, Vaibhav; Joshi, Kavita (Condensed Matter Physics, 2015)
In this work, we report an interesting observation of partial ionic bonding due to charge transfer in homogeneous sodium clusters. The charge transfer causes the electronic charge to accumulate on the surface, and the resulting charges on atoms range between +0.4 to -1.0 |e^-|. We also demonstrate that this disparity among effective charges on atoms is geometry dependent, such that atoms experiencing similar surrounding, have equal effective charge. It is speculated that this phenomenon will occur among other homogeneous clusters as well, and its extent will be defined by the valence electron delocalization.

Partial triples excitation to the fock space multi-reference singles and doubles: dipole moment of doublet radicals - Ravichandran, Lalitha; Vaval, Nayana; Pal, Sourav (Proceedings of the International Conference of Computational Methods in Sciences and Engineering 2010 (ICCMSE-2010), 2015)
We present the partial triples effect on the dipole moment of doublet radicals in Lagrangian formulation of Fockspace multi-reference coupled cluster response method(A FSMRCC). This specific scheme uses non-iterative triples, in addition to singles and doubles excitations(A FSMRCCSD(T*)), which accounts for the effects appearing at least at the third order in dipole moment. This method is applied to the ground states of small radicals.
Keywords: Dipole moment; Multi-reference; Triples

Pd loaded amphiphilic COF as catalyst for multi-fold Heck reactions, C-C couplings and CO oxidation - Mullangi, Dinesh; Nandi, Shyamapada; Shalini, Sorout; Sreedhala, Sheshadri; Vinod, Chathakudath P.; Vaidhyanathan, Ramanathan (Scientific Reports, 2015)
COFs represent a class of polymers with designable crystalline structures capable of interacting with active metal nanoparticles to form excellent heterogeneous catalysts. Many valuable ligands/monomers employed in making coordination/organic polymers are prepared via Heck and C-C couplings. Here, we report an amphiphilic triazine COF and the facile single-step loading of Pd-0 nanoparticles into it. An 18-20% nano-Pd loading gives highly active composite working in open air at low concentrations (Conc. Pd(0) < 0.05 mol%, average TON 1500) catalyzing simultaneous multiple site Heck couplings and C-C couplings using `non-boronic acid' substrates, and exhibits good recyclability with no sign of catalyst leaching. As an oxidation catalyst, it shows 100% conversion of CO to CO2 at 150 degrees C with no loss of activity with time and between cycles. Both vapor sorptions and contact angle measurements confirm the amphiphilic character of the COF. DFT-TB studies showed the presence of Pd-triazine and Pd-Schiff bond interactions as being favorable.

Pd-catalyzed benzylic C-H oxidation of cyclotriveratrylene - product diversity - Senthilkumar, B.; Gonnade, Rajesh G.; Ramana, C. V. (Organic & Biomolecular Chemistry, 2015)
The inner-rim functionalization of CTV has been examined by employing Pd-catalyzed benzylic oxidation. The outcome of the oxidation depends upon the solvent and co-oxidants employed. An interesting array of CTV derivatives has been synthesized with a simple change in the conditions.

Penicillin V acylase from pectobacterium atrosepticum exhibits high specific activity and unique kinetics - Avinash, Vellore Sunder; Ramasamy, Sureshkumar; Suresh, C. G.; Pundle, Archana (International Journal of Biological Macromolecules, 2015)
Penicillin V acylases (PVAs, E.C.3.5.11) belong to the Ntn hydrolase super family of enzymes that catalyze the deacylation of the side chain from phenoxymethyl penicillin (penicillin V). Penicillin acylases find use in the pharmaceutical industry for the production of semi-synthetic antibiotics. PVAs employ the N-terminal cysteine residue as catalytic nucleophile and are structurally and evolutionarily related to bile salt hydrolases (BSHs). Here, we report the cloning and characterization of a PVA enzyme from the Gram-negative plant pathogen, Pectobacterium atrosepticum (PaPVA). The enzyme was cloned and expressed in Escherichia coli attaining a very high yield (250 mg/l) and a comparatively high specific activity (430 IU/mg). The enzyme showed marginally better pH and thermo-stability over PVAs characterized from Gram-positive bacteria. The enzyme also showed enhanced activity in presence of organic solvents and detergents. The enzyme kinetics turned out to be significantly different from that of previously reported PVAs, displaying positive cooperativity and substrate inhibition. The presence of bile salts had a modulating effect on PaPVA activity. Sequence analysis and characterization reveal the distinctive nature of these enzymes and underscore the need to study PVAs from Gram-negative bacteria. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Cooperative; Enzyme kinetics; Gram-negative; Penicillin V acylase; Substrate inhibition

Perspective on atomically thin 2d inorganic layered materials for biosensor - Late, Dattatray J.; Rout, C. S.; Chakravarty, Disha; Ratha, S. (Journal of Nanomedicine Research, 2015)

Perturbations in inter-domain associations may trigger the onset of pathogenic transformations in PrPC: insights from atomistic simulations - Menon, Sneha; Sengupta, Neelanjana (Molecular Biosystems, 2015)
Conversion of the predominantly alpha-helical cellular prion protein (PrPC) to the misfolded beta-sheet enriched Scrapie form (PrPSc) is a critical event in prion pathogenesis. However, the conformational triggers that lead to the isoform conversion (PrPC to PrPSc) remain obscure, and conjectures about the role of unusually hydrophilic, short helix H1 of the C-terminal globular domain in the transition are varied. Helix H1 is anchored to helix H3 via a few stabilizing polar interactions. We have employed fully atomistic molecular dynamics simulations to study the effects triggered by a minor perturbation in the network of these non-bonded interactions in PrPC. The elimination of just one of the key H1-H3 hydrogen bonds led to a cascade of conformational changes that are consistent with those observed in partially unfolded intermediates of PrPC, with pathogenic mutations and in low pH environments. Our analyses reveal that the perturbation results in the enhanced conformational flexibility of the protein. The resultant enhancement in the dynamics leads to overall increased solvent exposure of the hydrophobic core residues and concomitant disruption of the H1-H3 inter-domain salt bridge network. This study lends credence to the hypothesis that perturbing the cooperativity of the stabilizing interactions in the PrPC globular domain can critically affect its dynamics and may lead to structural transitions of pathological relevance.

Perturbative order analysis of the similarity transformed hamiltonian in fock-space coupled cluster theory: difference energy and electric response properties - Bhattacharya, Debarati; Dutta, Achintya Kumar; Gupta, Jitendra; Pal, Sourav (Molecular Physics, 2015)
A perturbative analysis of the ground-state similarity transformed Hamiltonian and its effect on the various Fock-space coupled cluster (FSCC) sectors is presented through calculation of ionisation potential, electron affinity, excitation energies and response properties. Various truncation schemes of the effective Hamiltonian are presented with explicit form of the defining equations. Based on such a truncation, the approximate methods are labelled as FSCC(n), where n represents the correlation energy of the ionised, electron attached or excited states corrected at least up to nth order within coupled cluster singles and doubles scheme (CCSD). A lower scaling CC2 type of approach (abbreviated as FS-CC2) is compared against the group of FSCC(n) methods for energies. Electric response properties have been compared and contrasted for the two lower scaling methods: FSCC(2) and FS-CC2. The various truncated methods are tested for a number of small molecules. The results obtained from a range of truncated methods are compared against full FSCCSD calculations.
Keywords: electric response properties; Fock space; perturbative order; similarity transformed Hamiltonian

Pharmacophore and docking based virtual screening of validated mycobacterium tuberculosis targets - Vyas, Renu; Karthikeyan, Muthukumarasamy; Nainaru, Ganesh; Muthukrishnan, Murugan (Combinatorial Chemistry & High Throughput Screening, 2015)
Target based virtual screening has surpassed ligand based virtual screening methods in the recent past mainly as it provides more clues regarding intermolecular interactions and takes into consideration the flexible receptor as well. The current methodology describes a computational strategy of predicting Mycobacterium tuberculosis (M. tuberculosis) binders for five well studied targets representing M. tuberculosis proteome encompassing most of the known mechanisms of action. The diversity of the targets was affirmed by their active site analysis and structural studies. The current approach employed pharmacophore searching, docking and clustering techniques in tandem and was validated by enrichment studies using the available Schrodinger data set consisting of 1000 decoys. The application of this methodology was demonstrated by predicting potential molecular targets for fifty newly synthesized compounds. Cross docking studies on the targets were carried out with 4512 known inhibitors utilizing a high performance computing platform to reveal underlying affinity and promiscuity patterns. Optimum binding energy range for all targets as determined by high throughput docking was found to be -3 to -13 kcal/mol.
Keywords: Binding energy; docking; Mycobacterium tuberculosis; open source drug discovery (OSDD); pharmacophore; structure based drug design (SBDD)

Phase behavior, diffusion, structural characteristics, and pH of aqueous hydrophobic ionic liquid confined media: insights into microviscosity and microporsity in the [C(4)C(4)im][NTf2] + water system - Nanda, Raju; Kumar, Anil (Journal of Physical Chemistry B, 2015)
We present our studies on the physicochemical properties of water confined in Dibutylimidazolium bis(trifluoromethanesulfonylimide) ([C(4)C(4)im][NTf2]) reverse micelles through the NMR relaxation measurements that provide us an understanding of microviscosity and pH in the confined condition. We present experimental results on phase behavior, diffusion, structural characteristics and pH in aqueous ionic liquid-confined media. The ternary phase diagram was constructed by the cloud point measurements and the microheterogeneous regions were detected by the measurement of bulk viscosity and diffusion coefficients of K-4[Fe(CN)(6)] inside the homogeneous microemulsion systems through the cyclic voltammetric (CV) measurements. The size of the microemulsion systems was characterized by the dynamic light scattering (DLS) method. The H-1 NMR spectra of homogeneous microemulsion systems were taken which indicates the presence of bound and free water molecules inside the microemulsion system. The NMR spinlattice relaxation time (T-1) of water molecules in its homogeneous microemulsion systems were measured and the reorientational correlation time (t(c)) of water molecules obtained from it indicates that the fluidity of homogeneous confined media decreases with the decrease in the composition of water. Microviscosity of the aqueous confined media was calculated from the measured T-1 relaxation time values by applying the DebyeStokes equation and correlated with the bulk viscosity of the samples. It was observed that both the microviscosity and bulk viscosity show inverse relationship. The fraction of bound and free water molecules were calculated from the measured T-1 values. NMR spinspin relaxation time (T-2) of water molecules in its homogeneous microemulsion systems were measured with the varying pH of the aqueous core. A change in the T-2 relaxation time of the water proton was observed proposing an exchange of proton between the H2O and -OH group of the TX-100 molecules. Finally, methyl orange (MO) was used as a UVvis spectrophotometric molecular probe and the measured lambda(max) values of the probe were used for the detection of micropolarity of the homogeneous aqueous confined media and was found to be increase with the increase in the size of the confined media.

Phase behaviour of the ternary system: monoolein-water-branched polyethylenimine - Kumar, Manoj; Kumaraswamy, Guruswamy (Soft Matter, 2015)
Addition of a branched polymer, polyethyleneimine, significantly alters the organization of a glycerol monooleate (GMO) lipid-water system. We present detailed data over a wide range of compositions (water content from 10 to 40%, relative to GMO and PEI fractions from 0 to 4%) and temperatures (25-80 degrees C). The PEI molecular weight effects are examined using polymers over a range from 0.8 to 25 kDa. Addition of PEI induces the formation of higher curvature reverse phases. In particular, PEI induces the formation of the Fd3m phase: a discontinuous phase comprising reverse micelles of two different sizes stacked in a cubic AB(2) crystal. The formation of the Fd3m phase at room temperature, upon addition of polar, water soluble PEI is unusual, since such phases typically are formed only upon addition of apolar oils. The largest stability window for the Fd3m phase is observed for PEI with a molecular weight = 2 kDa. We discuss how PEI influences the formation and stability of high curvature phases.

Phenols from green tea as a dual functional coating to prepare devices for energy storage and molecular separation - Das, Chayanika; Jain, Bhanprakash; Krishnamoorthy, Kothandam (Chemical Communications, 2015)
Polyphenols from green tea were used to electrolessly deposit gold on silk cocoons (SCs) and nanoporous aluminum oxide (AAO) templates. The gold coated cocoons were used as electrodes in supercapacitors and showed a capacitance as high as 254 F g(-1) and a specific power of 2287 W kg(-1). A metal coated AAO template was used for molecular separation.

Phosphate enriched polyoxometalate based ionic salts for proton conduction - Dey, Chandan; Kundu, Tanay; Aiyappa, Harshitha Barike; Banerjee, Rahul (RSC Advances, 2015)
A series of [NiMo12O30(PO4)(8)](n-) POM anion and organic cation based ionic composites have been prepared in hydrothermal conditions. The ionic composites with protonated ethylene diamine molecules have been tested for proton conductivity.

Phosphonated USY, a promising catalyst for the development of environmentally benign biodiesel (methyl acetate) process - Nandiwale, Kakasaheb Y.; Gopal, Gahana C.; Bokade, Vijay V. (Journal of Energy Chemistry, 2015)
The present study focuses on the evaluation of the potential applicability of Ultra Stable Y (USY) and phosphonated USY (1 wt%-4 wt% phosphorous loading) as heterogeneous catalysts for biodiesel (methyl acetate) production. The synthesized catalysts were characterized by powder X-ray diffraction (XRD), Brunaer-Emmett-Teller (BET) surface area, total acidity by temperature-programmed desorption of ammonia (TPD-NH3) and Fourier Transform Infrared (FTIR) spectra. The performances of catalysts were evaluated for the transesterification of butyl acetate with methanol (a model reaction in biodiesel production). In view to obtain a maximum yield of methyl acetate, the optimization of process parameters such as reactant molar ratio, catalyst loading, reaction temperature and reaction time was performed. All the phosphonated USY catalysts showed higher catalytic activity than the parent USY, which can be attributed to the increase of total acidity due to phosphonation. 2 wt% P/USY (2% phosphorous loaded on USY) exhibited 92% methyl acetate yield with 100% selectivity, which was proved to be a potential catalyst for biodiesel production. The invented catalyst was found to be stable and reusable for five catalytic cycles, demonstrating that it might be a environmentally benign catalytic process.
Keywords: Biodiesel; methyl acetate; phosphonated USY; transesterification

Photochemical performance of ZnO nanostructures in dye sensitized solar cells - Das, Partha Pratim; Mukhopadhyay, Soumita; Agarkar, Shruti A.; Jana, Arpita; Devi, P. Sujatha (Solid State Sciences, 2015)
In this work, the photoconversion efficiencies of ZnO having diverse microstructures and structural defects have been investigated. A conversion efficiency of 138% was achieved for the DSSCs fabricated with as prepared ZnO nanorods having minimum vacancy defects and a favourable one dimensional directional pathway for electron conduction. The DSSCs fabricated with ZnO nanoparticles exhibited relatively low conversion efficiency of 1.004% probably due to multiple trapping/detrapping phenomena within the grain boundaries and ZnO flowers though exhibited a high dye adsorption capability exhibited the lowest conversion efficiency of 0.59% due to a high concentration of structural defects. Based on the experimental evidences, we believe that the type of defects and their concentrations are more important than shape in controlling the overall performance of ZnO based DSSCs. (C) 2015 Elsevier Masson SAS. All rights reserved.
Keywords: DSSC; Efficiency; Emission; Structural defects; ZnO

Photo-responsive pseudorotaxanes and assemblies - Mandal, Amal Kumar; Gangopadhyay, Monalisa; Das, Amitava (Chemical Society Reviews, 2015)
Chemists have achieved a predictable control over various non-covalent interactions and have used these weak interactions in their favour for developing a plethora of intricate functional structures. In this tutorial review we have summarized reports on such supramolecular structures that describe the rational approach in designing host and/or guest components, tagged with an appropriate fluorophore, for achieving the modified optical responses on formation of an assembly. This has relevance for designing new photo-responsive smart or adaptive stimuli responsive functional materials, self- healable materials, with interesting photo-physical property. These are also important in the area of supramolecular chemistry and biophysical chemistry in predicting the relative conformation in solution.

Photosensitive field emission study of SnS2 nanosheets - Joshi, Padmashree D.; Joag, Dilip S.; Rout, Chandra Shekhar; Late, Dattatray J. (Journal of Vacuum Science & Technology B, 2015)
SnS2 nanosheets (SnS(2)NSs), synthesized by one-step hydrothermal reaction, are subjected to field emission (FE) studies. For synthesis, specific concentrations of Na2SnO3 and thioamide solutions are used. The FE study is carried out in a planar diode configuration at a base pressure of similar to 10(-8) mbar. The emission photosensitivity is also investigated by illuminating the specimen with a visible light source. In dark, the turn on field, the electric field required to obtain a current density of 1 mu A/cm(2), is found to be 5.9 V/mu m. Upon illumination, the emitter with visible light, it is found to reduce to 5.0 V/mu m. A significant change in the nature of the Fowler-Nordheim plot with light illumination is also observed and has been explained on the basis of photoconductivity. Repetitive switching ON and OFF the light source, at a fixed applied voltage, is found to generate current pulses. The photosensitivity is also studied with various color filters. With the photoswitching and the enhanced field emission properties, it is envisaged that SnS(2)NSs possess a potential for optoelectronic applications of field emitters. (C) 2014 American Vacuum Society.

Polarity issues in room temperature ionic liquids - Shukla, Shashi Kant; Kumar, Anil (Clean Technologies and Environmental Policy, 2015)
The study on ionic liquids has occupied an important place in chemical processes because of several beneficial properties. In order to use these ionic liquids as solvent media in chemical processes, it is essential to know their solvent properties. In this review, an attempt has been made to critically evaluate and discuss the polarity parameters of ionic liquids. The experimental polarity data on ionic liquids are not yet available for numerous ionic liquids. This review will serve as a guideline to investigate polarity issues of these materials and emerge with a simple, but still sound theoretical or semi-empirical models to account for the variation in polarity in the ionic liquid solutions.

Polybenzimidazole based polymeric ionic liquids (PILs): effects of controlled degree of N-quaternization on physical and gas permeation properties - Rewar, Anita S.; Bhavsar, Rupesh S.; Sreekumar, K.; Kharul, Ulhas K. (Journal of Membrane Science, 2015)
Polymeric ionic liquids (PILs) are gaining increasing attention as potential membrane materials to be employed for CO2 separation. With a goal to improve gas permeability, this work presents a series of film forming PlLs obtained by controlled degree of N-quaternization (DQ) of PBI-BuI using a bulky 4-tertbutylbenzyl group. Concurrent effects of variation in ionic content and bulky group substitution were analyzed for physical and gas permeation properties of the resulting PILs. Attempted structural variations leading to simultaneous increments in ionic content and bulky groups offered amorphous polymers with acceptable thermal stability and non-monotonous chain packing density. Enhancement in pure gas permeability coupled with appreciable selectivity for various gas pairs was in accordance with the packing density variations in the series. Gas permeability showed maxima at DQ of just 13%. This conveyed that effects of bulky group substitution in retarding chain packing are overcome by attractive ionic interactions at much lower DQ in these PILs ionic interactions are thus more predominant in governing chain packing and gas permeation properties. These PILs possessed 3.3-20 times higher CO2 permeability in comparison to their parent PBI-BuI, without a significant loss in selectivity. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Degree of quaternization; Gas permeation; Polybenzimidazole; Polymeric ionic liquid

Polybenzimidazole-based polymeric ionic liquids (PILs): effects of `substitution asymmetry' on CO2 permeation properties - Shaligram, Sayali V.; Wadgaonkar, Prakash P.; Kharul, Ulhas K. (Journal of Membrane Science, 2015)
Polymeric Ionic Liquids (PILs) are being considered as promising membrane materials for CO2 separation. Present work aims at investigating effects substitution asymmetry on imidazole moiety of two structurally different polybenzimidazoles (PBI-BuI and PBI-HFA) on physical, gas sorption and transport properties of the resulting film forming PILs possessing symmetric substitution, while keeping one of the N-substituent as methyl group. PILs were obtained with high degree of substitution. The halide anion of these PILs was exchanged with BF4-, Tf-2(N) over bar and HF (B) over bar anions. Effects of substituents, cationic backbone and type of anions on gas permeation properties of PILs using pure gases (He, H-2, N-2 and CO2) were examined at 20 atm upstream pressure and correlated with their physical properties. Combination of typical ionic liquid character (effective towards enhancing CO2 sorption) and looser chain packing (ease in gas diffusion) offered improved CO2 permeation characteristics. As an outcome, some of the PILs exhibited higher CO2 permeation than that of hydrogen, typically known as `reverse selectivity'. These asymmetrically substituted PILs enhanced not only the gas permeability, but also selectivity than their symmetrically substituted counterparts. (C) 2015 Elsevier B.V. All rights reserved.

Polyelectrolytes in dilute solution: viscometric access to coil dimensions and salt effects - Suresha, P. R.; Badiger, Manohar V.; Wolf, Bernhard A. (RSC Advances, 2015)
Copolymers of acrylamide (AM) and diallyldimethylammonium chloride (DADMAC), differing in molar masses M (52.3 to 227 kDa) and degrees of charging y (0.2 to 0.6), were studied with respect to their viscometric behavior in dilute aqueous solutions containing variable amounts of NaCl. Complementary measurements were performed on a Brookhaven 90 plus particle size analyzer. M dominates the intrinsic viscosities [eta]. For the viscometric interaction parameters B this is only true for large concentrations of extra salt. [eta] and B as a function of solvent salinity follow Boltzmann laws. Coil dimensions, determined either via dynamic light scattering or viscometry, agree well. For low salt contents of the solvent the radii decrease with rising polymer concentration, whereas they increase for high salt concentrations; at a characteristic salinity of the solvent they become independent. Zeta potentials grow from +20 to +40 mV as y goes up.

Pore surface engineering in porous, chemically stable covalent organic frameworks for water adsorption - Biswal, Bishnu P.; Kandambeth, Sharath; Chandra, Suman; Shinde, Digambar Balaji; Bera, Saibal; Karak, Suvendu; Garai, Bikash; Kharul, Ulhas K.; Banerjee, Rahul (Journal of Materials Chemistry A, 2015)
Herein, we have explored the possibility of a class of covalent organic frameworks (COFs) as water adsorbing materials. We have selected, synthesized 12 chemically stable functionalized Schiff base COFs and thoroughly studied their water uptake behaviour. Further, a deep understanding was developed with these COFs towards the effects of condensation pressure of water and hydrophilic/hydrophobic groups present in the COF pores on water absorption capacity and ultimately, their recyclability. Among all reported COFs, TpPa-1 shows the highest water uptake of 30 wt% (368 cm(3) g(-1); 17 mmol g(-1)) at P/P-0 = 0.3, which is also comparable with the recently reported carbon materials and few well known MOFs. This study also reveals that the overall water uptake of COFs can be tuned systematically based on chemical functionality and pore size in a wider window of relative pressures.

Porous poly(ethylene glycol)-polyurethane hydrogels as potential biomaterials - Divakaran, Anumon V.; Torris, Arun A. T.; Lele, Ashish K.; Badiger, Manohar V. (Polymer International, 2015)
We report the synthesis of porous poly(ethylene glycol)-polyurethane (PEG-PU) hydrogels using PEG-4000 as a soft segment and 4,4-methylenebis(cyclohexylisocyanate) as a hard segment. The degree of swelling in the hydrogels could be controlled by varying the amount of crosslinking agent, namely 1,2,6-hexanetriol. Structural characterization of the hydrogels was performed using solid-state C-13 NMR and Fourier transform infrared spectroscopy. Wide-angle X-ray diffraction studies revealed the existence of crystalline domains of PEG and small-angle X-ray scattering studies showed the presence of lamellar microstructures. For generating a porous structure in the hydrogels, cryogenic treatment with lyophilization was used. Scanning electron microscopy and three-dimensional micro-computed tomography imaging of the hydrogels indicated the presence of interconnected pores. The mechanical strength of the hydrogels and xerogels was measured using dynamic mechanical analysis. The observed dynamic storage moduli (E) for the equilibrium swollen and dry gels were found to be 0.15 and 4.2 MPa, respectively. Interestingly, the porous PEG-PU xerogel also showed E of 5.6 MPa indicating a similar mechanical strength upon incorporating porosity into the gel matrix. Finally, preliminary cytocompatibility studies showed the ability of cells to proliferate in the hydrogels. These gels show promise for applications as scaffolds and implants in tissue engineering. (c) 2014 Society of Chemical Industry
Keywords: hydrogels; permeability; poly(ethylene glycol); polyurethane; porosity

Possible correlation between bile salt hydrolysis and ahl deamidation: staphylococcus epidermidis RM1, a potent quorum quencher and bile salt hydrolase producer - Mukherji, Ruchira; Prabhune, Asmita (Applied Biochemistry and Biotechnology, 2015)
The aim of the present work was to isolate a bile salt hydrolase (BSH) producer from fermented soy curd and explore the ability of the BSH produced to cleave bacterial quorum sensing signals. Bacterial isolates with possible ability to deconjugate bile salts were enriched and isolated on De Man, Rogosa and Sharpe (MRS) medium containing 0.2 % bile salts. BSH-producing positive isolate with orange-pink-pigmented colonies was isolated and was identified as a strain of Staphylococcus epidermidis using biochemical and phylogenetic tools. S. epidermidis RM1 was shown to possess both potent BSH and N-acyl homoserine lactone (AHL) cleavage activity. Genetic basis of this dual-enzyme activity was explored by means of specific primers designed using S. epidermidis ATCC 12228 genome as template. It was observed that a single enzyme was not responsible for both the activity. Two different genetic elements corresponding to each of the enzymatic activity were successfully amplified from the genomic DNA of the isolate.
Keywords: AHL acylase; Bile salt hydrolase; CV026; Quorum quenching; Staphylococcus epidermidis

Possible mechanism of antifungal phenazine-1-carboxamide from pseudomonas sp against dimorphic fungi Benjaminiella poitrasii and human pathogen Candida albicans - Tupe, S. G.; Kulkarni, R. R.; Shirazi, F.; Sant, D. G.; Joshi, Swati P.; Deshpande, Mukund V. (Journal of Applied Microbiology, 2015)
AimInvestigation of antifungal mechanism of phenazine 1-carboxamide (PC) produced by a Pseudomonas strain MCC2142. Methods and ResultsAn antifungal metabolite produced by a Pseudomonas was purified and identified as PC. Human pathogenic fungi such as Candida albicans, Candidaglabrata, Cryptococcus neoformans, Fusarium oxysporum, Aspergillus fumigatus and Aspergillus niger were found to be inhibited by PC (MIC90 32-64gml(-1)). Addition of PC (20gml(-1)) during yeast (Y)-hypha (H) transitions inhibited germ tube formation by >90% and >99% in C.albicans National Collection of Industrial Microorganisms (NCIM) 3471 and nonpathogenic model Benjaminiella poitrasii, respectively. After exposure to PC (20gml(-1)), 75-80% yeast cells of B.poitrasii and C.albicans NCIM 3471 showed rhodamine 123 fluorescence indicating high intracellular reactive oxygen species (ROS) production. ROS further led to hyperpolarization of mitochondrial membrane, subsequently induction of apoptosis as evident by externalization of phosphatidylserine, DNA fragmentation, chromatin condensation and finally death in B.poitrasii. In C.albicans NCIM 3471, PC (20gml(-1)) induced apoptosis. ConclusionsThe antifungal effect of PC in B.poitrasii and C.albicans may be due to ROS-mediated apoptotic death. Significance and Impact of the StudyInhibition of Y-H transition of B.poitrasii and C.albicans by PC indicates that it may prove useful in the control of dimorphic human pathogens.
Keywords: Apoptosis; Candida albicans; dimorphism; phenazines; Pseudomonas sp; reactive oxygen species

Potent inhibition of miR-27a by neomycin-bisbenzimidazole conjugates - Nahar, Smita; Ranjan, Nihar; Ray, Arjun; Arya, Dev P.; Maiti, Souvik (Chemical Science, 2015)
miRNAs are important components of regulatory networks that control gene expression and have implications in various diseases including cancer. Targeting oncogenic miRNAs with small molecules is currently being explored to develop cancer therapeutics. Here, we report the development of dual binding neomycin-bisbenzimidazole conjugates that target oncogenic miR-27a with high affinity (K-a = 1.2 to 7.4 x 10(8) M-1). These conjugates bring significant reduction (similar to 65% at 5 mu M) in mature miRNA levels and penetrate easily in the cells where they localise both in the cytoplasm and the nucleus. Cell cycle analysis showed significant increase in the G0/G1 phase (similar to 15%) and decrease in the S phase (similar to 7%) upon treatment with neomycin-bisbenzimidazole conjugates, suggesting inhibition of cell proliferation. Using the conjugation approach, we show that moderately binding ligands can be covalently combined into high affinity binders. This study also highlights the role of linker optimization in designing high affinity ligands for miR-27a targeting.

Potential applications of glucosyltransferases in terpene glucoside production: impacts on the use of aroma and fragrance - Schwab, Wilfried; Fischer, Thilo C.; Giri, Ashok; Wuest, Matthias (Applied Microbiology and Biotechnology, 2015)
The detection of glucoconjugated forms of monoterpene alcohols in rose petals in the late 1960s opened the new field of nonvolatile aroma precursors in flavor research. It is now well established that odorless glycosides represent a significant pool of aroma precursors in plants where they act as preformed but inactivated defense or attractive chemicals. Technical improvements in the separation and identification of plant secondary metabolites have provided a multitude of chemical structures, but functional characterization of glycosyltransferases that catalyze their formation lags behind. As technical efforts and costs for DNA sequencing dramatically dropped during the last decade, the number of plant genome sequences increased significantly, thus providing opportunities to functionally characterize the glycosyltransferase gene families in plants. These studies yielded the first glycosyltransferase genes that encode efficient biocatalysts for the production of monoterpene glucosides. They have applications in the food, feed, chemical, cosmetic, and pharmaceutical industries as slow release aroma chemicals.

Prediction of bioactive compounds using computed NMR chemical shifts - Karthikeyan, Muthukumarasamy; Rajamohanan, Pattuparambil Ramanpillai; Vyas, Renu (Combinatorial Chemistry & High Throughput Screening, 2015)
NMR based chemical shifts are an important diagnostic parameter for structure elucidation as they capture rich information related to conformational, electronic and stereochemical arrangement of functional groups in a molecule which is responsible for its activity towards any biological target. The present work discusses the importance of computing NMR chemical shifts from molecular structures. The NMR chemical shift data (experimental or computed) was used to generate fingerprints in binary formats for mapping molecular fragments (as descriptors) and correlating with the bioactivity classes. For this study, chemical shift data derived binary fingerprints were computed for 149 classes and 4800 bioactive molecules. The sensitivity and selectivity of fingerprints in discriminating molecules belonging to different therapeutic categories was assessed using a LibSVM based classifier. An accuracy of 82% for proton and 94% for carbon NMR fingerprints were obtained for anti-psoriatic and anti-psychotic molecules demonstrating the effectiveness of this approach for virtual screening.
Keywords: Chemical shift; fingerprints; NMR; similarity searching; virtual screening

Preferential enrichment of DL-leucine using cocrystal formation with oxalic acid under nonequilibrium crystallization conditions - Manoj, Kochunnoonny; Takahashi, Hiroki; Morita, Yoko; Gonnade, Rajesh G.; Iwama, Sekai; Tsue, Hirohito; Tamura, Rui (Chirality, 2015)
By utilizing the preferential enrichment (PE) technique, we achieved an improved enantiomeric resolution of DL-leucine (Leu) using a 1:1 cocrystal (DL-1) of DL-Leu and oxalic acid. The crystal structure analysis of DL-1 indicated the occurrence of a novel type of phase transition and subsequent preferential redissolution of one enantiomer from the resulting crystals into solution. Chirality 27:405-410 2015. (c) 2015 Wiley Periodicals, Inc.
Keywords: chiral resolution; cocrystal formation; leucine; phase transition; preferential enrichment

Preparation and characterization of flexible ferromagnetic nanocomposites for microwave applications - Thomas, Teena; Kanoth, Bipinbal P.; Nijas, C. M.; Joy, Pattayil Alias; Joseph, Joseph M.; Kuthirummal, Narayanan; Thachil, Eby T. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2015)
Magnetic Fe3O4 nanoparticles (similar to 20 nm) were synthesized using the chemical co-precipitation method with a view of developing flexible and easily processable ferromagnetic materials with high mouldability to be used as microwave absorbers. The nanoparticles prepared were incorporated into natural rubber through latex stage processing. This novel processing method gives better dispersion of particles in the rubber matrix. The composites were characterized using XRD, SEM, vibrating sample magnetometer, dynamic mechanical analyzer, cavity perturbation, thermogravimetry (TGA), and Fourier transform infrared photoacoustic spectroscopy (FTIR-PAS). A notable improvement in the mechanical properties of composites was observed upon adding Fe3O4 particles. Magnetic and microwave characteristics of the composites indicate the formation of a flexible ferromagnetic material with good microwave absorption characteristics. (C) 2015 Published by Elsevier B.V.
Keywords: Fe3O4; Ferromagnetic; FTIR-PAS; Microwave absorption; Natural rubber; SEM; XRD

Preparation and characterization of self-photostabilizing UV-durable bionanocomposite membranes for outdoor applications - Kushwaha, Omkar S.; Avadhani, C. V.; Singh, R. P. (Carbohydrate Polymers, 2015)
Here, we report a durable and ultraviolet (UV) resistant nanocomposite membrane of chitosan (CS) with effective photostabilization ascribed to Zinc oxide (ZnO) nanoparticles. Zinc oxide nanoparticles were successfully dispersed in the solution of chitosan polymer. The nanocomposite films with the homogenous dispersion of ZnO nanoparticles in the chitosan matrix were obtained by solution casting method and the influence of ZnO nanoparticles as a photostabilizer was studied. The nanocomposite membranes were photoirradiated by polychromatic radiations with lambda > 300 nm using mercury vapour lamps in SEPAP instrument. The resulting nanocomposite material exhibited excellent UV-resistance in very low percentages of ZnO nanoparticles. The chitosan membranes showed fast degradation attributes than the nanocomposite membranes. ZnO nanoparticles effectively absorbed UV radiations, thus protecting polymer from radiation degradation. The neat and irradiated nanocomposites of chitosan and ZnO nanoparticles (CS/ZnO) were characterized by Fourier Transform Infrared Spectroscopy (FT-IR) spectroscopy for the chemical changes/degradation taking place. Chitosan nanocomposites were further characterized for tensile properties, contact angle measurements and surface morphology. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Bionanocomposite membrane; Chitosan; Contact angle measurement; Fourier transform infrared spectroscopy; Photostabilization; Zinc oxide nanoparticles

Preparation of Ag(Shell)-Au(Core) nanoparticles by anti-galvanic reactions: are capping agents the ``real heroes'' of reduction? - Sahu, Puspanjali; Bhagavatula L. V. Prasad (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2015)
The formation of Ag(shell)-Au(core) nanoparticles by the reduction of Ag+ ions on preformed Au NPs, mediated by the capping agents like dodecylamine is described. We clearly established that while monodisperse Ag(shell)-Au(core) structures can be formed in presence of weak surface binding ligands such as amines, strong binding ligands such as thiols, lead to formation of separate monometallic Au and Ag particles. Apart from highlighting the influence of metal-ligand binding strength on the formation of core-shell nanoparticle architectures, our study also provides an easy means to produce Ag( shell)-Au( core) structures. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Ag(shell)-Au(core) nanoparticles; Anti-Galvanic reactions

Preparation of mesoporous titanosilicate with isolated Ti active centers for cyclohexene oxidation - Gupta, S.; Vinod, C. P.; Jagadeesan, Dinesh (RSC Advances, 2015)
We report the preparation of mesoporous titanosilicate with active Ti centres using CTAB as the structure directing agent and ethylenediamine as the complexing agent (TSC-ED). The finalmaterial contained isolated Ti4+ centres substituting Si4+ in the mesoporous silica framework. The crucial role played by ethylenediamine in complexing with Ti4+ during the sol-gel process and preventing the phase segregation of TiO2 was studied systematically. The textural parameters, structural order, morphology, nature and co-ordination of Ti species were analyzed using various techniques such as X-ray diffraction (XRD), UV-vis diffused reflectance spectroscopy (UV-vis DRS), UV resonance Raman spectroscopy, Fourier transformed Infrared spectroscopy (FT-IR), field emission scanning electron microscopy (FESEM), transition electron microscopy (TEM), and X-ray photoelectron spectroscopy. Finally, the catalysts were tested for catalytic activity in the oxidation of cyclohexene using various oxidants.

Preparation of Ni3S2 and Ni3S2-Ni nanosheets via solution based processes - Busupalli, Balanagulu; Date, Kalyani S.; Datar, Suwarna; Bhagavatula L. V. Prasad (Crystal Growth & Design, 2015)
An easy and convenient preparation of nanometer-thick sheets of Ni3S2 and Ni3S2–Ni from solution processed molecularly thin sheets of Ni-thiolates is described. Both the Ni3S2 and Ni3S2–Ni possessed sheet-like morphologies and displayed room temperature ferromagnetic characteristics. The ferromagnetic nature of these samples was also confirmed by MFM studies, and AFM/TEM investigations substantiated the sheet-like morphology of the samples.

Process optimization by response surface methodology for transesterification of renewable ethyl acetate to butyl acetate biofuel additive over borated USY zeolite - Nandiwale, Kakasaheb Y.; Galande, Nitish D.; Bokade, Vijay V. (RSC Advances, 2015)
Butyl acetate, a renewable biofuel additive was synthesized by transesterification of butanol with ethyl acetate via a renewable and sustainable route. Use of fermentation derived bio-butanol and bio-ethyl acetate for synthesis of butyl acetate would be a more advantageous route over conventional Fischer Esterification. For the first time, a heterogeneous zeolite catalyst such as Ultra Stable Y (USY) and its modified versions obtained by borating on parent USY were used for the synthesis of butyl acetate. Response surface methodology (RSM) was employed to optimize the process parameters for transesterification of butanol with ethyl acetate over a 4% (w/w) B-USY catalyst. The influence of three crucial process variables such as catalyst loading, molar ratio, and reaction temperature on yield of butyl acetate were addressed by Box-Behnken experimental design (BBD). 4% (w/w) B-USY was proved to be a potential catalyst with 96% yield of butyl acetate at optimum process parameters. The 4% (w/w) B-USY catalyst was found to be reusable for 6 catalytic cycles.

Production of polyunsaturated fatty acids in recombinant lipomyces starkeyi through submerged fermentation - Salunke, Devyani; Manglekar, Rupali; Gadre, Ramchandra V.; Nene, Sanjay; Harsulkar, Abhay M. (Bioprocess and Biosystems Engineering, 2015)
Long chain polyunsaturated fatty acids (LCPUFA) are known to play an important role in human health and nutrition. Considering the limitation of LCPUFA sources, it is necessary to search new avenues for their production. Oleaginous yeasts are an attractive target for harvesting single cell oil, mainly because of the ease of cultivation with cheaper raw material. Lipomyces starkeyi is one such oleaginous yeast, which can accumulate oil to the extent of 60 % of its biomass and where genetic transformation can be achieved. In our earlier work, Delta 15 desaturase gene (AEP37840) from flax was transformed into L. starkeyi. In the present work, we report optimization of medium for the production of omega-3 enriched oil from this transformed yeast. A basic medium containing 20 g/l glucose as a carbon source and 10 g/l yeast extract as a nitrogen source was used during fermentation. At regular time intervals, glucose was fed to maintain high C:N ratio (65:10) during fermentation. Under the most favorable conditions, dry biomass and total lipid content were 18 and 7.29 g/l, respectively. Prior to genetic transformation, L. starkeyi contained 56.03 mg/l DHA along with 71.4 mg/l EPA and 42.2 mg/l ALA. Genetic engineering of this yeast resulted in a strain that produced 1080 mg/l DHA (17.4 %) along with 74.28 mg/l EPA and 126.72 mg/l ALA possibly through modification of PUFA biosynthetic pathway. To the best of our knowledge, this is a first report of DHA enrichment and opens up avenues for LCPUFA production through L. starkeyi.
Keywords: Fermentation; LCPUFA; Lipid production; Oleaginous yeast

Proline-catalyzed alpha-aminooxylation of beta-amino aldehydes: access to enantiomerically pure syn- and anti-3-amino-3-aryl-1,2-alkanediols - Venkataramasubramanian, V.; Kiran, I. N. Chaithanya; Sudalai, Arumugam (Synlett, 2015)
A new synthetic method for enantioselective synthesis of syn 3-amino-3-aryl-1,2-alkanediols via praline catalyzed alpha-aminaoxn y ylation of beta-amino aldehydes des are described. This methodology is successfully applied to a concise and protecting group-free asymmetric synthesis of (-)-cytoxazone (+)-epi-cytoxazone and formal synthesis of N-thiolated 2-oxazolidinone.
Keywords: amino aldehydes; Asymmetric synthesis; catalysis; diastereoselectivity; Enantioselectivity; Natural product

Proline-catalyzed sequential syn-mannich and [4+1]-annulation cascade reactions to form densely functionalized pyrrolidines - Aher, Ravindra D.; Kumar, B. Senthil; Sudalai, Arumugam (Journal of Organic Chemistry, 2015)
A highly efficient one-pot [4 + 1]-annulation process for the asymmetric synthesis of densely functionalized pyrrolidine derivatives is described. The in situ generated syn-Mannich adduct obtained via proline catalysis acts as a four-atom component, and Coreys sulfur ylide or ethyl bromoacetate acts as a one-atom carbon source to construct pyrrolidine units in a highly enantio- and diastereoselective manner.

Propensity of self-assembled leucine-lysine diblock copolymeric alpha-helical peptides to remain in parallel and antiparallel alignments in water - Sarkar, Sujit; Pandey, Prithvi Raj; Roy, Sudip (Journal of Physical Chemistry B, 2015)
Molecular dynamics Simulation study of alpha-helical diblock copolypeptides: preassembled in parallel and antiparallel alignments in water are presented. The assembled peptide lamellar structures were not disrupted even: after performing three step simulation protocols. Primarily hydrogen bonds between peptide are responsible for the stability: The analysis of the trajectory also suggests that Water plays a significant role in favoring self assembly We have detected continuous hydrogen bonded network structure, which is further responsible for the stability Of the lamellar structures. We have performed a detailed analysis of the hydrogen bonded network structure and its length. Further, free energy calculations revealed that the degree of stability for both lamellae are similar. The present study provides structural insight into the stability of self-assembled structures of block copolypeptides.

Protein ligand complex guided approach for virtual screening - Karthikeyan, Muthukumarasamy; Pandit, Deepak; Vyas, Renu (Combinatorial Chemistry & High Throughput Screening, 2015)
The target ligand association data is a rich source of information which is not exploited enough for drug design efforts in virtual screening. A java based open-source toolkit for Protein Ligand Network Extraction (J-ProLiNE) focused on protein-ligand complex analysis with several features integrated in a distributed computing network has been developed. Sequence alignment and similarity search components have been automated to yield local, global alignment scores along with similarity and distance scores. 10000 proteins with co-crystallized ligands from pdb and MOAD databases were extracted and analyzed for revealing relationships between targets, ligands and scaffolds. Through this analysis, we could generate a protein ligand network to identify the promiscuous and selective scaffolds for multiple classes of proteins targets. Using J-ProLiNE we created a 507 x 507 matrix of protein targets and native ligands belonging to six enzyme classes and analyzed the results to elucidate the protein-protein, protein-ligand and ligand-ligand interactions. In yet another application of the J-ProLiNE software, we were able to process kinase related information stored in US patents to construct disease-gene-ligand-scaffold networks. It is hoped that the studies presented here will enable target ligand knowledge based virtual screening for inhibitor design.
Keywords: Complexes; ligand; protein; scaffolds; sequences; similarity score; virtual screening

Proton transport mechanism of imidazole, triazole and phosphoric acid mixtures from ab initio molecular dynamics simulations - Pahari, Swagata; Roy, Sudip (Physical Chemistry Chemical Physics, 2015)
We performed first principles molecular dynamics simulations to elucidate the mechanism and role of 1,2,3-triazole in proton transport while it is mixed with phosphoric acid (PA) and a phosphoric acid imidazole mixture. PA doped imidazole based polymer acts as an efficient polyelectrolyte membrane for fuel cells. The conductivity of this membrane increases when triazole is added to the system. For the first time we performed ab initio molecular dynamics simulations of complex mixtures of PA, imidazole and triazole. We have quantitatively estimated the structural diffusion and vehicular motion of protons. We found that upon the addition of triazole in PA and the PA imidazole mixture, the structural diffusion of protons increases significantly. The mechanism of proton transport is different when triazole is added to the mixture. We have also identified two different paths for structural diffusion (constructive and non-constructive) that contribute to long and short range proton transport.

Pt-nanoparticle functionalized carbon nano-onions for ultra-high energy supercapacitors and enhanced field emission behaviour - Suryawanshi, Sachin R.; Kaware, Vaibhav; Chakravarty, Disha; Walke, Pravin S.; More, Mahendra A.; Joshi, Kavita; Rout, Chandra Sekhar; Late, Dattatray J. (RSC Advances, 2015)
In the present work, we have investigated the charge storage capacitive response and field emission behaviour of platinum (Pt) nanoparticles decorated on carbon nano onions (CNOs) and compared them with those of pristine carbon nano onions. The specific capacitance observed for Pt-CNOs is 342.5 F g(-1), about six times higher than that of pristine CNOs, at a scan rate of 100 mV s(-1). The decoration with Pt nanoparticles, without any binder or polymer separator on the CNO, leading to enhanced supercapacitance is due to easy accessibility of Na2SO4 electrolyte in the active material. The Density Functional Theory (DFT) calculations of these systems reveal enhancement in the Density of States (DOS) near the Fermi energy (E-F) on account of platinum decoration on the CNOs. Furthermore, the field emission current density of similar to 0.63 mA cm(-2) has been achieved from the Pt-CNOs emitter at an applied electric field of similar to 4.5 V mu m(-1) and from the pristine CNOs sample current density of similar to 0.4 mA cm(-2) has been achieved at an applied electric field of similar to 6.6 V mu m(-1). The observed enhanced field emission behavior has been attributed to the improved electrical conductivity and increased emitting sites of the Pt-CNO emitter. The field emission current stability of the Pt-CNO emitter over a longer duration is found to be good. The observed results imply multifunctional potential of Pt-CNOs, as supercapacitor material in various next generation hybrid energy storage devices, and field emitters for next generation vacuum nano/microelectronic devices.

p-type NiO hybrid visible photodetector - Mallows, John; Planells, Miguel; Thakare, Vishal; Bhosale, Reshma; Ogale, Satishchandra; Robertson, Neil (ACS Applied Materials & Interfaces, 2015)
A novel hybrid visible-light photodetector was created using a planar p-type inorganic NiO layer in a junction with an organic electron acceptor layer. The effect of different oxygen pressures on formation of the NiO layer by pulsed laser deposition shows that higher pressure increases the charge carrier density of the film and lowers the dark current in the device. The addition of a monolayer of small molecules containing conjugated pi systems and carboxyl groups at the device interface was also investigated and with correct alignment of the energy levels improves the device performance with respect to the quantum efficiency, responsivity, and photogeneration. The thickness of the Organic layer was also optimized for the device, giving a responsivity of 1.54 X 10(-2) A W-1 in 460 nm light.
Keywords: nickel oxide; organic; oxygen vacancies; photodetector; pulsed laser deposition; surface modifier

Pulsed laser-driven molecular self-assembly of cephalexin: aggregation-induced fluorescence and its utility as a mercury ion sensor - Singh, Pradeep Kumar; Prabhune, Asmita; Ogale, Satishchandra (Photochemistry and Photobiology, 2015)
A fluorescent self-assembly of cephalexin is obtained by pulsed laser irradiation process. An intense fluorescence emission is found in the self-assembled form due to occurrence of a typical aggregation-induced emission in cephalexin molecules. It is observed that fluorescence quenching of the self-assembled fluorescent nanostructures occurs in the presence of extremely low Hg++ ions concentrations (10(-7) M) as compared to other heavy metal ions e.g. Ferrous (Fe++), Manganese (Mn++), Magnesium (Mg++), Cobalt (Co++), Nickel (Ni++) and Zinc (Zn++) at the same concentrations.

Purification and characterization of an agglutinin from datura innoxia with antineoplastic activity - Singh, Ruby; Nawale, Laxman; Gaikwad, Sushama M.; Suresha, C. G. (National Science Day, At CSIR-NCL, 2015)
Lectins are carbohydrate binding proteins of non-immune origin. Due to their multivalency, lectins can be easily detected using agglutination. Lectins are reported to induce cytotoxicity or inhibition of growth in various cancer cells., hence good therapeutic startegy against cancer. Factors such as specificity, stability, assay rapidity, and costs combine to make lectins attractive diagnostic reagents. Datura innoxia belongs to family of Solanaceae.All parts of the plant are hallucinogenic, hypnotic and narcotic. Application: at low dose acts as pain killer, relieves asthma and rheumatism.

Pyrazine-based organometallic complex: synthesis, characterization, and supramolecular chemistry - Bhowmick, Sourav; Chakraborty, Sourav; Das, Atanu; Rajamohanan, P. R.; Das, Neeladri (Inorganic Chemistry, 2015)
The design, synthesis, and characterization of a new pyrazine-based ditopic platinum(II) organometallic complex are reported. The molecular structure of the organoplatinum pyrazine dipod was determined by single-crystal X-ray crystallography. The potential utility of this organometallic ditopic acceptor as a building block in the construction of neutral metallasupramolecular macrocycles containing the pyrazine motif was explored. Pyrazine motifs containing supramolecules were characterized by multinuclear NMR (including H-1 DOSY), mass spectrometry, and elemental analysis. The geometry of each supramolecular framework was optimized by employing the PM6 semi-empirical molecular orbital method to predict its shape and size. The ability of the pyrazine-based organoplatinum complex to act as a host for nitroaromatic guest (2,4-dinitrotoluene and PA) molecules was explored by isothermal titration calorimetry (ITC). The binding stoichiometry and thermodynamic parameters of these host guest complexation reactions were evaluated using ITC. Theoretical calculations were performed to obtain insight into the binding pattern between the organometallic host and nitroaromatic guests. The preferable binding propensity of the binding sites of complex 1 for both nitroaromatics (PA and 2,4-dinitrotoluene) determined by molecular simulation studies corroborates well with the experimental results as obtained by ITC experiments.

P4VP and oligo(phenylenevinylene)-perylenebisimide mixed donor-acceptor supramolecular comb polymer complexes with improved charge carrier mobility - Saibal, B.; Chithiravel, Sundaresan; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2016)
Random donor-acceptor (D-A) supramolecular comb polymers were formed when hydroxyl functionalized donor and acceptor small molecules based on Oligo(phenylenevinylene) (named OPVCN-OH) and Perylenebisimide (named UPBI-PDP), respectively, were complexed with Poly(4-vinyl pyridine) (P4VP). A series of random D-A supramolecular comb polymers were formed by varying the ratios of UPBI-PDP and OPVCN-OH with P4VP. A 100% P4VP-donor polymer complex [P4VP(OPV1.00)] and a 100% P4VP-acceptor polymer complex [P4VP(UPBI1.00)] were also synthesized and characterized. Complex formation was confirmed by FT-IR and H-1 NMR spectroscopy. Solid state structural studies carried out using small angle X-ray scattering and wide angle X-ray diffraction experiments revealed altered packing of the D and A molecules in the complexes. Transmission electron microscopy images showed lamellar structures in the <10 nm scale for the P4VP(OPV1.00), P4VP(UPBI1.00), and mixed P4VP (D-A) complexes. The effect of the nanoscopic D-A self-assembly on the bulk mobility of the materials was probed using SCLC measurements. The mixed D-A random complexes exhibited ambipolar charge transport characteristics with higher values for the average bulk hole mobility estimate. P4VP(OPV0.25+UPBI0.75) exhibited an average hole mobility in the order of 10(-2) cm(2) V-1 s(-1) and electron mobility 10(-5) cm(2) V-1 s(-1). (C) 2016 Wiley Periodicals, Inc.
Keywords: donor-acceptor; oligo(phenylenevinylene); P4VP; Perylenebisimide; Self-assembly; structure-property relations; supramolecular comb polymer; supramolecular structures

Palladium supported on fluorite structured redox CeZrO4-δ for heterogeneous suzuki coupling in water: a green protocol - Burange, Anand S.; Shukla, Rakesh; Tyagi, Avesh Kumar; Gopinath, Chinnakonda S. (Chemistry Select, 2016)
Pd on redox CeZrO4-δ catalysts was prepared, characterized and their activity was evaluated for Suzuki coupling reaction in water under reflux condition. Fresh and reduced form of 5 % Pd (R−Pd5) on CeZrO4-δ catalyst exhibited 100 % conversion in 2.5 and 1 h, respectively. R−Pd5 shows significant activity for wide range of substrate compatibility and for less reactive aryl bromides too. The mechanistic investigations proved the important role of redox CeZrO4-δ support on the catalytic activity. It was observed that the presence of oxygen vacancy along with Ce3+ enhances the activity. 1 wt % Pd photodeposited on pre-reduced CeZrO4-δ support requires a mere 20 min. for 100 % conversion of Suzuki coupling. Effect of metal dispersion and particle size on catalytic activity is also discussed. High Pd dispersion with small particle size (4±1 nm), particle size preservation after reaction, strong metal-support interaction and no leaching fully suggest the heterogeneous mechanism is operative for Suzuki coupling on 1 wt % Pd photodeposited on reduced CeZrO4-δ support. Present work hints the possibility of achieving high conversion for Suzuki reaction with very small amount of Pd through better dispersion by taking advantage of redox support and in water.

Palladium-catalyzed internal nucleophile-assisted hydration-olefin insertion cascade: diastereoselective synthesis of 2,3-dihydro-1H-inden-1-ones - Vinoth, Perumal; Nagarajan, Subbiah; Maheswari, C. Uma; Sudalai, Arumugam; Pace, Vittorio; Sridharan, Vellaisamy (Organic Letters, 2016)
A novel palladium-catalyzed hydration-olefin insertion cascade assisted by internal nucleophiles was developed for the synthesis of biologically significant 2,3-dihydro-1H-inden-1-ones under mild conditions. A detailed mechanistic study revealed that the assistance of the internal nucleophiles is crucial to trigger the cascade reaction via nucleopalladation of the alkyne moiety. The overall reaction is equivalent to regioselective hydration of alkynes followed by intramolecular Michael addition. This highly efficient and 100% atom-economical domino sequence afforded cis-2,3-disubstituted 2,3-dihydro-1H-inden-1-ones in excellent yields (up to 99%) with complete diastereoselectivity.

Parasitism by Chelonus blackburni (Hymenoptera) affects food consumption and development of Helicoverpa armigera (Lepidoptera) and cellular architecture of the midgut - Sanap, Yogita; Dawkar, Vishal V.; Giri, Ashok P.; Sen, Avalokiteswar; Pandit, Radhakrishna S. (Journal of Asia-Pacific Entomology, 2016)
Biological control agents are vital components of an integrated pest management strategy, and this is frequently referred to as natural control. Natural enemies of insect pests include predators, parasitoids, and pathogens. Among them, a parasitoid, Chelonus blackburni (Cameron), was found to be the best biological control agent for the polyphagous pest, Helicoverpa armigera (Hubner). C. blackburni alters the feeding performance of H. annigera larvae upon parasitism and as a result severely affects growth and development. Moreover, it shortens the feeding period of H. armigera and increases mortality. Furthermore, total hemocyte count (THC) was significantly decreased in parasitized larvae than control. Parasitized H. armigera had 26% less number of blood cells compared to healthy larvae. Histological studies showed that the structure of midgut of H. annigera is drastically affected by C. blackburni leading to reduced food consumption, which ultimately led to larval death. The present study provides an insight to changes involved in H. annigera due to parasitism by C blackburni, a parasite that could be used as an effective biocontrol agent to manage H. armigera. (C) 2015 Korean Society of Applied Entomology, Taiwan Entomological Society and Malaysian Plant Protection Society. Published by Elsevier B.V. All rights reserved.

Passive microrheology in the effective time domain: analysing time dependent colloidal dispersions - Vyas, Bhavna M.; Orpe, Ashish V.; Kaushal, Manish; Joshi, Yogesh M. (Soft Matter, 2016)
We studied the aging dynamics of an aqueous suspension of LAPONITE (R), a model time dependent soft glassy material, using a passive microrheology technique. This system is known to undergo physical aging during which its microstructure evolves progressively to explore lower free energy states. Optical microscopy is used to monitor the motion of micron-sized tracer probes embedded in a sample kept between two glass plates. The mean square displacements (MSD) obtained from the motion of the tracer particles show a systematic change from a purely diffusive behavior at short aging times to a subdiffusive behavior as the material ages. Interestingly, the MSDs at all the aging times as well as different LAPONITE (R) concentrations superpose remarkably to show a time-aging time master curve when the system is transformed from the real time domain to the effective time domain, which is obtained by rescaling the material clock to account for the age dependent relaxation time. The transformation of the master curve from the effective time domain to the real time domain leads to the prediction of the MSD in real time over a span of 5 decades when the measured data at individual aging times are only over 2 decades. Since the MSD obtained from microrheology is proportional to the creep compliance of a material, by using the Boltzmann superposition principle along with the convolution relation in the effective time domain, we predict the stress relaxation behavior of the system in real time. This work shows that the effective time approach applied to microrheology facilitates the prediction of long time creep and relaxation dynamics of a time dependent soft material by carrying out short time experiments at different aging times.

Pb2+-N bonding chemistry: recycling of polyaniline-pb nanocrystals waste for generating high-performance supercapacitor electrodes - Jha, Plawan Kumar; Singh, Santosh K.; Gatla, Suresh; Mathon, Olivier; Kurungot, Sreekumar; Ballav, Nirmalya (Journal of Physical Chemistry C, 2016)
Understanding of Pb-N bonding chemistry is not only fundamentally important in the view of relativistic inert-pair effect but also is important for therapeutic as well as environmental applications. In the present study, an unusual reactivity of N-containing pi-conjugated polyaniline emeraldine base (EB) toward aqueous Pb2+ ions has been identified. In the course of sequestering Pb2+ ions by EB, cuboid-shaped nanocrystals were isolated. Synchrotron-based X-ray absorption near-edge structure and extended X-ray absorption fine structure techniques were employed to understand Pb-N bonding chemistry in EB-Pb nanocrystals. The adopted methodology of slow exposure of HCl vapor to EB-Pb nanomaterial facilitated the isolation of polyaniline emeraldine-salt (ES) with unique morphological patterns, porosity and electrical conductivity. The electrochemical device based on recycled ES showed high-capacitance value (similar to 606 F/g @1 A/g and similar to 663 F/g @10 mV/s), high-energy density (similar to 14.8 Wh/kg at power density of similar to 663 W/kg) and excellent-cycling stability (only similar to 15% degradation after 1100 continued cycles at current density of 5 A/g). Notably, ES materials prepared directly from EB and upon exposing HNO3 vapor exhibited greatly inferior device performance.

Pd-catalyzed reductive cleavage of N-N bond in dibenzyl-1-alkylhydrazine-1,2-dicarboxylates with PMHS: application to a formal enantioselective synthesis of (R)-sitagliptin - Dey, Soumen; Gadakh, Sunita K.; Ahuja, Brij Bhushan; Kamble, Sanjay P.; Sudalai, Arumugam (Tetrahedron Letters, 2016)
An environmentally benign approach involving Pd-catalyzed reductive N-N bond cleavage in dibenzyl-1-alkylhydrazine-1,2-dicarboxylates leading to the synthesis of N-(tert-butoxy)carbamates under very mild conditions has been described. PMHS serves as an inexpensive source of hydride in MeOH/deionized H2O medium. This protocol has been successfully applied in the formal synthesis of (R)-sitagliptin, an anti-diabetic drug. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: anti-Diabetic; Environmentally benign; Hydrazine; PMHS; Reductive cleavage

Pd(II)-catalyzed intramolecular tandem olefin amidation/C-H activation protocol for the syntheses of the protoberberine class of natural products - Garad, Dnyaneshwar N.; Mhaske, Santosh B. (Organic Letters, 2016)
A Pd(II)-catalyzed intramolecular tandem olefin amidation/C-H activation protocol has been developed for the synthesis of an 8-oxoprotoberberine core. It was successfully applied for the syntheses of (+/-)-8-oxocanadine, (+/-)-8-oxotetrahydropalmitine, and (+/-)-8-oxostylopine, which can be easily converted to the respective protoberberine natural products. The short synthetic route demonstrated would be useful for the synthesis of a large number of natural products and their analogues featuring a protoberberine scaffold.

Peeping into genomic architecture by re-sequencing of Ochrobactrum intermedium M86 strain during laboratory adapted conditions - Gohil, K. N.; Neurgaonkar, P. S.; Paranjpe, A.; Dastager, S. G.; Dharne, M. S. (Genomics Data, 2016)
Advances in de novo sequencing technologies allow us to track deeper insights into microbial genomes for restructuring events during the course of their evolution inside and outside the host. Bacterial species belonging to Ochrobactrum genus are being reported as emerging, and opportunistic pathogens in this technology driven era probably due to insertion and deletion of genes. The Ochrobactrum intermedium M86 was isolated in 2005 from a case of non-ulcer dyspeptic human stomach followed by its first draft genome sequence in 2009. Here we report re-sequencing of O. intermedium M86 laboratory adapted strain in terms of gain and loss of genes. We also attempted for finer scale genome sequence with 10 times more genome coverage than earlier one followed by comparative evaluation on Ion PGM and Illumina MiSeq. Despite their similarities at genomic level, lab-adapted strain mainly lacked genes encoding for transposase protein, insertion elements family, phage tail-proteins that were not detected in original strain on both chromosomes. Interestingly, a 5 kb indel was detected in chromosome 2 that was absent in original strain mapped with phage integrase gene of Rhizobium spp. and may be acquired and integrated through horizontal gene transfer indicating the gene loss and gene gain phenomenon in this genus. Majority of indel fragments did not match with known genes indicating more bioinformatic dissection of this fragment. Additionally we report genes related to antibiotic resistance, heavy metal tolerance in earlier and re-sequenced strain. Though SNPs detected, there did not span urease and flagellar genes. We also conclude that third generation sequencing technologies might be useful for understanding genomic architecture and re-arrangement of genes in the genome due to their ability of larger coverage that can be used to trace evolutionary aspects in microbial system.

Penicillin acylases revisited: importance beyond their industrial utility - Avinash, Vellore Sunder; Pundle, Archana Vishnu; Ramasamy, Sureshkumar; Suresh, Cheravakkattu Gopalan (Critical Reviews In Biotechnology, 2016)
It is of great importance to study the physiological roles of enzymes in nature; however, in some cases, it is not easily apparent. Penicillin acylases are pharmaceutically important enzymes that cleave the acyl side chains of penicillins, thus paving the way for production of newer semi-synthetic antibiotics. They are classified according to the type of penicillin (G or V) that they preferentially hydrolyze. Penicillin acylases are also used in the resolution of racemic mixtures and peptide synthesis. However, it is rather unfortunate that the focus on the use of penicillin acylases for industrial applications has stolen the spotlight from the study of the importance of these enzymes in natural metabolism. The penicillin acylases, so far characterized from different organisms, show differences in their structural nature and substrate spectrum. These enzymes are also closely related to the bacterial signalling phenomenon, quorum sensing, as detailed in this review. This review details studies on biochemical and structural characteristics of recently discovered penicillin acylases. We also attempt to organize the available insights into the possible in vivo role of penicillin acylases and related enzymes and emphasize the need to refocus research efforts in this direction.
Keywords: beta-lactam; choloyl glycine; in vivo role; Ntn hydrolases; pathogenicity; quorum sensing; regulation; signalling

Pharmaceutical cocrystals: walking the talk - Bolla, Geetha; Nangia, Ashwini (Chemical Communications, 2016)
Pharmaceutical cocrystals belong to a sub-class of cocrystals wherein one of the components is a drug molecule (or an active pharmaceutical ingredient, API) and the second is a benign food or drug grade additive (generally regarded as safe, GRAS). The two components are hydrogen-bonded in a fixed stoichiometric ratio in the crystal lattice. In the past decade, pharmaceutical cocrystals have demonstrated significant promise in their ability to modify the physicochemical and pharmacokinetic properties of drug substances, such as the solubility and dissolution rate, bioavailability, particle morphology and size, tableting and compaction, melting point, physical form, biochemical and hydration stability, and permeability. In this feature review, we highlight some prominent examples of drug cocrystals which exhibit variable hardness/softness and elasticity/plasticity depending on coformer selection, improvement of solubility and permeability in the same cocrystal, increase of the melting point for solid formulation, enhanced color performance, photostability and hydration stability, and a longer half-life. Cocrystals of flavanoids and polyphenols can make improved pharmaceuticals and also extend to the larger class of nutraceuticals. The application of crystal engineering to assemble ternary cocrystals expands this field to drug-drug cocrystals which may be useful in multi-drug resistance, mitigating side effects of drugs, or attenuating/enhancing drug action synergistically by rational selection. The advent of new techniques for structural characterization beyond the standard X-ray diffraction will provide a better understanding of drug phases which are at the borderline of crystalline-amorphous nature and even newer opportunities in the future.

Phenothiazine and carbazole substituted pyrene based electroluminescent organic semiconductors for OLED devices - Salunke, Jagadish K.; Wong, F. L.; Feron, Krishna; Manzhos, Sergei; Lo, Ming Fai; Shinde, Durgaprasad; Patil, Abhijeet; Lee, C. S.; Roy, V. A. L.; Sonar, Prashant; Wadgaonkar, Prakash P. (Journal of Materials Chemistry C, 2016)
Due to their easy availability, low cost and opportunities for exploiting reactions of bromo substituents, 1,3,6,8-tetrabromopyrene has attracted major attention in the organic electronics community for designing and constructing novel classes of pyrene based organic semiconducting functional materials. In the present work, 1,3,6,8-tetrabromo pyrene was transformed into the corresponding tetrasubstituted carbazole and phenothiazine derivatives using the classical Suzuki coupling reaction. These newly synthesized materials with a carbazole substituent (PY-CA) and a phenothiazine substituent (PY-PH) were characterised thoroughly and were successfully used as an active light-emitting layer in organic light emitting diodes which resulted in blue and green emission with promising device performance. PY-CA exhibited the maximum brightness at around 2500 cd m(-2) and the power efficiency of 1.5 lm W-1 while that of PY-PH exhibited 2116 cd m(-2) and 0.45 lm W-1 respectively.

Phenylacetylene hydrogenation on Au@Ni bimetallic core-shell nanoparticles synthesized under mild conditions - Vysakh, A. B.; Lazar, Anish; Yadukiran, V.; Singh, A. P.; Vinod, C. P. (Catalysis Science & Technology, 2016)
The synthesis of Au@Ni bimetallic core-shell nanoparticles through an energy efficient (lower temperature) route in oleylamine following a sequential reduction strategy is reported. The method is found to be useful for the synthesis of a very thin nickel shell (2 nm) over a gold core (15 nm). Synergistic effects are observed in catalyzing phenylacetylene hydrogenation under different solvent conditions.

Photocatalytic degradation of ciprofloxacin center dot HCl using Aeroxide (R) P-25 TiO2 photocatalyst: comparative evaluation of solar and artificial radiation - Shetty, Rohit; Kothari, Gaurav; Tambe, Amruta S.; Kulkarni, Bhaskar D.; Kamble, Sanjay P. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2016)
The photocatalytic degradation of ciprofioxacin (CFX) has been investigated using Aeroxide (R) P-25 TiO2 photocatalyst in the presence of solar as well as artificial radiation. The effects of different operating parameters like initial concentration of CFX, catalyst loading, pH of solution and effect of co-existing ions on photocatalytic degradation of CFX have been investigated with a view to establish the optimum operating conditions. It is observed that as the initial concentration of CFX increases, the rate of photocatalytic degradation decreases. Optimum catalyst loading is observed at 1 g L-1 for CFX concentration of 100 mg L-1. Over the pH range 3-11, maximum degradation rate occurs at pH 9. The mechanism and intermediates formed during the photocatalytic degradation of CFX are discussed based on UPLC-MS/MS analysis. From kinetic studies, it is found that the photocatalytic degradation obeys pseudo-first order kinetics. The degradation rate constant using solar radiation is about 1.7 times higher than that under artificial radiation.
Keywords: Advanced oxidation process; Aeroxide (R) P-25 TiO2; Artificial radiation; Ciprofloxacin center dot HCl; Degradation; Pharmaceutical micropollutants; Photocatalysis; Solar radiation

Photocatalytic degradation of methylene blue on Sn-doped titania nanoparticles synthesized by solution combustion route - Bhange, P. D.; Awate, S. V.; Gholap, Ramkrishna S.; Gokavi, G. S.; Bhange, Deu S. (Materials Research Bulletin, 2016)
Series of tin-doped titania nanoparticles with varying tin content in the range 0-20 mol% have been prepared by solution combustion synthesis route using urea as a fuel. The structure, surface morphology and optical activity of Sn-doped TiO2 nanoparticles were investigated by various analytical techniques such as powder XRD, SEM, TEM, UV-vis and N-2 adsorption study. The crystalline structures of the various phases were studied by rietveld refinement of the XRD data. The photocatalytic performance of Sn-doped titania nanoparticles were tested for degradation of MB under UV and visible light irradiation. The results reveal that the photocatalytic activity increases with increase in tin content which may be due to decrease in crystallite size with increase in surface area. The doping of Sn into TiO2 lattice hinders the recombination of electrons and holes thus enhance the quantum efficiency of photocatalytic reaction. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; composites; Nanostructures; X-ray diffraction

Photocatalytic H-2 evolution from water-methanol mixtures on InGaO3(ZnO)(m) with an anisotropic layered structure modified with CuO and NiO cocatalysts - Narendranath, Soumya B.; Thekkeparambil, Saranya V.; George, Leena; Thundiyil, Shibin; Devi, R. Nandini (Journal of Molecular Catalysis A-Chemical, 2016)
InGaO3(ZnO)(m) series of oxides is found to be active for photocatalytic H-2 evolution from water-methanol mixtures. The structure of this series is highly anisotropic with InO6 octahedral layers sandwiching Ga/ZnOn polyhedra. The structural anisotropy in which the conducting layer is spatially separated from the charge generation sites may help in suppressing charge recombination and consequently enhance catalytic activity. The band gaps of the series obtained from absorption spectra are above 3.6 eV and hence they are not active under visible light irradiation. H-2 evolution is considerably enhanced under UV light on employing NiO as cocatalyst due to facile electron transfer from InGaO3(ZnO)(m). to NiO. However, when CuO is used as cocatalyst, visible light activity could be brought out. Due to the very low band gap of CuO, it can act as a sensitizer absorbing in visible light. The band positions become conducive for H-2 evolution due to band alignments consequent to electron accumulation in CuO conduction band. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: InGaO3(ZnO)(m); photocatalytic water splitting; visible light; XPS; XRD

Photochromic metal-organic frameworks for inkless and erasable printing - Garai, Bikash; Mallick, Arijit; Banerjee, Rahul (Chemical Science, 2016)
Inkless and erasable printing is the key solution towards a more sustainable paper industry, in terms of reducing paper wastages and the associated environmental hazards from waste paper processing. However, only a few cases have been reported in the literature where inkless printing has been tested in some practical systems. In an attempt to address this solution, we used photochromic metal-organic frameworks (MOFs) and tested their capability as inkless and erasable printing media. The printing was performed using sunlight as the light source on MOF-coated papers. The resulting printing had good resolution and stability, and was capable of being read both by the human eye and smart electronic devices; furthermore, the paper could be reused for several cycles without any significant loss in intensity. Interestingly, different coloured printing with a similar efficiency was achieved by varying the structure of the MOF.

Photoluminescent tetrahedral d(10)-metal Schiff base complexes exhibiting highly ordered mesomorphism - Chakraborty, Sutapa; Purkayastha, Debraj Dhar; Das, Gobinda; Bhattacharjee, Chira R.; Mondal, Paritosh; Prasad, S. Krishna; Rao, D. S. Shankar (Polyhedron, 2016)
A series of four-coordinate d(10)-metal complexes of the type [ML2] {M = Zn, Cd, Hg; L = 4-nitro-2-((octadecylimino)methyl)phenol}, incorporating a new N-alkylated bidentate [N,O]-donor salicylaldimine Schiff base ligand, has been synthesized and characterized by elemental analyses, FT-IR, UV-Vis, H-1 NMR and FAB-mass spectroscopies. The ligand is non-mesomorphic and devoid of any photoluminescence. The zinc(II) and cadmium(II) complexes displayed highly ordered mesophases reminiscent of soft crystals. The phases have been characterized by polarizing optical microscopy (POM), differential scanning calorimetry (DSC) and powder X-ray diffraction (PXRD) studies. The complex of mercury(II) decomposed prior to melting. An orthogonal symmetry with a `herringbone' array for the zinc complex and a primitive triclinic symmetry (p(1)) for the cadmium complex, respectively, has been proposed. The complexes exhibited fluorescence at room temperature, both in the solution and in the solid state, with emission maxima in the blue region. Density functional theory (DFT) calculations carried out using the GAUSSIAN 09 program at the B3LYP level revealed a distorted tetrahedral geometry around the metal center in all the complexes. Natural bond orbital (NBO) analysis suggested appreciable charge transfer from the ligand to the metal center in the complexes. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Density functional theory; Luminescence; Mesophase; Schiff base; X-ray diffraction

Photoresponsive assemblies of linear-dendritic copolymers containing azobenzene in the dendron interior: the effect of the dendron structure on dye encapsulation and release - Kalva, Nagendra; Basutkar, Nitin B.; Ambade, Ashootosh V. (RSC Advances, 2016)
Hydrophobic dendrons with different numbers and positions of azobenzenes as well as different groups benzyl and dodecyl, on the periphery were synthesised and attached to poly(ethylene glycol) using copper-catalysed azide-alkyne cycloaddition to obtain linear-dendritic copolymers. Self-assembly of the polymers in aqueous solution was characterised using dynamic light scattering (DLS), transmission electron microscopy (TEM) and critical micelle concentration (cmc). Formation of H-aggregates during micellisation was shown for polymers with a higher number of azobenzene units. Photoisomerisation of azobenzene in the assemblies was studied and the rate constant of thermal photoisomerisation was calculated. Release of hydrophobic dye Nile red upon photoisomerisation of azobenzene occurred without disruption of micellar aggregates. Dye release varied with the pathway - thermal or visible light irradiation, followed for cis-trans isomerisation. The encapsulation capacity of the micelles and extent of dye release in either pathway were found to be influenced by the dendron structure. A polymer with a lower number of azobenzenes and aliphatic periphery on the dendron showed significantly different behaviour than polymers with a larger number of aromatic units.

Physicochemical and antimicrobial photodynamic chemotherapy of unsymmetrical indium phthalocyanines alone or in the presence of magnetic nanoparticles - Osifeko, Olawale L.; Uddin, Imran; Mashazi, Philani N.; Nyokong, Tebello (New Journal of Chemistry, 2016)
An AB(3) type photosensitiser, consisting of 4-pyridylsulfanyl units (denoted as B-3) and one aminophenoxy (denoted as A) group (complex 3) was synthesized. Complex 3 was then quaternized to form complex 4. The aminophenoxy substituent of complex 3 was used for the formation of the amide linkage with the carboxylic functionalised magnetic nanoparticles. Complexes 3 and 4 and their conjugates with magnetic nanoparticles were then used for photodynamic antimicrobial chemotherapy on E. coli. The cationic photosensitiser 4 showed a high efficiency for photodynamic antimicrobial chemotherapy at a very low concentration compared to its conjugate on E. coli.

Phytase production by solid-state fermentation of groundnut oil cake by Aspergillus niger: A bioprocess optimization study for animal feedstock applications - Buddhiwant, Priyanka; Bhavsar, Kavita; Kumar, V. Ravi; Khire, Jayant M. (Preparative Biochemistry & Biotechnology, 2016)
This investigation deals with the use of agro-industrial waste, namely groundnut oil cake (GOC), for phytase production by the fungi Aspergillus niger NCIM 563. Plackett-Burman design (PBD) was used to evaluate the effect of 11 process variables and studies here showed that phytase production was significantly influenced by glucose, dextrin, distilled water, and MgSO4 center dot 7H(2)O. The use of response surface methodology (RSM) by Box-Behnken design (BBD) of experiments further enhanced the production by a remarkable 36.67-fold from the original finding of 15 IU/gds (grams of dry substrate) to 550 IU/gds. This is the highest solid-state fermentation (SSF) phytase production reported when compared to other microorganisms and in fact betters the best known by a factor of 2. Experiments carried out using dried fermented koji for phosphorus and mineral release and also thermal stability have shown the phytase to be as efficient as the liquid enzyme extract. Also, the enzyme, while exhibiting optimal activity under acidic conditions, was found to have significant activity in a broad range of pH values (1.5-6.5). The studies suggest the suitability of the koji supplemented with phytase produced in an SSF process by the "generally regarded as safe" (GRAS) microorganism A. niger as a cost-effective value-added livestock feed when compared to that obtained by submerged fermentation (SmF).

Phytogenic silver, gold, and bimetallic nanoparticles as novel antitubercular agents - Singh, Richa; Nawale, Laxman; Arkile, Manisha A.; Wadhwani, Sweety; Shedbalkar, Utkarsha; Chopade, Snehal; Sarkar, Dhiman; Chopade, Balu Ananda (International Journal of Nanomedicine, 2016)
Purpose: Multi- and extensively drug-resistant tuberculosis (TB) is a global threat to human health. It requires immediate action to seek new antitubercular compounds and devise alternate strategies. Nanomaterials, in the present scenario, have opened new avenues in medicine, diagnosis, and therapeutics. In view of this, the current study aims to determine the efficacy of phytogenic metal nanoparticles to inhibit mycobacteria. Methods: Silver (AgNPs), gold (AuNPs), and gold-silver bimetallic (Au-AgNPs) nanoparticles synthesized from medicinal plants, such as Barleria prionitis, Plumbago zeylanica, and Syzygium cumini, were tested against Mycobacterium tuberculosis and M. bovis BCG. In vitro and ex vivo macrophage infection model assays were designed to determine minimum inhibitory concentration (MIC) and half maximal inhibitory concentration of nanoparticles. Microscopic analyses were carried out to demonstrate intracellular uptake of nanoparticles in macrophages. Besides this, biocompatibility, specificity, and selectivity of nanoparticles were also established with respect to human cell lines. Results: Au-AgNPs exhibited highest antitubercular activity, with MIC of <2.56 mu g/mL, followed by AgNPs. AuNPs did not show such activity at concentrations of up to 100 mu g/mL. In vitro and ex vivo macrophage infection model assays revealed the inhibition of both active and dormant stage mycobacteria on exposure to Au-AgNPs. These nanoparticles were capable of entering macrophage cells and exhibited up to 45% cytotoxicity at 30 mu g/mL (ten times MIC concentration) after 48 hours. Among these, Au-AgNPs synthesized from S. cumini were found to be more specific toward mycobacteria, with their selectivity index in the range of 94-108. Conclusion: This is the first study to report the antimycobacterial activity of AuNPs, AgNPs, and Au-AgNPs synthesized from medicinal plants. Among these, Au-AgNPs from S. cumini showed profound efficiency, specificity, and selectivity to kill mycobacteria. These should be investigated further to develop novel TB nanoantibiotics.
Keywords: Antimycobacterial agent; Cytotoxicity; drug resistance; Mycobacteria; Nanoparticles; tuberculosis

Pick and choose the spectroscopic method to calibrate the local electric field inside proteins - Haldar, Tapas; Kashid, Somnath M.; Deb, Pranab; Kesh, Sandeep; Bagchi, Sayan (Journal of Physical Chemistry Letters, 2016)
Electrostatic interactions in proteins play a crucial role in determining the structure function relation in biomolecules. In recent years, fluorescent probes have been extensively employed to interrogate the polarity in biological cavities through dielectric constants or semiempirical polarity scales. A choice of multiple spectroscopic methods, not limited by fluorophores, along with a molecular level description of electrostatics involving solute-solvent interactions, would allow more flexibility to pick and choose the experimental technique to determine the local electrostatics within protein interiors. In this work we report that ultraviolet/visible-absorption, infrared-absorption, or C-13 NMR can be used to calibrate the local electric field in both hydrogen bonded and non-hydrogen bonded protein environments. The local electric field at the binding site of a serum protein has been determined using the absorption wavelength as well as the carbonyl stretching frequency of its natural steroid substrate, testosterone. Excellent agreement is observed in the results obtained from two independent spectroscopic techniques.

Polybenzimidazole based polymeric ionic liquids possessing partial ionic character: effects of anion exchange on their gas permeation properties - Rewar, Anita S.; Shaligram, Sayali V.; Kharul, Ulhas K. (Journal of Membrane Science, 2016)
Polymeric ionic liquids (PILs) are emerging as promising membrane materials for CO2 separation. Present work is in continuation with our earlier efforts on evaluating gas permeation properties (especially, CO2) of film forming PILs based on polybenzimidazoles and efforts towards improving their permeability by structural tuning. This work specifically aims at evaluating effect of anion variation in chosen PILs possessing partial N-quaternization of imidazole moiety of PBI-Bul. Three anions (viz., Tf2N-, BF4- and Ac-) were chosen for the bromide exchange of two PILs, viz., [TBzPBI-Bul][Br](10) and [TBzPBI-Bul][Br](18), possessing degree of PEI N-quaternization (DQ) as 10 and 18%, respectively. Concurrent effects of variation in anion and DQ were analyzed in terms of physical and gas permeation properties of the resulting PILs. All of them possessed amorphous nature, adequate thermal stability ( >= 250 degrees C) and solvent solubility, which are primary requisites towards their applicability as a membrane material. PILs possessing BF4- anion exhibited improved CO2 permeability coefficient as well as its permselectivity over CH4 and N-2, in comparison to their counterparts with other anions. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Anion exchange; Gas separation; Polybenzimidazole; Polymeric ionic liquids (PILs)

Polyhedral oligomeric silsesquioxane-containing thiol-ene fibers with tunable thermal and mechanical properties - Fang, Yichen; Ha, Heonjoo; Shanmuganathan, Kadhiravan; Ellison, Christopher J. (ACS Applied Materials & Interfaces, 2016)
Polyhedral oligomeric silsesquioxanes (POSS) are versatile inorganic-organic hybrid building blocks that have potential applications as reinforcement nanofillers, thermal stabilizers, and catalyst supports for metal nano particles. However, fabrication of fibrous materials with high POSS content has been a challenge because of the aggregation and solubility limits of POSS units. In this paper, we describe a robust and environmentally friendly fabrication approach of inorganic-organic hybrid POSS fibers by integrating UV initiated thiol-ene polymerization and centrifugal fiber spinning. The use of monomeric liquids in this approach not only reduces the consumption of heat energy and solvent, but it also promotes homogeneous mixing of organic and inorganic components that allows integration of large amount of POSS (up to 80 wt %) into the polymer network. The POSS containing thiol-ene fibers exhibited enhanced thermomechanical properties compared to purely organic analogs as revealed by substantial increases in residual weight and a factor of 4 increase in modulus after thermal treatment at 1000 degrees C. This simple fabrication approach combined with the tunability in fiber properties afforded by tailoring monomer composition make POSS containing thiol-ene fibers attractive candidates for catalyst supports and filtration media, particularly in high-temperature and harsh environments.
Keywords: cross-linked fiber; enhanced thermomechanical properties; inorganic-organic hybrid fiber; POSS; reactive centrifugal spinning; thiol-ene photopolymerization

PolyHIPE derived freestanding 3D carbon foam for cobalt hydroxide nanorods based highperformance supercapacitor - Patil, Umakant M.; Ghorpade, Ravindra V.; Nam, Min Sik; Nalawade, Archana C.; Lee, Sangrae; Han, Haksoo; Jun, Seong Chan (Scientific Reports, 2016)
The current paper describes enhanced electrochemical capacitive performance of chemically grown Cobalt hydroxide (Co(OH)(2)) nanorods (NRs) decorated porous three dimensional graphitic carbon foam (Co(OH)(2)/3D GCF) as a supercapacitor electrode. Freestanding 3D porous GCF is prepared by carbonizing, high internal phase emulsion (HIPE) polymerized styrene and divinylbenzene. The PolyHIPE was sulfonated and carbonized at temperature up to 850 degrees C to obtain graphitic 3D carbon foam with high surface area (389 m(2) g(-1)) having open voids (14 mu m) interconnected by windows (4 mu m) in monolithic form. Moreover, entangled Co(OH)(2) NRs are anchored on 3D GCF electrodes by using a facile chemical bath deposition (CBD) method. The wide porous structure with high specific surface area (520 m(2) g(-1)) access offered by the interconnected 3D GCF along with Co(OH)(2) NRs morphology, displays ultrahigh specific capacitance, specific energy and power. The Co(OH)(2)/3D GCF electrode exhibits maximum specific capacitance about similar to 1235 F g(-1) at similar to 1 Ag-1 charge-discharge current density, in 1 M aqueous KOH solution. These results endorse potential applicability of Co(OH)(2)/3D GCF electrode in supercapacitors and signifies that, the porous GCF is a proficient 3D freestanding framework for loading pseudocapacitive nanostructured materials.

Porous thin films towards bridging the material gap in heterogeneous catalysis - Dubey, Anjani; Kolekar, Sadhu K.; Gnanakumar, Edwin S.; Roy, Kanak; Vinod, C. P.; Gopinath, Chinnakonda S. (Catalysis, Structure & Reactivity, 2016)
An attempt has been made to bridge the material gap, existing between ideal single crystals and real-world powder nanocatalyst employed in surface science and heterogeneous catalysis, respectively. Simple wet chemical method (sol–gel and spin-coating deposition) has been applied to make continuous Ce1 − xZrxO2 (x = 0–1) (CZ) thin films with uniform thickness (~40 nm) and smooth surface characteristics. Uniform thickness and surface smoothness of the films over a large area was supported by a variety of measurements. Molecular beam (MB) studies of O2 adsorption on CZ surfaces reveals the oxygen storage capacity (OSC), and sticking coefficient increases from 400 to 800 K. Porous nature of Ce-rich CZ compositions enhances O2 adsorption and OSC, predominantly due to O-diffusion and redox nature, even at 400 K. A good correlation exists between MB measurements made on CZ films for oxygen adsorption, and OSC, and ambient pressure CO oxidation on powder form of CZ; this demonstrates the large potential to bridge the material gap. CZ was particularly chosen as a model system for the present studies, since it has been well-studied and a correlation between surface science properties made on thin films and catalysis on powder CZ materials could be a litmus test. Ambient catalysis on ceria-zirconia nanocatalyst correlates well with surface properties measured through molecular beam on thinfilm and close the material gap.

Potential dual role of eugenol in inhibiting advanced glycation end products in diabetes: proteomic and mechanistic insights - Singh, Priyanka; Jayaramaiah, Ramesha H.; Agawane, Sachin B.; Vannuruswamy, Garikapati; Korwar, Arvind M.; Anand, Atul; Dhaygude, Vitthal S.; Shaikh, Mahemud L.; Joshi, Rakesh S.; Boppana, Ramanamurthy; Kulkarni, Mahesh J.; Thulasiram, Hirekodathakallu V.; et al. (Scientific Reports, 2016)
Medicinally important genus Ocimum harbors a vast pool of chemically diverse metabolites. Current study aims at identifying anti-diabetic candidate compounds from Ocimum species. Major metabolites in O. kilimandscharicum, O. tenuiflorum, O. gratissimum were purified, characterized and evaluated for anti-glycation activity. In vitro inhibition of advanced glycation end products (AGEs) by eugenol was found to be highest. Preliminary biophysical analysis and blind docking studies to understand eugenol-albumin interaction indicated eugenol to possess strong binding affinity for surface exposed lysines. However, binding of eugenol to bovine serum albumin (BSA) did not result in significant change in secondary structure of protein. In vivo diabetic mice model studies with eugenol showed reduction in blood glucose levels by 38% likely due to inhibition of alpha-glucosidase while insulin and glycated hemoglobin levels remain unchanged. Western blotting using anti-AGE antibody and mass spectrometry detected notably fewer AGE modified peptides upon eugenol treatment both in vivo and in vitro. Histopathological examination revealed comparatively lesser lesions in eugenol-treated mice. Thus, we propose eugenol has dual mode of action in combating diabetes; it lowers blood glucose by inhibiting a-glucosidase and prevents AGE formation by binding to epsilon-amine group on lysine, protecting it from glycation, offering potential use in diabetic management.

Prediction of reactivity ratios in free radical copolymerization from monomer resonance-polarity (Q-e) parameters: genetic programming-based models - Shrinivas, K.; Kulkarni, Rahul P.; Shaikh, Saif; Ghorpade, Ravindra V.; Vyas, Renu; Tambe, Sanjeev S.; Ponrathnam, S.; Kulkarni, Bhaskar D. (International Journal of Chemical Reactor Engineering, 2016)
The principal deficiency of the widely utilized Alfrey-Price (AP) scheme for computing reactivity ratios in the widely used free radical copolymerization is that it ignores important factors, such as the steric effects. This often leads to inaccurate reactivity ratio predictions by AP model. Accordingly, in this study, exclusively data-driven, Q-e parameter-based new models have been developed for the reactivity ratio prediction in free radical copolymerization. In the model development, a novel artificial intelligence formalism known as ``genetic programming (GP)'' that performs symbolic regression has been employed. The GP-based models possess a different functional form than AP model. Further, parameters of GP-based models were fine-tuned using Levenberg-Marquardt (LM) nonlinear regression method. A comparison of AP, GP and GP-LM as well as artificial neural network (ANN)-based models indicates that GP and GP-LM models exhibit superior reactivity ratio prediction accuracy and generalization performance (with correlation coefficient magnitudes close to or greater than 0.9) when compared with AP and ANN models. The GPbased reactivity ratio prediction models developed here due to their higher accuracy and generalization capability have the potential of replacing the widely used AP models.
Keywords: Alfrey-Price scheme; free radical copolymerization; genetic programming; reactivity ratio; symbolic regression

Preparation and characterization of microcapsules containing industrially important reactive water-soluble polyamine - Shukla, Parshuram G.; Jagtap, Siddheshwar B.; Biradar, Satish C.; Charpe, Vaibhav P.; Jadhav, Arun S. (Colloid and Polymer Science, 2016)
Polyurea microcapsules containing water-soluble reactive polyamine, namely, polyaziridine (A33), were prepared by interfacial polymerization technique in non-aqueous medium, wherein (i) A33 was encapsulated for the first time as a neat amine without forming its salt or adduct and (ii) microcapsules formed were without any deleterious effect on A33. A systematic study was conducted by preparing microcapsules with different polyurea wall architectures. Fourier transform infrared (FTIR) and proton nuclear magnetic resonance (H-1 NMR) spectroscopic analysis of extracted A33 from microcapsules do not show any structural changes during microencapsulation. A titration method was developed to analyze the amount of encapsulated A33 quantitatively. Polyurea microcapsules obtained from reaction of ethylene diamine (E) and isophorone diisocyanate (I) monomers have shown better properties such as encapsulation efficiency and extent of agglomeration. Significant reduction in the size was observed when microcapsules of EI wall material were prepared by homogenizing the initial emulsion of A33 in paraffin oil. The process described in this paper for the preparation of microcapsules is cost-effective and industrially viable, which can find applications in agrochemicals, coatings, self-healing composites, etc.

Pretreatment and enzymatic process modification strategies to improve efficiency of sugar production from sugarcane bagasse - Pal, Siddhartha; Joy, Shereena; Trimukhe, Kalpana D.; Kumbhar, Pramod S.; Varma, Anjani J.; Padmanabhan, Sasisanker (3 Biotech, 2016)
Pretreatment and enzymatic hydrolysis play a critical role in the economic production of sugars and fuels from lignocellulosic biomass. In this study, we evaluated diverse pilot-scale pretreatments and different post-pretreatment strategies for the production of fermentable sugars from sugarcane bagasse. For the pretreatment of bagasse at pilot-scale level, steam explosion without catalyst and combination of sulfuric and oxalic acids at low and high loadings were used. Subsequently, to enhance the efficiency of enzymatic hydrolysis of the pretreated bagasse, three different post-pretreatment process schemes were investigated. In the first scheme (Scheme 1), enzymatic hydrolysis was conducted on the whole pretreated slurry, without treatments such as washing or solid-liquid separation. In the second scheme (Scheme 2), the pretreated slurry was first pressure filtered to yield a solid and liquid phase. Following filtration, the separated liquid phase was remixed with the solid wet cake to generate slurry, which was then subsequently used for enzymatic hydrolysis. In the third scheme (Scheme 3), the pretreated slurry was washed with more water and filtered to obtain a solid and liquid phase, in which only the former was subjected to enzymatic hydrolysis. A 10 % higher enzymatic conversion was obtained in Scheme 2 than Scheme 1, while Scheme 3 resulted in only a 5-7 % increase due to additional washing unit operation and solid-liquid separation. Dynamic light scattering experiments conducted on post-pretreated bagasse indicate decrease of particle size due to solid-liquid separation involving pressure filtration provided increased the yield of C6 sugars. It is anticipated that different process modification methods used in this study before the enzymatic hydrolysis step can make the overall cellulosic ethanol process effective and possibly cost effective.
Keywords: Dilute acid treatment; High-solid enzymatic hydrolysis; Pilot-scale pretreatment; Pressure filtration; Solid-liquid separation

Probing the ATP-induced conformational flexibility of the PcrA helicase protein using molecular dynamics simulation - Mhashal, Anil R.; Choudhury, Chandan Kumar; Roy, Sudip (Journal of Molecular Modeling, 2016)
Helicases are enzymes that unwind double-stranded DNA (dsDNA) into its single-stranded components. It is important to understand the binding and unbinding of ATP from the active sites of helicases, as this knowledge can be used to elucidate the functionality of helicases during the unwinding of dsDNA. In this work, we investigated the unbinding of ATP and its effect on the active-site residues of the helicase PcrA using molecular dynamic simulations. To mimic the unbinding process of ATP from the active site of the helicase, we simulated the application of an external force that pulls ATP from the active site and computed the free-energy change during this process. We estimated an energy cost of similar to 85 kJ/mol for the transformation of the helicase from the ATP-bound state (1QHH) to the ATP-free state (1PJR). Unbinding led to conformational changes in the residues of the protein at the active site. Some of the residues at the ATP-binding site were significantly reoriented when the ATP was pulled. We observed a clear competition between reorientation of the residues and energy stabilization by hydrogen bonds between the ATP and active-site residues. We also checked the flexibility of the PcrA protein using a principal component analysis of domain motion. We found that the ATP-free state of the helicase is more flexible than the ATP-bound state.
Keywords: ATP; DNA helicase; PcrA; Residue reorientation; Translocation; Umbrella sampling; Unwinding

Problem solving and environmentally benign approach toward diversity oriented synthesis of novel 2-amino-3-phenyl (or Alkyl) sulfonyl-4H-chromenes at ambient temperature - Pandit, Kapil S.; Kupwade, Ravindra V.; Chavan, Pramod V.; Desai, Uday V.; Wadgaonkar, Prakash P.; Kodam, Kisan M. (ACS Sustainable Chemistry & Engineering, 2016)
A problem solving, environmentally benign, and diversity oriented protocol has been described for multi component synthesis of medicinally privileged 2-amino-3-phenyl (or methyl) sulfonyl-4H-chromenes by one-pot, three component condensation among aldehydes, phenyl (or methyl) sulphonyl acetonitrile, and alpha-naphthol, 3-dimethylamino phenol, 4-hydroxy-N-methyl-quinoline-2-one as well as 4-hydroxycarbazole, using diethylamine as an efficient organo catalyst. The catalyst employed is commercially available, inexpensive, and nontoxic. Ambient reaction conditions, very high yields, wide scope, and avoidance of conventional isolation as well as chromatographic purification have improved the practical utility of this protocol manifold.
Keywords: 2-Amino-3-methylsulfonyl-4H-chromenes; 2-Amino-3-phenylsulfonyl-4H-chromenes; diethylamine; green chemistry; Multicomponent synthesis; organocatalyst

Processing of TGA data: analysis of isoconversional and model fitting methods - Jain, Ankit A.; Mehra, Anurag; Ranade, Vivek V. (Fuel, 2016)
Thermogravimetric analysis (TGA) is routinely used to characterize coal. Apart from proximate analysis, TGA data is also used to characterize kinetics of devolatilization and char combustion. Various methods have been proposed to process the TGA data [isoconversional or model free methods such as Friedman method, Kissinger method, Flynn-Wall-Ozawa method (FWO), Kissinger-Akahira-Sunose method (KAS) or single or multi-reaction models (SRMs/MRMs) and distributed activation energy models (DAEMs)]. In this work, we have critically examined various models for processing TGA data obtained with typical Indian coal. A generalized equation has been proposed to encompass different models as special cases. We have also considered a model based on a possibility of distribution of frequency factor along with constant or distribution of activation energies. The results of TGA data described by different models were critically analyzed. The presented results and methodology will be useful for selecting appropriate strategy for processing TGA data. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: DAEM; High ash coal; Isoconversional methods; Pyrolysis; TGA

Product distribution in hydrogenation of styrene oxide over Pd/chitosan catalyst - Viswanadhan, Maya; Potdar, Aparna; Divakaran, Anumon V.; Badiger, Manohar V.; Rode, Chandrashekhar (Research on Chemical Intermediates, 2016)
Palladium-decorated chitosan catalyst was synthesized by an impregnation method by varying the Pd loading in the range of 1-6 %, and was evaluated for the regioselective hydrogenation of styrene oxide. In order to correlate the chemical and textural properties with the catalytic activity, all the prepared catalysts were characterized by techniques such as Fourier transform infrared spectroscopy, X-ray diffraction, scanning electron microscopy, transmission electron spectroscopy, thermo-gravimetric analysis, temperature-programmed desorption of NH3, and CO2 and N-2 physisorption. The synthesized catalysts were utilized for the efficient and regioselective ring opening of styrene oxide by hydrogenation under different conditions. The complete conversion of styrene oxide with 65 % selectivity for 2-phenyl ethanol and 33 % for 1-phenyl ethanol were obtained using 4 % Pd/CS catalyst at 70 degrees C temperature and 3 MPa pressure. The mechanism for the regio selective ring opening of styrene oxide to 1- and 2-phenyl ethanol was also proposed on the basis of properties of the catalyst support, catalytic activity and selectivity. These results indicated that the catalytic activity and selectivity of the catalysts were affected by the nature of support. Further, the basic properties of the support play an important role in the selectivity of the styrene oxide hydrogenation reaction.

Production of bikaverin by a Fusarium fujikuroi mutant in submerged cultures - Lale, Geetanjali; Gadre, R. V. (AMB Express, 2016)
A variety of mutants having different colony characteristics, morphology and soluble pigmentation were generated from Fusarium fujikuroi by exposure to UV radiation. Mutants were selected that formed dry, compact, small colonies with reddish-violet pigment on regeneration agar plates. The production of bikaverin by Mut-4 was examined in shake flasks in media with different nitrogen and carbon sources. The optimal C: N ratio for the maximal bikaverin production by Mut-4 was 150: 1. It produced still higher bikaverin (6.3 g l(-1)) in a medium containing defatted cottonseed meal as nitrogen source, in combination with glucose. Bikaverin produced was extracted, purified and characterized by UV-visible and NMR spectroscopy. Bikaverin production in the present investigation was substantially higher than that reported by earlier investigators in submerged and solid-state fermentations.
Keywords: Bikaverin; Fusarium fujikuroi; Gibberella fujikuroi; Pigment production; Submerged cultures

Proline catalyzed enantioselective synthesis of (2S,3S)-3-hydroxypipecolic acid and formal synthesis of (+)-swainsonine - Aher, Ravindra D.; Sudalai, Arumugam (Tetrahedron Letters, 2016)
A short enantioselective synthesis of (2S,3S)-3-hydroxypipecolic acid (overall yield: 18.8%; 96% ee) and formal synthesis of (+)-swainsonine (overall yield: 13.6%; 96% ee) have been described starting from commercially available acrolein. The synthetic strategy involves a high enantioselective L-proline catalyzed sequential c-amination and diastereoselective (dr > 99:1) Barbier allylation of aldehyde in one-pot as the key reaction. (C) 2016 Elsevier Ltd. All rights reserved.

Promising field electron emission performance of vertically aligned one dimensional (1D) brookite (beta) TiO2 nanorods - Devan, Rupesh S.; Ma, Yuan-Ron; More, Mahendra A.; Khare, Ruchita T.; Antad, Vivek V.; Patil, Ranjit A.; Thakare, Vishal P.; Dhayal, Rajendra S.; Schmidt-Mende, Lukas (RSC Advances, 2016)
We evidence field-electron emission (FE) studies on the large-area array of one-dimensional (1D) brookite (beta) TiO2 nanorods. The pure 1D beta-TiO2 nanorods of 10 nm width and 760 nm long were synthesized on Si substrate utilizing hot-filament metal vapor deposition technique. X-ray diffraction (XRD) and transmission electron microscopy (TEM) analysis evidenced the beta-TiO2 nanorods to be composed of orthorhombic crystals in brookite (beta) phase. X-ray photoemission spectroscopy (XPS) revealed the formation of pure stoichiometric (i.e. 1 : 1.98) 1D TiO2 nanorods. The values of turn-on field, required to draw current density of 10 mA cm(-2), was observed 3.9 V mu m(-1) for pristine 1D beta-TiO2 nanorods emitters, which were found significantly lower than doped/undoped 1D TiO2 nanostructures (i.e. nanotubes, nanowires, nanorods) based field emitters. The enhanced FE behavior of the TiO2/Si emitter can be attributed to modulation of electronic properties due to the high aspect ratio of vertically aligned TiO2 nanorods. Furthermore, the orthodox emission situation of pristine TiO2/Si emitters exhibit good emission stability and reveal their potentials as promising FE material.

Promotional effect of Fe on the performance of supported Cu catalyst for ambient pressure hydrogenation of furfural - Manikandan, Marimuthu; Venugopal, Ashok Kumar; Nagpure, Atul S.; Chilukuri, Satyanarayana V.; Raja, Thirumalaiswamy (RSC Advances, 2016)
A noble-metal free FeCu based bimetallic catalyst system prepared by facile co-impregnation method was found to be highly admirable for vapour phase selective hydrogenation of furfural to furfuryl alcohol at ambient pressure. Monometallic Cu/gamma-Al2O3, Fe/gamma-Al2O3 and bimetallic FeCu/gamma-Al2O3 catalysts with different Fe loadings were prepared. Structural and morphological features of the catalysts were thoroughly investigated by several physico-chemical characterization techniques. The influence of various reaction parameters, such as Fe loading, reaction temperature and flow of reactants was examined with respect to furfural conversion and furfuryl alcohol yield. The results clearly showed that an optimum amount of Fe is necessary to enhance the catalytic activity of monometallic Cu/gamma-Al2O3 for the selective hydrogenation of furfural. The catalyst FC-10 with 10 wt% Fe exhibited excellent activity which led to high furfural conversion (>93%) and furfuryl alcohol selectivity (>98%) under mild reaction conditions. The higher activity of bimetallic FeCu/gamma-Al2O3 compared to monometallic Cu/gamma-Al2O3 is ascribed to the formation of FeCu bimetallic particles and the existence of oxygen vacancies in the Fe oxide system. The superior activity after Fe loading on the Cu-based catalyst was attributed to the synergy between Cu and Fe. A plausible mechanism is proposed to explain the promoting effect of Fe, which involves synergism between Fe sites with strong oxophilic nature and Cu sites with a high ability for hydrogen activation. Based on the activity results, prolonged catalytic activity and spent catalyst analysis, the developed FeCu/gamma-Al2O3 catalyst is inexpensive, eco-benign and robust, which makes it a promising candidate for the efficient conversion of biomass-derived substrates to fine chemicals and drop-in biofuels.

Protein-dependent membrane interaction of a partially disordered protein complex with oleic acid : Implications for cancer lipidomics - Chaudhuri, Arunima; Prasanna, Xavier; Agiru, Priyanka; Chakraborty, Hirak; Rydstrom, Anna; Ho, James C. S.; Svanborg, Catharina; Sengupta, Durba; Chattopadhyay, Amitabha (Scientific Reports, 2016)
Bovine α-lactalbumin (BLA) forms cytotoxic complexes with oleic acid (OA) that perturbs tumor cell membranes, but molecular determinants of these membrane-interactions remain poorly understood. Here, we aim to obtain molecular insights into the interaction of BLA/BLA-OA complex with model membranes. We characterized the folding state of BLA-OA complex using tryptophan fluorescence and resolved residue-specific interactions of BLA with OA using molecular dynamics simulation. We integrated membrane-binding data using a voltage-sensitive probe and molecular dynamics (MD) to demonstrate the preferential interaction of the BLA-OA complex with negatively charged membranes. We identified amino acid residues of BLA and BLA-OA complex as determinants of these membrane interactions using MD, functionally corroborated by uptake of the corresponding α-LA peptides across tumor cell membranes. The results suggest that the α-LA component of these cytotoxic complexes confers specificity for tumor cell membranes through protein interactions that are maintained even in the lipid complex, in the presence of OA.

Proteomic insight reveals elevated levels of albumin in circulating immunecomplexes in diabetic plasma - Bhat, Shweta; Jagadeeshaprasad, Mashanipalya G.; Patil, Yugendra R.; Shaikh, Mahemud L.; Regin, Bhaskaran S.; Mohan, Viswanathan; Giri, Ashok P.; Balasubramanyam, Muthuswamy; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Molecular & Cellular Proteomics, 2016)
A Hyperglycemic condition in diabetes promotes formation of advanced glycation end products, which are known to elicit immune response and form complexes with immunoglobulins called circulating immune complexes. To investigate the involvement of advanced glycation end product (AGE)-modified proteins in the elicitation of an immune response, circulating immune complexes were isolated and proteins associated were identified and characterized. Label-free-based mass spectrometric analysis of circulating immune complexes in clinical plasma of prediabetic, newly diagnosed diabetes, and diabetic microalbuminurea revealed elevated levels of serum albumin in the circulating immune complexes, which were also observed to be AGE modified. Further, to examine the role of glycation, circulating immune complexeswere analyzed in the streptozotocin-induced diabetic mice treated with or without aminoguanidine, a prototype glycation inhibitor. Mass spectrometric analysis of circulating immune complexes showed elevated levels of serum albumin in plasma from diabetic mice over that of control animals. Aminoguanidine-treated diabetic mice displayed decreased AGE modification of plasma albumin, accompanied by a reduced level of albumin in the circulating immune complexes. In addition, elevated levels of proinflammatory cytokines such as IL-1b, IL-2, and TNF-alpha were observed in diabetes, which were reduced with aminoguanidine treatment, suggesting the involvement of glycation in the immune response.

Proton play in the formation of low molecular weight chitosan (LWCS) by hydrolyzing chitosan with a carbon based solid acid - Krishnan, R. Akhil; Deshmukh, Pranjal; Agarwal, Siddharth; Purohit, Poorvi; Dhoble, Deepa Arun; Waske, Prashant; Khandekar, Dileep; Jain, Ratnesh; Dandekar, Prajakta (Carbohydrate Polymers, 2016)
Low molecular weight chitosan (LWCS) constitute a special class of value added chemicals that are primarily obtained from crustacean shells, which are the main water pollutants from crabs and shrimp processing centers. Unlike chitin and chitosan, LWCS possess improved solubility in water and aqueous solutions, making them widely applicable in numerous fields ranging from drug delivery to waste water treatment. Among the methods employed for their production, chemical breakdown by strong liquid acids has yielded good success. However, this method is met with severe concerns arising from the harsh nature of liquid acids, which may corrode the reactors for commercial synthesis, and their limited reusability. The physical methods like ultrasound and microwave are energy intensive in nature, while the enzymatic methods are expensive and offers limited scope for reuse. We have attempted to overcome these problems by employing carbon based solid acid (CSA) for hydrolyzing chitosan to LWCS. CSA can be easily produced using activated carbon, a cost-effective and easily available raw material. Reactions were carried out between chitosan and CSA in a hydrothermal glass reactor and the products, separated by cold centrifugation, were purified and dried. The dried products were characterized for their molecular weight and solubility. Results indicated more than ten-fold decrease in the molecular weight of chitosan and the product exhibited water solubility. The CSA could be used upto four times, without regeneration, to give a consistent quality product. The aqueous solution of resulting LWCS exhibited a pH of 6.03 +/- 0.11, as against the acidic pH range of solutions of commercially available LWCS, indicating its suitability for biomedical applications. Our investigation facilitates a `green approach' that may be employed for commercial production of value added chemicals from waste products of marine industry. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Carbon based solid acid; Chitosan; green synthesis; Hydrolysis; Low molecular weight chitosan

Proton-coupled electron transfer in a hydrogen-bonded charge transfer complex - Verma, Sandeep; Aute, Sunil; Das, Amitava; Ghosh, Hirendra N. (Journal of Physical Chemistry B, 2016)
A proton-coupled electron transfer (PCET) reaction in a hydrogen bonded charge-transfer (CT) complex of 4-([2,2'-bipyridin]-4-yl)phenol (bpy-phenol) with a F- ion has been investigated by ultrafast time-resolved transient absorption spectroscopy. The phenolic receptor molecule, bpy-phenol, binds to the F- ion through a hydrogen bond and senses the F- ion-via the Stokes-shifted CT band. Upon photoexcitation, CT from the phenol residue to the bpy residue promotes proton transfer from the phenol radical cation (ArOH center dot+) to the fluoride ion at ultrafast time scales of <150 fs (instrument response function limited) and 3 ps, separately. The fast and slow proton-transfer times are linked to two different types of hydrogen-bonding networks between the phenol residue and fluoride ion. Crystalline water in the fluoride salt hydrates mediates the proton-transfer reaction. This work demonstrates the participation of a hydrogen-bonded water bridge within a PCET reaction in a water restricted environment.

Pt- and TCO-free flexible cathode for DSSC from highly conducting and flexible PEDOT paper prepared via in situ interfacial polymerization - Anothumakkool, Bihag; Agrawal, Ishita; Bhange, Siddheshwar N.; Soni, Roby; Game, Onkar S.; Ogale, Satishchandra B.; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2016)
Here, we report the preparation of a flexible, free-standing, Pt- and TCO-free counter electrode in dye-sensitized solar cell (DSSC)-derived from polyethylenedioxythiophene (PEDOT)-impregnated cellulose paper. The synthetic strategy of making the thin flexible PEDOT paper is simple and scalable, which can be achieved via in situ polymerization all through a roll coating technique. The very low sheet resistance (4 Omega/square) obtained from a film of 40 mu m thick PEDOT paper (PEDOT-p-5) is found to be superior to the conventional fluorine-doped tin oxide (FTO) substrate. The high conductivity (357 S/cm) displayed by PEDOT-p-5 is observed to be stable under ambient conditions as well as flexible and bending conditions. With all of these features in place, we could develop an efficient Pt- and TCO-free flexible counter electrode from PEDOT-p-5 for DSSC applications. The catalytic activity toward the tri-iodide reduction of the flexible electrode is analyzed by adopting various electrochemical methodologies. PEDOT-p-5 is found to display higher exchange current density (7.12 mA/cm(2)) and low charge transfer resistance (4.6 Omega) compared to the benchmark Pt-coated FTO glass (2.40 mA/cm(2) and 9.4 Omega, respectively). Further, a DSSC fabricated using PEDOT-p-5 as the counter electrode displays a comparable efficiency of 6.1% relative to 6.9% delivered by a system based on Pt/FTO as the counter electrode.
Keywords: counter electrode; dye-sensitized solar cell; flexible and thin devices; impedance analysis; interfacial polymerization; polyethylenedioxythiophene

Pulsed laser-deposited nanocrystalline GdB6 thin films on W and Re as field emitters - Suryawanshi, Sachin R.; Singh, Anil K.; Phase, Deodatta M.; Late, Dattatray J.; Sinha, Sucharita; More, Mahendra A. (Applied Physics A-Materials Science & Processing, 2016)
Gadolinium hexaboride (GdB6) nanocrystalline thin films were grown on tungsten (W), rhenium (Re) tips and foil substrates using optimized pulsed laser deposition (PLD) technique. The X-ray diffraction analysis reveals formation of pure, crystalline cubic phase of GdB6 on W and Re substrates, under the prevailing PLD conditions. The field emission (FE) studies of GdB6/W and GdB6/Re emitters were performed in a planar diode configuration at the base pressure similar to 10(-8) mbar. The GdB6/W and GdB6/Re tip emitters deliver high emission current densities of similar to 1.4 and 0.811 mA/cm(2) at an applied field of similar to 6.0 and 7.0 V/mu m, respectively. The Fowler-Nordheim (F-N) plots were found to be nearly linear showing metallic nature of the emitters. The noticeably high values of field enhancement factor (beta) estimated using the slopes of the F-N plots indicate that the PLD GdB6 coating on Wand Re substrates comprises of high-aspect-ratio nanostructures. Interestingly, the GdB6/W and GdB6/Re planar emitters exhibit excellent current stability at the preset values over a long-term operation, as compared to the tip emitters. Furthermore, the values of workfunction of the GdB6/W and GdB6/Re emitters, experimentally measured using ultraviolet photoelectron spectroscopy, are found to be same, similar to 1.6 +/- 0.1 eV. Despite possessing same workfunction value, the FE characteristics of the GdB6/W emitter are markedly different from that of GdB6/Re emitter, which can be attributed to the growth of GdB6 films on W and Re substrates.

Purification and characterization of an extracellular beta-xylosidase from Pseudozyma hubeiensis NCIM 3574 (PhXyl), an unexplored yeast - Mhetras, Nutan; Liddell, Susan; Gokhale, Digambar (AMB Express, 2016)
This paper reports on the production of beta-xylosidase from an unexplored yeast, Pseudozyma hubeinsis. The expression of this enzyme could be induced by beech wood xylan when the yeast was grown at 27 degrees C. The enzyme was purified to homogeneity as a glycoprotein with 23 % glycosylation. The purification protocol involved ammonium sulphate precipitation, QAE-Sephadex A50 ion exchange chromatography and sephacryl-200 column chromatography which resulted in 8.3-fold purification with 53.12 % final recovery. The purified enzyme showed prominent single band on SDS-PAGE. It is a monomeric protein of 110 kDa molecular weight confirmed by SDS-PAGE followed by MALDI-TOF mass spectrometry (112.3 kDa). The enzyme was optimally active at 60 degrees C and pH 4.5 and stable at pH range (4-9) and at 50 degrees C for 4 h. Chemical modification studies revealed that active site of the purified enzyme comprised of carboxyl, tyrosine and tryptophan residues. The carboxyl residue is involved in catalysis and tryptophan residue is solely involved in substrate binding. The best match from the search of the NCBInr database was with gi vertical bar 808364558 glycoside hydrolase of Pseudozyma hubeiensis SY62 with 26 % sequence coverage confirming that it is a glycoside hydrolase/beta-glucosidase. From the search of customized SWISSPROT database, it was revealed that SWISSPROT does not contain any entries that are similar to the purified enzyme.

Purification and partial characterization of novel penicillin V acylase from Acinetobacter sp AP24 isolated from loktak lake, an indo-burma biodiversity hotspot - Philem, Pushparani Devi; Sonalkar, Vidya V.; Dharne, Mahesh S.; Prabhune, Asmita (Preparative Biochemistry & Biotechnology, 2016)
Members of the bacterial genus Acinetobacter have attracted great attention over the past few decades, on account of their various biotechnological applications and clinical implications. In this study, we are reporting the first experimental penicillin V acylase (PVA) activity from this genus. Penicillin acylases are pharmaceutically important enzymes widely used in the synthesis of semisynthetic beta-lactam antibiotics. The bacterium, identified as Acinetobacter sp. AP24, was isolated from the water of Loktak Lake (Manipur, India), an Indo-Burma biodiversity hotspot. PVA production was increased threefold in an optimized medium with 0.2% sodium glutamate and 1% glucose as nitrogen and carbon sources respectively, after 24hr of fermentation at 28 degrees C and pH 7.0 with shaking at 180rpm. The enzyme was purified to homogeneity by cation-exchange chromatography using SP-sepharose resin. The PVA is a homotetramer with subunit molecular mass of 34 kD. The enzyme was highly specific toward penicillin V with optimal hydrolytic activity at 40 degrees C and pH 7.5. The enzyme was stable from pH 5.0 to 9.0 at 25 degrees C for 2hr. The enzyme retained 75% activity after 1hr of incubation at 40 degrees C at pH 7.5.
Keywords: 6-APA; Acinetobacter; Loktak Lake; Penicillin V acylase

PVAc/PEDOT:PSS/graphene-iron oxide nanocomposite (GINC): an efficient thermoelectric material - Dey, Abhijit; Maity, Arunava; Khan, Md Abdul Shafeeuulla; Sikder, Arun Kanti; Chattopadhyay, Santanu (RSC Advances, 2016)
A green method for the synthesis of a graphene-iron oxide nanocomposite (GINC) and its PVAc based polymer nanocomposites was reported in an earlier communication. The fabricated PVAc-GINC film exhibited a conductivity of 2.18 x 104 S m(-1) with a Seebeck coefficient of 38.8 mu V K-1. Hence, the power factor (PF) reached a value of 32.90 mu W m(-1) K-2 which is 27 fold higher than a thermoelectric material based on a PVAc-graphene composite as reported in the contemporary literature. In continuation of the above mentioned study, PEDOT:PSS was used to further enhance the power factor (PT) and figure of merit (ZT) of the system. During evaluation, a PEDOT: PSS/GINC composite (5 : 95) showed a remarkable increase in various thermoelectric properties like electrical conductivity (8.0 x 10(4) S m(-1)) with a Seebeck coefficient of 25.42 mu V K-1 and thermal conductivity 0.90 m(-1) K-1. Hence PF and ZT reach up to 51.93 mW m(-1) K-2 and 0.017, respectively. To improve the mechanical strength of the polymer composite, cellulose fibre was also employed. By the addition of cellulose fibre, though the mechanical strength of the composite increases the PF reaches 5.6, which is 10 times lower than the PEDOT:PSS/GINC composite.

Pyramiding PvPGIP2 and TAXI-III but not PvPGIP2 and PMEI enhances resistance against fusarium graminearum - Tundo, Silvio; Kalunke, Raviraj; Janni, Michela; Volpi, Chiara; Lionetti, Vincenzo; Bellincampi, Daniela; Favaron, Francesco; D'Ovidio, Renato (Molecular Plant-Microbe Interactions, 2016)
Plant protein inhibitors counteract the activity of cell wall degrading enzymes (CWDEs) secreted by pathogens to breach the plant cell-wall barrier. Transgenic plants expressing a single protein inhibitor restrict pathogen infections. However, since pathogens secrete a number of CWDEs at the onset of infection, we combined more inhibitors in a single wheat genotype to reinforce further the cell-wall barrier. We combined polygalacturonase (PG) inhibiting protein (PGIP) and pectin methyl esterase inhibitor (PMEI), both controlling the activity of PG, one of the first CWDEs secreted during infection. We also pyramided PGIP and TAXI-M, a xylanase inhibitor that controls the activity of xylanases, key factors for the degradation of xylan, a main component of cereal cell wall. We demonstrated that the pyramiding of PGIP and PMEI did not contribute to any further improvement of disease resistance. However, the presence of both pectinase inhibitors ensured a broader spectrum of disease resistance. Conversely, the PGIP and TAXI-HI combination contributed to further improvement of Fusarium head blight (FHB) resistance, probably because these inhibitors target the activity of different types of CWDEs, i.e., PGs and xylanases. Worth mentioning, the reduction of FHB symptoms is accompanied by a reduction of deoxynivalenol accumulation with a foreseen great benefit to human and animal health.

Palladacycles for directed and nondirected C H bond functionalization of (Hetero)arenes - Soni, Vineeta; Punji, Benudhar (Strategies for palladium-catalyzed non-directed and directed C-H bond functionalization, 2017)
Application of palladacycle complexes in catalytic organic transformation is rapidly expanding. This chapter is mainly focused on the use of palladacycle precatalysts in CH bond functionalizations, as well as an overview of palladacycle intermediates in directed CH bond functionalization reactions. The described palladacycle precatalysts are more efficient and more selective than the traditional palladium complexes for CH bond functionalization processes. The second part of the chapter summarizes the involvement of palladacycle intermediates in various directed CH bond functionalizations that are proposed with experimental evidence. Some of the palladacycle intermediates described are shown to be competent as catalyst precursors. It has been demonstrated that the formation of palladacycle (precatalyst or intermediate) makes the CH functionalization process more facile, because of the high stability associated with palladacycles.

Palladium incorporated on carbonaceous catalyst for Suzuki coupling reaction in water - Rathod, P. V.; Jadhav, V.H. (Tetrahedron Letters, 2017)
A new palladium incorporated carbonaceous catalyst Pd@CC SO3H -NH2 was synthesized by introducing palladium on glucose derived carbocatalyst. The catalyst was well characterized and was used for the Suzuki coupling of phenyl boronic acid with different aryl halides under aqueous conditions. This green methodology represents a ligand free, cost-effective and operationally convenient method for the synthesis of a variety of biaryl's under the conditions that are tolerant for a broad range of functional groups with good to excellent yields. Moreover, the catalyst could be easily recycled and reused at least five times without any significant loss of its catalytic activity.

Palladium supported ionic liquid phase catalyst (Pd@SILP-PS) for room temperature Suzuki-Miyaura cross-coupling reaction - More, S.; Jadhav, S; Salunkhe, R.; Kumbhar, A. (Molecular Catalysis, 2017)
A new Pd-SILP based on amino functionalized imidazolium ionic liquid immobilized on Merrifield resin (Pd@SILP-PS) has been synthesized. The catalyst was characterized by different techniques like FT-IR, SEM-EDS, TEM, TGA-DTA and XPS. The catalyst has shown to be highly active in Suzuki-Miyaura cross-coupling reaction of various aryl halides and aryl boronic acids in ethanol at room temperature. The activity of catalyst and the nature of product were highly dependent on the type of the solvent used, as well as the substituents present on the aryl halides. The protic polar solvent ethanol gave desired cross-coupling product in good to excellent yields at room temperature. However the aprotic polar solvent THF gave homocoupling product. The catalyst showed at least five times recyclability without a decrease in product yield.
Keywords: Immobilization; Ionic liquid; Palladium; SILP; Suzuki-Miyaura reaction

Palladium supported on fluorinated magnesium hydroxide: an efficient catalyst for hydrogenation under ambient conditions - Kokane, Reshma S.; Acham, Vaibhav R.; Kulal, Atul B.; Kemnitz, Erhard; Dongare, Mohan K.; Umbarkar, Shubhangi B. (Chemistryselect, 2017)
In this study palladium supported on fluorinated magnesium hydroxide (Pd-MgF2-x(OH)(x)) was synthesized by fluorination of magnesium hydroxide using aqueous HF as fluorinating agent. The Mg(OH)(2) dissolves in HF and precipitates as magnesium hydroxide fluoride. The Pd precursor was added in the same pot during precipitation of MgF2-x(OH)(x). The final catalyst after drying at 250 degrees C has shown very high efficiency for hydrogenation of styrene and range of nitro aromatics at room temperature and atmospheric pressure. Hydrogenation of styrene has led to 37% conversion with 100% selectivity for hydrogenation of double bond after 3 h. The catalyst was successfully recycled for styrene hydrogenation without appreciable loss in the activity. Further hydrogenation of nitro-aromatics was achieved with 99% conversion and 100% aniline selectivity at room temperature and atmospheric pressure. The turnover number of similar to 21774 was obtained for nitrobenzene hydrogenation. The catalyst has shown mesoporous nature (pore volume 0.25 cc/g, pore diameter 4.8 nm) with very high surface area of 106 m(2)/g. The palladium particle size was found to be in the range of 10-11 nm. Acidity measurements by FTIR of adsorbed pyridine revealed presence of Lewis acidic sites with moderate acidity. Mechanistic studies using in-situ FTIR analysis for nitrobenzene hydrogenation revealed activation of nitrobenzene on the Lewis acid sites of the support whereas activation of hydrogen by heterolytic cleavage on Pd center.

Panchromatic sensitizer for dye-sensitized solar cells: un-symmetrical squaraine dyes incorporating benzodithiophene π-spacer with alkyl chains to extend conjugation, control the dye assembly on TiO2 and retard charge recombination - Bisht, Rajesh; Munavvar, Fairoos Mk; Singh, Ambarish Kumar; Nithyanandhan, Jayaraj (Journal of Organic Chemistry, 2017)
Metal-free near-infrared (NIR) active unsymmetrical squaraine dyes, RSQ1 and RSQ2, with benzodithiophene (BDT) π-spacer and cyanoacrylic acid acceptor were synthesized by utilizing palladium catalyzed direct (hetero)arylation reaction. Methyl and 2-ethylhexyl groups were strategically placed at the BDT unit for RSQ1 and RSQ2 respectively, to investigate the effect of alkylated π-spacer on dye aggregation on the TiO2 surface and recombination reactions at TiO2/dye/electrolyte interface. These dyes have strong absorption ( ε>10(5) M(-1)cm(-1)) in near-infra red (NIR) region and exhibit similar optical and electrochemical properties as they have same conjugated framework. RSQ2 performed better than RSQ1 owing to its higher open-circuit voltage (Voc) and fill factor (ff) in spite of having comparable short-circuit current density (Jsc). The panchromatic incident photon-to-current conversion efficiency (IPCE) response was also observed for both the dyes. RSQ2 showed power conversion efficiency (PCE) of 6.72% with short-circuit current density (Jsc) of 18.53 mA/cm(2), open circuit voltage (Voc) of 0.538 V, and fill factor (ff) of 67.4%, without any co-adsorbent. Attenuation of the charge recombination for RSQ2 was revealed by electrochemical impedance analysis (EIS) and open-circuit potential decay transients (OCVD), which attributes to its higher Voc and ff in comparison to RSQ1.

Partially bio-based poly(amide imide)s by polycondensation of aromatic diacylhydrazides based on lignin-derived phenolic acids and aromatic dianhydrides: synthesis, characterization, and computational studies - Kuhire, Sachin S.; Sharma, Pragati; Chakrabarty, Suman; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2017)
Two new bio-based diacylhydrazide monomers, namely, 4,4-(propane-1,3-diylbis(oxy))bis(3-methoxybenzohydrazide) and 4,4-(propane-1,3-diylbis(oxy))bis(3,5-dimethoxybenzohydrazide) were synthesized starting from lignin-derived phenolic acids, namely, vanillic acid and syringic acid. A series of poly(amide imide)s was synthesized by polycondensation of these diacylhydrazide monomers with commercially available aromatic dianhydrides. Poly(amide imide)s showed inherent viscosity in the range 0.44-0.56 dLg(-1) and exhibited good solubility in organic solvents. Poly(amide imide)s could be cast into transparent, flexible, and tough films from their N,N-dimethylacetamide solutions. Poly(amide imide)s showed 10% weight loss in the temperature range 340-364 degrees C indicating their good thermal stability. Glass transition temperature (T-g) of poly(amide imides)s were measured by DSC and DMA which were in the range 201-223 degrees C and 214-248 degrees C, respectively. The T-g values of poly(amide imide)s were dependent on the number methoxy substituents on aromatic rings of diacylhydrazide monomers. Molecular dynamics simulation studies revealed that chain rigidity is the dominant factor for observed trends in T-g. (c) 2017 Wiley Periodicals, Inc.
Keywords: Biobased Polymers; Computational studies; Glass-transaction temperature; lignin; Monomers; Plant oils; Polyimide; Reneable resources; Renewable resources; Step-growth polymers; structure-property relations; Sustanaible Polymers; Thermal night; Thermosetting resins; Vanillin

Partially bio-based processable polyimides based on aromatic diamine derived from cardanol - Shingte, Rahul D.; Tawade, Bhausaheb V.; Wadgaonkar, Prakash P. (green Materials, 2017)
A partially bio-based aromatic diamine, namely, 1,1-bis(4-aminophenyl)-3-pentadecylcyclohexane (BAC15) was synthesized starting from cardanol. A series of polyimides were synthesized by one-step high-temperature solution polycondensation of BAC15 with aromatic dianhydrides. Copolyimides were also synthesised by polycondensation of various compositions of BAC15 and 4,4’-oxydianiline with 3,3’,4,4’-biphenyl tetracarboxylic dianhydride. Inherent viscosities and number average molecular weights of (co)polyimides were in the range 0.33-1.4 dL/g and 14700-31900 g/mol, respectively, indicating formation of reasonably high molecular weight polymers. Polyimides were soluble in common organic solvents such as chloroform, dichloromethane and tetrahydrofuran and could be cast into transparent, flexible and tough films from their solutions in chloroform. (Co)polyimides exhibited Tg in the range 161–254 °C. The lowering of Tg could be attributed to the presence of flexible pentadecyl chains which act as “packing disruptive” groups. The temperature at 10% weight loss (T10) of (co)polyimides was in the range 490–515 °C demonstrating their good thermal stability. The virtue of solubility and large gap between Tg and T10 offers (co)polyimides opportunities of both solution as well as melt processability. Copolyimides containing pendent pentadecyl chains exhibited pretilt angle in the range 2.51-2.75° indicating their potential application as alignment layer in liquid crystal display devices.

PbS nanostar-like structures as field emitters - Pawar, Mahendra S.; Bankar, Prashant K.; More, Mahendra A.; Late, Dattatray J. (Chemistryselect, 2017)
The crystalline PbS nanostars were synthesized by thermal decomposition of thioacetamide (TAA) in aqueous solutions of lead acetate and acetic acid at 80 8 degrees C. The structure and morphology of the PbS nanostars have been characterized using X-Ray Diffraction (XRD), Raman Spectroscopy, Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM). The optical properties of the PbS nanostars have been studied using UV-Visible absorption Spectroscopy (UVVis). The field emission investigations have been carried out on the as synthesized PbS nanostars at the base pressure of similar to 13 10(-8) mbar. The turn on field required to draw an emission current density of 1 mu A/cm(2) is found to be 1.8 V/mm. The emission current-time plots show good emission current stability of the PbS nanostar emitter over a period of 4 hrs. The results in terms of low turn-on field and long term emission current stability of the PbS nanostars emitter reveals that it can be used in field emission based vacuum microelectronics / nanoelectronic devices.

Pd-catalyzed regioselective mono-arylation: quinazolinone as the inherent directing group for C(sp(2))-H activation - Garad, Dnyaneshwar N.; Viveki, Amol B.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2017)
The Pd-catalyzed quinazolinone-directed regioselective monoarylation of aromatic rings by C-H bond activation is developed. A broad substrate scope is demonstrated for both quinazolinone as well as diary-liodonium triflates. The use of a base was found to be crucial for this transformation, unlike for the known nitrogen-directed arylations. All of the novel quinazolinones of biological interest were synthesized by using the operationally simple Pd(II)-catalyzed arylation reaction.
Keywords: Aromatic rings; catalysis; Chemical activation; Chemical reactions; Palladium compounds; Regioselectivity

PD@SBA-15 Nanocomposite catalyst: synthesis and efficient solvent-free semihydrogenation of phenylacetylene under mild conditions - Bhuyan, Diganta; Selvaraj, Kaliaperumal; Saikia, Lakshi (Microporous and Mesoporous Materials, 2017)
Pd-0 nanoparticles (NPs) have been fabricated on SBA-15 using a facile, rapid and highly reproducible microwave-assisted reduction by solvent method. The as-synthesized Pd@SBA-15 nanocomposite was well characterized using low angle and wide angle XRD, TEM, FE-SEM, N-2 adsorption-desorption isotherm, FTIR, XPS etc. The Pd@SBA-15 nanocomposite act as an active, recyclable heterogeneous catalyst for semihydrogenation of phenylacetylene under solvent-free mild reaction conditions (303 K, atmospheric H-2). A maximum of 94.4% phenylacetylene conversion was achieved with very high selectivity for styrene (95.5%). Moreover, the used catalyst was recovered by centrifugation and reused up to four times without significant loss in their catalytic activity. This optimized reaction protocol for phenylacetylene was also well performed in case of various other alkynes with similar or better performance. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Pd-0 nanoparticles; Phenylacetylene; SBA-15; Semihydrogenation; Solvent-free

Penicillin V acylases from gram-negative bacteria degrade N-acylhomoserine lactones and attenuate virulence in Pseudomonas aeruginosa - Sunder, Avinash Vellore; Utari, Putri Dwi; Ramasamy, Sureshkumar; van Merkerk, Ronald; Quax, Wim; Pundle, Archana (Applied Microbiology and Biotechnology, 2017)
Virulence pathways in gram-negative pathogenic bacteria are regulated by quorum sensing mechanisms, through the production and sensing of N-acylhomoserine lactone (AHL) signal molecules. Enzymatic degradation of AHLs leading to attenuation of virulence (quorum quenching) could pave the way for the development of new antibacterials. Penicillin V acylases (PVAs) belong to the Ntn hydrolase superfamily, together with AHL acylases. PVAs are exploited widely in the pharmaceutical industry, but their role in the natural physiology of their native microbes is not clearly understood. This report details the characterization of AHL degradation activity by homotetrameric PVAs from two gram-negative plant pathogenic bacteria, Pectobacterium atrosepticum (PaPVA) and Agrobacterium tumefaciens (AtPVA). Both the PVAs exhibited substrate specificity for degrading long-chain AHLs. Exogenous addition of these enzymes into Pseudomonas aeruginosa greatly diminished the production of elastase and pyocyanin and biofilm formation and increased the survival rate in an insect model of acute infection. Subtle structural differences in the PVA active site that regulate specificity for acyl chain length have been characterized, which could reflect the evolution of AHL-degrading acylases in relation to the environment of the bacteria that produce them and also provide strategies for enzyme engineering. The potential for using these enzymes as therapeutic agents in clinical applications and a few ideas about their possible significance in microbial physiology have also been discussed.
Keywords: N-acylhomoserine lactone acylase; Ntn hydrolase; pathogenesis; Penicillin Vacylase; Quorum quenching

Performance of colloidal CdS sensitized solar cells with ZnO nanorods/nanoparticles - Roy, Anurag; Das, Partha Pratim; Tathavadekar, Mukta; Das, Sumita; Devi, Parukuttyamma Sujatha (Beilstein Journal of Nanotechnology, 2017)
As an alternative photosensitizer in dye-sensitized solar cells, bovine serum albumin (BSA) (a nonhazardous protein) was used in the synthesis of colloidal CdS nanoparticles (NPs). This system has been employed to replace the commonly used N719 dye molecule. Various nanostructured forms of ZnO, namely, nanorod and nanoparticle-based photoanodes, have been sensitized with colloidal CdS NPs to evaluate their effective performance towards quantum dot sensitized solar cells (QDSSCs). A polysulphide (S-x(2-))-based electrolyte and CuxS counter electrode were used for cell fabrication and testing. An interesting improvement in the performance of the device by imposing nanorods as a scattering layer on a particle layer has been observed. As a consequence, a maximum conversion efficiency of 1.06% with an open-circuit voltage (V-OC) of 0.67 V was achieved for the ZnO nanorod/nanoparticle assembled structure. The introduction of ZnO nanorods over the nanoparticle led to a significant enhancement of the overall efficiency compared to the corresponding bare nanoparticles.

Perspective article: flow synthesis of functional materials - Sebastian, Victor; Khan, Saif A.; Kulkarni, Amol A. (Journal of Flow Chemistry, 2017)
Continuous-flow synthesis of specific functional materials is now seen as a reliable synthesis approach that gives consistent product properties. This perspective article aims to survey recent work in some of the relevant areas and to identify new domains where flow synthesis of functional materials can be better than the conventional synthesis methods. It also emphasizes the need for developing high-throughput integrated synthesis and screening systems for almost all functional materials so that laboratory-scale recipes can be transformed into reliable manufacturing processes. New areas relevant to functional materials which have remained unexplored in flow synthesis are also highlighted.

Phenol oxidative dearomatization of modified nucleoside templates: a simple access to the c7-spiroannulated octosyl acid framework - Mullapudi, Venkannababu; Bhogade, Ravindra B.; Deshpande, Mukund V.; Ramana, Chepuri V. (Synthesis-Stuttgart, 2017)
Phenol oxidative dearomatization and cyclization has been executed successfully on nucleoside templates to synthesize C7-spiroannulated perhydrofuropyran nucleosides and C6-spiroannulated perhydrofurofuran nucleosides as novel analogues of octosyl acid and related peptidyl nucleosides.
Keywords: Analogs; antibiotics; Biosynthesis; Chitin synthase; Derivatives; Ezomycins; Glucose Diacetonide Natural-products; Griseofulvin; Malayamycin; Modified nucleosides; Moiety; Peptidyl Glycosides; Phenol Oxidative Dearomatization; Vorbruggen Glycosylation

Phenothiazine-based D-A-π-A dyes for highly efficient dye sensitized solar cells: effect of internal acceptor and non-conjugated π-spacer on device performance - Nagane, Satyawan; Ichake, Amol; Agrawal, Ishita; Sadhanala, Aditya; Friend, Richard H.; Ogale, Satishchandra; Wadgaonkar, Prakash P. (ChemPlusChem, 2017)
Three new D-A-pi-A metal-free organic dyes based on phenothiazine as a donor (D) and non-conjugated pi-spacer were designed and synthesized. The incorporation of different 'internal acceptors' (electron traps) such as benzothiadiazole (BTD), benzotriazole (BTA), and pyridine were shown to allow systematic tuning of the energy levels and the photophysical properties. The AI-1 dye showed lower electronic disorder compared with the other two dyes. The efficiencies achieved with AI-1, AI-2, and AI-3 dyes were 8.5% (J(sc) = 15.42 mA cm(-2), V-oc = 0.78 V, FF = 68%), 7% (J(sc) = 12.8 mA cm(-2), V-oc = 0.78 V, FF = 68%) and 6.7% (J(sc) = 11.57 mA cm(-2), V-oc = 0.82 V, FF = 68.26 %), respectively. The incorporation of non-conjugated phenothiazine as a p-spacer in D-A-pi-A dyes showed remarkable enhancement in the photovoltaic performance of dye-sensitized solar cell (DSSC) devices. The sealed DSSC devices with iodide/tri-iodide (I-/I-3(-) @)based liquid electrolyte showed promising stability under ambient conditions.

Photocatalytic degradation of herbicide by using aeroxide®P-90 TiO2 photocatalyst and photo-fenton process in the presence of artificial and solar radiation - Telang, T.,; Deosarkar, M.P.; Shetty, R.; Kamble, S.P. (Novel water treatment and separation methods: simulation of chemical processes, 2017)
The presence of herbicide residues in the aquatic environment is an emerging issue due to their uncontrolled release through water and accumulation in the environment that may affect living organisms, environment, and public health. Consequently, the efforts are being made to develop the viable methods to eliminate the herbicides from the environment. The degradation of herbicide particularly amitrole has been investigated in aqueous solutions by using artificial and solar radiation. The effect of Aeroxide TiO2 P-90 photocatalyst loading (1-4 g L-1) on photocatalytic degradation of amitrole (50 mg L-1) was investigated. The degradation of amitrole (initial concentration ranging from 20 to 100 mg L-1) also studied by using photo-Fenton process (FeSO4 (10-30 mg L-1) and H2O2 (100-300 mg L-1)). The effect of pH (3-11), effect of co-existing salts (ammonium sulfate, sodium chloride, and sodium carbonate) as well as effect of type of radiation (artificial or solar radiation) on the degradation of amitrole was evaluated and optimized. The degradation of amitrole was accompanied by formation of intermediates which were detected by LC-MS. According to the results presented in this study, the photo-Fenton process using solar radiation is an efficient technique for degradation of amitrole.

Photocatalytic degradation of pharmaceuticals pollutants using N-doped TiO 2 photocatalyst: identification of CFX degradation intermediates - Shetty, Rohit; Chavan, Vilas B.; Kulkarni, Prashant Shripad; Kulkarni, Bhaskar D.; Kamble, Sanjay P. (Indian Chemical Engineer, 2017)
The N-doped TiO2 photocatalyst was synthesized by the sol–gel method and characterized in detail in terms of its morphology, structure and composition. The prepared N-doped TiO2 exhibited polycrystalline structure having particle sizes of around 50–120 nm and rod-shaped geometry. The N-doped TiO2 was subsequently used for the photocatalytic degradation (PCD) of pharmaceutical micropollutants, namely ciprofloxacin HCl (CFX), naproxen (NPX) and paracetamol (PARA) and it was found that the rate of degradation of CFX and NPX is higher than that of PARA. To verify the beneficial effect of N-doped TiO2 for PCD of CFX, similar experiments were carried out using commercially available Aeroxide P-25 TiO2. It was observed that N-doped TiO2 was more efficient than Aeroxide® P-25 TiO2. It was also found that the PCD of CFX in the presence of N-doped TiO2 was highly efficient under the solar radiation as compared with artificial radiation. The effect of various operating parameters, such as adsorption of CFX, pH of the aqueous solution, effect of co-existing ions on PCD of CFX, was investigated using artificial radiation and optimum conditions were established. The intermediates formed during the PCD of CFX were identified using liquid chromatography tandem mass chromatography (LC-MS/MS). The presented results demonstrate that N-doped TiO2 photocatalyst shows excellent photocatalytic activity in the visible region for the degradation of pharmaceutical pollutants.

Photo-induced cytotoxicity and anti-metastatic activity of ruthenium(II)-polypyridyl complexes functionalized with tyrosine or tryptophan - Ramu, Vadde; Aute, Sunil; Taye, Nandaraj; Guha, Rweetuparna; Walker, Michael G.; Mogare, Devaraj; Parulekar, Apoorva; Thomas, Jim A.; Chattopadhyay, Samit; Das, Amitava (Dalton Transactions, 2017)
The synergistic effect of oxygen, light, and photosensitizer (PS) has found applications in medicine for the treatment of cancer through photodynamic therapy (PDT). Induction of apoptosis to cancerous cells will prevent tumor metastasis that spreads cancer cells to the neighboring organs/tissues. Herein, we report the two apoptotic Ru(II)-polypyridyl complexes that are functionalized with pendant amino acid moieties tyrosine (1) and tryptophan (2), respectively. These two water soluble complexes were found to interact strongly (K-a(1) = (1.18 +/- 0.28) x 10(5) M-1 and K-a(2) = (1.57 +/- 0.77) x 10(5) M-1) with CT-DNA. Isothermal titration calorimetry (ITC) studies revealed that these complexes bind to CT-DNA through an entropically driven process. Both the complexes showed photo-induced cytotoxicity and exhibit apoptotic activity under photo-irradiation conditions. The comet assay indicated that these complexes can damage cellular DNA, which is attributed to the significant build-up of O-1(2) level even on irradiation with low intensity light (10 J cm(-2), lambda(Range) 450-480 nm). This photoinduced DNA damage and apoptosis in A549 cells was induced by reactive oxygen species (ROS) and occurred through up-regulation of apoptotic marker caspase-3. Control experiments under dark conditions revealed an insignificant cytotoxicity towards these cells for two photosensitive molecules.

Photovoltaic and photocatalytic performance of electrospun Zn2SnO4 hollow fibers - Das, P. P.; Roy, A .; Tathavadekar, M.; Devi, P. S. (Applied Catalysis B, 2017)
The phase pure hollow Zn2SnO4 and green emitting ZnO-SnO2-Zn2SnO4 composite fiber have been prepared by post calcining the as formed fiber by electrospin technique. Depending upon the calcination temperature, the as prepared fiber exhibited a striking variation in composition, microstructure, optical and photo-electrochemical properties. The composition dependent dissimilarity in photovoltaic performance and photocatalytic activity has been established in this work. A relatively enhanced open circuit voltage (Voc) of 0.76 V, fill factor (FF) of 59.78%, short circuit current Qsc) of 4.2 mA/cm(2) and an overall conversion efficiency (n) of 1.93% have been achieved for the phase pure Zn2SnO4 porous fiber obtained at the elevated calcination temperature of 1000 degrees C. On the contrary, a relatively reduced Voc, FF, J(sc) and n of 0.70 V, 42.54%, 3.8 mA/cm(2) and 1.17%, respectively, have been achieved for the 800 degrees C calcined dense fiber consisting of a mixture of three distinct phases ZnO, SnO2 and Zn2SnO4. Unlike photovoltaic behaviour the trend in photocatalytic performance interestingly got reversed for the ZnO-nO(2)-Zn2SnO4 composite fiber owing to its superior photo-induced charge separation ability followed by generation of larger amount of active hydroxyl radicals (OFF). Our results establish the composite fiber as a preferred photocatalyst in comparison to phase pure Zn2SnO4 towards the textile dyes Methylene blue and Congo red and non absorbing organic pollutants such as Phenol and Bisphenol A under UV illumination.

Physical mechanism behind enhanced photoelectrochemical and photocatalytic properties of superhydrophilic assemblies of 3D-TiO2 microspheres with arrays of oriented, single-crystalline TiO2 nanowires as building blocks deposited on fluorine-doped tin oxid - Sadhu, Subha; Gupta, Preeti; Poddar, Pankaj (ACS Applied Materials & Interfaces, 2017)
In comparison to the one-dimensional (1D) semiconductor nanostructures, the hierarchical, three-dimensional (3D) microstructures, composed of the arrays of 1D nanostructures as building blocks, show quite unique physicochemical properties due to efficient photon capture and enhanced surface to volume ratio, which aid in advancing the performance of various optoelectronic devices. In this contribution, we report the fabrication of surfactant-free, radially assembled, 3D titania (rutile-phase) microsphere arrays (3D-TMSAs) composed of bundles of single-crystalline titania nanowires (NWs) directly on fluorine-doped conducting oxide (FTO) substrates with tunable architecture. The effects of growth parameters on the morphology of the 3D-TMSAs have been studied thoroughly. The 3D-TMSAs grown on the FTO-substrate showed superior photon-harvesting owing to the increase in light-scattering. The photocatalytic and photon to electron conversion efficiency of dye sensitized solar cells (DSSC), where the optimized 3D-TMSAs were used as an anode, showed around 44% increase in the photoconversion efficiency compared to that of Degussa P-25 as a result of the synergistic effect of higher surface area and enhanced photon scattering probability. The TMSA film showed superhydrophilicity without any prior UV irradiation. In addition, the presence of bundles of almost parallel NWs led to the formation of arrays of microcapacitors, which showed stable dielectric performance. The fabrication of single-crystalline, oriented, self-assembled TMSAs with bundles of titania nanowires as their building blocks deposited on transparent conducting oxide (TCO) substrates has vast potential in the area of photoelectrochemical research.

Phytase production by aspergillus niger NCIM 563 for a novel application to degrade organophosphorus pesticides - Shah, Parin C.; Kumar, V. Ravi; Dastager, Syed G.; Khire, Jayant M. (AMB Express, 2017)
The production of phytase using Aspergillus niger NCIM 563 under submerged fermentation conditions was studied using protein rich chickpea flour as substrate. Employing a hybrid statistical media optimization strategy of Plackett-Burman and Box-Behnken experimental designs in shake-flasks gave an increased phytase activity from an initial 66 IU/mL in 216 h to 160 IU/mL in a reduced time of 132 h. Productivity, thus increased by 3.97 times from 7.3 to 29 IU/mL/day. Using the optimized media, the production was successfully scaled-up further and improved up to 164 IU/mL in 96 h by studies carried out employing 2 and 10-L fermenters. The enzyme supernatant was recovered using centrifugal separation of biomass and the stability of the produced phytase was tested for animal feed applications under gastric conditions. In vitro degradation studies of water soluble monocrotophos, methyl parathion and water insoluble chlorpyrifos, pesticides used extensively in agriculture was carried out. It was observed by HPLC analysis that phytase could degrade 72% of chlorpyrifos at pH 7.0, 35 degrees C. Comparable results were obtained with monocrotophos and methyl parathion. With chlorpyrifos at higher temperature 50 degrees C as much as 91% degradation could be obtained. The degradation of chlorpyrifos was further validated by spraying phytase on harvested green chilli ( Capsicum annuum L) under normal conditions of pH 7.0, 35 degrees C and the degradation products obtained analyzed by LCMS. Thus, the present study brings out a potentially novel application of phytase for biodegradation of organophosphorus pesticides.

pi-Conjugated chromophore incorporated polystyrene nanobeads as single optical agent for three-channel fluorescent probe in bioimaging application - Makkad, Sarabjot Kaur; Asha, S. K. (ACS Biomaterials Science & Engineering, 2017)
Fluorescent polystyrene (PS) nanobeads in the size range similar to 70-120 nm incorporating perylene bisimide (PBI-PS) and/or oligo(p-phenylenevinylene) (OPV-PS) was developed by miniemulsion polymerization technique. A dye loading content (DLC) of <3% was sufficient to impart high fluorescence emission capability to the PS beads. OPV-PS exhibited emission in the range 400-550 nm with peak emission at 450 nm (lambda(ex) = 350 nm; phi(FL) = 26%); PBI-PS showed emission from 520-650 nm with peak emission at 545 nm (lambda(ex) = 490 nm; phi(FL) = 9.7%) in 1x PBS buffer, whereas OPV(PBI)-PS nanobeads incorporating both the fluorophores exhibited multicolor emission capabilities (lambda(ex) from 350 to 490 nm). The nanoparticles were characterized by field-emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM) and dynamic light scattering (DLS) for size and zeta potential for surface charge. For bioimaging applications, the PS nanoparticles were incubated with HeLa cells. Cell viability analysis involving HeLa cells showed more than 90% cell viability confirming the biocompatibility of the PS The cellular uptake of the nanoparticles was confirmed by flow cytometry analysis and confocal laser scanning microscopy (CLSM) images. The subcellular localization of the nanoparticles in the cytoplasm could be precisely established by their simultaneous multicolor emission. The PS-based single optical agent presented here that can function as three-channel fluorescent probe to meet the requirements for multicolor bioimaging is advantageous.
Keywords: Biocompatibility; bioimaging

Pilot-scale pretreatments of sugarcane bagasse with steam explosion and mineral acid, organic acid, and mixed acids: synergies, enzymatic hydrolysis efficiencies, and structure-morphology correlations - Pal, Siddhartha; Joy, Shereena; Kumbhar, Pramod S.; Trimukhe, Kalpana D.; Gupta, Rishi; Kuhad, Ramesh Chander; Varma, Anjani J.; Shankar, Sasi (Biomass Conversion and Biorefinery, 2017)
In lignocellulosic (LC) ethanol processes, to facilitate enzymatic hydrolysis of cellulose, a physical chemical pretreatment is vital. In this study, we explored a single as well as a two-step physical-chemical pretreatment involving steam and mixed acid on unwashed sugarcane bagasse at pilot-scale level in a continuous horizontal reactor. To serve as a large-scale model, pretreatments were carried out at high solid levels of 18–20 % w/w. For the pretreatment, partial replacement of corrosive sulfuric acid with a milder acid-like oxalic acid was explored to derive possible advantages and synergies accruing by using a mixture of mineral acid and organic acid. The results of this work showed that first-step pretreatment carried out by the mixing of sulfuric acid (1.5 % w/w) and oxalic acid (1.5 % w/w) at 150 °C followed by a second-step steam explosion pretreatment at 180 °C gave significant synergies and advantages over other variants of pretreatments investigated, such as lower inhibitor levels and lower reaction severity. On post-pretreated bagasse, this study conducted comparative enzymatic hydrolysis study using a simple lab enzyme and a robust commercial enzyme. It was found that the addition of Tween 80 to the lab enzyme improved its performance to match the performance of the commercial enzyme. Scanning electron microscopy (SEM) studies were further carried out to correlate the morphology of pretreated samples with efficiency of enzyme hydrolysis. Besides morphological study, Fourier transform infrared (FTIR) studies of pretreated samples showed higher syringyl/guaiacyl ratio for all pretreatments, indicating lower levels of pseudo-lignins, which is beneficial for improved enzyme hydrolysis.

Pinched tube flow reactor: hydrodynamics and suitability for exothermic multiphase reactions - Sharma, Mrityunjay K.; Potdar, Shital B.; Kulkarni, Amol A. (AIChE Journal, 2017)
A novel tubular flow reactor where a straight tube is modified by pinching it periodically at a fixed pitch and at different angles is presented. Pinched tubes (straight tube as well as helical coils) with different pitch and angles between successive pinching are studied. This work reports a detailed hydrodynamic study involving single and two-phase flow. Mixing experiments showed that having an angle of 90° between successive pinchs achieves the shortest mixing length when compared to lower angles. Pressure recovery along with sequence of high and low shear zones and change of flow direction imposed better mixing. Residence time distribution studies showed that higher number of pinch sections decreases the extent of dispersion, yet it deviates from plug flow. The performance is evaluated by carrying a homogeneous and two-phase aromatic nitration and also liquid-liquid extraction. Pinched tube presents an economical option as a flow reactor for conducting exothermic reactions. © 2016 American Institute of Chemical Engineers AIChE J, 2016
Keywords: pinched tube flow reactor; pressure drop; residence time distribution; mass transfer; reactions

Placental proteomics provides insights into pathophysiology of pre-eclampsia and predicts possible markers in plasma - Mary, Sheon; Kulkarni, Mahesh J.; Malakar, Dipankar; Joshi, Sadhana Ramchandra; Mehendale, Savita S.; Giri, Ashok P. (Journal of Proteome Research, 2017)
Pre-eclampsia is a hypertensive disorder characterized by the new onset of hypertension >140/90 mmHg and proteinuria after the 20th week of gestation. The disorder is multi-factorial and originates with abnormal placentation. Comparison of the placental proteome of normotensive (n=25) and pre-eclamptic (n=25) patients by gel-free proteomic techniques, identified a total of 2145 proteins in the placenta of which 180 were differentially expressed (>1.3 fold, p<0.05). Gene ontology enrichment analysis of biological process suggested that the differentially expressed proteins belonged to various physiological processes such as angiogenesis, apoptosis, oxidative stress, hypoxia, placental development, which are implicated in the pathophysiology of pre-eclampsia. Some of the differentially expressed proteins were monitored in the plasma by multiple reaction monitoring (MRM) analysis, which showed an increase in Apolipoprotein AI and AII in gestational week 26-30th (2-fold, p<0.01) while haptoglobin and hemopexin decreased in gestational week 26-30th and 40th week/at delivery (1.8 fold, p<0.01) in pre-eclamptic patients. This study provides a proteomic insight into the pathophysiology of pre-eclampsia. Identified candidate proteins can be evaluated further for the development of potential biomarkers associated with pre-eclampsia pathogenesis.

Plant cholesterol biosynthetic pathway overlaps with phytosterol metabolism - Sonawane, P. D.; Pollier, J.; Panda, S.; Szymanski, J.; Massalha, H.; Yona, M.; Unger, T.; Malitsky, S.; Arendt, P.; Pauwels, L.; Almekias-Siegl, E.; Rogachev, I.; et al. (Nature Plants, 2017)
The amount of cholesterol made by many plants is not negligible. Whereas cholesterogenesis in animals was elucidated decades ago, the plant pathway has remained enigmatic. Among other roles, cholesterol is a key precursor for thousands of bioactive plant metabolites, including the well-known Solanum steroidal glycoalkaloids. Integrating tomato transcript and protein co-expression data revealed candidate genes putatively associated with cholesterol biosynthesis. A combination of functional assays including gene silencing, examination of recombinant enzyme activity and yeast mutant complementation suggests the cholesterol pathway comprises 12 enzymes acting in 10 steps. It appears that half of the cholesterogenesis-specific enzymes evolved through gene duplication and divergence from phytosterol biosynthetic enzymes, whereas others act reciprocally in both cholesterol and phytosterol metabolism. Our findings provide a unique example of nature's capacity to exploit existing protein folds and catalytic machineries from primary metabolism to assemble a new, multi-step metabolic pathway. Finally, the engineering of a 'high-cholesterol' model plant underscores the future value of our gene toolbox to produce high-value steroidal compounds via synthetic biology.

Plasmonic behavior of ionic liquid stabilized gold nanoparticles in molecular solvents - Thawarkar, Sachin; Thombare, Balu; Khupse, Nageshwar D. (New Journal of Chemistry, 2017)
In this paper, we have demonstrated the facile synthesis of stable gold nanoparticles (AuNPs) using imidazolium ionic liquids (ImILs) as a stabilizer as well as a surfactant and their surface plasmon resonance (SPR) in different molecular solvents with varying dielectric properties. The preparation of AuNPs capped with N,N'-dialkyl ImILs of different chain lengths (denoted as [C-4, C-n-im]Br, n = carbon number of the alkyl chain) has been investigated. With one long alkyl chain (n >= 14), these AuNPs could be stably dispersed in solution over a month. The amphiphilic nature of the imidazolium salt dictates the stability and dispersion of these AuNPs in organic or aqueous solvents. Alkyl chain lengths (n >= 14) and the amount of ImILs have insignificant effect on the size of AuNPs and they possess an average size of 5 nm. These ionic liquid stabilized AuNPs were exploited to examine their optical properties when exposed to various solvent systems by measuring the change in the SPR spectrum. It was seen that the position of the SPR band of AuNPs is greatly influenced by the solvents under consideration. The shift in the SPR absorption band is observed to be in the range of 520 nm to 605 nm for AuNP@[C-4,C-16-im]Br from nonpolar to highly polar solvents. The considerable discovery presented here is that the lambda(SPR) of the SPR shifts to the blue with the increase of carbon atom in the alcohol chain from methanol to 1-decanol. Also for polyethylene glycols (PEGs), the lambda(SPR) shifts to the blue with the increase in molecular weight from PEG 200 to PEG 600. In above both cases, the variation in SPR of AuNPs is observed according to the dielectric properties of the medium in addition to the steric factor of alcohols and PEGs during their interaction with AuNP surfaces.

Poly(ether urethane)s from aromatic diisocyanates based on lignin-derived phenolic acids - Kuhire, Sachin; Nagane, Samadhan S.; Wadgaonkar, Prakash (Polymer International, 2017)

Polyhydroxyalkanoates as biomaterials - Bhagyashri, S.; Gadgil, Thorat; Killi, Naresh; Rathna, Gundloori V. N. (MedChemComm, 2017)
Polyhydroxyalkanoates (PHAs) are biopolymers synthesized by bacteria under unbalanced growth conditions. These biopolymers are considered as potential biomaterials for future applications because they are biocompatible, biodegradable, and easy to produce and functionalize with strong mechanical strength. Currently, PHAs are being extensively innovated for biomedical applications due to their prerequisite properties. The wide range of biomedical applications includes drug delivery systems, implants, tissue engineering, scaffolds, artificial organ constructs, etc. In this article we review the utility of PHAs in various forms (bulk/nano) for biomedical applications so as to bring about the future vision for PHAs as biomaterials for the advancement of research and technology.
Keywords: Biomedical Applications; Cancer-therapy; Drug-delivery Systems; In-vitro; Molecular-weight; Poly(Ester Urethane)S; poly(ethylene glycol); Regenerative Medicine; Tissue Engineering Applications; Vitro Antibiotic Release

Polylactic acid (PLA) biocomposites filled with waste leather buff (WLB) - Ambone, Tushar; Joseph, Seena; Deenadayalan, E.; Mishra, Satyendra; Jaisankar, S.; Saravanan, P. (Journal of Polymers and the Environment, 2017)
A large amount of leather waste is generated from tanning industries and most of which are disposed of landfill or discharged into the natural water bodies without any treatment, causing environmental problems. The aim of this study is to develop eco-biocomposites using waste leather buff (WLB) as filler in Polylactic acid (PLA) matrix to reduce the environmental issues and provide sustainable solution. WLB/PLA composites were prepared by twins-screw micro extruder varying the WLB content from 2% to 30 wt%. These composite were extensively characterise by several techniques. Tensile properties of the composites showed addition of WLB resulted in improvement of tensile property of composite and reduction in percentage crystallinity of PLA matrix observed with increase in WLB content. The effect of WLB on properties of interfacial adhesion and dispersion in WLB/PLA composites were studied by SEM. Wettability of composites was tested by contact angle and water absorption studies. WLB/PLA composite showed increase in water absorption with WLB loading. These WLB/PLA composite could be used to develop low cost eco-friendly product material.

Polymer and graphene layer to increase dye regeneration and suppress back electron transfer in dye sensitized solar cells - Sudhakar, Vediappan; Arulkashmir, Arulraj; Krishnamoorthy, Kothandam (Chemical Communications, 2017)
Dye regeneration was improved by using an optimum quantity of graphene, which was dispersed in a polymer that suppresses back electron transfer. Using this approach, DSSCs with an efficiency of 10.4% have been fabricated.

Polymer-based hybrid catalyst of low Pt content for electrochemical hydrogen evolution - Chakrabartty, S. (International Journal of Hydrogen Energy, 2017)
Hydrogen is regarded as the most promising fuel to replace conventional fossil fuel. The electrochemical production of hydrogen requires catalyst and development of efficient non-Pt catalysts or catalysts with low Pt content are in demand. Herein, we demonstrate the photochemical synthesis of a hydrogen evolution electrocatalyst poly(α-terthiophene)-Pt nanoparticle hybrid material (polyTT-Pt) of low Pt content and its electrocatalytic activity. The synthesis of polyTT-Pt hybrid material involves the photoinduced electron transfer between α-terthiophene (α-TT) and and the subsequent in situ growth of polymer and Pt nanoparticles. The irradiation of the mixture of α-TT and with sunlamp initiates the oxidative polymerization and reduction of Pt complex to Pt nanoparticles. The polymer has cabbage-like microstructure and the in situ grown Pt nanoparticles have an average size of 1.8 nm. The Pt nanoparticles are embedded into the polymer matrix as well as randomly distributed over the polymer. The hybrid material contains 2.91 wt% of Pt and it shows characteristic electrochemical signature with an electrochemically active surface area of 35.7 m²/gPt. The hybrid material polyTT-Pt is electrocatalytically highly active though it contains very small amount of Pt. It efficiently catalyses hydrogen evolution reaction (HER) and the bench mark current density of 10 mA/cm² is achieved at an overpotential of 67 mV. The mass activity of the hybrid catalyst is 1172 mA/mgPt at the overpotential of 67 mV. The high activity is ascribed to the high electronic conductivity of the polymer matrix, facile access of electrolyte due to the embedded small nanoparticles and the presence of large number of catalytically active Pt sites. Tafel analysis suggests that the HER follows the Volmer-Tafel mechanism. Polymer-based hybrid catalyst of low Pt content for electrochemical hydrogen evolution. Available from: https://www.researchgate.net/publication/319039592_Polymer-based_hybrid_catalyst_of_low_Pt_content_for_electrochemical_hydrogen_evolution [accessed Oct 16 2017].

Polymerization-incompetent uromodulin in the pregnant stroke-prone spontaneously hypertensive rat - Mary, Sheon; Small, Heather Yvonne; Siwy, Justyna; Mullen, William; Giri, Ashok; Delles, Christian (Hypertension, 2017)
The kidney is centrally involved in blood pressure regulation and undergoes extensive changes during pregnancy. Hypertension during pregnancy may result in an altered urinary peptidome that could be used to indicate new targets of therapeutic or diagnostic interest. The stroke-prone spontaneously hypertensive rat (SHRSP) is a model of maternal chronic hypertension. Capillary electrophoresis-mass spectrometry was conducted to interrogate the urinary peptidome in SHRSP and the control Wistar-Kyoto strain at three time points: prepregnancy and gestational days 12 and 18. The comparison within and between the Wistar-Kyoto and SHRSP peptidome at all time points detected 123 differentially expressed peptides (fold change >1.5; P<0.05). Sequencing of these peptides identified fragments of collagen a-chains, albumin, prothrombin, actin, serpin A3K, proepidermal growth factor, and uromodulin. Uromodulin peptides showed a pregnancy-specific alteration in SHRSP with a 7.8-fold (P<0.01) and 8.8-fold (P<0.05) increase at gestational days 12 and 18, respectively, relative to the Wistar-Kyoto. Further investigation revealed that these peptides belonged to the polymerization-inhibitory region of uromodulin. Two forms of uromodulin (polymerization competent and polymerization incompetent) were found in urine from both Wistar-Kyoto and SHRSP, where the polymerizationincompetent form was increased in a pregnancy-specific manner in SHRSP. Nifedipine-treated pregnant SHRSP showed only polymerization-competent uromodulin, indicating that calcium may be mechanistically involved in uromodulin polymerization. This study highlights, for the first time, a potential role of uromodulin and its polymerization in hypertensive pregnancy.
Keywords: Hypertension; Kidney; Nifedipine; pregnancy; uromodulin

Polymorphism, isostructurality and physicochemical properties of glibenclamide salts - Suresh, Kuthuru; Khandavilli, U. B. Rao; Gunnam, Anilkumar; Nangia, Ashwini (CrystEngComm, 2017)
Novel salts of glibenclamide (GBA), namely glibenclamide-sodium (GBA-Na), glibenclamide-potassium (GBA-K) and glibenclamide-ammonium (GBA-NH4) were crystallized under different conditions to obtain their polymorphs, and their aqueous solubility and hydration stability studies are reported. The GBA-Na salt is dimorphic (forms I and II)and also exists as hydrate GBA-Na-H2O (form III). The GBA-K salt exists in anhydrous and hydrate forms (GBA-K, forms I and II). Crystal structure analysis of GBA-Na forms I and II showed differences in geometry of the central metal atom and ligand orientation. This kind of polymorphism of sulfonyl urea salts appears to be novel in the Cambridge Structural Database (CSD). The iso-structurality of GBA-Na form I with GBA-NH4 and GBA-K form I salts is discussed. The potassium salts of GBA exhibited higher solubility compared to pure GBA. Specifically GBA-K salt forms I and II showed higher solubility by 77 fold in the water and 33 fold in phosphate buffer (pH 7) compared to the other salts. Dynamic vapor sorption (DVS) showed reversible water sorption without hysteresis for all salts, except for GBA-K form II which transformed to form I after a sorption and desorption cycle as confirmed by PXRD.

Polymorphs and cocrystals: a comparative analysis - Gonnade, Rajesh G.; Sangtani, Ekta (Journal of the Indian Institute of Science, 2017)
Controlling polymorphism has been the subject of vigorous research in the recent past in the pharmaceutical industry due to the distinct physicochemical properties associated with each solid form. Developing cocrystals/salts of active pharmaceutical ingredients (APIs) has gained tremendous research interest in recent years owing to their potential to improve pharmaceutically relevant properties without affecting therapeutic efficacy. It is observed that compounds that exhibit polymorphism and also contain several H bond donor/acceptor groups have a tendency to form cocrystals and sometime even display cocrystal polymorphism, although this tendency cannot be generalized. The aim of this contribution is to correlate crystal structures of some polymorphic APIs and their respective cocrystals to understand the rationale behind a polymorphic compound generating cocrystals. Here, we make an attempt to compare how the conformation of the molecule observed in its polymorphs support the generation of cocrystals/salts. We understand that it is impossible to cover all the polymorphs and their cocrystals/salts available in the CSD; the comparative study has been carried out with a few case studies, wherein APIs displayed polymorphism (conformation) and also formed cocrystals/salts.

Polyphenylene sulfide- expanded graphite nanocomposites: processing route dependent electrical percolation - Ramanujam, B. T. S.; Radhakrishnan, S.; Deshpande, S. D. (Journal of Thermoplastic Composite Materials, 2017)
Polyphenylene sulfide (PPS)-expanded graphite (ExGr) conducting nanocomposites have been prepared by powder mixing and in situ polymerization routes after sonicating ExGr particles in acetone. Synthesized PPS has been used to make powder mixed composites. The powder mixed composites exhibit a percolation threshold of 3 wt% due to the formation of graphite nanosheets. When PPS-ExGr composites are prepared by in situ polymerization route, very low electrical percolation threshold less than 0.5 wt% ExGr is obtained. The low percolation threshold obtained is attributed to better dispersion of ExGr nanosheets in the polymer matrix when compared to powder mixed composites. The synthesized PPS has been characterized by X-ray diffraction, differential scanning calorimetry, and infrared spectroscopy. The formation of graphite nanosheets has been confirmed by transmission and scanning electron microcopy analysis.

Polypropylene-based conducting nanocomposites: effect of aspect ratio of second conducting filler on the electrical percolation - Ramanujam, B. T. S.; Radhakrishnan, S.; Deshpande, S. D. (Journal of Thermoplastic Composite Materials, 2017)
Powder-mixed polypropylene (PP)-graphite binary composites exhibit an electrical percolation threshold at 10 wt% graphite signifying insulator-semiconductor transition. Three conducting fillers such as carbon black (CB), sonicated expanded graphite (s-ExGr), and carbon nanofiber (CNF) are mixed with PP-7 wt% graphite binary composites. The electrical percolation threshold has been found to have inverse relation to the aspect ratio of second conducting fillers in hybrid composites. The aspect ratio of second conducting fillers varies in the order CB < ExGr < CNF. The electrical percolation threshold is found to vary for the hybrid composites as 2.2 wt% for CB addition, 0.75 wt% for ExGr addition, and 0.2 wt% for CNF addition in the PP-7 wt% graphite binary composites. When the aspect ratio of second conducting fillers increases, they reduce the barrier for the charge transport. The second conducting fillers occupy the interspace of graphite and alternating current studies show that the effective dielectric constant increases with the concentration of second conducting filler in the hybrid composites. The composites are characterized by transmission electron microscopy and scanning electron microscopy. Melt-crystallized PP-7 wt% graphite-CNF composites exhibit higher percolation threshold due to decrease in the polymer viscosity which increases the interparticulate distance.
Keywords: carbon nanofiber; Conducting polymer composites; Electrical properties; graphite nanosheets; hybrid composites; percolation; scanning; transmission electron microscopy

Porous porphyrin organic polymer (PPOP) for visible light triggered hydrogen production - Mukherjee, Gargi; Thote, Jayshri; Aiyappa, Harshitha Barike; Kandambeth, Sharath; Banerjee, Subhrashis; Vanka, Kumar; Banerjee, Rahul (Chemical Communications, 2017)
A visible light active porphyrin-based porous organic polymer having high chemical stability and surface area has been synthesized and its ability to influence the photocatalytic activity of large band gap-TiO2 nanoparticles has been tested. The resultant composite shows improved photocatalytic activity as compared to the parent precursors. This study provides insights into the photosensitizing ability of the polymer in addition to its ability to firmly harbor nanoparticles onto its surface.

Porous reduced graphene oxide modified electrodes for the analysis of protein aggregation. part 1: lysozyme aggregation at pH 2 and 7.4 - Vasilescu, Alina; Boulahneche, Samia; Chekin, Fereshteh; Gaspar, Szilveszter; Medjram, Mohamed Salah; Diagne, Abdou Aziz; Singh, Santosh K.; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (Electrochimica Acta, 2017)
Protein instability due to misfolding and aggregation is of big concern for protein based therapeutics because it impacts the bioavailability and immunogenicity of such drugs. The development of simple and cost-effective methods for the analysis of pharmaceutical formulations, indicating the presence or absence of protein aggregates, is consequently of high importance. This work proposes a novel electrochemical interface based on porous reduced graphene oxide coated glassy carbon electrode (GC/prGO) allowing for the early and sensitive identification of protein aggregation by following the change in the oxidative current of the proteins. The novelty of this work lies in the exploration of the ability of GC/prGO interfaces to capture different aggregation behaviors. Lysozyme is used as a model to follow by electrochemistry its aggregation at two pH values, pH 2 and pH 7.4, leading to the formation of amyloid and amorphous aggregates, respectively. Comparing the oxidation peak of lysozyme by differential pulse voltammetry (DPV) for different electrode architectures allowed validating the higher sensitivity of the GC/prGO interface versus bare glassy electrodes or electrodes coated with non-porous reduced graphene oxide. Parallel experiments were performed by fluorescence with thioflavin T, size exclusion chromatography and Atomic Force Microscopy (AFM) imaging. These tests further highlighted the usefulness of GC/prGO electrode to visualize in a fast and reliable manner the changes in the protein structure and the differences between the processes occurring at pH 2 and pH 7.4. In particular, the ability to emphasize changes related to the first steps in aggregation that could be indicative of the aggregation course, recommend the GC/prGO electrode in combination with DPV as a new analytical tool for aggregation studies of biopharmaceuticals. Part 2 of this work will demonstrate later the utility of this approach for the analysis of a fast acting injectable human insulin formulation, Humulin R, used for diabetes treatment as well as for calcitonin. (C) 2017 Elsevier Ltd. All rights reserved.

Possibly scalable solar hydrogen generation with quasi-artificial leaf approach - Patra, Kshirodra Kumar; Bhuskute, Bela D.; Gopinath, Chinnakonda S. (Scientific Reports, 2017)
Any solar energy harvesting technology must provide a net positive energy balance, and artificial leaf concept provided a platform for solar water splitting (SWS) towards that. However, device stability, high photocurrent generation, and scalability are the major challenges. A wireless device based on quasi-artificial leaf concept (QuAL), comprising Au on porous TiO2 electrode sensitized by PbS and CdS quantum dots (QD), was demonstrated to show sustainable solar hydrogen (490 +/- 25 mu mol/h (corresponds to 12 ml H-2 h(-1)) from similar to 2mg of photoanode material coated over 1 cm(2) area with aqueous hole (S2-/SO32-) scavenger. A linear extrapolation of the above results could lead to hydrogen production of 6 L/h.g over an area of similar to 23 x 23 cm(2). Under one sun conditions, 4.3 mA/cm(2) photocurrent generation, 5.6% power conversion efficiency, and spontaneous H-2 generation were observed at no applied potential (see S1). A direct coupling of all components within themselves enhances the light absorption in the entire visible and NIR region and charge utilization. Thin film approach, as in DSSC, combined with porous titania enables networking of all the components of the device, and efficiently converts solar to chemical energy in a sustainable manner.

Potent antimicrobial activity of lipidated short alpha,gamma-hybrid peptides - Benke, Sushil N.; Thulasiram, Hirekodathakallu V.; Gopi, Hosahudya N. (ChemMedChem, 2017)
Herein we report the potent antimicrobial activity of alpha,gamma-hybrid lipopeptides composed of 1:1 alternating - and gamma-amino acids. Along with their potent antimicrobial activity against various Gram-positive and Gram-negative bacteria, these hybrid lipopeptides were found to be less hemolytic. Studies into the mechanism of action revealed that these short cationic lipopeptides bind and disrupt the bacterial cell membrane. Time-kill kinetics analyses revealed that the potent alpha,gamma-hybrid lipopeptides completely inhibit bacterial growth in less than 20 minutes. Overall, the promising antimicrobial activity along with lower hemolytic activity displayed by these alpha,gamma-hybrid lipopeptides make them well suited for further exploration into the design of potent lipopeptide antibiotics.

Predesigned metal-anchored building block for in situ generation of Pd nanoparticles in porous covalent organic framework: application in heterogeneous tandem catalysis - Bhadra, Mohitosh; Sasmal, Himadri Sekhar; Basu, Arghya; Midya, Siba P.; Kandambeth, Sharath; Pachfule, Pradip; Balaraman, Ekambaram; Banerjee, Rahul (ACS Applied Materials & Interfaces, 2017)
The development of nanoparticle-polymer-hybrid-based heterogeneous catalysts with high reactivity and good recyclability is highly desired for their applications in the chemical and pharmaceutical industries: Herein, we have developed a novel synthetic strategy by choosing a predesigned metal-anchored building block for in situ generation of metal (Pd) nanoparticles in the stable, porous, and crystalline covalent organic framework (COF), without using conventional reducing agents. In situ generation of Pd nanoparticles in the COF Skeleton is explicitly confirmed' from PXRD, XPS, TEM images, and N-15 NMR spectral analysis. This hybrid material is found to be an excellent reusable heterogeneous catalyst for the synthesis of biologically and pharmaceutically important 2-substituted benzofurans from 2-bromophencils and terminal alkynes via a tandem process with the turnover number up to 1101. The heterogeneity of the catalytic process is unambiguously verified by a mercury poisoning experiment and leaching test. This hybrid material shows superior catalytic performance compared to commercially available homogeneous as well as heterogeneous Pd catalysts.

Prediction of degrees API values of crude oils by use of saturates/aromatics/resins/ asphaltenes analysis: computational-intelligence-based models - Goel, Purva; Saurabh, Kumar; Patil-Shinde, Veena; Tambe, Sanjeev S. (SPE Journal, 2017)
The degrees API value is an important physicochemical characteristic of crude oils often used in determining their properties and quality. There exist models-predominantly linear ones-for predicting the degrees API magnitude from the molecular composition of a crude oil. This approach is tedious and time-consuming because it requires quantitative determination of numerous crude-oil components. Usually, the hydrocarbons present in a crude oil are grouped according to their molecular average structures into saturates, aromatics, resins, and asphaltenes (SARA) fractions. An degrees API-value prediction model dependent on these four fractions is relatively easier to develop, although this approach has been rarely used. A rigorous scrutiny suggests that some of the dependencies between the individual SARA fractions and the corresponding degrees API value could be nonlinear. Accordingly, in this study, SARA-fraction-based nonlinear models have been developed for the prediction of values using three computational-intelligence (CI) formalisms: genetic programming (GP), artificialneural networks (ANNs), and support-vector regression (SVR). The SARA analyses and degrees API values of 403 crude-oil samples covering wide ranges have been used in developing these models. A comparison of the CI-based models with an existing linear model indicates that all the former class of models possess a significantly better degrees API-value prediction and generalization performance than those exhibited by the linear model. Also, the SVR-based model has been found to be the most accurate degrees API-value predictor. Because of their better prediction accuracy, CI-based models can be gainfully used to predict degrees API values of crude oils.

Preparation of MgO supported platinum nanoparticle catalyst using toluene dispersed platinum sol - Seth, J.; Nepak, D.; Chaudhari, V. R.; Prasad, B.L.V. (Applied Surface Science, 2017)
An effective way of anchoring Pt nanoparticles on MgO using toluene dispersed platinum nanoparticles (Pt-NPs) as one of the ingredient is demonstrated. The usage of particles dispersed in toluene allows the retention of size and size distribution of preformed Pt-NPs even after deposition on MgO support with high active surface area, which is crucial for heterogeneous catalysis. The catalyst thus prepared, displayed selective hydrogenation of cinnamaldehyde to cinnamyl alcohol with high turn on frequency (TOF − 105 h−1) with respect to the total Pt content. We attribute this efficient catalytic performance to the uniform distribution and deposition of Pt on the active MgO support and its better accessible surface as evidenced by the cyclic-voltammetry results.
Keywords: catalysis; Catalysts; cyclic voltammetry; Deposition; Magnesia; Nanoparticles; sol-gel process

Probing cavity versus surface preference of fluorescent template molecules in molecularly imprinted polystyrene microspheres - Sonawane, Swapnil L.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2017)
Functional polystyrene (PS) crosslinked microbeads were developed by dispersion polymerization as fluorescent molecularly imprinted polymers (MIPs) having cavities with specific recognition sites. The functional azobenzene molecule modified with pyridine was self-assembled with Pyrenebutyric acid (template molecules), and introduced during the second stage of dispersion polymerization of polystyrene. The template molecule was removed from MIP by Soxhlet using acetonitrile as solvent. Non imprinted polymer (NIP) having no template was also synthesized for comparative study. Fluorescence spectroscopy could be used as a tool to derive insight into the location of the template molecules on the MIP or NIP. The template molecules were adsorbed on the surface of the NIPs during binding studies, which was evidenced from the pyrene excimeric emission observed at 440 nm. The template binding efficiency of the NIPs were much lower compared to MIPs. Pyrene emission from MIP upon rebinding showed typical monomeric emission in the 375-395 nm range, confirming its location in isolated cavities. In rebinding studies of the template molecules, the MIPs selectively took up the template for which the cavity was designed, which demonstrated their selectivity towards template molecules. (C) 2017 Wiley Periodicals, Inc.

Probing the solute-solvent interactions in the binary mixtures of ionic liquids with water and alcohols by conductance, viscosity and IR spectroscopy - Jain, Preeti; Kumar, Anil (Journal of Molecular Liquids, 2017)
The molar conductance and viscosities of the bisulfate ([HSO4](-)) and ethylsulfate ([EtSO4](-))-based imidazolium ionic liquids in various molecular solvents have been measured at 298.15 K as a function of concentration of ionic liquids (1 x 10(-4) to 0.1 mol L-1). It is shown that the anions have considerable effect on the molar conductance and association constant of the [HSO4](-) and [EtSO4](-)-based imidazolium ionic liquids. Higher molar conductance of the [HSO4](-)-based imidazolium ionic liquids in polar protic solvents (water and methanol) is noted as compared to the [EtSO4](-)-based imidazolium ionic liquids, though the [HSO4](-)-based imidazolium ionic liquids possess higher association constant in water than in methanol. The intermolecular interactions in the pure and binary mixture of [HSO4](-) and [EtSO4](-)-based imidazolium ionic liquids have been investigated by IR spectroscopy. The C-2-H stretching vibration frequency of the imidazolium ring reveals the H-bonding between cations and anions of pure ionic liquids and their solutions. The transport properties (limiting molar conductance, transport number, ionic mobility and diffusion coefficient) of cations and anions correlate well with the hydrodynamic radius in their aqueous solutions. The study shows that the energy barrier for charge transfer is minimal as compared to the fluidity of the aqueous solution of the studied ionic liquids obtained from the Arrhenius equation. (C) 2017 Elsevier B.V. All rights reserved.

Processing and characterization of waste leather based polycaprolactone biocomposites - Joseph, Seena; Ambone, Tushar S.; Salvekar, Abhijit V.; Jaisankar, S. N.; Saravanan, P.; Deenadayalan, E. (Polymer Composites, 2017)
Waste leather buff (WLB) filled polycaprolactone (PCL) composites were prepared by twin-screw extrusion varying the WLB content from 2% to 40%. These composites were extensively characterized by several techniques in order to establish micro and macroscopic properties. Addition of WLB resulted in improvement of tensile modulus of neat PCL and reduction in percentage crystallinity of PCL matrix was observed with increase in WLB content. Interfacial adhesion and dispersion of WLB on PCL matrix was investigated using Scanning Electron Microscope. Percentage of water uptake increased with increase in concentration of WLB in the composite. These biodegradable composites could be used to develop low cost materials suitable for applications in footwear industry, for making bags, suitcases, etc., eliminating the environmental issues arising from WLB generated from tanneries in leather industry. POLYM. COMPOS., 38:2889-2897, 2017. (c) 2015 Society of Plastics Engineers

Promotional effect of WOx in Pt-WOx/AlPO4-5 catalyzed deoxygenation of fatty acids - Janampelli, Sagar; Darbha, Srinivas (ChemistrySelect, 2017)
WOx promoted Pt/AlPO4-5 catalysts with varying Pt and W contents were prepared by wet-impregnation method and characterized. Catalysts with Pt to W weight ratio of 1: 2 exhibited higher catalytic performance than the other compositions in deoxygenation of oleic acid (OA). WOx enhanced significantly the catalytic activity of Pt and enabled quantitative conversion of OA to linear alkanes (predominantly C-18/C-17) at a temperature as low as 280 degrees C. It changed the reaction pathway from decarbonylation/ decarboxylation (DCO for Pt/AlPO4-5) to hydrodeoxygenation (HDO for Pt-WOx/AlPO4-5). It affected the particle size and redox behaviour of Pt. The enhanced H-spill over (by 14.8%) and presence of strong acid sites (300 - 500 degrees C) are the cause for the high activity of Pt-WOx/AlPO4-5 catalysts even at lower temperatures. Partially reduced WOx activates OA and leads to the HDO product (C-18). In the absence of WOx, Lewis acid sites of the support activate OA through the C=O group and Pt facilitates C-C cleavage and formation of DCO product (C-17).
Keywords: biofuels; Deoxygenation; Fatty acids; Green Diesel; Hydrocarbons

Proton conduction in a hydrogen-bonded complex of copper(II)-bipyridine glycoluril nitrate - Tayade, Sakharam B.; Dhavale, Vishal M.; Kumbhar, Avinash S.; Kurungot, Sreekumar; Loennecke, Peter; Hey-Hawkins, Evamarie; Pujari, Bhalchandra (Dalton Transactions, 2017)
Bipyridine glycoluril (BPG), a urea-fused bipyridine tecton, forms a square-pyramidal secondary building unit with copper(II) which further self-assembles to give a porous hydrogen-bonded complex. This complex displays a high proton conductivity of 4.45 x 10(-3) S cm(-1) at 90 degrees C and 95% relative humidity (RH). Chains consisting of coordinated water, solvent water and nitrate anions embedded in the complex are responsible for high proton conduction. The proton conduction pathway was corroborated by ab initio electronic structure calculations with molecular dynamics (MD) simulations using the Nudged Elastic Band (NEB) method. The theoretical activation energy estimated to be 0.18 eV is in close agreement with the experimental value of 0.15 eV which evidences a Grotthuss proton hopping mechanism. We thus demonstrate that the hydrogen-bonded complex encapsulating appropriate counter ions, coordinated water and solvent water molecules exhibts superprotonic conductivity.

Proton-coupled electron-transfer processes in ultrafast time domain: evidence for effects of hydrogen-bond stabilization on photoinduced electron transfer - Dey, Ananta; Dana, Jayanta; Aute, Sunil; Maity, Partha; Das, Amitava; Ghosh, Hirendra N. (Chemistry-A European Journal, 2017)
The proton-coupled electron-transfer (PCET) reaction is investigated for a newly synthesized imidazoleanthraquinone biomimetic model with a photoactive RuIIpolypyridyl moiety that is covalently coupled to the imidazole fragment. Intramolecular H-bonding interactions between imidazole and anthraquinone moieties favor the PCET process; this can be correlated to an appreciable positive shift in the one-electron reduction potential of the coordinated anthraquinone moiety functionalized with the imidazole fragment. This can also be attributed to the low luminescence quantum yield of the RuII-polypyridyl complex used. The dynamics of the intramolecular electron-transfer (ET) and PCET processes are studied by using femtosecond transient absorption spectroscopy. The steady- state spectroscopic studies and the results of the time- resolved absorption studies confirm that H- bonded water molecules play a major role in both ET and PCET dynamics as a proton relay in the excited state. The electron- transfer process is followed by a change in the H- bonding equilibrium between AQ and imidazole in acetonitrile solvent, and protonation of AQ(-) water leads to PCET in the presence of water. A slower forward and backward electron- transfer rate is observed in the presence of D2O compared with that in H2O. These results provide further experimental support for a detailed understanding of the PCET process.

p-Selective (sp(2))-C-H functionalization for an acylation/alkylation reaction using organic photoredox catalysis - Pandey, Ganesh; Tiwari, Sandip Kumar; Singh, Bhawana; Vanka, Kumar; Jain, Shailja (Chemical Communications, 2017)
p-Selective (sp(2))-C-H functionalization of electron rich arenes has been achieved for acylation and alkylation reactions, respectively, with acyl/alkylselenides by organic photoredox catalysis involving an interesting mechanistic pathway.

Pyrethrin accumulation in elicited hairy root cultures of chrysanthemum cinerariaefolium - Khan, Shamshad A.; Verma, Priyanka; Banerjee, Suchitra; Chaterjee, Arnab; Tandon, Sudeep; Kalra, Alok; Khaliq, Abdul; Rahman, Laiq Ur (Plant Growth Regulation, 2017)
The flowers of Pyrethrum (Chrysanthemum cinerariaefolium) are known to contain Pyrethrins that are naturally occurring potential insecticide. Hairy roots were induced from leaves of C. cinerariaefolium using Agrobacterium rhizogenes strain A4. The root clones were characterized in to four groups i.e. thick, unbranched (D2 and D5), thin, highly branched (D3), thick, branched (B2) and thick, highly branched (D1, D6). Six established hairy root clones showed the presence of pyrethrin and were selected for elicitation studies. Growth kinetics studies revealed highest growth index in hairy root clone D1 (592.0) followed by D6 and D3 on dry weight basis after 40 days of culture. The maximum pyrethrin content was found in the clone D3 (7.2 mg/g dw) which is comparable to the flowers obtained from the variety "Avadh". Hairy root clone D2 (5.2 mg/g dw) and D6 (1.3 mg/g dw) contained pyrethrin but in less amount as compared to clone D3. The PCR analysis showed the presence of rol B and rol C genes in all the six hairy root clones while rol A was detected only in D2 clone. The methanolic extract of D3 clone showed antifungal activities against phytopathogenic fungal strains which were found maximum against Curvuleria andropogonis followed by Colletotrichum acutatum and Rhizoctonia solani. Hairy root clones D2, D3 and D6 were elicited with culture filtrate of endophytic fungus (Fusarium oxysporum) and bacteria (Bacillus subtilis). The culture filtrate (4.0 %v/v) of both the fungal and bacterial origin was found to be effective in enhancing the pyrethrin content in all the tested hairy root clones. Clone D3 showed maximum pyrethrin content on elicitation with F. oxysporum (9.7 mg/g dw) and B. subtilis (9.7 mg/g dw) culture filtrate, which is 32 % higher than the non elicited D3 hairy roots (7.2 mg/g dw). F. oxysporum also enhanced the hairy root growth resulting into the higher biomass yield of D3 (50 %) and D2 (76 %) in comparison to control non elicited hairy root clones of D3 and D2, respectively leading to higher pyrethrin yield.

Patho-physiological evaluation of Duranta erecta for the treatment of urolithiasis - Agawane, S. B.; Gupta, V. S.; Kulkarni, Mahesh J.; Bhattacharya, A. K.; Koratkar, Santosh; Rao, Vankudoth Koteswara (Journal of Ayurveda and integrative medicine, 2018)
Background: Urolithiasis is the third common disorder of the urinary system affecting 10-15% of the general population. In recent years, search for new antilithiatic drugs from natural sources has assumed greater importance. Objectives: This study was performed to investigate the anti-urolithiatic activity of methanolic extract of Duranta erecta leaves by in vitro and in vivo analysis. Materials and methods: The study was designed to determine presence of phytochemicals in D. erecta, its yield in percentage, antioxidant activity against 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and anti-microbial property against few bacteria. In vitro analysis was carried out study anti-urolithiatic property of D. erecta by nucleation assay and synthetic urine assay for inhibition of calcium oxalate and calcium oxalate monohydrate crystals formation. An in vivo experiment was performed on Wistar rats for confirmation of anti-urolithiatic property of D. erecta in animal model. Results: D. erecta has the presence of primary and secondary metabolites like glycoside, saponins, sterols, flavonoids, phenols, tannins, alkaloids, carbohydrates and proteins. Methanolic extract of D. erecta gave a very good yield (60%). D. erecta proved its antioxidant potential by 93.51% inhibition of DPPH radical at a concentration of 1000 μg/mL where ascorbic showed 94.71% of DPPH radical at the same concentration. In vitro tests like nucleation assay and synthetic urine assay showed that D. erecta inhibits formation of calcium oxalate and calcium oxalate monohydrate crystals. It also showed the anti-microbial property by formation of zone of inhibition against few bacteria. An in vivo experiment on Wistar rat animal model confirmed the anti-urolithiatic property of D. erecta L. leaves extract. Conclusions: Based on the results, we reported that D. erecta may treat calcium oxalate crystal deposition in the kidney by preventing hyperoxaluria-induced peroxidative damage to the renal tubular membrane surface (lipid peroxidation). It has anti-microbial potential so it may also inhibit the secondary bacterial infection in kidney. Based on the data, it can be concluded that this herb can be used as a potential anti-urolithiasis agent for kidney stone removal.

Pd(II)-Catalyzed gamma-C(sp(3))-H alkynylation of amides: selective functionalization of R chains of amides (RC)-C-1(O)NHR - Landge, Vinod G.; Parveen, Ayisha; Nandakumar, Avanashiappan; Balaraman, Ekambaram (Chemical Communications, 2018)
The gamma C(sp(3))-H bond alkynylation of R chains of amides (RC)-C-1(O)NHR, a fundamental class of synthetic substrates, has not been accomplished to date. Here, the first example of palladium(ii)-catalyzed alkynylation of an unactivated gamma C(sp(3))-H bond of alkyl amides (cyclic, linear, and amino acids) is reported. The kinetic experiment shows that the rate of the reaction depends on the coupling partners and the amides. Late-stage diversification of alkynylated amides was developed by utilizing amine and alkyne functionalities.

Perspectives on leishmania species and stage-specific adaptive mechanisms - Subramanian, Abhishek; Sarkar, Ram Rup (Trends In Parasitology, 2018)
The hurdles in drug and vaccine development pipelines for leishmaniasis, a complex, multifaceted disease, are largely due to the digenetic lifecycle, differential clinical manifestations of the parasite, and the incomplete understanding of its adaptations within its hosts. Here, we discuss the distinct computational and experimental techniques employed to identify the species and stage-specific adaptive mechanisms at different levels of biological organization, the progress made so far, and limitations in comprehending leishmaniasis as a systems biology disease. Based on the available perspectives, we also provide suggestions and requirements to tackle the growing challenges for bridging the genotype with the phenotype. A systems perspective can be instrumental in understanding the complexities of the disease and can provide insights for targeted control.

pH- and time-resolved in situ SAXS study of self-assembled twisted ribbons formed by elaidic acid sophorolipids - Dhasaiyan, Prabhu; Prevost, Sylvain; Baccile, Niki; Prasad, Bhagavatula L. V. (Langmuir, 2018)
Conditions that favor the helical structure formation in structurally similar sophorolipids (SLs), that is, elaidic acid SLs (having a trans double bond between the C9 and C10 positions of the alkyl chain) and stearic acid SLs (no double bond), are presented here. The helical self-assembled structures formed by elaidic acid SLs were independent of pH and also were mediated by a micellar intermediate. On the other hand, the stearic acid SLs formed helical structures under low pH condition only. Astonishingly, the formation routes were found to be different, albeit the molecular geometry of both SLs is similar. Even if a conclusive mechanistic understanding must await further work, our studies strongly point out that the noncovalent weak interactions in elaidic acid SLs are able to overcome the electrostatic repulsions of the sophorolipid carboxylate groups at basic pH and facilitating the formation of helical structures. On the other hand, the hydrophobic interactions in stearic acid SLs endow the helical structures with extra stability, making them less vulnerable to dissolution upon heating.

pH dependent sophorolipid assemblies and their influence on gelation of silk fibroin protein - Dubey, Parul; Kumar, Sugam; Ravindranathan, Sapna; Vasudevan, Sahana; Aswal, Vinod K.; Rajamohanan, Pattuparambil R.; Nisal, Anuya; Prabhune, Asmita (Materials Chemistry and Physics, 2018)
Sophorolipid (SL), a bio-derived surfactant is an excellent gelling agent for natural fibrous protein, silk fibroin (SF) leading to potential biomedical applications. Interaction of SF with SL has been shown to accelerate the formation of hydrogel with the rate being dependent on the form of SL used. Here, we examine the effect of pH on SL-SF interaction and gel formation by employing rheology, fluorescence spectroscopy, SANS and NMR. The results indicate that the size of SL assemblies decrease as pH increases from acidic to alkaline and significantly impacts the association of SL and SF. The association of SF and SL is mainly via hydrophobic interactions, with the SL molecules forming bead like structures along the SF chain. The increased charge on the acidic form of SL at higher pH results in greater repulsion between acidic SL molecules, which are bound to the hydrophobic sites of SF, leading to rapid chain unfolding and subsequent gelation. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Assemblies; Nuclear magnetic resonance spectroscopy; pH; Silk fibroin; Small angle neutron scattering; Sophorolipid

Pharmaceutical standardization and physicochemical characterization of traditional ayurvedic marine drug: incinerated conch shell (shankha bhasma) - Chavan, Sandeep; Tayade, Sonali; Gupta, Vidya; Deshmukh, Vineeta; Sardeshmukh, Sadanand (Marine Drugs, 2018)
Natural resources such as plants, animals and minerals have always been used by mankind to develop drugs and marine world is no exception. Marine by-products like conches, pearls, mother of pearl shells, corals and so forth have been used by traditional Ayurvedic practitioners for centuries. The unique methods of these preparations are scientifically designed to eliminate unwanted impurities and convert them into bioavailable form. In this study, Conch (Xanchus pyrum) was used as a marine resource of calcium carbonate and was converted pharmaceutically from its aragonite form to calcite. All the steps of preparations and changes in the properties therein were documented and validated. Further, traditional as well as modern analytical tools were used to study its physical and chemical characters to develop a monograph. The physical characterization included particle size, X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), Thermogravimetric Analysis (TGA) and Fourier Transform Infra-red (FTIR). Metal composition and heavy metal limits were determined using Inductively Coupled Plasma Optical Emission Spectrometry (ICPOES). This study revealed the rearrangement of aragonite crystals into calcite form by grinding, trituration with aloe vera juice and incineration under controlled conditions. Moreover, the finished product was found to be devoid of organic matrix that is nacre. This study creates a foundation for the development of a master formula for commonly used Shankha Bhasma in Ayurvedic medicines.

Phase diagram of self-assembled sophorolipid morphologies from mesoscale simulations - Sarkar, Sujit; Chakraborty, Souvik; Roy, Sudip (Journal of Molecular Liquids, 2018)
We have constructed a phase diagram from the self-assembled morphologies of linolenic acid sophorolipid in water by performing mesoscale simulations in different concentrations. The dependence of morphologies and its properties of the self-assembled structure as a function of the concentration of bolaamphiphile in water are investigated. Two hydrophilic head groups and one hydrophobic tail group of bolaamphiphile have been mapped to beads for mesoscale simulation. The interaction parameters between different beads are calculated using Flory-Huggins solution theory. Flory-Huggins x-parameters have been calculated from atomistic simulation and experimental data of pure components constituting linolenic acid sophorolipid. We have obtained different self-assembled morphologies depending upon the concentrations of sophorolipid in water. We have explored the arrangements of hydrophobic and hydrophilic groups of the sophorolipid chains in the different morphologies. The sophorolipid chains found to be present in different structural arrangements. The residence time and flip frequency of these lipids in different orientations have been calculated and discussed in this work. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Bolaamphiphile; Flip frequency; Mesoscale simulation; Orientation of chains; Self-assembly

pH-dependent speciation and hydrogen (H-2) control U(VI) respiration by Desulfovibrio vulgaris - Kushwaha, Shilpi; Marcus, Andrew K.; Rittmann, Bruce E. (Biotechnology and Bioengineering, 2018)
In situ bioreduction of soluble hexavalent uranium U(VI) to insoluble U(IV) (as UO2) has been proposed as a means of preventing U migration in the groundwater. This work focuses on the bioreduction of U(VI) and precipitation of U(IV). It uses anaerobic batch reactors with Desulfovibrio vulgaris, a well-known sulfate, iron, and U(VI) reducer, growing on lactate as the electron donor, in the absence of sulfate, and with a 30-mM bicarbonate buffering. In the absence of sulfate, D. vulgaris reduced >90% of the total soluble U(VI) (1mM) to form U(IV) solids that were characterized by X-ray diffraction and confirmed to be nano-crystalline uraninite with crystallite size 2.8 +/- 0.2nm. pH values between 6 and 10 had minimal impact on bacterial growth and end-product distribution, supporting that the mono-nuclear, and poly-nuclear forms of U(VI) were equally bioavailable as electron acceptors. Electron balances support that H-2 transiently accumulated, but was ultimately oxidized via U(VI) respiration. Thus, D. vulgaris utilized H-2 as the electron carrier to drive respiration of U(VI). Rapid lactate utilization and biomass growth occurred only when U(VI) respiration began to draw down the sink of H-2 and relieve thermodynamic inhibition of fermentation.

Phenazine-containing poly(phenylenevinylene): a new polymer with impressive field emission properties - Chhatre, Shraddha; Ichake, Amol; Harpale, Kashmira; Patil, Sumati; Deshpande, Aparna; More, Mahendra; Wadgaonkar, Prakash P. (Journal of Polymer Research, 2018)
Phenazine-containing poly(phenylenevinylene) (P(PHN-PV)) was synthesized using Wittig-Horner polycondensation of the appropriately designed monomers viz. 5,10-dioctyl-5,10-dihydrophenazine-2,7-dicarbaldehyde and tetraethyl ((2,5-bis((2-ethylhexyl) oxy)-1,4 phenylene) bis(methylene)) bis(phosphonate). The design embraces the specific motivation of incorporating the nitrogen-containing heterocycle viz. .phenazine in poly(phenylenevinylene) backbone. P(PHN-PV) exhibited reversible redox properties. In the field emission measurements performed on the film of P(F'HN-PV), the turn-on field was observed to be 1.93 V/mu m for the current density of 10 mu A/cm(2). The maximum current density of similar to 4.87 mA/cm(2) was achieved at the applied field of 3.84 V/mu m. The emission current showed impressive stability for 6 h at a constant current of 1 mu A (current density of about 20 mu A/cm(2)). These results emphasize the role of phenazine heterocycle with lone pair of electrons on nitrogen in lowering the oxidation onset and in turn reduction of the turn-on voltage.
Keywords: field emission; Phenazine; Poly(phenylenevinylene)

Phosphine-free cobalt pincer complex catalyzed Z-selective semi-hydrogenation of unbiased alkynes - Landge, Vinod G.; Pitchaimani, Jayaraman; Midya, Siba P.; Subaramanian, Murugan; Madhu, Vedichi; Balaraman, Ekambaram (Catalysis Science & Technology, 2018)
Herein, we report a novel, molecularly defined NNN-type cobalt pincer complex catalyzed transfer semi-hydrogenation of unbiased alkynes to Z-selective alkenes. This unified process is highly stereo-and chemo-selective and exhibits a broad scope as well as wide functional group tolerance. Ammonia-borane (AB), a bench-stable substrate with high gravimetric hydrogen capacity, was used as a safe and practical transfer hydrogenating source.

Photocatalysis enabling acceptorless dehydrogenation of diaryl hydrazines at room temperature - Sahoo, Manoj K.; Saravanakumar, Krishnasamy; Jaiswal, Garima; Balaraman, Ekambaram (ACS Catalysis, 2018)
Aromatic azo compounds are privileged structural motifs, and they exhibit a myriad of pharmaceutical as well as industrial applications. Here, we report a catalytic acceptorless dehydrogenation of diarylhydrazine derivatives to access a wide variety of aryl-azo compounds with the removal of molecular hydrogen as the sole byproduct. This distinctive reactivity has been achieved under dual catalytic conditions by merging the visible-light active [Ru(bpy)(3)](2+) as the photoredox catalyst and Co(dmgH)(2)(py)Cl as the proton-reduction catalyst. The reaction proceeds smoothly under very mild and benign conditions and operates at ambient temperature. This dual catalytic approach is highly compatible with many different functional groups and has a broad substrate scope. We have also demonstrated the reversible hydrogen storage and release phenomenon on hydrazobenzene/azobenzene couple to show the utility of these compounds as hydrogen storage materials. Further diversification of azobenzene was shown by a transition metal-catalyzed azo-group-directed ortho-C-H bond functionalization.
Keywords: acceptorless dehydrogenation; Azo benzene; dual catalysis; Hydrogen; photoredox catalysis

Photo-induced surface modification to improve the performance of lead sulfide quantum dot solar - Tulsani, Srikanth Reddy; Rath, Arup Kumar (Journal of Colloid and Interface Science, 2018)
The solution-processed quantum dot (QD) solar cell technology has seen significant advancements in recent past to emerge as a potential contender for the next generation photovoltaic technology. In the development of high performance QD solar cell, the surface ligand chemistry has played the important role in controlling the doping type and doping density of QD solids. For instance, lead sulfide (PbS) QDs which is at the forefront of QD solar cell technology, can be made n-type or p-type respectively by using iodine or thiol as the surfactant. The advancements in surface ligand chemistry enable the formation of p-n homojunction of PbS QDs layers to attain high solar cell performances. It is shown here, however, that poor Fermi level alignment of thiol passivated p-type PbS QD hole transport layer with the n-type PbS QD light absorbing layer has rendered the photovoltaic devices from realizing their full potential. Here we develop a control surface oxidation technique using facile ultraviolet ozone treatment to increase the p-doping density in a controlled fashion for the thiol passivated PbS QD layer. This subtle surface modification tunes the Fermi energy level of the hole transport layer to deeper values to facilitate the carrier extraction and voltage generation in photovoltaic devices. In photovoltaic devices, the ultraviolet ozone treatment resulted in the average gain of 18% in the power conversion efficiency with the highest recorded efficiency of 8.98%. (C) 2018 Elsevier Inc. All rights reserved.

Photophysical studies on curcumin-sophorolipid nanostructures: applications in quorum quenching and imaging - Vasudevan, Sahana; Prabhune, Asmita A. (Royal Society Open Science, 2018)
Sophorolipid biosurfactants are biodegradable, less toxic and FDA approved. The purified acidic form of sophorolipid is stimuli-responsive with self-assembling properties and used for solubilizing hydrophobic drugs. This study encapsulated curcumin (CU) with acidic sophorolipid (ASL) micelles and analysed using photophysical studies like UV-visible spectroscopy, photoluminescence (PL) spectroscopy and timecorrelated single photon counting (TCSPC). TEM images have revealed ellipsoid micelles of approximately 100nm size and were confirmed by dynamic light scattering. The bacterial fluorescence uptake studies showed the uptake of formed CUASL nanostructures into both Gram-positive and Gram-negative bacteria. They also showed quorum quenching activity against Pseudomonas aeruginosa. The results have demonstrated this system has potential theranostic applications.
Keywords: curcumin; photophysical; Quorum quenching; Sophorolipid

Pioglitazone inhibits advanced glycation induced protein modifications and down-regulates expression of RAGE and NF-kappa B in renal cells - Adeshara, Krishna A.; Agrawal, Sanskruthi B.; Gaikwad, Sushama M.; Tupe, Rashmi S. (International Journal of Biological Macromolecules, 2018)
The present work aims to determine the effect of pioglitazone on in-vitro albumin glycation and AGE-RAGE induced oxidative stress and inflammation. Bovine serum albumin was glycated by methylglyoxal in absence or presence of pioglitazone. Glycation markers (fructosamine, carbonyl groups, (l-amyloid aggregation, thiol groups, bilirubin binding capacity and AOPP); protein conformational changes (native-PAGE and HPLC analysis) were determined. Cellular study was done by estimating antioxidants, ROS levels, expression profile of membrane RAGE, NF-kappa B and levels of inflammatory cytokines (IL-6, TNF-alpha) using HEK-293 cell line. We observed that levels of glycation markers were reduced at higher concentration of pioglitazone as compared to glycated albumin. Structural analysis of glycated albumin showed inhibition of protein migration and structural changes when treated with pioglitazone. Pioglitazone has potentially restored cellular antioxidants and reduced levels of IL-6 and TNF-alpha by declining expression of membrane RAGE and NF-kappa B. In conclusion, pioglitazone preferentially binds to protein and alleviates protein structural changes by maintaining its integrity. Additionally, it suppresses RAGE and NF-kappa B levels hence alleviate cellular oxidative stress and inflammation. (C) 2018 Elsevier B.V. All rights reserved.

Polycrystalline MnGe2 thin films on InAs(001) substrates - Gutierrez-Naranjo, David; Holguin-Momaca, Jose T.; Solis-Canto, Oscar O.; Gupta, Preeti; Poddar, Pankaj; Espinosa Magana, Francisco; Olive-Mendez, Sion F. (Thin Solid Films, 2018)
We report on the growth of MnGe2 thin films on InAs(001) substrates using radio frequency-magnetron cosputtering. Polycrystalline thin films were obtained at a substrate temperature of 353 K. X-ray diffractometry was used to identify the tetragonal MnGe2 phase (space group 14/mcm). Measurements of the magnetic field and temperature dependence of the magnetization revealed that the MnGe2 thin films are ferromagnetic with a magnetization of 280 kAm(-1) and a Curie temperature of 62 K. Additionally, an antiferromagnetic component is observed at low temperatures, which may arise atomic disorder at the grain boundaries between MnGe2 crystallites.

Polyethyleneglycol/silver functionalized Reduced graphene oxide aerogel for environmental application - Kumari, G. Vanitha; Asha, S.; Ananth, A. Nimrodh; Rajan, M. A. Jothi; Mathavan, T. (62nd Dae Solid State Physics Symposium, 2018)
Polyethylene glycol (PEG)/Silver (Ag) functionalized reduced graphene oxide aerogel (RGOA) was synthesized. PEG/Ag decorated reduced graphene oxide aerogel was characterized using XRD, Raman spectroscopy, Fourier transform infrared spectroscopy (FT-IR). The surface morphology of PEG/Ag/RGOA was analyzed using scanning electron microscope. The non-covalent interaction between reduced graphene oxide layers and the interaction between PEG and Ag on RGOA were studied by FT-IR spectra. It was observed that the interaction between Ag and PEG could enhance the properties of RGOA. Methyl Orange (MO) dye degradation was observed from UV-Vis Spectra. The process was studied by monitoring the simultaneous decrease in the height of UV-Vis absorption peak of dye solution. The results show that PEG/RGOA and PEG/Ag/RGOA are an efficient catalyst for dye degradation.

Polymer grafted smart mesoporous silica nanoparticles: challenges and advances in controlled drug delivery applications - Badiger, M. V.; Tiwari, N. (Nova Science Publishers, Inc., 2018)
The application of nanoparticles to intracellular drug delivery has attracted increasing attention in the last few decades. Among them, mesoporous silica nanoparticles (MSNs) have emerged as promising nanomaterials which have shown great potential towards incubation of both hydrophobic and hydrophilic drugs and their further internalization at the targeted site in physiological environment for the treatment of large number of diseases. Excellent properties of MSNs such as good stability control over morphology and tunable particle size and the pore structure gives them an edge over other organic or inorganic based nanoparticles. With these properties, there is a great scope in designing novel MSNs with functionalization at the surface as well as within the pores using biocompatible and biodegradable polymers, stimuli responsive groups, proteins etc. MSNs have shown great potential in biotechnological and biomedical applications. Efforts are also made to increase the biocompatibility and circulation time of drug loaded MSNs by coating various polymers onto the surface of MSNs. Extensive work on MSNs has been reported in the literature which is however scattered. In the present chapter, we have dealt with the advances made in MSNs as controlled and targeted drug delivery systems using either synthetic or natural polymers specifically towards cancer treatment.

Polysulfide-triggered fluorescent indicator suitable for super-resolution microscopy and application in imaging - Hoskere, Anila A.; Sreedharan, Sreejesh; Ali, Firoj; Smythe, Carl G.; Thomas, Jim A.; Das, Amitava (Chemical Communications, 2018)
A new physiologically benign and cell membrane permeable BODIPY based molecular probe, MB-S-n, specifically senses intracellular hydrogen polysulfides (H2Sn, n > 1) localized in the endoplasmic reticulum. This reagent is suitable for mapping the intracellular distribution of H2Sn by wide-field as well as super-resolution Structured Illumination Microscopy (SIM).

Population genetic structure of banana corm weevil Cosmopolites sordidus (Germar) in India - Sunil Kumar, L.; Singh, J. (Journal of asia-pacific entomology, 2018)
The population genetic structure of Cosmopolites sordidus (Germar), an economically important pest of bananas, was studied using the sequence data of the internal transcribed rDNA (ITS1+ITS2) and the mitochondrial ‘COI-tRNALeu-COII’ region from seventy nine individuals collected from six sampling locations in India. The ITS data revealed 70% within population variation and non-significant genetic differentiation estimates suggesting lack of phylogeographic sub-structuring. 49% within population variation and highly significant genetic differentiation values were obtained with the mitochondrial data. The Mantel test revealed lack of correlation between genetic and geographic distance with both the markers. Demographic expansion of the populations was confirmed by the star shaped haplotype networks, demographic tests and mismatch distribution curves using both the markers. Molecular diversity indices show a high haplotype diversity (Hd) but low nucleotide diversity (π) suggesting that the populations are closely related. Considering the low self-dispersal ability of the weevils, these results suggest that the range expansion of this banana pest in India has taken place mainly through transport of infested corms and plant material resulting in the weevils forming localised populations which are not genetically distinct from each other. The high gene diversity (Hd) has enabled the weevils to adapt to varying environmental conditions which could explain the range expansion of this pest in India. The observed discrepancy in the genetic differentiation estimates using these two markers can be attributed to the evolutionary dynamics of the nuclear and mitochondrial genomes.

Porosity prediction through hydrogen bonding in covalent organic frameworks - Karak, Suvendu; Kumar, Sushil; Pachfule, Pradip; Banerjee, Rahul (Journal of the American Chemical Society, 2018)
Easy and bulk-scale syntheses of two-dimensional (2D) covalent organic frameworks (COFs) represent an enduring challenge in material science. Concomitantly, the most critical aspect is to precisely control the porosity and crystallinity of these robust structures. Disparate complementary approaches such as solvothermal synthesis have emerged recently and are fueled in part by the usage of different modulators and acids that have enriched the COF library. Yet, the fundamental understanding of the integral processes of 2D COF assembly, induding their growth from nucleating sites and the origin of periodicity, is an intriguing chemical question that needs to be answered. To address these cardinal questions, a green and easy-to-perform approach of COF formation has been delineated involving acid-diamine salt precursors. The role of hydrogen bonding [d(av)(N-amine-H center dot center dot center dot O-acid); d(av) signifies the average N-amine-H center dot center dot center dot O-acid distances, i.e., the average distance from the H atom of the amine to the O atom of the acid] present in the acid-diamine salts in improving the COFs' crystallinity and porosity has further been decoded by thorough crystallographic analyses of the salt molecules. What is particularly noteworthy is that we have established the hydrogen-bonding distances d(av)(N-amine-H center dot center dot center dot O-acid) in the acid-diamine salts that are pivotal in maintaining the reversibility of the reaction, which mainly facilitates highly crystalline and porous COF formation. Moreover, this reactant-structure to the product-quality relationship has further been utilized for the synthesis of highly crystalline and porous COFs that are unattainable by other synthetic means.

Porous reduced graphene oxide modified electrodes for the analysis of protein aggregation. Part 2: Application to the analysis of calcitonin containing pharmaceutical formulation - Vasilescu, Alina; Ye, Ran; Boulahneche, Samia; Lamraoui, Sabrina; Jijie, Roxana; Medjram, Mohamed Salah; Gaspar, Szilveszter; Singh, Santosh K.; Kurungot, Sreekumar; Melinte, Sorin; Boukherroub, Rabah; Szunerits, Sabine (Electrochimica Acta, 2018)
In part 1 (A. Vasilescu et al., Porous reduced graphene oxide modified electrodes for the analysis of protein aggregation. Part 1: Lysozyme aggregation at pH 2 and 7.4 Electrochem. Acta, 254 (2017) 375 -383) we proposed porous reduced graphene oxide coated glassy carbon electrode (GC/prGO) in combination with differential pulse voltammetry as a new analytical tool for aggregation studies of proteins. Lysozyme was used as a model to follow its aggregation by electrochemical means at pH 2 and pH 7.4, leading to the formation of amyloid and amorphous aggregates, respectively. Part 2 of this work widens the scope of this approach by investigating a biopharmaceutical product, as the aggregation of peptide based drugs affects their therapeutic activity and can induce allergic reactions in patients. The salmon polypeptide calcitonin (sCT) was chosen as an example of a bioactive peptide with limited pharmaceutical potential due to a tendency to form cytotoxic aggregates and amyloid fibrils. For practical applications, screen printed electrodes (SPE) and flexible electrodes (FE) modified with polydiallyldimethylammonium (PDDA) and prGO by using the layer-by-layer deposition technique have been developed for the detection of sCT. The results indicate that these electrodes can differentiate between formation of amyloid aggregates of calcitonin (2 mg mL(-1)) in citrate buffer to no aggregation in acetate buffer. It was further demonstrated that these electrodes are able to analyze a pharmaceutical drug product of low potency, Miacalcic (8.3 mu g mL(-1)), where no aggregation was observed. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Calcitonin; Disposable electrodes; Electrochemistry; Porous reduced graphene oxide; Protein aggregation

Prediction of coal ash fusion temperatures using computational intelligence based models - Tambe, S.S.; Naniwadekar, M.; Tiwary, S.; Mukherjee, A.; Das, T. B. (International Journal of Coal Science and Technology, 2018)
In the coal-based combustion and gasification processes, the mineral matter contained in the coal (predominantly oxides), is left as an incombustible residue, termed ash. Commonly, ash deposits are formed on the heat absorbing surfaces of the exposed equipment of the combustion/gasification processes. These deposits lead to the occurrence of slagging or fouling and, consequently, reduced process efficiency. The ash fusion temperatures (AFTs) signify the temperature range over which the ash deposits are formed on the heat absorbing surfaces of the process equipment. Thus, for designing and operating the coal-based processes, it is important to have mathematical models predicting accurately the four types of AFTs namely initial deformation temperature, softening temperature, hemispherical temperature, and flow temperature. Several linear/nonlinear models with varying prediction accuracies and complexities are available for the AFT prediction. Their principal drawback is their applicability to the coals originating from a limited number of geographical regions. Accordingly, this study presents computational intelligence (CI) based nonlinear models to predict the four AFTs using the oxide composition of the coal ash as the model input. The CI methods used in the modeling are genetic programming (GP), artificial neural networks, and support vector regression. The notable features of this study are that the models with a better AFT prediction and generalization performance, a wider application potential, and reduced complexity, have been developed. Among the CI-based models, GP and MLP based models have yielded overall improved performance in predicting all four AFTs.

Preparation and investigations of ABPBI membrane for HT-PEMFC by immersion precipitation method - Chaudhari, Harshal D.; Illathvalappil, Rajith; Kurungot, Sreekumar; Kharul, Ulhas K. (Journal of Membrane Science, 2018)
Poly(2,5-benzimidazole) (ABPBI) membranes were prepared by an easy and benign 'immersion precipitation' method; alleviating drawbacks of conventional solution casting method involving evaporation of the corrosive solvent. The importance of varying inherent viscosity on the properties of resulting membranes was investigated. The porous membranes formed by immersion precipitation method were analyzed for basic properties (water flux, porosity and dimensional analysis). Since the dense structure is required for their applicability for a fuel cell, through-porosity of the formed membranes was successfully eliminated using a unique shrinkage (similar to 50%) property of ABPBI, initially, at 60 degrees C followed by at higher temperature. The correlation of membranes annealing temperature with the mechanical properties, phosphoric acid doping and proton conductivity was established. The present membranes exhibited high doping level (5.1 mol/RU), proton conductivity (0.083 S cm(-1)) and fuel cell performance. For comparison, solution casted membranes were prepared and analyzed. The OCP (0.91 V) and max power density (766mWcm(-2)) are quite promising features of this new type of membranes.

Preparation of colourless phosphate glass by stabilising higher Fe[II] in microwave heating - Mandal, Ashis K.; Mandal, B.; Illath, Kavya; Ajithkumar, T. G.; Halder, A.; Sinha, P. K.; Sen, Ranjan (Scientific Reports, 2018)
Iron impurity in raw material remains a major challenge in producing colourless glass. In this investigation, we report microwave (MW) heating capable of altering Fe-redox ratio (Fe2+/Sigma Fe) enabling preparation of colourless phosphate glass. The effect of Sn concentration in retention of Fe[II] in glass melted in MW was compared with conventional glasses. Colourimetric study developing Fe2+-ferrozine colour complex reveals Fe-redox ratio >= 0.49 required to obtain colourless phosphate glass. In microwave heating, addition of 1 wt.% Sn metal powder can impart the desired effect whereas addition of 1.9 wt.% Sn metal powder is required in conventional heating. The correlation equation of Fe-redox ratio with concentration of Sn metal is found to be different in microwave and conventional heating. Thus, exploiting this different redox changes in MW heating optical properties can be tailored. Preservation of higher Fe[II] in MW melted glass is also confirmed by XPS and TGA. P-31 MAS NMR spectra suggest that transition from cross linked ultra phosphate to linear polymer metaphosphate network in incorporation of Sn is found different in glass prepared adopting microwave irradiation. (27)A1 MAS NMR spectra suggest higher relative content of Al6+ in glass obtained from MW heating. Energy consumption analysis revels 3.4 kWh in MW heating while 14 kWh in conventional glass melting using resistance heating. Further, glass melting in MW can be completed within 2 h unlike similar to 5 h needed in conventional. MW heating plays a significant role in improving properties to make colourless phosphate glass in addition to significant energy and time saving.

Preparation of macroporous scaffolds with holes in pore walls and pressure driven flows through them - Chatterjee, Soumyajyoti; Potdar, Aditi; Kuhn, Simon; Kumaraswamy, Guruswamy (RSC Advances, 2018)
Controlling the pore architecture in macroporous scaffolds has important implications for their use as reactor packings and as catalyst supports. We report the preparation of a macroporous structure, where the pore walls are perforated by holes. These materials are prepared by modification of the ice-templating protocol developed in our group. We freeze a dispersion of colloidal silica, polymer and cross-linker in a water/acetonitrile medium and allow crosslinking to proceed in the frozen state. The presence of a small fraction of acetonitrile (varying between 1.6% to 6.4%) results in the formation of holes in the pore walls. Increasing the acetonitrile concentration changes the pore size distribution, and produces smaller pores on average. This also results in an increasing fraction of the wall area being covered by small pores, of the order of a few microns in size. Perforation of the walls by pores does not change the overall porosity or modulus of the scaffolds. However, the introduction of pores leads to a drastic reduction in the pressure drop required to pump liquid through the scaffolds. The observed residence time distribution (RTD) in the scaffolds is represented by two plug flow reactors (PFRs) in parallel. The RTD results indicate that increasing the hole fraction in the pore walls results in increased channelling which explains the aforementioned decreased pressure drop during pressure driven flow.

Preparation of metal oxide supported catalysts and their utilization for understanding the effect of a support on the catalytic activity - Seth, Jhumur; Dubey, Prashant; Chaudhari, Vijay R.; Prasad, Bhagavatula L. V. (New Journal of Chemistry, 2018)
A convenient way of anchoring transition metal nanoparticles (palladium, platinum, rhodium and ruthenium) onto metal oxide supports (magnesium oxide and zirconium oxide) by means of a modified sol-gel technique is demonstrated. Use of toluene dispersed, ligand protected pre-synthesized nanoparticles during sol-gel synthesis delivered size-controlled, spatially distributed, well-adhered transition metal nanoparticles (MNPs) on metal oxide supports. The catalytic activities of these supported nanoparticles were tested for the p-nitro phenol reduction reaction. It was observed that the reaction kinetics were crucially dependent on the catalyst support and MNP size. The influence of the magnesium oxide and zirconium oxide supports towards the catalytic performance of the anchored transition MNPs was probed using cyclic voltammetry and the differences in the same were attributed to the support-induced modification in the electronic properties of the MNPs. Our results indicated that magnesium oxide is a better support than zirconium oxide.

Pressure equalization approach for flow uniformity in microreactor with parallel channels - Madane, Ketan; Kulkarni, Amol A. (Chemical Engineering Science, 2018)
Numbering-up using parallel channels helps to achieve higher processing capacity while retaining the advantages of microreactors. However it may also lead to non-uniformity in flow across all the channels. Here we report the CFD simulations and experimental observations on the extent of uniformity in the flow from an assembly of several parallel channels. In the conventional parallel channel geometry, smaller channel size (<300 m) as well as higher fluid viscosity is seen to give better flow uniformity. Inequality in pressure distribution at the inlet of a large number of parallel channels is overcome by having two `pressure equalization slots' at an equal distance from inlet and outlets that open in the respective manifolds. Having such an arrangement helped to reduce the standard deviation in the flow by almost 90% when compared to the conventional geometry. However the modification was seen to increase the extent of back mixing to some extent. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: CFD; Experiments; Flow distribution; microreactor; Numbering-up; Parallel channels

Prion-like propagation of post-translationally modified tau in alzheimer's disease: a hypothesis - Sonawane, Shweta Kishor; Chinnathambi, Subashchandrabose (Journal of Molecular Neuroscience, 2018)
The microtubule-associated protein Tau plays a key role in the neuropathology of Alzheimer's disease by forming intracellular neurofibrillary tangles. Tau in the normal physiological condition helps stabilize microtubules and transport. Tau aggregates due to various gene mutations, intracellular insults and abnormal post-translational modifications, phosphorylation being the most important one. Other modifications which alter the function of Tau protein are glycation, nitration, acetylation, methylation, oxidation, etc. In addition to forming intracellular aggregates, Tau pathology might spread in a prion-like manner as revealed by several in vitro and in vivo studies. The possible mechanism of Tau spread can be via bulk endocytosis of misfolded Tau species. The recent studies elucidating this mechanism have mainly focussed on the aggregation and spread of repeat domain of Tau in the cell culture models. Further studies are needed to elucidate the prion-like propagation property of full-length Tau and its aggregates in a more intense manner in vitro as well as in vivo conditions. Varied post-translational modifications can have discrete effects on aggregation propensity of Tau as well as its propagation. Here, we review the prion-like properties of Tau and hypothesize the role of glycation in prion-like properties of Tau. This post-translationally modified Tau might have an enhanced propagation property due to differential properties conferred by the modifications.
Keywords: Alzheimer disease; Post-translational modifications of tau; Propagation of tau; Tau; Tauopathies

Process intensification strategies for enhanced holocellulose solubilization: Beneficiation of pineapple peel waste for cleaner butanol production - Khedkar, Manisha A.; Nimbalkar, Pranhita R.; Kamble, Sanjay P.; Gaikwad, Shashank G.; Chavan, Prakash V.; Bankar, Sandip B. (Journal of Cleaner Production, 2018)
Biorefinery sector has become a serious dispute for cleaner and sustainable development in recent years. In the present study, pretreatment of pineapple peel waste was carried out in high pressure reactor using various pretreatment-enhancers. The type and concentration effect of each enhancer on hemicellulose solubilization was systematically investigated. The binary acid (phenol + sulfuric acid) at 180 degrees C was found to be superior amongst other studied enhancers, giving 81.17% (w/v) hemicellulose solubilization in liquid-fraction under optimized conditions. Solid residue thus obtained was subjected to enzymatic hydrolysis that resulted into 24.50% (w/v) cellulose breakdown. Treated solid residue was further characterized by scanning electron microscopy and fourier transform infrared spectroscopy to elucidate structural changes. The pooled fractions (acid treated and enzymatically hydrolyzed) were fermented using Clostridium acetobutylicum NRRL B 527 which resulted in butanol production of 5.18 g/L with yield of 0.13 g butanol/g sugar consumed. Therefore, pretreatment of pineapple peel waste evaluated in this study can be considered as milestone in utilization of low cost feedstock, for bioenergy production. (C) 2018 Elsevier Ltd. All rights reserved.

Proline-catalyzed asymmetric -amination in the synthesis of bioactive molecules - Kumar, Pradeep; Sharma, Brijesh M. (Synlett, 2018)
The direct -amination of carbonyl compounds using organocatalysts represents a powerful and atom-economical tool for asymmetric C-N bond formation. We describe a complete account of -functionalization of carbonyl compounds, through iterative sequential -aminoxylation/amination using electrophilic O and N sources, as well as sequential -amination/HWE reaction for enantio- and diastereoselective synthesis of both syn - and anti -1,3-aminoalcohols and 1,3-diamines. Additionally this protocol is further extended for the easy construction of alkaloids such as indolizidine, pyrrolizidine, and quinolizidine fused-ring systems just by tuning the chain length of the aldehyde used as a starting material. This methodology provides further scope to extrapolate it for a variety of naturally occurring hydroxylated monocyclic and fused bicyclic pyrrolidine and piperidine based alkaloids such as lentiginosine, epi -lentiginosine, dihydroxypyrrolizidine, (+)-deoxoprosophylline and (-)-deoxoprosopinine alkaloids. Furthermore, we have also uncovered proline-catalyzed anti -selectivity for the synthesis of 1,2-amino alcohols in -amination of aldehyde and one-pot indium-mediated Barbier type allylation of -hydrazino aldehydes to accomplish the total synthesis of clavaminols, sphinganine and spisulosine with reduced number of steps and with high overall yields. 1 Introduction 2 Application in the Total Synthesis of Alkaloids 3 Conclusion

Proteomic study of endothelial dysfunction induced by Ages and its possible role in diabetic cardiovascular complications - Banarjee, Reema; Sharma, Akshay; Bai, Shakuntala; Deshmukh, Arati; Kulkarni, Mahesh J. (Journal of Proteomics, 2018)
Endothelial dysfunction is one of the primary steps in the development of diabetes associated cardiovascular diseases. Hyperglycemic condition in diabetes promotes accumulation of advanced glycation end products (AGEs) in the plasma, that interact with the receptor for AGEs (RAGE) present on the endothelial cells and negatively affect their function. Using Human umbilical vascular endothelial cells (HUVECs) in culture, the effect of glycated human serum albumin on global proteomic changes was studied by SWATH-MS, a label free quantitative proteomic approach. Out of the 1860 proteins identified, 161 showed higher abundance while 123 showed lesser abundance in cells treated with glycated HSA. Bioinformatic analysis revealed that the differentially regulated proteins were involved in various processes such as apoptosis, oxidative stress etc. that are associated with endothelial dysfunction. Furthermore, the iRegulon analysis and immunofuorescence studies indicated that several of the differentially regulated proteins were transcriptionally regulated by NF-kappa B, that is downstream to AGE-RAGE axis. Some of the important differentially regulated proteins include ICAM1, vWF, PAI-1 that affect important endothelial functions like cell adhesion and blood coagulation. qPCR analysis showed an increase in expression of the AGE receptor RAGE along with other genes involved in endothelial function. AGE treatment to HUVEC cells led to increased oxidative stress and apoptosis. This is the first proteomics study that provides insight into proteomic changes downstream to AGE-RAGE axis leading to endothelial dysfunction and predisposing to cardiovascular complications. Significance: Cardiovascular disease (CVD) is a major pathological outcome in diabetic patients and it is important to address ways that target its development before the onset. Elevated plasma AGEs in diabetes can affect endothelial function and can continue to show their effects even after blood glucose levels are back to normal. Since endothelial dysfunction acts as one of the initiating factors for the development of CVD, understanding how AGEs affect the endothelial cell proteome to cause dysfunction will provide insight into the mechanisms involved and aid designing new therapeutic approaches.

Pt - g-C3N4 - (Au/TiO2): electronically integrated nanocomposite for solar hydrogen generation - Devaraji, Perumal; Gopinath, Chinnakonda S. (International Journal of Hydrogen Energy, 2018)
A potential nanocomposite photocatalyst was designed by integrating Pt nanoclusters (co catalyst and electron sink) with graphitic carbon nitride (g-C3N4 (gcn)) (charge diffusion) and 0.5 wt % Au containing Au-TiO2 (AuT) (plasmonic on semiconductor) for solar water splitting (SWS). Variety of Pt-gcn-AuTiO2 compositions has been evaluated for SWS under one sun conditions. Complexity of the photocatalyst was increased systematically from Au-TiO2, gcn-TiO2 to Pt-gcn-Au-TiO2 to explore the influence of different combinations. Electronic integration of charge separation/diffusion component (gcn) with light absorbing sensitizer components (Au and gcn), and co-catalyst (Pt) seems to be the critical factor to improve hydrogen yield (HY) or overall efficiency. Although addition of gcn increase the HY of composites, there is no SWS activity observed on bare TiO2 or gcn. Au or Pt on gcn enhances the charge separation effectively and interface between Au and/or Pt with gcn works as the Schottky barrier. A monodispersion of Au over TiO2 and Pt nanoclusters over gcn/AuTiO2 composite lead to the maximum solar hydrogen yield (1.52 mmol/h g) with an apparent quantum yield (AQY) of 7.5%. Photoelectron and photoluminescence spectral studies confirm the electron transfer from Au to gcn, and Au and/or gcn to titania. A thorough physico-chemical investigation of various composites underscores the electronic integration aspects of the nanocomposite towards storage of electrons in the Pt co-catalyst and hence an effective charge separation and an increase in AQY. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Electronic integration; Photocatalysis; Schottky barrier; Solar hydrogen; water splitting

Paintable room-temperature phosphorescent liquid formulations of alkylated bromonaphthalimide - Goudappagouda; Manthanath, A.; Wakchaure, V. C.; Ranjeesh, K. C.; Das, T.; Vanka, K.; Nakanishi, T.; Babu, S. S. (Angewandte Chemie - International Edition, 2019)
Organic phosphors have been widely explored with an understanding that crystalline molecular ordering is a requisite for enhanced intersystem crossing. In this context, we explored the room‐temperature phosphorescence features of a solvent‐free organic liquid phosphor in air. While alkyl chain substitution varied the physical states of the bromonaphthalimides, the phosphorescence remained unaltered for the solvent‐free liquid in air. As the first report, a solvent‐free liquid of a long swallow‐tailed bromonaphthalimide exhibits room‐temperature phosphorescence in air. Doping of the phosphor with carbonyl guests resulted in enhanced phosphorescence, and hence a large‐area paintable phosphorescent liquid composite with improved lifetime and quantum yield was developed.

Palladium impregnated amine Co-condensed hexagonal mesoporous silica: a novel catalyst in tailoring suzuki and heck coupling reactions in base free condition - Das, Prangya Paramita; Prabhakaran, Vinod C.; Nanda, Samik; Sen, Debasis; Chowdhury, Biswajit (ChemistrySelect, 2019)
Palladium impregnated amine co-condensed hexagonal mesoporous silicas (HMS-X) were synthesized (sol-gel process) using different amines (Ethylene diamine and pyridine) of various concentrations (0.25 equiv. and 2 equiv.). The effect of amine concentration on the local structure of hexagonal mesoporous silica was studied. The catalyst shows excellent catalytic activity and high TOF towards both Suzuki and Heck coupling reactions without using any base in reaction medium with the solvent DMF:water in (1:1) ratio. The catalyst was reused and it was recyclable up to three cycle without any appreciable loss of activity and the kinetics of the reaction varying different parameters also have been studied thoroughly.
Keywords: Amine functionalized silica; Base free; Heck reaction; Palladium supported catalysts; Suzuki reaction

Partially bio-based aromatic poly(ether sulfone)s bearing pendant furyl groups: synthesis, characterization and thermo-reversible cross-linking with a bismaleimide - Nagane, Samadhan S.; Kuhire, Sachin S.; Mane, Shivshankar R.; Wadgaonkar, Prakash P. (Polymer Chemistry, 2019)
A fully bio-based bisphenol bearing pendant furyl group, viz., 4,4'-(furan-2-ylmethylene) bis(2-methoxyphenol) (BPF) was synthesized by base-catalyzed condensation of furfural with guaiacol. New partially bio-based (co) poly(ether sulfone) s bearing pendant furyl groups were synthesized via aromatic nucleophilic substitution polycondensation of BPF and various mixtures of BPF and bisphenol-A with bis(4-fluorophenyl) sulfone in N, N-dimethylacetamide as a solvent. (Co) poly(ether sulfone) s showed inherent viscosities in the range 0.92-1.47 dL g(-1) and number average molecular weights ((M-n) over bar), obtained from GPC, were in the range 91 300-131 000 g mol(-1). (Co) poly(ether sulfone) s could be cast into tough, transparent and flexible films from chloroform solutions. (Co)poly(ether sulfone)s showed 10% weight loss in the temperature range 431-481 degrees C and DSC showed T-g in the range 179-190 degrees C. Tensile strength, Young's modulus and elongation at break, obtained from tensile testing of (co) poly(ether sulfone) s containing pendant furyl groups, were in the range 76.7-83.8 MPa, 1.02-1.18 GPa and 21.4-89.7%, respectively. Most interestingly, pendant furyl groups in (co) poly(ether sulfone) s provide reactive sites for click modification and cross-linking via Diels-Alder reaction with maleimides and bismaleimides, respectively. Crosslinked (co) poly(ether sulfone) was prepared via Diels-Alder reaction of a representative (co) poly(ether sulfone) containing pendant furyl groups with 1,1'-(methylenedi-1,4-phenylene) bismaleimide (BMI) at 60 degrees C. The formation of cross-linked poly(ether sulfone) was demonstrated by gelation tests, solubility tests and DSC. The cross-linked copoly(ether sulfone) prepared using BMI showed enhanced tensile strength and Young's modulus compared to parent copoly(ether sulfone) and was recycled two times with retention of mechanical properties.

Pathways to defense metabolites and evading fruit bitterness in genus Solanum evolved through 2-oxoglutarate-dependent dioxygenases - Cardenas, Pablo D.; Sonawane, Prashant D.; Heinig, Uwe; Jozwiak, Adam; Panda, Sayantan; Abebie, Bekele; Kazachkova, Yana; Pliner, Margarita; Unger, Tamar; Wolf, Dalia; Ofner, Itai; Vilaprinyo, Ester; et al. (Nature Communications, 2019)
The genus Solanum comprises three food crops (potato, tomato, and eggplant), which are consumed on daily basis worldwide and also producers of notorious anti-nutritional steroidal glycoalkaloids (SGAs). Hydroxylated SGAs (i.e. leptinines) serve as precursors for leptines that act as defenses against Colorado Potato Beetle (Leptinotarsa decemlineata Say), an important pest of potato worldwide. However, SGA hydroxylating enzymes remain unknown. Here, we discover that 2-OXOGLUTARATE-DEPENDENT-DIOXYGENASE (2-ODD) enzymes catalyze SGA-hydroxylation across various Solanum species. In contrast to cultivated potato, Solanum chacoense, a widespread wild potato species, has evolved a 2-ODD enzyme leading to the formation of leptinines. Furthermore, we find a related 2-ODD in tomato that catalyzes the hydroxylation of the bitter a-tomatine to hydroxytomatine, the first committed step in the chemical shift towards downstream ripening-associated non-bitter SGAs (e.g. esculeoside A). This 2-ODD enzyme prevents bitterness in ripe tomato fruit consumed today which otherwise would remain unpleasant in taste and more toxic.

Phase transfer ceria-supported nanocatalyst for nitrile hydration reaction - Gupta, Nikitra N.; Punekar, Amrin S.; Raj, Karthik Raja E. K.; Ghodekar, Medha M.; Patil, Vipul S.; Gopinath, Chinnakonda S.; Raja, Thirumalaiswamy (ACS Omega, 2019)
The present study elaborates the catalytic effect of rare-earth metal oxides (Sm2O3 and La2O3) over ceria as a support phase transfer catalyst. The synthesized catalysts have been subjected to different characterization techniques, such as field-emission scanning electron microscopy, high-resolution transmission electron microscopy, powder X-ray diffraction, N-2 adsorption-desorption (BET surface analysis), temperature-programmed desorption study (NH3/CO2-TPD), Fourier transform infrared, Raman analysis, and X-ray photoelectron spectroscopy to get better insights into the catalytic activity of the catalysts for hydration of nitrile.

Phosphite-Catalyzed C-H allylation of azaarenes via an enantioselective [2,3]-Aza-wittig rearrangement - Motaleb, Abdul; Rani, Soniya; Das, Tamal; Gonnade, Rajesh G.; Maity, Pradip (Angewandte Chemie-International Edition, 2019)
A phosphite-mediated [2,3]-aza-Wittig rearrangement has been developed for the regio- and enantioselective allylic alkylation of six-membered heteroaromatic compounds (azaarenes). The nucleophilic phosphite adducts of N-allyl salts undergo a stereoselective base-mediated aza-Wittig rearrangement and dissociation of the chiral phosphite for overall C-H functionalization of azaarenes. This method provides efficient access to tertiary and quaternary chiral centers in isoquinoline, quinoline, and pyridine systems, tolerating a broad variety of substituents on both the allyl part and azaarenes. Catalysis with chiral phosphites is also demonstrated with synthetically useful yields and enantioselectivities.

Photo sensor based on 2D materials - Late, Dattatray J.; Bhat, Anha; Rout, Chandra Sekhar (Fundamentals and Sensing Applications of 2D Materials, 2019)
This chapter starts with a general introduction to the interaction of light with matter and use of this principle for sensing. Photo-sensing devices based on two-dimensional (2D) materials are compared to conventional designs and their respective differences discussed in detail. A range of 2D materials are introduced with a generic comparison based on their individual properties and importance to the generation of a photoresponse. Besides transition-metal dichalcogenides, the chapter also deals with black phosphorous photosensor devices. Different heterostructure architectures based on 2D layered structures are investigated and their role in next generation optoelectronics is discussed.

Photoexcited toluidine blue inhibits tau aggregation in Alzheimer's disease - Dubey, Tushar; Nalini, Gorantla Vijay; Chandrashekara, Kagepura Thammaiah; Chinnathambi, Subashchandrabose (Acs Omega, 2019)
The aggregates of microtubule-associated protein Tau are considered as a major hallmark of Alzheimer's disease. Tau aggregates accumulate intracellularly leading to neuronal toxicity. Numerous approaches have been targeted against Tau protein aggregation, which include application of synthetic and natural compounds. Toluidine blue is a basic dye of phenothiazine family, which on irradiation with a 630 nm light gets converted into a photoexcited form, leading to generation of singlet oxygen species. Methylene blue is the parent compound of toluidine blue, which has been reported to be potent against tauopathy. In the present work, we studied the potency of toluidine blue and photoexcited toluidine blue against Tau aggregation. Biochemical and biophysical analyses using sodium dodecyl sulfate-polyacrylamide gel electrophoresis, ThS fluorescence, circular dichroism spectroscopy, and electron microscopy suggested that toluidine blue inhibited the aggregation of Tau in vitro. The photoexcited toluidine blue potentially dissolved the matured Tau fibrils, which indicated the disaggregation property of toluidine blue. The cell biology studies including the cytotoxicity assay and reactive oxygen species (ROS) production assay suggested toluidine blue to be a biocompatible dye as it reduced ROS levels and cell death. The photoexcited toluidine blue modulates the cytoskeleton network in cells, which was supported by immunofluorescence studies of neuronal cells. The studies in a UAS Tau E14 transgenic Drosophila model suggested that photoexcited toluidine blue was potent to restore the survival and memory deficits of Drosophila. The overall finding of our studies suggested toluidine blue to be a potent molecule in rescuing the Tau-mediated pathology by inhibiting its aggregation, reducing the cell death, and modulating the tubulin levels and behavioral characteristics of Drosophila. Thus, toluidine blue can be addressed as a potent molecule against Alzheimer's disease.

pH-responsive “supra-amphiphilic” nanoparticles based on homoarginine polypeptides - Praveen, Korra; Das, Soumen; Dhaware, Vinita; Pandey, Bhawana; Mondal, Basudeb; Sengupta, Sayam (ACS Applied Bio Materials, 2019)
pH-responsive “supra-amphiphiles” based on double hydrophilic, positively charged block copolypeptides such as PEG-b-poly-l-lysine together with low molecular weight stimuli-sensitive partners that contain phosphate and carboxylate groups have been widely studied. In contrast, the other widely used cationic polypeptide poly-l-arginine whose cell-penetrating properties are well-known has been much less explored for the synthesis of supra-amphiphile-based nanomaterials. It is also known that the guanidine side chain of arginine binds to carboxylate anions with binding constants that are 2.5 times higher than the corresponding amines of poly-l-lysine. Here, we demonstrate the fabrication of pH-sensitive supra-amphiphilic nanoparticles by simple mixing of PEG2k-b-poly(homoarginine) block copolymer and carboxylic acid containing functional low molecular weight organic compounds. A high yielding three-step methodology was developed for the synthesis of ε-N,N′-di-Boc-l-homoarginine-α-N-carboxyanhydride which was polymerized using amine-terminated PEG (2000 MW) to yield 100% guanine-functionalized polypeptide (PEG2k-b-PHR30) with controlled molecular weights and low PDIs. Incubation of PEG2k-b-PHR30 with four different carboxylic acids (including dexamethasone a glucocorticoid receptor used in cancer therapy) in water leads to the formation of “supra-amphiphilic” nanoparticles (<200 nm size) due to the charge neutralization resulting from the strong interaction between the guanidine group and the carboxylate group. All these nanoparticles were able to encapsulate the hydrophobic dye Nile red with varying efficiency. Although these assemblies were stable at neutral pH, upon lowering the pH of the solution between 4 and 5, the protonation of the carboxylic acids leads to disassembly of these nanoparticles. The cytotoxicity of all four “supra-amphiphilic” nanoparticles varied depending on the carboxylic acid used for their fabrication. While the nanoparticle formed using dioctylbenzoic acid displayed 80% cell viability at concentration of 60 μg/mL, those formed with the steroid deoxycholic acid or dexamethasone showed only 40% cell viability at similar concentrations. Colocalization studies performed using epifluorescence microscopy demonstrate the successful uptake of intact dye-encapsulated nanoparticle inside the cell.

Phytochemical profile, anti-oxidant, anti-inflammatory, and anti-proliferative activities of Pogostemon deccanensis essential oils - Kumar, Vinay; Shriram, Varsha; Bhagat, Rani; Khare, Tushar; Kapse, Shivanjali; Kadoo, Narendra (3 Biotech, 2019)
Essential oils (EOs) obtained from aerial parts of Pogostemon deccanensis were analyzed for GC-MS profiling, and evaluated for antioxidant, anti-inflammatory, and anti-proliferative activities. GC-MS analysis revealed a total of 47 constituents, establishing the EOs rich in sesquiterpene with >20 sesquiterpenes constituting around 77% of the total EO yield. Major constituents included Curzerene (Benzofuran, 6-ethenyl-4,5,6,7-tetrahydro-3,6-dimethyl-5-isopropenyl-, trans-) (26.39%) and epi-Cadinol (22.68%), Ethanone, 1-(2,4,6-trihydroxyphenyl) (6.83%, Acetophenones), and Boldenone (3.47%, anabolic steroid). EOs found to be rich in phytochemicals attributed for antioxidant potentials of aromatic/medicinal plants, viz., flavonoids (2.71 mu g quercetin equivalents g(-1) EO), total phenols (3.94 mu g gallic acid equivalents (GAE) g(-1) EO), carotenoids (14.3 mu g -carotene equivalents g(-1) EO), and ascorbic acid (2.21 mu g ascorbic acid equivalents g(-1) EO). P. deccanensis EOs exhibited striking antioxidant activities assessed by wide range of assays including ferric reducing antioxidant potential (FRAP, 255.3 GAE at 2 mu g mL(-1) EO), total antioxidant activity (TAA, 264.3 GAE at 2 mu g ml(-1)) of EO, DPPH (65% inhibition at 2 mu g mL(-1)), and OH (58% inhibition at 2 mu g mL(-1)) scavenging. Interestingly, EOs showed considerably higher anti-lipid peroxidation activity than the standard antioxidant molecule ascorbic acid, with 50% protection by 1.29 mu g mL(-1) EO against 20.0 mu g mL(-1) standard. EOs showed strong anti-inflammatory activity with 50% inhibition at 1.95 mu g mL(-1) EO. The anti-proliferative activity of EOs was tested against mouse cancer cell line and the EOs proved a potent anti-proliferative agent with only 2.1% cell survival at 2 mu g mL(-1) EO, whereas the EOs were largely non-toxic-to-normal (non-cancerous) cells with approximately 80% cell survival at the 2 mu g mL(-1) EOs. This being the first attempt of phytochemical profiling and wide array of biological activities of P. deccanensis EOs holds significance as the striking activities were observed at very low concentrations, in some cases at lower than the commercial standards, and has, therefore, great potential for pharmaceutical or commercial exploration.
Keywords: Anti-inflammatory activity; Anti-proliferative activity; Antioxidants; Cytotoxicity; Essential oils

Phyto-inspired cyclic peptides derived from plant Pin-II type protease inhibitor reactive center loops for crop protection from insect pests - Sailthedkar, Nidhi S.; Joshi, Rakesh S.; Yadav, Amit K.; Seal, Shubhendu; Fernandes, Moneesha; Giri, Ashok P. (Biochimica ET Biophysica Acta-General Subjects, 2019)
Background: Natural defence of plants against insect pests involves protease inhibitors (PIs) that interfere with insect digestive proteases. Pin-II type plant PIs are wound inducible upon insect damage and possess multiple inhibitory repeat domains that can inhibit trypsin and chymotrypsin-like proteases in the insect midgut. Yet, their agricultural ex-vivo application is limited due to large molecular size and environmental instability, which could be overcome by small peptides. Methods: Bicyclic peptides were designed by grafting Pin-II PIs derived reactive center loop (RCL) on synthetic tris(bromomethyl)benzene scaffold. In vitro binding with trypsin-like proteases was evaluated by biochemical and biophysical assays, followed by molecular dynamics simulations. In vivo effects on two major lepidopteran insect pests, Helicoverpa armigera and Spodoptera litura were studied upon feeding with peptide treated leaves. Affinity based pull down assays were used to identify target proteins in insect gut. Results: Bicyclic RCLs showed ten-fold enhanced protease inhibition compared to their linear counterparts. They exhibited feeding deterrence and growth reduction of lepidopteran insects. Bicyclic peptides predominantly interact with midgut serine proteases. Possible binding modes involve simultaneous interaction with the active site and specificity-determining residues of insect gut trypsin. Conclusion: Bicyclic peptides are potent inhibitors of serine proteases in the insect midgut. They cause feeding aversion and larval growth retardation. Bi-domain cyclic peptides interact with two sites on trypsin, leading to enhanced efficacy over linear RCL peptides. General significance: Bicyclic peptides mimic natural PIs by inhibiting insect proteases leading to growth reduction, thus, could be used as pest control molecules in agriculture.
Keywords: Cyclic peptide; Lepidoptera; Pest control; protease inhibitor; Reactive loop

pi-Extended cis-configured unsynimetrical squaraine dyes for dye-sensitized solar cells: panchromatic response - Punitharasu, Vellimalai; Kavungathodi, Munavvar Fairoos Mele; Singh, Ambarish Kumar; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2019)
{Light absorbing sensitizer is the heart of the third generation photovoltaic technologies such as dye sensitized solar cells. Despite possessing large extinction coefficients for the metal-free organic dyes, the light harvesting efficiency is limited with the narrow absorption 20 profile in either visible or NIR regions of the solar spectrum. Though monolayer formation of organic sensitizers on semiconducting metal oxide surface leads to dye-dye interaction that leads to broadening the absorption profile, the contribution of the aggregated state to the power conversion process is found out to be poor. Here, we have engineered far-red active pi-extended cis-configured unsymmetrical squaraine dyes with carboxylic acid and cycnoacetic acid as anchoring groups with controlled aggregation and panchromatic light absorption by including the steric and electronic factors. The presence of sp(3)-C (out-of-plane) and N-alkyl (in-plane) groups played an important role in modulating the assembly of the dyes on the TiO2 electrode; the cis-squaraine unit helps to extend the conjugation in the NIR region besides enhancing the visible transition and the incident photon-to-current conversion efficiency profile that showed the importance of anchoring groups for the panchromatic response. Dye PSQ10 showed solar-to electric conversion with an onset of 850 nm with the device performance of 7.0% (V-oc = 0.581 V, J(sc) = 17.06 mA/cm(2)
Keywords: cis-squaraine dyes; Dye aggregation; Dye-sensitized solar cells; extended far-red absorption; panchromatic response

p-Nitrophenylcarbonates: a new class of compounds for chemodosimetric colorimetric fluoride anion sensing detectable by the naked eye - Yadav, Amit Kumar; Chilukuri, Harsha; Kumari, Linthoinganbi Raj; Karthikeyan, Muthukumarasamy; Fernandes, Moneesha (ChemistrySelect, 2019)
A new class of compounds containing the p-nitrophenylcarbonate motif is reported, that can selectively sense fluoride anions over other halide anions with a detection limit ranging from 0.29 to 0.48 mu M. The fluoride ion acts as nucleophile, leading to the liberation of p-nitrophenol, that is easily detectable and quantifiable colorimetrically.
Keywords: colorimetric sensing; p-nitrophenyl carbonate; selective fluoride detection

Polyesteramide of neem oil and its blends as an active nanomaterial for tissue regeneration - Killi, Naresh; Pawar, Anil Tukaram; Gundloori, Rathna V. N. (ACS Applied Bio Materials, 2019)
Neem oil gained importance due to its antibacterial properties. Therefore, it is extensively being used for various applications. Oils can be polymerized as a polyesteramide to extend their utility as biomaterials. In our studies, we synthesized polyesteramide from neem oil and various compositions of blends were prepared with the drug, chlorohexidine digluconate (CH) to develop a nanomaterial for tissue regeneration. The studies such as cytotoxicity, biodegradable, antibacterial, in vitro drug release, in vivo wound healing, and histopathological studies were performed to identify their potential for tissue regeneration. In vivo wound healing studies of the nanofiber mats with and without CH recorded a faster healing rate as compared to the commercial cream (povidone–iodine). Most importantly, there was no requirement of repeated application of nanofiber mats during the treatment. The histopathology studies also suggested the re-epithelialization of the wounds. Hence, these nanomaterials are considered to be environmentally safe scaffolds for efficient tissue regeneration applications.

Polyhydroxyalkanoates as biomaterials (vol 8, pg 1774, 2017) - Gadgil, Bhagyashri S. Thorat; Killi, Naresh; Rathna, Gundloori V. N. (MedChemComm, 2019)
Correction for `Polyhydroxyalkanoates as biomaterials' by Bhagyashri S. Thorat Gadgil et al., Med. Chem. Commun., 2017, 8, 1774-1787.

Polylactic acid: synthesis and biomedical applications - Singhvi, M. S.; Zinjarde, S. S.; Gokhale, D. V. (Journal of Applied Microbiology, 2019)
Social and economic development has driven considerable scientific and engineering efforts on the discovery, development and utilization of polymers. Polylactic acid (PLA) is one of the most promising biopolymers as it can be produced from nontoxic renewable feedstock. PLA has emerged as an important polymeric material for biomedical applications on account of its properties such as biocompatibility, biodegradability, mechanical strength and process ability. Lactic acid (LA) can be obtained by fermentation of sugars derived from renewable resources such as corn and sugarcane. PLA is thus an eco-friendly nontoxic polymer with features that permit use in the human body. Although PLA has a wide spectrum of applications, there are certain limitations such as slow degradation rate, hydrophobicity and low impact toughness associated with its use. Blending PLA with other polymers offers convenient options to improve associated properties or to generate novel PLA polymers/blends for target applications. A variety of PLA blends have been explored for various biomedical applications such as drug delivery, implants, sutures and tissue engineering. PLA and their copolymers are becoming widely used in tissue engineering for function restoration of impaired tissues due to their excellent biocompatibility and mechanical properties. The relationship between PLA material properties, manufacturing processes and development of products with desirable characteristics is described in this article. LA production, PLA synthesis and their applications in the biomedical field are also discussed.
Keywords: Biocompatible; biodegradable; drug delivery; implants; l- and d-lactic acid; polylactic acid

Polysaccharide hydrogel incorporated carbon nanofiber microelectrode for designing neural interfaces - Torris, Arun; Badiger, Manohar V. (Journal of Bionic Engineering, 2019)
Bionic devices are an integral part of human life, and continuous innovations in their design and functions with the help of nanotechnology has revolutionized the area of neuroscience and technology. Bio-interfaces play a key role in bionic devices such as neural implants for efficient transfer of the signal to smart prosthetics. We report here on the design of a new microelectrode, comprising Carbon Nanofiber (CNF) and a biopolymer, namely carboxymethyl xyloglucan (CMX) hydrogel inside the CNF, which enhances the current density across the interface. Microelectrode was prepared by in-situ cross-linking of CMX inside CNF, with optimized CMX: CNF ratio, resulting in continuous ionic channels confined within the hollow core of CNF. Electron microscopy images of microelectrodes illustrate the formation of CMX hydrogel network inside the CNF hollow core without wrapping its surface. The presence of hydrogel in the CNF was confirmed by Scanning Electron Microscope (SEM) and Transmission Electron Microscopy (TEM). The electrochemical studies indicate the enhancement in charge density as well as the active surface area of the microelectrodes due to the presence of CMX hydrogel network. These microelectrodes have great potential as neural interfaces for designing smart prosthetics with voluntary control.

Population balance-enabled model for batch and continuous crystallization processes - Pandit, Ajinkya; Bhambure, Rahul; Ranade, Vivek V. (Chemical Engineering in the Pharmaceutical Industry, 2019)
Crystallization is a critical unit operation in manufacturing of various active pharmaceutical ingredients and drugs. Irrespective of the large-scale use of crystallization in pharmaceutical manufacturing industry, crystallization is still considered as an art. Recently, quality by design (QbD) is gaining industry acceptance as an approach toward development and commercialization of the pharmaceutical drug molecules. In QbD, the unit operations and the process are designed and controlled to deliver specified quality attributes consistently. The proposed chapter is motivated by the necessity of the prediction of crystallization events like onset of the crystallization, nucleation, and growth during crystallization of active pharmaceutical ingredients. The chapter demonstrates the integrated use of population balance modeling framework for developing a fundamental understanding of the kinetic aspects of crystallization and correlating the developed understanding for scale-up and design for the crystallization processes. Efforts are made to discuss the impact of various critical process parameters like metastable zone width, scale effects, and residence time on crystal size during batch and continuous modes with the help of couple of case studies. The presented model and approach will be useful for implementing QbD for crystallizers.

Population genetic and phytochemical dataset of Saraca asoca: a traditionally important medicinal tree - Hegde, Satisha; Pai, Sandeep Ramchandra; Bhagwat, Rasika M.; Sainia, Archana; Rathore, Poonam Kanwar; Jalalpure, Sunil Satyappa; Hegde, Harsha Vasudev; Sugunan, Attayoor Purushottaman; Gupta, Vidya S.; Kholkute, Sanjiva D.; Roy, Subarna (Data in Brief, 2019)
The data presented in this article is in support of the research paper “Genetic and phytochemical investigations for understanding population variability of the medicinally important tree Saraca asoca to help develop conservation strategies” Hegde et al., 2018. This article provides PCR based Inter-Simple Sequence Repeat (ISSR) and HPLC datasets of 106 individual samples of Saraca asoca collected from various geographical ranges of the Western Ghats of India. The ISSR data includes information on genetic diversity and images of population structures generated through amplified DNA products from samples of Saraca asoca leaf. Phytochemical data obtained from HPLC includes concentration (mg/g) of gallic acid (GA), catechin (CAT), and epicatechin (EPI). The data also presents information obtained from various statistical analysis viz. standard error of the mean values, distribution variables, prediction accuracy, and multiple logistic regression analysis.

Porosity switching in polymorphic porous organic cages with exceptional chemical stability - Bera, Saibal; Dey, Kaushik; Pal, Tapan K.; Halder, Arjun; Tothadi, Srinu; Karak, Suvendu; Addicoat, Matthew; Banerjee, Rahul (Angewandte Chemie-International Edition, 2019)
Porous solids that can be switched between different forms with distinct physical properties are appealing candidates for separation, catalysis, and host-guest chemistry. In this regard, porous organic cages (POCs) are of profound interest because of their solution-state accessibility. However, the application of POCs is limited by poor chemical stability. Synthesis of an exceptionally stable imine-linked (4+6) porous organic cage (TpOMe-CDA) is reported using 2,4,6-trimethoxy-1,3,5-triformyl benzene (TpOMe) as a precursor aldehyde. Introduction of the -OMe functional group to the aldehyde creates significant steric and hydrophobic characteristics in the environment around the imine bonds that protects the cage molecules from hydrolysis in the presence of acids or bases. The electronic effect of the -OMe group also plays an important role in enhancing the stability of the reported POCs. As a consequence, TpOMe-CDA reveals exceptional chemical stability in neutral, acidic and basic conditions, even in 12m NaOH. Interestingly, TpOMe-CDA exists in three different porous and non-porous polymorphic forms (, , and ) with respect to differences in crystallographic packing and the orientation of the flexible methoxy groups. All of the polymorphs retain their crystallinity even after treatment with acids and bases. All the polymorphs of TpOMe-CDA differ significantly in their properties as well as morphology and could be reversibly switched in the presence of an external stimulus.
Keywords: chemical stability; Morphology; organic cages; polymorphism; porosity switching

Potent chitin-hydrolyzing enzyme from Myrothecium verrucaria affects growth and development of Helicoverpa armigera and plant fungal pathogens - Vidhate, Ravindra P.; Bhide, Amey J.; Gaikwad, Sushama M.; Giri, Ashok P. (International Journal of Biological Macromolecules, 2019)
Chitin, a crucial structural and functional component of insects and fungi, serves as a target for pest management by utilizing novel chitinases. Here, we report the biocontrol potential of recombinant Myrothecium verrucaria endochitinase (rMvEChi) against insect pest and fungal pathogens. A complete ORF of MvEChi (1185 bp) was cloned and heterologously expressed in Escherichia coli. Structure based sequence alignment of MvEChi revealed the presence of conserved domains SXGG and DXXDXDXE specific for GH-18 family, involved in substrate binding and catalysis, respectively. rMvEChi (46.6 kDa) showed optimum pH and temperature as 7.0 and 30 degrees C, respectively. Furthermore, rMvEChi remained stable within the pH range of 6.0 to 8.0 and up to 40 degrees C. rMvEChi exhibited k(cat)/K-m values of 129.83 x 10(3) [(g/L)(-1) s(-1)] towards 4MU chitotrioside. Hydrolysis of chitooligosaccharides with various degrees of polymerization (DP) using rMvEChi indicated the release of DP2 as main end product with order of reaction as DP6 > DP5 > DP4 > DP3. Bioassay of rMvEChi against Helicoverpa armigera displayed potent anti-feedant activity and induced mortality. In vitro antifungal activity against plant pathogenic fungi (Ustilago maydis and Bipolaris sorokiniana) exhibited significant inhibition of mycelium growth. These results suggest that MvEChi has significant potential in enzyme-based pest and pathogen management. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Biocontrol; endochitinase; Myrothecium verrucaria

Preparation and activity of copper-gallium nanocomposite catalysts for carbon dioxide hydrogenation to methanol - Hengne, Amol M.; Yuan, Ding Jier; Date, Nandan S.; Saih, Youssef; Kamble, Sanjay P.; Rode, V. Chandrashekhar; Huang, Kuo-Wei (Industrial & Engineering Chemistry Research, 2019)
Copper (Cu) nanocomposite catalysts with gallium (Ga) and aluminum (Al) were prepared using the simultaneous coprecipitation digestion method. The catalysts were characterized by N-2 adsorption, N2O titration, XRD (X-ray diffraction), H-2-TPR (H-2 temperature-programmed reduction), XPS (X-ray photoelectron spectroscopy), and CO2-TPD (CO2 temperature-programmed desorption) techniques, and CO2 hydrogenation to methanol synthesis was performed. The use of Ga in Cu catalysts enhanced the weak basic sites more than the Cu catalysts with Al. With the CuGa nanocomposite formation, the catalyst showed a sequential reduction of CuO, for example, Cu+2 to Cu+ to Cu-0, and the Cu surface area was also high in comparison with CuAl. These findings confirmed that both the Cu surface area and CuO reducibility in the catalyst helped to boost the conversion of CO2, whereas selectivity to methanol was associated with the basicity of the catalyst. CuAl catalysts showed very poor selectivity to methanol despite CO formation, which could be due to the weak interaction of the CuAl nanocomposite catalysts compared to the CuGa nanocomposite catalysts.

Pressure-induced phase transitions in germanium telluride: raman signatures of anharmonicity and oxidation - Pawbake, Amit; Bellin, Christophe; Paulatto, Lorenzo; Beneut, Keevin; Biscaras, Johan; Narayana, Chandrabhas; Late, Dattatray J.; Shukla, Abhay (Physical Review Letters, 2019)
Pressure-induced phase transitions in GeTe, a prototype phase change material, have been studied to date with diffraction which is not sensitive to anharmonicity-induced dynamical effects. GeTe is also prone to surface oxidation which may compromise surface sensitive measurements. These factors could be responsible for the lack of clarity about the phases and transitions intervening in the phase diagram of GeTe. We have used high-pressure Raman scattering and ab initio pseudopotential density functional calculations to unambiguously establish the high-pressure phase diagram and identify three phases up to 57 GPa, a low-pressure rhombohedral phase, an intermediate pressure cubic phase, and a high-pressure orthorhombic phase. We detect substantial broadening and softening of Raman modes at low pressure and identify the transition regions and possible intermediate phases.

Probing the catalytic activity of pristine and doped Pd and Ni metal clusters towards H2O molecule - Samal, Pragnya Paramita; Joshi, Krati; Kaliaperumal, Selvaraj; Krishnamurty, Sailaja (Computational and Theoretical Chemistry, 2019)
Electrolysis of H2O to produce molecular hydrogen, the most environment friendly and energy efficient fuel, using cost effective catalysts is one of the major global research challenges. To date, Pt remains the best suitable and yet highly expensive electro-catalyst for hydrogen evolution reaction. Design of an alternative cost-effective catalyst requires a fundamental molecular level understanding of the water molecule adsorption and its activation. In that context, we examine the adsorption and activation of water molecule on model alternative catalysts namely, Ni-6 and Pd-6 clusters using density functional theory based methodology. Ni-6 and Pd-6 clusters and their singly doped counterparts are used for this study. Mo, W, Fe, Co and Cu are used as doping elements. To quantify the influence of medium (neutral and alkaline) on the activation of the water molecule, Ni based clusters are considered in neutral and anionic states, respectively. The activity of these clusters towards H2O molecule is evaluated in terms of the adsorption energy, charge transfer, bandgap, red shift in O-H stretching frequency and dissociation barriers for H2O. The studies demonstrate that doping with Co in all the studied clusters (Pd-6, Ni-6 and anionic Ni-6) increases their activity. Best activity is noted for Fe doped neutral Ni b clusters with a dissociation barrier of 5.76 kcal/mol.
Keywords: Activation barrier; Ni clusters; O-H activation; Pd clusters; Red shift of O-H stretching frequency; Water adsorption

Probing the effect of selenium substitution in kesterite-Cu2ZnSnS4 nanocrystals prepared by hot injection method - Pandharkar, Subhash; Rondiya, Sachin; Bhorde, Ajinkya; Nair, Shruthi; Aher, Rahul; Vairale, Priti; Waghmare, Ashish; Naik, Dhirsing; Waykar, Ravindra; Jadhav, Yogesh (Journal of Materials Science-Materials in Electronics, 2019)
In this paper, we report the effect of sulfur (S) substitution with selenium (Se) in CZTS nanocrystals prepared by hot injection method. The formation of kesterite-copper zinc tin sulfide (Cu2ZnSnS4, CZTS) and copper zinc tin selenide (Cu2ZnSnSe4, CZTSe) nanocrystals is confirmed by X-ray diffraction (XRD), Raman spectroscopy and transmission electron microscopy (TEM) analysis. The XRD, TEM and atomic force microscopy (AFM) analysis shows an overall increase in average crystallite size upon Se substitution. AFM images revealed an increase in root mean square surface roughness (S-q) and average surface roughness (S-a) when S in CZTS is replaced by Se. The substitution of S by Se in host CZTS narrows the optical band gap from 1.56 to 1.03 eV. The ultraviolet photoelectron spectroscopy (UPS) analysis shows shift in valence band and conduction band edge in CZTSe compared to CZTS. The photocurrent density measurement in synthesized CZTSe thin films is similar to 4 to 5 times higher than CZTS thin films. The obtained results show that CZTSe can be a promising candidate as absorber material in photovoltaic applications.

Process development of silica extraction from RHA: a cradle to gate environmental impact approach - Joglekar, Saurabh N.; Kharkar, Rhushikesh A.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Environmental Science and Pollution Research, 2019)
India is one of the major rice-producing countries. Rice husk is a major agricultural by-product from rice production, which is used as a fuel in boilers. Its use as fuel produces huge amounts of silica-rich rice husk ash (RHA). This paper aims at providing an overall assessment of environmental impacts associated with the extraction of silica from RHAa process developed by our study group. The functional unit used in this study is production of 100kg of silica. The analysis included the extraction and transportation of other raw materials; RHA was assumed to be processed at the site. The study was conducted in accordance with the international ISO 14040 procedural framework. LCA is performed using GaBi Education software, and five midpoint indicators are chosen to assess the environmental impacts of silica extraction. The overall climate change (CC) of the extraction process is 7.26kg CO2 equivalent per kg of silica produced. A high contribution of calcination to CC is attributed to the use of electricity. The comprehensive environmental impacts of silica-rich RHA resulting from processing of RHA and improvement options to achieve sustainable production are presented. The negative impacts that can be avoided during silica extraction are also discussed. It is observed that calcination is a major contributor to the overall environmental indicators. The work also stresses on the use of renewable energy for electricity generation, which would help in decreasing the overall greenhouse gas emissions during extraction while ensuring waste utilization.
Keywords: Environmental impacts; Life cycle assessment; Rice husk ash; silica

Process of fruit peel waste biorefinery: a case study of citrus waste biorefinery, its environmental impacts and recommendations - Joglekar S.N., , ,; Pathak, P. D.; Mandavgane, S. A.; Kulkarni, B. D. (Environmental Science and Pollution Research, 2019)
Fruit peels are a rich source of cellulose, hemicellulose, phenolic compounds, and terpenic compounds. Thus, they have the potential to be a novel renewable, sustainable, and low-cost raw material (source) for the production of several value-added products based on framework and concepts such as waste hierarchy that includes biofertilizers, dietary fiber, animal feed, industrial enzymes, substrate for the bioactive compounds production, synthesis of nanomaterials, and clean energy (from residual biomass). With a view of evaluating the environmental burden of biorefinery, a life cycle assessment (LCA) is performed for a representative citrus waste (CW) biorefinery. The functional unit used for LCA was set as 2500 kg of CW processed. The overall GWP was observed to be 937.3 kg CO2 equivalent per 2500 kg of CW processed. On further analysis of the environmental impact, it was found that different steps contributed significantly, as shown by the various environmental indicator values. Alternative advanced process intensification technologies like microwave and ultrasound-assisted steps replacing the conventional steps when implemented show considerable reduction in environmental indicator values. The variations in the contribution to environmental indicators should be considered during the design and process selection of biorefineries.

Progress in total synthesis of subincanadine alkaloids and their congeners - Kalshetti, Manojkumar G.; Argade, Narshinha P. (Organic & Biomolecular Chemistry, 2019)
A concise account of isolation, characterization, bioactivity, plausible biogenetic pathways, and most importantly, total synthesis of structurally fascinating and biologically imperious indole-based subincanadine alkaloids and their biogenetic congeners are described in the present review with special emphasis on total synthesis and therein an involved set of key reactions.

Proline catalyzed sequential alpha-amination/ Prins/ Ritter amidation of aldehydes: new method of construction of tetrahydropyran units - Ahuja, Brijbhushan; Gadakh, Sunita; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2019)
An efficient ``one-pot'' synthetic method toward highly substituted tetrahydrofuran (THP) units is reported. The key transformation involves an atom-efficient sequential proline catalyzed alpha-amination of aldehydes to give alpha-aminated aldehydes in situ and the subsequent cyclomerization with homoallylic alcohols under Prins/Ritter conditions. Notably, this method provides access to enantiopure 1,2-syn and 1,4-anti diamino alcohols via reductive ring opening of THP units.
Keywords: alpha-aminoxylation; organocatalysis; Proline catalyzed; sequential; tetrahydropyran unit

Promising visible-light driven hydrogen production from water on a highly efficient CuCo2S4 nanosheet photocatalyst - Chauhan, Meenakshi; Soni, Kiran; Karthik, P. E.; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S.; Deka, Sasanka (Journal of Materials Chemistry A, 2019)
Here we report the development of CuCo2S4 nanosheets (NSs) as a promising semiconductor photocatalyst for the first time for water splitting reactions under visible light ( 420 nm) conditions, without the support of any noble metal co-catalyst. These NSs were produced via a simple hydrothermal route and have desirable properties with a band gap of 2.24 eV, and are photo-catalytically active under visible light with an apparent quantum yield (AQY) of 2.48%. Under visible light, CuCo2S4 NSs exhibit excellent weight-normalized photoactivity that generates approximate to 25900 mol h(-1) H-2 for 1 g of material with sulphide + sulphite as the sacrificial agent under 7.68 mW cm(-2) illumination, which is the best evolution reported for any chalcogenide semiconductor material without any co-catalyst to date with unprecedented long-term operational stability (up to 12 h study time). The rate and number of hydrogen gas molecules produced are 8.2855 x 10(15) s(-1) cm(-2) which remained constant for three catalytic cycles with a turnover frequency (TOF) value of 0.017 s(-1). The effect of Cu substitution on photoactivity was also investigated for comparative studies and it was found that CuCo2S4 NSs show superior activity to Cu0.5Co2.5S4 and Co3S4. These CuCo2S4 NSs absorb the entire visible range of the spectrum from 420 to 800 nm, and have a highly populated density of states at the Fermi level and a high donor concentration of 7.22 x 10(18) cm(-3) which have been evaluated by Mott-Schottky analysis and favourable adsorption of H+ on S-sites and conversion to H-2 corroborate their efficient photocatalytic activity.

Protein α-amylase inhibitor from withania somnifera and its role in overall quality and nutritional value improvement of potato chips during processing - Kasar, S. S.; Giri, A. P.; Pawar, P. K.; Maheshwari, V. L. (Food and Bioprocess Technology, 2019)
Cold storage and processing increase the reducing sugar level in potato (Solanum tuberosum L.) which is responsible for browning and acrylamide formation that adversely affect sensory and nutrient quality of chips. Effect of α-amylase inhibitor from Withania somnifera (WSAI) treatment on the overall quality improvement of potato chips during processing was studied. WSAI treatment to potato slices at 200 ppm for 30 min was found to reduce browning (60%), residual amylase, and polyphenol oxidase activities (~ 40%) and reduce sugar level by 25%, respectively, over control. Color match analysis indicated an improvement in whiteness and brightness indices and a significant reduction in yellowness index of potato chips. The treatment proved to be superior over blanching and reduction in acrylamide generation during frying was which also observed in chips treated with it. Furthermore, our results were comparable to that of treatment with α-amylase inhibitor of Triticum aestivum and better than synthetic inhibitor, acarbose.
Keywords: Acrylamide; alpha-amylase inhibitor; Browning of potato; Reducing sugars; Sensory and nutrient quality

Protein-capped metal nanoparticles inhibit tau aggregation in alzheimer's disease - Sonawane, Shweta Kishor; Ahmad, Absar; Chinnathambi, Subashchandrabose (Acs Omega, 2019)
The Alzheimer's disease (AD) therapeutic research is yielding a large number of potent molecules. The nanoparticle-based therapeutics against the protein aggregation in AD is also taking a lead especially with amyloid-beta as a primary target. In this work, we have screened for the first time protein-capped (PC) metal nanoparticles for their potency in inhibiting Tau aggregation in vitro. We present a novel function of PC-Fe3O4 and PC-CdS nanoparticles as potent Tau aggregation inhibitors by fluorescence spectrometry, sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and electron microscopy. We demonstrate that the biologically synthesized PC-metal nanoparticles, especially iron oxide do not affect the viability of neuroblastoma cells. Moreover, PC-CdS nanoparticles show dual properties of inhibition and disaggregation of Tau. Thus, the nanoparticles can take a lead as potent Tau aggregation inhibitors and can be modified for specific drug delivery due to their very small size. The current work presents unprecedented strategy to design anti-Tau aggregation drugs, which provides interesting insights to understand the role of biological nanostructures in Alzheimer's disease.

Proteins as nanocarriers to regulate parenteral delivery of tramadol - Agrawal, Shubhang; Patel, Pratikshkumar R.; Gundloori, Rathna Venkata Naga (ACS Omega, 2019)
Tramadol (Td) is a centrally acting opioid analgesic drug used for the treatment of moderate to severe pain. However, the half-life of Td is about 6-8 h, which is a major drawback. To increase the half-life of Td, it needs to be entrapped in a suitable substrate with the capability to release the drug for an extended period of time. Accordingly, in our studies, new protein blends in various compositions were prepared using hydrophilic (egg albumin) and hydrophobic (zein) proteins and fabricated them as nanoparticles with Td by the desolvation method. The prepared nanoparticles were characterized using analytical techniques. The morphology and diameter of the nanoparticles were determined by an environmental scanning electron microscope. The interactions between Td and proteins were confirmed by fluorescence spectroscopy, and the secondary structural changes were evaluated by circular dichroism. The hemolysis test and MTT assay indicated that the nanoparticles were nontoxic, and drug release studies showed an extended duration of release of Td for more than 48 h. The mechanism of the drug release followed the zero order. The overall studies inferred that these protein based nanoparticles have potential to release Td at a slow rate for an extended period of time. Further manipulation of the protein composition may regulate the duration of Td release for an effective therapy.

Puzzle of highly virulent Metarhizium anisopliae strains from Annona squamosa fields against Helicoverpa armigera - Pathan, Ejaj K.; Deshpande, Mukund V. (Journal of Basic Microbiology, 2019)
In our search for indigenous virulent strains of the entomopathogenic fungi, we observed that Metarhizium isolates from soils associated with Annona squamosa (custard apple) have higher virulence (>90% mortality of Helicoverpa armigera larvae at 1/10(th) spore concentration) than strains isolated from Solanum lycopersicum (tomato) fields. Proteomic analysis revealed two insecticidal cyclopeptides of A. squamosa origin in the M. anisopliae strains that led to higher virulence against H. armigera. Transcriptomic and genomic data indicated that M. anisopliae strains and A. squamosa had more than 20 genes in common, including those for cyclic hexapeptide synthase, non-ribosomal peptide synthetase, and plant cyclotide genes, which are involved in the biosynthesis of insecticidal cyclopeptides. These genes were absent in M. anisopliae strains isolated from the S. lycopersicum fields. Further, these strains can establish an endophytic relationship with A. squamosa suggesting that these rhizospheric strains originally could be endophytes, which were eventually released into the soil. Further, Metarhizium strains associated with Capsicum annuum (chili), Azadirachta indica (neem), and Carica papaya (papaya) - plants with insecticidal properties - also had higher virulence against H. armigera. Thus exploration of rhizospheres of plants producing insecticidal metabolites to isolate entomopathogenic fungi, per se, could be a viable strategy in agricultural for crop protection.
Keywords: Annona squamosa; Biocontrol; endophyte; entomopathogen; Helicoverpa armigera; horizontal gene transfer; insecticidal peptides; Metarhizium; natural transformation

Pyridine immobilised on magnetic silica as an efficient solid base catalyst for Knoevenagel condensation of furfural with acetyl acetone - Tarade, Komal; Shinde, Suhas; Sakate, Sachin; Rode, Chandrashekhar (Catalysis Communications, 2019)
Novel heterogeneous pyridine immobilised magnetic silica (Fe3O4@SiO2-Py) was found to be an efficient, greener and heterogeneous solid base catalyst for the Knoevenagel condensation of furfural with acetylacetone under optimized reaction conditions. The Knoevenagel condensation product 3-(2-furylmethylene)-2,4-pentanedione (FMP), a jet fuel precursor, was produced in high yield of 85% with 94% conversion of furfural at 100 degrees C within a period of 4 h. Fe3O4@SiO2-Py catalyst showed excellent stability and recyclability without losing its initial activity.
Keywords: furfural; Jet fuel; Knoevenagel condensation; Silica immobilised pyridine; Solid base

P2O5-mediated Friedel-Crafts acylation of activated arenes with carboxylic acid as acylating agent - Kalshetti, Rupali G.; Mandle, Ram D.; Kamble, Sanjay P.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2020)
P2O5 has been found to be a highly efficient and environmental friendly catalyst for the liquid-phase acylation of activated aromatic substrates giving aromatic ketones (45-93%) in a regioselective manner. Both aromatic and aliphatic carboxylic acids can be employed as acylating source. The process is particularly demonstrated at 100 g scale in the case of anisole and acetic acid to produce 4-methoxyacetophenone.
Keywords: 4-methoxyacetophenone; Carboxylic acid; Friedel-Crafts acylations; phosphorus pentoxide

P301 L, an FTDP-17 mutant, exhibits enhanced glycation in vitro - Sonawane, Shweta Kishor; Chinnathambi, Subashchandrabose (Journal of Alzheimers Disease, 2020)
Background: Frontotemporal dementia and parkinsonism-linked to chromosome-17 are a group of diseases with tau mutations leading to primary tauopathies which include progressive supranuclear palsy, corticobas al syndrome, and frontotemporal lobar degeneration. Alzheimer's disease is a non-primary tauopathy, which displays tau neuropathology of excess tangle formation and accumulation. FTDP-17 mutations are responsible for early onset of AD, which can be attributed to compromised physiological functions due to the mutations. Tau is a microtubule-binding protein that secures the integrity of polymerized microtubules in neuronal cells. It malfunctions owing to various insults and stress conditions-like mutations and post-translational modifications. Objective: In this study, we modified the wild type and tau mutants by methyl glyoxal and thus studied whether glycation can enhance the aggregation of predisposed mutant tau. Methods: Tau glycation was studied by fluorescence assays, SDS-PAGE analysis, conformational evaluation, and transmission electron microscopy. Results: Our study suggests that FTDP-17 mutant P301 L leads to enhanced glycation-induced aggregation as well as advanced glycation end products formation. Glycation forms amorphous aggregates of tau and its mutants without altering its native conformation. Conclusion: The metabolic anomalies and genetic predisposition have found to accelerate tau-mediated neurodegeneration and prove detrimental for the early-onset of Alzheimer's disease.
Keywords: advanced glycation end products; Alzheimer's disease; FTDP-17; tau glycation

Palladium-catalyzed insertion of ethylene and 1,1-disubstituted difunctional olefins: an experimental and computational study - Gaikwad, Shahaji R.; Patel, Ketan; Deshmukh, Satej S.; Mote, Nilesh R.; Birajdar, Rajkumar S.; Pandole, Satish P.; Chugh, Jeetender; Chikkali, Samir H. (ChemPlusChem, 2020)
Insertion or coordination copolymerization of ethylene with di-substituted olefins is challenging and the choice of di-substituted mono-functional olefin versus di-substituted di-functional olefin (DDO) appears to be decisive. Here we show that DDO-inserted species are amenable to ethylene insertion and polymerization. DDOs such as 2-acetamidoacrylic acid (AAA), methyl 2-acetamidoacrylate (MAAA), and ethyl 2-cyanoacrylate (ECA) were treated with palladium complex [P perpendicular to OPdMe(L)] (P perpendicular to O=kappa(2)-P,O-Ar2PC6H4SO2O with Ar=2-MeOC6H4; L=C2H6OS) and the existence of respective insertion intermediates in moderate yield (up to 37 %) was established. These intermediates were exposed to ethylene and corresponding ethylene-inserted products were isolated and characterized. A careful comparison with three model compounds confirmed ethylene insertion and polymerization. Thus, the combined experimental and computational investigations show that DDO-inserted species can undergo ethylene insertion and polymerization.
Keywords: Homogeneous catalysis; insertion copolymerization; Olefins; Palladium; Polyethylene

Palladium-catalyzed oxidative annulation of pyrrolylalkyl-1H-azoles: towards the synthesis of polyheterocyclic arenes - Tripathi, Krishna N.; Bansode, Avinash H.; Singh, Ravi P. (Synthesis-Stuttgart, 2020)
A highly efficient and regioselective palladium-catalyzed annulation protocol for a series of linear and terminally substituted 1,2- and 1,3-di(heteroaryl)alkanes to the corresponding polyheterocyclic arenes is reported. Herein, intramolecular oxidative coupling involving double C(sp(2))-H bond functionalization provides a feasible access to biheteroaryl systems annulated to a six-membered ring. The methodology is not restricted to six-membered annulations and was extended to the synthesis of compounds with a seven-membered ring and biheteroaryl core.
Keywords: C-H functionalization; imidazoles; oxidative coupling; Palladium; pyrroles

Pan-genomics of Ochrobactrum species from clinical and environmental origins reveals distinct populations and possible links - Gohil, Kushal; Rajput, Vinay; Dharne, Mahesh (Genomics, 2020)
Ochrobactrum genus is comprised of soil-dwelling Gram-negative bacteria mainly reported for bioremediation of toxic compounds. Since last few years, mainly two species of this genus, O. intermedium and O. anthropi were documented for causing infections mostly in the immunocompromised patients. Despite such ubiquitous presence, study of adaptation in various niches is still lacking. Thus, to gain insights into the niche adaptation strategies, pan-genome analysis was carried out by comparing 67 genome sequences belonging to Ochrobactrum species. Pan-genome analysis revealed it is an open pan-genome indicative of the continuously evolving nature of the genus. The presence/absence of gene clusters also illustrated the unique presence of antibiotic efflux transporter genes and type IV secretion system genes in the clinical strains while the genes of solvent resistance and exporter pumps in the environmental strains. A phylogenomic investigation based on 75 core genes depicted better and robust phylogenetic resolution and topology than the 16S rRNA gene. To support the pan-genome analysis, individual genomes were also investigated for the mobile genetic elements (MGE), antibiotic resistance genes (ARG), metal resistance genes (MRG) and virulence factors (VF). The analysis revealed the presence of MGE, ARG, and MRG in all the strains which play an important role in the species evolution which is in agreement with the pan-genome analysis. The average nucleotide identity (ANI) based on the genetic relatedness between the Ochrobactrum species indicated a distinction between individual species. Interestingly, the ANI tool was able to classify the Ochrobactrum genomes to the species level which were assigned till the genus level on the NCBI database.
Keywords: Antibiotic resistance; Average nucleotide identity; Clinical and environmental strains; Core genes; MinION; Virulence factors

Para-selective copper-catalyzed C(sp(2))-H amidation/dimerization of anilides via a radical pathway - Viveki, Amol B.; Garad, Dnyaneshwar N.; Gonnade, Rajesh G.; Mhaske, Santosh B. (Chemical Communications, 2020)
Copper-catalyzed amidation/dimerization of anilides via regioselective C(sp(2))-H functionalization is achieved. The para-selective amidation is accomplished on the anilide aromatic ring via a radical pathway leading to C-N bond formation in the presence of ammonium persulfate as a radical source/oxidant for the copper catalyst. The developed protocol tolerates a wide range of anilide substrates. The regioselectivity is confirmed by single-crystal X-ray studies.

Particle size effect in different base fluids on the thermal conductivity of fatty acid coated magnetite nanofluids - Dadwal, Arun; Joy, P. A. (Journal of Molecular Liquids, 2020)
The effect of particle size on the thermal conductivity of nanofluids is studied by dispersing myristic acid coated magnetite (Fe3O4) nanoparticles in two different base fluids; toluene and kerosene. Magnetite nanoparticles of three different sizes 4, 7 and 10 nm dispersed in toluene and kerosene showed a linear increase in the thermal conductivity with increasing concentration of the nanopartides, above a critical concentration. The critical concentration below which the thermal conductivity remained unchanged with the concentration of the nanopartides is found to be lower for the kerosene-based fluids. The variation of thermal conductivity with particle size is without any clear trend. However, within the measurement errors (+/- 1%), the toluene-based fluids showed a decrease in the thermal conductivity with increasing particle size, whereas the opposite trend is observed for the kerosene-based fluids. Also, the kerosene-based fluids at similar concentrations of the nanopartides showed relatively larger enhancement in the thermal conductivity than the toluene-based fluids. The observed role of the base fluid in enhancing the thermal conductivity is correlated with the difference in the solvent-surfactant interactions which in turn affect the interfacial thermal resistance at the particle-fluid interface. The thermal conductivity of the nanofluids in toluene and kerosene is also found to show different trends with the size of the particles in the presence of an external magnetic field. The difference in the enhancement of thermal conductivity of the fluids in a magnetic field is explained in terms of the differences in the magnetic dipolar interactions, clustering/ agglomeration, and magnetic characteristics of the samples as well as the characteristics of the base fluid. (C) 2020 Elsevier B.V. All rights reserved.

Pd-catalyzed annulation of beta-iodovinyl sulfones with 2-halophenols: a general route for the synthesis of 3-sulfonyl benzofuran derivatives - Reddy, Raju Jannapu; Kumar, Jangam Jagadesh; Kumari, Arram Haritha; Krishna, Gamidi Rama (Advanced Synthesis & Catalysis, 2020)
The palladium-catalyzed annulation between beta-iodovinyl sulfones and 2-halophenols or 1-bromo-2-naphthol or 2-bromo-3-pyridinol is presented. The annulation process involving oxa-Michael addition-elimination and intramolecular Heck reaction leading to form 2,3-disubstituted benzofurans (aryl benzofuryl sulfones) in good to high yields. The regioselective tandem construction of C-O and C-C bonds has been achieved with a variety of substitution patterns. Moreover, the tandem process is reliable at gram-scale reactions and a plausible mechanism is also proposed.
Keywords: Benzofurans; beta-Iodovinyl sulfones; Heck reaction; Naphthofurans; oxa-Michael addition

Pd-iminocarboxylate complexes and their behavior in ethylene polymerization - Deshmukh, Satej S.; Gaikwad, Shahaji R.; Gonnade, Rajesh G.; Pandole, Satish P.; Chikkali, Samir H. (Chemistry-An Asian Journal, 2020)
Designing co-catalyst-free late transition metal complexes for ethylene polymerization is a challenging task at the interface of organometallic and polymer chemistry. Herein, a set of new, co-catalyst-free, single-component catalytic systems for ethylene polymerization have been unraveled. Treatment of anthranilic acid with various aldehydes produced four iminocarboxylate ligands (L1-L4) in very good to excellent yield (75-92 %). The existence of 2-((2-methoxybenzylidene)amino) benzoic acid (L1) has been unambiguously demonstrated using NMR spectroscopy, MS and single-crystal X-ray diffraction. A neutral Pd-iminocarboxylate complex [N OPdMe(L1)] (N O=kappa(2)-N,O-ArCHNC6H4CO2 with Ar=2-MeOC6H4) C1 was prepared by treating stoichiometric amount of L1.Na with palladium precursor. The identity of C1 was confirmed by 1-2D NMR spectroscopy and single-crystal X-ray diffraction studies. Along the same lines, palladium complexes C2-C4 were prepared from ligands L2-L4 respectively. In-situ high-pressure NMR investigations revealed that these Pd complexes are amenable to ethylene insertion and undergo facile beta-H elimination to produce propylene. These palladium complexes were then evaluated in ethylene polymerization reaction and various reaction parameters were screened. When C1-C4 were exposed to ethylene pressures of 10-50 bar, formation of low-molecular-weight polyethylene was observed.
Keywords: imine; Imine-carboxylate; Insertion polymerization; Pd complexes; Polyethylene

Penicillium janthinellum NCIM1366 shows improved biomass hydrolysis and a larger number of CAZymes with higher induction levels over Trichoderma reesei RUT-C30 - Sreeja-Raju, Athiraraj; Christopher, Meera; Kooloth-Valappil, Prajeesh; Kuni-Parambil, Rajasree; Gokhale, Digambar Vittal; Sankar, Meena; Abraham, Amith; Pandey, Ashok; Sukumaran, Rajeev K. (Biotechnology for Biofuels, 2020)
Background Major cost of bioethanol is attributed to enzymes employed in biomass hydrolysis. Biomass hydrolyzing enzymes are predominantly produced from the hyper-cellulolytic mutant filamentous fungus Trichoderma reesei RUT-C30. Several decades of research have failed to provide an industrial grade organism other than T. reesei, capable of producing higher titers of an effective synergistic biomass hydrolyzing enzyme cocktail. Penicillium janthinellum NCIM1366 was reported as a cellulase hyper producer and a potential alternative to T. reesei, but a comparison of their hydrolytic performance was seldom attempted. Results Hydrolysis of acid or alkali-pretreated rice straw using cellulase enzyme preparations from P. janthinellum and T. reesei indicated 37 and 43% higher glucose release, respectively, with P. janthinellum enzymes. A comparison of these fungi with respect to their secreted enzymes indicated that the crude enzyme preparation from P. janthinellum showed 28% higher overall cellulase activity. It also had an exceptional tenfold higher beta-glucosidase activity compared to that of T. reesei, leading to a lower cellobiose accumulation and thus alleviating the feedback inhibition. P. janthinellum secreted more number of proteins to the extracellular medium whose total concentration was 1.8-fold higher than T. reesei. Secretome analyses of the two fungi revealed higher number of CAZymes and a higher relative abundance of cellulases upon cellulose induction in the fungus. Conclusions The results revealed the ability of P. janthinellum for efficient biomass degradation through hyper cellulase production, and it outperformed the established industrial cellulase producer T. reesei in the hydrolysis experiments. A higher level of induction, larger number of secreted CAZymes and a high relative proportion of BGL to cellulases indicate the possible reasons for its performance advantage in biomass hydrolysis.
Keywords: Bioethanol; CAZymes; Cellulase; Penicillium janthinellum; Secretome; Trichoderma reesei

Phagocytosis of full-length Tau oligomers by Actin-remodeling of activated microglia - Das, Rashmi; Balmik, Abhishek Ankur; Chinnathambi, Subashchandrabose (Journal of Neuroinflammation, 2020)
Background Alzheimer's disease is associated with the accumulation of intracellular Tau tangles within neurons and extracellular amyloid-beta plaques in the brain parenchyma, which altogether results in synaptic loss and neurodegeneration. Extracellular concentrations of oligomers and aggregated proteins initiate microglial activation and convert their state of synaptic surveillance into a destructive inflammatory state. Although Tau oligomers have fleeting nature, they were shown to mediate neurotoxicity and microglial pro-inflammation. Due to the instability of oligomers, in vitro experiments become challenging, and hence, the stability of the full-length Tau oligomers is a major concern. Methods In this study, we have prepared and stabilized hTau40(WT) oligomers, which were purified by size-exclusion chromatography. The formation of the oligomers was confirmed by western blot, thioflavin-S, 8-anilinonaphthaalene-1-sulfonic acid fluorescence, and circular dichroism spectroscopy, which determine the intermolecular cross-beta sheet structure and hydrophobicity. The efficiency of N9 microglial cells to phagocytose hTau40(WT) oligomer and subsequent microglial activation was studied by immunofluorescence microscopy with apotome. The one-way ANOVA was performed for the statistical analysis of fluorometric assay and microscopic analysis. Results Full-length Tau oligomers were detected in heterogeneous globular structures ranging from 5 to 50 nm as observed by high-resolution transmission electron microscopy, which was further characterized by oligomer-specific A11 antibody. Immunocytochemistry studies for oligomer treatment were evidenced with A11(+) Iba1(high) microglia, suggesting that the phagocytosis of extracellular Tau oligomers leads to microglial activation. Also, the microglia were observed with remodeled filopodia-like actin structures upon the exposure of oligomers and aggregated Tau. Conclusion The peri-membrane polymerization of actin filament and co-localization of Iba1 relate to the microglial movements for phagocytosis. Here, these findings suggest that microglia modified actin cytoskeleton for phagocytosis and rapid clearance of Tau oligomers in Alzheimer's disease condition.
Keywords: Actin; activation; Alzheimer's disease; microglia; migration; neurodegeneration; Tau Oligomers; Tauopathy

Phase- and morphology-controlled synthesis of tunable plasmonic MoO3-x nanomaterials for ultrasensitive surface-enhanced raman spectroscopy detection - Patil, Manoj Krishnat; Gaikwad, Supriya Hanmant; Mukherjee, Shatabdi Porel (Journal of Physical Chemistry C, 2020)
The enhancement of the surface-enhanced Raman scattering (SERS) property of the plasmonic metal oxide semiconductor nanostructures by controlling their phase, shape, size, and oxygen vacancy to detect trace amounts of organics is of significant interest. In this study, a simple surfactant-free hydrothermal strategy was proposed to fabricate crystalline h-MoO3-x and alpha-MoO3-x nanomaterials with tunable plasmonic properties. Herein, the crystal phase, morphology, and oxygen vacancy of MoO3-x nanostructures were precisely controlled under suitable synthetic conditions. The plasmonic properties of the as-synthesized h-MoO3-x and alpha-MoO3-x micro-/nanostructures were controlled by adjusting the residual volume in the autoclaving chamber. In addition, the plasmonic MoO3-x exhibited SERS activity with a detection limit as low as 1.0 x 10(-9) M and the maximum enhancement factor (EF) up to 6.99 x 10(5) for h-MoO3-x, while for alpha-MoO3-x, the detection limit was 1.0 x 10(-7) M with the corresponding EF up to 8.51 x 10(3), comparable with plasmonic noble metal nanomaterials without a ``hot spot''.

Phenylboronic acid-catalyzed tandem construction of S-S and C-S bonds: a new method for the synthesis of benzyl disulfanylsulfone derivatives from S-benzyl thiosulfonates - Reddy, Raju Jannapu; Waheed, Md; Krishna, Gamidi Rama (Organic & Biomolecular Chemistry, 2020)
A unique phenylboronic acid-catalyzed dimerization-sulfonylation of S-benzyl thiosulfonates has been disclosed. A metal-free tandem construction of S-S and C-S bonds is an operationally simple method to access a wide range of benzyl disulfanylsulfone derivatives in high to excellent yields. Moreover, the robustness of this tandem transformation has been demonstrated by gram-scale reactions, and a plausible mechanism is also proposed.

Phosphorous-doped graphitic material as a solid acid catalyst for microwave-assisted synthesis of beta-ketoenamines and baeyer-villiger oxidation - Maity, Sayantan; Ram, Farsa; Dhar, Basab Bijayi (ACS Omega, 2020)
Synthesis of phosphorous-doped graphitic materials (P-Gc) using phytic acid as a precursor was done in a microwave oven in a cost- and time-effective green way. The material was used as a solid acid catalyst for microwave (MW)-assisted synthesis of beta-ketoenamines and Baeyer-Villiger (By) oxidation. In the case of BV oxidation, hydrogen peroxide (H2O2) was used as a green oxidant. For beta-ketoenamines, in most cases, 100% conversion with an similar to 95% yield was achieved in ethyl acetate medium. In solvent-free conditions, the yield of beta-ketoenamines was similar to 75%. A kinetic study suggested that the resonance stabilization of the positive reaction center happens in the transition state for beta-ketoenamine synthesis. In BV oxidation, cyclic ketones were converted to their corresponding cyclic esters in good to high yields (similar to 80% yield) in a shorter reaction time (6-20 min). As per our knowledge, this is the first report of BV oxidation catalyzed by a heteroatom-doped graphitic material. For BV oxidation, the phosphoric acid functional groups present in P-Gc might increase the electrophilicity of the carbonyl group of the ketones to compensate for the weakness of H2O2 as a nucleophile and a spiro-bisperoxide intermediate has been identified in high-resolution mass spectrometry.

Photocatalytic hydrogen generation and CO2 conversion using g-C3N4 decorated dendritic fibrous nanosilica: role of interfaces between silica and g-C3N4 - Rawool, Sushma A.; Samanta, Anupam; Ajithkumar, T. G.; Kar, Yusuf; Polshettiwar, Vivek (ACS Applied Energy Materials, 2020)
We have synthesized g-C3N4 decorated over dendritic fibrous nanosilica (DFNS). The generation of C-N-Si interfaces by coating each fiber of DFNS with g-C3N4 not only provided high surface area but also affected the optical and electronic properties of the composite. The catalyst synthesis reproducibility issue of g-C3N4 was resolved using a vacuum-sealed quartz tube. The extended light absorption in the visible region, enhanced lifetime of photogenerated charge carriers due to the formation of interfaces between silica and g-C3N4 (confirmed by solid-state NMR), and increased surface area result in the improved photocatalytic activity of DFNS/g-C(3)N(4)for hydrogen generation and CO2 conversion.
Keywords: CO2 conversion; DFNS; g-C3N4; Hydrogen generation; nanocatalysts; photocatalysts; Solid-state NMR

Photocatalytic hydrogen production from H2S using nanostructured CNT blended CdZnS/Fe2O3 thin film on glass substrate - Raja, M. Anthony; Vijayarengan, Preethi; Pal, Yash; Nalajala, Naresh; Gopinath, Chinnakonda (Journal of Physics Conference Series, 2020)
<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">A co-precipitation method was employed to prepare the CNT blended CdZnS/Fe<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">3<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> photocatalyst. Using the powder photocatalyst, the thin film of CNT blended CdZnS/Fe<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">3<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> photocatalyst over a glass substrate was prepared using the drop-casting method. The obtained thin film was characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), energy-dispersive X-ray analysis (EDAX), photoluminescence (PL), and hydrogen production activity studies in order to obtain information on their structural, morphology, chemical composition, optical and hydrogen production efficiency. The hydrogen production activity of catalyst or effective conversion of H<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">S into hydrogen (H<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">) and sulfur (S) using thin-film photocatalyst was evaluated using a simulated sulfide solution. The results showed that 1 mg of CNT blended CdZnS/Fe<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">3<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> catalyst coated as thin film over glass substrate (4.69 cm<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; bottom: 1ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">) showed the highest hydrogen production value of 3180 μmol h<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; bottom: 1ex; color: rgb(51, 51, 51);">−1<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">g<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; bottom: 1ex; color: rgb(51, 51, 51);">−1<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">; compared to that of 1 mg CNT blended CdZnS/Fe<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">3<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> powder of 2510 μmol h<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; bottom: 1ex; color: rgb(51, 51, 51);">−1<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">g<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; bottom: 1ex; color: rgb(51, 51, 51);">−1<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">. From the above results, it is concluded that the thin film form of photocatlyst produced more hydrogen than the powder form. This is attributed to the effective charge separation and increased specific surface area in thin film photocatalyst.

Photodynamic exposure of Rose-Bengal inhibits Tau aggregation and modulates cytoskeletal network in neuronal cells - Dubey, Tushar; Gorantla, Nalini Vijay; Chandrashekara, Kagepura Thammaiah; Chinnathambi, Subashchandrabose (Scientific Reports, 2020)
The intracellular Tau aggregates are known to be associated with Alzheimer's disease. The inhibition of Tau aggregation is an important strategy for screening of therapeutic molecules in Alzheimer's disease. Several classes of dyes possess a unique property of photo-excitation, which is applied as a therapeutic measure against numerous neurological dysfunctions. Rose Bengal is a Xanthene dye, which has been widely used as a photosensitizer in photodynamic therapy. The aim of this work was to study the protective role of Rose Bengal against Tau aggregation and cytoskeleton modulations. The aggregation inhibition and disaggregation potency of Rose Bengal and photo-excited Rose Bengal were observed by in-vitro fluorescence, circular dichroism, and electron microscopy. Rose Bengal and photo-excited Rose Bengal induce minimal cytotoxicity in neuronal cells. In our studies, we observed that Rose Bengal and photo-excited Rose Bengal modulate the cytoskeleton network of actin and tubulin. The immunofluorescence studies showed the increased filopodia structures after photo-excited Rose Bengal treatment. Furthermore, Rose Bengal treatment increases the connections between the cells. Rose Bengal and photo-excited Rose Bengal treatment-induced actin-rich podosome-like structures associated with cell membranes. The in-vivo studies on UAS E-14 Tau mutant Drosophila suggested that exposure to Rose Bengal and photo-excited Rose Bengal efficiency rescues the behavioural and memory deficit in flies. Thus, the overall results suggest that Rose Bengal could have a therapeutic potency against Tau aggregation.

Photoresponse properties of CdSe thin film photodetector - Shelke, Nitin T.; Karle, S. C.; Karche, B. R. (Journal of Materials Science-Materials in Electronics, 2020)
In the present investigation, the performance of highly sensitive photodetector based on CdSe thin film has been demonstrated. The cadmium selenide (CdSe) films were deposited successfully by spray pyrolysis method on glass substrate. The as-deposited films were used as visible light detector. Further, the structural, morphological, and optical properties of CdSe films were investigated through X-ray diffraction (XRD), scanning electron microscopy (SEM), atomic force microscopy, and optical absorption spectrophotometer. The XRD studies show that the produced samples are polycrystalline in nature. A UV-Visible absorbance spectrum indicates direct allowed transition with bandgap about 1.75 eV. The SEM micrographs depict uniformly distributed well defined uneven hexagonal grains. The CdSe film-based photodetector exhibits high responsivity, detectivity and shows an ultrafast photoresponse. The excellent photoresponse and high photosensitivity of CdSe film makes it a strong candidate for high-performance photodetectors.

Phytochemicals in cancer treatment: from preclinical studies to clinical practice - Choudhari, Amit S.; Mandave, Pallavi C.; Deshpande, Manasi; Ranjekar, Prabhakar; Prakash, Om (Frontiers in Pharmacology, 2020)
Cancer is a severe health problem that continues to be a leading cause of death worldwide. Increasing knowledge of the molecular mechanisms underlying cancer progression has led to the development of a vast number of anticancer drugs. However, the use of chemically synthesized drugs has not significantly improved the overall survival rate over the past few decades. As a result, new strategies and novel chemoprevention agents are needed to complement current cancer therapies to improve efficiency. Naturally occurring compounds from plants known as phytochemicals, serve as vital resources for novel drugs and are also sources for cancer therapy. Some typical examples include taxol analogs, vinca alkaloids such as vincristine, vinblastine, and podophyllotoxin analogs. These phytochemicals often act via regulating molecular pathways which are implicated in growth and progression of cancer. The specific mechanisms include increasing antioxidant status, carcinogen inactivation, inhibiting proliferation, induction of cell cycle arrest and apoptosis; and regulation of the immune system. The primary objective of this review is to describe what we know to date of the active compounds in the natural products, along with their pharmacologic action and molecular or specific targets. Recent trends and gaps in phytochemical based anticancer drug discovery are also explored. The authors wish to expand the phytochemical research area not only for their scientific soundness but also for their potential druggability. Hence, the emphasis is given to information about anticancer phytochemicals which are evaluated at preclinical and clinical level.
Keywords: Anticancer; clinical; medicinal plants; phytochemicals; preclinical

Phytochemicals in cancer treatment: from preclinical studies to clinical practice (vol 10, 1614, 2020) - Choudhari, Amit S.; Mandave, Pallavi C.; Deshpande, Manasi; Ranjekar, Prabhakar; Prakash, Om (Frontiers in Pharmacology, 2020)
Keywords: Anticancer; clinical; medicinal plants; phytochemicals; preclinical

Piezoelectric energy harvesting from a ferroelectric hybrid salt [Ph3MeP](4)[Ni(NCS)(6)] embedded in a polymer matrix - Vijayakanth, Thangavel; Ram, Farsa; Praveenkumar, Balu; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Angewandte Chemie-International Edition, 2020)
Organic-inorganic hybrid ferroelectrics are an exciting class of molecular materials with promising applications in the area of energy and electronics. The synthesis, ferroelectric and piezoelectric energy harvesting behavior of a 3d metal ion-containing A(4)BX(6) type organic-inorganic hybrid salt [Ph3MeP](4)[Ni(NCS)(6)] (1) is now presented. P-E hysteresis loop studies on 1 show a remnant ferroelectric polarization value of 18.71 mu C cm(-2), at room temperature. Composite thermoplastic polyurethane (TPU) devices with 5, 10, 15 and 20 wt % compositions of 1 were prepared and employed for piezoelectric energy harvesting studies. A maximum output voltage of 19.29 V and a calculated power density value of 2.51 mW cm(-3) were observed for the 15 wt % 1-TPU device. The capacitor charging experiments on the 15 wt % 1-TPU composite device shows an excellent energy storage performance with the highest stored energies and measured charges of 198.8 mu J and 600 mu C, respectively.
Keywords: energy conversion; mechanical properties; non-covalent interactions; organic-inorganic hybrid composites; Phosphorus

Plant probiotic bacterial endophyte, alcaligenes faecalis, modulates plant growth and forskolin biosynthesis incoleus forskohlii - Mastan, Anthati; Rane, Digeshwar; Dastager, Syed G.; Vivek Babu, Chikkarasanahalli Shivegowda (Probiotics and Antimicrobial Proteins, 2020)
Coleus forskohliiis an herb, well-known for its medicinal compound forskolin present in its roots, with wide range of pharmaceutical applications. Here, we report, for the first time, the role of plant-probiotic bacterial endophytes ofC. forskohlii, CFLB1 and CFRB1, isolated from leaf and root, which regulate plant growth andin plantforskolin content. Native bacterial endophyte, CFRB1 (Alcaligenes faecalis), significantly modulates primary plant productivity and forskolin content under pot and field conditions. Under field conditions, CFRB1 endophyte application significantly enhanced photosynthetic pigments and reduced the severity of root-knot and root rot diseases. Expression analyses of functional genes involved in the forskolin biosynthesis inC. forskohliiplants treated with CFRB1 endophyte under field conditions revealed differential upregulation of fourC. forskohliiditerpene synthases (CfTPSs),CfTPS1,CfTPS2,CfTPS3andCfTPS4, along with cytochrome P450 (CfCYP76AH15) and acyltransferase (CfACT1-8) genes. CFRB1 treatment reduced the severity of nematode infection and root rot inC. forskohliiplants by 81 and 78%, respectively. Overall, we demonstrate that cross-talk of plant-endophyte interaction inC. forskohliiis beneficial, leading to enhanced forskolin content through modulation of forskolin biosynthetic pathway genes along with increased plant yield and reduced disease incidence. Thus, endophytic isolate,A. faecalis(CFRB1), could be deployed as a novel bio-stimulant for enhancingin plantaforskolin content during cultivation ofC. forskohlii.
Keywords: Alcaligenes faecalis; CfACT1-8; CfCYP76AH15; CfTPSs; Coleus forskohlii; Forskolin; Plant-probiotic bacterial endophyte

Plant-pathogen interactions: microRNA-mediated trans-kingdom gene regulation in fungi and their host plants - Mathur, Monika; Nair, Aswathy; Kadoo, Narendra (Genomics, 2020)
MicroRNAs (miRNAs) have been prevalently studied in plants, animals, and viruses. However, recent studies show evidences of miRNA-like RNAs (milRNAs) in fungi as well. It is known that after successful infection, pathogens hijack the host machinery and use it for their own growth and multiplication. Alternatively, resistant plants can overcome the pathogen attack by a variety of mechanisms. Based on this prior knowledge, we computationally predicted milRNAs from 13 fungi, and identified their targets in transcriptomes of the respective fungi as well as their host plants. The expressions of the milRNAs and targets were confirmed using qRT-PCR. We found that plant miRNAs targeted fungal virulence genes, while fungal milRNAs targeted plant resistance genes; corroborating miRNA-mediated trans-kingdom gene regulation and the roles of miRNAs in plantpathogen interactions. Transgenic plants with miRNAs targeting fungal virulence genes, or anti-sense of fungal milRNAs, would be expected to be highly resistant to the fungal pathogens.
Keywords: Disease resistance; Fungal miRNAs; qRT-PCR; Resistance genes; Target prediction; Virulence genes

Plausible diagnostic value of urinary isomeric dimethylarginine ratio for diabetic nephropathy - Parmar, Dharmeshkumar; Bhattacharya, Nivedita; Kannan, Shanthini; Vadivel, Sangeetha; Pandey, Gautam Kumar; Ghanate, Avinash; Ragi, Nagarjuna Chary; Prabu, Paramasivam; Pramodkumar, Thyparambil Aravindakshan; Manickam, Nagaraj; Mohan, Viswanathan; Sripadi, Prabhakar; et al. (Scientific Reports, 2020)
Altered circulatory asymmetric and symmetric dimethylarginines have been independently reported in patients with end-stage renal failure suggesting their potential role as mediators and early biomarkers of nephropathy. These alterations can also be reflected in urine. Herein, we aimed to evaluate urinary asymmetric to symmetric dimethylarginine ratio (ASR) for early prediction of diabetic nephropathy (DN). In this cross-sectional study, individuals with impaired glucose tolerance (IGT), newly diagnosed diabetes (NDD), diabetic microalbuminuria (MIC), macroalbuminuria (MAC), and normal glucose tolerance (NGT) were recruited from Dr. Mohans' Diabetes Specialties centre, India. Urinary ASR was measured using a validated high-throughput MALDI-MS/MS method. Significantly lower ASR was observed in MIC (0.909) and MAC (0.741) in comparison to the NGT and NDD groups. On regression models, ASR was associated with MIC [OR: 0.256; 95% CI: 0.158-0.491] and MAC [OR 0.146; 95% CI: 0.071-0.292] controlled for all the available confounding factors. ROC analysis revealed ASR cut-point of 0.95 had C-statistic of 0.691 (95% CI: 0.627-0.755) to discriminate MIC from NDD with 72% sensitivity. Whereas, an ASR cut-point of 0.82 had C-statistic of 0.846 (95% CI: 0.800 - 0.893) had 91% sensitivity for identifying MAC. Our results suggest ASR as a potential early diagnostic biomarker for DN among the Asian Indians.

Poly (vinylpyrrolidone)-iodine engineered poly (epsilon-caprolactone) nanofibers as potential wound dressing materials - Shitole, Ajinkya A.; Raut, Piyush; Giram, Prabhanjan; Rade, Priyanka; Khandwekar, Anand; Garnaik, Baijayantimala; Sharma, Neeti (Materials Science & Engineering C-Materials for Biological Applications, 2020)
Facilitating the process of wound healing and effective treatment of wounds remains a serious challenge in healthcare. Wound dressing materials play a major role in the protection of wounds and in accelerating the natural healing process. In the present study, novel core/shell (c/s) nanofibrous mats of poly(vinyl pyrrolidone)-iodine (PVPI) and polycaprolactone (PCL) were fabricated using a co-axial electrospinning process followed by their surface modification with poly-L-lysine. The developed nanofibrous mats were extensively characterized for their physicochemical properties using various analytical techniques. The core/shell structure of the PVP-I/PCL nanofibers was confirmed using TEM analysis. The PVP-I release studies showed an initial burst phase followed by a sustained release pattern of PVP-I over a period of 30 days. The developed nanofibers exhibited higher BSA and fibrinogen adsorption as compared to pristine PCL. Cytotoxicity studies using MTT assay demonstrated that the PVP-I/PCL (c/s) nanofibers were cytocompatible at optimized PVP-I concentration (3 wt%). The PCL-poly-L-lysine and PVP-I/PCL-poly-L-lysine nanofibers exhibited higher cell viability (24.2% and 21.4% higher at day 7) when compared to uncoated PCL and PVP-I/PCL nanofibers. The PVP-I/PCL nanofibers showed excellent antimicrobial activity against both Gram-positive (S. aureus) and Gram-negative (E. coli) bacteria. The inflammatory response of Mouse RAW 264.7 macrophage cells towards the nanofibers was studied using RTPCR. It revealed that the pro-inflammatory cytokines (TNF-alpha and IL-1 beta) were significantly upregulated on PCL nanofibers, while their expression was comparatively lower on poly-L-lysine coated PCL or PVP-I/PCL(c/s) nanofibers. Overall, the study highlights the ability of poly-L-lysine coated PVP-I/PCL (c/s) nanofibers as potential wound dressing materials effectively facilitating the early stage wound healing and repair process by virtue of their selective modulation of inflammation, cell adhesion and antimicrobial properties.
Keywords: biodegradable; Controlled release; Core/shell; electrospinning; scaffolds; tissue engineering

Polymer nanorings with uranium specific clefts for selective recovery of uranium from acidic effluents via reductive adsorption - Kushwaha, Shilpi; Mane, Manoj; Ravindranathan, Sapna; Das, Amitava (ACS Sensors, 2020)
Nanostructured polymeric materials, functionalized with an appropriate receptor, have opened up newer possibilities for designing a reagent that shows analyte-specific recognition and efficient scavenging of an analyte that has either a detrimental influence on human physiology and environment or on its recovery for further value addition. Higher active surface area, morphological diversity, synthetic tunability for desired surface functionalization, and the ease of regeneration of a nanostructured material for further use have provided such materials with a distinct edge over conventional reagents. The use of a biodegradable polymeric backbone has an added significance owing to the recent concern over the impact of polymers on the environment. Functionalization of biodegradable sodium alginate with AENA (6.85% grafting) as the receptor functionality led to a unique open framework nanoring (NNRG) morphology with a favorable spatial orientation for specific recognition and efficient binding to uranyl ions (U) in an aqueous medium over a varied pH range. Nanoring morphology was confirmed by transmission electron microscopy and atomic force microscopy images. The nanoscale design maximizes the surface area for the molecular scavenger. A combination of all these features along with the reversible binding phenomenon has made NNRG a superior reagent for specific, efficient uptake of UO22+ species from an acidic (pH 3-4) solution and compares better than all existing UO22+-scavengers reported till date. This could be utilized for the recovery of uranyl species from a synthetic acidic effluent of the nuclear power. The results of the U uptake experiments reveal a maximum adsorption capacity of 268 mg of U per g of NNRG in a synthetic nuclear effluent. X-ray photoelectron spectroscopy studies revealed a reductive complexation process and stabilization of U(IV)-species in adsorbed uranium species (U@NNRG).
Keywords: biodegradable polymeric backbone; molecular recognition; nanostructured material; sodium alginate; uranium; uranyl-specific receptor

Porphyrin-based conducting polymer hydrogel for supercapacitor application - Das, Debasree; Kurungot, Sreekumar (Energy Technology, 2020)
Herein, the electrochemical properties and energy storage capability of a flexible, all-solid-state supercapacitor based on the supramolecular assembly of polypyrrole (PPy) and the anion of 5,10,15,20-tetrakis(4-sulfonatophenyl)-21H,23H-porphine manganese(III) chloride (MnTSPP) are reported. The electrode material consists of a conductive polymer hydrogel formed through the gelation initiated by cross-linking of the dopant MnTSPP anion in the PPy chains. The morphology of the cross-linked polymer hydrogel is that of a particle-decorated nanofiber, which can perform as a flexible supercapacitor electrode material with a specific capacitance of 300 Fg(-1) and capacitance retention of 78% up to 10 000 cycles. The anion of MnTSPP plays a pivotal role in enhancing the charge storage capability by facilitating the electron transfer between the polymer interchains. In addition, the steric hindrance due to the large size of the dopant counter ions of MnTSPP reduces the counterion drain effect and structural pulverization of PPy, thereby improving the capacitive retention.
Keywords: conductive hydrogels; energy storage devices; Flexible Supercapacitors; nanofibers; porphyrin-based polymers

Possible role of glycation in the regulation of amyloid beta precursor protein processing leading to amyloid beta accumulation - Patil, Gouri V.; Joshi, Rakesh S.; Kazi, Rubina S.; Kulsange, Shabda E.; Kulkarni, Mahesh J. (Medical Hypotheses, 2020)
Alzheimer's disease (AD) is one of the most common forms of neurodegenerative diseases amongst the aged population. The disease is multifactorial, and diabetes has been considered as one of the major risk factors for the development of AD. Chronic hyperglycemic condition in diabetes promotes non-enzymatic protein modification by glucose termed as glycation, which affects protein structure and function. Previous studies have shown that many of the enzymes, including proteases, are affected by glycation. Conversely, glycated proteins are known to become resistant to protease action. In these hypotheses, we have extended these two concepts to the regulation of amyloid-beta protein precursor (A beta PP) by secretases leading to amyloid-beta (Af3) accumulation. The first hypothesis deals with the glycation of alpha-secretases leading to its reduced activity, while in the second hypothesis, A beta PP glycation may prevent a-secretases action, rendering its processing by beta secretase. As diabetes is a risk factor for the development of AD, either or both these pathways may operate, leading to the manifestation of AD.
Keywords: Alpha-secretase; Alzheimer `s disease; Amyloid-beta; Amyloid-beta protein precursor; Beta-secretase; Diabetes; glucose; Glycation; Type-3 diabetes

Potential of myo-inositol as a starting material for natural product synthesis - Shashidhar, Mysore; Patil, Nivedita (Journal of the Indian Chemical Society, 2020)
Phosphorylated derivatives of myo-inositol are involved in various cellular processes and they are crucial for the survival of cells. Discoveries related to these biological aspects revived the interest in the chemistry of inositols, since derivatives and analogs of phosphoinositols were required as molecular tools for the delineation of the myo-inositol cycle in eukaryotic cells. Extensive research on the chemistry of inositols in the last 3-4 decades encouraged organic chemists to explore the use of myo-inositol, the most abundantly available inositol, as a starting material for the synthesis of natural products. This article is an attempt to review the progress in this area of synthetic chemistry and identify aspects that need to be addressed to increase the potential of myo-inositol as a starting material for natural product synthesis.

Prediction of survival rate and effect of drugs on cancer patients with somatic mutations of genes: an AI-based approach - Saurabh, Rochi; Nandi, Sutanu; Sinha, Noopur; Shukla, Mudita; Sarkar, Ram Rup (Chemical Biology & Drug Design, 2020)
The causal role of somatic mutation and its interrelationship with gene expression profile during tumor development has already been observed, which plays a major role to decide the cancer grades and overall survival. Accurate and robust prediction of tumor grades and patients' overall survival are important for prognosis, risk factors identification and betterment of the treatment strategy, especially for highly lethal tumors, like gliomas. Here, with the help of more accurate and widely used machine learning-based approaches, we propose an integrative computational pipeline that incorporates somatic mutations and gene expression profile for survival and grade prediction of glioma patients and simultaneously relates it to the drugs to be administered. This study gives us a clear understanding that the same drug is not effective for the treatment of same grade of cancer if the gene mutations are different. The alteration in a specific gene plays a very important role in tumor progression and should also be considered for the selection of appropriate drugs. This proposed framework includes all the necessary factors required for enhancement of therapeutic designs and could be useful for clinicians in determining an accurate and personalized treatment strategy for individual patients suffering from different life threatening diseases.
Keywords: gene expression and copy number variation; gliomas; grade and survival prediction; machine learning strategy; significant gene prediction and effect of drugs; somatic mutation

Preparation, spectroscopic characterization, theoretical investigations, and in vitro anticancer activity of Cd(II), Ni(II), Zn(II), and Cu(II) complexes of 4(3H)-quinazolinone-derived schiff base - Ashok, Ubale Panchsheela; Kollur, Shiva Prasad; Anil, Nishad; Arun, Bansode Prakash; Jadhav, Sanjay Namdev; Sarsamkar, Sanjay; Helavi, Vasant Baburao; Srinivasan, Asha; Kaulage, Sandeep; Veerapur, Ravindra; Al-Rashed, Sarah; Syed, Asad; et al. (Molecules, 2020)
Herein, we report the synthesis and characterization of a new Schiff base ligand 3-[[(E)-(3-hydroxyphenyl)-methylidene]amino]-2-methyl-quinazolin-4(3 H)-one (HAMQ) and its Cd(II), Ni(II), Zn(II), and Cu(II) complexes (C-1-C-4). The ligand HAMQ was synthesized by reacting 3-hydroxybenzaldehyde and 3-amino-2-methyl-4(3H)-quinazolinone in a 1:1 molar ratio. The structure of the ligand and its complexes (C-1-C-4) were evaluated using ultraviolet (UV)-visible (Vis) light spectroscopy, H-1-NMR, Fourier-transform infrared (FT-IR) spectroscopy, MS, elemental analysis, conductance data, and thermogravimetric analysis (TGA). The characterization results suggested that the bidentate ligand, HAMQ, coordinated to the metal center through the lactum oxygen and the azomethine nitrogen. Moreover, all the metal complexes were analyzed using powder X-ray diffraction studies, which revealed that all of them belong to a triclinic crystal system. The research was supplemented by density functional theory (DFT) studies on the IR and UV-Vis spectra, as well as the chemical reactivity of the HAMQ and its four metallic derivatives making use of conceptual density functional theory (CDFT) by means of KID (Koopmans in DFT) methodology. The synthesized complexes displayed significant in vitro anticancer activity against human cancer cell lines (HeLa and HCT-115).
Keywords: 3-quinolin-4(3H)-one; chemical reactivity properties; conceptual DFT; Metal complexes; spectral studies

Process development for 6-aminopenicillanic acid production using lentikats-encapsulated escherichia coli cells expressing penicillin V acylase - Sawant, Amol M.; Sunder, Avinash Vellore; Vamkudoth, Koteswara Rao; Ramasamy, Sureshkumar; Pundle, Archana (ACS Omega, 2020)
Penicillin V acylase (PVA, EC 3.5.1.11) hydrolyzes the side chain of phenoxymethylpenicillin (Pen V) and finds application in the manufacture of the pharmaceutical intermediate 6-aminopenicillanic acid (6-APA). Here, we report the scale-up of cultivation of Escherichia coli whole cells expressing a highly active PVA from Pectobacterium atrosepticum and their encapsulation in polyvinyl alcohol-poly(ethylene glycol) Lentikats hydrogels. A biocatalytic process for the hydrolysis of 2% (w/v) Pen V was set up in a 2 L reactor using the Lentikats-immobilized whole cells, with a customized setup to enable continuous downstream processing of the reaction products. The biocatalytic reaction afforded complete conversion of Pen V for 10 reaction cycles, with an overall 90% conversion up to 50 cycles. The bioprocess was further scaled up to the pilot-scale at 10 L, enabling complete conversion of Pen V to 6-APA for 10 cycles. The 6-APA and phenoxy acetic acid products were recovered from downstream processing with isolated yields of 85-90 and 87-92%, respectively. Immobilization in Lentikats beads improved the stability of the whole cells on storage, maintaining 90-100% activity and similar conversion efficiency after 3 months at 4 degrees C. The robust PVA biocatalyst can be employed in a continuous process to provide a sustainable route for bulk 6-APA production from Pen V.

Protein misfolding and aggregation of tau protein in alzheimer’s disease - Chandrashekar, Madhura; Chinnathambi, Subashchandrabose (Advances in Bioengineering, 2020)
Protein misfolding has interestingly been referred to as the ‘dark side’ of the protein world. The cytotoxicity of misfolded and unfolded polypeptides is due to an overwhelmed quality control system, mainly comprising molecular chaperones to assist in folding, the unfolded protein response (UPR) in the endoplasmic reticulum and the heat shock response (HSR) in the cytosol, which are aimed at clearing misfolded proteins and their early aggregates. When misfolded/unfolded polypeptides exceed the quality control measures of the chaperone–ubiquitin–proteasome clearing system, they form toxic pre-fibrillar aggregates which interact with the cell membrane, disrupting redox potential due to aggregate organization into non-specific membrane pores. In most cases, increases in intracellular free Ca²⁺ and consequent disruption of the redox potential are among the earliest biochemical alterations in exposed cells. An improved understanding of the mechanisms of protein misfolding and intermediate structures that lead from monomers to oligomers ready to aggregate could provide crucial impetus to therapeutic interventions such as upregulating molecular chaperone machinery, use of antibodies and high throughput screening of promising candidate molecules.

Proteomic analysis detects deregulated reverse cholesterol transport in human subjects with ST-segment elevation myocardial infarction (vol 222, 103796, 2020) - Das, Apabrita Ayan; Choudhury, Kamalika Roy; Jagadeeshaprasad, M. G.; Kulkarni, Mahesh J.; Mondal, Prakash Chandra; Bandyopadhyay, Arun (Journal of Proteomics, 2020)

Proteomic analysis detects deregulated reverse cholesterol transport in human subjects with ST-segment elevation myocardial infarction - Das, Apabrita Ayan; Choudhury, Kamalika Roy; Jagadeeshaprasad, M. G.; Kulkarni, Mahesh J.; Mondal, Prakash Chandra; Bandyopadhyay, Arun (Journal of Proteomics, 2020)
Reverse cholesterol transport (RCT) plays a critical role in removing cholesterol from the arterial wall. However, very few reports directly relate chronic inflammation and RCT with atherosclerosis. The present study was undertaken to investigate clinical implications of significantly altered circulating proteins in subjects with ST-segment elevation myocardial infarction (STEMI) in the manifestation of atherosclerotic events. Using a casecontrol design, more than 2500 proteins in both STEMI and healthy control subjects were identified by Orbitrap mass spectrometer. Quantitative proteomics study revealed downregulation of 26 proteins while expression of 38 proteins increased significantly in STEMI subjects compared to healthy controls. Pathway enrichment analyses indicated that most of the identified proteins were related to chronic inflammation, atherosclerosis, and RCT. Altered proteins such as AZGP1, ABCA5, Calicin, PGLYRP2, HAVCR2 and C17ORF57 were further validated by Western blotting analysis of human plasma. Pathophysiological significance was studied using macrophage derived foam cell for their critical role in RCT which indicated the imbalance of RCT via the interaction of AZGP1 with CD36. In summary, this study revealed a unique relationship of some novel proteins apparently responsible for impaired RCT and chronic inflammation leading to atherothrombosis and myocardial infarction. Significance: In the present study we identified >= 2500 unique circulating proteins in healthy control and clinically diagnosed STEMI subjects among which 423 proteins were found to be common in both the groups. We further show 64 proteins significantly different between healthy control and STEMI subjects. Proteomic analyses reveal a panel of proteins associated with atherosclerosis and STEMI. One of the proteins, AZGP1, an adipokine, is likely to act as the missing link between chronic inflammation and cholesterol transport. Deregulation of reverse cholesterol transport might be orchestrated by AZGP1, CD36, ABCA5, and PPARy in STEMI subjects. The present study employs shotgun and quantitative proteomics followed by in vitro validations demonstrating a biochemical basis for reverse cholesterol transport in the local milieu of the luminal wall of the artery which are critical for plaque build-up and atherosclerosis.
Keywords: Atherosclerosis; AZGP1; CD36; Plasma proteomics; Reverse cholesterol transport; STEMI

Protonation-induced dynamic allostery in PDZ domain: evidence of perturbation-independent universal response network - Kumawat, Amit; Chakrabarty, Suman (Journal of Physical Chemistry Letters, 2020)
Dynamic allostery is a relatively new paradigm where certain external perturbations may lead to modulation of conformational dynamics at a distant part of a protein without significant changes in the overall structure. While most well-characterized examples of dynamic allostery involve binding with other entities like small molecules, peptides, or nucleic acids, in this work we demonstrate that chemical modifications like protonation may lead to significant dynamical allosteric response in a PDZ domain protein. Tuning the protonation states of two histidine residues (H317 and H372), we identify the allosteric pathways responsible for the dynamic response. Interestingly, the same set of residues that constitute the allosteric response network upon ligand binding seem to be responsible for protonation-induced dynamic allostery. Thus, we propose the existence of an inherent universal response network in signaling proteins, where the same set of residues can respond to varying types of external perturbations in terms of rearrangement of hydrogen-bonded network and redistribution of electrostatic interaction energies.

PVDF/BaTiO3 films with nanocellulose impregnation: investigation of structural, morphological and mechanical properties - Ram, Farsa; Kaviraj, P.; Pramanik, R.; Krishnan, Amrutha; Shanmuganathan, Kadhiravan; Arockiarajan, A. (Journal of Alloys and Compounds, 2020)
Polyvinylidene fluoride (PVDF) composite films have witnessed widespread applications in biomedical and flexible electronic devices in recent years. These applications require a material that has enhanced electrical properties, mechanical flexibility along with sufficient strength. A lot of research has been carried out to enhance the piezoelectric and dielectric properties of the PVDF composite films. However, the improvements in the mechanical properties of nano filler reinforced PVDF composite films has not received due attention. In this regard, the present work focuses towards enhancing the mechanical strength and load-bearing capability of PVDF, by preparing composites of PVDF films impregnated with Cellulose Nanocrystals (CNC) and Barium Titanate (BTO) nanoparticles. Solution casting method was adapted to fabricate the PVDF/BTO/CNC films. X-ray diffractograms and FTIR (Fourier Transform infrared spectroscopy) corroborate the presence of ferroelectric gamma phase in PVDF. Mechanical and viscoelastic measurements have been carried out to examine the influence of CNC and BTO nano fillers in the PVDF matrix. The addition of CNC and BTO in PVDF film has improved the mechanical strength significantly. The stress achieved for PVDF/5% BTO and PVDF/5% BTO with 0.9% of CNC at 5% strain was 17% and 130% higher than the pristine PVDF, respectively. This study can be helpful for the design engineers to meet custom/specific requirements for a myriad of end- user applications such as piezoelectric nanogenerators. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: BaTiO3; Composite films; Mechanics; Morphology; Nanocellulose; PVDF

Palladium supported on magnesium hydroxyl fluoride: an effective acid catalyst for the hydrogenation of imines and N-heterocycles - Kokane, Reshma; Corre, Yann; Kemnitz, Erhard; Dongare, Mohan K.; Agbossou-Niedercorn, Francine; Michon, Christophe; Umbarkar, Shubhangi B. (New Journal of Chemistry, 2021)
Palladium catalysts supported on acidic fluorinated magnesium hydroxide Pd/MgF2-x(OH)(x) were prepared through precipitation or impregnation methods. Applications to the hydrogenation of various aldimines and ketimines resulted in good catalytic activities at mild temperatures using one atmosphere of hydrogen. Quinolines, pyridines and other N-heterocycles were successfully hydrogenated at higher temperature and hydrogen pressure using low palladium loadings and without the use of any acid additive. Such reactivity trend confirmed the positive effect of the Bronsted and Lewis acid sites from the fluorinated magnesium hydroxide support resulting in the effective pre-activation of N-heterocycle substrates and therefore in the good catalytic activity of the palladium nanoparticles during the hydrogenations. As demonstrated in the hydrogenation of imines, the catalyst was recycled up to 10 times without either loss of activity or palladium leaching.

Partially bio-based furyl-functionalized organosoluble poly(ether ether ketone)s - Kuhire, Sachin S.; Talanikar, Aniket A.; Tawade, V, Bhausaheb; Nagane, Samadhan S.; Wadgaonkar, Prakash P. (Polymer International, 2021)
A new series of partially bio-based (co)poly(ether ether ketone)s bearing pendent furyl groups was synthesized by nucleophilic aromatic substitution polycondensation of varying molar proportions of 4,4 `-(furan-2-ylmethylene)bis(2-methoxyphenol) and bisphenol-A with 4,4 `-difluorobenzophenone. The chemical structures, compositions and random nature of (co)poly(ether ether ketone)s were confirmed by NMR spectroscopy. Inherent viscosities and number-average molecular weights of the (co)poly(ether ether ketone)s were in the range 0.74-2.90 dL g(-1) and 33 500-46 300 g mol(-1), respectively, indicating the formation of reasonably high molecular weight polymers. (Co)poly(ether ether ketone)s were readily soluble in common organic solvents and could be cast into tough, transparent and flexible films from chloroform solutions. (Co)poly(ether ether ketone)s exhibited 10% weight loss and glass transition temperatures in the range 429-464 and 152-156 degrees C, respectively. A representative copoly(ether ether ketone) was crosslinked with 1,1 `-(methylenedi-1,4-phenylene)bismaleimide via Diels-Alder reaction to form a crosslinked polymer which showed improved mechanical properties and was recycled twice without significant loss of mechanical properties. Diels-Alder/retro Diels-Alder reaction was demonstrated by studies of sol-gel transformation, solubility tests, DSC and stress-strain measurements. (c) 2020 Society of Chemical Industry
Keywords: aromatic poly(ether ether ketone)s; bio-based; crosslinking; Diels-Alder reaction; pendent furyl groups

Partially bio-based triarylamine-containing polyimides: synthesis, characterization and evaluation in non-volatile memory device applications - Chatterjee, Deepshikha; Jadhav, Uday A.; Javaregowda, Bharathkumar H.; Dongale, Tukaram D.; Patil, Pramod S.; Wadgaonkar, Prakash P. (European Polymer Journal, 2021)
A new triarylamine-containing diamine, viz. 4, 4'-diamino-4 `' pentadecyltriphenylamine was synthesised starting from cashew nut shell liquid (CNSL) - a non-edible by-product of cashew processing industry. Three new partially bio-based triarylamine-containing polyimides were synthesised by one-step high temperature solution poly-condensation of 4, 4'-diamino-4 `' pentadecyltriphenylamine with aromatic dianhydrides, namely, 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 4,4'-oxydiphthalic anhydride (ODPA) and 4,4'-(hexa-fluoroisopropylidene) diphthalic anhydride (6-FDA). Polyimides were determined to be of reasonably high molecular weights as inherent viscosity and number average molecular weights (M-n, Polystyrene standard) values were in the range 0.54-0.60 dL g(-1) and 26,800-43,500 g mol(-1), respectively. Polyimides exhibited excellent solubility in common organic solvents and film-forming nature along with reasonably good thermal properties as indicated by temperature for 10% weight loss (T-10) and glass transition temperatures (T-g) which were in the range 418-447 and 165-225 degrees C, respectively. The optical and electrochemical band-gap values were in the range of 1.95-1.98 eV and 1.671-1.745 eV, respectively. Among triarylamine-containing polyimide devices, BPDA-based device showed acceptable current-voltage and non-volatile memory properties such as the endurance of 500 cycles and 1000 s of retention time. The conduction mechanism developed in the memory devices was also explored and was found to follow Ohmic and Schottky conduction mechanisms.
Keywords: Bio-based polyimides; CNSL; Memory device; pentadecyl; Triarylamine

Pd(II)-catalyzed chemoselective acetoxylation of C(sp(2))-H and C(sp(3))-H bonds in tertiary amides - Vijaykumar, Muniyappa; Punji, Benudhar (Journal of Organic Chemistry, 2021)
Palladium-catalyzed chemoselective C(sp(2))-H and C(sp(3))-H acetoxylation of synthetically useful tertiary amides is reported under relatively mild reaction conditions. This protocol proceeds through the assistance of a weakly coordinated directing group (C = O) and requires low catalyst (1.0 mol %) loading. Diverse functionalities, such as C(sp(2))-Cl, C(sp(3))-Cl, -CF3, -COOEt, and -NO2 groups, including morpholinyl, piperazinyl, and pyrrolidinyl heterocycles, are compatible under the reaction conditions. Further functionalization of this protocol is demonstrated by hydrolysis to alcohols, alcohol-acids, as well as reduction to tertiary amines. A preliminary kinetic isotope effect study supported the rate-limiting C-H bond activation process.

PdP/WO3 multi-functional catalyst with high activity and stability for direct liquid fuel cells (DLFCs) - Kumar, Sachin; Soni, Roby; Kurungot, Sreekumar (Sustainable Energy & Fuels, 2021)
Direct liquid fuel cells are energy conversion devices which utilize formate and methanol as fuels. These systems are relieved of the problem of H-2 transport and storage, making them highly desirable for various practical applications. However, the low stability and activity of carbon supported catalysts such as Pt/C both in the anode and cathode is a critical hindering factor towards their further development. As a practical solution to overcome this issue, in this work, we report on the development of phosphorus-doped palladium (PdP) nanoparticle-supported tungsten oxide (WO3) nanorods (PdP/WO3) as a versatile multifunctional catalyst for facilitating the oxidation of formate and methanol in the anode and the oxygen reduction reaction (ORR) in the cathode. Strong metal-support interactions and electronic modifications incurred by the doped phosphorus help this system to achieve desirable properties to enable it to effectively function both for the anode and cathode applications. PdP/WO3 showed 16-times higher mass activity compared to Pt/C even after 3000 start/stop cycles for the ORR. For formate and methanol oxidation, PdP/WO3 exhibited current densities of 0.50 and 0.734 A mg(Pd)(-1), respectively, outperforming the state-of-the-art catalysts. With these bifunctional features, PdP/WO3 stands out as a potential system to be used as an anode and cathode catalyst in direct liquid fuel cells, all the while offering an opportunity for the development of carbon-free electrocatalysts.

PEGylated ethyl cellulose micelles as a nanocarrier for drug delivery - Singam, Amarnath; Killi, Naresh; Patel, Pratikshkumar R.; Gundloori, Rathna V. N. (RSC Advances, 2021)
Natural polymers provide a better alternative to synthetic polymers in the domain of drug delivery systems (DDSs) because of their renewability, biocompatibility, and low immunogenicity; therefore, they are being studied for the development of bulk/nanoformulations. Likewise, current methods for engineering natural polymers into micelles are in their infancy, and in-depth studies are required using natural polymers as controlled DDSs. Accordingly, in our present study, a new micellar DDS was synthesized using ethyl cellulose (EC) grafted with polyethylene glycol (PEG); it was characterized, its properties, cell toxicity, and hemocompatibility were evaluated, and its drug release kinetics were demonstrated using doxorubicin (DOX) as a model drug. Briefly, EC was grafted with PEG to form the amphiphilic copolymers EC-PEG1 and EC-PEG2 with varying PEG concentrations, and nano-micelles were prepared with and without the drug (DOX) via a dialysis method; the critical micelle concentrations (CMCs) were recorded to be 0.03 mg mL(-1) and 0.00193 mg mL(-1) for EC-PEG1 and EC-PEG2, respectively. The physicochemical properties of the respective nano-micelles were evaluated via various characterization techniques. The morphologies of the nano-micelles were analyzed via transmission electron microscopy (TEM), and the average size of the nano-micelles was recorded to be similar to 80 nm. In vitro, drug release studies were done for 48 h, where 100% DOX release was recorded at pH 5.5 and 52% DOX release was recorded at pH 7.4 from the micelles. In addition, cytotoxicity studies suggested that DOX-loaded micelles were potent in killing MDA-MB-231 and MCF-7 cancer cells, and the blank micelles were non-toxic toward cancerous and normal cells. A cellular uptake study via fluorescence microscopy indicated the internalization of DOX-loaded micelles by cancer cells, delivering the DOX into the cellular compartments. Based on these studies, we concluded that the developed material should be studied further via in vivo studies to understand its potential as a controlled DDS to treat cancer.

Performance of Aspergillus niger (NCIM 563) phytase based feed supplement for broiler growth and phosphorus excretion - Puppala, Kumar Raja; Buddhiwant, Priyanka G.; Agawane, Sachin B.; Kadam, Avinash S.; Mote, Chandrashekhar S.; Lonkar, Vijaysinh D.; Khire, Jayant M.; Dharne, Mahesh S. (Biocatalysis and Agricultural Biotechnology, 2021)
Despite availability of commercial enzymes, the phytase produced from relatively inexpensive systems with high yields are gaining global attention in the feed industries in post-antibiotic era. We studied A. niger NCIM 563 Phytase produced in solid state fermentation (SSF) derived Koji powder and evaluated its utility in the poultry feed for broiler growth performance and phosphorous (P) excretion. The ability of phytase in the dried powder was estimated to dephytinize the poultry feed under simulated gastric conditions. Poultry feed was formulated using A. niger NCIM 563 phytase followed by a 42 days feed trial on broilers. After supplementation of phytase to the diet, there was a reduction of dietary P, maintained growth performance, skeletal development of broilers and reduced levels of phytic acid and available P in the litter. Extracellular phytase was able to replace up to 0.1% P in poultry feed. Minimal downstream processing a low-cost feed supplement with significant phytase activity could provide added advantage for anti-nutrition free poultry feed.
Keywords: Phosphorus; Phytase; Poultry feed; Solid state fermentation

Perspective on perovskite solar cells - Bhaumik, Saikat; Saha, Sudip K.; Rath, Arup K. (New Research Directions in Solar Energy Technologies, 2021)

Pharmacophore modeling of pretomanid (PA-824) derivatives for antitubercular potency against replicating and non-replicating Mycobacterium tuberculosis - Aher, Rahul Balasaheb; Sarkar, Dhiman (Journal of Biomolecular Structure & Dynamics, 2021)
Pretomanid (PA-824) is the recently (2019) approved drug for the treatment of extensively drug-resistant (XDR) TB and the multidrug-resistant (MDR) TB by US FDA. The experimental data of antitubercular activity of 543 pretomanid derivatives (total 6 datasets) against replicating (active) and non-replicating (dormant) forms of Mycobacterium tuberculosis (strain H37Rv) are available in the literature. Such vast experimental data of pretomanid derivatives against both of these endpoints, and recent approval of pretomanid molecule as a drug encouraged us to utilize this existing experimental information for the development of the 3D-pharmacophore models. The developed model (Hypo-1, MABA) showed the three physicochemical features namely, the oxygen atom of nitro group (HBA_1), fused pyran ring of imidazopyran heterocycle (HYAl_2) and the 4-fluorophenyl moiety (HYAr_3) are crucial for the antitubercular activity against replicating M. tb. Subsequently, the pharmacophore model (Hypo-1, LORA) developed against the non-replicating form of M. tb also showed the contribution of three physicochemical features namely, the 4-tri-fluoromethyl group (HYAl_2) and both the phenyl groups (HYAr_3, HYAr_4) of biaryl moiety in increasing the antitubercular activity. Both the pharmacophoric classifier models showed the classification accuracies of 82.98 and 74.42% for the training set compounds, and 63.91 and 61.60% for the test set compounds respectively, for labelling the compounds into higher and lower active classes. Both the models were also found to be retaining the higher active compounds in top 1.00% of the total number of compounds (decoys and actives), after performing the decoy set screening. Communicated by Ramaswamy H. Sarma
Keywords: LORA assay; MABA assay; Mycobacterium tuberculosis; non-replicating M; pharmacophore modeling; pretomanid derivatives; replicating M; tuberculosis; virtual screening

Pharmacore maping based on docking, ADME/toxicity, virtual screening on 3,5-dimethyl-1,3,4-hexanetriol and dodecanoic acid derivates for anticancer inhibitors - Prakash, Palanisamy; Vijayasarathi, Durairaj; Selvam, Kuppusamy; Karthi, Sengodan; Manivasagaperumal, Rengarajan (Journal of Biomolecular Structure & Dynamics, 2021)
Plants produced natural generating products play a significant role in drug discovery of new bioactive compounds and these are used for advancement of innovative curative drugs for specific target health diseases. In this study Docking and ADME/T virtual screening method are apply for in drug discovery and can be divided into ligand- and target structure-based. The aim of this study was to analyze theDecalepis hamiltoniiisolated compounds by using the evaluation of molecular docking and virtual screening of anticancer drugs. MOE docking ADME/Toxicity and virtual screening approaches. A docking energy -12.97 kcal/mol; -9.93- kcal/mol on cancer responsible protein was targeted. Further, the compounds were filtered through the rule of five, ADME/Toxicity risk and synthetic accessibility. The active compound were then docked to recognize the possible target binding pocket to obtain a set of a ligand poses and to prioritize the predicted active compounds. The scrutinize compounds, as well as their metabolites were evaluated for different pharmacokinetics parameter such as ADME/Toxicity. Therefore, the result shows that a large number of compounds were found to be ADME/toxicity positive to be a positive drug molecule against cancer, selected compounds under study satisfies parameters for ADME and Toxicity properties. The present study demonstrate to identifying the novel structures which are having similar structural feature with like activity with respect to the compounds 3,5-Dimethyl-1,3,4-Hexanetriol and Dodecanoic acid that are shown best binding energy with the receptors 4igk and 4b3z respectively. This study may provide significant clues for discovery novel drug inhibitors for cancer properties.
Keywords: ADME; Decalepis hamiltonii; docking; drug discovery; Toxicity; virtual screening

pH-dependent protein stability switch coupled to the perturbed pKa of a single ionizable residue - Mishra, Prajna; Patni, Divya; Jha, Santosh Kumar (Biophysical Chemistry, 2021)
The contribution of electrostatic interactions in protein stability has not been fully understood. Burial of an ionizable amino acid inside the hydrophobic protein core can affect its ionization equilibrium and shift its pKa differentially in the native (N) and unfolded (U) states of a protein and this coupling between the folding/ unfolding cycle and the ionization equilibria of the ionizable residue can substantially influence the protein stability. Here, we studied the coupling of the folding/unfolding cycle with the ionization of a buried ionizable residue in a multi-domain protein, Human Serum Albumin (HSA) using fluorescence spectroscopy. A pHdependent change in the stability of HSA was observed in the near native pH range (pH 6.0-9.0). The protonation-deprotonation equilibrium of a single thiol residue that is buried in the protein structure was identified to give rise to the pH-dependent protein stability. We quantified the pKa of the thiol residue in the N and the U states. The mean pKa of the thiol in the N state was upshifted by 0.5 units to 8.7 due to the burial of the thiol in the protein structure. Surprisingly, the mean pKa of the thiol in the U state was observed to be downshifted by 1.3 units to 6.9. These results indicate that some charged residues are spatially proximal to the thiol group in the U state. Our results suggest that, in addition to the N state, electrostatic interactions in the U state are important determinants of protein stability.
Keywords: electrostatic interactions; Fluorescence spectroscopy; Thermodynamic stability; Unfolded proteins

Phosphine-free manganese(II)-catalyst enables acceptorless dehydrogenative coupling of alcohols with indoles - Yadav, Vinita; Balaraman, Ekambaram; Mhaske, Santosh B. (Advanced Synthesis & Catalysis, 2021)
Herein, an air-stable, molecularly defined NNN-Mn(II) pincer complex catalyzed acceptorless dehydrogenative coupling of alcohols with indoles is reported. A wide variety of symmetrical and unsymmetrical bis(indolyl)methane derivatives as well as some structurally important products such as Vibrindole A, Turbomycin B alkaloid, Antileukemic, and Anticancer agents were synthesized. Mechanistic studies illustrate the importance of the NH moiety in the complex and the crucial role of metal-ligand cooperation during catalysis.
Keywords: acceptorless dehydrogenation; Alcohol; Indole; manganese; phosphine-free

Phosphite mediated asymmetric N to C migration for the synthesis of chiral heterocycles from primary amines - Rani, Soniya; Dash, Soumya Ranjan; Bera, Asish; Alam, Md Nirshad; Vanka, Kumar; Maity, Pradip (Chemical Science, 2021)
A phosphite mediated stereoretentive C-H alkylation of N-alkylpyridinium salts derived from chiral primary amines was achieved. The reaction proceeds through the activation of the N-alkylpyridinium salt substrate with a nucleophilic phosphite catalyst, followed by a base mediated [1,2] aza-Wittig rearrangement and subsequent catalyst dissociation for an overall N to C-2 alkyl migration. The scope and degree of stereoretention were studied, and both experimental and theoretical investigations were performed to support an unprecedented aza-Wittig rearrangement-rearomatization sequence. A catalytic enantioselective version starting with racemic starting material and chiral phosphite catalyst was also established following our understanding of the stereoretentive process. This method provides efficient access to tertiary and quaternary stereogenic centers in pyridine systems, which are prevalent in drugs, bioactive natural products, chiral ligands, and catalysts.

Phosphoinositides signaling modulates microglial actin remodeling and phagocytosis in Alzheimer's disease - Desale, Smita Eknath; Chinnathambi, Subashchandrabose (Cell Communication and Signaling, 2021)
Alzheimer's disease is one of the neurodegenerative diseases, characterized by the accumulation of abnormal protein deposits, which disrupts signal transduction in neurons and other glia cells. The pathological protein in neurodegenerative diseases, Tau and amyloid-P contribute to the disrupted microglial signaling pathways, actin cytoskeleton, and cellular receptor expression. The important secondary messenger lipids i.e., phosphatidylinositols are largely affected by protein deposits of amyloid-beta in Alzheimer's disease. Phosphatidylinositols are the product of different phosphatidylinositol kinases and the state of phosphorylation at D3, D4, and D5 positions of inositol ring. Phosphatidylinositol 3,4,5-triphosphate (PI 3, 4, 5-P3) involves in phagocytic cup formation, cell polarization, whereas Phosphatidylinositol 4,5-bisphosphate (PI 4, 5-P2)-mediates the process of phagosomes formation and further its fusion with early endosome.. The necessary activation of actin-binding proteins such as Rac, WAVE complex, and ARP2/3 complex for the actin polymerization in the process of phagocytosis, migration is regulated and maintained by PI 3, 4, 5-P3 and PI 4, 5-P2. The ratio and types of fatty acid intake can influence the intracellular secondary lipid messengers along with the cellular content of phaphatidylcholine and phosphatidylethanolamine. The Amyloid-beta deposits and extracellular Tau seeds disrupt phosphatidylinositides level and actin cytoskeletal network that hamper microglial-signaling pathways in AD. We hypothesize that being a lipid species intracellular levels of phosphatidylinositol would be regulated by dietary fatty acids. Further we are interested to understand phosphoinositide-based signaling cascades in phagocytosis and actin remodeling.
Keywords: actin remodeling; Alzheimer's disease; Dietary fatty acids; Phagocytosis; Phosphoinositides; PI3K signaling

Phosphorus ligands in hydroformylation and hydrogenation: a personal account - Tewari, Tanuja; Kumar, Rohit; Chandanshive, Amol C.; Chikkali, Samir H. (Chemical Record, 2021)
Metal-catalyzed hydroformylation and hydrogenation heavily rely on ligands, among which phosphorous ligands play a pivotal role. This personal account presents a selection of three distinct classes of phosphorous ligands, namely, monodentate meta-substituted phosphinites, bis-phosphites, and P-chiral supramolecular phosphines, developed in our group. The synthesis of these ligands, isolation, characterization, and their performance in transition metal-catalyzed hydroformylation, isomerizing hydroformylation, and asymmetric hydrogenation of olefins is summarized. The state of the art development in iron-catalyzed hydroformylation of alkenes and our contributions to the field is discussed. Use of phosphines enabled iron-catalyzed hydroformylation of alkenes under mild conditions. Thus, this account demonstrates the central role of phosphorus ligands in industrially relevant transformations such as hydrogenation and hydroformylation. The seemingly matured field of ligand discovery still holds significant potential and will steer the field of homogeneous catalysis.
Keywords: Homogeneous catalysis; Hydroformylation; Hydrogenation; Olefins; Phosphorus ligands

Photoactivatable prodrug for simultaneous release of mertansine and CO along with a BODIPY derivative as a luminescent marker in mitochondria: a proof of concept for NIR image-guided cancer therapy - Tiwari, Rajeshwari; Shinde, Prashant S.; Sreedharan, Sreejesh; Dey, Anik Kumar; Vallis, Katherine A.; Mhaske, Santosh B.; Pramanik, Sumit kumar; Das, Amitava (Chemical Science, 2021)
Controlled and efficient activation is the crucial aspect of designing an effective prodrug. Herein we demonstrate a proof of concept for a light activatable prodrug with desired organelle specificity. Mertansine, a benzoansamacrolide, is an efficient microtubule-targeting compound that binds at or near the vinblastine-binding site in the mitochondrial region to induce mitotic arrest and cell death through apoptosis. Despite its efficacy even in the nanomolar level, this has failed in stage 2 of human clinical trials owing to the lack of drug specificity and the deleterious systemic toxicity. To get around this problem, a recent trend is to develop an antibody-conjugatable maytansinoid with improved tumor/organelle-specificity and lesser systematic toxicity. Endogenous CO is recognized as a regulator of cellular function and for its obligatory role in cell apoptosis. CO blocks the proliferation of cancer cells and effector T cells, and the primary target is reported to be the mitochondria. We report herein a new mitochondria-specific prodrug conjugate (Pro-DC) that undergoes a photocleavage reaction on irradiation with a 400 nm source (1.0 mW cm(-2)) to induce a simultaneous release of the therapeutic components mertansine and CO along with a BODIPY derivative (BODIPY(PPH3)(2)) as a luminescent marker in the mitochondrial matrix. The efficacy of the process is demonstrated using MCF-7 cells and could effectively be visualized by probing the intracellular luminescence of BODIPY(PPH3)(2). This provides a proof-of-concept for designing a prodrug for image-guided combination therapy for mainstream treatment of cancer.

Photoactive anthraquinone-based host-guest assembly for long-lived charge separation - Jha, Ajay; Mote, Kaustubh R.; Chandra, Suman; Madhu, Perunthiruthy K.; Dasgupta, Jyotishman (Journal of Physical Chemistry C, 2021)
Porous 2D covalent organic frameworks (COF) that are assembled axially through weak p-stacking interactions can provide reticular charge transport channels while playing host to kinetically stabilized reactive molecular redox states. Here we demonstrate a host-guest supramolecular charge transfer (CT) assembly using photoactive anthraquinone-based COF as an acceptor while incarcerating the electron donor N,N-dimethylaniline (DMA) inside it. Employing femtosecond broadband transient absorption spectroscopy in combination with electron paramagnetic resonance (EPR) studies, we show that the CT occurs rapidly within <110 fs after photoexcitation, subsequently leading to long-lived charge separation with 13% quantum efficiency at room temperature. The photoinduced EPR signature of the long-lived confined DMA cation radical confirms the disparate regions of charge localization while H-1-C-13 correlation experiments using solid-state NMR spectroscopy enumerate the packing of the amines inside the host-guest COF assembly. Our work demonstrates the potency of charge transport pathways in supramolecular assemblies for efficient charge separation which if optimally tuned should pave the way for COF-based photocatalytic reaction centers.

Photodynamic sensitizers modulate cytoskeleton structural dynamics in neuronal cells - Dubey, Tushar; Chinnathambi, Subashchandrabose (Cytoskeleton, 2021)
The neuronal cytoskeleton plays a crucial role in maintaining cell integrity and functioning of neurons. Cytoskeleton deformities have been reported to be associated with neurodegenerative diseases thus; cytoskeleton can be targeted for therapeutic strategies. The therapeutic application of photosensitive molecule is termed as photodynamic therapy (PDT). PDT has been applied in the field of dermatology, cancer biology, and antimicrobial therapy. PDT induces several changes in cells, which include induction of apoptosis, DNA damage, and induction of inflammatory response. PDT has been also reported to modulate cytoskeleton such as actin dynamics. The in vitro studies suggested that PDT using dyes such as Toluidine Blue and Rose Bengal effectively modulated the actin cytoskeleton, neurite outgrowth, tubulin, and Tau aggregation. In this review, we focused on the effect of photosensitized molecules on various cytoskeleton proteins. We hypothesize that PDT could have potency against Alzheimer's disease and other neurodegenerative disorders.
Keywords: Actin; Alzheimer' cytoskeleton modulation; neuronal cytoskeleton; photodynamic therapy; s disease; Tubulin

Photodynamic treatment modulates various GTPase and cellular signalling pathways in Tauopathy - Dubey, Tushar; Chinnathambi, Subashchandrabose (Small GTPases, 2021)
ABSTRACTThe application of photo-excited dyes for treatment is known as photodynamic therapy (PDT). PDT is known to target GTPase proteins in cells, which are the key proteins of diverse signalling cascades which ultimately modulate cell proliferation and death. Cytoskeletal proteins play critical roles in maintaining cell integrity and cell division. Whereas, it was also observed that in neuronal cells PDT modulated actin and tubulin resulting in increased neurite growth and filopodia. Recent studies supported the role of PDT in dissolving the extracellular amyloid beta aggregates and intracellular Tau aggregates, which indicated the potential role of PDT in neurodegeneration. The advancement in the field of PDT led to its clinical approval in treatment of cancers, brain tumour, and dermatological acne. Although several question need to be answered for application of PDT in neuronal cells, but the primary studies gave a hint that it can emerge as potential therapy in neural cells.

Photoinduced multicomponent regioselective synthesis of 1,4,5-trisubstituted-1,2,3-triazoles: transition metal-, azide- and oxidant-free protocol - Sai Allaka, Bhargava; Basavoju, Srinivas; Rama Krishna, Gamidi (Advanced Synthesis & Catalysis, 2021)
A transition metal- and azide-free approach is explored to synthesize 1,4,5-trisubstituted-1,2,3-triazoles under sunlight. The reaction proceeds via C-N and N-N bond formations. These regioselective 1,2,3-triazoles are obtained from isatin Schiff bases, benzaldehydes and tosylhydrazine in the presence of base. This protocol offers the structurally diverse 1,2,3-triazole derivatives with 75-90% yields.
Keywords: 1; 2; 3-triazoles; 4; 5-trisubstituted-1; azide- and oxidant free protocol; Cycloaddition; milder reaction conditions; molecular diversity; Multicomponent reaction; Regioselectivity; transition metal-

Physicochemical and in vitro antibacterial evaluation of metronidazole loaded eudragit S-100 nanofibrous mats for the intestinal drug delivery - Rade, Priyanka P.; Giram, Prabhanjan S.; Shitole, Ajinkya A.; Sharma, Neeti; Garnaik, Baijayantimala (Advanced Fiber Materials, 2021)
Metronidazole (MTZ) loaded Eudragit S-100 (ES-100) nonwoven nanofibrous mats were successfully electrospun and evaluated for intestinal drug delivery. MTZ was varied in the range of 1–15% (w/w) in ES-100 nanofibrous mats, the morphological characterization of nanofibrous mats was carried out using FE-SEM and the average diameter of nanofiber was found in the range 150–600 nm. WAXD and DSC demonstrated the amorphous nature of MTZ in ES-100 nanofibrous mats. Their contact angle analysis confirmed the hydrophobic nature. The mechanical strength of ES-100 nanofibrous mats decreased with increasing MTZ concentration. The drug release profiles showed 74% MTZ release from ES-100d within 2 h at pH 6.8 which is the colonic environment. Antibacterial activities against gram-positive bacteria (Staphylococcus aureus) and gram-negative bacteria (Escherichia coli) showed that the ES-100 nanofibrous mats loaded with MTZ exhibited good activity.

PINIR: a comprehensive information resource for Pin-II type protease inhibitors - Yadav, Nikhilesh K.; Saikhedkar, Nidhi S.; Giri, Ashok P. (BMC Plant Biology, 2021)
Background: Serine protease inhibitors belonging to the Potato type-II Inhibitor family Protease Inhibitors (Pin-II type PIs) are essential plant defense molecules. They are characterized by multiple inhibitory repeat domains, conserved disulfide bond pattern, and a tripeptide reactive center loop. These features of Pin-II type PIs make them potential molecules for protein engineering and designing inhibitors for agricultural and therapeutic applications. However, the diversity in these PIs remains unexplored due to the lack of annotated protein sequences and their functional attributes in the available databases. Results: We have developed a database, PINIR (Pin-II type PIs Information Resource), by systematic collection and manual annotation of 415 Pin-II type PI protein sequences. For each PI, the number and position for signature sequences are specified: 695 domains, 75 linkers, 63 reactive center loops, and 10 disulfide bond patterns are identified and mapped. Database analysis revealed novel subcategories of PIs, species-correlated occurrence of inhibitory domains, reactive center loops, and disulfide bond patterns. By analyzing linker regions, we predict that alternative processing at linker regions could generate PI variants in the Solanaceae family. Conclusion: PINIR (https://pinir.ncl.res.in) provides a web interface for browsing and analyzing the protein sequences of Pin-II type PIs. Information about signature sequences, spatio-temporal expression, biochemical properties, gene sequences, and literature references are provided. Analysis of PINIR depicts conserved species-specific features of Pin-II type PI protein sequences. Diversity in the sequence of inhibitory domains and reactive loops directs potential applications to engineer Pin-II type PIs. The PINIR database will serve as a comprehensive information resource for further research into Pin-II type PIs.
Keywords: annotation; Data analysis; Database; Knowledge representation; Pin-II type protease inhibitor; Protein sequence analysis

Plasma-derived extracellular vesicles reveal galectin-3 binding protein as potential biomarker for early detection of glioma - Rana, Rashmi; Chauhan, Kirti; Gautam, Poonam; Kulkarni, Mahesh; Banarjee, Reema; Chugh, Parul; Chhabra, Satnam Singh; Acharya, Rajesh; Kalra, Samir Kumar; Gupta, Anshul; Jain, Sunila; Ganguly, Nirmal Kumar (Frontiers in Oncology, 2021)
{Gliomas are the most common type of the malignant brain tumor, which arise from glial cells. They make up about 40% of all primary brain tumors and around 70% of all primary malignant brain tumors. They can occur anywhere in the central nervous system (CNS) and have a poor prognosis. The average survival of glioma patients is approximately 6-15 months with poor aspects of life. In this edge, identification of proteins secreted by cancer cells is of special interest because it may provide a better understanding of tumor progression and provide early diagnosis of the diseases. Extracellular vesicles (EVs) were isolated from pooled plasma of healthy controls (n=03) and patients with different grades of glioma (Grade I or II or III
Keywords: blood-based biomarker; early detection; galectin-3 binding protein; plasma-derived extracellular vesicles; proteomics

PNA-mediated efflux inhibition as a therapeutic strategy towards overcoming drug resistance in Mycobacterium smegmatis - Ghosh, Saptarshi; Cotta, Karishma Berta; Hande, Aniket A.; Fernandes, Moneesha; Mehra, Sarika (Microbial Pathogenesis, 2021)
The emergence of antibiotic-resistant strains of Mycobacterium tuberculosis and the decelerating development of new and effective antibiotics has impaired the treatment of tuberculosis (TB). Efflux pump inhibitors (EPIs) have the potential to improve the efficacy of existing anti-TB drugs although with toxicity limitations. Peptide nucleic acids (PNAs), oligonucleotide mimics, by virtue of their high nucleic acid binding specificity have the capability to overcome this drawback. We, therefore, investigated the efflux pump inhibitory properties of a PNA designed against an efflux pump of Mycobacterium smegmatis. LfrA, an efflux pump found in M. smegmatis, is majorly involved in conferring innate drug resistance to this strain and, therefore, was selected as a target for gene silencing via PNA. qRT-PCR and EtBr assays confirmed the EPI activity of the anti-lfrA PNA. On testing the effect of the anti-lfrA PNA on the bactericidal activity of a fluoroquinolone, norfloxacin, we observed that 5 mu M of anti-lfrA PNA in combination with norfloxacin led to an enhanced killing of up to 2.5 log-fold against wild-type and a lab-generated multidrug resistant strain, exemplifying its potential in countering resistance. Improved efficacy was also observed against intra-macrophage mycobacteria, where the drug-PNA combination enhanced bacterial clearance by 1.3 log-fold. Further, no toxicity was observed with PNA concentrations up to 4 times higher than the efficacious anti-lfrA PNA concentration. Thus, PNA, as an adjuvant, presents a novel and viable approach to rejuvenate anti-TB therapeutics.
Keywords: Adjuvant; Antibiotic resistance; Antisense; Efflux pump; Gene silencing; Mycobacteria; Peptide nucleic acid (PNA)

Polyaryletherketone in energy conversion and storage devices - a highly tailorable material with versatile properties - Feroze Gooty Saleha, Wasim; Nalajala, Naresh; Neergat, Manoj (Polymer International, 2021)
Polymers have been a highly useful class of material for the last few decades owing to their ease of bulk production and fabrication. With the myriad of applications in day to day life, they have also found an important role in energy conversion and storage devices, not just as a housing material of the device but with an important role in the energy conversion process. Among the several polymers used in this area, polyaryletherketones (PAEKs) are one of the most versatile materials owing to their easy tailorability. The ether and ketone groups can be introduced in the main polymer chain in several ways to achieve the desired material properties. The main role of a polymer in an energy conversion device is that of a barrier to avoid the mixing of reactants and to selectively transport ions from one electrode to the other to maintain charge neutrality. The polymer membrane finds application in various electrochemical energy conversion devices such as fuel cells, lithium ion batteries, redox flow batteries, supercapacitors etc. The main focus of this work is to briefly review the extent of development in the PAEKs in various energy conversion and storage devices. (c) 2021 Society of Industrial Chemistry.
Keywords: electrolyte membrane; energy conversion and storage; fuel cells; lithium ion batteries; redox flow batteries; separator

Polycomb group methyltransferase StE(z)2 and deposition of H3K27me3 and H3K4me3 regulate the expression of tuberization genes in potato - Kumar, Amit; Kondhare, Kirtikumar R.; Malankar, Nilam N.; Banerjee, Anjan K. (Journal of Experimental Botany, 2021)
Polycomb repressive complex (PRC) group proteins regulate various developmental processes in plants by repressing target genes via H3K27 trimethylation, and they function antagonistically with H3K4 trimethylation mediated by Trithorax group proteins. Tuberization in potato has been widely studied, but the role of histone modifications in this process is unknown. Recently, we showed that overexpression of StMSI1, a PRC2 member, alters the expression of tuberization genes in potato. As MSI1 lacks histone-modification activity, we hypothesized that this altered expression could be caused by another PRC2 member, StE(z)2, a potential H3K27 methyltransferase in potato. Here, we demonstrate that a short-day photoperiod influences StE(z)2 expression in the leaves and stolons. StE(z)2 overexpression alters plant architecture and reduces tuber yield, whereas its knockdown enhances yield. ChIP-sequencing using stolons induced by short-days indicated that several genes related to tuberization and phytohormones, such as StBEL5/11/29, StSWEET11B, StGA2OX1, and StPIN1 carry H3K4me3 or H3K27me3 marks and/or are StE(z)2 targets. Interestingly, we observed that another important tuberization gene, StSP6A, is targeted by StE(z)2 in leaves and that it has increased deposition of H3K27me3 under long-day (non-induced) conditions compared to short days. Overall, our results show that StE(z)2 and deposition of H3K27me3 and/or H3K4me3 marks might regulate the expression of key tuberization genes in potato.
Keywords: ChIP-sequencing; Epigenetics; PcG; photoperiod; polycomb repressive complex; potato tuberization; short-day; Solanum tuberosum; StE(z)2

Polymer graphene-based nanofibers and their application for batteries - Mishra, Sasmita; Singh, Sandip; Singh, Ajeet (Electrospinning of Graphene, 2021)
Polymer graphene-based nanofibers are increasingly used in energy storage devices, especially in lithium-ion batteries and thus attracting more and more industrial and academic research in material chemistry. Metal-doped graphene-based polymer nanofibers are now gaining much attention and recently are successfully used in related energy storage devices, including supercapacitors and more. This chapter primarily focuses on a brief of nanofibers, electrospinning and graphene followed by the review of polymer graphene-based nanofibers in the present scenario.

Polymorphs and hydrates of the anticancer drug erlotinib: X-ray crystallography, phase transition and biopharmaceutical studies - Thorat, Shridhar H.; George, Christy P.; Shaligram, Parth S.; Suresha, P. R.; Gonnade, Rajesh G. (CrystEngComm, 2021)
Erlotinib, a non-small cell lung cancer BCS class II drug, was found to occur as two polymorphs and two hydrates depending on the crystallization conditions. The monohydrate (form III), which has been reported in patents and publications, is the preferred crystalline phase from solution crystallization. The other forms (polymorphs, forms I and II, and a trihydrate, form IV) are solvent and condition-specific. Form I was exclusively and reproducibly obtained from dried non-polar solvents (viz. toluene, benzene, and xylene) using a solution crystallization method under controlled conditions. In contrast, form II was obtained by the rotary evaporation technique under reduced pressure from polar solvents (viz. dichloromethane, ethyl acetate, acetone, and acetonitrile). Slow evaporation from polar and non-polar solvents under open conditions yielded form III crystals, whereas evaporation from acetone-acetonitrile-water mixtures yielded form IV crystals. DSC and variable temperature PXRD studies revealed form I to be the most stable phase while the other solid forms displayed thermally induced polymorphic transitions into form I crystals. Further, form I and form III are found to be stable over the 30-90% RH range. Further, form I displayed solution-mediated transformation into form III (monohydrate) when left to stand in the mother liquor for a longer duration (1-2 days). Similarly, the unstable form IV crystals transformed into the stable form III crystals within 1-2 h when exposed to an open atmosphere. Fast crystallization from polar solvents using the rotary evaporation technique enabled us to capture the metastable polymorph, form II. Early separation of form I from its mother liquor prevented its solution-mediated transformation into the monohydrate, form III. The water activity study revealed that form III is the most preferred solid phase in the presence of water. Dissolution rate measurements showed that the rate of form II is almost comparable to that of the marketed erlotinib hydrochloride. In contrast, for the other forms, the dissolution profiles showed a considerable decrease. Although the crystal structures of form I and form III have been published previously, this manuscript gives a comprehensive overview of the free base solid forms of erlotinib, the phase transitions amongst them and their biopharmaceutical properties.

Possible electron doping of geometrically perfect spin-1/2 kagome-lattice barlowite by reduced graphene oxide - Gupta, Kriti; Ninawe, Pranay; Jain, Anil; Dadwal, Arun; Anas, M.; Malik, V. K.; Yusuf, S. M.; Joy, Pattayil A.; Ballav, Nirmalya (Physical Review B, 2021)
Doping of quantum spin liquid (QSL) insulators by electron or hole leads to intriguing phase transitions to metallic and superconducting states. The barlowite family with geometrically perfect S = 1/2 kagome planes and tunable interkagome coupling is an emerging platform to realize spin-ordered, valence bond crystal, QSL states. Theoretical investigations on electron doping revealed localized states in the band gap of barlowite unlike metallicity in cuprate (Nd2CuO4). We present successful anchoring of phase-pure barlowite crystallites onto reduced graphene oxide (rGO). The resulting barlowite-rGO system was found to be an electrical semiconductor with Arrhenius activation energy of 0.07 eV. Semiconducting properties of the barlowite-rGO system were further modulated with retention of structural integrity. We have attributed such a transformation of electrical transport response to plausible electron doping thereby making charge-doping experiments on barlowite and its analogs propitious.

Practical synthesis of 5-hydroxy-2(5H)-furanone from furan - Subhash P. Chavan; Appasaheb L. Kadam (Results in Chemistry, 2021)
A simple, efficient and scalable method for the synthesis of 5-hydroxy-2(5H)-furanone from furan has been developed on a multigram scale. Oxidation of furan has been performed using oxone as the sole oxidant and water as a solvent, which makes this protocol practical and thus industrially applicable.
Keywords: 5-Hydroxy-2(5)-furanone; Furan oxidation; On-water reaction; Oxone; scalable synthesis

Priestia veravalensis sp. nov., isolated from coastal sample - Wagh, Vasudev S.; Ram, Hari; Dastager, Syed G. (Archives of Microbiology, 2021)
The taxonomic position of two isolates, SGD-V-76(T) and SGD-M-37, isolated from sediment sample of Veraval coast, India, was examined using the polyphasic taxonomic approach. The morphological and chemotaxonomic characteristics of these two organisms are typical of the genus Priestia. The phylogenetic analyses performed using almost complete 16S rRNA gene sequences demonstrated that the isolate belongs to the Bacillaceae family, and forms a clade within the cluster containing Priestia flexus MTCC 2909(T), Priestia aryabhattai B8W22(T) and Priestia megaterium KCTC 3007(T) and both strains showed highest similarity of > 98% with 3-29 nucleotide differences. The cell wall contained meso-diaminopimelic acid as the diagnostic diamino acid. The predominant isoprenoid quinone was MK-7 and the G + C content of strains was 37.5-37.7 mol%. However, the DNA-DNA hybridization and the phenotypic characteristics revealed that, the strain SGD-V-76(T) and strain SGD-M-37 are similar species but different from any known Priestia species with ANI values of 79.2, 79.3 and 79.2 and the dDDH values of 17.7, 17.8 and 18.0% respectively. On the basis of phenotypic characteristics, phylogenetic analysis and the results of biochemical and physiological tests, and genomic data strain SGD-V-76(T) was clearly distinguished from closely related members of the Priestia genus. Based on the above data analysis strain SGD-V-76(T) (= DSM28242(T) = KCTC33802(T) = CIP111056(T) = NCIM5510(T)) represents a novel species of the genus Priestia, and we propose the name Priestia veravalensis sp. nov.
Keywords: Coastal sediment; genome; Priestia; Veraval

Probiotics in the prophylaxis of COVID-19: something is better than nothing - Gohil, Kushal; Samson, Rachel; Dastager, Syed; Dharne, Mahesh (3 Biotech, 2021)
The new viral pandemic of COVID-19 is caused by a novel coronavirus (SARS-CoV-2) that has brought the world at another unprecedented crisis in terms of health and economy. The lack of specific therapeutics necessitates other strategies to prevent the spread of infection caused by this previously unknown viral etiological agent. Recent pieces of evidence have shown an association between COVID-19 disease and intestinal dysbiosis. Probiotics comprise living microbes that upon oral administration benefit human health by reshaping the composition of gut microbiota. The close kinship of the gastrointestinal and respiratory tract suggests why the dysfunction of one may incite illness in others. The emerging studies suggest the capability of probiotics to regulate immune responses in the respiratory system. The efficacy of probiotics has been studied previously on several respiratory tract viral infections. Therefore, the purpose of this review is to comprehend existing information on the gut mediated-pulmonary immunity conferred by probiotic bacteria, in the course of respiratory virus infections and administration as a prophylactic measure in COVID-19 pandemic in managing intestinal dysbiosis as well.
Keywords: Anti-viral; COVID-19; Gut-lung axis; Probiotics; Respiratory tract infection

Process-induced microstructure in viscose and lyocell regenerated cellulose fibers revealed by SAXS and SEM of acid-etched samples - Sharma, Aakash; Wankhede, Parnashri; Samant, Roopali; Nagarkar, Shailesh; Thakre, Shirish; Kumaraswamy, Guruswamy (ACS Applied Polymer Materials, 2021)
Regenerated cellulose fibers represent an important class of bioderived commercial fibers. The traditional viscose process requires the use of environmentally harmful carbon disulfide solvent to produce fibers. Lyocell fibers, produced using a more sustainable recent process, exhibit differences in properties from viscose. These differences arise from their semicrystalline microstructure, formed during fiber spinning. It is widely believed that regenerated cellulose fibers predominantly form fringed fibrillar crystals. We optimize acid etching, followed by SEM as an experimental tool to visualize this fibrillar structure. Acid etching provides sufficient topological contrast to directly visualize similar to O(10 nm) fibrils using field-emission scanning electron microscopy (SEM). We combine SEM with small-angle X-ray scattering (SAXS) to reveal other microstructural details. We observe a Bragg peak, indicating the coexistence of stacked lamellar structure with crystalline fibrils for viscose fibers, but not for lyocell. Viscose and lyocell fibers are characterized by partially oriented semicrystalline microstructure. We present a methodology to calculate the Lorentz correction for such microstructure and employ this to analyze the lamellar scattering from viscose fibers using a 1D correlation function approach. We characterize the lamellar microstructure after swelling viscose fibers with water and observe expansion of the Bragg spacing due to water absorption in the amorphous regions. Our data suggest that the water-induced plasticization of amorphous regions is inhomogeneous. Lamellar stacks that are more misoriented from the fiber direction exhibit lower swelling than those along the fiber direction. The experimental methods described in this work reveal interesting details of semicrystalline microstructure in regenerated cellulose fibers, with important implications for the mechanical response of dry and wet fibers. The methods developed here might find use in investigations of other polymer fibers as well.
Keywords: acid etching; crystalline lamellae; fibers; fibrils; Lorentz correction; Regenerated cellulose; SAXS

Prominence of Cu in a plasmonic Cu-Ag alloy decorated SiO2@S-doped C3N4 core-shell nanostructured photocatalyst towards enhanced visible light activity - Babu, Pradeepta; Dash, Soumya Ranjan; Behera, Arjun; Vijayaraghavan, T.; Ashok, Anuradha; Parida, Kulamani (Nanoscale Advances, 2021)
A series of Cu-Ag bimetal alloys decorated on SiO2 and the fabrication of few-layer S-doped graphitic carbon nitride (SC) warped over it to form a core-shell nanostructured morphology have been demonstrated and well characterized through various physiochemical techniques. HRTEM data confirmed the formation of a compact nanojunction between the SiO2 and SC, where Cu-Ag is embedded uniformly with an average particle size of 1.3 nm. The Ag : Cu (1 : 3) between SiO2 and SC produces 1730 mu mol h(-1) g(-1) of H-2 under visible light illumination. Moreover, 6.2-fold current enhancement in the case of Ag : Cu (1 : 3) as compared to the Ag-loaded core-shell nanostructured photocatalyst indicates higher electron-hole-pair separation. The excellent activity was due to the synergistic alloying and plasmonic effect of Ag and Cu. DFT studies reveal that the Cu atom in the Cu-Ag bimetal alloy plays a pivotal role in the generation of H-2, and the reaction proceeds via a 4-membered transition state. The mechanistic insight proceeds from the generation of hot electrons due to the LSPR effect and their transfer to the SC layer via a compact nanojunction.

Promoted mesoporous Fe-alumina catalysts for the non-oxidative dehydrogenation of isobutane - Venugopalan, Aswathy Thareparambil; Kandasamy, Prabu; Gupta, Nikitra Nihalchand; Thirumalaiswamy, Raja (Catalysis Communications, 2021)
Production of isobutene is commercially consequential and highly demanding from the end-use industries being a key platform molecule as well as an intermediate for a variety of value-added chemicals. Traditionally, isobutene is prepared via steam cracking and fluid catalytic cracking methods. However, the catalysts used in these conventional methods have disadvantages like coke formation, sintering, etc. In this study, the catalytic non-oxidative dehydrogenation of isobutane over acidic, alkaline, and noble metal promoted mesoporous iron-doped catalysts was investigated. Iron doping has a significant function in controlling isobutene selectivity. The synthesis method is crucial to achieve successful metal doping in the mesoporous alumina matrix. Promoted catalysts exhibited a notable difference in isobutane conversion with a marginal change in dehydrogenation selectivity. Silver promoted catalyst showed slightly higher isobutene yield due to the optimal catalytic properties. This catalyst was stable for a considerable duration, and coke deposition, as well as particle agglomeration, were observed to faintly inhibit the catalytic activity.
Keywords: iron; Isobutane; Isobutene; Mesoporous alumina; Non-oxidative dehydrogenation

Protonation-deprotonation switch controls the amyloid-like misfolding of nucleic-acid-binding domains of TDP-43 - Patni, Divya; Jha, Santosh Kumar (Journal of Physical Chemistry B, 2021)
Nutrient starvation stress acidifies the cytosol and leads to the formation of large protein assemblies and misfolded aggregates. However, how starvation stress is sensed at the molecular level and leads to protein misfolding is poorly understood. TDP-43 is a vital protein, which, under stress-like conditions, associates with stress granule proteins via its functional nucleic-acid-binding domains (TDP-43(t)(RRM)) and misfolds to form aberrant aggregates. Here, we show that the monomeric N form of TDP-43(t)(RRM) forms a misfolded amyloid-like protein assembly, beta form, in a pH-dependent manner and identified the critical protein side-chain residue whose protonation triggers its misfolding. We systematically mutated the three buried ionizable residues, D105, H166, and H256, to neutral amino acids to block the pH-dependent protonation-deprotonation titration of their side chain and studied their effect on the N-to-beta transition. We observed that D105A and H2S6Q resembled TDP-43(t)(RRM) in their pH-dependent misfolding behavior. However, H166Q retains the N-like secondary structure under low-pH conditions and does not show pH-dependent misfolding to the beta form. These results indicate that H166 is the critical side-chain residue whose protonation triggers the misfolding of TDP-43(t)(RRM) and shed light on how stress-induced misfolding of proteins during neurodegeneration could begin from site-specific triggers.

Protriptyline improves spatial memory and reduces oxidative damage by regulating NF kappa B-BDNF/CREB signaling axis in streptozotocin-induced rat model of Alzheimer's disease - Tiwari, Virendra; Mishra, Akanksha; Singh, Sonu; Mishra, Sandeep Kumar; Sahu, Kiran Kumari; Parul; Kulkarni, Mahesh J.; Shukla, Rakesh; Shukla, Shubha (Brain Research, 2021)
Antidepressants are well known to exert their role via upregulation of brain derived neurotrophic factor (BDNF). BDNF has been reported to exerts its neuroprotective effect in rodent and primate models as well as in patients of Alzheimer's disease (AD). The aim of our study was to evaluate the effect of protriptyline (PRT), a tricyclic antidepressant, in streptozotocin (STZ)- induced rat model of AD. Total 10 mu l of STZ was injected into each ventricle (1 mg/kg). PRT (10 mg/kg, i.p.) treatment was started 3-day post STZ administration and continued till 21 days. We found that STZ treatment significantly increased pTau, A beta 42 and BACE-1 expression, oxidative stress and neurodegeneration in hippocampus and cortex of adult rats. STZ induced impairment in spatial learning and retention memory was associated with increased WO and reduced CREB and BDNF expression in cortex and hippocampus. Interestingly, PRT treatment significantly reduced pTau, A beta 42 and BACE-1 levels, neurodegeneration, oxidative stress and glial activation, contributing to the improved spatial learning and retention memory in STZ treated rats. Moreover, PRT treatment significantly improved p-ERK/ERK ratio and enhanced BDNF and CREB levels by reducing NFXB and GFAP expression in STZ treated rats. Our data suggest that impaired NFXB and CREB signaling potentially contribute in AD pathogenesis by elevating oxidative stress and neuroinflammation mediated neurodegeneration. Our study has established protriptyline as a multi target molecule in pre-clinical model of AD and further investigations on PRT like molecules could pave way for further development of effective new treatments in neurodegenerative disorders.
Keywords: Alzheimer's disease; antidepressant; BDNF; Memory; Oxidative stress; Protriptyline

Pyridylpyrrolido ligand in Ge(II) and Sn(II) chemistry: synthesis, reactivity and catalytic application - Pahar, Sanjukta; Sharma, Vishal; Tothadi, Srinu; Sen, Sakya S. (Dalton Transactions, 2021)
In our previous communication, we have reported the synthesis of a new chlorogermylene (B) featuring a pyridylpyrrolido ligand. This study details the preparation of a series of new germylenes and stannylenes starting from B. A transmetallation reaction between B and SnCl2 led to the analogous chlorostannylene (1) with the simultaneous elimination of GeCl2. This is a very unusual example of transmetallation between two elements of the same group. The preparation of 1via lithiation led to the formation of 2 as a side product, where the ortho C-H bond of the pyridine ring was activated and functionalized with a Bu-n moiety. Subsequently, B and 1 were used as precursors to generate germylene (4) and stannylene (5) featuring tris(trimethylsilyl)silyl (hypersilyl) moieties. We also prepared tetrafluoropyridyl germylene (6) by reacting 4 with C5F5N with the simultaneous elimination of (Me3Si)(3)SiF by utilizing the fluoride affinity of the silicon atom. As there is scarcity of Sn(II) compounds as single-site catalysts, we investigated 5 as a catalyst towards the hydroboration of aldehydes, ketones, alkenes and alkynes. All the compounds have been characterized by single-crystal X-ray diffraction and by state of the art spectroscopic studies.

Palladium mediated selective cleavage of benzyl and allyl phosphates: a convenient non-hydrogenolytic method for the synthesis of phosphates and phospholipids. - Mart, Alson; Sarkar, Nitai N.; Shashidhar, Mysore S. (ChemistrySelect, 2022)
Palladium(II) hydroxide on carbon is a catalyst routinely used for the cleavage of O-benzyl groups by hydrogenolysis to obtain the corresponding parent organic compound. The work described in this article shows that allyl and benzyl phosphates, can be cleaved efficiently and selectively using palladium(II) hydroxide on carbon, under non-hydrogenolytic and neutral conditions, precluding the migration of acyl groups. The utility of these cleavage reactions for the synthesis of diacylglycerol and phosphatidic acid, containing unsaturation, is demonstrated. These methods have high potential for the synthesis of a variety of phosphates and natural phospholipids.
Keywords: Carbohydrate; Ether cleavage; Palladium; Phosphate; Phospholipid; Protecting group

Pectinase production by aspergillus niger and its applications in fruit juice clarification - Wagh, Vrushali; Patel, Hirvitaben; Patel, Nafisa; Vamkudoth, Koteswara Rao; Ajmera, Shanthipriya (Journal of Pure and Applied Microbiology, 2022)
Pectinases (EC 3.2.1.15) are a class of enzymes that catalyze the depolymerization or de-esterification reactions that degrade pectic substances. In the present study, we have isolated the Aspergillus niger strain from soil samples, in India and evaluated pectinase production. The highest pectinase producing A. niger strain was further evaluated and optimized with various agricultural wastes. Plackett-Burman design (PBD) and Central composite design ‘(CCD)’ were used to determine the best parameters for maximum pectinase production. Pectinase activity was increased to 99.21 U/ml after optimizing the production medium using PBD and CCD statistical analysis. A positive correlation of pectinase activity between predicted (112.65 U/ml) and experimental (99.21 U/ml with SD=0.005) optimum was observed. Maximum pectinase was produced by A. niger under submerged fermentation, utilizing orange peel, which is a cost-effective, adaptable, and environmentally friendly approach. The partially purified pectinase showed significant application for apple juice clarification and showed the ability to degrade pectin and therefore the colour change was observed in apple juice within 120 min. Maximum pectinase was produced by A. niger using agricultural waste orange peel under submerged fermentation which is an economical, versatile and eco-friendly process and pectinase showed a significant application for apple juice clarification.

Pendant propargyloxy-functionalized aromatic (co)polycarbonates: synthesis, thermal crosslinking and chemical modification - Nagane, Samadhan S.; Maher, Deepak M.; Verma, Savita; Talanikar, Aniket A.; Wadgaonkar, Prakash P. (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2022)
A bisphenol monomer bearing pendant propargyloxy group viz, 1, 1-bis (4-hydoxyphenyl)-1-(4 `-propargyloxyphenyl) ethane (BPP) was synthesized starting from commercially available 1, 1, 1-tris (4-hydroxyphenyl) ethane (THPE) by mono O-propargylation reaction using propargyl bromide. A new series of pendant propargyloxy-functionalized aromatic (co)polycarbonates was synthesized by low-temperature solution polycondensation of BPP or different molar ratios of BPP and bisphenol-A with triphosgene in dichloromethane in the presence of triethylamine. The formation of reasonably high molecular weight (co)polycarbonates was confirmed by inherent viscosity (0.52-0.83 dL/g) and gel permeation chromatography (M-n 37,000-69,800 g/mol, polystyrene standards) measurements. C-13 NMR spectral studies supported formation of random copolycarbonates in copolymerization of BPP and BPA with triphosgene. The 10% weight loss temperature (T-10) values of (co)polycarbonates, determined by thermogravimetric analysis under nitrogen atmosphere, were in the range 427-438 degrees C indicating their good thermal stability. The glass transition temperature (T-g) values of (co)polycarbonates were observed in the range 147-152 degrees C. The crosslinking ability of (co)polycarbonates involving pendant propargyloxy groups leading to formation of networked structure was evaluated via non-isothermal curing studies by DSC. As a proof-of-concept, the post-modification of a representative polycarbonate bearing pendant propargyloxy groups with 1-octane thiol as a model compound via thiol-yne click reaction was briefly studied.
Keywords: Aromatic polycarbonate; Chemical modification; propargyloxy groups; thermal crosslinking; thiol-yne click reaction

Perception of glycerol carbonate as green chemical: synthesis and applications - Gade, Swapna M.; Saptal, Vitthal B.; Bhanage, Bhalchandra M. (Catalysis Communications, 2022)
Glycerol carbonate (GC) is a prominent component in industrial practice and has a remarkable potential for the sophisticated applications. While GC has come into prominence due to the perceived overflow of glycerol (GLY) as a coproduct of biodiesel industry, its contemporary and future downstream applications are driving tremendous interest in recent years. This review comprises strategies for glycerol carbonate synthesis, properties and its applications. The conversion of GLY to GC via transesterification has appeared in consensus to be the most promising route. A detailed explanation of the effect of the catalysts and operating conditions on the GC yield to provide an updated understanding of the process are summarized. Future directions for GC production through catalytic transesterification are also discussed.
Keywords: Biodiesel; biofuels; catalysis; Glycerol; Glycerol carbonate; green chemistry; transesterification

Pharmaceutical standardization and physicochemical characterization of traditional ayurvedic mineral drug red ochre roasted in cow's ghee (Shuddha Gairik) - Chavan, S. B.; Gupta, V. S.; Deshmukh, V. V.; Sardeshmukh, S. P. (Indian Journal of Traditional Knowledge, 2022)
Rasashastra is a pharmaceutics branch of Ayurveda describing scientific methods to convert metals and minerals into bio-compatible formulations used individually or plant admixed to enhance their bioavailability and efficacy. In the present study, red ochre (Gairik) powder was processed in cow's ghee by textual method of roasting. The steps of preparation and changes in the properties therein were documented and validated in triplicate batches to develop a monograph. Ayurvedic and basic tests were performed to determine the properties of Shuddha Gairik. The physical characterization included Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), Fourier Transform Infra-red (FT-IR), Dynamic Light Scattering (DLS) and Thermo-gravimetric Analysis (TGA). Elemental composition was estimated by titration and gravimetric analysis while heavy metal limits were assessed using Inductively Coupled Plasma Optical Emission Spectrophotometry (ICPOES). This study depicted that crude red ochre, containing Kaolinite with high iron percentage, on roasting in cow's ghee led to the formation of fatty acids adsorbed red ochre particles. The developed monograph will be a guideline to the Ayurvedic industry for precise formulation of Shuddha Gairik. This will help researchers for better understanding the importance of Ayurvedic methods of pharmaceutical preparations and carry out their mechanistic studies in various diseases.
Keywords: Ferric oxide; Gairik; Kaolinite; Monograph; Red ochre; Roasting

Polymorphs of green fluorescence protein chromophore analogue: fluorescence switching with thermal stimuli - Mali, Bhupendra P.; Dash, Soumya Ranjan; Biswas, Anupam; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Crystal Growth & Design, 2022)
Polymorphs of fluorescent organic materials offer significant implications in optoelectronics and advanced materials as they modulate photoluminescence properties. A slight alteration in the conformation/packing of molecules in the crystals shows variation in photoluminescence. This necessitates the polymorph screening of these materials to develop novel crystalline forms with distinct fluorescence emissions for broader application. In continuation of our work on the polymorph screening of Green Fluorescence Protein Chromophore (GFPc), we have synthesized a new imidazoline derivative, ethyl (Z)-2-(2-methyl-5-oxo-4-(3,4,5-trimethoxybenzylidene)-4,5-dihydro-1H-imi dazol-1- yl)acetate (1). Polymorph screening of 1 under different crystallization conditions revealed three polymorphs, Form I (needle), Form II (block), and Form III (polycrystalline material). Forms I and II are the outcome of solution crystallization, whereas Form III was produced from the melt crystallization of Forms I and II. DSC, HSM, and powder and single-crystal XRD studies indicate the conversion of Form I and Form III crystals to Form II crystals on thermal stimuli. The photoluminescence studies revealed cyan, yellow, and yellowish-green fluorescence emission for Forms I, II, and III crystals, respectively. The difference in photoluminescence could be due to the variance in aggregation modes like H-aggregation in Form I and J-aggregation in Form II crystals. Form I, Form II, and Form III crystals also showed irreversible thermal fluorescent switching from cyan-yellow-green due to polymorphic phase transitions. The study correlates the direct observation of the modulation of the excited-state transition under thermal stimuli in the crystalline phase. It will help augment the pace in the research of thermally responsive fluorescent materials.

Poly(N-vinylcaprolactam) containing solid lipid polymer hybrid nanoparticles for controlled delivery of a hydrophilic drug gemcitabine hydrochloride - Surapaneni, Sai Geetika; Ambade, V. Ashootosh (RSC Advances, 2022)
Folic acid tagged and hydrophilic polymer containing solid lipid nanoparticles (SLNs) were formulated for the controlled and targeted delivery of gemcitabine, a hydrophilic drug. Drug loaded SLNs were prepared by double emulsion method and optimized by 3(2) level factorial design. Then, a hydrophilic polymer, namely, poly(N-vinylcaprolactam) (PVCL) was incorporated in the optimized SLN batch in the first aqueous phase (W1) to obtain solid lipid polymer hybrid nanoparticles (SLPHNs) that were further decorated with folic acid (F-SLPHNs). TEM analysis of SLNs and SLPHNs revealed the spherical shape with no aggregation while SLPHNs showed higher % EE. SLPHNs exhibited limited burst release of gemcitabine compared to SLNs as well as lower overall % release. All the formulations showed good cytocompatibility against MDA-MB-231 cell lines and folic acid-tagged hybrid particles (F-SLPHNs) showed remarkably higher cellular uptake.

Polyoxometalate clusters: inorganic ligands for functional materials - Dey, Chandan (Journal of Cluster Science, 2022)
Research in polyoxometalates (POMs) is a diverse growing field with variations in application. POMs are consisting of metal ion and oxide. Peripheral oxides of POM can share spare electron pairs to behave as ligands. This property of POM was utilized for constructing coordination polymers (CPs), synthesizing transitional metal substituted POM for catalysis, synthesizing and stabilizing nano-particles, etc. POM connected structures have provided an opportunity of heterogenization of some homogeneous POM catalyst. Furthermore, diamagnetic POM ligands have been suitable for stabilizing and isolating magnetic ions inside clusters. The scope of this review is to summarize the role of POMs as ligands to prepare POM based CPs, synthesize and stabilize metal nano-particles and isolate magnetic ion or unit.
Keywords: Coordination polymer; Inorganic ligand; materials science; polyoxometalates; synthesis design

Porous covalent organic nanotubes and their assembly in loops and toroids - Koner, Kalipada; Karak, Shayan; Kandambeth, Sharath; Karak, Suvendu; Thomas, Neethu; Leanza, Luigi; Perego, Claudio; Pesce, Luca; Capelli, Riccardo; Moun, Monika; Bhakar, Monika; Ajithkumar, Thalasseril G.; et al. (Nature Chemistry, 2022)
Carbon nanotubes, and synthetic organic nanotubes more generally, have in recent decades been widely explored for application in electronic devices, energy storage, catalysis and biosensors. Despite noteworthy progress made in the synthesis of nanotubular architectures with well-defined lengths and diameters, purely covalently bonded organic nanotubes have remained somewhat challenging to prepare. Here we report the synthesis of covalently bonded porous organic nanotubes (CONTs) by Schiff base reaction between a tetratopic amine-functionalized triptycene and a linear dialdehyde. The spatial orientation of the functional groups promotes the growth of the framework in one dimension, and the strong covalent bonds between carbon, nitrogen and oxygen impart the resulting CONTs with high thermal and chemical stability. Upon ultrasonication, the CONTs form intertwined structures that go on to coil and form toroidal superstructures. Computational studies give some insight into the effect of the solvent in this assembly process.

Possible fine-tuning of methane activation toward C2 oxygenates by 3d-transition metal-ions doped nano-ceria-zirconia - Kanungo, Subhashree S.; Mishra, Abhaya Kumar; Mhamane, Nitin B.; Marelli, Udaya Kiran; Kumar, Dharmesh; Gopinath, Chinnakonda S. (Inorganic Chemistry, 2022)
In this work, we demonstrate a simple sol-gel technique to prepare metal-ion(s)-doped ceria-zirconia solid solution for efficient catalytic methane activation. The cation -depicting formula units are Ce0.80Zr0.20 (CZ), Ce0.79Zr0.20M0.01 (CZM), and Ce0.79Zr0.20M0.005M10.005 (CZMM1) (M and M1 = V, Mn, Fe, Co, and Cu), employed for undoped, mono-metal-ion -doped, and bi-metal-ion-doped solid solutions, respectively. Methane activation with Mn, Fe, Cu mono-metal-ion-doped CZ favors the C1 product, while CZCo assists C-C coupling with the formation of acetaldehyde. On the other hand, the Co-and Fe -doped bi-metal-ion combination catalyst (CZCoFe) shows significant ethanol but predominant formic acid formation. This is further promoted by the Co + V bi-metal-ion combination (CZCoV) catalyst, and it shows ethanol as the major product along with methyl hydrogen peroxide, methanol, and formic acid as minor products. An impressive ethanol yield of 93 mu mol/g h with 76% selectivity obtained with the CZCoV catalyst is at par with that obtained with noble-metal-based catalysts under comparable reaction conditions. When Co and V content was increased two and four times from 0.005 to 0.01 and 0.02, ethanol yield increased at the expense of formic acid. The 213 mu mol/g h ethanol yield (86% selectivity) observed with Ce0.76Zr0.20Co0.02V0.02 is probably the highest observed. The partial oxidation of CH4 in Co-based bi-metal combinations (Co + V or Co + Fe) suggests the synergistic effect of doped metal ions owing to the heterogeneous near -neighbor environment. The present results are attributed to the surface heterogeneity between the host and the dopants, which selectively promotes methane activation as well as C-C coupling. This indicates a large scope to tune the activity of partial oxidation of methane and product selectivity with different metal-ion(s) combinations.

Postmodification of voxelotor (GBT 440) via [Rh]-catalyzed cross dehydrogenative coupling with olefins br - Kalshetti, Rupali G.; Rajput, Raveena; Motiwala, Zenia; Reddy, D. Srinivasa; Kulkarni, Kiran A.; V. Ramana, Chepuri (Bioorganic & Medicinal Chemistry Letters, 2022)
The directed Rh(III)-catalyzed cross dehydrogenative coupling of the pyrazole unit of the GBT-440 scaffold has been explored with simple as well as conjugated olefins to synthesize post-functionalized GBT-440 analogues. The screening of these synthesized compounds for improving the oxygen binding efficiency of the hemoglobin isolated from the sickled red blood cells revealed that some of these compounds are as good as GBT-440.
Keywords: CDC Coupling; GBT-440 (Voxelotor); Rh(III) catalysis; sickle cell anemia

Post-polymerization modifiable aromatic (co)poly(ether sulfone)s possessing pendant norbornenyl groups based upon a new bisphenol - Talanikar, Aniket A.; Nagane, Samadhan S.; Wadgaonkar, Prakash P.; Rashinkar, Gajanan S. (European Polymer Journal, 2022)
A new bisphenol possessing pendant norbornenyl group viz., 4, 4 `-(bicyclo (2.2.1) hept-5-en-2 yl methylene) bis (2-methoxyphenol) (BPA-NB) was synthesized by a single-step base-catalyzed condensation reaction of 5-norbor-nene-2-carboxaldehyde with guaiacol. NMR spectral data indicated formation of BPA-NB comprising of isomeric components. A series of (co)poly(ether sulfone)s possessing pendant norbornenyl groups was synthesized by nucleophilic aromatic substitution polycondensation of varying molar ratio of BPA-NB and bisphenol-A (BPA) with bis(4-fluorophenyl) sulfone. Inherent viscosity values and number average molecular weights of (co)poly (ether sulfone)s were in the range 0.67-1.01 dL/g and 75,400-1,16,300 g/mol, respectively indicating the formation of reasonably high molecular weight polymers. Tough, transparent, and flexible films could be cast from chloroform solutions of these (co)poly(ether sulfone)s. (Co)poly(ether sulfone)s were characterized using FT-IR, H-1 NMR and C-13 NMR spectroscopy, XRD, TGA and DSC analysis. The formation of random copoly(ether sulfone)s was demonstrated by( 13)C NMR analysis. The incorporation of BPA-NB into (co)poly(ether sulfone)s resulted into improvement in Tg values. BPA-NB-based (co)poly(ether sulfone)s offered possibilities for post -modifications involving either methoxyl or norbornenyl groups. A representative copoly(ether sulfone) (PSU-NB-2) possessing pendant norbornenyl groups was chemically modified via thiol-ene reaction with three representative thiol compounds, namely, 1-dodecanethiol, 2-furanmethanethiol and 2-mercaptoethanol to yield corresponding post-modified polymers in a quantitative manner. Additionally, it was demonstrated that copoly (ether sulfone) possessing pendant norbornenyl groups could be used to form insoluble cross-linked gel in the presence of a multifunctional thiol cross-linker.
Keywords: (Co)poly(ether sulfone)s; bisphenol; Cross -linking; Pendant norbornenyl groups; Thiol-ene reaction

Potassium phosphate catalyzed highly efficient synthesis of structurally diverse thioethers at ambient temperature - Mitragotri, Satish D.; Kulkarni, Makarand A.; Desai, V. Uday; Wadagaonkar, Prakash P. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2022)
Commercially available potassium phosphate has been demonstrated to be a highly efficient catalyst for the synthesis of thioethers employing two different routes viz. alkylation of thiols with alkyl/aralkyl halides and by Michael addition of thiols to conjugated alkenes.
Keywords: Alkyl halides; Potassium phosphate; thia-Michael reaction; thioethers; thiols

Potential- and time-dependent dynamic nature of an oxide-derived pdin nanocatalyst during electrochemical CO2 reduction - Bagchi, Debabrata; Sarkar, Shreya; Singh, Ashutosh Kumar; Vinod, Chathakudath P.; Peter, Sebastian C. (ACS Nano, 2022)
Electrochemical reduction of CO2 into valuable fuels and chemicals is a promising route of replacing fossil fuels by reducing CO2 emissions and minimizing its adverse effects on the climate. Tremendous efforts have been carried out for designing efficient catalyst materials to selectively produce the desired product in high yield from CO2 by the electrochemical process. In this work, a strategy is reported to enhance the electrochemical CO2 reduction reaction (ECO2RR) by constructing an interface between a metal-based alloy (PdIn) nanoparticle and an oxide (In2O3), which was synthesized by a facile solution method. The oxide-derived PdIn surface has shown excellent eCO(2)RR activity and enhanced CO selectivity with a Faradaic efficiency (FE) of 92.13% at -0.9 V (vs RHE). On the other hand, surface PdO formation due to charge transfer on the bare PdIn alloy reduces the CO2RR activity. With the support of in situ (EXAFS and IR) and ex situ (XPS, Raman) spectroscopic techniques, the optimum presence of the Pd-In-O interface has been identified as a crucial parameter for enhancing eCO(2)RR toward CO in a reducing atmosphere. The influence of eCO(2)RR duration is reported to affect the overall performance by switching the product selectivity from H-2 (from water reduction) to CO (from eCO(2)RR) on the oxide-derived alloy surface. This work also succeeded in the multifold enhancement of the current density by employing the gas diffusion electrode (GDE) and optimizing its process parameters in a flow cell configuration.
Keywords: CO2 reduction; Electrochemistry; heterostructure interface; in situ mechanism; nanocatalyst

Predicting the redox potentials of phenazine derivatives using DFT-assisted machine learning - Ghule, Siddharth; Dash, Soumya Ranjan; Bagchi, Sayan; Joshi, Kavita; Vanka, Kumar (ACS Omega, 2022)
This study investigates four machine-learning (ML) models to predict the redox potentials of phenazine derivatives in dimethoxyethane using density functional theory (DFT). A small data set of 151 phenazine derivatives having only one type of functional group per molecule (20 unique groups) was used for the training. Prediction accuracy was improved by a combined strategy of feature selection and hyperparameter optimization, using the external validation set. Models were evaluated on the external test set containing new functional groups and diverse molecular structures. High prediction accuracies of R2 > 0.74 were obtained on the external test set. Despite being trained on the molecules with a single type of functional group, models were able to predict the redox potentials of derivatives containing multiple and different types of functional groups with good accuracies (R2 > 0.7). This type of performance for predicting redox potential from such a small and simple data set of phenazine derivatives has never been reported before. Redox flow batteries (RFBs) are emerging as promising candidates for energy storage systems. However, new green and efficient materials are required for their widespread usage. We believe that the hybrid DFT-ML approach demonstrated in this report would help in accelerating the virtual screening of phenazine derivatives, thus saving computational and experimental costs. Using this approach, we have identified promising phenazine derivatives for green energy storage systems such as RFBs.

Preface to special issue on protein-mediated membrane remodeling - Chakraborty, Hirak; Sengupta, Durba (Journal of Membrane Biology, 2022)

Probes and techniques used in active and the hypoxia-based dormant state of an antitubercular drug screening assay - Yeware, Amar; Akhtar, Shamim; Sarkar, Dhiman (Medicine in Drug Discovery, 2022)
Current antitubercular drug therapy requires more than six months and is unable to kill latent or dormant forms of tuberculosis. Thus, it is a need of new drug therapy to fight against dormant tuberculosis. However, the major obstacle in the development of novel drugs for dormant tuberculosis is the lack of relevant screening systems and using reliable probes to measure growth inhibition. Until now, several probes used in active state assays are significantly determining the inhibitory effect against the active state of mycobacteria. The dormant condition assays are based on hypoxia-derived dormancy which include resazurin reduction assay, nitrite reductase assay, XTT reduction menadione assay and low oxygen recovery assay. Major probes used in those assays are colorimetric/fluorescent dyes, enzymatic activity, and reporter genes include luciferase and fluorescent proteins. Although these dormant assays are based on hypoxia-induced features and difficult to maintain for a longer duration. Also, they further complicated by growth detection and pursuit of high throughput screening criteria. Here we reviewed complications of probes and assay techniques used for anti-dormant drug screening programs of tuberculosis. This will provide the knowledge to design better alternative drug screening method for the anti-dormant form of tuberculosis.
Keywords: Active and dormant states; and; Drug screening assay; Probes; tuberculosis

Probing the site-specific reactivity and catalytic activity of Ag-n (n=15-20) silver clusters - Anis, Insha; Dar, Mohd Saleem; Bhat, Gulzar Ahmad; Rather, Ghulam Mohammad; Dar, Manzoor Ahmad (ACS Omega, 2022)
Density functional theory calculations within the framework of generalized gradient approximation (GGA), meta-GGA, and local functionals were carried out to investigate the reactivity and catalytic activity of Ag-n (n = 15-20) clusters. Our results reveal that all the Ag-n dusters in this size range, except Ag-20, adsorb O-2 preferably in the bridged mode with enhanced binding energy as compared to the atop mode. The O-2 binding energies range from 0.77 to 0.29 in the bridged mode and from 0.36 to 0.15 eV in the atop mode of O-2 adsorption. The strong binding in the case of the bridged mode of O-2 adsorption is also reflected in the increase in O-O bond distance. Natural bond orbital charge analysis and vibrational frequency calculations reveal that enhanced charge transfer occurs to the O-2 molecule and there is significant red shift in the stretching frequency of O-O bond in the case of the bridged mode of O-2 adsorption on the clusters, thereby confirming the above results. Moreover, the simulated CO oxidation reaction pathways show that the oxidation of the CO molecule is highly facile on Ag-16 and Ag-18 clusters involving small kinetic barriers and higher heats toward CO2 formation.

Process development for crystalline xylitol production from corncob biomass by Pichia caribbica - Dasgupta, Diptarka; Sidana, Arushdeep; Sarkar, Bipul; More, Snehal; Ghosh, Debashish; Bhaskar, Thallada; Ray, Anjan (Food and Bioproducts Processing, 2022)
Xylitol, a commodity chemical, is widely used in nutraceutical and pharmaceutical formulations. Microbial xylitol production is a promising alternative to mitigate current industrial practice issues and offers an environment-friendly sustainable conversion route. This study demonstrates a bioprocess for xylitol production from corncob using a mesophilic yeast Pichia caribbica. Corncob was hydrolyzed by dilute acid and steam explosion to recover fermentable xylose and used as the feed for xylitol production. Activated carbon treatment (3% w/v) completely removed the biomass-derived inhibitors furfural and hydroxymethyl furfural from the liquid hydrolysate. The fermenting yeast Pichia caribbica produced 124.1 +/- 0.45 g/L xylitol from the detoxified and concentrated corncob hydrolysate with a high yield of 0.80 +/- 0.02 g/g. The crystallized xylitol with 96.5% purity demonstrated no harmful effects on the cell line used as a control for the in-vitro toxicity studies. This proof of concept can be applied to help scale up for bio-refinery-based large-scale production of xylitol from corncob biomass.(c) 2022 Institution of Chemical Engineers. Published by Elsevier Ltd. All rights reserved.
Keywords: Biomass; Corncob; Detoxification; Fermentation; Toxicity analysis; xylitol

Process development for detoxification of corncob hydrolysate using activated charcoal for xylitol production - Ahuja, Vishal; Kshirsagar, Siddheshwar; Ghosh, Prasenjit; Sarkar, Bipul; Sutar, Ajit; More, Snehal; Dasgupta, Diptarka (Journal of Environmental Chemical Engineering, 2022)
The work describes process development for detoxification of corncob hydrolysate using activated carbon for microbial xylitol production. Activated carbon was used as an adsorbent to completely remove the major fermentation inhibitors obtained during dilute acid and steam explosion of biomass. A xylitol yield of 0.78 g/g was achieved from the detoxified hydrolysate in a 5 L fermenter by Pichia caribbica. The spent carbon was effectively regenerated and used for three consecutive cycles of operation. The successive regeneration and reuse of carbon could reduce the operational cost by similar to 38% and be used as a reference dataset for process scale-up and cost-effective xylitol production.
Keywords: Activated charcoal; Detoxification; Fermentation; Regeneration; xylitol

Process optimization for biodiesel production using agro-waste substrate - RaviKumar, Ameeta; Bed, Rashmi; Kumar, V. Ravi (Journal of the American Oil Chemists Society, 2022)

Profiling of metabolic alterations in mice infected with malaria parasites via high-resolution metabolomics - Chhibber-Goel, Jyoti; Shukla, Anurag; Shanmugam, Dhanasekaran; Sharma, Amit (Molecular and Biochemical Parasitology, 2022)
Background: Malaria infection can result in distinct clinical outcomes from asymptomatic to severe. The association between patho-physiological changes and molecular changes in the host, and their correlation with severity of malaria progression is not fully understood. Methods: In this study, we addressed mass spectrometry-based temporal profiling of serum metabolite levels from mice infected with Plasmodium berhgei (strain ANKA). Results: We show global perturbations and identify changes in specific metabolites in correlation with disease progression. While metabolome-wide changes were apparent in late-stage malaria, a subset of metabolites exhibited highly correlated changes with disease progression. These metabolites changed early on following infection and either continued or maintained the change as mice developed severe disease. Some of these have the potential to be sentinel metabolites for severe malaria. Moreover, glycolytic metabolites, purine nucleotide precursors, tryptophan and its bioactive derivatives were many fold decreased in late-stage disease. Interestingly, uric acid, a metabolic waste reported to be elevated in severe human malaria, increased with disease progression, and subsequently appears to be detoxified into allantoin. This detoxification mechanism is absent in humans as they lack the enzyme uricase. Conclusions: We have identified candidate marker metabolites that may be of relevance in the context of human malaria.
Keywords: Host response; Infectious diseases; malaria; metabolite; Plasmodium

Progress and potential of electrospinning-derived substrate-free and binder-free lithium-ion battery electrodes - Joshi, Bhavana; Samuel, Edmund; Kim, Yong-il; Yarin, Alexander L.; Swihart, Mark T.; Yoon, Sam S. (Chemical Engineering Journal, 2022)
Carbon nanofibers derived from electrospun precursors show great promise for electronic applications owing to their flexibility, conductivity, high surface area, and open structure. The integration of metal oxides and sulfides in carbon nanofibers, rather than using them with other binders, eliminates many problems caused by poor adhesion, nanomaterial agglomeration, excess mass contributed by inactive binders, and low conductivity of embedded active materials. The engineering of electrospun fibers with novel morphologies, such as core-shell, hollow, or porous structures, and the use of decorated carbon nanofibers (e.g., by electrodeposition or co precipitation) are discussed in this review. Representative schematic illustrations of the lithium-storage mechanism for these binder-free electrodes are presented. We describe how the electrospinning technique can offer a cost-effective strategy for fabrication of lightweight lithium-ion batteries with high capacity and excellent bendability. This review presents the fascinating morphologies of these specially designed carbon nanofiber electrodes, which enhance the electrochemical performance of metal oxides and sulfides, illustrating their enormous potential for use in wearable electronic devices and hybrid electric vehicles.
Keywords: Carbon nanofibers; Co-axial; composites; core-shell; electrospinning; Flexible

Proteomic profile of candida albicans biofilm - Abdulghani, Mazen; Iram, Rasiqua; Chidrawar, Priti; Bhosle, Kajal; Kazi, Rubina; Patil, Rajendra; Kharat, Kiran; Zore, Gajanan (Journal of Proteomics, 2022)
Candida albicans biofilms are characterized by structural and cellular heterogeneity that confers antifungal resistance and immune evasion. Despite this, biofilm formation remains poorly understood. In this study, we used proteomic analysis to understand biofilm formation in C. albicans related to morphophysiological and architectural features. LC-MS/MS analysis revealed that 64 proteins were significantly modulated, of which 31 were upregulated and 33 were downregulated. The results indicate that metabolism (25 proteins), gene expression (13 proteins), stress response (7 proteins), and cell wall (5 proteins) composition are modulated. The rate of oxidative phosphorylation (OxPhos) and biosynthesis of UDP-N-acetylglucosamine, vitamin B6, and thiamine increased, while the rate of methionine biosynthesis decreased. There was a significant modification of the cell wall architecture due to higher levels of Sun41, Pir1 and Csh1 and increased glycosylation of proteins. It was observed that C. albicans induces hyphal growth by upregulating the expression of genes involved in cAMP-PKA and MAPK pathways. This study is significant in that it suggests an increase in OxPhos and alteration of cell wall architecture that could be contributing to the recalcitrance of C. albicans cells growing in biofilms. Nevertheless, a deeper investigation is needed to explore it further.Significance: Candida sps is included in the list of pathogens with potential drug resistance threat due to the increased frequency especially colonization of medical devices, and tissues among the patients, in recent years. Significance of our study is that we are reporting traits like modulation in cell wall composition, amino acid and vitamin biosynthesis and importantly energy generation (OxPhos) etc. These traits could be conferring antifungal resistance, host immune evasion etc. and thus survival, in addition to facilitating biofilm formation. These findings are expected to prime the further studies on devising potent strategy against biofilm growth among the patients.
Keywords: Biofilm; Candida albicans; Cell wall; LC-MS; Metabolism; MS; proteomics

Protophilic solvent-impelled quasi-catalytic CO2 valorization to formic acid and N-formamides - Wu, Hongguo; Li, Hu; Zhao, Wenfeng; Sudarsanam, Putla; Yang, Song (Fuel, 2022)
As a low-price and luxuriant C1 sustainable resource, CO2 has the privilege of synthesizing hydrogen carriers and valuable chemicals. However, expensive metallic and organic catalysts are often indispensable for going on wheels of the relevant reaction processes. In this work, a protophilic solvent-impelled quasi-catalytic system was developed for efficient synthesis of formic acid and various N-formamides with high yields of 76-94% via reductive CO2 functionalization under mild reaction conditions (50 ?). Direct activation of the liquid hydrosilane toward the reduction of CO2 enabled by DMSO with optimum basicity/protophilicity is the predominant reaction route among the examined interaction models, while carbonic acid potentially derived from excessive CO2 and residual water inhibits the reaction, as explicitly disclosed by theoretical calculations and isotope labeling experiments. In addition, the in situ formed O-formyl species is conductive to the cascade CO2 reduction steps, which remarkably facilitated the overall quasi-catalytic upgrading process.
Keywords: CO2 utilization; Formic acid; Green energy; Nitrogenous chemicals; Quasi-catalysis

Pseudo-boehmite AlOOH supported NGr composite-based air electrode for mechanically rechargeable Zn-air battery applications - Kharabe, Geeta Pandurang; Manna, Narugopal; Nadeema, Ayasha; Singh, Santosh K.; Mehta, Shweta; Nair, Aathira; Joshi, Kavita; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2022)
Both mechanically and electrically rechargeable zinc-air batteries (ZABs) have received much interest due to their high energy density and suitability for mobile and stationary applications. However, their commercialization has been impeded by the lack of robust, low-cost and environmentally benign catalyst materials that can be easily scaled up. In this context, the present work introduces a new type of transition metal-free catalytic material (AlOOH/NGr) by anchoring the pseudo-boehmite phase of aluminium oxyhydroxide (AlOOH) nanosheets over nitrogen-doped graphene (NGr) via a single-step and straightforward hydrothermal process. Furthermore, density functional theory (DFT) based computation demonstrates that the nucleation of AlOOH starts from the N-sites and points towards the strong surface interaction between AlOOH and NGr via doped nitrogen. AlOOH/NGr consisting of thin layered pseudo-boehmite sheets uniformly distributed over NGr has displayed an oxygen reduction reaction onset potential of 0.83 V and a half-wave potential of 0.72 V, along with good catalytic durability in alkaline medium. With this, AlOOH/NGr, when used as an air electrode for fabricating a primary Zn-air battery, the system has exhibited an open circuit voltage of similar to 1.27 V with a flat discharge profile at a current rate of 10 mA cm(-2). The fabricated system delivered a specific capacity of similar to 720 mA h g(-1) and a high power density of 204 mW cm(-2) and is comparable to the counterpart system based on the state-of-the-art Pt/C (20 wt% Pt) cathode. Additionally, the homemade battery was able to maintain its performance after 4 times of mechanical recharging of the battery, which lasted for more than 35 h at a discharge current density of 10 mA cm(-2). Thus, we have uncovered the potential of an earth-abundant metal-based catalytic system for fabricating and demonstrating a robust mechanically rechargeable zinc-air battery.

Palladium-catalyzed chemoselective oxygenation of C(sp2)-H and C(sp3)-H bonds in isatins - Vijaykumar, Muniyappa; Pradhan, Chandini; Gonnade, Rajesh G.; Punji, Benudhar (Organic Letters, 2023)
The palladium-catalyzed chemoselective C(sp2)-H and C(sp3)-H bond oxygenation of substituted isatin derivatives is reported. This mild protocol exhibits the C5 C(sp2)-H oxygenation of isatins through electrophilic intermolecular C-H palladation in concentrated solutions using PhI(OAc)2 or Selectfluor as an oxidant, whereas it exhibits- N-CH3 C(sp3)-H oxygenation in dilute solutions via carbonyl-assisted intramolecular palladation in the presence of K2S2O8. This oxygenation reaction provides a direct and unified approach for synthesizing diverse oxygenated isatins with sensitive functionalities, including biorelevant compounds.

Palladium-catalyzed oxidative cyclization of ?-allenols in the presence of TBN: access to 3(2H)-furanones - Ghotekar, Ganesh S.; Shinde, Ravi A.; Saswade, Sagar S.; Muthukrishnan, M. (Journal of Organic Chemistry, 2023)
A new palladium-catalyzed oxidative cyclization of alpha-allenols is described. The readily accessible alpha-allenols participate in intra-molecular oxidative cyclization in the presence of TBN to grant access to multisubstituted 3(2H)-furanones, which are common motifs in several biologically important natural products and pharmaceuticals.
Keywords: Alternatively; conditions; cumbersome workup; intramolecular electrophilic; multiple reaction steps; noted examples

Palladium-catalyzed polar solvent empowered synthesis of hyper-branched ethylene oligomers and their applications - Birajdar, Rajkumar S.; Gonnade, Rajesh G.; Pol, Harshawardhan V.; Prabhu, M. Basava; Rokade, Dhammaraj; Nandimath, Sheetal; Chikkali, Samir H. (Polymer Chemistry, 2023)
In this contribution, we report the synthesis of two naphthoxy imine ligands, 2-(((2,6-dibenzhydryl-4-methoxyphenyl)imino)methyl)naphthalen-1-ol (L1) and 2-(((2,6-diisopropylphenyl)imino)methyl)naphthalen-1-ol (L2), with different steric and electronic features. L1 and L2 were treated with [(TMEDA)PdMe2] to obtain the corresponding neutral palladium(ii) complexes Cat.1 and Cat.2 in excellent yields. The identity of Cat.1 and Cat.2 was unambiguously ascertained using a combination of spectroscopic and analytical methods, including single-crystal X-ray diffraction. When exposed to 5 bar ethylene pressure, Cat.1 produced hyperbranched ethylene oligomers. The microstructure analysis of ethylene oligomers confirmed the existence of methyl, ethyl, propyl, and sec-butyl branches, with a molecular weight (M-n) of 500-1400 g mol(-1), a PDI of 1.46-2.10, and 67-106 branches per 1000 carbon atoms. The use of a polar solvent, tetrahydrofuran, led to a remarkable 3-fold increase in oligomerization activity without compromising the branching and molecular weight. The resultant hyperbranched ethylene oligomers were selectively monofunctionalized using industrially practiced hydroformylation, ozonolysis, and epoxidation, almost quantitatively. The hydroxy functionalized ethylene oligomer (F4) (5 wt%) was melt-compounded with LLDPE and Nylon-6 to produce a tough yet flexible blend with a higher strain-to-failure as compared to an uncompatibilized blend.

Palmitoylation of the glucagon-like peptide-1 receptor modulates cholesterol interactions at the receptor-lipid microenvironment - Naglekar, Amit; Chattopadhyay, Amitabha; Sengupta, Durba (Journal of Physical Chemistry B, 2023)
The G protein-coupled receptor (GPCR) superfamily of cell surface receptors has been shown to be functionally modulated by post-translational modifications. The glucagon-like peptide receptor-1 (GLP-1R), which is a drug target in diabetes and obesity, undergoes agonist-dependent palmitoyl tail conjugation. The palmitoylation in the C-terminal domain of GLP-1R has been suggested to modulate the receptor-lipid microenvironment. In this work, we have performed coarse-grain molecular dynamics simulations of palmitoylated and nonpalmitoylated GLP-1R to analyze the differential receptor-lipid interactions. Interestingly, the placement and dynamics of the C-terminal domain of GLP-1R are found to be directly dependent on the palmitoyl tail. We observe that both cholesterol and phospholipids interact with the receptor but display differential interactions in the presence and absence of the palmitoyl tail. We characterize important cholesterol-binding sites and validate sites that have been previously reported in experimentally resolved structures of the receptor. We show that the receptor acts like a conduit for cholesterol flip-flop by stabilizing cholesterol in the membrane core. Taken together, our work represents an important step in understanding the molecular effects of lipid modifications in GPCRs.

Parallel evolution of cannabinoid biosynthesis - Berman, Paula; de Haro, Luis Alejandro; Jozwiak, Adam; Panda, Sayantan; Pinkas, Zoe; Dong, Younghui; Cveticanin, Jelena; Barbole, Ranjit; Livne, Rotem; Scherf, Tali; Shimoni, Eyal; Levin-Zaidman, Smadar; et al. (Nature Plants, 2023)
This study reveals a cannabinoid biosynthetic pathway in Helichrysum umbraculigerum, a plant genetically distant from Cannabis, providing a potential source of new cannabinoids and metabolic engineering tools. Modulation of the endocannabinoid system is projected to have therapeutic potential in almost all human diseases. Accordingly, the high demand for novel cannabinoids stimulates the discovery of untapped sources and efficient manufacturing technologies. Here we explored Helichrysum umbraculigerum, an Asteraceae species unrelated to Cannabis sativa that produces Cannabis-type cannabinoids (for example, 4.3% cannabigerolic acid). In contrast to Cannabis, cannabinoids in H. umbraculigerum accumulate in leaves' glandular trichomes rather than in flowers. The integration of de novo whole-genome sequencing data with unambiguous chemical structure annotation, enzymatic assays and pathway reconstitution in Nicotiana benthamiana and in Saccharomyces cerevisiae has uncovered the molecular and chemical features of this plant. Apart from core biosynthetic enzymes, we reveal tailoring ones producing previously unknown cannabinoid metabolites. Orthology analyses demonstrate that cannabinoid synthesis evolved in parallel in H. umbraculigerum and Cannabis. Our discovery provides a currently unexploited source of cannabinoids and tools for engineering in heterologous hosts.

Pd loaded bismuth ferrite: a versatile perovskite for dual applications as acetone gas sensor and photocatalytic dye degradation of malachite green - Ghadage, Pandurang; Kodam, Pavan; Nadargi, Digambar; Patil, Suraj; Tamboli, Mohaseen; Bhandari, Nagesh; Mulla, Imtiaz; Park, Chinho; Suryavanshi, Sharad (Ceramics International, 2023)
Herein we report the palladium loaded bismuth ferrite for its bidirectional application as acetone gas sensor and photocatalytic dye degradation of malachite green. The motivation for loading Pd on bismuth ferrite (BFO) is due to its fascinating catalytic redox reactions causing faster adsorption and desorption of the oxygen molecules over the metal oxide. The planned perovskites were developed via surfactant assisted sol-gel auto-combustion route, and characterized their physico-chemical properties using XRD, SEM, TEM, HRTEM, EDAX, XPS and BET. The developed BFO showed the best selectivity towards acetone, whose response was 69% at 300 degrees C operating temperature for 500 ppm gas concentration. By tuning the surface area and catalytic behavior using CTAB and Pd loading, respectively, the enhancement in the gas response properties of BFO was achieved to 95% with the response and recovery time of 75 s and 104 s. The 1 wt% Pd loaded BFO showed the highest response (95%) in comparison to rest of the Pd loadings (0.5, 1.5 and 2.0 wt%). Moreover, the sunlight driven photocatalytic dye degradation of malachite green is carried out at 1 h exposure time. Here as well, 1 wt% Pd loaded BFO exhibited the maximum dye degradation efficiency of 51%. The results of this study demonstrate the developed perovskites have a significant potential for the use in dual applications such as acetone gas sensor and MG photocatalysis.
Keywords: Acetone sensor; Bismuth ferrite; Palladium loading; Photo dye -degradation

Pd nanoparticles supported on N-incorporated hybrid organosilica as an active and selective low-temperature phenol hydrogenation catalyst - Betsy, K. J.; Bajpai, Priyam; Lazar, Anish; Vanka, Kumar; Vinod, C. P. (ACS Applied Nano Materials, 2023)
A heterogeneous Pd-NPMO hybrid-silicacatalyst is synthesized andits application for aqueous phase selective hydrogenation of phenolto cyclohexanone at near ambient temperature (40 degrees C) and underatmospheric hydrogen pressure is demonstrated. The homogeneously distributedPd nanoparticles on N-bridged hybrid mesoporous organosilica showedremarkable activity and selectivity for cyclohexanone compared tothe unmodified Pd-SBA-15 catalyst. Control experiments strongly claimthe role of nitrogen domains in the organic framework of hybrid silicasupport in stabilizing small Pd nanoparticles and possibly modifyingthe Pd sites responsible for catalysis to activate the substrate moleculesin water. The hybrid silica catalyst was stable and reused severaltimes without any significant drop-in activity, proving the heterogeneityof the bifunctional Pd catalyst. Based on the density functional theorystudy and experimental interventions, a possible reaction mechanismfor the low-temperature phenol hydrogenation explaining the role oforganic domains in the hybrid-silica framework is proposed.
Keywords: cyclohexanone; Hybrid silica; palladium nanoparticles; Periodic mesoporous organosilica; phenol hydrogenation

Pd(II)-catalyzed tandem cycloannulative-alkenylation of o-alkynyl-phenols/anilines with (E)-β-Iodovinyl sulfones: a direct strategy to construct 3-(Vinyl sulfonyl)benzoheterole derivatives - Reddy, Raju Jannapu; Sharadha, Nunavath; Krishna, Gamidi Rama (Journal of Organic Chemistry, 2023)
Benzoheterolesand vinyl sulfones are the most promisingpharmaceuticalrelevance motifs, yet the hybrid analogues of these scaffolds stillneed to be explored. We report herein a general and highly efficientPd(OAc)(2)-catalyzed intramolecular cyclization and vinylationof o-alkynylphenols/o-alkynylanilineswith (E)-beta-iodovinyl sulfones under mild reactionconditions. A direct C(sp(2))-C(sp(2)) cross-couplingis enabled for the diversity-oriented synthesis of vinyl sulfone-tetheredbenzofurans and indoles in good to high yields with excellent stereoselectivity.Notably, this tandem process was consistent at the gram scale, andin situ, generation of 2-(phenylethynyl)phenol has also been utilizedin a scalable synthesis. Late-stage synthetic transformations werealso further explored, including isomerization and desulfonylative-sulfenylation.Moreover, several control experiments were accomplished, and we proposeda plausible mechanism based on existing experimental results.

Permeable polymersomes from temperature and pH dual stimuli-responsive PVCL-b-PLL block copolymers for enhanced cell internalization and lysosome targeting - Surapaneni, Sai Geetika; Choudhari, Shakeb N.; Avhad, Shankarrao V.; Ambade, Ashootosh V. (Biomaterials Advances, 2023)
A series of dual stimuli-responsive block copolymers comprising temperature-responsive poly(N-vinyl-caprolactam) (PVCL) and biodegradable pH-responsive poly(L-lysine) (PLL) of varying chain length were syn-thesized by a combination of free radical polymerization and ring opening polymerization. The block copolymers formed micelles and vesicles (polymersomes) in response to temperature and pH, respectively, in aqueous so-lution. The nanoassemblies were characterized by transmission electron microscopy and dynamic light scattering techniques. Encapsulation of both hydrophobic and hydrophilic dyes in the polymersomes was shown. Doxo-rubicin (DOX) was loaded in the polymersomes and its controlled release in response to the two stimuli, inde-pendently and jointly, was studied. The drug was found to be released due to stimuli-induced increased permeability without disassembly of the polymersomes. A significant increase in the cellular uptake of the drug-loaded polymersomes at hyperthermia conditions was demonstrated at 41 degrees C and release of the drug upon localization in lysosomes was observed. Cellular internalization pathway of the polymersomes was investigated by competitive inhibition assay and a combination of endocytic pathways dominated by caveolae-mediated mechanism was found to be operative.
Keywords: block copolymers; Controlled release; drug delivery; endocytosis; Polymersomes; Stimuli-responsive

Phased short-interfering RNA siRD29(-) regulates GIBBERELLIN 3-OXIDASE 3 during stolon-to-tuber transitions in potato - Malankar, Nilam; Kondhare, Kirtikumar; Saha, Kishan; Mantri, Mohit; Banerjee, Anjan (Plant Physiology, 2023)
Phased short-interfering RNAs (phasiRNAs) fine tune various stages of growth, development, and stress responses in plants. Potato (Solanum tuberosum) tuberization is a complex process, wherein a belowground modified stem (stolon) passes through developmental stages like swollen stolon and minituber before it matures to a potato. Previously, we identified several phasiRNA-producing loci (PHAS) from stolon-to-tuber transition stages. However, whether phasiRNAs mediate tuber development remains unknown. Here, we show that a gene encoding NB-ARC DOMAIN-CONTAINING DISEASE RESISTANCE PROTEIN (StRGA4; a PHAS locus) is targeted by Stu-microRNA482c to generate phasiRNAs. Interestingly, we observed that one of the phasiRNAs, referred as short-interfering RNA D29(-), i.e. siRD29(-), targets the gibberellin (GA) biosynthesis gene GIBBERELLIN 3-OXIDASE 3 (StGA3ox3). Since regulation of bioactive GA levels in stolons controls tuber development, we hypothesized that a gene regulatory module, Stu-miR482c-StRGA4-siRD29(-)-StGA3ox3, could govern tuber development. Through transient expression assays and small RNA sequencing, generation of siRD29(-) and its phase was confirmed in planta. Notably, the expression of StGA3ox3 was higher in swollen stolon compared to stolon, whereas siRD29(-) showed a negative association with StGA3ox3 expression. Antisense (AS) lines of StGA3ox3 produced more tubers compared to wild type. As expected, StRGA4 overexpression (OE) lines had high levels of siRD29(-) and mimicked the phenotypes of StGA3ox3-AS lines, indicating the functionality of this module in potato. In vitro tuberization assays (with or without a GA inhibitor) using StGA3ox3 antisense lines and overexpression lines of StGA3ox3 or StRGA4 revealed that StGA3ox3 controls the tuber stalk development. Taken together, our findings suggest that a phasiRNA, siRD29(-), mediates the regulation of StGA3ox3 during stolon-to-tuber transitions in potato. A phasiRNA module, Stu-miR482c-StRGA4-siRD29(-), regulates the expression of a gibberellin biosynthesis gene StGA3ox3 during stolon-to-tuber transitions in potato.

Phenol hydrogenation to cyclohexanol catalysed by palladium supported on CuO/CeO2 - Kasabe, Mirabai M.; Kotkar, Vaibhav R.; Dongare, Mohan K.; Umbarkar, Shubhangi B. (Chemistry-an asian jounrnal, 2023)
Hydrogenation of phenol to cyclohexanone/cyclohexanol is an important reaction in production of nylon-6, nylon-66 and in petroleum industry. Liquid phase phenol hydrogenation over Pd-CuO/CeO2 was carried out under mild conditions. Palladium impregnated over CuO/CeO2 synthesized by co-precipitation method showed excellent catalytic activity for phenol hydrogenation (99% conversion with 80% cyclohexanol yield) at 90 degrees C and 10 bar H-2 pressure in water. Commercial 10%Pd/C showed only 8% phenol conversion under identical conditions. The detailed characterization revealed significant improvement in surface area of ceria after addition of CuO and decrease in crystallite size with creation of defects in CeO2 lattice. XPS analysis showed Pd loading on CuO/CeO2 to cause hydrogen spillover on the surface leading to increase in the oxygen vacancies. The interaction of phenol with catalyst surface studied by detailed FTIR analysis, revealed activation of phenol on oxygen vacancy of ceria as phenoxide ion with perpendicular orientation of aromatic ring on catalyst surface.
Keywords: Cyclohexanol; Hydrogen spillover; oxygen vacancies; Pd-CuO/CeO2; phenol hydrogenation

Photocatalytic C-N bond construction toward high-value nitrogenous chemicals - Li, Jie; Liu, Tengyu; Singh, Nittan; Huang, Zhuochun; Ding, Yan; Huang, Jinshu; Sudarsanam, Putla; Li, Hu (Chemical Communications, 2023)
The construction of carbon-nitrogen bonds is vital for producing versatile nitrogenous compounds for the chemical and pharmaceutical industries. Among developed synthetic approaches to nitrogenous chemicals, photocatalysis is particularly prominent and has become one of the emerging fields due to its unique advantages of eco-sustainable characteristics, efficient process integration, no need for high-pressure H2, and tunable synthesis methods for developing advanced photocatalytic materials. Here, the review focuses on potential photocatalytic protocols developed for the construction of robust carbon-nitrogen bonds in discrepant activation environments to produce high-value nitrogenous chemicals. The photocatalytic C-N bond construction strategies and involved reaction mechanisms are elucidated. This review focuses on potential photocatalytic protocols developed for the construction of robust carbon-nitrogen bonds in discrepant activation environments to produce high-value nitrogenous chemicals.

Photocatalytic setup for in situ and operando ambient-pressure X-ray photoelectron spectroscopy at MAX IV Laboratory - Klyushin, Alexander; Ghosalya, Manoj; Kokkonen, Esko; Eads, Calley; Jones, Rosemary; Nalajala, Naresh; Gopinath, Chinnakonda S.; Urpelainen, Samuli (Journal of Synchrotron Radiation, 2023)
The Ambient-Pressure X-ray Photoelectron Spectroscopy (APXPS) endstation at the SPECIES beamline at MAX IV Laboratory has been improved. The latest upgrades help in performing photo-assisted experiments under operando conditions in the mbar pressure range using gas and vapour mixtures whilst also reducing beam damage to the sample caused by X-ray irradiation. This article reports on endstation upgrades for APXPS and examples of scientific cases of in situ photocatalysis, photoreduction and photo-assisted atomic layer deposition (photo-ALD).
Keywords: APXPS; photo-ALD; Photocatalysis; solar simulator

Photogating induced high sensitivity and speed from heterostructure of few-layer MoS2 and reduced graphene oxide-based photodetector - Das, Chayan; Kumar, Ashok; Kumar, Suresh; Dambhare, Neha V.; Kumar, Mahesh; Rath, Arup K.; Sahu, Satyajit (Physical Chemistry Chemical Physics, 2023)
Over the past few years, two-dimensional transition metal dichalcogenides (2D-TMDC) have attracted huge attention due to their high mobility, high absorbance, and high performance in generating excitons (electron and hole pairs). Especially, 2D molybdenum disulfide (MoS2) has been extensively used in optoelectronic and photovoltaic applications. Due to the low photo-to-dark current ratio (I-photo/dark) and low speed, pristine MoS2-based devices are unsuitable for these applications. So, they need some improvements, i.e., by adding layers or decorating with materials of complementary majority charges. In this work, we decorated pristine MoS2 with reduced graphene oxide (rGO) and got improved dark current, I-photo/dark, and response time. When we compared the performance of pristine MoS2 based device and rGO decorated MoS2 based device, the rGO/MoS2-based device showed an improved performance of responsivity of 3.36 A W-1, along with an I-photo/dark of about 154. The heterojunction device exhibited a detectivity of 4.75 x 10(12) Jones, along with a very low response time of 0.184 ms. The stability is also outstanding having the same device performance even after six months.

Photoinduced CO2 and N2 reductions on plasmonically enabled gallium oxide - Ojha, Niwesh; Thakkar, Kavita; Bajpai, Abhinav; Joshi, Kavita; Kumar, Sushant (Journal of Colloid and Interface Science, 2023)
Ag-containing ZnO/ b-Ga2O3 semiconductor, which exhibit reduced bandgap, increased light absorption, and hydrophilicity, have been found to be useful for photocatalytic CO2 reduction and N2 fixation by water. The charge-separation is facilitated by the new interfaces and inherent vacancies. The Ag@GaZn demonstrated the highest photocurrent response, about 20-and 2.27-folds that of the Ga and GaZn sam-ples, respectively. CO, CH4, and H2 formed as products for photo-reduction of CO2. Ag@GaZn catalyst exhibited the highest AQY of 0.121 % at 400 nm (31.2 W/m2). Also, Ag@GaZn generated 740 lmolg-1 of NH4+ ions, which was about 18-folds higher than Ga sample. In situ DRIFTS for isotopic-labelled 13CO2 and 15N2 reaffirmed the photo-activity of as-synthesized catalysts. Density functional theory pro-vided insight into the relative affinity of different planes of heterostructures towards H2O, CO2 and N2 molecules. The structure-photoactivity rationale behind the intriguing Ag@GaZn sample offers a funda-mental insight into the role of plasmonic Ag and design principle of heterostructure with improved pho-toactivity and stability.(c) 2022 Elsevier Inc. All rights reserved.
Keywords: CO2 reduction; DRIFTS density functional theory; hydrophilicity; Photocurrent response

Photoplethysmograph based arrhythmia detection using morphological features - Neha; Sardana, H. K.; Kanawade, R.; Dogra, N. (Biomedical Signal Processing and Control, 2023)
Photoplethysmography (PPG) is a non-invasive optical technique that is used for the detection of cardiovascular diseases. The paroxysmal nature of arrhythmic events and the lack of timely recorded data emphasize the need to develop an automated method for the identification of arrhythmias. The literature shows the detection of a single type of arrhythmia using PPG. However, limited research has been carried out for the detection of multiple types of arrhythmia. In this research work, a new set of morphological features have been proposed for the automated detection of multiple arrhythmias using rule-based and statistical learning-based approaches. The proposed work has been implemented on the retrospective dataset and validated on the prospective dataset. The results show that the rule-based arrhythmia detection method is equipollent to the statistical learning approach with an accuracy of 98.43%/94.16% on the retrospective dataset and 94.16%/93% on the prospective dataset.
Keywords: Arrhythmia; Machine learning algorithms; Photoplethysmography; Signal processing

Photo-stable, 1D-nanofilaments TiO2-based lepidocrocite for photocatalytic hydrogen production in water-methanol mixtures - Badr, Hussein O.; Natu, Varun; Neatu, Stefan; Neatu, Florentina; Kuncser, Andrei; Rostas, Arpad M.; Racey, Matthew; Barsoum, Michel W.; Florea, Mihaela (Matter, 2023)
Water and sunlight are the cleanest, most renewable, and abundant resources on Earth. Developing inexpensive, scalable photocatalysts that are highly stable for hydrogen (H-2) production has long been a cherished dream of humanity. Herein, we report on one-dimensional lepidocrocite-based sub-nanofilaments (NFs), approximate to 5 x 7 & Aring;(2) in cross-section, that generate H-2 from 80:20 v/v water/methanol mixtures when illuminated by simulated sunlight. The NFs were stable in the mixtures for times >4,300 h, 300 h of which were under irradiation. Apparent quantum yields as high as 11.7% were obtained. Based on deuterated water results, we conclude that water is the H-2 source. Further, no carbon dioxide (CO2) due to photocatalytic degradation of methanol was detected. Therefore, the NFs have strong green credentials and lucrative economic prospects for large scale up. We expect these NFs will lead to new lines for developing cheap and ultra-stable materials to produce H-2 photochemically for a long time.

Physiologically-based pharmacokinetic model for tuberculosis drug disposition at extrapulmonary sites - Ramachandran, Aparna; Gadgil, Chetan J. (CPT-Pharmacometrics & Systems Pharmacology, 2023)
Tuberculosis (TB) is a leading cause of mortality attributed to an infectious agent. TB primarily targets the lungs, but in about 16% cases can affect other organs as well, giving rise to extrapulmonary TB (EPTB). However, an optimal regimen for EPTB treatment is not defined. Although the recommended treatment for most forms of EPTB is the same as pulmonary TB, the pharmacokinetics of EPTB therapy are not as well studied. To address this gap, we formulate a whole-body physiologically-based pharmacokinetic (PBPK) model for EPTB that for the first time includes the ability to simulate drug concentrations in the pleura and lymph node, the most commonly affected sites of EPTB. Using this model, we estimate the time-dependent concentrations, at potential EPTB infection sites, of the following four first-line anti-TB drugs: rifampicin, ethambutol, isoniazid, and pyrazinamide. We use reported plasma concentration kinetics data to estimate model parameters for each drug and validate our model using reported concentration data not used for model formulation or parameter estimation. Model predictions match the validation data, and reported pharmacokinetic parameters (maximum plasma concentration, time to reach maximum concentration) for the drugs. The model also predicts ethambutol, isoniazid, and pyrazinamide concentrations in the pleura that match reported experimental values from an independent study. For each drug, the predicted drug concentrations at EPTB sites are compared with their critical concentration. Simulations suggest that although rifampicin and isoniazid concentrations are greater than critical concentration values at most EPTB sites, the concentrations of ethambutol and pyrazinamide are lower than their critical concentrations at most EPTB sites.

PIDA-mediated N-N bond formation to access pyrazolidine-3,5-diones: a novel process for uricosuric agents G-25671 and sulfinpyrazone - Halder, Priyanka; Mhaske, Santosh B. (Chemical Communications, 2023)
Traditionally, toxic and expensive hydrazine building blocks are required to construct pharmaceutically important pyrazolidine-3,5-diones. Herein, we have described a novel method for their synthesis based on metal-free oxidative dehydrogenative N-N bond formation by PIDA-mediated reaction of easily accessible dianilide precursors. The developed mild reaction protocol features a good functional group tolerance and scalability. The application of this method is demonstrated by offering a unique route for the synthesis of uricosuric agents G-25671 and sulfinpyrazone from inexpensive starting material aniline via smooth functionalization of the well-designed diversity-oriented cyclopropyl key intermediate.

Polyethylene-grafted sheet-like silsesquioxane nanocomposites with unprecedented adhesion to polar substrates - Sharma, Vivek; Paulbudhe, Uday; Bachhar, Nirmalya; Chikkali, Samir H.; Kumaraswamy, Guruswamy (ACS Applied Polymer Materials, 2023)
Polyethylene is a highly apolar polymer with very pooradhesionto most substrates, necessitating the use of tie layers. Therefore,the synthesis of functional polyethylene is a long-standing challengein catalytic ethylene polymerization. Here, we report the preparationof a nanocomposite comprising polyethylene covalently grafted ontosheet-like silsesquioxanes, with unprecedented adhesion to metal andglass. A norbornene-grafted, layered Mg-silsesquioxane is treatedwith Grubbs second-generation catalyst (G-II), and the identity ofcovalently tethered G-II is unambiguously ascertained. Covalentlytethered G-II catalyzes the ring opening metathesis polymerizationof cyclooctene to poly(cyclooctene). The resulting poly(cyclooctene)is catalytically hydrogenated to yield polyethylene. This polyethylenenanocomposite exhibited a bonding strength of the order of 100 MPaon stainless steel and aluminum, 10-fold higher than reported forengineered polyethylene copolymers. The nanocomposite exhibits anincrease in the polar component of surface energy, yet remains compatibleand cocrystallizes with a polyethylene matrix.
Keywords: adhesion; clay; Nanocomposite; Polyethylene; silsesquioxane

Poly-gamma-glutamic acid biopolymer: a sleeping giant with diverse applications and unique opportunities for commercialization - Nair, Pranav; Navale, Govinda R.; Dharne, Mahesh S. (Biomass Conversion and Biorefinery, 2023)
Poly-gamma-glutamic acid (gamma-PGA) is a biodegradable, non-toxic, ecofriendly, and non-immunogenic biopolymer. Its phenomenal properties have gained immense attention in the field of regenerative medicine, the food industry, wastewater treatment, and even in 3D printing bio-ink. The gamma-PGA has the potential to replace synthetic non-degradable counterparts, but the main obstacle is the high production cost and lower productivity. Extensive research has been carried out to reduce the production cost by using different waste; however, it is unable to match the commercialization needs. This review focuses on the biosynthetic mechanism of gamma-PGA, its production using the synthetic medium as well as different wastes by L-glutamic acid-dependent and independent microbial strains. Furthermore, various metabolic engineering strategies and the recovery processes for gamma-PGA and their possible applications are discussed. Finally, highlights on the challenges and unique approaches to reduce the production cost and to increase the productivity for commercialization of gamma-PGA are also summarized.
Keywords: Commercialization; Multi-nutritious; Poly-gamma-glutamic acid; Waste valorization

Polymerizable solvent-free organic liquids: a new approach for large area flexible and foldable luminescent films - Wakchaure, Vivek Chandrakant; Veer, Sairam Dnyaneshwar; Nidhankar, Aakash D.; Kumar, Viksit; Narayanan, Aswini; Babu, Sukumaran Santhosh (Angewandte chemie-international editon, 2023)
The high demand for light-emitting and display devices made luminescent organic materials as attractive candidates. Solvent-free organic liquids are one of the promising emitters among them due to the salient features. However, the inherent limitations of forming sticky and noncurable surfaces must be addressed to become an alternate emitter for large-area device applications. Herein, we functionalized solvent-free organic liquids having monomeric emission in bulk with polymerizable groups to improve the processability. The polymerizable group on carbazole, naphthalene monoimide, and diketopyrrolopyrrole-based solvent-free liquid emitters enabled on-surface polymerization. These emitters alone and in combinations can be directly coated on a glass substrate without the help of solvents. Subsequent photo or thermal polymerization leads to stable, non-sticky, flexible, foldable, and free-standing large-area films with reasonably high quantum yield. Our demonstration of the tunable and white light-emitting films using polymerizable solvent-free liquids might be a potential candidate in flexible/foldable/stretchable electronics. The new concept of polymerizable liquid can be extended to other functional features suitable for futuristic applications.
Keywords: Energy Transfer; polymerization; Solvent-Free Organic Liquids; Thin-Film; White Light

Polymerized stimuli-responsive microgels for the removal of organic dye from water - Pany, Biswajit; Majundar, Amrito Ghosh; Mohanty, Madhuchhanda; Fyis, K. P.; Dey, Tanima; Tripathy, Gautam; Bhat, Suresh; Yamanaka, Junpei; Mohanty, Priti S. (Journal of Molecular Liquids, 2023)
Polymerized hydrogel materials (PGM) containing uniform-sized stimuli-responsive microgel particles could be promising alternatives for solution-based microgels to remove organic dyes from water. In the current work, PGM is prepared using Poly(N-isopropylacrylamide-co-acrylic acid) based anionic microgels and their ability for uptake and release studies with an oppositely charged dye, methylene blue (MB) is carried out using UV-vis spectroscopy. The mechanism of dye adsorption is understood at a single particle level using light scattering, and zeta potential and the contributions from different molecular interactions among dye molecules and constituting entities of microgels are obtained from molecular docking studies. The maximum dye uptake by PGM is around 80 % in the swollen state (at pH 7 and 20 degrees C). In contrast, the dye release studies in the deswollen state (at pH 3 and 50 degrees C) show a decrease in the release efficiency from 87 % to 63 % of the total dye adsorbed in 4-repeated cycles. The adsorption isotherm follows a sigmoidal (S) model that has been majorly used in different multi-layer adsorption systems. Extensive dynamic and static light scattering studies demonstrate a deswelling of hydrody-namic radius and core-shell radius of microgels at low temperatures (20 degrees C) induced by dye adsorption. At higher temperatures, the dye-adsorbed microgels have a higher hydrodynamic radius than the pure microgels due to the remaining dye molecules within the microgel that do not release even in the deswollen state. Molecular docking studies show that electrostatic interaction dominates between COO- and MB and van der Waals/hydrophobic dominates for MB-NIPAM and MB-COOH docking complex respectively. Our work covering adsorption/desorption properties of the material to the single-particle level can provide a better understanding in formulating reusable smart materials for the remediation of different water pollutants.(c) 2023 Elsevier B.V. All rights reserved.
Keywords: dynamic light scattering; Molecular docking; PNIPAM microgels; Removal of organic pollutants; Stimuli -responsive microgels

Polymorph II of hydroxyurea 150 years after its first synthesis - Rai, Sunil K.; Tothadi, Srinu; Arhangelskis, Mihails; George, Christy P.; Gonnade, Rajesh G.; Nangia, Ashwini K. (Crystengcomm, 2023)
A new polymorph of hydroxyurea (HU) was crystallized 150 years after its first synthesis. Due to its medicinal use in neoplastic diseases and sickle cell anemia, a high throughput screen of HU binary cocrystals was attempted. Instead of a cocrystal, an isoenergetic form II crystallized concomitantly with urea in methanol.

Possible handle for broadening the catalysis regime towards low temperatures: proof of concept and mechanistic studies with CO oxidation on surface modified Pd-TiO2 - Mhamane, Nitin B. B.; Panchal, Suresh; Kolekar, Sadhu K. K.; Ranjan, Ravi; Salgaonkar, Kranti N. N.; Burange, Anand S. S.; Nalajala, Naresh; Datar, Suwarna; Gopinath, Chinnakonda S. S. (Physical Chemistry Chemical Physics, 2023)
The present work demonstrates the effect of temperature-dependent surface modification (SM) treatment and its influence in broadening the catalysis regime with Pd-TiO2 catalysts prepared by various methods. Due to SM induced changes, a shift in the onset of CO oxidation activity as well as broadening of the oxidation catalysis regime by 30 to 65 K to lower temperatures is observed compared to the temperature required for virgin counterparts. SM carried out at 523 K for Pd-Photo-TiO2 exhibits the lowest onset (10% CO2 production - T-10) and T-100 for CO oxidation at 360 and 392 K, respectively, while its virgin counterpart shows T-10 and T-100 at 393 and 433 K, respectively. The SMd Pd-TiO2 catalysts were investigated using X-ray photoelectron spectroscopy (XPS), ultra-violet photoelectron spectroscopy (UPS) and atomic force microscopy (AFM). It is observed that diffusion of atomic oxygen into Pd-subsurfaces leads to SM and changes the nature of the surface significantly. These changes are demonstrated by work function (& phi;), surface potential, catalytic activity, and correlation among them. UPS results demonstrate the maximum increase in & phi; by 0.5 eV for Pd-Photo-TiO2 after SM, compared to all other catalysts. XPS study shows a moderate to severe change in the oxidation states of Pd due to atomic oxygen diffusion into the subsurface layers of Pd. Kelvin probe force microscopy (KPFM) study also reveals corroborating evidence that the surface potential increases linearly with increasing temperature deployed for SM up to 523 K, followed by a marginal decrease at 573 K. The & phi; measured by KPFM and UPS shows a similar trend and correlates well with the changes in catalysis observed. Our results indicate that there is a strong correlation between surface physical and chemical properties, and & phi; changes could be considered as a global marker for chemical reactivity.

Post-refolding stability considerations for optimization of in-vitro refolding: L-asparaginase as a case study - Mihooliya, Kanti Nandan; Nitika, Nitika; Bhambure, Rahul; Rathore, Anurag S. S. (Biotechnology Journal, 2023)
BackgroundL-Asparaginase is an essential enzyme for the food and biopharmaceutical industry. The stability, however, of L-asparaginase is widely known to be an issue. Commercial manufacturing of any biopharmaceutical involves hold-ups during processing, and can result in product loss if stability is an issue, as is the case with L-asparaginase. This interplay of product intermediate stability and process design is the focus of this investigation. Methods and ResultsIn this study, we propose a strategy to simultaneously increase the refolding yield and stability of refolded L-asparaginase so as to improve overall process yield. Using one variable at a time (OVAT) experiments, urea (6 M), solubilized inclusion bodies (15 mg/ml), refolding method (step dilution), and pH (8.6) were identified as significant process parameters. A design of experiment (DOE)-based optimization was then performed for the refolding step. The net outcome was more than a three-fold increase in enzyme recovery (i.e., 4.90 IU/ml) compared to unoptimized conditions (i.e., 1.26 IU/ml). Further, the L-asparaginase process intermediate was found to be stable for more than a week at room temperature and 2-8 degrees C, while the unoptimized sample was stable at 2-8 degrees C but did not show any activity at room temperature after 72 h. ConclusionsThe current study elucidates how process intermediate stability needs to be given due consideration during process optimization, particularly for products such as L-asparaginase which are labile.
Keywords: design of experiment; L-asparaginase; refolding; stability

Potential of Y. lipolytica epoxide hydrolase for efficient production of enantiopure (R)-1,2-octanediol - Godase, Vijaya P. P.; Kumar, V. Ravi; Kumar, Ameeta Ravi (AMB Express, 2023)
The recombinant Yleh from a tropical marine yeast Yarrowia lipolytica NCIM 3589 exhibited a high epoxide hydrolase activity of 9.34 +/- 1.80 mu mol min(-1) mg(-1) protein towards 1,2-epoxyoctane (EO), at pH 8.0 and 30 degrees C. The reaction product was identified as 1,2-Octanediol (OD) by GC-MS using EO and H2O18 as substrate, affirming the functionality of Yleh as an epoxide hydrolase. For EO, the K-m, V-max, and k(cat)/K-m values were 0.43 +/- 0.017 mM, 0.042 +/- 0.003 mM min(-1), and 467.17 +/- 39.43 mM(-1) min(-1), respectively. To optimize the reaction conditions for conversion of racemic EO by Yleh catalyst to enantiopure (R)-1,2-octanediol, initially, Response Surface Methodology was employed. Under optimized reaction conditions of 15 mM EO, 150 mu g purified Yleh at 30 degrees C a maximal diol production of 7.11 mM was attained in a short span of 65 min with a yield of 47.4%. Green technology using deep eutectic solvents for the hydrophobic substrate (EO) were tested as co-solvents in Yleh catalyzed EO hydrolysis. Choline chloride-Glycerol, produced 9.08 mM OD with an increased OD yield of 60.5%. Thus, results showed that deep eutectic solvents could be a promising solvent for Yleh-catalyzed reactions making Yleh a potential biocatalyst for the biosynthesis of enantiopure synthons. [GRAPHICS] .
Keywords: Deep Eutectic solvents; Optimization; Recombinant epoxide hydrolase; Response surface methodology; Yarrowia lipolytica

Potential role of lewis acid-base adducts in enhancing stereoselectivity in ziegler-natta catalysts: a DFT study - Raj, K. Vipin; Gupta, Virendra Kumar; Vanka, Kumar (Journal of Physical Chemistry C, 2023)
Ziegler-Natta (Z-N) systems have been well established as heterogeneous catalysts that produce isotactic polypropylene and polyethylene with great efficiency. Such systems benefit considerably from donors (Lewis bases), whose addition significantly improves the stereoselectivity of polymerization. There is a consensus that the primary role of the external donors is to coordinate at the vacant site created by the extraction of internal donors and thus maintain the stereoselectivity. However, the bite difference between internal donors such as phthalates or succinate derivatives and external donors such as alkoxysilanes raises the question of how external donors can effectively replace internal donors. In order to investigate this, we have chosen four external alkoxysilane donors: (1) diisopropyl dimethoxysilane, (2) dicyclopentyl dimethoxysilane, (3) disec-butyl dimethoxysilane, and (4) sec-butyl(methyl) dimethoxysilane. DFT studies reveal that the bite difference problem can be overcome by the favorable formation of adducts between the alkoxysilane external donors and AlEt2Cl in the Z-N systems. These adducts tend to coordinate in the vicinity of the active site. Furthermore, our findings demonstrate the potential of these Lewis acid-base adducts to enhance the stereoselectivity of Z-N catalysts significantly.

PPO-ZIF MMMs possessing metal-polymer interactions for propane/ propylene separation - Kunjattu, H. Shebeeb; Kharul, Ulhas K. (Journal of Membrane Science, 2023)
An assertive formation of ZIF-based mixed matrix membranes (MMMs) with polyphenylene oxide (PPO), a high permeability polymer as a host, is presented. The interfacial interactions between the filler particles and polymer matrix are established by DSC and XPS analyses. The ZIF loading could be achieved up to 40% without hampering the stability of the resulting MMMs. These membranes were evaluated for pure gas permeability, specifically aiming at C3H6/C3H8 separation, a highly desired application in industry. The ZIF-PPO hybrids display promising pure gas as well as mixed gas permeation performance. The 40% ZIF-8 and ZIF-67 loaded membrane display promising C3H6/C3H8 selectivity of 27.5 and 25, with a permeability of 12 and 13 barrer, respectively. The enhanced selectivity is attributed to the absence of defects eliminated due to metal-polymer interactions. The permeation study of a 30% ZIF-8 loaded membrane while varying transmembrane pressure and long-time exposure (150 h) of propylene at 60 psi indicated the excellent stability of the membrane. The sorption analysis further confirmed the molecular sieving characteristics of the ZIF@PPO MMMs. The mixed gas permeation performance showed promising results of high permeability as well as maintaining selectivity over a wide range of compositions.
Keywords: Interfacial interactions; Mixed matrix membrane; Olefin-paraffin separation; poly(phenyleneoxide); Zeolitic imidazole framework

Progressions in cathodic catalysts for oxygen reduction and hydrogen evolution in bioelectrochemical systems: Molybdenum as the next-generation catalyst - Mishra, Puranjan; Sudarsanam, Putla; Mahapatra, Durga Madhab; Elmekawy, Ahamad; Pant, Deepak; Singh, Lakhveer (Catalysis Reviews- Science and Engineering, 2023)
Oxygen reduction reactions (ORRs) are unanimously a key factor of system performances in bioelectrochemical systems (BESs), low-temperature fuel cells, and generally in several electrochemical platforms. Platinum (Pt)-based catalyst is the finest electrocatalyst for ORR in BESs; however, it is constrained by its low abundance, high price, and poor catalytic durability in an electrochemical setup for cathodic reaction kinetics. In recent years, significant efforts in trimming the metal-based catalyst up to nanoscale to cater high performance of ORR have been explored. Still, there are many opportunities to improve catalyst performance at cathode through proper selection of an efficient low-cost metal-based ORR catalyst. Molybdenum (Mo) with its multi-dimensional form as 2D and 3D layers and synergistic combination with other non-metals offers prospects of extraordinary performance as low-cost metal-based ORR catalyst over the Pt in delivering enhanced ORR potential. The present review throws light on current requirements of a sturdier catalyst material and thus provides a comprehensive review on the continuing efforts in exploring the possibility of Mo as a low-cost metal-based ORR catalyst. This literature analysis would enlighten the significance of ORR in BESs, followed by the electrochemistry of Mo-based cathodic catalyst, its underlying mechanism and performance limiting factors in the operation of ORR. Moreover, the extensive and systematic acumen in the context of Mo-based catalytic formulations for increased ORR potentials including nano-composite Mo-cathode catalyst; development of Mo-catalyst with varied configurations; carbon-supported Mo-catalyst; morphological changes; surface area modifications; and Mo-coupling with other transition metal and its derivatives were discussed in great detail to provide prospective application of Mo-based catalyst. Lastly, numerous opportunities and projections for future research in fabrication, juxtaposition, and implementation of Mo-based cathodic catalysts and consequent recommendations were discussed as conclusive remarks for bringing out the state-of-the-art review on this subject.
Keywords: Bioelectrochemical system; catalytic formulations; H-2-evolution reaction; Mo-based cathodic catalyst; multifunctional catalysts; oxygen reduction reaction

Promoting effect of titanium on C-O hydrogenolysis of erythritol to 1,4-butanediol over Pt/W/Ti-SBA-15 catalysts - Bhowmik, Susmita; Akula, Venugopal; Sethia, Govind; Marimuthu, Banu; Darbha, Srinivas (Applied Catalysis A-General, 2023)
The C-O hydrogenolysis of erythritol was investigated using Pt/W/Ti-SBA-15 catalysts (4 wt% Pt, 1 wt% W and Si/Ti molar ratio = 50, 33, 20 and 10). Ti-incorporation enhanced the hydrogenolysis activity and the yield of 1,4-butanediol (1,4-BDO). A catalyst with Si/Ti = 20 afforded erythritol conversion of 94 mol% with 1,4-BDO yield of 32.6 mol% and total BDOs yield of 51.7 mol% at 190 degrees C, 50 bar H2 and 12 h. For the catalyst with no titanium (Pt/W/SBA-15), a double the time was required to achieve such yield. There observed electronic connectivity amongst Ti, Pt and W. For the catalyst with Si/Ti = 20, a greater amount of interfacial Pt-O-W(Ti) sites with Pt in + 2 oxidation state was present. The enhanced catalytic performance of these catalysts was corresponded to dispersed Pt (that facilitate hydrogen activation and spillover) and acidic interfacial Pt-O-W sites (that promote the adsorption and hydrogenolysis of erythritol to diols).
Keywords: Biomass conversion; Erythritol; Hydrogenolysis; Polyols; Promotional effect of Ti; Terminal diol; Ti-SBA-15-supported Pt/W catalysts

Pt-anchored-zirconium phosphate nanoplates as high-durable carbon-free oxygen reduction reaction electrocatalyst for PEM fuel cell applications - Kumar, Sachin; Yoyakki, Athira; Pandikassala, Ajmal; Soni, Roby; Kurungot, Sreekumar (Advanced Sustainable Systems, 2023)
Commercially available platinum-supported carbon (Pt/C) catalysts are the most widely used oxygen reduction reaction (ORR) electrocatalysts in polymer electrolyte membrane fuel cells (PEMFCs). However, inadequate active triple-phase boundary formation and carbon oxidation in Pt/C during PEMFC operation shorten its lifetime and efficiency. In this direction, a new class of carbon-free electrocatalysts for ORR is prepared by dispersing Pt nanoparticles on ZrP (Zirconium phosphates) nanoplates. In one case (ZrP@Pt), the Pt nanoparticles are found to be closely distributed and completely covering the ZrP nanoplates, whereas in the second case (Pt/ZrP), the Pt nanoparticles selectively restrict dispersion along the edges of the support. ZrP as the support displays an intrinsic proton conductivity of approximate to 0.5 x 10(-4) S cm(-1) at 70 degrees C, with an activation energy (E-a) of 0.19 eV. Pt/ZrP shows better durability after 3000 start-stop cycles. The mass activity of Pt/ZrP is increased by 4.6 times compared to Pt/C, which exhibits a loss in mass activity by 1.37 times. The single-cell level validation of ZrP@Pt, Pt/ZrP, and Pt/C as the electrocatalysts in PEMFC at an operating potential of 0.60 V shows the achievable current densities of 0.600, 0.890, and 0.890 A cm(-2).
Keywords: carbon-free electrocatalysts; fuel cells; oxygen reduction reaction; zirconium phosphate

PANI-grafted boron, nitrogen co-doped carbon fiber: An outstanding, high-performance supercapacitor electrode - Nayan, Rajiv; Sinha, Shubhra; Dixit, Vaibhav; Satnami, Manmohan L.; Ghosh, Kallol K.; Pervez, Shamsh; Deb, Manas Kanti; Shrivas, Kamlesh; Rai, Manish K.; Yenchalwar, Sandeep G.; Wasnik, Kundan; Jadkar, Sandesh R.; et al. (JOURNAL OF ENERGY STORAGE, 2024)
Keywords: Composite; polyaniline; Solid-state supercapacitor

Pathological mutations D169G and P112H electrostatically aggravate the amyloidogenicity of the functional domain of TDP-43 - Pillai, Meenakshi; Patil, Anjali D.; Das, Atanu; Jha, Santosh Kumar (ACS Chemical Neuroscience, 2024)
Aggregation of TDP-43 is linked to the pathogenesis of many neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS). Notably, electrostatic point mutations such as D169G and P112H, located within the highly conserved functional tandem RNA recognition motif (RRM) domains of the TDP-43 protein (TDP-43tRRM), have been identified in diseased patients as well. In this study, we address how the electrostatic mutations alter both the native state stability and aggregation propensity of TDP-43tRRM. The mutants D169G and P112H show increased chemical stability compared to the TDP-43tRRM at physiological pH. However, at low pH, both the mutants undergo a conformational change to form amyloid-like fibrils, though with variable rates-the P112H mutant being substantially faster than the other two sequences (TDP-43tRRM and D169G mutant) showing comparable rates. Moreover, among the three sequences, only the P112H mutant undergoes a strong ionic strength-dependent aggregability trend. These observations signify the substantial contribution of the excess charge of the P112H mutant to its unique aggregation process. Complementary simulated observables with atomistic resolution assign the experimentally observed sequence-, pH-, and ionic strength-dependent aggregability pattern to the degree of thermal lability of the mutation site-containing RRM1 domain and its extent of dynamical anticorrelation with the RRM2 domain whose combination eventually dictate the extent of generation of aggregation-prone partially unfolded conformational ensembles. Our choice of a specific charge-modulated pathogenic mutation-based experiment-simulation-combination approach unravels the otherwise hidden residue-wise contribution to the individual steps of this extremely complicated multistep aggregation process.
Keywords: amyloid fibrils; conformational changes; disease mutations; electrostatics; Protein aggregation; stability

Performance of Li exchange hierarchical X zeolite for CO2 adsorption and H2 separation - Shrotri, Aadesh R.; Birje, Amit R.; Niphadkar, Prashant S.; V. Bokade, Vijay; Mali, Nilesh A.; Nandanwar, Sachin U. (Journal of Industrial and Engineering Chemistry, 2024)
Li exchange hierarchical X zeolite (Li-H-X) was prepared by decationization of X zeolite by NH4Cl solution followed by Li exchange and subsequent calcination. NH4-X and Li-X were prepared to compare the results of LiH-X. XRD, FE-SEM, EDS, N2 adsorption-desorption, and micro-/mesoporous volume were performed. The higher mesoporosity was confirmed in Li-H-X due to the framework dealumination during decationization. Static and dynamic sorption capacity of sorbents was evaluated to identify the performance of sorbent. The CO2 and H2 equilibrium adsorption capacity of Li-H-X was found to be 9.6 mmol g-1 and 0.78 mmol g-1, respectively, at 298 K and 20 bar, which was 25 % (CO2) and 30 % (H2) higher than Li-X. Static experimental data were validated using the Langmuir, Freundlich, and Sips models. The CO2 & H2 dynamic sorption capacity of Li-H-X sorbent for binary gas (CO2/H2, 25/75 %) was 4.145 mmol g-1 and 0.258 mmol g-1 at 303 K and 10 bar. The higher sorption capacity of Li-H-X was obtained due to large micro-/mesoporous volume of sorbent, which may allow to access unoccupied sites at higher pressure. This result reveals that micro-/mesoporous structure of zeolite adsorbs significantly higher CO2 from binary gas stream, which can use to separate pure H2 from gas stream.
Keywords: Adsorption; Carbon dioxide; Hydrogen; Microporous-mesoporous; Separation

Perturbation of fermi resonance on hydrogen-bonded > C=O: 2D IR studies of small ester probes - Sakpal, Sushil; Chakrabarty, Suranjana; Reddy, Kambham Devendra; Deshmukh, Samadhan H.; Biswas, Rajib; Bagchi, Sayan; Ghosh, Anup (Journal of Physical Chemistry B, 2024)
We utilized linear and 2D infrared spectroscopy to analyze the carbonyl stretching modes of small esters in different solvents. Particularly noteworthy were the distinct carbonyl spectral line shapes in aqueous solutions, prompting our investigation of the underlying factors responsible for these differences. Through our experimental and theoretical calculations, we identified the presence of the hydrogen-bond-induced Fermi resonance as the primary contributor to the varied line shapes of small esters in aqueous solutions. Furthermore, our findings revealed that the skeletal deformation mode plays a crucial role in the Fermi resonance for all small esters. Specifically, the first overtone band of the skeletal deformation mode intensifies when hydrogen bonds form with the carbonyl group of esters, whereas such coupling is rare in aprotic organic solvents. These spectral insights carry significant implications for the utilization of esters as infrared probes in both biological and chemical systems.

Photo and pH dual stimuli-responsive block copolymer micelles with defined incorporation of o-nitrobenzyl units in poly(ε-caprolactone) ε-caprolactone) block for controlled release - Avhad, V. Shankarrao; Choudhari, Shakeb N.; Ambade, V. Ashootosh (European Polymer Journal, 2024)
A series of dual stimuli-responsive block copolymers with varying content of photocleavable o-nitrobenzyl (ONB) ester group pendent in the hydrophobic poly(epsilon-caprolactone) block and pH-cleavable acetal linkage at the junction with hydrophilic poly(ethylene glycol) block is synthesized. The hydrophobic block is a random copolymer synthesized by ring-opening copolymerization of epsilon-caprolactone and ONB-substituted epsilon-caprolactone containing varying compositions of the two monomers. Kinetics of polymerization shows that ONBfunctionalized monomer has lower reactivity than that of the unsubstituted monomer. The series of block copolymers shows self-assembly into well-defined spherical micelles of average size of 150-200 nm in aqueous solution. Photocleavage of ONB groups is studied by NMR and UV-vis spectroscopy, and its extent is determined. The two stimuli viz. . UV light and pH are used individually as well as simultaneously to study the controlled release of the encapsulated drug Camptothecin and the synergistic effect of the two stimuli is demonstrated. The effect of varying content of ONB groups is observed on drug release profile. MTT assay showed non-cytotoxic nature of the polymer. Cell uptake and photoinduced release of doxorubicin (DOX) from the micelles in MDAMB-231 cells is demonstrated.
Keywords: drug delivery; micelles; O-nitrobenzyl; pH-responsive; Photoresponsive; Poly(epsilon-caprolactone)

photoarchitectonic hydrogel for synergistic in vitro chemo–phototherapy of breast cancer - Paul, Shatabdi; Yadav, Binduma; Patil, Mahesh D.; Pujari, Anil Kumar; Singh, Umesh; Rishi, Vikas; Bhaumik, Jayeeta (Materials Advances, 2024)
Currently, combinatorial therapy has evoked interest in cancer treatment, and may promote achieving a synergistic effect using cancer medicines. Laser-assisted and pH-responsive therapies have attracted significant attention, and their combination leads to high efficiency cancer treatment. Herein, we developed a chemo–phototherapeutic hydrogel comprised of doxorubicin (DOX, a chemotherapeutic drug) and zinc phthalocyanine (ZnPc, a phototherapeutic drug) for combinatorial and synergistic treatment of breast cancer. Firstly, we have developed carbon dots (CDs, size of ∼5 nm) utilizing lignin and folic acid as biocompatible sources. Then doxorubicin was loaded on the surface of the carbon dots via conjugation (DOX@CDs). Later on, zinc phthalocyanine and acrylic acid derivatives were utilized to develop a laser-responsive hydrogel (ZnPc-PP H). Afterward, doxorubicin-conjugated carbon dots were incorporated into the photoarchitectonic hydrogel to develop a chemo–phototherapeutic drug-loaded hydrogel (DOX@CDs–ZnPc-PP H). Subsequently, the in vitro pH-triggering experiments demonstrated that the hydrogel loaded with both DOX and ZnPc could release the drugs in an acidic environment. Interestingly, in vitro assays confirmed that DOX@CDs–ZnPc-PP H could effectively target breast cancer cells (MCF-7). Furthermore, the developed chemo–phototherapeutic hydrogel exhibited non-cytotoxic behavior. Owing to laser assisted reactive oxygen species generation from ZnPc present in the hydrogel, the growth of MCF-7 cells was significantly lowered. In conclusion, all experimental outcomes indicate that the photoarchitectonic hydrogel has the potential to be applied in synergistic chemo- and photodynamic therapy of cancer.

Photocatalytic CO2 reduction to syngas using nickel phosphide-loaded CdS under visible light irradiation - Yadav, Poonam; Kumar, Santosh; Velankanni, Nandhakumar; Kuehne, Thomas D.; Gosavi, Suresh; Raghupathy, Ramya Kormath Madam; Bhosale, Reshma; Held, Georg; Shelke, Manjusha; Ogale, Satishchandra (Journal of Physics-Energy, 2024)
Photocatalytic CO2 reduction is a sustainable pathway to produce syngas (H-2 + CO), which is a key feedstock for the production of several important liquid fuels on the industrial scale. However, achieving an appropriate tunable ratio of H-2:CO in syngas for commercial purposes is a challenging task. In this work, we present a low-cost and non-noble metal, phosphide-based co-catalyst-Ni2P-loaded cadmium sulfide (CdS) photocatalyst system, for photocatalytic CO2 reduction. As a co-catalyst, Ni2P fosters an efficient charge separation of photoexcited charges generated in the CdS production of syngas. In total, 3 wt.% Ni2P/CdS exhibited exceptional performance of 50.6 mu mol g(-1) h(-1) in the CO evolution rate and 115 mu mol g(-1) h(-1) in the H-2 evolution rate, with a syngas composition varying from 2 to 4 in the H-2:CO ratio. Furthermore, first-principles density functional theory calculations were performed to study the surface energetics of the catalyst system and the results are found to be consistent with our experimental findings. Indeed, they establish that the composite favors CO2 photoreduction into syngas more efficiently than pure surfaces.
Keywords: CdS; CO2 reduction; Photocatalysis; Syngas; transition metal phosphides

Photocatalytic regeneration of reactive cofactors with inP quantum dots for the continuous chemical synthesis - Chakraborty, Indra Narayan; Jain, Vanshika; Roy, Pradyut; Kumar, Pawan; Vinod, Chathakudath P.; Pillai, Pramod P. (ACS Catalysis, 2024)
The shuttling of redox-active nicotinamide cofactors between the light and dark cycles is the key to the continuous production of biomass in photosynthesis. The replication of such processes in artificial photosynthetic systems demands fast photoregeneration as well as simultaneous integration of these nicotinamide cofactors into the dark cycle. Here, we report the design of an artificial photosynthetic system for the continuous production of butanol via the constant photoregeneration and consumption of nicotinamide cofactors, powered by an indium phosphide quantum dot (InP QD) photocatalyst and alcohol dehydrogenase (ADH) enzyme, respectively. A strong electrostatic attraction between the oppositely charged InP QDs and electron mediators significantly enhanced the charge extraction and utilization processes, enabling a fast (similar to 30 min, with a turn over frequency of similar to 1333 h(-1)), quantitative (>99%), and selective photoregeneration of enzymatically active nicotinamide cofactors in the light cycle. These photoregenerated nicotinamide cofactors were further coupled in the dark cycle to trigger the ADH oxidoreductase enzyme for the production of butanol, via sequential as well as simultaneous light-dark cycles. The amount of butanol produced under simultaneous light-dark cycles was higher than the stoichiometric limit, proving the constant regeneration and consumption of nicotinamide cofactors in light and dark cycles, respectively. Thus, a proper design and integration of the InP QD-based photocatalytic cycle with the enzymatic cycle led to the effective electron shuttling between light and dark cycles, as seen in photosynthesis.
Keywords: artificial photosynthesis; biologicalcofactors; charge transfer; indiumphosphide; Photocatalysis; quantum dots

Phytic acid customized hydrogel polymer electrolyte and prussian blue analogue cathode material for rechargeable zinc metal hydrogel batteries - Dilwale, Swati; Puthiyaveetil, Priyanka Pandinhare; Babu, Athira; Kurungot, Sreekumar (Small, 2024)
Zinc anode deterioration in aqueous electrolytes, and Zn dendrite growth is a major concern in the operation of aqueous rechargeable Zn metal batteries (AZMBs). To tackle this, the replacement of aqueous electrolytes with a zinc hydrogel polymer electrolyte (ZHPE) is presented in this study. This method involves structural modifications of the ZHPE by phytic acid through an ultraviolet (UV) light-induced photopolymerization process. The high membrane flexibility, high ionic conductivity (0.085 S cm-1), improved zinc corrosion overpotential, and enhanced electrochemical stability value of approximate to 2.3 V versus Zn|Zn2+ show the great potential of ZHPE as an ideal gel electrolyte for rechargeable zinc metal hydrogel batteries (ZMHBs). This is the first time that the dominating effect of chelation of phytic acid with M2+ center over H-bonding with water is described to tune the gel electrolyte properties for battery applications. The ZHPE shows ultra-high stability over 360 h with a capacity of 0.50 mAh cm-2 with dendrite-free plating/stripping in Zn||Zn symmetric cell. The fabrication of the ZMHB with a high-voltage zinc hexacyanoferrate (ZHF) cathode shows a high-average voltage of approximate to 1.6 V and a comparable capacity output of 63 mAh g-1 at 0.10 A g-1 of the current rate validating the potential application of ZHPE. A novel phytic acid (PA) modulated zinc hydrogel polymer electrolyte (ZHPE) as an efficient electrolyte and separator for rechargeable Zn-metal hydrogel batteries (ZMHB) is designed. The zincophilic, and hydrogen bonding characteristics of ZHPE help in regulating uniform dendrite-free Zn-deposition over the Zn anode surface. ZHPE in combination with the developed high-voltage zinc hexacyanoferrate (ZHF) cathode performs as an efficient ZMHB. image
Keywords: high voltage cathode; high-conducting gel polymer electrolyte; phytic acid; rechargeable Zn-metal hydrogel batteries; Zn hydrogel polymer electrolyte

Polymer nanocomposites with UiO-derived zirconia fillers for energy generation and pressure-sensing devices: the role of crystal structure and surface characteristics - Mukherjee, Gargi; Verma, Ankur; Madhu, Arjun Hari; Prasad, Bhagavatula L. V.; Karumuthil, Subash Cherumannil (ACS Applied Nano Materials, 2024)
Piezoelectric energy harvesting and pressure sensing using polymer nanocomposites have opened up promising avenues in the field of flexible electronics. Herein, the influence of varying crystal structures of zirconia nanoparticles on a piezoelectric energy-generating zirconia-poly(vinylidene difluoride) (PVDF) composite is investigated, and the fabrication of a security alert pavement unit using the material with an optimized composition is demonstrated. More specifically, two metal-organic frameworks, UiO-66 and UiO-67, were employed to synthesize four different types of zirconia nanoparticles with precise control of the monoclinic and tetragonal phases. Polymer nanocomposite with monoclinic zirconia nanoparticles derived from UiO-66 (ZrO2-66m) performed better than other derivatives with 61% enhancement in the beta phase with respect to pure PVDF. It was hypothesized that the stable crystalline structure of the monoclinic phase might act as a better nucleating agent, and among monoclinic derivatives, ZrO2-66m was found to be more hydrophobic, probably enabling a better interaction with PVDF. Subsequently, a prototype device with a PVDF-ZrO2-66m (P/66m) film was made and tested for its energy generation. The maximum output voltage generated by the device under an irregular biomechanical hand tapping force of 8-9 N was 80 V, while the maximum open circuit current was found to be 65 mu A. The prototype displayed a power of 2162.24 mu W at a load resistance of 1 M Omega. A laboratory scale demonstration was executed with the prototype as an energy-generating and security alert pavement unit. A wireless, Bluetooth-based security alert system supported by an Android application was developed and demonstrated as a promising application with the fabricated prototype. The results and demonstrations validate that the PVDF-monoclinic ZrO2 nanoparticle nanocomposites will be an excellent value addition for flexible, durable energy generation and pressure-sensing applications.
Keywords: energy generation and pressure sensing; piezoelectric materials; PVDF/ZrO2 polymernanocomposite; self-powered devices; wearable electronics

Polymeric PEI/PEG coated optical fiber fabry-perot interferometer for CO2 detection - Pawar, Dnyandeo; Lo Presti, Daniela; Lemma, Enrico D.; Rainer, Alberto; Kumar, Ajay; Kanawade, Rajesh; Silvestri, Sergio; Schena, Emiliano; Massaroni, Carlo (IEEE Sensors Journal, 2024)
Monitoring carbon dioxide (CO2) gas is essential for numerous applications, but the detection of CO2 in miniaturized devices presents significant challenges. In this study, a polyethyleneimine/poly(ethylene glycol) (PEI/PEG) coated optical fiber Fabry-Perot interferometer (FPI) and its charge transfer process toward CO2 are investigated. Scanning electron microscopy and Fourier transform infrared spectroscopy were used to analyze the surface morphology and vibration bands of the PEI/PEG composite. The PEI/PEG composite Fabry-Perot (FP) cavity of length similar to 13 mu m is coated at the distal end of the single-mode fiber using a dip coating technique. A highly sensitive optical and low-cost FPI probe fabrication has displayed a linear sensitivity of 17.10 nm/% in the range of 0.31%-1.25% CO2 gas. The response and recovery times of the sensor are in a few tens of seconds. The enhanced performance of the sensor is primarily due to the protonation and charge transfer between CO2 gas molecules and PEI/PEG composite. Due to low-cost fabrication and high sensitivity, this FPI sensor can be used in a range of potential applications in bioprocessing, healthcare, and environmental monitoring.
Keywords: dip coating; Fresnel's reflection; Interference; monitoring; Optical fiber sensors; Optical fibers; polymer composite; Polymers; refractive index; sensitivity; Sensor phenomena and characterization; sensors; swelling; Temperature sensors

Polymerized stimuli-responsive microgel hybrids of silver nanoparticles as efficient reusable catalyst for reduction reaction - Pany, Biswajit; Majumdar, Amrito Ghosh; Bhat, Suresh; Si, Satybrata; Yamanaka, Junpei; Mohanty, Priti S. (Heliyon, 2024)
We have showcased the potential of polymerized hydrogels (PGMs) with uniform -sized stimuliresponsive microgel particles as promising alternatives to prevent aggregation in solution based nanoparticle systems. In the current work, we implemented the PGM concept by embedding anionic stimuli -responsive microgels (PNIPAM-co-AAc)-silver (Ag) hybrids within a hydrogel matrix. These PGM@AgNP hybrid materials are used as catalysts for the reduction of 4-nitrophenol (4 -NP) to 4-aminophenol (4 -AP) in the presence of sodium borohydride. UV-VIS spectroscopy is used for studying catalytic activity. In the solution based system, the complete reduction of 4NP to 4 -AP took 30 minutes with pure Ag nanoparticles, 24 minutes with PNIPAM-Ag hybrid (Neutral) microgels and 15 minutes with PNIPAM-co-AAc-Ag (Anionic) hybrid microgels. In contrast PGM containing PNIPAM-co-AAc-Ag hybrids achieved full reduction in just 15 minutes, along with a 3 -minute induction period. For pure Ag nanoparticles, the first -order rate constant is found to be 0.25 min - 1, for PNIPAM-Ag hybrid (Neutral), it is 0.21 min- 1 and for PNIPAM-coAAc-Ag (Anionic), it is 0.5 min- 1 where as for PGM containing anionic microgel hybrids it is found to be 0.8 min - 1. Furthermore, the reusability of the PGM-Ag (anionic) materials for catalytic activity remains unaltered even after several washings. In summary, our study highlights the effectiveness of PGM@AgNP materials as efficient catalysts for the reduction of 4-nitrophenol to 4-aminophenol, indicating their versatile potential in various catalytic applications.
Keywords: Light scattering; Microgel-metal hybrids; Nanomaterial catalysts; PNIPAM microgels; Polymerized hydrogel matrix(PGM; Stimuli-responsive microgels

Poly(N-vinylpyrrolidone)-assisted crystal growth of zeolitic imidazolate framework (ZIF-67) and electrochemical properties of its derivatives for flexible supercapacitors - Jain, Manisha; Joshi, Bhavana; Poddar, Pankaj (Crystal Growth and Design, 2024)
A simple and explicit wet chemical method enables the room-temperature crystallization of the zeolitic imidazolate framework (ZIF-67) using cotton-cloth (CC) as a substrate; where time-dependent Avrami's kinetic studies demonstrated sluggish nucleation and fast crystal growth resulting in unprecedented morphologies-truncated cubes [synthesized without poly(N-vinylpyrrolidone); PVP], and rhombic dodecahedra (with PVP) with average sizes ranging from 500 nm to 1.41 mu m; wherein amphiphilic PVP plays a crucial function of structure directing agent by modulation of complex formation and deprotonation equilibria. To study the potential of pristine ZIF-67 (ZP0) and PVP-functionalized ZIF-67 (ZP50, ZP100, and ZP200) grown on the CC substrate for application as a flexible electrode in supercapacitors, ZP0, ZP50, ZP100, and ZP200 were annealed to form CZP0, CZP50, and CZP100, respectively. Areal capacitances of 181 and 214 mFcm(-2) were achieved at a current density of 1 mAcm(-2) and a potential window of 1.6 V for CZP0 and CZP100, respectively, and compared to the derivatives without PVP; CZP100 exhibited a superior energy density of 76.3 mu Whcm(-2) and a capacitance retention of 84.3% after 5000 cycles at a current density of 0.5 mAcm(-2).

Poly(d,l-lactide-co-glycolide) surface-anchored biotin-loaded irinotecan nanoparticles for active targeting of colon cancer - Giram, Prabhanjan S.; Nimma, Ramakrishna; Bulbule, Anuradha; Yadav, Amit Singh; Gorain, Mahadeo; Radharani, Nalukurthi Naga Venkata; Kundu, Gopal C.; Garnaik, Baijayantimala (ACS Omega, 2024)
A poly-(d,l-lactide-co-glycolide) (PLGA) copolymer was synthesized using the ring-opening polymerization of d,l-lactide and glycolide monomers in the presence of zinc proline complex in bulk through the green route and was well characterized using attenuated total reflectance-Fourier transform infrared, H-1 and C-13 nuclear magnetic resonance, gel permeation chromatography, differential scanning calorimetry, X-ray diffraction, matrix-assisted laser desorption/ionization time-of-flight, etc. Furthermore, PLGA-conjugated biotin (PLGA-B) was synthesized using the synthesized PLGA and was employed to fabricate nanoparticles for irinotecan (Ir) delivery. These nanoparticles (PLGA-NP-Ir and PLGA-B-NP-Ir) were tested for physicochemical and biological characteristics. PLGA-B-NP-Ir exhibited a stronger cellular uptake and anticancer activity as compared to PLGA-NP-Ir in CT-26 cancer cells (log p < 0.05). The accumulation and retention of fluorescence-labeled nanoparticles were observed to be better in CT-26-inoculated solid tumors in Balb/c mice. The PLGA-B-NP-Ir-treated group inhibited tumor growth significantly more (log p < 0.001) than the untreated control, PLGA-NP-Ir, and Ir-treated groups. Furthermore, no body weight loss, hematological, and blood biochemical tests demonstrated the nanocarriers' nontoxic nature. This work presents the use of safe PLGA and the demonstration of a proof-of-concept of biotin surface attached PLGA nanoparticle-mediated active targeted Ir administration to combat colon cancer. To treat colon cancer, PLGA-B-NP-Ir performed better due to specific active tumor targeting and greater cellular uptake due to biotin.

Polyvalent interaction and confinement to suppress polysulfide dissolution and improve electrocatalysis - Bharathkumar, H. J.; Shivankar, Bhavana R.; Krishnamurty, Sailaja; Chen, Dehong; Caruso, Rachel A.; Krishnamoorthy, Kothandam (CATALYSIS SCIENCE & TECHNOLOGY, 2024)
Keywords: cathode material; HIGH-CAPACITY; Particles; SULFUR CATHODE

Positive role of polyunsaturated fatty acids on sustainable crop production against salt stress: an overview - Srivastava, Smita; Yadav, Sagar (Biologia, 2024)
Abiotic stresses have become more severe and capricious due to global warming and varying climatic conditions, with increased temperature reducing the yield of important agricultural crops due to high evapotranspiration, resulting in the increased amount of soil salinization in arid and semi-arid areas, which has become a significant threat that restricts agricultural practices and leads to the overexploitation of cultivation land. One of the crucial environmental elements limiting plant development and yield is salinity. The special effects of salt stress on the superiority of numerous crops have yet to be discovered. Under salinity, plants tend to activate multiple physiological and biochemical mechanisms to overcome the stress by altering their morphology, photosynthesis, water relations, and biochemical adaptations, such as the antioxidative metabolism response and trigger polyunsaturated fatty acids (PUFAs), which act as a biomarker for salinity stress. With the help of PUFAs, which have become popular as all-purpose defenders, decorative techniques have been created to prevent the consequences of saline. The most prevalent PUFAs in plants are those with 18 carbons, specifically 18:1 (oleic), 18:2 (linoleic), and 18:3 (alpha-linolenic) acids which operate as glycerolipids, a source of energy and carbon in triacylglycerol, precursors of numerous bioactive chemicals, stores of extracellular barrier components, and intrinsic antioxidants, modulating cellular membranes and enhancing crop quality and yield. However, limited information about PUFAs and their roles in enhancing crop stress tolerance is available. Therefore, producers and breeders must understand salinity's influence on crop composition to enhance fatty acids under salinity conditions. However, brief work has been reported; this review will help comprehend the role of fatty acids in salinity for food security through the genetic engineering of synthetic genes encoding fatty acids to improve crop stress tolerance and grain quality.
Keywords: Cuticle wax; Membrane lipids; photosynthesis; Polyunsaturated fatty acid; ROS; salt stress; Sensing mechanism; stress tolerance

Potential utility of bacterial protein nanoreactor for sustainable in-situ biocatalysis in wide range of bioprocess conditions - Shinde, Yashodhara D.; Chowdhury, Chiranjit (Enzyme and microbial technology, 2024)
Bacterial microcompartments (MCPs) are proteinaceous organelles that natively encapsulates the enzymes, substrates, and cofactors within a protein shell. They optimize the reaction rates by enriching the substrate in the vicinity of enzymes to increase the yields of the product and mitigate the outward diffusion of the toxic or volatile intermediates. The shell protein subunits of MCP shell are selectively permeable and have specialized pores for the selective inward diffusion of substrates and products release. Given their attributes, MCPs have been recently explored as potential candidates as subcellular nano-bioreactor for the enhanced production of indus-trially important molecules by exercising pathway encapsulation. In the current study, MCPs have been shown to sustain enzyme activity for extended periods, emphasizing their durability against a range of physical challenges such as temperature, pH and organic solvents. The significance of an intact shell in conferring maximum pro-tection is highlighted by analyzing the differences in enzyme activities inside the intact and broken shell. Moreover, a minimal synthetic shell was designed with recruitment of a heterologous enzyme cargo to demonstrate the improved durability of the enzyme. The encapsulated enzyme was shown to be more stable than its free counterpart under the aforementioned conditions. Bacterial MCP-mediated encapsulation can serve as a potential strategy to shield the enzymes used under extreme conditions by maintaining the internal microen-vironment and enhancing their cycle life, thereby opening new means for stabilizing, and reutilizing the enzymes in several bioprocess industries.
Keywords: Bioprocess industries; Encapsulation; Enzyme recycling; Enzyme Stability; Microcompartment; Nanobioreactor

Power generation with negative CO2 emissions through bio-electricity with CCS using dry co-gasification of coal-biomass blends - Vasireddy, Satyam Naidu; Jayanti, Sreenivas (Clean Technologies and Environmental Policy, 2024)
Among the measures proposed for decarbonization of electricity generation, large reductions in CO2 emissions are possible by the adoption of bio-electricity with carbon dioxide capture and sequestration. In the present study, thermodynamic analysis of a thermal power plant that produces electricity through co-gasification of high-ash coal and Casuarina equisetifola (CE), a crop which grows along the Indian coastline, and which is not in competition with other agricultural crops for land and water use, is considered for integrated gasification combined cycle (IGCC) with CO2 capture via oxyfuel combustion and gasification technology. The integrated power plant layout includes the energy required for CO2 gasification of coal, biomass blended fuel, air separation to produce oxygen for oxyfuel combustion as well as for purification and compression of the flue gas up to 30 bar. Simulation results show that a net efficiency of 37% can be achieved using high-ash Indian coal and CE blends up to 30% of the latter. Synergetic effect of co-gasification components is observed in mass, molar and thermal energy flowrates for biomass blended fuel. With the help of CCS, CO2 emissions are reduced to 69.91 gCO(2)/kWh for 100% coal-based IGCC-CC plant and further to -21.69 gCO(2)/kWh (negative CO2 emissions) for 30% biomass blending, thus paving way for CO2-negative power generation.
Keywords: BECCS; Combustion; Dry co-gasification; IGCC-CC plant; Negative CO2 emissions; Oxyfuel; Thermodynamic analysis

Preparation and structural characterization of disordered Na-gallosilicate zeolite with natrolite framework and itsK+ and NH4+ exchanged analogues exchanged analogues - Gavhane, Manjusha J.; Jha, R. K.; Nam, Kyung-Wan; Bhange, Deu S. (JOURNAL OF POROUS MATERIALS, 2024)

Pressure swing adsorption of Li exchange hierarchical X zeolite for pure hydrogen from binary gas mixture - Shrotri, Aadesh R.; Birje, Amit R.; Nandanwar, Sachin U. (International Journal of Hydrogen Energy, 2024)
This study reports the separation of pure hydrogen (H2) employing pressure swing adsorption (PSA). The Li-X and Li-hierarchical X (Li-H-X) zeolite were prepared by an ion exchange process. The sorbents were evaluated through several experiments including, breakthrough, empty bed contact time (EBCT), single-bed, and two-bed PSA with different steps. The effect of pressure, purity, and recovery relationship was developed. The highpressure PSA study was performed at 4, 6, and 10 bar with varying feed flow rates to assess their efficacy in pure H2 separation using binary gas stream (H2/CO2, 75/25 vol.%). The breakthrough adsorption capacity of Li-H-X exhibited 3.4 mmol g-1 and 0.212 mmol g-1 of CO2 and H2, respectively. Li-H-X shows -8% higher CO2 sorption capacity than the Li-X sorbent at 1 bar and 300 K due to the large meso-microporous structure of the sorbent. The two-bed PSA purity and recovery were found higher than single-bed PSA. Using two-bed PSA, the Li-H-X achieved a 99.5% of purity, 92.9% of recovery, and 10.4 mL min-1 g-1 of productivity, which was -16% higher recovery and productivity than single-bed PSA at a flow rate of 1200 mL min-1 at 6 bar. With increasing the pressure and flow rate, the recovery of Li-H-X was enhanced up to 93.7% with 99.1%-99.9% H2 purity. The long-term PSA was run using Li-H-X sorbent for 7.5 h with 230 cycles with H2 purity between 98.5 and 99.5% at 6 bar. Interestingly, the adsorbent shows the scalability of PSA for efficient H2 separation for a binary mixture of H2/CO2.
Keywords: adsorbent; Binary gas mixture; Hydrogen purification; Li-H-X; Mesoporous zeolite; Pressure swing adsorption

Probing surface interactions in CdSe quantum dots with thiocyanate ligands - Deshmukh, Samadhan H.; Yadav, Sushma; Chowdhury, Tubai; Pathania, Akhil; Sapra, Sameer; Bagchi, Sayan (NANOSCALE, 2024)
Keywords: COLLOIDAL NANOCRYSTALS; STRUCTURAL DYNAMICS; Thin-films

Probing the energy landscape of the lipid interactions of the serotonin 1A receptor - Mohole, Madhura; Naglekar, Amit; Sengupta, Durba; Chattopadhyay, Amitabha (Biophysical Chemistry, 2024)
G protein-coupled receptors (GPCRs) are lipid-regulated transmembrane proteins that play a central role in cell signaling and pharmacology. Although the role of membrane lipids in GPCR function is well established, the underlying GPCR-lipid interactions have not been thermodynamically characterized due to the complexity of these interactions. In this work, we estimate the energetics and dynamics of lipid association from coarse-grain simulations of the serotonin1A receptor embedded in a complex membrane. We show that lipids bind to the receptor with varying energetics of 1-4 kT, and timescales of 1-10 mu s. The most favorable energetics and longest residence times are observed for cholesterol, glycosphingolipid GM1, phosphatidylethanolamine (PE) and phosphatidylserine (PS) lipids. Multi-exponential fitting of the contact probability suggests distinct dynamic regimes, corresponding to ps, ns and mu s timescales, that we correlate with the annular, intermediate and nonannular lipid sites. The timescales of lipid binding correspond to high barrier heights, despite their relatively weaker energetics. Our results highlight that GPCR-lipid interactions are driven by both thermodynamic interactions and the dynamical features of lipid binding.
Keywords: GPCR-lipid interactions; Lipid energetics; Lipid residence time; Molecular dynamics simulations; Serotonin 1 a receptor

Proteome dataset of Candida albicans (ATCC10231) opaque cell - Zore, Gajanan; Abdulghani, Mazen; Kodgire, Santosh; Kazi, Rubina; Shelar, Amruta; Patil, Rajendra (BMC Research Notes, 2024)
<h3 class="c-article__sub-heading" data-test="abstract-sub-heading" style="margin: 0px 0px 8px; box-sizing: inherit; font-size: 1.5rem; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, Oxygen-Sans, Ubuntu, Cantarell, "Helvetica Neue", sans-serif; line-height: 1.24; font-weight: 400;"> Objectives Candida albicans, a polymorphic yeast, is one of the most common, opportunistic fungal pathogens of humans. Among the different morphological forms, opaque form is one of the least-studied ones. This opaque phenotype is essential for mating and is also reported to be involved in colonizing the gastrointestinal tract. Considering the significance of the clinical and sexual reproduction of C. albicans, we have investigated the morphophysiological modulations in opaque form using a proteomic approach. <h3 class="c-article__sub-heading" data-test="abstract-sub-heading" style="margin: 24px 0px 8px; box-sizing: inherit; font-size: 1.5rem; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, Oxygen-Sans, Ubuntu, Cantarell, "Helvetica Neue", sans-serif; line-height: 1.24; font-weight: 400;"> Data description In the current investigation, we have used Micro-Liquid Chromatography-Mass Spectrometry (LC-MS/MS) analysis to create a protein profile for opaque-specific proteins. Whole-cell proteins from C. albicans (ATCC10231) cells that had been cultured for seven days on synthetic complete dextrose (SCD) medium in both as an opaque (test) and as a white (control) form cells were extracted, digested, and identified using LC-MS/MS. This information is meant to serve the scientific community and represents the proteome profile (SWATH Spectral Libraries) of C. albicans opaque form.

Purification of waste-generated biogas mixtures using covalent organic framework's high CO2 Selectivity - Paul, Ratul; Maibam, Ashakiran; Chatterjee, Rupak; Wang, Wenjing; Mukherjee, Triya; Das, Nitumani; Yellappa, Masapogu; Banerjee, Tanmay; Bhaumik, Asim; Venkata Mohan, S.; BabaRao, Ravichandar; Mondal, John (ACS APPLIED MATERIALS & INTERFACES, 2024)
Keywords: CAPTURE; CARBON-DIOXIDE; Efficiency; Energy; Hydrogen; STORAGE

Pyridazine-Based Aggregation Induced Emission Active Conjugates: Synthesis, Single Crystal XRD Analysis, and Self-Assembly Assessment - Waghchoure, Aishwarya P.; Sangale, Vijay B.; Shaligram, Parth S.; Lambud, Sushil; Pardeshi, Satish K.; Gonnade, Rajesh G.; Bandaru, Sateesh; More, Sandeep; Reddy, J. Prakasha; Bhosale, Rajesh S. (CHEMISTRYSELECT, 2024)
Keywords: AIE; Pyridazine; Self-assembly; Single crystal

Pair of dinuclear Fe(II) enantiomers: syntheses and structures of ΛΔ/ΔΛ-Bis(Dihydridoborate) complexes - Kaur, Urminder; Gayen, Sourav; Sharma, Himanshu; Vanka, Kumar; Ghosh, Sundargopal (CHEMISTRY-A EUROPEAN JOURNAL, 2025)
In our effort to establish a direct synthetic approach for bis(dihydridoborate) complexes of first-row transition metals, we have investigated the reactivity of [Cp*Fe(dppe)Cl] (dppe =1,2-bis(diphenylphosphino)ethane) with Na[BH3L] (L =2-mercaptopyridine (mp) and 2-mercaptobenzothiazole (mbz)) that led to the formation of iron(II) dihydridoborate complexes, [Cp*Fe{kappa 3-S,H,H-(H2BH(L))}] 1 a-b (L=mp (1 a) and L=mbz (1 b)). Further, in an attempt to isolate the bis(dihydridoborate) complex of iron by the insertion of borane into the kappa 2-N,S-chelated iron complex, [(dppe)Fe{kappa 2-N,S-(mp)}2] (2), we have isolated and structurally characterized a rare example of dimeric iron bis(dihydridoborate) complex, [Fe{kappa 3-S,H,H-(H2BH(mp))}2]2, Lambda Delta/Delta Lambda-3 as pair of enantiomers. Interestingly, these enantiomers Lambda Delta/Delta Lambda-3 have two trans-[Fe{kappa 3-S,H,H-(H2BH(mp))}2] moieties bridged through sulfur atoms of 2-mercaptopyridinyl ligands, where the iron centres are hepta-coordinated. The natural bond-orbital (NBO) analyses of Lambda Delta-3 and Delta Lambda-3 show considerable electron donation from the filled sigma B-H bonding orbital to vacant dz2 \${{d}_{{z}<\^>{2}}}\$ orbital of iron with a substantial contribution from the hydrogen atoms. The localized orbital bonding analysis (LOBA) method suggests that all the iron centres are in +2 oxidation state.
Keywords: B-H activation; Bis(dihydridoborate); Enantiomer; Heptacoordinate; iron

Palladium-catalyzed regioselective C(4)-H fluoroalkoxylation of indoles through weak chelation assistance - Vijaykumar, Muniyappa; Gonnade, Rajesh G.; Punji, Benudhar (ChemCatChem, 2025)
Installing fluoroalkyl motifs into biorelevant indoles is particularly interesting due to their ubiquitous presence in drug molecules. Herein, we demonstrate the regioselective C4 fluoroalkoxylation of indoles using fluoroalcohols via palladium-catalyzed chelation-assisted C & horbar;H activation. The weak chelating benzoyl moiety at the C3 position acts as a directing group for remote C(4)& horbar;H fluoroalkoxylation of diversely substituted indoles. This methodology demonstrates a high level of regioselectivity and tolerates a range of crucial functional groups, yielding diverse trifluoroalkoxylated indoles in moderate to good yields. Removal of directing/protecting groups and further functionalization established the synthetic utility of the methodology. A preliminary mechanistic investigation is conducted by isolating the palladacycle intermediate and performing the deuterium scrambling study. The regioselective C4 fluoroalkoxylation of indoles with various fluoroalcohols is achieved by the palladium-catalyzed weak chelation assistance strategy. The reaction is compatible for a range of important functionalities and proceeds via the intermediacy of a six-membered palladacycle following a Pd(II)/Pd(IV) pathway. image
Keywords: C-H activation; indoles; Palladium; Regioselective; Trifluoroalkoxylation

Peganutonin A: computationally informed synthesis of its revised structure - Saranya, N. Sathya Sai; Choudhury, Rahul; Supekar, Prathmesh R.; Beduru, Srinivas; Williams, Craig M.; Elyashberg, Mikhail E.; Kutateladze, Andrei G.; Bates, Roderick W.; Reddy, D. Srinivasa (Journal of Natural Products, 2025)
The structure of the recently isolated natural product peganutonin A was shown to be incorrect by analysis of the reported spectroscopic data, and therefore, the structure was reassigned utilizing computational methods. Subsequently, the computationally proposed reassignment was confirmed by total synthesis, which was achieved in seven steps from 6-methoxyindole. It is assumed that peganutonin A is not a natural product but an artifact arising from photooxidation of the alkaloid harmaline.

Peptide functionalization with dithioate and trithioate groups: A CS2-mediated solid-phase approach - Shinde, Dinesh R.; Bodake, Supriya Mahadev; Marelli, Udaya Kiran (Organic Letters, 2025)
The dithiocarbamate group is an important class of compounds whose presence in small molecules and peptides leads to antimicrobial, anticancer, and enzyme inhibition properties. This study introduces an efficient and selective method for incorporating dithioate and trithioate moieties into amino acids and peptides using CS2 chemistry under mild conditions. Utilizing a N,N-diisopropylethylamine (DIPEA)-CS2-benzyl chloride system, we achieved modifications at the N-terminal amines and the side chains of Lys and Cys residues through solid-phase peptide synthesis (spps). The method exhibits excellent yields and broad compatibility with diverse amino acids, their protection groups, peptide chemistry reagents, and varied peptide sequences. Notably, the successful incorporation of trithioate groups into peptides via cysteines, reported here for the first time, expands the functional repertoire of peptide chemistry, offering new possibilities for peptide-based drug design and related applications.

Peptide-triazolobenzodiazepine hybrids: a catalyst-free on-resin strategy to build complex therapeutic motifs into peptides - Kamble, Sandip Sushila Mohan; Bodake, Supriya Mahadev; Marelli, Udaya Kiran (Chemistry-A European Journal, 2025)
The merger of peptide and heterocyclic chemistry presents significant opportunities for enhancing the structural and functional diversity of therapeutic agents. In this study, we introduce a streamlined on-resin method to modify peptides at the N-terminus amines and the side chain amines of Lys/Orn amino acids by incorporating the biologically active triazolobenzodiazepine scaffold. In the presented solid-phase peptide synthesis (SPPS), the triazolobenzodiazepine core is formed on-resin through a combination of N-alkylation, amide bond formation, and an alkyne-azide 1,3-dipolar cycloaddition, of which the latter two happen as a single-step one-pot reaction- proceeding under mild conditions without metal catalysts. This protocol tolerates a wide variety of amino acids and functional groups, providing a versatile method for synthesizing peptide-triazolobenzodiazepine hybrids. Using orthogonal protection group strategies, we further demonstrate the method's adaptability for two site modifications in peptides involving both the N-terminus and Lys side chain amines. These modifications enhance the scope of ``peptide medicinal chemistry'' by creating multifunctional peptides with potential therapeutic applications. The method's compatibility with SPPS, room temperature conditions, and elimination of metal catalysis make it an efficient and powerful tool for peptide modification.
Keywords: hybrid peptides; peptide chemistry; peptide modification; spps compatibility; triazolobenzodiazepines

Phosphite mediated molecular editing via switch to meta-C-H alkylation of isoquinolines: emergence of a distinct photochemical [1,3] N to C rearrangement - Rani, Soniya; Ray, Anuj Kumar; Dewangan, Devendra Kumar; Patil, Nita Aruna Ramchandra; Aarthika, M.; Paul, Ankan; Maity, Pradip (Chemical Science, 2025)
The isoquinoline core is present in one of the largest subsets of bioactive natural products. The multifunctional isoquinoline core exerts diverse bioactivity, resulting in the development of numerous isoquinoline-based drugs and molecules that are currently under clinical trials. We developed a new approach for phosphite-mediated [1,2] alkyl migration for an overall ortho-C-H alkylation via N-alkylation of isoquinoline. Tuning the phosphite-mediated protocol to switch the site selectivity would expedite direct and diverse multi-C-H bond functionalization. We report a new approach starting with a simple N-alkylation of isoquinoline with sterically and electronically diverse alkyl bromides for their phosphite-mediated photochemical [1,3] N to C rearrangement followed by a rearomatization sequence that leads to meta-C-H (C4) alkylation. Combined experimental and computational studies unveiled the emergence of an unprecedented C-N bond cleavage pathway from the singlet excited state of the enamine-type intermediate. Our radical bond-cleavage pathway favors substituted alkyl group migration that complements the recently successful meta-alkylation methods with smaller and more reactive electrophiles. This switch in site selectivity via tuning the phosphite-mediated protocol resulted in sequential C-H difunctionalization of isoquinoline including regiodivergent ortho, meta-dialkylations of isoquinolines.

Photocatalytic hydrogen evolution by MoO3@g-C3N4 and MoO3@f-MWCNT nanocomposites in deionized and natural seawater under visible light - Kangutkar, Raju S.; Walko, Priyanka; Dhepe, P. L.; Nayaka, G. P.; Manjanna, J. (ACS Applied Nano Materials, 2025)
Visible-light-driven photocatalysts are predominantly useful for converting solar to hydrogen energy via photocatalytic water-splitting reactions. The heterojunction composite materials have exhibited remarkable advantages for visible-light photocatalytic H-2 evolution. We have successfully synthesized MoO3@f-MWCNT and MoO3@g-C3N4 nanocomposites and characterized them using PXRD, UV-DRS, Raman spectroscopy, XPS, PL, TRPL, FE-SEM, HR-TEM, BET, and photocurrent. The photocatalytic water-splitting efficiency of MoO3@f-MWCNT and MoO3@g-C3N4 was measured under visible light (lambda >= 420 nm) irradiation using TEOA as a sacrificial reagent in DI water and natural seawater. The H-2 evolution rate in DI water for MoO3@f-MWCNT is 2313.56 mu mol g(-)(1) h(-)(1), and for MoO3@g-C3N4 is 2530.35 mu mol g(-1) h(-1) with an apparent quantum efficiency (AQE) of 6.38 and 6.93%, respectively. In natural seawater, the H-2 evolution rate is 2632.20 and 2845.06 mu mol g(-1) h(-1), with an AQE of 7.21 and 7.77%, respectively. The rate of H-2 evolution slightly increased in natural seawater than DI water. The Tafel slope values for MoO3@g-C3N4 and MoO3@f-MWCNT are 59 and 92 mV dec(-1), respectively. The lowest Tafel value of MoO3@g-C3N4 exhibited a faster rate of reaction. Thus, the surface interaction between the MoO3 and the porous g-C3N4 materials may create synergistic effects, which facilitate electron transport at the interface and significantly boost the photocatalytic activity. Thus, MoO3@g-C3N4 is a promising photocatalyst for renewable energy production.
Keywords: deionized water; electrochemicalHER; MoO3@f-MWCNT; MoO3@g-C3N4 nanocomposites; natural seawater; photocatalytic H-2 evolution

Photocatalytic oxidation of α-substituted amines to lactams/amides - Kumar, Manish; Kumar, Pawan; Das, Utpal (Advanced Synthesis & Catalysis, 2025)
We, herein, report a base free, photocatalytic decyanation of alpha-aminonitriles. A range of amides and lactams were obtained in 52-95% yields. Control experiments indicate O2 as an amide/lactam oxygen source and the reaction (lactam formation) follows radical pathway via dioxetanimine species. This methodology also applied for alpha-ester/aldehyde substituted pyrrolidines in the presence of a base, probably via decarboxylation pathway.
Keywords: alpha-Aminonitriles; Decyanation; Dioxetanimine; Photocatalytic; pyrrolidine

Photo-induced cracking in a Bi-component molecular solid: capturing structural intermediates - Ahsan, Mollah Rohan; Mishra, Manish Kumar; Mukherjee, Arijit (Chemistry-An Asian Journal, 2025)
A photo-responsive bi-component solid is designed based on robust large synthons. The study not only provides a template-based approach for a system that was difficult to photo-dimerize, but the designed solid also leads to photo-induced cracking upon photodimerization. The delicate structural design helps in capturing the structural intermediates, which reveals a possible reorientation of the photodimer within the crystal to maintain structural integrity.
Keywords: bi-component solid; crystal engineering; photoinduced cracking; single-crystal-to-single crystal transformation; [2+2] photodimerization

Phytochemical investigation of Cannabis sativa: Isolation and structure determination of spiroindans - Nalli, Yedukondalu; Komal; Boccia, Eleonora; Lauro, Gianluigi; Bifulco, Giuseppe; Krishna, Gamidi Rama (Journal of Molecular Structure, 2025)
Four undescribed, beta-, alpha-chevicospiranol (1, 2), 4-prenylspirenone B (3), and, 6-prenylspirenone B (4), along with ten known spiroindans were discovered in Cannabis sativa. The structures were determined through 1D, 2D NMR, HRMS, and quantum mechanical calculations. Compounds 1 and 2 have an unprecedented fused system of 3hydroxychavicol with beta- and alpha-cannabispiranol core, respectively, while 3 and 4 are prenylated spiroindan congeners. Detailed NMR data assignments of isomeric pairs 2a - 2b, 3a - 3b, and 4a - 4b, corrected the misidentification of the previously reported spiroindane, prenylspirodinone (5). Besides, the crystal structures of 2a, 3a, and 5a were determined by SC-XRD experiments.
Keywords: Cannabaceae; Cannabis sativa L.; Crystal structure analysis of spiro-indans; Indian cannabis variety; NMR data of spiro-indans; Spiro-indans

Portal substituent modulations in chiral imido-Pd(II) cages for the enhanced separation of styrene oxide enantiomers - Jose, Cavya; Sarkar, Abhradeep; Khopade, Kishor V.; Boomishankar, Ramamoorthy (Inorganic Chemistry, 2025)
Sensing and separation of enantiomers are crucial for the synthesis of biologically relevant compounds as well as for applications in catalysis and pharmaceutical development. Chiral coordination cages have gained significant attention as effective platforms for enantioselective processes through their well-defined, tunable cavities that facilitate host-guest interactions. In this study, we systematically explored the enantioselective binding and separation properties of two tetrahedral Pd(II) cages, 1-R and 2-R, with the molecular formula [Pd3(PO[N(RCH(CH3)Ph)3])4(C6O4X2)6] (X = Cl for 1-R, and X = F for 2-R). Their enantioselective abilities were investigated for small chiral molecules with diverse functional groups. Notably, the 2-R cage demonstrated a high enantioselectivity value of 88 for R-styrene oxide. Chiral separation experiments further revealed impressive enantiomeric excess (ee) values of 98% for R-styrene oxide from their racemic mixtures upon desorption from 2-R. The enhanced selectivity and separation efficiency were attributed to an optimal guest-to-cavity fit and the presence of multiple interaction sites within the host framework. Remarkably, portal substituent modulation in 2-R led to a 16-fold enhancement in enantioselective separation efficiency compared to 1-R, primarily due to improved portal dimensions, tighter molecular packing, and increased hydrogen bonding interactions. These findings highlight the potential of neutral chiral coordination cages for various enantioselective applications.

Probing the effect of fluorine on hydrogen bonding interactions in a pharmaceutical hydrate using Advanced Solid-State NMR - Hareendran, Chaithanya; Ajithkumar, T. G. (Molecular Pharmaceutics, 2025)
Structural studies of pharmaceutical hydrates are essential to understanding stability-related issues, especially during the heating process of formulation. A thorough understanding of the hydration and dehydration behavior of active pharmaceutical ingredient (API) hydrate is also important since phase transitions can occur during the formulation process. This is because dehydration could result in a considerable rearrangement in the structure if water-API hydrogen bonding is present. We perform advanced solid-state NMR experiments on regorafenib monohydrate to investigate the role of fluorine in hydrogen bonding interaction, and the results are compared to its anhydrous form and its structural analogue, namely, sorafenib. Our results show that significant structural changes could not be observed on dehydration. Based on our study, it can be concluded that the introduction of fluorine restricts the intramolecular hydrogen bonding and the asymmetry in the structure of regorafenib monohydrate is absent, in comparison to sorafenib.
Keywords: DQSQ; Hydrogenbonding; pharmaceutical hydrate; regorafenib; Solid-state NMR

Pt-based 3D electrocatalyst with process-friendly features for PEMFCs possessing fast activation and improved mass-transfer properties - Pandikassala, Ajmal; Nadumattuvayil, Varsha; Singh, Mayank U.; Jadhav, Swapnil D.; Yoyakki, Athira; Kurungot, Sreekumar (Advanced Sustainable Systems, 2025)
Polymer-electrolyte-membrane fuel cells (PEMFCs) face the challenges like slow oxygen reduction reaction (ORR) kinetics and limited mass transport at high current densities, which affects their performance. The efficient water removal from the cathode is essential to improve oxygen diffusion. Addressing this, a catalyst is presented with platinum (Pt) nanoparticles distributed within a 3D carbon network (Pt/3DPDC) derived from the polydopamine-coated melamine foam. This unique architecture enhances Pt utilization and water management due to its high porosity and ample free spaces, providing a process-friendly feature for the electrode under PEMFC conditions. The pores and accessible texture of the 3D polydopamine derived carbon (3DPDC) framework facilitate ionomer uptake during the electrode fabrication, extending the active triple-phase boundary and improving the membrane electrode assembly (MEA) performance. The high porosity of Pt/3DPDC is mitigated by adding a small amount of commercial fuel cell catalayst (Pt/C), which maintains the effective catalyst number density per unit area by utilizing the excess porosity of the 3DPDC framework. This controlled interplay of the unique catalyst structure and spatially confined distribution of Pt/C within the Pt/3DPDC framework offers fast activation, reduced electrode flooding, and improved current densities across the operating potential window. This carefully engineered catalyst, designed through bottom-up strategies, is a promising electrocatalyst for practical PEMFC applications.
Keywords: Oxygen Evolution Reaction; oxygen reduction reaction; rechargeable flexible zinc-air battery